Restriction of Intravenous Fluid in ICU Patients with Septic Shock - Meyhoff, Tine S; Hjortrup, Peter B.; Wetterslev, JÃ¸rn; Sivapalan, Praleene; Laake, Jon H.; Cronhjort, Maria; Jakob, Stephan M.; Cecconi, Maurizio; Nalos, Marek; Ostermann, Marlies; Malbrain, Manu; PettilÃ¤, Ville; et al. (The New England journal of medicine, 2022)
BACKGROUND: Intravenous fluids are recommended for the treatment of patients who are in septic shock, but higher fluid volumes have been associated with harm in patients who are in the intensive care unit (ICU). METHODS: In this international, randomized trial, we assigned patients with septic shock in the ICU who had received at least 1 liter of intravenous fluid to receive restricted intravenous fluid or standard intravenous fluid therapy; patients were included if the onset of shock had been within 12 hours before screening. The primary outcome was death from any cause within 90 days after randomization. RESULTS: We enrolled 1554 patients; 770 were assigned to the restrictive-fluid group and 784 to the standard-fluid group. Primary outcome data were available for 1545 patients (99.4%). In the ICU, the restrictive-fluid group received a median of 1798 ml of intravenous fluid (interquartile range, 500 to 4366); the standard-fluid group received a median of 3811 ml (interquartile range, 1861 to 6762). At 90 days, death had occurred in 323 of 764 patients (42.3%) in the restrictive-fluid group, as compared with 329 of 781 patients (42.1%) in the standard-fluid group (adjusted absolute difference, 0.1 percentage points; 95% confidence interval [CI], -4.7 to 4.9; P = 0.96). In the ICU, serious adverse events occurred at least once in 221 of 751 patients (29.4%) in the restrictive-fluid group and in 238 of 772 patients (30.8%) in the standard-fluid group (adjusted absolute difference, -1.7 percentage points; 99% CI, -7.7 to 4.3). At 90 days after randomization, the numbers of days alive without life support and days alive and out of the hospital were similar in the two groups. CONCLUSIONS: Among adult patients with septic shock in the ICU, intravenous fluid restriction did not result in fewer deaths at 90 days than standard intravenous fluid therapy.
ICU感染性休克患者中限制静脉补液 背景：建议静脉注射液用于脓毒性休克患者的治疗，但高液体量与重症监护室(ICU)患者的伤害相关。 方法：在这项国际、随机试验中，我们将ICU中至少接受1L静脉注射液治疗的感染性休克患者分配至接受限制性静脉注射液或标准静脉注射液治疗；如果休克发生在筛选前12小时内，则纳入患者。主要结局是随机分组后90天内全因死亡。 结果：我们入选了1554例患者；770例分配至限制液组，784例分配至标准液组。获得了1545例患者(99.4%)的主要结局数据。在ICU中，限制液体组接受了中位数为1798 mL的静脉注射液（四分位距为500-4366）；标准液体组接受了中位数为3811 mL的静脉注射液（四分位距为1861-6762）。90天时，限制液组764例患者中的323例(42.3%)发生死亡，标准液组781例患者中的329例(42.1%)发生死亡（调整后的绝对差异，0.1个百分点；95%置信区间[CI]，-4.7至4.9；P = 0.96）。在ICU中，限制液组的751例患者中有221例(29.4%)发生了至少一次严重不良事件，标准液组的772例患者中有238例(30.8%)发生了至少一次严重不良事件（调整后的绝对差异，-1.7个百分点；99%CI，-7.7至4.3）。随机分组后90天时，两组中无生命支持的存活天数和存活及出院天数相似。 结论：在ICU的脓毒性休克成人患者中，与标准静脉补液治疗相比，静脉补液限制不会导致90天时更少的死亡。
Keywords: Humans; Intensive Care Units; Adult; Administration, Intravenous; Critical Care/methods; *Fluid Therapy/adverse effects/methods; *Shock, Septic/mortality/therapy

Intravenous Fluids in Septic Shock - More or Less? - McIntyre, Lauralyn A; Marshall, John C. (The New England journal of medicine, 2022)
脓毒性休克中的静脉补液-或多或少？
Keywords: Humans; Administration, Intravenous; *Shock, Septic/therapy; *Fluid Therapy/methods; Rehydration Solutions/administration & dosage

Intravenous Vitamin C in Adults with Sepsis in the Intensive Care Unit - Lamontagne, François; Masse, Marie-Hélène; Menard, Julie; Sprague, Sheila; Pinto, Ruxandra; Heyland, Daren K; Cook, Deborah J.; Battista, Marie-Claude; Day, Andrew G.; Guyatt, Gordon H.; Kanji, Salmaan; Parke, Rachael; et al. (The New England journal of medicine, 2022)
BACKGROUND: Studies that have evaluated the use of intravenous vitamin C in adults with sepsis who were receiving vasopressor therapy in the intensive care unit (ICU) have shown mixed results with respect to the risk of death and organ dysfunction. METHODS: In this randomized, placebo-controlled trial, we assigned adults who had been in the ICU for no longer than 24 hours, who had proven or suspected infection as the main diagnosis, and who were receiving a vasopressor to receive an infusion of either vitamin C (at a dose of 50 mg per kilogram of body weight) or matched placebo administered every 6 hours for up to 96 hours. The primary outcome was a composite of death or persistent organ dysfunction (defined by the use of vasopressors, invasive mechanical ventilation, or new renal-replacement therapy) on day 28. RESULTS: A total of 872 patients underwent randomization (435 to the vitamin C group and 437 to the control group). The primary outcome occurred in 191 of 429 patients (44.5%) in the vitamin C group and in 167 of 434 patients (38.5%) in the control group (risk ratio, 1.21; 95% confidence interval [CI], 1.04 to 1.40; P = 0.01). At 28 days, death had occurred in 152 of 429 patients (35.4%) in the vitamin C group and in 137 of 434 patients (31.6%) in the placebo group (risk ratio, 1.17; 95% CI, 0.98 to 1.40) and persistent organ dysfunction in 39 of 429 patients (9.1%) and 30 of 434 patients (6.9%), respectively (risk ratio, 1.30; 95% CI, 0.83 to 2.05). Findings were similar in the two groups regarding organ-dysfunction scores, biomarkers, 6-month survival, health-related quality of life, stage 3 acute kidney injury, and hypoglycemic episodes. In the vitamin C group, one patient had a severe hypoglycemic episode and another had a serious anaphylaxis event. CONCLUSIONS: In adults with sepsis receiving vasopressor therapy in the ICU, those who received intravenous vitamin C had a higher risk of death or persistent organ dysfunction at 28 days than those who received placebo.
重症监护室中脓毒血症成人静脉注射维生素C 背景：评价在重症监护室(ICU)接受血管加压药治疗的脓毒症成人中静脉给予维生素C的研究显示，在死亡和器官功能障碍风险方面的结果不一致。 方法：在这项随机、安慰剂对照试验中，我们将ICU住院时间不超过24小时的成人患者分配，确诊或疑似感染为主要诊断，以及正在接受血管加压药以接受维生素C输注（剂量为50 mg/kg体重）或匹配的安慰剂，每6小时给药一次，持续96小时。主要结局是第28天死亡或持续性器官功能障碍（定义为使用血管加压药、有创机械通气或新的肾脏替代治疗）的复合终点。 结果：共有872例患者接受随机分组（435例进入维生素C组，437例进入对照组）。维生素C组429例患者中有191例(44.5%)发生主要结局，对照组434例患者中有167例(38.5%)发生主要结局（风险比，1.21；95%置信区间[CI]，1.04至1.40；P = 0.01）。第28天，维生素C组429例患者中的152例(35.4%)和安慰剂组434例患者中的137例(31.6%)死亡（风险比，1.17；95%CI，0.98-1.40），429例患者中的39例(9.1%)和434例患者中的30例(6.9%)分别发生了持续性器官功能障碍（风险比，1.30；95%CI，0.83 to 2.05).两组器官功能障碍评分、生物标志物、6个月生存期、健康相关生活质量、3期急性肾损伤和低血糖发作结果相似。在维生素C组中，1例患者发生重度低血糖发作，另1例发生严重过敏反应事件。 结论：在ICU接受升压治疗的脓毒症成人患者中，接受静脉注射维生素C的患者28天时死亡或持续器官功能障碍的风险高于接受安慰剂的患者。
Keywords: Humans; Intensive Care Units; Adult; Quality of Life; Multiple Organ Failure; Vasoconstrictor Agents/adverse effects; *Sepsis/drug therapy; Hypoglycemic Agents/therapeutic use; *Ascorbic Acid/adverse effects; Vitamins/adverse effects

Nasal High-Flow Therapy during Neonatal Endotracheal Intubation - Hodgson, Kate A.; Owen, Louise S.; Kamlin, C. Omar F.; Roberts, Calum T.; Newman, Sophie E.; Francis, Kate L.; Donath, Susan M.; Davis, Peter G.; Manley, Brett J. (The New England journal of medicine, 2022)
BACKGROUND: Neonatal endotracheal intubation often involves more than one attempt, and oxygen desaturation is common. It is unclear whether nasal high-flow therapy, which extends the time to desaturation during elective intubation in children and adults receiving general anesthesia, can improve the likelihood of successful neonatal intubation on the first attempt. METHODS: We performed a randomized, controlled trial to compare nasal high-flow therapy with standard care (no nasal high-flow therapy or supplemental oxygen) in neonates undergoing oral endotracheal intubation at two Australian tertiary neonatal intensive care units. Randomization of intubations to the high-flow group or the standard-care group was stratified according to trial center, the use of premedication for intubation (yes or no), and postmenstrual age of the infant (â‰¤28 or >28 weeks). The primary outcome was successful intubation on the first attempt without physiological instability (defined as an absolute decrease in the peripheral oxygen saturation of >20% from the preintubation baseline level or bradycardia with a heart rate of <100 beats per minute) in the infant. RESULTS: The primary intention-to-treat analysis included the outcomes of 251 intubations in 202 infants; 124 intubations were assigned to the high-flow group and 127 to the standard-care group. The infants had a median postmenstrual age of 27.9 weeks and a median weight of 920 g at the time of intubation. A successful intubation on the first attempt without physiological instability was achieved in 62 of 124 intubations (50.0%) in the high-flow group and in 40 of 127 intubations (31.5%) in the standard-care group (adjusted risk difference, 17.6 percentage points; 95% confidence interval [CI], 6.0 to 29.2), for a number needed to treat of 6 (95% CI, 4 to 17) for 1 infant to benefit. Successful intubation on the first attempt regardless of physiological stability was accomplished in 68.5% of the intubations in the high-flow group and in 54.3% of the intubations in the standard-care group (adjusted risk difference, 15.8 percentage points; 95% CI, 4.3 to 27.3). CONCLUSIONS: Among infants undergoing endotracheal intubation at two Australian tertiary neonatal intensive care units, nasal high-flow therapy during the procedure improved the likelihood of successful intubation on the first attempt without physiological instability in the infant.
新生儿气管插管期间的经鼻高流量治疗 背景：新生儿气管插管经常涉及多次尝试，氧饱和度下降很常见。目前尚不清楚在接受全身麻醉的儿童和成人中，在选择性插管期间延长至去饱和时间的经鼻高流量治疗是否能改善新生儿首次尝试成功插管的可能性。 方法：我们进行了一项随机化、对照试验，在两个澳大利亚三级新生儿重症监护室接受口腔气管插管的新生儿中，比较经鼻高流量治疗与标准治疗（无经鼻高流量治疗或辅助供氧）。将插管随机分配至高流量组或标准治疗组，根据试验中心、插管术前用药的使用（是或否）和婴儿经后年龄（â‰ë28或 > 28周）进行分层。主要结局为婴儿在首次尝试时成功插管，无生理不稳定（定义为外周血氧饱和度相对于插管前基线水平绝对下降 > 20%或心动过缓，心率 < 100次/分）。 结果：主要意向治疗分析包括202例婴儿的251次插管的结局；124次插管被分配至高流量组，127次插管被分配至标准治疗组。婴儿的中位月经后年龄为27.9周，插管时的中位体重为920 g。高流量组124次插管中的62次(50.0%)和标准治疗组127次插管中的40次(31.5%)在首次尝试时成功插管而无生理不稳定（调整的风险差异，17.6个百分点；95%置信区间[CI]，6.0至29.2），对于需要治疗的数量6例(95%CI，4-17)，1例婴儿获益。在68.5%的患者中实现了首次尝试时成功插管，无论生理学稳定性如何高流量组的插管率和标准治疗组的插管率分别为54.3%和15.8%（校正的风险差异，15.8个百分点；95%CI，4.3-27.3）。 结论：在两个澳大利亚三级新生儿重症监护室接受气管插管的婴儿中，手术过程中经鼻高流量治疗提高了婴儿首次尝试成功插管的可能性，且无生理不稳定。
Keywords: Humans; Infant, Newborn; Australia; Elective Surgical Procedures; Intensive Care Units, Neonatal; *Intubation, Intratracheal/methods; *Oxygen Inhalation Therapy/methods; Oxygen/analysis

Prone Positioning of Intubated Patients with an Elevated Body-Mass Index - Hao, David; Low, Sarah; Di Fenza, Raffaele; Shenoy, Erica S.; Ananian, Lillian; Prout, Laura A.; La Vita, Carolyn J.; Berra, Lorenzo (2022)
身体质量指数升高的插管患者的俯卧位
Keywords: Humans; Respiration, Artificial; Body Mass Index; Prone Position; *Respiratory Insufficiency/therapy; Intubation, Intratracheal; *Patient Positioning

Lung Transplantation for Covid-19-Related Respiratory Failure in the United States - Roach, Amy; Chikwe, Joanna; Catarino, Pedro; Rampolla, Reinaldo; Noble, Paul W.; Megna, Dominick; Chen, Qiudong; Emerson, Dominic; Egorova, Natalia; Keshavjee, Shaf; Kirklin, James K. (The New England journal of medicine, 2022)
美国肺移植治疗Covid-19相关呼吸衰竭
Keywords: Humans; Female; Male; Middle Aged; Adult; United States/epidemiology; COVID-19/*complications; Lung Transplantation/mortality/*statistics & numerical data; Postoperative Complications/mortality; Respiratory Insufficiency/etiology/*surgery

Extracorporeal Kidney-Replacement Therapy for Acute Kidney Injury - Gaudry, StÃ©phane; Palevsky, Paul M.; Dreyfuss, Didier (The New England journal of medicine, 2022)
体外肾脏替代治疗急性肾损伤
Keywords: Humans; Treatment Outcome; Acute Kidney Injury/*therapy; Renal Replacement Therapy/instrumentation/*methods

Resuscitation Fluid Composition and Acute Kidney Injury in Critical Illness - Ostermann, Marlies; Randolph, Adrienne G. (The New England journal of medicine, 2022)
危重病患者的复苏液体成分与急性肾损伤
Keywords: Humans; Resuscitation; *Critical Illness/therapy; *Acute Kidney Injury/etiology/therapy

Multistate Outbreak of Melioidosis Associated with Imported Aromatherapy Spray - Gee, Jay E.; Bower, William A.; Kunkel, Amber; Petras, Julia; Gettings, Jenna; Bye, Maria; Firestone, Melanie; Elrod, Mindy G.; Liu, Lindy; Blaney, David D.; Zaldivar, Allison; Raybern, Chelsea; et al. (The New England journal of medicine, 2022)
Melioidosis, caused by the bacterium Burkholderia pseudomallei, is an uncommon infection that is typically associated with exposure to soil and water in tropical and subtropical environments. It is rarely diagnosed in the continental United States. Patients with melioidosis in the United States commonly report travel to regions where melioidosis is endemic. We report a cluster of four non-travel-associated cases of melioidosis in Georgia, Kansas, Minnesota, and Texas. These cases were caused by the same strain of B. pseudomallei that was linked to an aromatherapy spray product imported from a melioidosis-endemic area.
进口芳香喷雾剂对类鼻疽多状态爆发的影响 类鼻疽由类鼻疽杆菌(Burkholderia pseudomallei)引起，是一种不常见的感染，通常与热带和亚热带环境中暴露于土壤和水有关。在美国大陆很少诊断。在美国，类鼻疽患者通常报告前往类鼻疽流行的地区旅行。我们报告了格鲁吉亚、堪萨斯州、明尼苏达州和德克萨斯州4例非旅行相关类鼻疽病例。这些病例是由类鼻疽流行区进口的香料喷雾剂产品相关的类鼻疽杆菌菌株引起。
Keywords: Humans; Female; Male; Middle Aged; Child, Preschool; Phylogeny; United States/epidemiology; Fatal Outcome; *Disease Outbreaks; Aerosols; Aromatherapy/*adverse effects; Brain/microbiology/pathology; Burkholderia pseudomallei/genetics/*isolation & purification; COVID-19/complications; Genome, Bacterial; Lung/microbiology/pathology; Melioidosis/complications/*epidemiology; Shock, Septic/microbiology

Isolated Persistent Left Superior Vena Cava - Tang, Pok-Tin; Chan, Kenneth (The New England journal of medicine, 2022)
孤立性持续性左上腔静脉
Keywords: Humans; Male; Aged; Tomography, X-Ray Computed; Catheterization; Ultrasonography; Renal Dialysis; Acute Kidney Injury/complications; Incidental Findings; Persistent Left Superior Vena Cava/*diagnostic imaging; Shock, Septic/complications/microbiology; Vena Cava, Superior/*diagnostic imaging

Balanced Multielectrolyte Solution versus Saline in Critically Ill Adults - Finfer, Simon; Micallef, Sharon; Hammond, Naomi; Navarra, Leanlove; Bellomo, Rinaldo; Billot, Laurent; Delaney, Anthony; Gallagher, Martin; Gattas, David; Li, Qiang; Mackle, Diane; Mysore, Jayanthi; et al. (The New England journal of medicine, 2022)
BACKGROUND: Whether the use of balanced multielectrolyte solution (BMES) in preference to 0.9% sodium chloride solution (saline) in critically ill patients reduces the risk of acute kidney injury or death is uncertain. METHODS: In a double-blind, randomized, controlled trial, we assigned critically ill patients to receive BMES (Plasma-Lyte 148) or saline as fluid therapy in the intensive care unit (ICU) for 90 days. The primary outcome was death from any cause within 90 days after randomization. Secondary outcomes were receipt of new renal-replacement therapy and the maximum increase in the creatinine level during ICU stay. RESULTS: A total of 5037 patients were recruited from 53 ICUs in Australia and New Zealand - 2515 patients were assigned to the BMES group and 2522 to the saline group. Death within 90 days after randomization occurred in 530 of 2433 patients (21.8%) in the BMES group and in 530 of 2413 patients (22.0%) in the saline group, for a difference of -0.15 percentage points (95% confidence interval [CI], -3.60 to 3.30; P = 0.90). New renal-replacement therapy was initiated in 306 of 2403 patients (12.7%) in the BMES group and in 310 of 2394 patients (12.9%) in the saline group, for a difference of -0.20 percentage points (95% CI, -2.96 to 2.56). The mean (±SD) maximum increase in serum creatinine level was 0.41±1.06 mg per deciliter (36.6±94.0 μmol per liter) in the BMES group and 0.41±1.02 mg per deciliter (36.1±90.0 μmol per liter) in the saline group, for a difference of 0.01 mg per deciliter (95% CI, -0.05 to 0.06) (0.5 μmol per liter [95% CI, -4.7 to 5.7]). The number of adverse and serious adverse events did not differ meaningfully between the groups. CONCLUSIONS: We found no evidence that the risk of death or acute kidney injury among critically ill adults in the ICU was lower with the use of BMES than with saline.
危重成人患者中的电解质平衡液与生理盐水比较 背景：在危重患者中优先使用平衡多电解质溶液(BMES)而不是0.9%氯化钠溶液（生理盐水）是否可降低急性肾损伤或死亡的风险尚不确定。 方法：在一项双盲、随机、对照试验中，我们将危重患者分配至重症监护室(ICU)接受BMES(Plasma-Lyte 148)或生理盐水作为液体治疗，持续90天。主要结局是随机分组后90天内全因死亡。次要结局是接受新的肾脏替代治疗和ICU住院期间肌酐水平的最大增幅。 结果：从澳大利亚和新西兰的53个ICU招募总计5037例患者-2515例患者分配至BMES组，2522例患者分配至生理盐水组。BMES组2433例患者中的530例(21.8%)和生理盐水组2413例患者中的530例(22.0%)在随机分组后90天内死亡，差异为-0.15个百分点（95%置信区间[CI]，-3.60至3.30；P = 0.90）。在BMES组的306/2403例患者(12.7%)和盐水组的310/2394例患者(12.9%)中开始了新的肾脏替代治疗，差异为-0.20个百分点（95%CI，-2.96至2.56）。BMES组血清肌酐水平的平均最大增幅为0.42 μm±1.06 mg/dl(36.6 μm±94.0 μm/l)，生理盐水组为0.41 μm±1.02 mg/dl(36.1 μm±90.0 μm/l)，差异为0.01 mg/dl（95%CI，-0.05至0.06）（0.5 μm/l[95%CI，-4.7 to 5.7]).治疗组间不良事件和严重不良事件的数量没有有意义的差异。 结论：我们未发现证据表明，与生理盐水相比，使用BMES时ICU重症成人患者的死亡或急性肾损伤风险较低。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Double-Blind Method; Aged; Intensive Care Units; Adult; Fluid Therapy; Critical Care/methods; Critical Illness/mortality/*therapy; Acute Kidney Injury/etiology/*prevention & control; Gluconates/adverse effects/therapeutic use; Magnesium Chloride/adverse effects/therapeutic use; Potassium Chloride/adverse effects/therapeutic use; Saline Solution/adverse effects/*therapeutic use; Sodium Acetate/adverse effects/therapeutic use; Sodium Chloride/adverse effects/therapeutic use

Futility of Suppressing Seizurelike Activity in Postresuscitation Coma - Wijdicks, Eelco F. M. (The New England journal of medicine, 2022)
抑制复苏后昏迷患者癫痫样活动的无效性
Keywords: Humans; *Medical Futility; *Coma/etiology/therapy

Plastic Bronchitis - Maqsood, Aadil; Imel, Lukken R. (The New England journal of medicine, 2022)
塑料支气管炎
Keywords: Humans; Male; Middle Aged; Lung/diagnostic imaging; Bronchitis/diagnostic imaging/*pathology/therapy; Bronchoscopy; Lymphatic Vessels/diagnostic imaging/*pathology

Treating Rhythmic and Periodic EEG Patterns in Comatose Survivors of Cardiac Arrest - Ruijter, Barry J.; Keijzer, Hanneke M.; Tjepkema-Cloostermans, Marleen C.; Blans, Michiel J.; Beishuizen, Albertus; Tromp, Selma C.; Scholten, Erik; Horn, Janneke; van Rootselaar, Anne-Fleur; Admiraal, Marjolein M.; van den Bergh, Walter M.; Elting, Jan-Willem J.; et al. (The New England journal of medicine, 2022)
BACKGROUND: Whether the treatment of rhythmic and periodic electroencephalographic (EEG) patterns in comatose survivors of cardiac arrest improves outcomes is uncertain. METHODS: We conducted an open-label trial of suppressing rhythmic and periodic EEG patterns detected on continuous EEG monitoring in comatose survivors of cardiac arrest. Patients were randomly assigned in a 1:1 ratio to a stepwise strategy of antiseizure medications to suppress this activity for at least 48 consecutive hours plus standard care (antiseizure-treatment group) or to standard care alone (control group); standard care included targeted temperature management in both groups. The primary outcome was neurologic outcome according to the score on the Cerebral Performance Category (CPC) scale at 3 months, dichotomized as a good outcome (CPC score indicating no, mild, or moderate disability) or a poor outcome (CPC score indicating severe disability, coma, or death). Secondary outcomes were mortality, length of stay in the intensive care unit (ICU), and duration of mechanical ventilation. RESULTS: We enrolled 172 patients, with 88 assigned to the antiseizure-treatment group and 84 to the control group. Rhythmic or periodic EEG activity was detected a median of 35 hours after cardiac arrest; 98 of 157 patients (62%) with available data had myoclonus. Complete suppression of rhythmic and periodic EEG activity for 48 consecutive hours occurred in 49 of 88 patients (56%) in the antiseizure-treatment group and in 2 of 83 patients (2%) in the control group. At 3 months, 79 of 88 patients (90%) in the antiseizure-treatment group and 77 of 84 patients (92%) in the control group had a poor outcome (difference, 2 percentage points; 95% confidence interval, -7 to 11; P = 0.68). Mortality at 3 months was 80% in the antiseizure-treatment group and 82% in the control group. The mean length of stay in the ICU and mean duration of mechanical ventilation were slightly longer in the antiseizure-treatment group than in the control group. CONCLUSIONS: In comatose survivors of cardiac arrest, the incidence of a poor neurologic outcome at 3 months did not differ significantly between a strategy of suppressing rhythmic and periodic EEG activity with the use of antiseizure medication for at least 48 hours plus standard care and standard care alone.
心脏骤停幸存者节律及周期脑电图模式的处理 背景：心脏骤停昏迷幸存者节律性和周期性脑电图(EEG)模式的治疗是否改善结局尚不确定。 方法：我们进行了一项开放标签试验，以抑制心脏骤停昏迷存活者在连续EEG监测中检测到的节律性和周期性EEG模式。以1:1的比例将患者随机分配至一种逐步策略的抗癫痫药物，以抑制这种活性至少连续48小时加标准治疗（抗癫痫治疗组）或仅标准治疗（对照组）；标准治疗包括两组中的目标温度管理。根据3个月时脑功能分类(CPC)量表的评分，主要结局为神经系统结局，分为良好结局（CPC评分表示无、轻度或中度残疾）或不良结局（CPC评分表示重度残疾、昏迷或死亡）。次要结局为死亡率、重症监护室(ICU)住院时间和机械通气持续时间。 结果：我们入选了172例患者，其中88例分配至抗癫痫治疗组，84例分配至对照组。心脏骤停后中位35小时检测到节律性或周期性EEG活动；有可用数据的157例患者中98例患者(62%)有肌阵挛。抗癫痫治疗组88例患者中的49例(56%)和对照组83例患者中的2例(2%)发生了连续48小时的节律性和周期性EEG活动的完全抑制。在3个月时，抗癫痫治疗组88例患者中的79例(90%)和对照组84例患者中的77例(92%)结局较差（差异，2个百分点；95%置信区间，-7-11；P = 0.68）。抗癫痫治疗组的3个月死亡率为80%，对照组为82%。抗癫痫治疗组的平均ICU住院时间和平均机械通气时间比对照组略长。 结论：在心脏骤停昏迷存活者中，采用抑制节律性和周期性EEG活动的策略，联合使用抗癫痫药物至少48小时 + 标准治疗与单独使用标准治疗，3个月时较差神经学结局的发生率无显著差异。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Aged; Glasgow Coma Scale; *Electroencephalography; Anticonvulsants/adverse effects/*therapeutic use; Coma/etiology/*physiopathology; Heart Arrest/*complications/physiopathology; Seizures/diagnosis/*drug therapy/etiology

Lymphatic Plastic Bronchitis - Mehta, Ishan; Patel, Kavita (The New England journal of medicine, 2022)
淋巴塑料性支气管炎
Keywords: Humans; Male; Adult; Lung/diagnostic imaging; Lymphatic Vessels/diagnostic imaging/*pathology; Airway Obstruction/etiology; Bronchitis/diagnostic imaging/*pathology; Bronchoalveolar Lavage; Embolization, Therapeutic; Lymphography; Thoracic Duct/diagnostic imaging/*pathology

Neonatal Resuscitation in 22-Week Pregnancies - Lee, Clement D.; Nelin, Leif; Foglia, Elizabeth E. (The New England journal of medicine, 2022)
22周妊娠期间的新生儿复苏
Keywords: Humans; Infant, Newborn; Gestational Age; *Resuscitation; *Fetal Viability; *Infant, Extremely Premature

Case 39-2021: A 26-Year-Old Woman with Respiratory Failure and Altered Mental Status - Kadar, Aran; Shah, Viral S.; Mendoza, Dexter P.; Lai, Peggy S.; Aghajan, Yasmin; Piazza, Gregory; Camargo, Erica C.; Viswanathan, Kartik (The New England journal of medicine, 2021)
病例39-2021：一例26岁的呼吸衰竭和精神状态改变女性患者。
Keywords: Humans; Female; Adult; Diagnosis, Differential; Tomography, X-Ray Computed; Brain/diagnostic imaging/pathology; Brain Diseases/complications/*diagnosis; Bronchoalveolar Lavage Fluid/cytology; Embolism, Fat/complications/*diagnosis; Lipoabdominoplasty/*adverse effects; Lung/drug effects/pathology; Mental Disorders; Respiratory Insufficiency

Emphysematous Hepatitis - Bofill, Alex; Marco, Francesc (The New England journal of medicine, 2021)
气肿性肝炎
Keywords: Humans; Male; Aged, 80 and over; Tomography, X-Ray Computed; Fatal Outcome; Emphysema/diagnostic imaging/etiology; Hepatitis/*diagnostic imaging/microbiology; Klebsiella Infections/complications/*diagnosis; Klebsiella pneumoniae/*isolation & purification; Liver/*diagnostic imaging/microbiology

Therapeutic Anticoagulation with Heparin in Critically Ill Patients with Covid-19 - Goligher, Ewan C.; Bradbury, Charlotte A.; McVerry, Bryan J.; Lawler, Patrick R.; Berger, Jeffrey S.; Gong, Michelle N.; Carrier, Marc; Reynolds, Harmony R.; Kumar, Anand; Turgeon, Alexis F.; Kornblith, Lucy Z.; Kahn, Susan R.; et al. (The New England journal of medicine, 2021)
BACKGROUND: Thrombosis and inflammation may contribute to morbidity and mortality among patients with coronavirus disease 2019 (Covid-19). We hypothesized that therapeutic-dose anticoagulation would improve outcomes in critically ill patients with Covid-19. METHODS: In an open-label, adaptive, multiplatform, randomized clinical trial, critically ill patients with severe Covid-19 were randomly assigned to a pragmatically defined regimen of either therapeutic-dose anticoagulation with heparin or pharmacologic thromboprophylaxis in accordance with local usual care. The primary outcome was organ support-free days, evaluated on an ordinal scale that combined in-hospital death (assigned a value of -1) and the number of days free of cardiovascular or respiratory organ support up to day 21 among patients who survived to hospital discharge. RESULTS: The trial was stopped when the prespecified criterion for futility was met for therapeutic-dose anticoagulation. Data on the primary outcome were available for 1098 patients (534 assigned to therapeutic-dose anticoagulation and 564 assigned to usual-care thromboprophylaxis). The median value for organ support-free days was 1 (interquartile range, -1 to 16) among the patients assigned to therapeutic-dose anticoagulation and was 4 (interquartile range, -1 to 16) among the patients assigned to usual-care thromboprophylaxis (adjusted proportional odds ratio, 0.83; 95% credible interval, 0.67 to 1.03; posterior probability of futility [defined as an odds ratio <1.2], 99.9%). The percentage of patients who survived to hospital discharge was similar in the two groups (62.7% and 64.5%, respectively; adjusted odds ratio, 0.84; 95% credible interval, 0.64 to 1.11). Major bleeding occurred in 3.8% of the patients assigned to therapeutic-dose anticoagulation and in 2.3% of those assigned to usual-care pharmacologic thromboprophylaxis. CONCLUSIONS: In critically ill patients with Covid-19, an initial strategy of therapeutic-dose anticoagulation with heparin did not result in a greater probability of survival to hospital discharge or a greater number of days free of cardiovascular or respiratory organ support than did usual-care pharmacologic thromboprophylaxis. (REMAP-CAP, ACTIV-4a, and ATTACC ClinicalTrials.gov numbers, NCT02735707, NCT04505774, NCT04359277, and NCT04372589.).
伴有Covid-19的危重患者中的肝素抗凝治疗 背景：血栓形成和炎症可能会导致2019年冠状病毒疾病患者的发病和死亡(Covid-19)。我们假设治疗性剂量抗凝治疗可改善Covid-19重症患者的结局。 方法：在一项开放标签、适应性、多平台、随机化临床试验中，伴有重度Covid-19的重症患者被随机分配至实用定义的方案组：肝素抗凝治疗剂量抗凝或根据当地常规治疗的药物血栓预防。主要结局是无器官支持的天数，采用序级量表评价，结合院内死亡（指定值为-1）和存活至出院的患者中截至第21天无心血管或呼吸器官支持的天数。 结果：当达到预先设定的治疗剂量抗凝治疗无效标准时，试验停止。获得了1098例患者（534例分配至抗凝治疗剂量组，564例分配至血栓预防常规治疗组）的主要结局数据。分配接受治疗剂量抗凝治疗的患者无器官支持天数的中位值为1（四分位距，-1至16），分配接受常规血栓预防治疗的患者为4（四分位距，-1至16）（调整后的比例优势比，0.83；95%置信区间，0.67至1.03；无效的后验概率[定义为比值比 < 1.2]，99.9%）。两组中存活至出院的患者百分比相似（分别为62.7%和64.5%；调整后比值比，0.84；95%置信区间，0.64-1.11）。3.8%的治疗剂量抗凝组患者和2.3%的常规治疗药物血栓预防组患者发生大出血。 结论：在伴有Covid-19的重症患者中，与常规治疗药物血栓预防相比，初始治疗剂量肝素抗凝治疗不会导致出院生存率更高或无心血管或呼吸器官支持的天数更多。（REMAP-CAP、ACTIV-4a和ATTACC临床试验。gov数，NCT02735707、NCT04505774、NCT04359277和NCT04372589）。
Keywords: Humans; Female; Male; Middle Aged; Aged; Critical Illness; Respiration, Artificial; Hospital Mortality; Logistic Models; Odds Ratio; Treatment Failure; Hemorrhage/chemically induced; Anticoagulants/*administration & dosage/adverse effects/therapeutic use; COVID-19/*drug therapy/mortality; Heparin/*administration & dosage/adverse effects/therapeutic use; Thrombosis/*prevention & control

Surviving Covid-19 with Heparin? - Ten Cate, Hugo (The New England journal of medicine, 2021)
是否通过肝素生存Covid-19？
Keywords: Humans; Critical Illness; Dose-Response Relationship, Drug; COVID-19/*drug therapy; Thrombosis/*prevention & control; Anticoagulants/*administration & dosage/therapeutic use; Heparin, Low-Molecular-Weight/*administration & dosage/therapeutic use; Heparin/*administration & dosage/therapeutic use

Milrinone as Compared with Dobutamine in the Treatment of Cardiogenic Shock - Mathew, Rebecca; Di Santo, Pietro; Jung, Richard G.; Marbach, Jeffrey A.; Hutson, Jordan; Simard, Trevor; Ramirez, F. Daniel; Harnett, David T.; Merdad, Anas; Almufleh, Aws; Weng, Willy; Abdel-Razek, Omar; et al. (The New England journal of medicine, 2021)
BACKGROUND: Cardiogenic shock is associated with substantial morbidity and mortality. Although inotropic support is a mainstay of medical therapy for cardiogenic shock, little evidence exists to guide the selection of inotropic agents in clinical practice. METHODS: We randomly assigned patients with cardiogenic shock to receive milrinone or dobutamine in a double-blind fashion. The primary outcome was a composite of in-hospital death from any cause, resuscitated cardiac arrest, receipt of a cardiac transplant or mechanical circulatory support, nonfatal myocardial infarction, transient ischemic attack or stroke diagnosed by a neurologist, or initiation of renal replacement therapy. Secondary outcomes included the individual components of the primary composite outcome. RESULTS: A total of 192 participants (96 in each group) were enrolled. The treatment groups did not differ significantly with respect to the primary outcome; a primary outcome event occurred in 47 participants (49%) in the milrinone group and in 52 participants (54%) in the dobutamine group (relative risk, 0.90; 95% confidence interval [CI], 0.69 to 1.19; P = 0.47). There were also no significant differences between the groups with respect to secondary outcomes, including in-hospital death (37% and 43% of the participants, respectively; relative risk, 0.85; 95% CI, 0.60 to 1.21), resuscitated cardiac arrest (7% and 9%; hazard ratio, 0.78; 95% CI, 0.29 to 2.07), receipt of mechanical circulatory support (12% and 15%; hazard ratio, 0.78; 95% CI, 0.36 to 1.71), or initiation of renal replacement therapy (22% and 17%; hazard ratio, 1.39; 95% CI, 0.73 to 2.67). CONCLUSIONS: In patients with cardiogenic shock, no significant difference between milrinone and dobutamine was found with respect to the primary composite outcome or important secondary outcomes.
米力农与多巴酚丁胺治疗心源性休克的比较 背景：心源性休克与相当大的发病率和死亡率相关。尽管正性肌力支持是心源性休克药物治疗的主要手段，但在临床实践中很少有证据指导正性肌力药物的选择。 方法：我们以双盲的方式将心源性休克患者随机分配接受米力农或多巴酚丁胺治疗。主要结局包括全因住院死亡、心脏骤停复苏、接受心脏移植或机械循环支持、非致死性心肌梗死、短暂性脑缺血发作或神经科医生诊断的卒中或开始肾脏替代治疗。次要结局包括主要复合结局的单个组分。 结果：共入选192名参与者（每组96名）。治疗组之间的主要结局并无显著性差异；米力农组47名参与者(49%)和多巴酚丁胺组52名参与者(54%)发生了主要结局事件（相对风险，0.90；95%置信区间[CI]，0.69-1.19；P = 0.47）。在次要结局方面，组间也没有显著差异，包括住院期间死亡（分别为37%和43%的受试者；相对风险，0.85；95%CI，0.60至1.21）、心脏骤停复苏（7%和9%；风险比，0.78；95%CI，0.29至2.07），接受机械循环支持（12%和15%；风险比，0.78；95%CI，0.36-1.71），或开始肾脏替代治疗（22%和17%；风险比，1.39；95%CI，0.73-2.67）。 结论：心源性休克患者中，米力农与多巴酚丁胺之间的主要复合结局或重要的次要结局并无显著性差异。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Hospital Mortality; Comorbidity; Adrenergic beta-Agonists/therapeutic use; Cardiotonic Agents/adverse effects/*therapeutic use; Dobutamine/adverse effects/*therapeutic use; Milrinone/adverse effects/*therapeutic use; Phosphodiesterase 3 Inhibitors/therapeutic use; Shock, Cardiogenic/*drug therapy/mortality

Case 19-2021: A 54-Year-Old Man with Irritability, Confusion, and Odd Behaviors - Kontos, Nicholas; Parsons, Michael W.; Biffi, Alessandro; GonzÃ¡lez, R. Gilberto (The New England journal of medicine, 2021)
病例19-2021：一名54岁的男性，有易怒、意识模糊和怪异行为
Keywords: Humans; Male; Middle Aged; Diagnosis, Differential; Magnetic Resonance Imaging; Brain/diagnostic imaging/pathology; Confusion/etiology; Drug Overdose/*complications; Irritable Mood; Leukoencephalopathies/*diagnosis/etiology/psychology; Mental Disorders/*etiology

Translating Targeted Temperature Management Trials into Postarrest Care - Morrison, Laurie J.; Thoma, Brent (The New England journal of medicine, 2021)
将目标温度管理试验转化为停搏后护理
Keywords: Humans; *Hypothermia, Induced; *Heart Arrest/therapy

Hypothermia versus Normothermia after Out-of-Hospital Cardiac Arrest - Dankiewicz, Josef; Cronberg, Tobias; Lilja, Gisela; Jakobsen, Janus C.; Levin, Helena; Ullén, Susann; Rylander, Christian; Wise, Matt P.; Oddo, Mauro; Cariou, Alain; Bělohlávek, Jan; Hovdenes, Jan; et al. (The New England journal of medicine, 2021)
BACKGROUND: Targeted temperature management is recommended for patients after cardiac arrest, but the supporting evidence is of low certainty. METHODS: In an open-label trial with blinded assessment of outcomes, we randomly assigned 1900 adults with coma who had had an out-of-hospital cardiac arrest of presumed cardiac or unknown cause to undergo targeted hypothermia at 33°C, followed by controlled rewarming, or targeted normothermia with early treatment of fever (body temperature, ≥37.8°C). The primary outcome was death from any cause at 6 months. Secondary outcomes included functional outcome at 6 months as assessed with the modified Rankin scale. Prespecified subgroups were defined according to sex, age, initial cardiac rhythm, time to return of spontaneous circulation, and presence or absence of shock on admission. Prespecified adverse events were pneumonia, sepsis, bleeding, arrhythmia resulting in hemodynamic compromise, and skin complications related to the temperature management device. RESULTS: A total of 1850 patients were evaluated for the primary outcome. At 6 months, 465 of 925 patients (50%) in the hypothermia group had died, as compared with 446 of 925 (48%) in the normothermia group (relative risk with hypothermia, 1.04; 95% confidence interval [CI], 0.94 to 1.14; P = 0.37). Of the 1747 patients in whom the functional outcome was assessed, 488 of 881 (55%) in the hypothermia group had moderately severe disability or worse (modified Rankin scale score ≥4), as compared with 479 of 866 (55%) in the normothermia group (relative risk with hypothermia, 1.00; 95% CI, 0.92 to 1.09). Outcomes were consistent in the prespecified subgroups. Arrhythmia resulting in hemodynamic compromise was more common in the hypothermia group than in the normothermia group (24% vs. 17%, P<0.001). The incidence of other adverse events did not differ significantly between the two groups. CONCLUSIONS: In patients with coma after out-of-hospital cardiac arrest, targeted hypothermia did not lead to a lower incidence of death by 6 months than targeted normothermia.
院外心脏骤停后低体温与正常体温的比较 背景：建议心脏骤停后患者进行目标温度管理，但支持性证据的确定性较低。 方法：在一项结局评估设盲的开放标签试验中，我们将1900例推测有心脏或未知原因的院外心脏骤停的昏迷成人随机分配至接受33 ℃靶向低温治疗，随后进行控制性复温，或早期发热（体温、â‰¥37.8Â°C).主要结局为6个月时全因死亡。次要结局包括改良Rankin量表评估的6个月时功能结局。预先规定的亚组根据性别、年龄、初始心律、至自主循环恢复的时间和入院时是否存在休克进行定义。预先规定的不良事件为肺炎、败血症、出血、导致血液动力学受损的心律失常以及与温度管理设备相关的皮肤并发症。 结果：共评价了1850例患者的主要结局。6个月时，低温组925例患者中465例(50%)死亡，而正常体温组925例患者中446例(48%)死亡（低温相对风险，1.04；95%置信区间[CI]，0.94至1.14；P = 0.37）。在评估功能结局的1747名患者中，881名低温组患者中有488名患者(55%)出现中重度残疾或更严重残疾（改良Rankin量表评分â‰¥4），相比之下，866名常温组患者中有479名患者(55%)出现中重度残疾或更严重残疾（低温的相对风险，1.00；95%CI，0.92至1.09）。预先设定的亚组结局一致。低温组中导致血液动力学受损的心律失常比正常体温组更常见(24%vs. 17%，P < 0.001)。两组间其他不良事件的发生率无显著差异。 结论：在院外心脏骤停后昏迷的患者中，与目标体温正常相比，目标体温过低不会导致6个月内的死亡率降低。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Aged; Kaplan-Meier Estimate; Single-Blind Method; Body Temperature; *Hypothermia, Induced/adverse effects; Cardiopulmonary Resuscitation/methods; Coma/etiology/therapy; Fever/etiology/*therapy; Out-of-Hospital Cardiac Arrest/complications/mortality/*therapy

Escaping the Labyrinth - On Finding a Common Path Forward in the ICU - Han, Jason J.; Raiten, Jesse M. (The New England journal of medicine, 2021)
走出迷路——ICU寻找共同的前进之路
Keywords: Humans; Female; Aged; Chronic Disease; Critical Illness/*therapy; Frail Elderly; *Professional-Family Relations; *Intensive Care Units/organization & administration; *Patient Care Management

Warming Up to Cold Perfusion - Williams, Winfred W.; Markmann, James F. (The New England journal of medicine, 2021)
预热至冷灌注
Keywords: Humans; Perfusion; *Liver Transplantation; Organ Preservation

Hypothermic Machine Perfusion in Liver Transplantation - A Randomized Trial - van Rijn, Rianne; Schurink, Ivo J.; de Vries, Yvonne; van den Berg, Aad P.; Cortes Cerisuelo, Miriam; Darwish Murad, Sarwa; Erdmann, Joris I.; Gilbo, Nicholas; de Haas, Robbert J.; Heaton, Nigel; van Hoek, Bart; Huurman, Volkert A. L.; et al. (The New England journal of medicine, 2021)
BACKGROUND: Transplantation of livers obtained from donors after circulatory death is associated with an increased risk of nonanastomotic biliary strictures. Hypothermic oxygenated machine perfusion of livers may reduce the incidence of biliary complications, but data from prospective, controlled studies are limited. METHODS: In this multicenter, controlled trial, we randomly assigned patients who were undergoing transplantation of a liver obtained from a donor after circulatory death to receive that liver either after hypothermic oxygenated machine perfusion (machine-perfusion group) or after conventional static cold storage alone (control group). The primary end point was the incidence of nonanastomotic biliary strictures within 6 months after transplantation. Secondary end points included other graft-related and general complications. RESULTS: A total of 160 patients were enrolled, of whom 78 received a machine-perfused liver and 78 received a liver after static cold storage only (4 patients did not receive a liver in this trial). Nonanastomotic biliary strictures occurred in 6% of the patients in the machine-perfusion group and in 18% of those in the control group (risk ratio, 0.36; 95% confidence interval [CI], 0.14 to 0.94; P = 0.03). Postreperfusion syndrome occurred in 12% of the recipients of a machine-perfused liver and in 27% of those in the control group (risk ratio, 0.43; 95% CI, 0.20 to 0.91). Early allograft dysfunction occurred in 26% of the machine-perfused livers, as compared with 40% of control livers (risk ratio, 0.61; 95% CI, 0.39 to 0.96). The cumulative number of treatments for nonanastomotic biliary strictures was lower by a factor of almost 4 after machine perfusion, as compared with control. The incidence of adverse events was similar in the two groups. CONCLUSIONS: Hypothermic oxygenated machine perfusion led to a lower risk of nonanastomotic biliary strictures following the transplantation of livers obtained from donors after circulatory death than conventional static cold storage.
低温机器灌注在肝移植中的应用-一项随机试验 背景：循环死亡后供体肝脏移植与非吻合口胆管狭窄风险增加相关。低温氧合机器肝脏灌注可能降低胆道并发症的发生率，但前瞻性、对照研究的数据有限。 方法：在这项多中心、对照试验中，我们将接受循环死亡后供体肝脏移植的患者随机分配至低温氧合机灌注后（机器灌注组）或常规单独静态冷藏后（对照组）接受肝脏移植。主要终点是移植后6个月内非吻合胆道狭窄的发生率。次要终点包括其他移植物相关和一般并发症。 结果：共入组160例患者，其中78例接受机器灌注肝脏，78例仅在静态冷藏后接受肝脏（本试验中4例患者未接受肝脏）。机器灌注组6%的患者和对照组18%的患者发生非吻合性胆道狭窄（风险比，0.36；95%置信区间[CI]，0.14至0.94；P = 0.03）。再灌注后综合征在机器灌注肝脏受体中的发生率为12%，在对照组中为27%（风险比，0.43；95%CI，0.20至0.91）。26%的机器灌注肝脏患者发生早期同种异体移植物功能障碍，相比之下，40%的对照肝脏患者发生早期同种异体移植物功能障碍（风险比，0.61；95%CI，0.39-0.96）。与对照组相比，机器灌注后非吻合口胆道狭窄的累积治疗次数几乎降低了4倍。两组不良事件发生率相似。 结论：与传统静态冷藏相比，低温氧合机器灌注导致循环死亡后供体肝脏移植后发生非吻合口胆道狭窄的风险较低。
Keywords: Humans; Perfusion; Female; Male; Middle Aged; Adult; *Liver Transplantation; Cold Temperature; *Cold Ischemia; Biliary Tract/*pathology; Constriction, Pathologic/prevention & control; Organ Preservation/*methods; Reperfusion Injury/prevention & control

Dexmedetomidine or Propofol for Sedation in Mechanically Ventilated Adults with Sepsis - Hughes, Christopher G.; Mailloux, Patrick T.; Devlin, John W.; Swan, Joshua T.; Sanders, Robert D.; Anzueto, Antonio; Jackson, James C.; Hoskins, Aimee S.; Pun, Brenda T.; Orun, Onur M.; Raman, Rameela; Stollings, Joanna L.; et al. (The New England journal of medicine, 2021)
BACKGROUND: Guidelines currently recommend targeting light sedation with dexmedetomidine or propofol for adults receiving mechanical ventilation. Differences exist between these sedatives in arousability, immunity, and inflammation. Whether they affect outcomes differentially in mechanically ventilated adults with sepsis undergoing light sedation is unknown. METHODS: In a multicenter, double-blind trial, we randomly assigned mechanically ventilated adults with sepsis to receive dexmedetomidine (0.2 to 1.5 Î¼g per kilogram of body weight per hour) or propofol (5 to 50 Î¼g per kilogram per minute), with doses adjusted by bedside nurses to achieve target sedation goals set by clinicians according to the Richmond Agitation-Sedation Scale (RASS, on which scores range from -5 [unresponsive] to +4 [combative]). The primary end point was days alive without delirium or coma during the 14-day intervention period. Secondary end points were ventilator-free days at 28 days, death at 90 days, and age-adjusted total score on the Telephone Interview for Cognitive Status questionnaire (TICS-T; scores range from 0 to 100, with a mean of 50Â±10 and lower scores indicating worse cognition) at 6 months. RESULTS: Of 432 patients who underwent randomization, 422 were assigned to receive a trial drug and were included in the analyses - 214 patients received dexmedetomidine at a median dose of 0.27 Î¼g per kilogram per hour, and 208 received propofol at a median dose of 10.21 Î¼g per kilogram per minute. The median duration of receipt of the trial drugs was 3.0 days (interquartile range, 2.0 to 6.0), and the median RASS score was -2.0 (interquartile range, -3.0 to -1.0). We found no difference between dexmedetomidine and propofol in the number of days alive without delirium or coma (adjusted median, 10.7 vs. 10.8 days; odds ratio, 0.96; 95% confidence interval [CI], 0.74 to 1.26), ventilator-free days (adjusted median, 23.7 vs. 24.0 days; odds ratio, 0.98; 95% CI, 0.63 to 1.51), death at 90 days (38% vs. 39%; hazard ratio, 1.06; 95% CI, 0.74 to 1.52), or TICS-T score at 6 months (adjusted median score, 40.9 vs. 41.4; odds ratio, 0.94; 95% CI, 0.66 to 1.33). Safety end points were similar in the two groups. CONCLUSIONS: Among mechanically ventilated adults with sepsis who were being treated with recommended light-sedation approaches, outcomes in patients who received dexmedetomidine did not differ from outcomes in those who received propofol.
右美托咪定或丙泊酚在机械通气成人脓毒症患者中的镇静作用 背景：指南目前推荐接受机械通气的成人以右美托咪定或丙泊酚作为轻度镇静的目标。这些镇静剂在可唤醒性、免疫力和炎症方面存在差异。尚不清楚其是否对行轻度镇静的机械通气脓毒症成人的结局有不同的影响。 方法：在一项多中心、双盲试验中，我们将接受机械通气的脓毒症成人随机分配至接受右美托咪定（0.2-1.5¼g/kg体重/小时）或丙泊酚（5-50¼g/kg体重/分钟），根据Richmond躁动-镇静量表（RASS，评分范围从-5[无应答]至 + 4[好斗]），由床边护士调整剂量以达到临床医生设定的目标镇静。主要终点是在14天干预期内存活天数，无谵妄或昏迷。次要终点是第28天的无呼吸机天数、第90天的死亡和第6个月时认知状态电话访问问卷（TICS-T；评分范围从0到100，平均值为50æ±10，评分越低表明认知越差）的年龄调整总分。 结果：在432例接受随机分组的患者中，422例被分配接受试验药物并纳入分析中-214例患者接受右美托咪定治疗，中位剂量为0.27≦g/kg/小时，208例患者接受丙泊酚治疗，中位剂量为10.21≦g/kg/分钟。接受试验药物的中位持续时间为3.0天（四分位距，2.0至6.0），中位RASS评分为-2.0（四分位距，-3.0至-1.0）。我们发现右美托咪定和丙泊酚在无谵妄或昏迷的存活天数（调整的中位数，10.7对比10.8天；比值比，0.96；95%置信区间[CI]，0.74-1.26）、无呼吸机天数（调整的中位数，23.7对比24.0天；比值比，0.98；95%CI，0.63-1.51）、90天时死亡（38%对比39%；风险比，1.06；95%CI，0.74-1.52），或6个月时TICS-T评分（校正的中位评分，40.9对比41.4；比值比，0.94；95%CI，0.66-1.33）。两组的安全性终点相似。 结论：在接受推荐的光镇静方法治疗的机械通气的脓毒症成人患者中，接受右美托咪定的患者的结局与接受丙泊酚的患者的结局无差异。
Keywords: Humans; Double-Blind Method; Critical Illness; Adult; Kaplan-Meier Estimate; *Respiration, Artificial; *Dexmedetomidine/administration & dosage; *Hypnotics and Sedatives/administration & dosage/adverse effects; *Propofol/administration & dosage; Cognition/drug effects; Conscious Sedation/*methods; Sepsis/mortality/*therapy

Effect of Oxygen Therapy on Mortality in the ICU - Young, Paul J. (The New England journal of medicine, 2021)
氧疗对ICU死亡率的影响
Keywords: Humans; Intensive Care Units; Oxygen; *Respiratory Insufficiency/therapy; *Oxygen Inhalation Therapy

Lower or Higher Oxygenation Targets for Acute Hypoxemic Respiratory Failure - Schjørring, Olav L.; Klitgaard, Thomas L.; Perner, Anders; Wetterslev, Jørn; Lange, Theis; Siegemund, Martin; Bäcklund, Minna; Keus, Frederik; Laake, Jon H.; Morgan, Matthew; Thormar, Katrin M.; Rosborg, Søren A.; et al. (The New England journal of medicine, 2021)
BACKGROUND: Patients with acute hypoxemic respiratory failure in the intensive care unit (ICU) are treated with supplemental oxygen, but the benefits and harms of different oxygenation targets are unclear. We hypothesized that using a lower target for partial pressure of arterial oxygen (Pao(2)) would result in lower mortality than using a higher target. METHODS: In this multicenter trial, we randomly assigned 2928 adult patients who had recently been admitted to the ICU (≤12 hours before randomization) and who were receiving at least 10 liters of oxygen per minute in an open system or had a fraction of inspired oxygen of at least 0.50 in a closed system to receive oxygen therapy targeting a Pao(2) of either 60 mm Hg (lower-oxygenation group) or 90 mm Hg (higher-oxygenation group) for a maximum of 90 days. The primary outcome was death within 90 days. RESULTS: At 90 days, 618 of 1441 patients (42.9%) in the lower-oxygenation group and 613 of 1447 patients (42.4%) in the higher-oxygenation group had died (adjusted risk ratio, 1.02; 95% confidence interval, 0.94 to 1.11; P = 0.64). At 90 days, there was no significant between-group difference in the percentage of days that patients were alive without life support or in the percentage of days they were alive after hospital discharge. The percentages of patients who had new episodes of shock, myocardial ischemia, ischemic stroke, or intestinal ischemia were similar in the two groups (P = 0.24). CONCLUSIONS: Among adult patients with acute hypoxemic respiratory failure in the ICU, a lower oxygenation target did not result in lower mortality than a higher target at 90 days.
急性低氧性呼吸衰竭的较低或较高氧合目标 背景：重症监护室(ICU)的急性低氧性呼吸衰竭患者接受了辅助供氧治疗，但不同氧合目标的益处和危害尚不清楚。我们假设采用较低的动脉血氧分压目标(pao2)比采用较高的目标会降低死亡率。 方法：在本项多中心试验中，我们将2928例近期入住ICU的成人患者（âë‰随机化前12小时）随机分配，在开放系统中每分钟至少接受10L氧气，或在密闭系统中吸入氧气分数至少为0.50的成人患者接受针对Pao(2)和Pao(2)的氧疗。er 60 mmHg（低氧合作用组）或90 mmHg（高氧合作用组），最长90天。主要结局为90天内死亡。 结果：第90天，低氧合组1441例患者中的618例(42.9%)和高氧合组1447例患者中的613例(42.4%)死亡（校正风险比，1.02；95%置信区间，0.94至1.11；P = 0.64）。在90天时，患者在没有生命支持的情况下存活的天数百分数或出院后存活的天数百分数没有显著的组间差异。两组中新发休克、心肌缺血、缺血性卒中或肠缺血的患者百分比相似(P = 0.24)。 结论：在ICU的急性低氧性呼吸衰竭成人患者中，较低的氧合目标不会导致90天时的死亡率低于较高目标。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Kaplan-Meier Estimate; Respiration, Artificial/methods; Oxygen Inhalation Therapy/*methods; Hypoxia/blood/etiology/therapy; Oxygen/*administration & dosage/*blood; Respiratory Distress Syndrome/blood/mortality/therapy; Respiratory Insufficiency/blood/complications/mortality/*therapy

Case 7-2021: A 19-Year-Old Man with Shock, Multiple Organ Failure, and Rash - Bendapudi, Pavan K.; Whalen, Michael J.; Lahoud-Rahme, Manuella; Villalba, Julian A. (The New England journal of medicine, 2021)
病例7-2021：一例19岁的男性患者发生休克、多器官功能衰竭和皮疹
Keywords: Humans; Male; Young Adult; Diagnosis, Differential; Anticoagulants/therapeutic use; Electrocardiography; Multiple Organ Failure/etiology; Disseminated Intravascular Coagulation/complications/*diagnosis; Exanthema/etiology; Meningococcal Infections/complications/*diagnosis; Neisseria meningitidis, Serogroup C/*isolation & purification; Purpura Fulminans/*diagnosis/etiology; Purpura, Thrombocytopenic/diagnosis; Shock/etiology; Vasculitis/diagnosis

The RECOVERY Platform - Normand, Sharon-Lise T. (The New England journal of medicine, 2021)
RECOVERY平台
Keywords: Humans; SARS-CoV-2; *COVID-19/drug therapy; Dexamethasone

Dexamethasone in Hospitalized Patients with Covid-19 - Horby, Peter; Lim, Wei Shen; Emberson, Jonathan R.; Mafham, Marion; Bell, Jennifer L.; Linsell, Louise; Staplin, Natalie; Brightling, Christopher; Ustianowski, Andrew; Elmahi, Einas; Prudon, Benjamin; Green, Christopher; et al. (The New England journal of medicine, 2021)
BACKGROUND: Coronavirus disease 2019 (Covid-19) is associated with diffuse lung damage. Glucocorticoids may modulate inflammation-mediated lung injury and thereby reduce progression to respiratory failure and death. METHODS: In this controlled, open-label trial comparing a range of possible treatments in patients who were hospitalized with Covid-19, we randomly assigned patients to receive oral or intravenous dexamethasone (at a dose of 6 mg once daily) for up to 10 days or to receive usual care alone. The primary outcome was 28-day mortality. Here, we report the final results of this assessment. RESULTS: A total of 2104 patients were assigned to receive dexamethasone and 4321 to receive usual care. Overall, 482 patients (22.9%) in the dexamethasone group and 1110 patients (25.7%) in the usual care group died within 28 days after randomization (age-adjusted rate ratio, 0.83; 95% confidence interval [CI], 0.75 to 0.93; P<0.001). The proportional and absolute between-group differences in mortality varied considerably according to the level of respiratory support that the patients were receiving at the time of randomization. In the dexamethasone group, the incidence of death was lower than that in the usual care group among patients receiving invasive mechanical ventilation (29.3% vs. 41.4%; rate ratio, 0.64; 95% CI, 0.51 to 0.81) and among those receiving oxygen without invasive mechanical ventilation (23.3% vs. 26.2%; rate ratio, 0.82; 95% CI, 0.72 to 0.94) but not among those who were receiving no respiratory support at randomization (17.8% vs. 14.0%; rate ratio, 1.19; 95% CI, 0.92 to 1.55). CONCLUSIONS: In patients hospitalized with Covid-19, the use of dexamethasone resulted in lower 28-day mortality among those who were receiving either invasive mechanical ventilation or oxygen alone at randomization but not among those receiving no respiratory support.
使用Covid-19的住院患者中的地塞米松 背景：2019年冠状病毒病(Covid-19)与弥漫性肺损伤相关。糖皮质激素可调节炎症介导的肺损伤，从而减少进展为呼吸衰竭和死亡。 方法：在这项对照、开放标签试验中，在使用Covid-19住院的患者中比较各种可能的治疗，我们将患者随机分配至接受口服或静脉注射地塞米松（剂量为6 mg，每日一次）长达10天或仅接受常规治疗。主要结局为28天死亡率。在此，我们报告了本次评估的最终结果。 结果：共有2104例患者被分配接受地塞米松治疗，4321例接受常规治疗。总体而言，地塞米松组482例患者(22.9%)和常规治疗组1110例患者(25.7%)在随机化后28天内死亡（年龄调整率比，0.83；95%置信区间[CI]，0.75-0.93；P < 0.001）。根据随机化时患者正在接受的呼吸支持水平，死亡率的比例和绝对组间差异有相当大的变化。在地塞米松组中，接受有创机械通气的患者（29.3%vs. 41.4%；率比，0.64；95%CI，0.51-0.81）和接受无创机械通气吸氧的患者（23.3%vs. 26.2%；率比，0.82；95%CI，0.72至0.94），但在随机化时未接受呼吸支持的患者中并非如此（17.8%vs. 14.0%；率比，1.19；95%CI，0.92至1.55）。 结论：在使用Covid-19住院的患者中，在随机化时接受有创机械通气或单独吸氧的患者中使用地塞米松降低了28天死亡率，但未接受呼吸支持的患者中未出现这种情况。
Keywords: Humans; Drug Therapy, Combination; Female; Male; Aged; Length of Stay; Aged, 80 and over; United Kingdom; Kaplan-Meier Estimate; Hospitalization; Administration, Oral; Odds Ratio; *Respiration, Artificial; *Oxygen Inhalation Therapy; Anti-Infective Agents/therapeutic use; COVID-19/*drug therapy/mortality/therapy; Dexamethasone/administration & dosage/adverse effects/*therapeutic use; Glucocorticoids/administration & dosage/adverse effects/*therapeutic use; Injections, Intravenous

Research in the Context of a Pandemic - Lane, H. Clifford; Fauci, Anthony S. (The New England journal of medicine, 2021)
流行病背景下的研究
Keywords: Humans; SARS-CoV-2; *Pandemics; *COVID-19/drug therapy; Dexamethasone

Case 2-2021: A 26-Year-Old Pregnant Woman with Ventricular Tachycardia and Shock - Scott, Nandita S.; Thomas, Sunu S.; DeFaria Yeh, Doreen; Fox, Andrew S.; Smith, R. Neal (The New England journal of medicine, 2021)
病例2-2021：一名26岁的患室性心动过速和休克的孕龄期妇女
Keywords: Humans; Female; Adult; Diagnosis, Differential; Tomography, X-Ray Computed; Pregnancy; Echocardiography; Extracorporeal Membrane Oxygenation; Lung/diagnostic imaging; Electrocardiography; Heart Transplantation; Heart-Assist Devices; *Pregnancy Complications, Cardiovascular; Aneurysm, Dissecting/complications; Coronary Artery Disease/complications; Heart Arrest/etiology; Heart/diagnostic imaging; Myocardial Infarction/complications/*diagnosis/therapy; Myocardium/pathology; Shock, Cardiogenic/*etiology; Tachycardia, Ventricular/*complications

Tocilizumab in Patients Hospitalized with Covid-19 Pneumonia - Salama, Carlos; Han, Jian; Yau, Linda; Reiss, William G.; Kramer, Benjamin; Neidhart, Jeffrey D.; Criner, Gerard J.; Kaplan-Lewis, Emma; Baden, Rachel; Pandit, Lavannya; Cameron, Miriam L.; Garcia-Diaz, Julia; et al. (The New England journal of medicine, 2021)
BACKGROUND: Coronavirus disease 2019 (Covid-19) pneumonia is often associated with hyperinflammation. Despite the disproportionate incidence of Covid-19 among underserved and racial and ethnic minority populations, the safety and efficacy of the anti-interleukin-6 receptor antibody tocilizumab in patients from these populations who are hospitalized with Covid-19 pneumonia are unclear. METHODS: We randomly assigned (in a 2:1 ratio) patients hospitalized with Covid-19 pneumonia who were not receiving mechanical ventilation to receive standard care plus one or two doses of either tocilizumab (8 mg per kilogram of body weight intravenously) or placebo. Site selection was focused on the inclusion of sites enrolling high-risk and minority populations. The primary outcome was mechanical ventilation or death by day 28. RESULTS: A total of 389 patients underwent randomization, and the modified intention-to-treat population included 249 patients in the tocilizumab group and 128 patients in the placebo group; 56.0% were Hispanic or Latino, 14.9% were Black, 12.7% were American Indian or Alaska Native, 12.7% were non-Hispanic White, and 3.7% were of other or unknown race or ethnic group. The cumulative percentage of patients who had received mechanical ventilation or who had died by day 28 was 12.0% (95% confidence interval [CI], 8.5 to 16.9) in the tocilizumab group and 19.3% (95% CI, 13.3 to 27.4) in the placebo group (hazard ratio for mechanical ventilation or death, 0.56; 95% CI, 0.33 to 0.97; P = 0.04 by the log-rank test). Clinical failure as assessed in a time-to-event analysis favored tocilizumab over placebo (hazard ratio, 0.55; 95% CI, 0.33 to 0.93). Death from any cause by day 28 occurred in 10.4% of the patients in the tocilizumab group and 8.6% of those in the placebo group (weighted difference, 2.0 percentage points; 95% CI, -ï»¿5.2 to 7.8). In the safety population, serious adverse events occurred in 38 of 250 patients (15.2%) in the tocilizumab group and 25 of 127 patients (19.7%) in the placebo group. CONCLUSIONS: In hospitalized patients with Covid-19 pneumonia who were not receiving mechanical ventilation, tocilizumab reduced the likelihood of progression to the composite outcome of mechanical ventilation or death, but it did not improve survival. No new safety signals were identified.
托珠单抗在Covid-19肺炎住院患者中的应用 背景：2019年冠状病毒病(Covid-19)相关肺炎通常与炎症反应相关。尽管Covid-19在服务不足人群以及人种和种族少数人群中的发生率不成比例，但在这些人群因Covid-19肺炎住院的患者中，抗白细胞介素-6受体抗体托珠单抗的安全性和疗效尚不清楚。 方法：我们将因Covid-19肺炎住院且未接受机械通气的患者随机（以2:1的比例）分配至接受标准治疗加1或2剂托珠单抗（静脉给药8 mg/kg体重）或安慰剂。研究中心选择的重点是纳入入组高风险和少数人群的研究中心。主要结局为第28天的机械通气或死亡。 结果：共389例患者接受随机分组，改良的意向治疗人群包括托珠单抗组249例患者和安慰剂组128例患者；56.0%为西班牙裔或拉丁裔，14.9%为黑人，12.7%为美洲印第安人或阿拉斯加原住民，12.7%为非西班牙裔白人，3.7%为其他或未知人种或种族组。托珠单抗组中接受机械通气或第28天死亡的患者的累积百分比为12.0%（95%置信区间[CI]，8.5至16.9），安慰剂组为19.3%（95%CI，13.3至27.4）（机械通气或死亡的风险比，0.56；95%CI，0.33至0.97；P = 0.04（对数秩检验）。在至事件发生时间分析中评估的临床失败结果支持托珠单抗优于安慰剂（风险比0.55；95%CI 0.33-0.93）。第28天时，托珠单抗组10.4%的患者和安慰剂组8.6%的患者发生了全因死亡（加权差异，2.0个百分点；95%CI,-ï»Γ»5.2至7.8）。在安全性人群中，250例患者中有38例(15.2%)发生严重不良事件托珠单抗组127例患者中的25例(19.7%)，安慰剂组127例患者中的25例。 结论：在未接受机械通气的Covid-19肺炎住院患者中，托珠单抗降低了进展为机械通气或死亡复合结局的可能性，但并未改善生存率。未发现新的安全性信号。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Respiration, Artificial; Disease Progression; Survival Rate; Intention to Treat Analysis; Hospitalization; Antibodies, Monoclonal, Humanized/*therapeutic use; COVID-19/*drug therapy/ethnology/mortality; Pneumonia, Viral/drug therapy

FDA Approval of Remdesivir - A Step in the Right Direction - Rubin, Daniel; Chan-Tack, Kirk; Farley, John; Sherwat, Adam (The New England journal of medicine, 2020)
FDA批准Remdesivir–朝正确方向迈出的一步
Keywords: Humans; Adult; Adolescent; Child; Randomized Controlled Trials as Topic; United States; COVID-19/*drug therapy; Antiviral Agents/therapeutic use; *Drug Approval; Adenosine Monophosphate/*analogs & derivatives/therapeutic use; Alanine/*analogs & derivatives/therapeutic use; Clinical Trials, Phase III as Topic; United States Food and Drug Administration

Severe Covid-19 - Berlin, David A.; Gulick, Roy M.; Martinez, Fernando J. (The New England journal of medicine, 2020)
重度Covid-19
Keywords: Humans; Male; Middle Aged; Respiration, Artificial; Tomography, X-Ray Computed; Brain/diagnostic imaging; Antiviral Agents/therapeutic use; Anti-Inflammatory Agents/therapeutic use; Patient Acuity; Dexamethasone/therapeutic use; Adenosine Monophosphate/analogs & derivatives/therapeutic use; Alanine/analogs & derivatives/therapeutic use; COVID-19 Testing; COVID-19/complications/diagnosis/*therapy; Dyspnea/etiology; Lung/diagnostic imaging/pathology; Radiography, Thoracic; Respiratory Distress Syndrome/etiology/therapy; SARS-CoV-2/genetics/*isolation & purification

Green Urine - Boshkovska Spaseski, Maja; Spaseski, Dejan (The New England journal of medicine, 2020)
绿色尿液
Keywords: Humans; Male; Middle Aged; *Color; *Urine; Bilirubin/blood; Hypnotics and Sedatives/*adverse effects; Propofol/*adverse effects; Respiratory Insufficiency/drug therapy

Cytokine Storm - Fajgenbaum, David C.; June, Carl H. (The New England journal of medicine, 2020)
细胞因子储存
Keywords: Humans; COVID-19/*complications; Autoimmune Diseases/complications; Bacterial Infections/complications; Blood Proteins/physiology; Chemokines/physiology; Cytokine Release Syndrome/etiology/*physiopathology/therapy; Cytokines/immunology/*physiology; Interleukins/physiology; Virus Diseases/complications

A Randomized Trial of Laryngeal Mask Airway in Neonatal Resuscitation - Pejovic, Nicolas J.; Myrnerts Höök, Susanna; Byamugisha, Josaphat; Alfvén, Tobias; Lubulwa, Clare; Cavallin, Francesco; Nankunda, Jolly; Ersdal, Hege; Blennow, Mats; Trevisanuto, Daniele; Tylleskär, Thorkild (The New England journal of medicine, 2020)
BACKGROUND: Face-mask ventilation is the most common resuscitation method for birth asphyxia. Ventilation with a cuffless laryngeal mask airway (LMA) has potential advantages over face-mask ventilation during neonatal resuscitation in low-income countries, but whether the use of an LMA reduces mortality and morbidity among neonates with asphyxia is unknown. METHODS: In this phase 3, open-label, superiority trial in Uganda, we randomly assigned neonates who required positive-pressure ventilation to be treated by a midwife with an LMA or with face-mask ventilation. All the neonates had an estimated gestational age of at least 34 weeks, an estimated birth weight of at least 2000 g, or both. The primary outcome was a composite of death within 7 days or admission to the neonatal intensive care unit (NICU) with moderate-to-severe hypoxic-ischemic encephalopathy at day 1 to 5 during hospitalization. RESULTS: Complete follow-up data were available for 99.2% of the neonates. A primary outcome event occurred in 154 of 563 neonates (27.4%) in the LMA group and 144 of 591 (24.4%) in the face-mask group (adjusted relative risk, 1.16; 95% confidence interval [CI], 0.90 to 1.51; P = 0.26). Death within 7 days occurred in 21.7% of the neonates in the LMA group and 18.4% of those in the face-mask group (adjusted relative risk, 1.21; 95% CI, 0.90 to 1.63), and admission to the NICU with moderate-to-severe hypoxic-ischemic encephalopathy at day 1 to 5 during hospitalization occurred in 11.2% and 10.1%, respectively (adjusted relative risk, 1.27; 95% CI, 0.84 to 1.93). Findings were materially unchanged in a sensitivity analysis in which neonates with missing data were counted as having had a primary outcome event in the LMA group and as not having had such an event in the face-mask group. The frequency of predefined intervention-related adverse events was similar in the two groups. CONCLUSIONS: In neonates with asphyxia, the LMA was safe in the hands of midwives but was not superior to face-mask ventilation with respect to early neonatal death and moderate-to-severe hypoxic-ischemic encephalopathy.
喉罩通气在新生儿复苏中的应用 背景：面罩通气是出生窒息最常见的复苏方法。在低收入国家的新生儿复苏期间，使用无套囊喉罩气道(LMA)通气较面罩通气具有潜在优势，但在窒息新生儿中使用LMA是否能降低死亡率和发病率尚不清楚。 方法：在乌干达进行的一项3期、开放标签、优效性试验中，我们将需要正压通气的新生儿随机分配至由助产士使用LMA或面罩通气。所有新生儿的估计胎龄至少为34周，估计出生体重至少为2000 g，或两者均有。主要结局是7天内死亡或入住新生儿重症监护室(NICU)（住院期间第1-5天患有中度至重度缺氧缺血性脑病）的复合结局。 结果：获得了99.2%新生儿的完整随访数据。LMA组154/563名新生儿(27.4%)和面罩组144/591名新生儿(24.4%)发生主要结局事件（校正后的相对风险，1.16；95%置信区间[CI]，0.90-1.51；P = 0.26）。LMA组21.7%的新生儿和面罩组18.4%的新生儿在7天内死亡（校正的相对风险，1.21；95%CI，0.90至1.63），住院期间第1-5天因中重度缺氧缺血性脑病入住NICU的比例分别为11.2%和10.1%，分别为（调整后的相对风险，1.27；95%CI，0.84-1.93）。在一项敏感性分析中，结果基本没有变化，其中缺失数据的新生儿被计为在LMA组发生了主要结局事件，而在面罩组未发生此类事件。两组中预先定义的干预相关不良事件的频率相似。 结论：在窒息新生儿中，LMA在助产士手中是安全的，但在早期新生儿死亡和中重度缺氧缺血性脑病方面并不优于面罩通气。
Keywords: Humans; Female; Male; Infant, Newborn; Cross-Over Studies; *Laryngeal Masks; Asphyxia Neonatorum/complications/mortality/*therapy; Hypoxia-Ischemia, Brain/etiology/*prevention & control; Intubation, Intratracheal/*instrumentation; Midwifery; Positive-Pressure Respiration/*instrumentation; Resuscitation/*instrumentation/methods

Colloid Transfusion, Natural Anticoagulant Depletion, and Symmetric Peripheral Gangrene - Warkentin, Theodore E.; Ning, Shuoyan; Lim, Wendy (The New England journal of medicine, 2020)
胶体输血、天然抗凝剂耗竭和对称性外周坏疽
Keywords: Humans; Female; Middle Aged; Critical Illness; Adult; Blood Transfusion; *Blood Coagulation Factors; Albumins/*adverse effects; Colloids/administration & dosage/*adverse effects; Disseminated Intravascular Coagulation/complications; Gangrene/*etiology; Shock, Septic/*complications/therapy

Building an Evidence Base for Survivors of Critical Illness - Lamas, Daniela (The New England journal of medicine, 2020)
建立危重疾病幸存者的证据基础
Keywords: Humans; Oxygen; Quality of Life; Survivors; *Critical Illness; *Tracheostomy

High-Flow Oxygen with Capping or Suctioning for Tracheostomy Decannulation - HernÃ¡ndez MartÃnez, Gonzalo; Rodriguez, Maria-Luisa; Vaquero, Maria-ConcepciÃ³n; Ortiz, RamÃ³n; Masclans, Joan-Ramon; Roca, Oriol; Colinas, Laura; de Pablo, Raul; Espinosa, Maria-Del-Carmen; Garcia-de-Acilu, Marina; Climent, Cristina; Cuena-Boy, Rafael (The New England journal of medicine, 2020)
BACKGROUND: When patients with a tracheostomy tube reach a stage in their care at which decannulation appears to be possible, it is common practice to cap the tracheostomy tube for 24 hours to see whether they can breathe on their own. Whether this approach to establishing patient readiness for decannulation leads to better outcomes than one based on the frequency of airway suctioning is unclear. METHODS: In five intensive care units (ICUs), we enrolled conscious, critically ill adults who had a tracheostomy tube; patients were eligible after weaning from mechanical ventilation. In this unblinded trial, patients were randomly assigned either to undergo a 24-hour capping trial plus intermittent high-flow oxygen therapy (control group) or to receive continuous high-flow oxygen therapy with frequency of suctioning being the indicator of readiness for decannulation (intervention group). The primary outcome was the time to decannulation, compared by means of the log-rank test. Secondary outcomes included decannulation failure, weaning failure, respiratory infections, sepsis, multiorgan failure, durations of stay in the ICU and hospital, and deaths in the ICU and hospital. RESULTS: The trial included 330 patients; the mean (Â±SD) age of the patients was 58.3Â±15.1 years, and 68.2% of the patients were men. A total of 161 patients were assigned to the control group and 169 to the intervention group. The time to decannulation was shorter in the intervention group than in the control group (median, 6 days [interquartile range, 5 to 7] vs. 13 days [interquartile range, 11 to 14]; absolute difference, 7 days [95% confidence interval, 5 to 9]). The incidence of pneumonia and tracheobronchitis was lower, and the duration of stay in the hospital shorter, in the intervention group than in the control group. Other secondary outcomes were similar in the two groups. CONCLUSIONS: Basing the decision to decannulate on suctioning frequency plus continuous high-flow oxygen therapy rather than on 24-hour capping trials plus intermittent high-flow oxygen therapy reduced the time to decannulation, with no evidence of a between-group difference in the incidence of decannulation failure. (REDECAP ClinicalTrials.gov number, NCT02512744.).
用于气管切开拔管的带盖高流量氧气或抽吸 背景：当放置气管切开插管的患者达到可能拔管的护理阶段时，通常会将气管切开插管加盖24小时，以观察其是否能够自主呼吸。尚不清楚这种确定患者是否准备拔管的方法是否比基于气道抽吸频率的方法获得更好的结果。 方法：在5个重症监护室(ICU)中，我们入选了有气管切开插管的清醒、危重成人患者；患者在机械通气断开后合格。在这项非盲试验中，患者被随机分配接受24小时封顶试验加间歇性高流量氧疗（对照组）或接受以抽吸频率作为准备拔管指标的连续高流量氧疗（干预组）。主要结局是拔管时间，通过对数秩检验进行比较。次要结局包括拔管失败、撤机失败、呼吸道感染、败血症、多器官衰竭、在ICU和医院的停留时间以及在ICU和医院的死亡。 结果：本试验共纳入330例患者；患者的平均(·±SD)年龄为58.3±15.1岁，68.2%的患者为男性。对照组共161例，干预组共169例。干预组的拔管时间短于对照组（中位数，6天[四分位距，5-7]对比13天[四分位距，11-14]；绝对差异，7天[95%置信区间，5-9]）。干预组肺炎和气管支气管炎的发生率低于对照组，住院时间短于对照组。两组的其他次要结局相似。 结论：以吸痰频率加持续高流量氧疗决定拔管，而不是以24小时封顶试验加间歇高流量氧疗决定拔管，减少了拔管时间，无证据表明拔管失败发生率的组间差异。（REDECAP临床试验gov编号，NCT02512744）。
Keywords: Humans; Female; Male; Middle Aged; Time Factors; Critical Illness; Kaplan-Meier Estimate; Intention to Treat Analysis; *Tracheostomy; Ventilator Weaning; *Oxygen Inhalation Therapy/methods; *Device Removal; *Suction

Outcomes of the Neonatal Trial of High-Frequency Oscillation at 16 to 19 Years - Harris, Christopher; Bisquera, Alessandra; Lunt, Alan; Peacock, Janet L.; Greenough, Anne (The New England journal of medicine, 2020)
16-19岁新生儿高频振荡试验的结局
Keywords: Humans; Treatment Outcome; Young Adult; Respiration, Artificial; Adolescent; Infant, Newborn; Follow-Up Studies; *High-Frequency Ventilation; Respiratory Function Tests; Bronchopulmonary Dysplasia/prevention & control; Forced Expiratory Flow Rates

Covid-19, Angiogenesis, and ARDS Endotypes - Hariri, Lida; Hardin, C. Corey (The New England journal of medicine, 2020)
Covid-19、血管生成和ARDS基因型
Keywords: Humans; COVID-19; SARS-CoV-2; *Betacoronavirus; *Pandemics; *Respiratory Distress Syndrome; *Thrombosis; *Coronavirus Infections; *Pneumonia, Viral

Pulmonary Vascular Endothelialitis, Thrombosis, and Angiogenesis in Covid-19 - Ackermann, Maximilian; Verleden, Stijn E.; Kuehnel, Mark; Haverich, Axel; Welte, Tobias; Laenger, Florian; Vanstapel, Arno; Werlein, Christopher; Stark, Helge; Tzankov, Alexandar; Li, William W.; Li, Vincent W.; et al. (The New England journal of medicine, 2020)
BACKGROUND: Progressive respiratory failure is the primary cause of death in the coronavirus disease 2019 (Covid-19) pandemic. Despite widespread interest in the pathophysiology of the disease, relatively little is known about the associated morphologic and molecular changes in the peripheral lung of patients who die from Covid-19. METHODS: We examined 7 lungs obtained during autopsy from patients who died from Covid-19 and compared them with 7 lungs obtained during autopsy from patients who died from acute respiratory distress syndrome (ARDS) secondary to influenza A(H1N1) infection and 10 age-matched, uninfected control lungs. The lungs were studied with the use of seven-color immunohistochemical analysis, micro-computed tomographic imaging, scanning electron microscopy, corrosion casting, and direct multiplexed measurement of gene expression. RESULTS: In patients who died from Covid-19-associated or influenza-associated respiratory failure, the histologic pattern in the peripheral lung was diffuse alveolar damage with perivascular T-cell infiltration. The lungs from patients with Covid-19 also showed distinctive vascular features, consisting of severe endothelial injury associated with the presence of intracellular virus and disrupted cell membranes. Histologic analysis of pulmonary vessels in patients with Covid-19 showed widespread thrombosis with microangiopathy. Alveolar capillary microthrombi were 9 times as prevalent in patients with Covid-19 as in patients with influenza (P<0.001). In lungs from patients with Covid-19, the amount of new vessel growth - predominantly through a mechanism of intussusceptive angiogenesis - was 2.7 times as high as that in the lungs from patients with influenza (P<0.001). CONCLUSIONS: In our small series, vascular angiogenesis distinguished the pulmonary pathobiology of Covid-19 from that of equally severe influenza virus infection. The universality and clinical implications of our observations require further research to define.
Covid-19中的肺血管内皮细胞炎、血栓形成和血管生成 背景：进展性呼吸衰竭是2019年(Covid-19)冠状病毒病大流行的主要死因。尽管人们对该病的病理生理学广泛关注，但对Covid-19死亡患者的外周肺脏相关形态学和分子学变化知之甚少。 方法：我们检查了Covid-19死亡患者尸检期间获得的7个肺，并与继发于甲型流感(H1N1)感染的急性呼吸窘迫综合征(ARDS)死亡患者尸检期间获得的7个肺和10个年龄匹配的未感染对照肺进行比较。使用七色免疫组化分析、微型计算机断层扫描成像、扫描电子显微镜、腐蚀铸型和直接多重测量基因表达对肺进行研究。 结果：在死于Covid-19相关或流感相关呼吸衰竭的患者中，外周肺的组织学模式为弥漫性肺泡损伤伴血管周围T细胞浸润。Covid-19患者的肺脏也表现出独特的血管特征，包括与细胞内病毒和破坏细胞膜相关的重度内皮损伤。Covid-19患者的肺血管组织学分析显示广泛血栓形成伴微血管病变。使用Covid-19的患者中肺泡毛细血管微血栓的患病率是流感患者的9倍(P < 0.001)。在Covid-19患者的肺中，新血管生长量（主要通过肠套叠血管生成机制）是流感患者肺中的2.7倍(P < 0.001)。 结论：在我们的小系列研究中，血管生成区分了Covid-19的肺部病理生物学与同样严重的流感病毒感染。我们的观察结果的普遍性和临床意义需要进一步研究来确定。
Keywords: Humans; Female; Male; Middle Aged; Aged; Aged, 80 and over; Pandemics; *Neovascularization, Pathologic; Betacoronavirus; COVID-19; SARS-CoV-2; Autopsy; Respiratory Insufficiency; Coronavirus Infections/mortality/*pathology; Endothelium, Vascular/*pathology/virology; Influenza A Virus, H1N1 Subtype; Influenza, Human/mortality/pathology; Lung/pathology; Pneumonia, Viral/mortality/*pathology; Respiratory Distress Syndrome/pathology/virology; Thrombosis/*virology

CPR in the Covid-19 Era - An Ethical Framework - Kramer, Daniel B.; Lo, Bernard; Dickert, Neal W. (The New England journal of medicine, 2020)
Covid-19时代的CPR-伦理框架
Keywords: Humans; Betacoronavirus; Coronavirus Infections; COVID-19; Pneumonia, Viral; SARS-CoV-2; Resuscitation Orders; Cardiopulmonary Resuscitation/*ethics/*standards; Health Personnel; Health Resources/supply & distribution; Occupational Exposure; Pandemics/*ethics

Case 19-2020: A 74-Year-Old Man with Acute Respiratory Failure and Unclear Goals of Care - Jacobsen, Juliet C.; Tran, Kathy M.; Jackson, Vicki A.; Rubin, Emily B. (The New England journal of medicine, 2020)
病例19-2020：一例74岁的急性呼吸衰竭患者，治疗目标不明
Keywords: Humans; Male; Aged; Diagnosis, Differential; Palliative Care; Pandemics; COVID-19; Acute Disease; Informed Consent; Lung/diagnostic imaging; *Cardiopulmonary Resuscitation; Patient Participation; *Resuscitation Orders; Fatal Outcome; Radiography, Thoracic; *Decision Making, Shared; *Influenza A virus/isolation & purification; Coronavirus Infections/diagnosis/therapy; Influenza, Human/complications/*diagnosis; Pneumonia, Viral/diagnosis/therapy; Respiratory Insufficiency/*etiology

Covid-19 and Kidney Transplantation - Akalin, Enver; Azzi, Yorg; Bartash, Rachel; Seethamraju, Harish; Parides, Michael; Hemmige, Vagish; Ross, Michael; Forest, Stefanie; Goldstein, Yitz D.; Ajaimy, Maria; Liriano-Ward, Luz; Pynadath, Cindy; et al. (The New England journal of medicine, 2020)
Covid-19与肾移植
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Risk Factors; Pandemics; Betacoronavirus; COVID-19; SARS-CoV-2; *Kidney Transplantation; *Transplant Recipients; Immunosuppressive Agents; New York City; Coronavirus Infections/*complications/mortality/physiopathology; Pneumonia, Viral/*complications/mortality/physiopathology

Case 18-2020: A 73-Year-Old Man with Hypoxemic Respiratory Failure and Cardiac Dysfunction - Kazi, Dhruv S.; Martin, Lila M.; Litmanovich, Diana; Pinto, Duane S.; Clerkin, Kevin J.; Zimetbaum, Peter J.; Dudzinski, David M. (The New England journal of medicine, 2020)
病例18-2020：一例73岁的低氧性呼吸衰竭和心功能不全患者
Keywords: Humans; Male; Aged; Diagnosis, Differential; Tomography, X-Ray Computed; Pandemics; Coronary Angiography; COVID-19; SARS-CoV-2; *Betacoronavirus; Lung/diagnostic imaging; Clinical Laboratory Techniques; Electrocardiography; COVID-19 Testing; Respiratory Insufficiency/*etiology; Atrial Fibrillation/etiology; Coronavirus Infections/complications/*diagnosis; Hypoxia/etiology; Pericarditis/diagnosis/*etiology; Pneumonia, Viral/complications/*diagnosis; Respiratory Distress Syndrome/*etiology; Troponin T/blood

Atrioventricular Dissociation during Ventricular Fibrillation - Salik, Jonathan R.; Thomas, Sunu S. (The New England journal of medicine, 2020)
室颤期间的房室分离
Keywords: Humans; Female; Middle Aged; Echocardiography; *Heart Transplantation; Electrocardiography; Fatal Outcome; *Graft Rejection/diagnosis; Heart Block/*complications/diagnosis; Heart Valves/diagnostic imaging/physiopathology; Ventricular Fibrillation/*complications

Repurposing a Pediatric ICU for Adults - Yager, Phoebe H.; Whalen, Kimberly A.; Cummings, Brian M. (The New England journal of medicine, 2020)
为成人重新设置儿科ICU
Keywords: Humans; Adult; Child; Pandemics; COVID-19; SARS-CoV-2; *Intensive Care Units; *Betacoronavirus; Coronavirus Infections/*therapy; Pneumonia, Viral/*therapy; Patient Care Team; *Intensive Care Units, Pediatric; Boston; Hospital Administration; Cooperative Behavior; Hospitals, Pediatric/*organization & administration

Case 17-2020: A 68-Year-Old Man with Covid-19 and Acute Kidney Injury - Sise, Meghan E.; Baggett, Meridale V.; Shepard, Jo-Anne O.; Stevens, Jacob S.; Rhee, Eugene P. (The New England journal of medicine, 2020)
病例17-2020：一名患有Covid-19和急性肾损伤的68岁男性
Keywords: Humans; Male; Aged; Pandemics; COVID-19; SARS-CoV-2; Antiviral Agents/therapeutic use; Anti-Inflammatory Agents/therapeutic use; Anticoagulants/therapeutic use; *Continuous Renal Replacement Therapy; Creatinine/blood; Adenosine Monophosphate/analogs & derivatives/therapeutic use; Alanine/analogs & derivatives/therapeutic use; Radiography, Thoracic; *Betacoronavirus/isolation & purification; Acute Kidney Injury/etiology/*therapy; Amides/therapeutic use; Coronavirus Infections/*complications/drug therapy/therapy; Hypertension/complications; Lung/diagnostic imaging/*pathology; Obesity/complications; Pneumonia, Viral/*complications/drug therapy/therapy; Pyrazines/therapeutic use

Acute Cor Pulmonale in Critically Ill Patients with Covid-19 - Creel-Bulos, Christina; Hockstein, Maxwell; Amin, Neha; Melhem, Samer; Truong, Alexander; Sharifpour, Milad (The New England journal of medicine, 2020)
伴有Covid-19的危重患者中的急性肺心病
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Adult; Pandemics; COVID-19; SARS-CoV-2; *Betacoronavirus; Fatal Outcome; Heart Arrest/etiology; Obesity/complications; Asthma/complications; Coronavirus Infections/*complications; Pneumonia, Viral/*complications; Pulmonary Heart Disease/*etiology/virology

Adaptations and Lessons in the Province of Bergamo - Fagiuoli, Stefano; Lorini, Ferdinando Luca; Remuzzi, Giuseppe (The New England journal of medicine, 2020)
贝加莫省的改编与教训
Keywords: Humans; Middle Aged; Aged; Intensive Care Units; Pandemics; Time-to-Treatment; COVID-19; SARS-CoV-2; *Betacoronavirus; Infection Control/*methods; Quarantine; Triage; Physicians; Hospital Bed Capacity; *Hospital Administration; *Epidemics/prevention & control; Coronavirus Infections/*epidemiology/mortality; Infectious Disease Transmission, Patient-to-Professional; Italy/epidemiology; Pneumonia, Viral/*epidemiology/mortality

Covid-19 in Critically Ill Patients in the Seattle Region - Case Series - Bhatraju, Pavan K.; Ghassemieh, Bijan J.; Nichols, Michelle; Kim, Richard; Jerome, Keith R.; Nalla, Arun K.; Greninger, Alexander L.; Pipavath, Sudhakar; Wurfel, Mark M.; Evans, Laura; Kritek, Patricia A.; West, T. Eoin; et al. (The New England journal of medicine, 2020)
BACKGROUND: Community transmission of coronavirus 2019 (Covid-19) was detected in the state of Washington in February 2020. METHODS: We identified patients from nine Seattle-area hospitals who were admitted to the intensive care unit (ICU) with confirmed infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Clinical data were obtained through review of medical records. The data reported here are those available through March 23, 2020. Each patient had at least 14 days of follow-up. RESULTS: We identified 24 patients with confirmed Covid-19. The mean (±SD) age of the patients was 64±18 years, 63% were men, and symptoms began 7±4 days before admission. The most common symptoms were cough and shortness of breath; 50% of patients had fever on admission, and 58% had diabetes mellitus. All the patients were admitted for hypoxemic respiratory failure; 75% (18 patients) needed mechanical ventilation. Most of the patients (17) also had hypotension and needed vasopressors. No patient tested positive for influenza A, influenza B, or other respiratory viruses. Half the patients (12) died between ICU day 1 and day 18, including 4 patients who had a do-not-resuscitate order on admission. Of the 12 surviving patients, 5 were discharged home, 4 were discharged from the ICU but remained in the hospital, and 3 continued to receive mechanical ventilation in the ICU. CONCLUSIONS: During the first 3 weeks of the Covid-19 outbreak in the Seattle area, the most common reasons for admission to the ICU were hypoxemic respiratory failure leading to mechanical ventilation, hypotension requiring vasopressor treatment, or both. Mortality among these critically ill patients was high.
西雅图地区危重患者中的Covid-19–病例系列 背景：2020年2月在华盛顿州检测到2019年冠状病毒(Covid-19)的社区传播。 方法：我们确定了来自9家西雅图地区医院的患者，这些患者因确诊感染严重急性呼吸综合征冠状病毒-2(SARS-CoV-2)入住重症监护室(ICU)。通过审查病历获得临床数据。此处报告的数据是截至2020年3月23日的数据。每例患者至少随访14天。 结果：我们确定了24例确认Covid-19的患者。患者的平均年龄为64岁±18岁，63%为男性，入院前7天±4天开始出现症状。最常见的症状是咳嗽和气促；50%的患者在入院时有发热，58%有糖尿病。所有患者均因低氧性呼吸衰竭入院，75%（18例）的患者需要机械通气。大部分患者(17)还出现低血压，需要血管加压素治疗。无患者的甲型流感、乙型流感或其他呼吸道病毒检测结果呈阳性。半数患者（12例）在ICU第1天至第18天期间死亡，包括4例入院时未要求复苏的患者。12例存活患者中，5例出院回家，4例离开ICU但仍在住院，3例继续在ICU接受机械通气。 结论：在西雅图地区Covid-19暴发的前3周内，入住ICU最常见的原因是导致机械通气的低氧性呼吸衰竭、需要血管加压素治疗的低血压或两者兼有。这些重症患者的死亡率较高。
Keywords: Humans; Middle Aged; Aged; Intensive Care Units; Length of Stay; Respiration, Artificial; Tomography, X-Ray Computed; Pandemics; COVID-19; SARS-CoV-2; Hospitalization; Clinical Laboratory Techniques; Radiography; Shock/etiology; COVID-19 Testing; Lung/diagnostic imaging/pathology; *Betacoronavirus/isolation & purification; Asthma/complications/drug therapy; Coronavirus Infections/complications/diagnosis/*epidemiology/mortality/*therapy; Critical Illness/*epidemiology/mortality; Glucocorticoids/adverse effects/therapeutic use; Pneumonia, Viral/complications/*epidemiology/mortality/*therapy; Respiratory Insufficiency/etiology; Washington/epidemiology

The Toughest Triage - Allocating Ventilators in a Pandemic - Truog, Robert D.; Mitchell, Christine; Daley, George Q. (The New England journal of medicine, 2020)
最有力的分类-在流行病中分配呼吸机
Keywords: Humans; COVID-19; United States/epidemiology; *Pandemics; *Ethics Committees, Clinical; Coronavirus Infections/epidemiology/*therapy; Health Care Rationing/ethics/*methods; Pneumonia, Viral/epidemiology/*therapy; Resource Allocation/ethics; Triage/ethics/*methods; Ventilators, Mechanical/*supply & distribution; Withholding Treatment/ethics

French Pandemic Resistance - Haug, Charlotte (The New England journal of medicine, 2020)
法国流行病耐药性
Keywords: Humans; COVID-19; France/epidemiology; Emergency Service, Hospital/*organization & administration; *Hospital Administration; Facility Design and Construction; Coronavirus Infections/epidemiology/prevention & control/*therapy; Pandemics/*prevention & control; Pneumonia, Viral/epidemiology/prevention & control/*therapy

Late-Onset Neonatal Sepsis in a Patient with Covid-19 - Coronado Munoz, Alvaro; Nawaratne, Upulie; McMann, David; Ellsworth, Misti; Meliones, Jon; Boukas, Konstantinos (The New England journal of medicine, 2020)
1例Covid-19患者的迟发型新生儿败血症
Keywords: Humans; Male; Positive-Pressure Respiration; Infant, Newborn; COVID-19; SARS-CoV-2; Infant, Premature; *Pandemics; Betacoronavirus/*isolation & purification; Intensive Care Units, Pediatric; *Coronavirus Infections/complications/therapy/virology; *Pneumonia, Viral/complications/therapy/virology; Hypotension/etiology; Infant, Premature, Diseases/therapy/*virology; Lung/*diagnostic imaging/pathology; Neonatal Sepsis/therapy/*virology; Pneumothorax/etiology

Ingestion of Caustic Substances - Hoffman, Robert S.; Burns, Michele M.; Gosselin, Sophie (The New England journal of medicine, 2020)
摄入腐蚀性物质
Keywords: Humans; Adult; Child; United States/epidemiology; History, 20th Century; Acids/adverse effects; Alkalies/adverse effects; Burns, Chemical/diagnosis/etiology/*therapy; Caustics/history/*poisoning; Endoscopy, Digestive System; Esophageal Perforation/chemically induced/*diagnosis; Esophageal Stenosis/*chemically induced/diagnosis/therapy; Esophagus/diagnostic imaging; Glucocorticoids/*therapeutic use; Government Regulation/history; Mitomycin/therapeutic use; Poisoning/epidemiology; Product Labeling/history/legislation & jurisprudence; Sucralfate/therapeutic use

Hospitalizations and Deaths Associated with EVALI - Werner, Angela K.; Koumans, Emilia H.; Chatham-Stephens, Kevin; Salvatore, Phillip P.; Armatas, Christina; Byers, Paul; Clark, Charles R.; Ghinai, Isaac; Holzbauer, Stacy M.; Navarette, Kristen A.; Danielson, Melissa L.; Ellington, Sascha; et al. (The New England journal of medicine, 2020)
BACKGROUND: As of January 7, 2020, a total of 2558 hospitalized patients with nonfatal cases and 60 patients with fatal cases of e-cigarette, or vaping, product use-associated lung injury (EVALI) had been reported to the Centers for Disease Control and Prevention (CDC). METHODS: In a national study, we compared the characteristics of patients with fatal cases of EVALI with those of patients with nonfatal cases to improve the ability of clinicians to identify patients at increased risk for death from the condition. Health departments reported cases of EVALI to the CDC and included, when available, data from medical-record abstractions and patient interviews. Analyses included all the patients with fatal or nonfatal cases of EVALI that were reported to the CDC as of January 7, 2020. We also present three case reports of patients who died from EVALI to illustrate the clinical characteristics common among such patients. RESULTS: Most of the patients with fatal or nonfatal cases of EVALI were male (32 of 60 [53%] and 1666 of 2498 [67%], respectively). The proportion of patients with fatal or nonfatal cases was higher among those who were non-Hispanic white (39 of 49 [80%] and 1104 of 1818 [61%], respectively) than among those in other race or ethnic groups. The proportion of patients with fatal cases was higher among those 35 years of age or older (44 of 60 [73%]) than among those younger than 35 years, but the proportion with nonfatal cases was lower among those 35 years of age or older (551 of 2514 [22%]). Among the patients who had an available medical history, a higher proportion of those with fatal cases than those with nonfatal cases had a history of asthma (13 of 57 [23%] vs. 102 of 1297 [8%]), cardiac disease (26 of 55 [47%] vs. 115 of 1169 [10%]), or a mental health condition (32 of 49 [65%] vs. 575 of 1398 [41%]). A total of 26 of 50 patients (52%) with fatal cases had obesity. Half the patients with fatal cases (25 of 54 [46%]) were seen in an outpatient setting before hospitalization or death. CONCLUSIONS: Chronic conditions, including cardiac and respiratory diseases and mental health conditions, were common among hospitalized patients with EVALI.
与EVALI相关的住院和死亡 背景：截至2020年1月7日，向疾病控制与预防中心(CDC)报告了共计2558例非致死性住院患者和60例产品使用相关的电子香烟或蒸汽肺损伤(EVALI)致死性病例。 方法：在一项国家研究中，我们比较了EVALI死亡病例患者与非死亡病例患者的特征，以提高临床医生识别该疾病死亡风险增加患者的能力。卫生部门向CDC报告了EVALI病例，并在可用时纳入来自病历摘录和患者访谈的数据。分析包括截至2020年1月7日向CDC报告的所有发生EVALI致死性或非致死性病例的患者。我们还介绍了3例EVALI死亡患者的病例报告，以说明此类患者的常见临床特征。 结果：大部分发生EVALI致死性或非致死性病例的患者为男性（分别为32/60[53%]和1666/2498[67%]）。非西班牙裔白人中发生致死性或非致死性病例的患者比例（分别为39/49[80%]和1104/1818[61%]）高于其他人种或种族组。≥35岁人群中发生致死性病例的患者比例（44/60例[73%]）高于 < 35岁人群，但≥35岁人群中发生非致死性病例的患者比例较低（551/2514例[22%]）。在有可用病史的患者中，有致死性病例的患者中有哮喘病史（57例中的13例[23%]与1297例中的102例[8%]）、心脏病史（55例中的26例[47%]与1169例中的115例[10%]）的患者比例高于有非致死性病例的患者，或精神健康状况(32/49[65%]vs. 575/1398[41%])。50例致死性病例中，共有26例(52%)患者肥胖。有一半致死性病例的患者（54例中的25例[46%]）在住院或死亡前在门诊就诊。 结论：在EVALI住院患者中，慢性疾病，包括心脏和呼吸系统疾病以及精神健康状况很常见。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Young Adult; Adolescent; Comorbidity; United States/epidemiology; Overweight/epidemiology; Patient Acuity; *Electronic Nicotine Delivery Systems; Asthma/epidemiology; Dronabinol/adverse effects; Heart Diseases/epidemiology; Hospitalization/*statistics & numerical data; Lung Injury/complications/epidemiology/*mortality; Mental Disorders/epidemiology; Vaping/*adverse effects

Case 12-2020: A 24-Year-Old Man with Fever, Cough, and Dyspnea - Barros, Nicolas; McDermott, Shaunagh; Wong, Alexandra K.; Turbett, Sarah E. (The New England journal of medicine, 2020)
病例12-2020：一名24岁的发热、咳嗽和呼吸困难男性
Keywords: Humans; Male; Young Adult; Diagnosis, Differential; Animals; Tomography, X-Ray Computed; Mice; Leukocyte Count; Bronchoscopy; Lung/diagnostic imaging/pathology; Antibodies, Viral/blood; Bites and Stings/*complications; Cough/etiology; Dyspnea/*etiology; Fever/etiology; Hantavirus Pulmonary Syndrome/complications/*diagnosis/transmission; Leukocytosis/diagnosis/etiology; Peromyscus; Pneumonia/diagnosis; Sin Nombre virus/immunology/*isolation & purification; Thrombocytopenia/diagnosis/etiology; Vaping/adverse effects

An Animal Model of Inhaled Vitamin E Acetate and EVALI-like Lung Injury - Bhat, Tariq A.; Kalathil, Suresh G.; Bogner, Paul N.; Blount, Benjamin C.; Goniewicz, Maciej L.; Thanavala, Yasmin M. (The New England journal of medicine, 2020)
吸入维生素E醋酸酯和EVALI样肺损伤动物模型
Keywords: Animals; *Disease Models, Animal; Mice; Aerosols; Vaping/*adverse effects; Acetates; Bronchoalveolar Lavage Fluid/chemistry; Electronic Nicotine Delivery Systems; Leukocyte Common Antigens/analysis; Leukocytes; Lung Injury/*etiology; Lung/*chemistry/drug effects/pathology; Vitamin E/*adverse effects/analysis

Calming Down about Sedation in Critically Ill Patients - GuÃ©rin, Claude (The New England journal of medicine, 2020)
缓解危重患者的镇静状况
Keywords: Humans; Hypnotics and Sedatives; *Critical Illness; *Respiration, Artificial; Conscious Sedation

Nonsedation or Light Sedation in Critically Ill, Mechanically Ventilated Patients - Olsen, Hanne T.; Nedergaard, Helene K.; Strøm, Thomas; Oxlund, Jakob; Wian, Karl-Andre; Ytrebø, Lars M.; Kroken, Bjørn A.; Chew, Michelle; Korkmaz, Serkan; Lauridsen, Jørgen T.; Toft, Palle (The New England journal of medicine, 2020)
BACKGROUND: In critically ill, mechanically ventilated patients, daily interruption of sedation has been shown to reduce the time on ventilation and the length of stay in the intensive care unit (ICU). Data on whether a plan of no sedation, as compared with a plan of light sedation, has an effect on mortality are lacking. METHODS: In a multicenter, randomized, controlled trial, we assigned, in a 1:1 ratio, mechanically ventilated ICU patients to a plan of no sedation (nonsedation group) or to a plan of light sedation (i.e., to a level at which the patient was arousable, defined as a score of -2 to -3 on the Richmond Agitation and Sedation Scale [RASS], on which scores range from -5 [unresponsive] to +4 [combative]) (sedation group) with daily interruption. The primary outcome was mortality at 90 days. Secondary outcomes were the number of major thromboembolic events, the number of days free from coma or delirium, acute kidney injury according to severity, the number of ICU-free days, and the number of ventilator-free days. Between-group differences were calculated as the value in the nonsedation group minus the value in the sedation group. RESULTS: A total of 710 patients underwent randomization, and 700 were included in the modified intention-to-treat analysis. The characteristics of the patients at baseline were similar in the two trial groups, except for the score on the Acute Physiology and Chronic Health Evaluation (APACHE) II, which was 1 point higher in the nonsedation group than in the sedation group, indicating a greater chance of in-hospital death. The mean RASS score in the nonsedation group increased from -1.3 on day 1 to -0.8 on day 7 and, in the sedation group, from -2.3 on day 1 to -1.8 on day 7. Mortality at 90 days was 42.4% in the nonsedation group and 37.0% in the sedated group (difference, 5.4 percentage points; 95% confidence interval [CI], -2.2 to 12.2; P = 0.65). The number of ICU-free days and of ventilator-free days did not differ significantly between the trial groups. The patients in the nonsedation group had a median of 27 days free from coma or delirium, and those in the sedation group had a median of 26 days free from coma or delirium. A major thromboembolic event occurred in 1 patient (0.3%) in the nonsedation group and in 10 patients (2.8%) in the sedation group (difference, -2.5 percentage points; 95% CI, -4.8 to -0.7 [unadjusted for multiple comparisons]). CONCLUSIONS: Among mechanically ventilated ICU patients, mortality at 90 days did not differ significantly between those assigned to a plan of no sedation and those assigned to a plan of light sedation with daily interruption.
机械通气的危重患者中的非镇静或轻度镇静 背景：在重症机械通气患者中，已证实每日中断镇静可减少通气时间和重症监护室(ICU)住院时间。与轻度镇静计划相比，无镇静计划是否对死亡率有影响的数据缺乏。 方法：在一项多中心、随机、对照试验中，我们以1:1的比例，将机械通气ICU患者分配至无镇静计划（无镇静组）或轻度镇静计划（即，患者苏醒时的水平，定义为Richmond躁动和镇静量表[RASS]评分为-2至-3分，评分范围为-5[无应答]至 + 4[好斗]（镇静组），每日中断。主要结局为90天时的死亡率。次要结局是重大血栓栓塞事件的数量、无昏迷或谵妄的天数、根据严重程度的急性肾损伤、无ICU的天数和无呼吸机的天数。组间差异计算为非镇静组值减去镇静组值。 结果：共有710例患者接受随机分组，700例纳入改良的意向治疗分析。两个试验组的患者基线特征相似，但急性生理学和慢性健康状况(APACHE)II评分除外，非镇静组比镇静组高1分，表明住院期间死亡的几率更大。非镇静组的平均RASS评分从 -第1天1.3至第7天-0.8，镇静组从第1天-2.3至 -第7天为1.8。90天时非镇静组的死亡率为42.4%，镇静组为37.0%（差异，5.4个百分点；95%置信区间[CI]，-2.2至12.2；P = 0.65）。试验组间无ICU天数和无呼吸机天数无显著差异。非镇静组患者的昏迷或谵妄中位时间为27天，镇静组患者的昏迷或谵妄中位时间为26天。非镇静组1例患者(0.3%)和镇静组10例患者(2.8%)发生重大血栓栓塞事件（差异，-2.5个百分点；95%CI，-4.8至-0.7[未校正多重比较]）。 结论：在机械通气的ICU患者中，90天时的死亡率在无镇静计划组和每日中断轻度镇静计划组之间无显著差异。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Length of Stay; Aged, 80 and over; Infusions, Intravenous; Kaplan-Meier Estimate; Intention to Treat Analysis; Critical Illness/mortality/*therapy; *Conscious Sedation/methods; *Respiration, Artificial/adverse effects; Coma/complications; Delirium/complications; Hypnotics and Sedatives/*administration & dosage; Midazolam/administration & dosage; Propofol/administration & dosage; Thromboembolism/etiology

Oxygen Therapy for the Critically Ill - Angus, Derek C. (The New England journal of medicine, 2020)
危重病患者的氧疗
Keywords: Humans; Intensive Care Units; Respiration, Artificial; Oxygen Inhalation Therapy; *Critical Illness; *Oxygen

Liberal or Conservative Oxygen Therapy for Acute Respiratory Distress Syndrome - Barrot, Loic; Asfar, Pierre; Mauny, Frederic; Winiszewski, Hadrien; Montini, Florent; Badie, Julio; Quenot, Jean-Pierre; Pili-Floury, Sebastien; Bouhemad, Belaid; Louis, Guillaume; Souweine, Bertrand; Collange, Olivier; et al. (The New England journal of medicine, 2020)
BACKGROUND: In patients with acute respiratory distress syndrome (ARDS), the National Heart, Lung, and Blood Institute ARDS Clinical Trials Network recommends a target partial pressure of arterial oxygen (Pao(2)) between 55 and 80 mm Hg. Prospective validation of this range in patients with ARDS is lacking. We hypothesized that targeting the lower limit of this range would improve outcomes in patients with ARDS. METHODS: In this multicenter, randomized trial, we assigned patients with ARDS to receive either conservative oxygen therapy (target Pao(2), 55 to 70 mm Hg; oxygen saturation as measured by pulse oximetry [Spo(2)], 88 to 92%) or liberal oxygen therapy (target Pao(2), 90 to 105 mm Hg; Spo(2), â‰¥96%) for 7 days. The same mechanical-ventilation strategies were used in both groups. The primary outcome was death from any cause at 28 days. RESULTS: After the enrollment of 205 patients, the trial was prematurely stopped by the data and safety monitoring board because of safety concerns and a low likelihood of a significant difference between the two groups in the primary outcome. Four patients who did not meet the eligibility criteria were excluded. At day 28, a total of 34 of 99 patients (34.3%) in the conservative-oxygen group and 27 of 102 patients (26.5%) in the liberal-oxygen group had died (difference, 7.8 percentage points; 95% confidence interval [CI], -4.8 to 20.6). At day 90, 44.4% of the patients in the conservative-oxygen group and 30.4% of the patients in the liberal-oxygen group had died (difference, 14.0 percentage points; 95% CI, 0.7 to 27.2). Five mesenteric ischemic events occurred in the conservative-oxygen group. CONCLUSIONS: Among patients with ARDS, early exposure to a conservative-oxygenation strategy with a Pao(2) between 55 and 70 mm Hg did not increase survival at 28 days. ClinicalTrials.gov number, NCT02713451.).
急性呼吸窘迫综合征的开放或保守氧疗 背景：在急性呼吸窘迫综合征(ARDS)患者中，美国国家心肺血液研究所ARDS临床试验网络推荐的目标动脉血氧分压(Pao(2))为55-80 mmHg。尚缺乏在ARDS患者中对该范围的前瞻性验证。我们假设以这个范围的下限为目标将改善ARDS患者的预后。 方法：在这项多中心、随机试验中，我们将ARDS患者分配接受保守氧疗（目标pao2，55-70 mmHg；通过脉搏血氧仪[spo2]测量的氧饱和度，88-92%）或自由氧疗（目标pao2，90-105 mmHg；spo2，â‰¥96%），持续7天。两组均采用相同的机械通气策略。主要结局为第28天因任何原因死亡。 结果：205例患者入组后，由于安全性问题和两组主要结局存在显著差异的可能性较低，数据和安全性监查委员会提前终止试验。排除了4例不符合合格性标准的患者。第28天时，保守氧疗组99例患者中的34例(34.3%)和自由氧疗组102例患者中的27例(26.5%)死亡（差异，7.8个百分点；95%置信区间[CI]，-4.8至20.6）。第90天，保守氧疗组44.4%的患者和游离氧疗组30.4%的患者死亡（差异，14.0个百分点；95%CI，0.7-27.2）。5例肠系膜缺血事件发生在保守氧疗组。 结论：ARDS患者中，Pao(2)55-70 mmHg时早期接受保守氧合策略未增加28天生存率。ClinicalTrials.gov编号，NCT02713451）。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Time Factors; Survival Analysis; Aged; Adult; *Respiratory Distress Syndrome/therapy; *Oxygen Inhalation Therapy/methods; *Respiration, Artificial/methods; Conservative Treatment; Oxygen/administration & dosage/blood

Conservative Oxygen Therapy during Mechanical Ventilation in the ICU - Mackle, Diane; Bellomo, Rinaldo; Bailey, Michael; Beasley, Richard; Deane, Adam; Eastwood, Glenn; Finfer, Simon; Freebairn, Ross; King, Victoria; Linke, Natalie; Litton, Edward; McArthur, Colin; et al. (The New England journal of medicine, 2020)
BACKGROUND: Patients who are undergoing mechanical ventilation in the intensive care unit (ICU) often receive a high fraction of inspired oxygen (Fio(2)) and have a high arterial oxygen tension. The conservative use of oxygen may reduce oxygen exposure, diminish lung and systemic oxidative injury, and thereby increase the number of ventilator-free days (days alive and free from mechanical ventilation). METHODS: We randomly assigned 1000 adult patients who were anticipated to require mechanical ventilation beyond the day after recruitment in the ICU to receive conservative or usual oxygen therapy. In the two groups, the default lower limit for oxygen saturation as measured by pulse oximetry (Spo(2)) was 90%. In the conservative-oxygen group, the upper limit of the Spo(2) alarm was set to sound when the level reached 97%, and the Fio(2) was decreased to 0.21 if the Spo(2) was above the acceptable lower limit. In the usual-oxygen group, there were no specific measures limiting the Fio(2) or the Spo(2). The primary outcome was the number of ventilator-free days from randomization until day 28. RESULTS: The number of ventilator-free days did not differ significantly between the conservative-oxygen group and the usual-oxygen group, with a median duration of 21.3 days (interquartile range, 0 to 26.3) and 22.1 days (interquartile range, 0 to 26.2), respectively, for an absolute difference of -0.3 days (95% confidence interval [CI], -2.1 to 1.6; P = 0.80). The conservative-oxygen group spent more time in the ICU with an Fio(2) of 0.21 than the usual-oxygen group, with a median duration of 29 hours (interquartile range, 5 to 78) and 1 hour (interquartile range, 0 to 17), respectively (absolute difference, 28 hours; 95% CI, 22 to 34); the conservative-oxygen group spent less time with an Spo(2) exceeding 96%, with a duration of 27 hours (interquartile range, 11 to 63.5) and 49 hours (interquartile range, 22 to 112), respectively (absolute difference, 22 hours; 95% CI, 14 to 30). At 180 days, mortality was 35.7% in the conservative-oxygen group and 34.5% in the usual-oxygen group, for an unadjusted odds ratio of 1.05 (95% CI, 0.81 to 1.37). CONCLUSIONS: In adults undergoing mechanical ventilation in the ICU, the use of conservative oxygen therapy, as compared with usual oxygen therapy, did not significantly affect the number of ventilator-free days.
ICU机械通气期间的保守氧疗 背景：在重症监护室(ICU)接受机械通气的患者经常接受高分数的吸入氧(Fio(2))，并且动脉血氧分压较高。保守使用氧气可减少氧气暴露，减少肺和全身氧化损伤，从而增加无呼吸机使用天数（存活天数和无机械通气天数）。 方法：我们随机分配了1000例预期在ICU招募后次日需要机械通气的成人患者接受保守或常规氧疗。在两组中，通过脉搏血氧测定法(Spo(2))测得的氧饱和度的默认下限为90%。在保守氧疗组，Spo(2)报警的上限设定为当水平达到97%时发出警报，如果Spo(2)高于可接受的下限，Fio(2)降低至0.21。在常规氧气组中，没有限制Fio(2)或Spo(2)的特定措施。主要结局是从随机分组至第28天无呼吸机通气的天数。 结果：保守氧疗组和常规氧疗组的无呼吸机使用天数无显著差异，中位持续时间分别为21.3天（四分位距，0-26.3）和22.1天（四分位距，0-26.2），绝对差异为-0.3天（95%置信区间[CI]，-2.1至1.6；P = 0.80）。保守氧疗组在ICU的Fio(2)为0.21的时间比常规氧疗组更长，中位持续时间分别为29小时（四分位距，5-78）和1小时（四分位距，0-17）（绝对差异，28小时；95%CI，22-34）；保守氧疗组Spo(2)超过96%的时间较短，持续时间为27小时（四分位距，11-63.5）和49小时（四分位距：22-112）（绝对差：22小时；95%CI：14-30）。在180天时，保守氧疗组的死亡率为35.7%，常规氧疗组的死亡率为34.5%，未校正的比值比为1.05(95%CI，0.81-1.37)。 结论：在ICU接受机械通气的成人中，与常规氧疗相比，使用保守氧疗并未显著影响无呼吸机治疗的天数。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Aged; Intensive Care Units; Adult; *Respiration, Artificial; Ventilator Weaning; *Oxygen Inhalation Therapy/methods; Conservative Treatment; Oxygen/administration & dosage

Pulmonary Illness Related to E-Cigarette Use in Illinois and Wisconsin - Final Report - Layden, Jennifer E.; Ghinai, Isaac; Pray, Ian; Kimball, Anne; Layer, Mark; Tenforde, Mark W.; Navon, Livia; Hoots, Brooke; Salvatore, Phillip P.; Elderbrook, Megan; Haupt, Thomas; Kanne, Jeffrey; et al. (The New England journal of medicine, 2020)
BACKGROUND: E-cigarettes are battery-operated devices that heat a liquid and deliver an aerosolized product to the user. Pulmonary illnesses related to e-cigarette use have been reported, but no large series has been described. In July 2019, the Wisconsin Department of Health Services and the Illinois Department of Public Health received reports of lung injury associated with the use of e-cigarettes (also called vaping) and launched a coordinated public health investigation. METHODS: We defined case patients as persons who reported use of e-cigarette devices and related products in the 90 days before symptom onset and had pulmonary infiltrates on imaging and whose illnesses were not attributed to other causes. Medical record abstraction and case patient interviews were conducted with the use of standardized tools. RESULTS: There were 98 case patients, 79% of whom were male; the median age of the patients was 21 years. The majority of patients presented with respiratory symptoms (97%), gastrointestinal symptoms (77%), and constitutional symptoms (100%). All case patients had bilateral infiltrates on chest imaging. A total of 95% of the patients were hospitalized, 26% underwent intubation and mechanical ventilation, and two deaths were reported. A total of 89% of the patients reported having used tetrahydrocannabinol products in e-cigarette devices, although a wide variety of products and devices was reported. Syndromic surveillance data from Illinois showed that the mean monthly rate of visits related to severe respiratory illness in June through August of 2019 was twice the rate that was observed in the same months in 2018. CONCLUSIONS: Case patients presented with similar clinical characteristics. Although the definitive substance or substances contributing to injury have not been determined, this initial cluster of illnesses represents an emerging clinical syndrome or syndromes. Additional work is needed to characterize the pathophysiology and to identify the definitive causes.
伊利诺斯州和威斯康星州与电子香烟使用相关的肺部疾病-最终报告 背景：电子烟是一种电池驱动的装置，可加热液体并将雾化产品提供给用户。报告了与电子烟使用相关的肺部疾病，但尚未描述大型系列。2019年7月，威斯康辛州卫生服务部和伊利诺伊州公共卫生部收到与使用电子烟（也称为挥发烟）相关的肺损伤报告，并启动了一项协调的公共卫生调查。 方法：我们将病例患者定义为报告在症状发作前90天内使用电子香烟装置和相关产品，影像学检查发现肺部浸润，且疾病未归因于其他原因的患者。使用标准化工具进行病历摘录和病例患者访谈。 结果：98例病例患者，其中79%为男性；患者的中位年龄为21岁。大多数患者表现为呼吸道症状(97%)、胃肠道症状(77%)和全身症状(100%)。所有病例患者的胸部成像均显示双侧浸润。共95%的患者住院，26%接受插管和机械通气，报告了2例死亡。共有89%的患者报告在电子烟装置中使用过四氢大麻酚产品，但报告的产品和装置种类繁多。来自伊利诺伊州的综合征监测数据显示，2019年6月至8月，与重度呼吸系统疾病相关的每月平均就诊率是2018年相同月份观察到的2倍。 结论：病例患者表现出相似的临床特征。虽然尚未确定导致损伤的明确物质或物质，但这种初始疾病集群代表一种新出现的临床综合征。需要额外的工作来描述病理生理学，并确定明确的原因。
Keywords: Humans; Female; Male; Middle Aged; Adult; Young Adult; Adolescent; Hospitalization; Population Surveillance; Disease Outbreaks; Illinois/epidemiology; Lung/diagnostic imaging/pathology; Radiography, Thoracic; *Electronic Nicotine Delivery Systems; Dronabinol/adverse effects; Vaping/*adverse effects; Leukocytosis/etiology; Lung Injury/*epidemiology/etiology/mortality/pathology; Wisconsin/epidemiology

Vaping-Induced Acute Lung Injury - Christiani, David C. (The New England journal of medicine, 2020)
蒸气诱导的急性肺损伤
Keywords: Humans; *Acute Lung Injury; *Electronic Nicotine Delivery Systems; *Vaping; Illinois; Wisconsin

Cornering the Suspects in Vaping-Associated EVALI - Gordon, Terry; Fine, Jonathan (The New England journal of medicine, 2020)
帮助怀疑与蒸汽相关的EVALI
Keywords: Humans; *Electronic Nicotine Delivery Systems; Acetates; *Vaping; Therapeutic Irrigation; Vitamin E

Vitamin E Acetate in Bronchoalveolar-Lavage Fluid Associated with EVALI - Blount, Benjamin C.; Karwowski, Mateusz P.; Shields, Peter G.; Morel-Espinosa, Maria; Valentin-Blasini, Liza; Gardner, Michael; Braselton, Martha; Brosius, Christina R.; Caron, Kevin T.; Chambers, David; Corstvet, Joseph; Cowan, Elizabeth; et al. (The New England journal of medicine, 2020)
BACKGROUND: The causative agents for the current national outbreak of electronic-cigarette, or vaping, product use-associated lung injury (EVALI) have not been established. Detection of toxicants in bronchoalveolar-lavage (BAL) fluid from patients with EVALI can provide direct information on exposure within the lung. METHODS: BAL fluids were collected from 51 patients with EVALI in 16 states and from 99 healthy participants who were part of an ongoing study of smoking involving nonsmokers, exclusive users of e-cigarettes or vaping products, and exclusive cigarette smokers that was initiated in 2015. Using the BAL fluid, we performed isotope dilution mass spectrometry to measure several priority toxicants: vitamin E acetate, plant oils, medium-chain triglyceride oil, coconut oil, petroleum distillates, and diluent terpenes. RESULTS: State and local health departments assigned EVALI case status as confirmed for 25 patients and as probable for 26 patients. Vitamin E acetate was identified in BAL fluid obtained from 48 of 51 case patients (94%) in 16 states but not in such fluid obtained from the healthy comparator group. No other priority toxicants were found in BAL fluid from the case patients or the comparator group, except for coconut oil and limonene, which were found in 1 patient each. Among the case patients for whom laboratory or epidemiologic data were available, 47 of 50 (94%) had detectable tetrahydrocannabinol (THC) or its metabolites in BAL fluid or had reported vaping THC products in the 90 days before the onset of illness. Nicotine or its metabolites were detected in 30 of 47 of the case patients (64%). CONCLUSIONS: Vitamin E acetate was associated with EVALI in a convenience sample of 51 patients in 16 states across the United States.
与EVALI相关的支气管肺泡灌洗液中的维生素E醋酸酯 背景：目前全国电子香烟或蒸汽产品使用相关肺损伤(EVALI)爆发的病原体尚未确定。检测EVALI患者的支气管肺泡灌洗(BAL)液中的毒物可提供肺内暴露的直接信息。 方法：采集了来自16个州的51例EVALI患者和99例健康受试者的BAL液体，这些受试者参与了一项正在进行的吸烟研究，包括非吸烟者、电子香烟或挥发产品的排他性使用者和2015年开始的排他性吸烟者。使用BAL液，我们进行了同位素稀释质谱法，以测定几种优先毒物：维生素E醋酸盐、植物油、中链甘油三酯油、椰子油、石油馏分和稀释萜。 结果：州和当地卫生部门将25例患者确定为EVALI病例状态，26例患者确定为可能EVALI病例状态。51例患者中48例(94%)在16个州的BAL液中鉴定出维生素E醋酸盐，而健康对照组的BAL液中未鉴定出维生素E醋酸盐。在病例患者或对照组的BAL液中未发现其他优先毒物，除了椰子油和柠檬烯各在1例患者中发现。在可获得实验室或流行病学数据的病例患者中，50例患者中的47例(94%)在BAL液中可检测到四氢大麻酚(THC)或其代谢物，或在发病前90天内报告了挥发性THC产品。47例病例患者中有30例(64%)检出尼古丁或其代谢产物。 结论：在美国16个州51名患者的便利抽样中，维生素E醋酸盐与EVALI相关。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Young Adult; Adolescent; United States; *Electronic Nicotine Delivery Systems; Vaping/*adverse effects; Acute Lung Injury/etiology/*pathology; Bronchoalveolar Lavage Fluid/*chemistry; Cigarette Smoking; Coconut Oil/analysis; Limonene/analysis; Vitamin E/*analysis

Longer-Term Outcomes of the ProACT Trial - Huang, David T.; Yealy, Donald M.; Angus, Derek C. (The New England journal of medicine, 2020)
ProACT试验的长期结局
Keywords: Humans; Kaplan-Meier Estimate; Biomarkers/blood; *Practice Guidelines as Topic; Anti-Bacterial Agents/*therapeutic use; Bacterial Infections/drug therapy; Practice Patterns, Physicians'; Procalcitonin/*blood; Respiratory Tract Infections/*drug therapy/mortality

Risk Prediction for Acute Kidney Injury - Super Important, Now suPAR Easy? - Tacke, Frank (The New England journal of medicine, 2020)
急性肾损伤的风险预测-非常重要，现在suPAR是否容易？
Keywords: Humans; *Acute Kidney Injury; *Urokinase-Type Plasminogen Activator; Receptors, Urokinase Plasminogen Activator

Clearing the Air - A Conservative Option for Spontaneous Pneumothorax - Broaddus, V. Courtney (The New England journal of medicine, 2020)
清理空气——自发性气胸的保守治疗选择
Keywords: Humans; *Pneumothorax; Pleurodesis

A Rapid Change in Pressure - D'Silva, Kristin; Vaidya, Anand; Smithy, James W.; Anderson, William J.; Cockrill, Barbara (The New England journal of medicine, 2020)
压力的快速变化
Keywords: Humans; Female; Aged; Palliative Care; Positron Emission Tomography Computed Tomography; Cardiac Catheterization; Echocardiography; Stroke Volume; Weight Loss; Computed Tomography Angiography; Lung/diagnostic imaging; Electrocardiography; Pulmonary Wedge Pressure; Fatal Outcome; Cough/etiology; Dyspnea/*etiology; Fatigue/etiology; Hypertension, Pulmonary/classification/*diagnosis/etiology; Tachycardia, Sinus/diagnosis; Ventricular Dysfunction, Right/*diagnostic imaging/etiology

Soluble Urokinase Receptor and Acute Kidney Injury - Hayek, Salim S.; Leaf, David E.; Samman Tahhan, Ayman; Raad, Mohamad; Sharma, Shreyak; Waikar, Sushrut S.; Sever, Sanja; Camacho, Alex; Wang, Xuexiang; Dande, Ranadheer R.; Ibrahim, Nasrien E.; Baron, Rebecca M.; et al. (The New England journal of medicine, 2020)
BACKGROUND: Acute kidney injury is common, with a major effect on morbidity and health care utilization. Soluble urokinase plasminogen activator receptor (suPAR) is a signaling glycoprotein thought to be involved in the pathogenesis of kidney disease. We investigated whether a high level of suPAR predisposed patients to acute kidney injury in multiple clinical contexts, and we used experimental models to identify mechanisms by which suPAR acts and to assess it as a therapeutic target. METHODS: We measured plasma levels of suPAR preprocedurally in patients who underwent coronary angiography and patients who underwent cardiac surgery and at the time of admission to the intensive care unit in critically ill patients. We assessed the risk of acute kidney injury at 7 days as the primary outcome and acute kidney injury or death at 90 days as a secondary outcome, according to quartile of suPAR level. In experimental studies, we used a monoclonal antibody to urokinase plasminogen activator receptor (uPAR) as a therapeutic strategy to attenuate acute kidney injury in transgenic mice receiving contrast material. We also assessed cellular bioenergetics and generation of reactive oxygen species in human kidney proximal tubular (HK-2) cells that were exposed to recombinant suPAR. RESULTS: The suPAR level was assessed in 3827 patients who were undergoing coronary angiography, 250 who were undergoing cardiac surgery, and 692 who were critically ill. Acute kidney injury developed in 318 patients (8%) who had undergone coronary angiography. The highest suPAR quartile (vs. the lowest) had an adjusted odds ratio of 2.66 (95% confidence interval [CI], 1.77 to 3.99) for acute kidney injury and 2.29 (95% CI, 1.71 to 3.06) for acute kidney injury or death at 90 days. Findings were similar in the surgical and critically ill cohorts. The suPAR-overexpressing mice that were given contrast material had greater functional and histologic evidence of acute kidney injury than wild-type mice. The suPAR-treated HK-2 cells showed heightened energetic demand and mitochondrial superoxide generation. Pretreatment with a uPAR monoclonal antibody attenuated kidney injury in suPAR-overexpressing mice and normalized bioenergetic changes in HK-2 cells. CONCLUSIONS: High suPAR levels were associated with acute kidney injury in various clinical and experimental contexts.
可溶性尿激酶受体与急性肾损伤 背景：急性肾损伤很常见，主要影响发病率和医疗保健利用。可溶性尿激酶纤溶酶原激活物受体(suPAR)是一种信号糖蛋白，被认为参与了肾病的发病机制。我们研究了在多种临床背景下高水平的suPAR是否使患者容易发生急性肾损伤，并使用实验模型来确定suPAR的作用机制，并将其作为治疗靶点进行评估。 方法：我们测定了行冠状动脉造影的患者和行心脏手术的患者术前以及重症患者入住重症监护室时的血浆suPAR水平。根据suPAR水平的四分位数，我们评估了7天时急性肾损伤的风险作为主要结局，90天时急性肾损伤或死亡作为次要结局。在实验研究中，我们使用尿激酶纤溶酶原激活物受体的单克隆抗体(uPAR)作为减轻接受造影剂的转基因小鼠急性肾损伤的治疗策略。我们还评估了暴露于重组suPAR的人近端肾小管(HK-2)细胞的细胞生物能量学和活性氧的产生。 结果：在3827例接受冠状动脉造影术的患者、250例接受心脏手术的患者和692例危重患者中评估了suPAR水平。318例(8%)接受冠状动脉造影术的患者发生了急性肾损伤。90天时，suPAR四分位数最高（与最低相比）急性肾损伤的校正比值比为2.66（95%置信区间[CI]，1.77-3.99），急性肾损伤或死亡的校正比值比为2.29(95%CI，1.71-3.06)。手术和重症队列的结果相似。与野生型小鼠相比，给予造影剂的suPAR过度表达小鼠有更大的急性肾损伤功能和组织学证据。经suPAR处理的HK-2细胞表现出更高的能量需求和线粒体超氧阴离子的产生。uPAR单克隆抗体预处理减轻了suPAR过度表达小鼠的肾损伤，并使HK-2细胞的生物能量变化恢复正常。 结论：在各种临床和实验背景下，高suPAR水平与急性肾损伤相关。
Keywords: Humans; Female; Male; Middle Aged; Aged; Critical Illness; Intensive Care Units; Animals; Disease Models, Animal; Mice, Transgenic; Mice; Risk Assessment/methods; Biomarkers/blood; Odds Ratio; Acute Kidney Injury/*blood/etiology/prevention & control; Antibodies, Monoclonal/pharmacology/therapeutic use; Cardiac Surgical Procedures/*adverse effects; Coronary Angiography/*adverse effects; Kidney Tubules/cytology/drug effects/pathology; Podocytes/drug effects/metabolism; Postoperative Complications/blood/etiology; Receptors, Urokinase Plasminogen Activator/*blood; Urokinase-Type Plasminogen Activator/*antagonists & inhibitors/pharmacology

Conservative versus Interventional Treatment for Spontaneous Pneumothorax - Brown, Simon G. A.; Ball, Emma L.; Perrin, Kyle; Asha, Stephen E.; Braithwaite, Irene; Egerton-Warburton, Diana; Jones, Peter G.; Keijzers, Gerben; Kinnear, Frances B.; Kwan, Ben C. H.; Lam, K. V.; Lee, Y. C. Gary; et al. (The New England journal of medicine, 2020)
BACKGROUND: Whether conservative management is an acceptable alternative to interventional management for uncomplicated, moderate-to-large primary spontaneous pneumothorax is unknown. METHODS: In this open-label, multicenter, noninferiority trial, we recruited patients 14 to 50 years of age with a first-known, unilateral, moderate-to-large primary spontaneous pneumothorax. Patients were randomly assigned to immediate interventional management of the pneumothorax (intervention group) or a conservative observational approach (conservative-management group) and were followed for 12 months. The primary outcome was lung reexpansion within 8 weeks. RESULTS: A total of 316 patients underwent randomization (154 patients to the intervention group and 162 to the conservative-management group). In the conservative-management group, 25 patients (15.4%) underwent interventions to manage the pneumothorax, for reasons prespecified in the protocol, and 137 (84.6%) did not undergo interventions. In a complete-case analysis in which data were not available for 23 patients in the intervention group and 37 in the conservative-management group, reexpansion within 8 weeks occurred in 129 of 131 patients (98.5%) with interventional management and in 118 of 125 (94.4%) with conservative management (risk difference, -4.1 percentage points; 95% confidence interval [CI], -8.6 to 0.5; P = 0.02 for noninferiority); the lower boundary of the 95% confidence interval was within the prespecified noninferiority margin of -9 percentage points. In a sensitivity analysis in which all missing data after 56 days were imputed as treatment failure (with reexpansion in 129 of 138 patients [93.5%] in the intervention group and in 118 of 143 [82.5%] in the conservative-management group), the risk difference of -11.0 percentage points (95% CI, -18.4 to -3.5) was outside the prespecified noninferiority margin. Conservative management resulted in a lower risk of serious adverse events or pneumothorax recurrence than interventional management. CONCLUSIONS: Although the primary outcome was not statistically robust to conservative assumptions about missing data, the trial provides modest evidence that conservative management of primary spontaneous pneumothorax was noninferior to interventional management, with a lower risk of serious adverse events.
自发性气胸的保守与介入治疗 背景：保守治疗是否是无并发症、中-大型原发性自发性气胸介入治疗的可接受替代疗法尚不清楚。 方法：在这项开放标签、多中心、非劣效性试验中，我们招募了14至50岁的首次已知的单侧中至大型原发性自发性气胸患者。患者被随机分配立即接受气胸介入治疗（介入组）或保守观察方法（保守治疗组），并随访12个月。主要结局为8周内的肺复张。 结果：共316例患者接受随机分组（154例患者进入干预组，162例患者进入保守治疗组）。在保守治疗组中，25例患者(15.4%)因方案预先规定的原因接受了干预措施来治疗气胸，137例患者(84.6%)未接受干预措施。在一项完整病例分析中，23例介入组患者和37例保守治疗组患者的数据不可用，131例介入治疗患者中129例(98.5%)在8周内发生了再扩张，125例保守治疗患者中118例(94.4%)在8周内发生了再扩张（风险差异，-4.1个百分点；95%置信区间[CI]，-8.6至0.5；非劣效性P = 0.02）；95%置信区间的下限在预先规定的非劣效性界值-9个百分点内。在一项敏感性分析中，56天后的所有缺失数据均插补为治疗失败（干预组138例患者中129例[93.5%]进行了再扩张，保守治疗组143例患者中118例[82.5%]进行了再扩张），风险差异为-11.0个百分点（95%CI，-18.4至-3.5）超出预先规定的非劣效性界值。保守治疗的严重不良事件或气胸复发风险低于介入治疗。 结论：尽管主要结局对缺失数据的保守假设不具有统计学稳健性，但试验提供的适度证据表明，原发性自发性气胸的保守治疗不劣于干预性治疗，严重不良事件的风险更低。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Length of Stay; Recurrence; Adult; Young Adult; Adolescent; Postoperative Complications; Follow-Up Studies; Patient Readmission/statistics & numerical data; Radiography, Thoracic; *Conservative Treatment; *Drainage/methods; Chest Tubes; Pneumothorax/diagnostic imaging/*therapy; Watchful Waiting

Crepitus and Subcutaneous Emphysema - Saleh, Yehia; Alratroot, Ahmad (2020)
骨擦音和皮下气肿
Keywords: Humans; Female; Aged, 80 and over; Tomography, X-Ray Computed; Lung/diagnostic imaging; Neck/diagnostic imaging/*physiopathology; Pneumothorax/diagnostic imaging; Subcutaneous Emphysema/*diagnostic imaging

Acute Severe Hypertension - Peixoto, Aldo J. (The New England journal of medicine, 2019)
急性重度高血压
Keywords: Humans; Female; Middle Aged; Intensive Care Units; Infusions, Intravenous; Practice Guidelines as Topic; Acute Disease; Electrocardiography; Blood Pressure Determination/methods; Blood Pressure/drug effects; Antihypertensive Agents/*therapeutic use; Cerebral Hemorrhage/drug therapy/etiology; Hypertension/complications/*drug therapy; Hypertrophy, Left Ventricular/complications; Medication Adherence; Posterior Leukoencephalopathy Syndrome/drug therapy/etiology

Prevention of Early Ventilator-Associated Pneumonia after Cardiac Arrest - François, Bruno; Cariou, Alain; Clere-Jehl, Raphaël; Dequin, Pierre-François; Renon-Carron, Françoise; Daix, Thomas; Guitton, Christophe; Deye, Nicolas; Legriel, Stéphane; Plantefève, Gaëtan; Quenot, Jean-Pierre; Desachy, Arnaud; et al. (The New England journal of medicine, 2019)
BACKGROUND: Patients who are treated with targeted temperature management after out-of-hospital cardiac arrest with shockable rhythm are at increased risk for ventilator-associated pneumonia. The benefit of preventive short-term antibiotic therapy has not been shown. METHODS: We conducted a multicenter, double-blind, randomized, placebo-controlled trial involving adult patients (>18 years of age) in intensive care units (ICUs) who were being mechanically ventilated after out-of-hospital cardiac arrest related to initial shockable rhythm and treated with targeted temperature management at 32 to 34°C. Patients with ongoing antibiotic therapy, chronic colonization with multidrug-resistant bacteria, or moribund status were excluded. Either intravenous amoxicillin-clavulanate (at doses of 1 g and 200 mg, respectively) or placebo was administered three times a day for 2 days, starting less than 6 hours after the cardiac arrest. The primary outcome was early ventilator-associated pneumonia (during the first 7 days of hospitalization). An independent adjudication committee determined diagnoses of ventilator-associated pneumonia. RESULTS: A total of 198 patients underwent randomization, and 194 were included in the analysis. After adjudication, 60 cases of ventilator-associated pneumonia were confirmed, including 51 of early ventilator-associated pneumonia. The incidence of early ventilator-associated pneumonia was lower with antibiotic prophylaxis than with placebo (19 patients [19%] vs. 32 [34%]; hazard ratio, 0.53; 95% confidence interval, 0.31 to 0.92; P = 0.03). No significant differences between the antibiotic group and the control group were observed with respect to the incidence of late ventilator-associated pneumonia (4% and 5%, respectively), the number of ventilator-free days (21 days and 19 days), ICU length of stay (5 days and 8 days if patients were discharged and 7 days and 7 days if patients had died), and mortality at day 28 (41% and 37%). At day 7, no increase in resistant bacteria was identified. Serious adverse events did not differ significantly between the two groups. CONCLUSIONS: A 2-day course of antibiotic therapy with amoxicillin-clavulanate in patients receiving a 32-to-34°C targeted temperature management strategy after out-of-hospital cardiac arrest with initial shockable rhythm resulted in a lower incidence of early ventilator-associated pneumonia than placebo. No significant between-group differences were observed for other key clinical variables, such as ventilator-free days and mortality at day 28.
心脏骤停后早期呼吸机相关性肺炎的预防 背景：可电击心律的院外心脏骤停后接受针对性温度管理的患者发生呼吸机相关性肺炎的风险增加。预防性短期抗生素治疗的获益尚未显示。 方法：我们进行了一项多中心、双盲、随机、一项安慰剂对照试验，纳入重症监护室(ICU)内成年患者（> 18岁），这些患者因与初始可电击节律相关的院外心脏骤停接受机械通气，并接受32至34 ℃的目标温度管理。患者正在接受抗生素治疗，排除了多重耐药菌的慢性定植或濒死状态。从心脏骤停后不到6小时开始，每日3次静脉给予阿莫西林-克拉维酸（剂量分别为1 g和200 mg）或安慰剂，持续2天。主要结局为早期呼吸机相关性肺炎（住院前7天）。由独立裁定委员会确定呼吸机相关性肺炎的诊断。 结果：共有198例患者接受随机分组，194例纳入分析。经判定，60例呼吸机相关性肺炎得到证实，其中51例为早期呼吸机相关性肺炎。抗生素预防治疗组早期呼吸机相关性肺炎的发生率低于安慰剂组（19例患者[19%]vs. 32例[34%]；风险比0.53；95%置信区间0.31至0.92；P = 0.03）。抗生素组和对照组之间未观察到晚期呼吸机相关性肺炎发生率（分别为4%和5%）、无呼吸机使用天数（21天和19天）的显著差异。ICU住院时间（如果患者出院，5天和8天；如果患者死亡，7天和7天）和第28天死亡率（41%和37%）。第7天，未发现耐药菌增加。两组间严重不良事件无显著差异。 结论：在伴有初始可电击节律的院外心脏骤停后接受32-34 ℃目标温度管理策略的患者中，为期2天的阿莫西林-克拉维酸抗生素治疗导致早期呼吸机相关性肺炎的发生率低于安慰剂组。其他关键临床变量未观察到显著的组间差异，如无呼吸机天数和第28天死亡率。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Double-Blind Method; Aged; Intensive Care Units; Length of Stay; Adult; Ventilator Weaning; Injections, Intravenous; Amoxicillin-Potassium Clavulanate Combination/adverse effects/*therapeutic use; Anti-Bacterial Agents/adverse effects/*therapeutic use; Out-of-Hospital Cardiac Arrest/*complications/mortality; Pneumonia, Ventilator-Associated/etiology/microbiology/*prevention & control

Pathology of Vaping-Associated Lung Injury - Butt, Yasmeen M.; Smith, Maxwell L.; Tazelaar, Henry D.; Vaszar, Laszlo T.; Swanson, Karen L.; Cecchini, Matthew J.; Boland, Jennifer M.; Bois, Melanie C.; Boyum, James H.; Froemming, Adam T.; Khoor, Andras; Mira-Avendano, Isabel; et al. (The New England journal of medicine, 2019)
蒸发相关性肺损伤的病理学
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Biopsy; Vaping/*adverse effects; Electronic Nicotine Delivery Systems; Lung Diseases/etiology/*pathology; Lung/*pathology; Pneumonia/etiology/pathology

Real-Time Digital Surveillance of Vaping-Induced Pulmonary Disease - Hswen, Yulin; Brownstein, John S. (The New England journal of medicine, 2019)
蒸汽诱导肺疾病的实时数字监测
Keywords: Humans; United States/epidemiology; Vaping/*adverse effects; Electronic Nicotine Delivery Systems; Disease Outbreaks/*statistics & numerical data; Lung Diseases/*epidemiology/etiology/mortality

Case 33-2019: A 35-Year-Old Woman with Cardiopulmonary Arrest during Cesarean Section - Bernstein, Sarah N.; Cudemus-Deseda, Gaston A.; Ortiz, Vilma E.; Goodman, Annekathryn; Jassar, Arminder S. (The New England journal of medicine, 2019)
病例33-2019：一例35岁的女性在剖宫产期间发生心肺骤停
Keywords: Humans; Female; Adult; Diagnosis, Differential; Pregnancy; Cardiopulmonary Resuscitation; Cesarean Section/*adverse effects; Echocardiography, Doppler, Color; Echocardiography, Transesophageal; Embolism, Amniotic Fluid/*diagnosis; Heart Arrest/*etiology/therapy; Heart Failure/*diagnosis/etiology/therapy; Hysterectomy; Myocardial Infarction/diagnosis; Placenta Previa/surgery; Pregnancy Complications, Cardiovascular/etiology; Pulmonary Embolism/diagnosis

Pulmonary Lipid-Laden Macrophages and Vaping - Maddock, Sean D.; Cirulis, Meghan M.; Callahan, Sean J.; Keenan, Lynn M.; Pirozzi, Cheryl S.; Raman, Sanjeev M.; Aberegg, Scott K. (The New England journal of medicine, 2019)
肺脂质沉积性巨噬细胞和喘息
Keywords: Macrophages; *Electronic Nicotine Delivery Systems; *Vaping; Illinois; Wisconsin; Lipids; Macrophages, Alveolar

Imaging of Vaping-Associated Lung Disease - Henry, Travis S.; Kanne, Jeffrey P.; Kligerman, Seth J. (The New England journal of medicine, 2019)
蒸汽相关肺部疾病成像
Keywords: Humans; *Electronic Nicotine Delivery Systems; *Vaping; Illinois; Wisconsin; *Lung Diseases

Disseminated Varicella Infection - Pannu, Ashok K.; Manikandan, Gopal (The New England journal of medicine, 2019)
播散性水痘感染
Keywords: Humans; Male; Adult; Fatal Outcome; Radiography, Thoracic; Lung/*diagnostic imaging/pathology; Anemia, Aplastic/complications; Chickenpox/complications/*diagnosis; Skin/pathology

Adrenal Crisis - Rushworth, R. Louise; Torpy, David J.; Falhammar, Henrik (The New England journal of medicine, 2019)
肾上腺危象
Keywords: Humans; Adult; Child; Infusions, Intravenous; Incidence; Acute Disease; *Adrenal Insufficiency/drug therapy/etiology/physiopathology/prevention & control; Hydrocortisone/*administration & dosage; Patient Education as Topic

Immediate Transfusion and Transfusion Volume in African Children with Severe Anemia - Ingelfinger, Julie R. (The New England journal of medicine, 2019)
非洲重度贫血儿童的即刻输血和输血量
Keywords: Humans; Child; Platelet Transfusion; *Anemia; *Blood Transfusion

Case 23-2019: A 52-Year-Old Man with Fever, Cough, and Hypoxemia - Hardin, Charles C.; Malhotra, Rajeev; PetranoviÄ‡, Milena; Klassen, Sheila; Mihatov, Nino; Oakley, Derek H. (The New England journal of medicine, 2019)
Case 12-2020: A 24-year-old man with fever, cough and dyspnea
Keywords: Humans; Male; Middle Aged; Diagnosis, Differential; Echocardiography; Electrocardiography; Radiography, Thoracic; Hypoxia/etiology; Lung/diagnostic imaging/*pathology; Cough/etiology; Fever/etiology; Tachycardia, Sinus/diagnosis; Heart/*diagnostic imaging; Lung Diseases/diagnosis; Mitral Valve Insufficiency/diagnosis/etiology; Mitral Valve Prolapse/*diagnosis/etiology; Mitral Valve/*pathology; Myocardial Infarction/complications/*diagnosis

A Multicenter Trial of Vena Cava Filters in Severely Injured Patients - Ho, Kwok M.; Rao, Sudhakar; Honeybul, Stephen; Zellweger, Rene; Wibrow, Bradley; Lipman, Jeffrey; Holley, Anthony; Kop, Alan; Geelhoed, Elizabeth; Corcoran, Tomas; Misur, Philip; Edibam, Cyrus; et al. (The New England journal of medicine, 2019)
BACKGROUND: Whether early placement of an inferior vena cava filter reduces the risk of pulmonary embolism or death in severely injured patients who have a contraindication to prophylactic anticoagulation is not known. METHODS: In this multicenter, randomized, controlled trial, we assigned 240 severely injured patients (Injury Severity Score >15 [scores range from 0 to 75, with higher scores indicating more severe injury]) who had a contraindication to anticoagulant agents to have a vena cava filter placed within the first 72 hours after admission for the injury or to have no filter placed. The primary end point was a composite of symptomatic pulmonary embolism or death from any cause at 90 days after enrollment; a secondary end point was symptomatic pulmonary embolism between day 8 and day 90 in the subgroup of patients who survived at least 7 days and did not receive prophylactic anticoagulation within 7 days after injury. All patients underwent ultrasonography of the legs at 2 weeks; patients also underwent mandatory computed tomographic pulmonary angiography when prespecified criteria were met. RESULTS: The median age of the patients was 39 years, and the median Injury Severity Score was 27. Early placement of a vena cava filter did not result in a significantly lower incidence of symptomatic pulmonary embolism or death than no placement of a filter (13.9% in the vena cava filter group and 14.4% in the control group; hazard ratio, 0.99; 95% confidence interval [CI], 0.51 to 1.94; P = 0.98). Among the 46 patients in the vena cava filter group and the 34 patients in the control group who did not receive prophylactic anticoagulation within 7 days after injury, pulmonary embolism developed in none of those in the vena cava filter group and in 5 (14.7%) in the control group, including 1 patient who died (relative risk of pulmonary embolism, 0; 95% CI, 0.00 to 0.55). An entrapped thrombus was found in the filter in 6 patients. CONCLUSIONS: Early prophylactic placement of a vena cava filter after major trauma did not result in a lower incidence of symptomatic pulmonary embolism or death at 90 days than no placement of a filter.
腔静脉滤器在严重损伤患者中的多中心试验 背景：早期置入下腔静脉滤器是否可降低有预防性抗凝禁忌症的严重损伤患者发生肺栓塞或死亡的风险尚不清楚。 方法：在这项多中心、随机、对照试验中，我们分配了240例严重损伤患者（损伤严重度评分 > 15[评分范围从0到75，评分越高表明损伤越严重]），禁忌使用抗凝剂的患者在损伤入院后的前72小时内置入腔静脉滤器或未置入滤器。主要终点是入组后90天症状性肺栓塞或全因死亡的复合终点；次要终点是在存活至少7天且在伤后7天内未接受预防性抗凝治疗的患者亚组中，第8天至第90天之间的症状性肺栓塞。所有患者在2周时接受腿部超声检查；当符合预先规定的标准时，患者还接受了强制性计算机断层扫描肺血管造影术。 结果：患者的中位年龄为39岁，中位损伤严重度评分为27。早期置入腔静脉滤器不会导致症状性肺栓塞或死亡的发生率显著低于未置入滤器（腔静脉滤器组为13.9%，对照组为14.4%；危害比，0.99；95%置信区间 [CI]，0.51至1.94；P = 0.98）。腔静脉滤器组46例和对照组34例伤后 7d 内未预防性抗凝的患者中，腔静脉滤器组无一例发生肺栓塞，对照组5例 (14.7%) 发生肺栓塞，包括1例死亡患者（肺栓塞的相对风险，0；95%CI，0.00-0.55）。在6名患者的滤器中发现了截留血栓。 结论：重大创伤后早期预防性置入腔静脉滤器不会导致症状性肺栓塞或90天时死亡的发生率低于未置入滤器。
Keywords: Humans; Middle Aged; Adult; Kaplan-Meier Estimate; Incidence; Ultrasonography; Risk; Treatment Failure; Computed Tomography Angiography; Lung/diagnostic imaging; *Vena Cava Filters; Injury Severity Score; Leg/diagnostic imaging; Pulmonary Embolism/diagnostic imaging/epidemiology/mortality/*prevention & control; Venous Thrombosis/diagnostic imaging; Wounds and Injuries/mortality/*therapy

Hemolytic Transfusion Reactions - Panch, Sandhya R.; Montemayor-Garcia, Celina; Klein, Harvey G. (The New England journal of medicine, 2019)
溶血性输血反应
Keywords: Humans; Diagnosis, Differential; History, 17th Century; History, 20th Century; *Transfusion Reaction/diagnosis/history/physiopathology/therapy; Blood Group Incompatibility/complications/diagnosis/immunology; Hemolysis

Inverting the Turing Test - Machine Learning to Detect Cognition in the ICU - Menon, David K.; Chennu, Srivas (The New England journal of medicine, 2019)
倒置图灵测试——机器学习检测 ICU 认知
Keywords: Humans; Intensive Care Units; Brain; Cognition; *Machine Learning; *Brain Injuries

Detection of Brain Activation in Unresponsive Patients with Acute Brain Injury - Claassen, Jan; Doyle, Kevin; Matory, Adu; Couch, Caroline; Burger, Kelly M.; Velazquez, Angela; Okonkwo, Joshua U.; King, Jean-RÃ©mi; Park, Soojin; Agarwal, Sachin; Roh, David; Megjhani, Murad; et al. (The New England journal of medicine, 2019)
BACKGROUND: Brain activation in response to spoken motor commands can be detected by electroencephalography (EEG) in clinically unresponsive patients. The prevalence and prognostic importance of a dissociation between commanded motor behavior and brain activation in the first few days after brain injury are not well understood. METHODS: We studied a prospective, consecutive series of patients in a single intensive care unit who had acute brain injury from a variety of causes and who were unresponsive to spoken commands, including some patients with the ability to localize painful stimuli or to fixate on or track visual stimuli. Machine learning was applied to EEG recordings to detect brain activation in response to commands that patients move their hands. The functional outcome at 12 months was determined with the Glasgow Outcome Scale-Extended (GOS-E; levels range from 1 to 8, with higher levels indicating better outcomes). RESULTS: A total of 16 of 104 unresponsive patients (15%) had brain activation detected by EEG at a median of 4 days after injury. The condition in 8 of these 16 patients (50%) and in 23 of 88 patients (26%) without brain activation improved such that they were able to follow commands before discharge. At 12 months, 7 of 16 patients (44%) with brain activation and 12 of 84 patients (14%) without brain activation had a GOS-E level of 4 or higher, denoting the ability to function independently for 8 hours (odds ratio, 4.6; 95% confidence interval, 1.2 to 17.1). CONCLUSIONS: A dissociation between the absence of behavioral responses to motor commands and the evidence of brain activation in response to these commands in EEG recordings was found in 15% of patients in a consecutive series of patients with acute brain injury. (Supported by the Dana Foundation and the James S. McDonnell Foundation.).
急性脑损伤无反应患者的脑激活检测 背景：临床无反应患者可通过脑电图 (EEG) 检测到对口语运动指令反应的脑激活。脑损伤后最初几天指令运动行为和大脑激活之间分离的患病率和预后重要性尚不十分清楚。 方法：我们研究了在单个重症监护室的一个前瞻性连续系列患者，这些患者患有各种原因引起的急性脑损伤，并且对口语指令无反应，包括一些能够定位疼痛刺激或注视或追踪视觉刺激的患者。将机器学习应用于 EEG 记录，检测患者移动双手指令引起的大脑激活。使用格拉斯哥结局量表-扩展（GOS-E；水平范围1-8，水平越高表明结局越好）确定12个月时的功能结局。 结果：104例无反应患者中共有16例 (15%) 在伤后中位 4d 脑电图检测到脑激活。这16例患者中的8例 (50%) 和88例无脑激活患者中的23例 (26%) 的病情改善，因此他们能够在出院前遵循指令。在12个月时，16例脑激活患者中的7例 (44%) 和84例无脑激活患者中的12例 (14%) 的 GOS-E 水平为4或更高，表明能够独立发挥功能8小时（比值比，4.6；95%置信区间，1.2-17.1）。 结论：在一个连续的急性脑损伤患者系列中，15%的患者在 EEG 记录中发现对运动指令无行为反应和对这些指令有反应的脑激活证据之间的分离。（由 Dana 基金会和James S. McDonnell基金会支持。）。
Keywords: Humans; Female; Male; Middle Aged; Prognosis; Prospective Studies; Aged; Intensive Care Units; Adult; Glasgow Coma Scale; Glasgow Outcome Scale; Reference Values; Cognition/*physiology; Brain/*physiopathology; Area Under Curve; *Electroencephalography; *Support Vector Machine; Brain Injuries/*physiopathology/psychology; Motor Activity/*physiology; Neurologic Examination; Unconsciousness/physiopathology

Early Sedation with Dexmedetomidine in Critically Ill Patients - Shehabi, Yahya; Howe, Belinda D.; Bellomo, Rinaldo; Arabi, Yaseen M.; Bailey, Michael; Bass, Frances E.; Bin Kadiman, Suhaini; McArthur, Colin J.; Murray, Lynnette; Reade, Michael C.; Seppelt, Ian M.; Takala, Jukka; et al. (The New England journal of medicine, 2019)
BACKGROUND: Dexmedetomidine produces sedation while maintaining a degree of arousability and may reduce the duration of mechanical ventilation and delirium among patients in the intensive care unit (ICU). The use of dexmedetomidine as the sole or primary sedative agent in patients undergoing mechanical ventilation has not been extensively studied. METHODS: In an open-label, randomized trial, we enrolled critically ill adults who had been undergoing ventilation for less than 12 hours in the ICU and were expected to continue to receive ventilatory support for longer than the next calendar day to receive dexmedetomidine as the sole or primary sedative or to receive usual care (propofol, midazolam, or other sedatives). The target range of sedation-scores on the Richmond Agitation and Sedation Scale (which is scored from -5 [unresponsive] to +4 [combative]) was -2 to +1 (lightly sedated to restless). The primary outcome was the rate of death from any cause at 90 days. RESULTS: We enrolled 4000 patients at a median interval of 4.6 hours between eligibility and randomization. In a modified intention-to-treat analysis involving 3904 patients, the primary outcome event occurred in 566 of 1948 (29.1%) in the dexmedetomidine group and in 569 of 1956 (29.1%) in the usual-care group (adjusted risk difference, 0.0 percentage points; 95% confidence interval, -2.9 to 2.8). An ancillary finding was that to achieve the prescribed level of sedation, patients in the dexmedetomidine group received supplemental propofol (64% of patients), midazolam (3%), or both (7%) during the first 2 days after randomization; in the usual-care group, these drugs were administered as primary sedatives in 60%, 12%, and 20% of the patients, respectively. Bradycardia and hypotension were more common in the dexmedetomidine group. CONCLUSIONS: Among patients undergoing mechanical ventilation in the ICU, those who received early dexmedetomidine for sedation had a rate of death at 90 days similar to that in the usual-care group and required supplemental sedatives to achieve the prescribed level of sedation. More adverse events were reported in the dexmedetomidine group than in the usual-care group.
危重患者使用右美托咪定的早期镇静 背景：右美托咪定在维持一定程度唤醒的同时产生镇静作用，可能减少重症监护室 (ICU) 患者机械通气和谵妄的持续时间。右美托咪定作为唯一或主要镇静剂在机械通气患者中的应用尚未得到广泛研究。 方法：在一项开放标签、随机试验中，我们纳入了在 ICU 通气不足12小时的危重成人患者，并预期在下一个日历日继续接受通气支持超过一个日历日，接受右美托咪定作为唯一或主要镇静剂或接受常规治疗（丙泊酚、咪达唑仑或其他镇静剂）。Richmond 激越和镇静量表（评分范围为-5[无反应] 至 + 4[好斗]）镇静评分的目标范围为-2至 + 1（轻度镇静至坐立不安）。主要结局是90天时全因死亡率。 结果：我们纳入了4000例患者，合格性和随机化之间的中位间隔为4.6小时。在一项涉及3904名患者的改良意向性治疗分析中，主要结果事件在右美托咪定组1948名患者中发生566例 (29.1%)，在常规治疗组1956名患者中发生569例 (29.1%)（校正风险差异，0.0个百分点；95%置信区间，-2.9至2.8）。一个辅助发现是，为了达到规定的镇静水平，右美托咪定组患者在随机化后的前2天补充丙泊酚（64%的患者）、咪达唑仑 (3%) 或两者 (7%)；在常规治疗组中，这些药物作为主要镇静剂给药的比例分别为60%、12%、和分别占患者的20%。心动过缓和低血压在右美托咪定组中更常见。 结论：在 ICU 接受机械通气的患者中，早期接受右美托咪定镇静的患者在90天时的死亡率与常规治疗组相似，需要补充镇静剂以达到规定的镇静水平。右美托咪定组报告的不良事件多于常规治疗组。
Keywords: Humans; Drug Therapy, Combination; Treatment Outcome; Female; Male; Middle Aged; Time Factors; Aged; Intensive Care Units; Adult; Intention to Treat Analysis; *Respiration, Artificial; Critical Illness/mortality/*therapy; *Dexmedetomidine/adverse effects; Hypotension/chemically induced; *Conscious Sedation; *Hypnotics and Sedatives/adverse effects; Bradycardia/chemically induced; Midazolam; Propofol

Heatstroke - Epstein, Yoram; Yanovich, Ran (The New England journal of medicine, 2019)
中暑
Keywords: Humans; Risk Factors; Acclimatization; *Heat Stroke/classification/diagnosis/etiology/therapy; Heat Exhaustion/diagnosis

Early Neuromuscular Blockade in the Acute Respiratory Distress Syndrome - Moss, Marc; Huang, David T.; Brower, Roy G.; Ferguson, Niall D.; Ginde, Adit A.; Gong, M. N.; Grissom, Colin K.; Gundel, Stephanie; Hayden, Douglas; Hite, R. Duncan; Hou, Peter C.; Hough, Catherine L.; et al. (The New England journal of medicine, 2019)
BACKGROUND: The benefits of early continuous neuromuscular blockade in patients with acute respiratory distress syndrome (ARDS) who are receiving mechanical ventilation remain unclear. METHODS: We randomly assigned patients with moderate-to-severe ARDS (defined by a ratio of the partial pressure of arterial oxygen to the fraction of inspired oxygen of <150 mm Hg with a positive end-expiratory pressure [PEEP] of â‰¥8 cm of water) to a 48-hour continuous infusion of cisatracurium with concomitant deep sedation (intervention group) or to a usual-care approach without routine neuromuscular blockade and with lighter sedation targets (control group). The same mechanical-ventilation strategies were used in both groups, including a strategy involving a high PEEP. The primary end point was in-hospital death from any cause at 90 days. RESULTS: The trial was stopped at the second interim analysis for futility. We enrolled 1006 patients early after the onset of moderate-to-severe ARDS (median, 7.6 hours after onset). During the first 48 hours after randomization, 488 of the 501 patients (97.4%) in the intervention group started a continuous infusion of cisatracurium (median duration of infusion, 47.8 hours; median dose, 1807 mg), and 86 of the 505 patients (17.0%) in the control group received a neuromuscular blocking agent (median dose, 38 mg). At 90 days, 213 patients (42.5%) in the intervention group and 216 (42.8%) in the control group had died before hospital discharge (between-group difference, -0.3 percentage points; 95% confidence interval, -6.4 to 5.9; P = 0.93). While in the hospital, patients in the intervention group were less physically active and had more adverse cardiovascular events than patients in the control group. There were no consistent between-group differences in end points assessed at 3, 6, and 12 months. CONCLUSIONS: Among patients with moderate-to-severe ARDS who were treated with a strategy involving a high PEEP, there was no significant difference in mortality at 90 days between patients who received an early and continuous cisatracurium infusion and those who were treated with a usual-care approach with lighter sedation targets.
急性呼吸窘迫综合征的早期神经肌肉阻滞 背景：早期持续神经肌肉阻滞对接受机械通气的急性呼吸窘迫综合征 (ARDS) 患者的益处仍不清楚。 方法：我们随机分配中度至重度 ARDS 患者（定义为动脉血氧分压与吸入氧分数之比 < 150 mmHg，呼气末正压 [PEEP] 为‰¥8 cm水）连续输注顺式阿曲库铵48小时，同时给予深度镇静（干预组）或无常规神经肌肉阻滞且镇静目标较轻的常规治疗方法（对照组）。两组均使用相同的机械通气策略，包括涉及高 PEEP 的策略。主要终点是90天时全因住院期间死亡。 结果：第二次期中分析因无效而停止试验。我们纳入了1006例中重度 ARDS 发病后早期（中位数，发病后7.6小时）的患者。在随机化后的前48小时内，干预组501例患者中的488例 (97.4%) 开始连续输注顺式阿曲库铵（中位输注持续时间，47.8小时；中位剂量，1807 mg），对照组505例患者中的86例 (17.0%) 接受神经肌肉阻滞剂（中位剂量，38 mg）。90d 时，干预组213例 (42.5%) 和对照组216例 (42.8%) 在出院前已死亡（组间差异，-0.3个百分点；95%可信区间，-6.4～5.9；P = 0.93）。而在医院，干预组患者较对照组患者体力活动少，不良心血管事件多。在3、6和12个月时评估的终点没有一致的组间差异。 结论：在接受高 PEEP 策略治疗的中度至重度 ARDS 患者中，早期连续输注顺式阿曲库铵的患者与镇静目标较轻的常规治疗患者在90天时的死亡率无显著差异。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Hospital Mortality; Combined Modality Therapy; Treatment Failure; *Positive-Pressure Respiration; Conscious Sedation; Atracurium/adverse effects/*analogs & derivatives/therapeutic use; Neuromuscular Blockade; Neuromuscular Blocking Agents/adverse effects/*therapeutic use; Respiratory Distress Syndrome/*drug therapy/mortality/therapy

Early Paralytic Agents for ARDS? Yes, No, and Sometimes - Slutsky, Arthur S.; Villar, JesÃºs (The New England journal of medicine, 2019)
ARDS 的早期麻痹剂？是、否，有时
Keywords: Humans; Respiration, Artificial; *Respiratory Distress Syndrome; Dyspnea; *Neuromuscular Blockade

Transmission of Nipah Virus - 14 Years of Investigations in Bangladesh - Nikolay, Birgit; Salje, Henrik; Hossain, M. Jahangir; Khan, A. K. M. Dawlat; Sazzad, Hossain M. S.; Rahman, Mahmudur; Daszak, Peter; StrÃ¶her, Ute; Pulliam, Juliet R. C.; Kilpatrick, A. Marm; Nichol, Stuart T.; Klena, John D.; et al. (The New England journal of medicine, 2019)
BACKGROUND: Nipah virus is a highly virulent zoonotic pathogen that can be transmitted between humans. Understanding the dynamics of person-to-person transmission is key to designing effective interventions. METHODS: We used data from all Nipah virus cases identified during outbreak investigations in Bangladesh from April 2001 through April 2014 to investigate case-patient characteristics associated with onward transmission and factors associated with the risk of infection among patient contacts. RESULTS: Of 248 Nipah virus cases identified, 82 were caused by person-to-person transmission, corresponding to a reproduction number (i.e., the average number of secondary cases per case patient) of 0.33 (95% confidence interval [CI], 0.19 to 0.59). The predicted reproduction number increased with the case patient's age and was highest among patients 45 years of age or older who had difficulty breathing (1.1; 95% CI, 0.4 to 3.2). Case patients who did not have difficulty breathing infected 0.05 times as many contacts (95% CI, 0.01 to 0.3) as other case patients did. Serologic testing of 1863 asymptomatic contacts revealed no infections. Spouses of case patients were more often infected (8 of 56 [14%]) than other close family members (7 of 547 [1.3%]) or other contacts (18 of 1996 [0.9%]). The risk of infection increased with increased duration of exposure of the contacts (adjusted odds ratio for exposure of >48 hours vs. â‰¤1 hour, 13; 95% CI, 2.6 to 62) and with exposure to body fluids (adjusted odds ratio, 4.3; 95% CI, 1.6 to 11). CONCLUSIONS: Increasing age and respiratory symptoms were indicators of infectivity of Nipah virus. Interventions to control person-to-person transmission should aim to reduce exposure to body fluids.
尼帕病毒传播-在孟加拉国进行的14年研究 背景：尼帕病毒是一种高毒力的人畜共患病原体，可在人与人之间传播。了解人与人之间传播的动态是设计有效干预措施的关键。 方法：我们使用2001年4月至2014年4月在孟加拉国暴发调查期间确定的所有尼帕病毒病例的数据，调查与继续传播相关的病例-患者特征和与患者接触者感染风险相关的因素。 结果：在确定的248例尼帕病毒病例中，82例由人与人之间传播引起，对应的繁殖数（即每个病例患者的平均继发病例数）为0.33（95%置信区间 [CI]，0.19～0.59）。预测的生殖数量随病例患者年龄增加而增加，在45岁或以上呼吸困难患者中最高 (1.1；95%CI，0.4-3.2)。没有呼吸困难的病例患者感染的接触者是其他病例患者的0.05倍 (95%CI，0.01～0.3)。1863例无症状接触者血清学检测未发现感染。病例患者的配偶感染的频率 (8/56[14%]) 高于其他近亲 (7/547[1.3%]) 或其他接触者 (18/1996[0.9%])。感染风险随着接触者暴露时间的增加（暴露 > 48小时的校正比值比vs.â‰当前1小时，13；95%CI，2.6-62）和体液暴露（校正比值比，4.3；95%CI，1.6-11）而增加。 结论：年龄增长和呼吸道症状是尼帕病毒感染性的指标。控制人与人之间传播的干预措施应旨在减少体液暴露。
Keywords: Humans; Female; Male; Middle Aged; Adult; Young Adult; Animals; Adolescent; Risk Factors; Child; Age Factors; *Nipah Virus; Bangladesh/epidemiology; Body Fluids/virology; Contact Tracing; Disease Transmission, Infectious/prevention & control; Henipavirus Infections/epidemiology/prevention & control/*transmission; Zoonoses/transmission

Diffuse Subcutaneous Emphysema - St Clair, Tiffany M.; Zwemer, Eric (The New England journal of medicine, 2019)
弥漫性皮下气肿
Keywords: Humans; Male; Adolescent; Radiography, Thoracic; Asthma/complications; Lung/*diagnostic imaging; Mediastinal Emphysema/*diagnostic imaging/etiology; Subcutaneous Emphysema/*diagnostic imaging/etiology

Sepsis Guidelines - Chen, Angela X.; Simpson, Steven Q.; Pallin, Daniel J. (The New England journal of medicine, 2019)
败血症指南
Keywords: Humans; Emergency Service, Hospital; *Practice Guidelines as Topic; Sepsis/*therapy; *Critical Care; Emergency Treatment; Time-to-Treatment/*standards

A Device on Trial - Intermittent Pneumatic Compression in Critical Care - Lauzier, FranÃ§ois; Douketis, James D.; Cook, Deborah J. (The New England journal of medicine, 2019)
一种试验装置-重症监护中的间歇气动压迫
Keywords: Humans; Critical Care; *Venous Thromboembolism; *Anticoagulants; Veins

Adjunctive Intermittent Pneumatic Compression for Venous Thromboprophylaxis - Arabi, Yaseen M.; Al-Hameed, Fahad; Burns, Karen E. A.; Mehta, Sangeeta; Alsolamy, Sami J.; Alshahrani, Mohammed S.; Mandourah, Yasser; Almekhlafi, Ghaleb A.; Almaani, Mohammed; Al Bshabshe, Ali; Finfer, Simon; Arshad, Zia; et al. (The New England journal of medicine, 2019)
BACKGROUND: Whether adjunctive intermittent pneumatic compression in critically ill patients receiving pharmacologic thromboprophylaxis would result in a lower incidence of deep-vein thrombosis than pharmacologic thromboprophylaxis alone is uncertain. METHODS: We randomly assigned patients who were considered adults according to the local standards at the participating sites (≥14, ≥16, or ≥18 years of age) within 48 hours after admission to an intensive care unit (ICU) to receive either intermittent pneumatic compression for at least 18 hours each day in addition to pharmacologic thromboprophylaxis with unfractionated or low-molecular-weight heparin (pneumatic compression group) or pharmacologic thromboprophylaxis alone (control group). The primary outcome was incident (i.e., new) proximal lower-limb deep-vein thrombosis, as detected on twice-weekly lower-limb ultrasonography after the third calendar day since randomization until ICU discharge, death, attainment of full mobility, or trial day 28, whichever occurred first. RESULTS: A total of 2003 patients underwent randomization - 991 were assigned to the pneumatic compression group and 1012 to the control group. Intermittent pneumatic compression was applied for a median of 22 hours (interquartile range, 21 to 23) daily for a median of 7 days (interquartile range, 4 to 13). The primary outcome occurred in 37 of 957 patients (3.9%) in the pneumatic compression group and in 41 of 985 patients (4.2%) in the control group (relative risk, 0.93; 95% confidence interval [CI], 0.60 to 1.44; P = 0.74). Venous thromboembolism (pulmonary embolism or any lower-limb deep-vein thrombosis) occurred in 103 of 991 patients (10.4%) in the pneumatic compression group and in 95 of 1012 patients (9.4%) in the control group (relative risk, 1.11; 95% CI, 0.85 to 1.44), and death from any cause at 90 days occurred in 258 of 990 patients (26.1%) and 270 of 1011 patients (26.7%), respectively (relative risk, 0.98; 95% CI, 0.84 to 1.13). CONCLUSIONS: Among critically ill patients who were receiving pharmacologic thromboprophylaxis, adjunctive intermittent pneumatic compression did not result in a significantly lower incidence of proximal lower-limb deep-vein thrombosis than pharmacologic thromboprophylaxis alone.
辅助间歇气动压迫预防静脉血栓形成 背景：接受药物血栓预防的重症患者中，辅助间歇性充气加压是否会导致深静脉血栓形成的发生率低于单独药物血栓预防尚不确定。 方法：我们根据参与研究中心的当地标准（‰â¥14，â‰¥16，或â‰¥18岁）入住重症监护室(ICU)后48小时内，除采用普通肝素或低分子量肝素进行药物血栓预防（气动压迫组）或单独进行药物血栓预防（对照组）外，每天接受至少18小时的间歇性气动压迫oup）。主要结局为从随机分组后第三个日历日之后每周两次下肢超声检查检测到的近端下肢深静脉血栓形成事件（即新发），直至出ICU、死亡、完全活动能力或试验第28天，以先发生者为准。 结果：共对2003例患者进行了随机化-气动加压组991例，对照组1012例。间歇充气加压的中位时间为每日22小时（四分位距：21-23），中位时间为7天（四分位距：4-13）。气动加压组957例患者中的37例(3.9%)和对照组985例患者中的41例(4.2%)发生了主要结局（相对风险，0.93；95%置信区间[CI]，0.60至1.44；P = 0.74）。气动加压组991例患者中的103例(10.4%)和对照组1012例患者中的95例(9.4%)发生了静脉血栓栓塞（肺栓塞或任何下肢深静脉血栓形成）（相对风险，1.11；95%CI，0.85至1.44），第90天，990例患者中的258例(26.1%)和1011例患者中的270例(26.7%)因任何原因死亡（相对风险，0.98；95%CI,0.84）。to 1.13). 结论：在接受药物血栓预防的重症患者中，辅助间歇性充气压迫未导致近端下肢深静脉血栓形成的发生率显著低于单独药物血栓预防。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Intensive Care Units; Adult; Adolescent; Hospital Mortality; Kaplan-Meier Estimate; Incidence; Ultrasonography; Combined Modality Therapy; Heparin, Low-Molecular-Weight/therapeutic use; *Intermittent Pneumatic Compression Devices/adverse effects; Anticoagulants/adverse effects/*therapeutic use; Heparin/adverse effects/*therapeutic use; Lower Extremity/diagnostic imaging; Venous Thromboembolism; Venous Thrombosis/epidemiology/*prevention & control

Gasping for a Diagnosis - D'Silva, Kristin; Brown, Sarah; Hunninghake, Gary M.; Vivero, Marina; Loscalzo, Joseph (The New England journal of medicine, 2019)
因诊断喘息
Keywords: Humans; Male; Adult; Diagnosis, Differential; Tomography, X-Ray Computed; Biopsy; Bronchoscopy; Bronchoalveolar Lavage; Hypoxia/etiology; Lung/diagnostic imaging/*pathology; Cough/etiology; Dyspnea/*etiology; Pneumonia/diagnosis; Granulocyte-Macrophage Colony-Stimulating Factor/therapeutic use; Pulmonary Alveolar Proteinosis/complications/*diagnosis/therapy

Bag-Mask Ventilation during Tracheal Intubation of Critically Ill Adults - Casey, Jonathan D.; Janz, David R.; Russell, Derek W.; Vonderhaar, Derek J.; Joffe, Aaron M.; Dischert, Kevin M.; Brown, Ryan M.; Zouk, Aline N.; Gulati, Swati; Heideman, Brent E.; Lester, Michael G.; Toporek, Alexandra H.; et al. (The New England journal of medicine, 2019)
BACKGROUND: Hypoxemia is the most common complication during tracheal intubation of critically ill adults and may increase the risk of cardiac arrest and death. Whether positive-pressure ventilation with a bag-mask device (bag-mask ventilation) during tracheal intubation of critically ill adults prevents hypoxemia without increasing the risk of aspiration remains controversial. METHODS: In a multicenter, randomized trial conducted in seven intensive care units in the United States, we randomly assigned adults undergoing tracheal intubation to receive either ventilation with a bag-mask device or no ventilation between induction and laryngoscopy. The primary outcome was the lowest oxygen saturation observed during the interval between induction and 2 minutes after tracheal intubation. The secondary outcome was the incidence of severe hypoxemia, defined as an oxygen saturation of less than 80%. RESULTS: Among the 401 patients enrolled, the median lowest oxygen saturation was 96% (interquartile range, 87 to 99) in the bag-mask ventilation group and 93% (interquartile range, 81 to 99) in the no-ventilation group (P = 0.01). A total of 21 patients (10.9%) in the bag-mask ventilation group had severe hypoxemia, as compared with 45 patients (22.8%) in the no-ventilation group (relative risk, 0.48; 95% confidence interval [CI], 0.30 to 0.77). Operator-reported aspiration occurred during 2.5% of intubations in the bag-mask ventilation group and during 4.0% in the no-ventilation group (P = 0.41). The incidence of new opacity on chest radiography in the 48 hours after tracheal intubation was 16.4% and 14.8%, respectively (P = 0.73). CONCLUSIONS: Among critically ill adults undergoing tracheal intubation, patients receiving bag-mask ventilation had higher oxygen saturations and a lower incidence of severe hypoxemia than those receiving no ventilation.
Bag-Mask通气在危重成人气管插管中的应用 背景：低氧血症是危重成人气管插管时最常见的并发症，可能增加心脏骤停和死亡的风险。在危重成人气管插管过程中采用袋式面罩装置（袋式面罩通气）的正压通气是否可在不增加误吸风险的情况下预防低氧血症仍存在争议。 方法：在美国7个重症监护室进行的一项多中心、随机试验中，我们将接受气管插管的成人随机分配至气囊面罩装置通气组或诱导与喉镜检查之间不通气组。主要结局是从诱导至气管插管后2 min之间观察到的最低氧饱和度。次要结局是重度低氧血症的发生率，定义为氧饱和度低于80%。 结果：在入选的401例患者中，面罩通气组的中位最低氧饱和度为96%（四分位距，87-99），无通气组为93%（四分位距，81-99）(P = 0.01)。袋式面罩通气组共有21例患者(10.9%)发生重度低氧血症，无通气组有45例患者(22.8%)发生重度低氧血症（相对风险，0.48；95%置信区间[CI]，0.30至0.77）。在面罩通气组2.5%的插管期间和无通气组4.0%的插管期间，发生了操作人员报告的误吸(P = 0.41)。气管插管后48小时内胸片新发不透明的发生率分别为16.4%和14.8%(P = 0.73)。 结论：在接受气管插管的重症成人中，与未接受通气的患者相比，接受气囊-面罩通气的患者的氧饱和度更高，重度低氧血症的发生率更低。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Adult; Oxygen/*blood; Critical Illness/*therapy; Hypoxia/etiology/*prevention & control; Intubation, Intratracheal/*adverse effects/methods; Laryngeal Masks; Respiration, Artificial/*instrumentation

Preventing Dogma from Driving Practice - Kritek, Patricia A.; Luks, Andrew M. (The New England journal of medicine, 2019)
预防犬类驾驶实践
Keywords: Humans; Critical Illness; Respiration; Intubation, Intratracheal; *Automobile Driving

Plazomicin for Infections Caused by Carbapenem-Resistant Enterobacteriaceae - McKinnell, James A.; Dwyer, Jamie P.; Talbot, George H.; Connolly, Lynn E.; Friedland, Ian; Smith, Alex; Jubb, Adrian M.; Serio, Alisa W.; Krause, Kevin M.; Daikos, George L. (The New England journal of medicine, 2019)
Plazomicin治疗碳青霉烯类耐药肠杆菌科细菌感染
Keywords: Humans; Kaplan-Meier Estimate; Intention to Treat Analysis; Drug Resistance, Bacterial; Anti-Bacterial Agents/*therapeutic use; *Carbapenem-Resistant Enterobacteriaceae; Sample Size; Creatinine/blood; Bacteremia/drug therapy; Colistin/therapeutic use; Enterobacteriaceae Infections/complications/*drug therapy/mortality; Healthcare-Associated Pneumonia/drug therapy; Pneumonia, Bacterial/drug therapy; Pneumonia, Ventilator-Associated/drug therapy; Sisomicin/*analogs & derivatives/therapeutic use

Needed: Antimicrobial Development - Cox, Edward; Nambiar, Sumathi; Baden, Lindsey (The New England journal of medicine, 2019)
需要：抗菌剂开发
Keywords: Humans; Anti-Bacterial Agents; *Anti-Infective Agents; *Urinary Tract Infections; Sisomicin/analogs & derivatives

Initial Care of the Severely Injured Patient - King, David R. (The New England journal of medicine, 2019)
重度损伤患者的初步护理
Keywords: Humans; Trauma Severity Indices; Blood Transfusion; Time-to-Treatment; Emergency Medical Services; Tourniquets; *Emergency Treatment; Antifibrinolytic Agents/therapeutic use; Endovascular Procedures; Hemorrhage/therapy; Traumatology/*methods/trends; Wounds and Injuries/*therapy

Aspiration Pneumonia - Mandell, Lionel A.; Niederman, Michael S. (The New England journal of medicine, 2019)
吸入性肺炎
Keywords: Humans; Risk Factors; Lung/diagnostic imaging; *Pneumonia, Aspiration/etiology/microbiology/prevention & control; Pneumonia/*chemically induced

Thrombus in Transit - Ng, Julie; Pelletier, Marc P. (2019)
转运血栓
Keywords: Humans; Male; Middle Aged; Tomography, X-Ray Computed; Electrocardiography; *Echocardiography; Pulmonary Embolism/*diagnostic imaging; Ultrasonography, Doppler, Duplex; Venous Thrombosis/*diagnostic imaging

Understanding Links among Opioid Use, Overdose, and Suicide - Bohnert, Amy S. B.; Ilgen, Mark A. (The New England journal of medicine, 2019)
了解阿片类药物使用、过量和自杀之间的关联
Keywords: Humans; Risk Factors; United States/epidemiology; Analgesics, Opioid/administration & dosage/*supply & distribution; Chronic Pain/*drug therapy; Drug Overdose/mortality/prevention & control/*psychology; Intention; Opioid-Related Disorders/epidemiology; Pain/physiopathology/*psychology; Suicide/prevention & control/*psychology/trends; Unemployment/psychology

Pantoprazole in Patients at Risk for Gastrointestinal Bleeding in the ICU - Krag, Mette; Marker, SÃ¸ren; Perner, Anders; Wetterslev, JÃ¸rn; Wise, Matt P.; Schefold, Joerg C.; Keus, Frederik; Guttormsen, Anne B.; Bendel, Stepani; Borthwick, Mark; Lange, Theis; Rasmussen, Bodil S.; et al. (The New England journal of medicine, 2018)
BACKGROUND: Prophylaxis for gastrointestinal stress ulceration is frequently given to patients in the intensive care unit (ICU), but its risks and benefits are unclear. METHODS: In this European, multicenter, parallel-group, blinded trial, we randomly assigned adults who had been admitted to the ICU for an acute condition (i.e., an unplanned admission) and who were at risk for gastrointestinal bleeding to receive 40 mg of intravenous pantoprazole (a proton-pump inhibitor) or placebo daily during the ICU stay. The primary outcome was death by 90 days after randomization. RESULTS: A total of 3298 patients were enrolled; 1645 were randomly assigned to the pantoprazole group and 1653 to the placebo group. Data on the primary outcome were available for 3282 patients (99.5%). At 90 days, 510 patients (31.1%) in the pantoprazole group and 499 (30.4%) in the placebo group had died (relative risk, 1.02; 95% confidence interval [CI], 0.91 to 1.13; P=0.76). During the ICU stay, at least one clinically important event (a composite of clinically important gastrointestinal bleeding, pneumonia, Clostridium difficile infection, or myocardial ischemia) had occurred in 21.9% of patients assigned to pantoprazole and 22.6% of those assigned to placebo (relative risk, 0.96; 95% CI, 0.83 to 1.11). In the pantoprazole group, 2.5% of patients had clinically important gastrointestinal bleeding, as compared with 4.2% in the placebo group. The number of patients with infections or serious adverse reactions and the percentage of days alive without life support within 90 days were similar in the two groups. CONCLUSIONS: Among adult patients in the ICU who were at risk for gastrointestinal bleeding, mortality at 90 days and the number of clinically important events were similar in those assigned to pantoprazole and those assigned to placebo.
泮托拉唑用于ICU存在胃肠道出血风险的患者 背景：在重症监护室(ICU)患者中常给予胃肠道应激性溃疡的预防治疗，但其风险和获益尚不清楚。 方法：在这项欧洲、多中心、平行组、设盲试验中，我们将因急性疾病（即计划外入院）入住ICU且有胃肠道出血风险的成人随机分配至在ICU住院期间每日接受40 mg静脉注射泮托拉唑（一种质子泵抑制剂）或安慰剂。主要结局是随机分组后90天的死亡。 结果：共入组3298例患者；1645例被随机分配至泮托拉唑组，1653例被分配至安慰剂组。获得了3282例患者(99.5%)的主要结局数据。90天时，泮托拉唑组510例患者(31.1%)和安慰剂组499例患者(30.4%)死亡（相对风险，1.02；95%置信区间[CI]，0.91至1.13；P = 0.76）。在ICU住院期间，泮托拉唑组21.9%的患者和安慰剂组22.6%的患者发生了至少一起临床重要事件（临床重要胃肠道出血、肺炎、艰难梭菌感染或心肌缺血的复合终点）（相对风险，0.96；95%CI，0.83至1.11）。在泮托拉唑组，2.5%的患者发生临床重要的胃肠道出血，相比之下，安慰剂组为4.2%。两组90天内发生感染或严重不良反应的患者数和无生命支持的存活天数百分比相似。 结论：在ICU有胃肠道出血风险的成人患者中，泮托拉唑组和安慰剂组90天时的死亡率和临床重要事件数量相似。
Keywords: Humans; Female; Male; Middle Aged; Survival Analysis; Aged; Intensive Care Units; Risk Factors; Single-Blind Method; Critical Illness/mortality/*therapy; Gastrointestinal Hemorrhage/epidemiology/*prevention & control; Injections, Intravenous; Pantoprazole/adverse effects/*therapeutic use; Peptic Ulcer/*prevention & control; Proton Pump Inhibitors/adverse effects/*therapeutic use; Stress, Physiological

Proton-Pump Inhibitor Prophylaxis in the ICU - Benefits Worth the Risks? - Barkun, Alan; Bardou, Marc (The New England journal of medicine, 2018)
ICU中质子泵抑制剂预防治疗-获益大于风险？
Keywords: Humans; Intensive Care Units; Proton Pump Inhibitors; *Pantoprazole; *Protons; Gastrointestinal Hemorrhage

Of Tragedies and Miracles - Neonatal Organ Donation - Lechner, Beatrice E. (The New England journal of medicine, 2018)
悲剧与奇迹——新生儿器官捐献
Keywords: Humans; Guidelines as Topic; *Tissue Donors; Parents; *Infant, Newborn; Brain Death/*diagnosis; Tissue and Organ Procurement/*methods

Cast of the Right Bronchial Tree - Woodard, Gavitt A.; Wieselthaler, Georg M. (The New England journal of medicine, 2018)
右支气管树管型
Keywords: Humans; Male; Adult; Heart Failure/*complications; Fatal Outcome; *Bronchi; Cough; Hemoptysis/*etiology

Ethical Problems in Decision Making in the Neonatal ICU - Lantos, John D. (The New England journal of medicine, 2018)
新生儿ICU决策中的伦理问题
Keywords: Humans; Infant, Newborn; United States; Intensive Care Units, Neonatal; *Decision Making; Communication; Medical Futility; *Parents; *Professional-Family Relations; Clinical Decision-Making/*ethics; Dissent and Disputes; Intensive Care, Neonatal/*ethics; Life Support Care/ethics; Neonatologists; Neonatology/*ethics; Treatment Refusal; Withholding Treatment/*ethics/legislation & jurisprudence

Energy-Dense versus Routine Enteral Nutrition in the Critically Ill - Chapman, Marianne; Peake, Sandra L.; Bellomo, Rinaldo; Davies, Andrew; Deane, Adam; Horowitz, Michael; Hurford, Sally; Lange, Kylie; Little, Lorraine; Mackle, Diane; O’Connor, Stephanie; Presneill, Jeffrey; et al. (The New England journal of medicine, 2018)
BACKGROUND: The effect of delivering nutrition at different calorie levels during critical illness is uncertain, and patients typically receive less than the recommended amount. METHODS: We conducted a multicenter, double-blind, randomized trial, involving adults undergoing mechanical ventilation in 46 Australian and New Zealand intensive care units (ICUs), to evaluate energy-dense (1.5 kcal per milliliter) as compared with routine (1.0 kcal per milliliter) enteral nutrition at a dose of 1 ml per kilogram of ideal body weight per hour, commencing at or within 12 hours of the initiation of nutrition support and continuing for up to 28 days while the patient was in the ICU. The primary outcome was all-cause mortality within 90 days. RESULTS: There were 3957 patients included in the modified intention-to-treat analysis (1971 in the 1.5-kcal group and 1986 in the 1.0-kcal group). The volume of enteral nutrition delivered during the trial was similar in the two groups; however, patients in the 1.5-kcal group received a mean (±SD) of 1863±478 kcal per day as compared with 1262±313 kcal per day in the 1.0-kcal group (mean difference, 601 kcal per day; 95% confidence interval [CI], 576 to 626). By day 90, a total of 523 of 1948 patients (26.8%) in the 1.5-kcal group and 505 of 1966 patients (25.7%) in the 1.0-kcal group had died (relative risk, 1.05; 95% CI, 0.94 to 1.16; P=0.41). The results were similar in seven predefined subgroups. Higher calorie delivery did not affect survival time, receipt of organ support, number of days alive and out of the ICU and hospital or free of organ support, or the incidence of infective complications or adverse events. CONCLUSIONS: In patients undergoing mechanical ventilation, the rate of survival at 90 days associated with the use of an energy-dense formulation for enteral delivery of nutrition was not higher than that with routine enteral nutrition.
危重患者能量密度与常规肠内营养的比较 背景：在危重病期间以不同的卡路里水平提供营养的效果尚不确定，患者通常接受低于推荐量的营养。 方法：我们进行了一项多中心、双盲、随机试验，涉及在46个澳大利亚和新西兰重症监护室(ICU)接受机械通气的成人患者，以1 mL/kg理想体重/小时的剂量，在开始营养支持时或开始后12小时内开始，并在患者入住ICU时持续长达28天，与常规(1.0 kcal/ml)肠内营养相比，评估能量密度(1.5 kcal/ml)。主要结局为90天内的全因死亡率。 结果：有3957例患者纳入改良的意向治疗分析（1.5-kcal组1971例，1.0-kcal组1986例）。试验期间，两组患者的肠内营养输送量相似；然而，1.5-kcal组患者接受的平均(·±SD)为1863 kcal±478 kcal/天，而1.0-kcal组为1262 kcal±313 kcal/天（平均差异为601 kcal/天；95%置信区间[CI]，576-626）。到第90天，1.5-kcal组1948例患者中共有523例(26.8%)死亡，1.0-kcal组1966例患者中共有505例(25.7%)死亡（相对风险，1.05；95%CI，0.94至1.16；P = 0.41）。7个预定义亚组的结果相似。较高热量的传递并不影响存活时间、接受器官支持、存活和离开ICU和医院的天数或无器官支持的天数，或感染性并发症或不良事件的发生率。 结论：在接受机械通气的患者中，使用能量密集配方肠内营养90天的存活率不高于常规肠内营养。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Intensive Care Units; Adult; Respiration, Artificial; Survival Rate; Intention to Treat Analysis; Critical Illness/mortality/*therapy; *Energy Intake; Enteral Nutrition/adverse effects/*methods; Gastrointestinal Diseases/etiology

Timing of Renal-Replacement Therapy in Patients with Acute Kidney Injury and Sepsis - Barbar, Saber D.; Clere-Jehl, Raphaël; Bourredjem, Abderrahmane; Hernu, Romain; Montini, Florent; Bruyère, Rémi; Lebert, Christine; Bohé, Julien; Badie, Julio; Eraldi, Jean-Pierre; Rigaud, Jean-Philippe; Levy, Bruno; et al. (The New England journal of medicine, 2018)
BACKGROUND: Acute kidney injury is the most frequent complication in patients with septic shock and is an independent risk factor for death. Although renal-replacement therapy is the standard of care for severe acute kidney injury, the ideal time for initiation remains controversial. METHODS: In a multicenter, randomized, controlled trial, we assigned patients with early-stage septic shock who had severe acute kidney injury at the failure stage of the risk, injury, failure, loss, and end-stage kidney disease (RIFLE) classification system but without life-threatening complications related to acute kidney injury to receive renal-replacement therapy either within 12 hours after documentation of failure-stage acute kidney injury (early strategy) or after a delay of 48 hours if renal recovery had not occurred (delayed strategy). The failure stage of the RIFLE classification system is characterized by a serum creatinine level 3 times the baseline level (or ≥4 mg per deciliter with a rapid increase of ≥0.5 mg per deciliter), urine output less than 0.3 ml per kilogram of body weight per hour for 24 hours or longer, or anuria for at least 12 hours. The primary outcome was death at 90 days. RESULTS: The trial was stopped early for futility after the second planned interim analysis. A total of 488 patients underwent randomization; there were no significant between-group differences in the characteristics at baseline. Among the 477 patients for whom follow-up data at 90 days were available, 58% of the patients in the early-strategy group (138 of 239 patients) and 54% in the delayed-strategy group (128 of 238 patients) had died (P=0.38). In the delayed-strategy group, 38% (93 patients) did not receive renal-replacement therapy. Criteria for emergency renal-replacement therapy were met in 17% of the patients in the delayed-strategy group (41 patients). CONCLUSIONS: Among patients with septic shock who had severe acute kidney injury, there was no significant difference in overall mortality at 90 days between patients who were assigned to an early strategy for the initiation of renal-replacement therapy and those who were assigned to a delayed strategy.
急性肾损伤伴败血症患者的肾脏替代治疗时机 背景：急性肾损伤是感染性休克患者最常见的并发症，是死亡的独立风险因素。虽然肾脏替代治疗是重度急性肾损伤的标准治疗，但是开始治疗的理想时间仍有争议。 方法：在一项多中心、随机、对照试验中，我们将患有早期脓毒性休克的患者，在风险、损伤、衰竭、损失、和终末期肾病(RIFLE)分类系统，但无与急性肾损伤相关的危及生命的并发症，在记录到衰竭期急性肾损伤后12小时内（早期策略）或如果未发生肾功能恢复，延迟48小时后（延迟策略）接受肾脏替代治疗。RIFLE分类系统的失败阶段的特征是血清肌酐水平是基线水平的3倍（或者â‰¥4 mg/dl，快速增加â‰¥0.5 mg/dl），24小时或者更长时间内每小时尿量低于0.3 mL/kg体重，或无尿至少12小时。主要结局为90天时的死亡。 结果：在第二次计划的中期分析后，试验因无效而提前终止。共有488例患者接受了随机化；基线时的特征没有显著的组间差异。在477例90天随访数据可用的患者中，58%的早期策略组患者（239例患者中的138例）和54%的延迟策略组患者（238例患者中的128例）死亡(P = 0.38)。在延迟策略组中，38%（93例患者）未接受肾脏替代治疗。延迟策略组（41名患者）17%的患者符合紧急肾脏替代治疗的标准。 结论：在伴有重度急性肾损伤的脓毒性休克患者中，分配至早期肾脏替代治疗策略组的患者与分配至延迟肾脏替代治疗策略组的患者之间90天时总死亡率无显著差异。
Keywords: Humans; Female; Male; Middle Aged; Survival Analysis; Aged; Treatment Failure; *Renal Replacement Therapy; *Time-to-Treatment; Acute Kidney Injury/complications/mortality/*therapy; Kidney Failure, Chronic/classification/etiology; Shock, Septic/*complications

A Candida auris Outbreak and Its Control in an Intensive Care Setting - Eyre, David W.; Sheppard, Anna E.; Madder, Hilary; Moir, Ian; Moroney, Ruth; Quan, T. Phuong; Griffiths, David; George, Sophie; Butcher, Lisa; Morgan, Marcus; Newnham, Robert; Sunderland, Mary; et al. (The New England journal of medicine, 2018)
BACKGROUND: Candida auris is an emerging and multidrug-resistant pathogen. Here we report the epidemiology of a hospital outbreak of C. auris colonization and infection. METHODS: After identification of a cluster of C. auris infections in the neurosciences intensive care unit (ICU) of the Oxford University Hospitals, United Kingdom, we instituted an intensive patient and environmental screening program and package of interventions. Multivariable logistic regression was used to identify predictors of C. auris colonization and infection. Isolates from patients and from the environment were analyzed by whole-genome sequencing. RESULTS: A total of 70 patients were identified as being colonized or infected with C. auris between February 2, 2015, and August 31, 2017; of these patients, 66 (94%) had been admitted to the neurosciences ICU before diagnosis. Invasive C. auris infections developed in 7 patients. When length of stay in the neurosciences ICU and patient vital signs and laboratory results were controlled for, the predictors of C. auris colonization or infection included the use of reusable skin-surface axillary temperature probes (multivariable odds ratio, 6.80; 95% confidence interval [CI], 2.96 to 15.63; P<0.001) and systemic fluconazole exposure (multivariable odds ratio, 10.34; 95% CI, 1.64 to 65.18; P=0.01). C. auris was rarely detected in the general environment. However, it was detected in isolates from reusable equipment, including multiple axillary skin-surface temperature probes. Despite a bundle of infection-control interventions, the incidence of new cases was reduced only after removal of the temperature probes. All outbreak sequences formed a single genetic cluster within the C. auris South African clade. The sequenced isolates from reusable equipment were genetically related to isolates from the patients. CONCLUSIONS: The transmission of C. auris in this hospital outbreak was found to be linked to reusable axillary temperature probes, indicating that this emerging pathogen can persist in the environment and be transmitted in health care settings.
重症监护条件下的金黄色念珠菌暴发及其控制 背景：耳念珠菌是一种新出现的多重耐药病原体。我们在此报告了医院内暴发的耳衣原体定植和感染的流行病学。 方法：在确认英国牛津大学医院神经科学重症监护室(ICU)的一组C. auris感染后，我们制定了强化患者和环境筛查计划以及干预措施包。采用多变量logistic回归分析确定了耳衣原体定植和感染的预测因子。通过全基因组测序分析患者和环境中的分离株。 结果：2015年2月2日至2017年8月31日期间，共70例患者被确定为定植或感染了C. auris；其中66例(94%)在诊断前已入住神经科学ICU。7例患者发生侵袭性耳衣原体感染。当控制住神经科学ICU的时间以及患者的生命体征和实验室结果时，耳衣原体定植或感染的预测因子包括使用可重复使用的皮肤表面腋下温度探头（多变量比值比，6.80；95%置信区间[CI]，2.96至15.63；P < 0.001）和全身性氟康唑暴露（多变量比值比，10.34；95%CI，1.64-65.18；P = 0.01）。在一般环境中很少检测到C. auris。但是，在来自可重复使用设备的分离物中检测到，包括多个腋窝皮肤表面温度探头。尽管采取了一系列感染控制干预措施，但仅在移除温度探头后新发病例的发生率才会降低。所有的爆发序列在南非C. auris进化枝内形成一个单一的基因簇。从可重复使用设备中测序的分离株在遗传学上与患者分离株相关。 结论：C.的传播。此次医院爆发的先兆被发现与可重复使用的腋下温度探头有关，表明这种新出现的病原体可持续存在于环境中，并在医疗环境中传播。
Keywords: Humans; Female; Male; Middle Aged; Case-Control Studies; Adult; Risk Factors; Incidence; Multivariate Analysis; *Intensive Care Units; Phylogeny; Microbial Sensitivity Tests; Infection Control/*methods; *Disease Outbreaks; *Candida/genetics/isolation & purification; *Equipment Contamination; *Equipment Reuse; Candidiasis/*epidemiology/mortality/transmission; Cross Infection/*epidemiology/mortality/transmission; Hospital Departments; Neurology; Thermometers/*microbiology; United Kingdom/epidemiology

Prophylaxis against Upper Gastrointestinal Bleeding in Hospitalized Patients - Cook, Deborah; Guyatt, Gordon (The New England journal of medicine, 2018)
住院患者上消化道出血的预防
Keywords: Humans; Risk Factors; Incidence; Critical Illness/*therapy; Hospitalization; Iatrogenic Disease; Proton Pump Inhibitors/adverse effects/*therapeutic use; Gastric Mucosa/physiology; Gastrointestinal Hemorrhage/epidemiology/etiology/*prevention & control; Gastrointestinal Tract/physiology; Histamine H2 Antagonists/adverse effects/*therapeutic use; Intestinal Mucosa/physiology; Peptic Ulcer/prevention & control; Pneumonia/chemically induced

Nurse-Led Communication in the Intensive Care Unit - Lamas, Daniela (The New England journal of medicine, 2018)
重症监护室护士主导的沟通
Keywords: Critical Care; *Intensive Care Units; *Communication; Nurses

A Randomized Trial of a Family-Support Intervention in Intensive Care Units - White, Douglas B.; Angus, Derek C.; Shields, Anne-Marie; Buddadhumaruk, Praewpannarai; Pidro, Caroline; Paner, Cynthia; Chaitin, Elizabeth; Chang, Chung-Chou H.; Pike, Francis; Weissfeld, Lisa; Kahn, Jeremy M.; Darby, Joseph M.; et al. (The New England journal of medicine, 2018)
BACKGROUND: Surrogate decision makers for incapacitated, critically ill patients often struggle with decisions related to goals of care. Such decisions cause psychological distress in surrogates and may lead to treatment that does not align with patients' preferences. METHODS: We conducted a stepped-wedge, cluster-randomized trial involving patients with a high risk of death and their surrogates in five intensive care units (ICUs) to compare a multicomponent family-support intervention delivered by the interprofessional ICU team with usual care. The primary outcome was the surrogates' mean score on the Hospital Anxiety and Depression Scale (HADS) at 6 months (scores range from 0 to 42, with higher scores indicating worse symptoms). Prespecified secondary outcomes were the surrogates' mean scores on the Impact of Event Scale (IES; scores range from 0 to 88, with higher scores indicating worse symptoms), the Quality of Communication (QOC) scale (scores range from 0 to 100, with higher scores indicating better clinician-family communication), and a modified Patient Perception of Patient Centeredness (PPPC) scale (scores range from 1 to 4, with lower scores indicating more patient- and family-centered care), as well as the mean length of ICU stay. RESULTS: A total of 1420 patients were enrolled in the trial. There was no significant difference between the intervention group and the control group in the surrogates' mean HADS score at 6 months (11.7 and 12.0, respectively; beta coefficient, -0.34; 95% confidence interval [CI], -1.67 to 0.99; P=0.61) or mean IES score (21.2 and 20.3; beta coefficient, 0.90; 95% CI, -1.66 to 3.47; P=0.49). The surrogates' mean QOC score was better in the intervention group than in the control group (69.1 vs. 62.7; beta coefficient, 6.39; 95% CI, 2.57 to 10.20; P=0.001), as was the mean modified PPPC score (1.7 vs. 1.8; beta coefficient, -0.15; 95% CI, -0.26 to -0.04; P=0.006). The mean length of stay in the ICU was shorter in the intervention group than in the control group (6.7 days vs. 7.4 days; incidence rate ratio, 0.90; 95% CI, 0.81 to 1.00; P=0.045), a finding mediated by the shortened mean length of stay in the ICU among patients who died (4.4 days vs. 6.8 days; incidence rate ratio, 0.64; 95% CI, 0.52 to 0.78; P<0.001). CONCLUSIONS: Among critically ill patients and their surrogates, a family-support intervention delivered by the interprofessional ICU team did not significantly affect the surrogates' burden of psychological symptoms, but the surrogates' ratings of the quality of communication and the patient- and family-centeredness of care were better and the length of stay in the ICU was shorter with the intervention than with usual care.
重症监护室中家庭支持干预的随机试验 背景：对于失能、危重患者，替代决策者通常与护理目标相关的决策进行斗争。此类决定会给替代者造成心理压力，可能导致治疗与患者的偏好不一致。 方法：我们进行了一项阶梯式楔形、集群随机试验，涉及5个重症监护室(ICU)中死亡风险高的患者及其代理人，以比较由跨专业ICU团队提供的多成分家庭支持干预与常规护理。主要结局为6个月时医院焦虑抑郁量表(HADS)的替代物平均评分（评分范围为0-42，评分越高表明症状越差）。预先规定的次要结局为事件影响量表（IES；评分范围从0至88，评分越高表明症状越差）、沟通质量(QOC)量表（评分范围从0至100，评分越高表明临床医生-家庭沟通越好）的替代物平均评分，和改良的患者对以患者为中心的感觉(PPPC)量表（评分范围为1-4，评分越低表明以患者和家庭为中心的护理越多），以及平均ICU住院时间。 结果：共有1420例患者入组试验。6个月时干预组和对照组的替代物平均HADS评分（分别为11.7和12.0；β系数，-0.34；95%置信区间[CI]，-1.67至0.99；P = 0.61）或平均IES评分（21.2和20.3；β系数，0.90；95%CI， -1.66至3.47；P = 0.49）。干预组的替代指标平均QOC评分优于对照组（69.1 vs. 62.7；β系数，6.39；95%CI，2.57至10.20；P = 0.001），改良PPPC平均评分也是如此（1.7 vs. 1.8；β系数，-0.15；95%CI，-0.26至-0.04；P = 0.006）。干预组患者的平均ICU住院时间短于对照组（6.7天vs. 7.4天；发生率比值，0.90；95%CI，0.81至1.00；P = 0.045），这是由死亡患者的平均ICU住院时间缩短介导的结果（4.4天vs. 6.8天；发生率比值，0.64；95%CI，0.52至0.78；P < 0.001）。 结论：在危重患者及其代理人中，由跨专业ICU团队提供的家庭支持干预未显著影响代理人的心理症状负担，但是，干预组的沟通质量、护理的患者和家庭中心性的替代评分较常规护理组更好，ICU住院时间较常规护理组更短。
Keywords: Humans; Female; Male; Middle Aged; Aged; Length of Stay; Critical Care; Hospital Mortality; *Intensive Care Units; *Critical Illness/therapy; Family; *Decision Making; Communication; *Professional-Family Relations; *Critical Care Nursing; Anxiety/prevention & control; Caregivers/*psychology; Depression/prevention & control; Stress, Psychological/*prevention & control; Third-Party Consent

Fluid Composition, Infusion Rate, and Brain Injury in Diabetic Ketoacidosis - Sperling, Mark A. (The New England journal of medicine, 2018)
糖尿病酮症酸中毒中的液体成分、输注速率和脑损伤
Keywords: Humans; Brain Edema; Blood Glucose; *Fluid Therapy; *Diabetic Ketoacidosis; Insulin

Clinical Trial of Fluid Infusion Rates for Pediatric Diabetic Ketoacidosis - Kuppermann, Nathan; Ghetti, Simona; Schunk, Jeff E.; Stoner, Michael J.; Rewers, Arleta; McManemy, Julie K.; Myers, Sage R.; Nigrovic, Lise E.; Garro, Aris; Brown, Kathleen M.; Quayle, Kimberly S.; Trainor, Jennifer L.; et al. (The New England journal of medicine, 2018)
BACKGROUND: Diabetic ketoacidosis in children may cause brain injuries ranging from mild to severe. Whether intravenous fluids contribute to these injuries has been debated for decades. METHODS: We conducted a 13-center, randomized, controlled trial that examined the effects of the rate of administration and the sodium chloride content of intravenous fluids on neurologic outcomes in children with diabetic ketoacidosis. Children were randomly assigned to one of four treatment groups in a 2-by-2 factorial design (0.9% or 0.45% sodium chloride content and rapid or slow rate of administration). The primary outcome was a decline in mental status (two consecutive Glasgow Coma Scale scores of <14, on a scale ranging from 3 to 15, with lower scores indicating worse mental status) during treatment for diabetic ketoacidosis. Secondary outcomes included clinically apparent brain injury during treatment for diabetic ketoacidosis, short-term memory during treatment for diabetic ketoacidosis, and memory and IQ 2 to 6 months after recovery from diabetic ketoacidosis. RESULTS: A total of 1389 episodes of diabetic ketoacidosis were reported in 1255 children. The Glasgow Coma Scale score declined to less than 14 in 48 episodes (3.5%), and clinically apparent brain injury occurred in 12 episodes (0.9%). No significant differences among the treatment groups were observed with respect to the percentage of episodes in which the Glasgow Coma Scale score declined to below 14, the magnitude of decline in the Glasgow Coma Scale score, or the duration of time in which the Glasgow Coma Scale score was less than 14; with respect to the results of the tests of short-term memory; or with respect to the incidence of clinically apparent brain injury during treatment for diabetic ketoacidosis. Memory and IQ scores obtained after the children's recovery from diabetic ketoacidosis also did not differ significantly among the groups. Serious adverse events other than altered mental status were rare and occurred with similar frequency in all treatment groups. CONCLUSIONS: Neither the rate of administration nor the sodium chloride content of intravenous fluids significantly influenced neurologic outcomes in children with diabetic ketoacidosis.
儿科糖尿病酮症酸中毒的液体输注速率临床试验 背景：儿童糖尿病酮症酸中毒可能导致轻度至重度脑损伤。数十年来，关于静脉输液是否会导致这些损伤一直存在争议。 方法：我们进行了一项13中心、随机、对照试验，检查了糖尿病酮症酸中毒儿童中静脉输液的给药速率和氯化钠含量对神经系统结局的影响。采用2 × 2析因设计（氯化钠含量为0.9%或0.45%，给药速度快或慢）将儿童随机分配至4个治疗组之一。主要结局是糖尿病酮症酸中毒治疗期间精神状态的下降（连续两次Glasgow昏迷量表评分 < 14，量表范围为3-15，评分越低表明精神状态越差）。次要结局包括糖尿病酮症酸中毒治疗期间的临床明显脑损伤，糖尿病酮症酸中毒治疗期间的短期记忆，以及糖尿病酮症酸中毒恢复后2-6个月的记忆和IQ。 结果：1255例儿童共报告1389例次糖尿病酮症酸中毒。48起事件(3.5%)的Glasgow昏迷量表评分下降至14分以下，12起事件(0.9%)发生临床明显的脑损伤。在Glasgow昏迷量表评分降至14分以下的发作百分比、Glasgow昏迷量表评分的下降幅度或Glasgow昏迷量表评分小于14分的持续时间方面，未观察到治疗组间的显著差异；短期记忆测试的结果；或糖尿病酮症酸中毒治疗期间临床明显脑损伤的发生率。儿童糖尿病酮症酸中毒恢复后获得的记忆和IQ评分也没有显著的组间差异。除精神状态改变外，严重不良事件罕见，所有治疗组的发生率相似。 结论：在糖尿病酮症酸中毒儿童中，给药速率和静脉输液的氯化钠含量均未显著影响神经系统结局。
Keywords: Humans; Female; Male; Prospective Studies; Glasgow Coma Scale; Adolescent; Child; Infant; Child, Preschool; Infusions, Intravenous; Drug Administration Schedule; Brain Edema/etiology; Fluid Therapy/*methods; Brain Injuries/diagnosis/*etiology/prevention & control; Diabetic Ketoacidosis/complications/psychology/*therapy; Rehydration Solutions/*administration & dosage/chemistry; Sodium Chloride/administration & dosage

Substitute Decision Making in End-of-Life Care - Caulley, Lisa; Gillick, Muriel R.; Lehmann, Lisa S. (The New England journal of medicine, 2018)
临终关怀中替代决策
Keywords: Humans; Female; Aged; *Terminal Care; *Decision Making; *Resuscitation Orders; *Third-Party Consent

ICU Admissions for Sepsis or Pneumonia in Australia and New Zealand in 2017 - Burrell, Aidan; Huckson, Sue; Pilcher, David V. (The New England journal of medicine, 2018)
澳大利亚和新西兰2017年因败血症或肺炎入住ICU
Keywords: Humans; Adult; *Intensive Care Units; New Zealand/epidemiology; Australia/epidemiology; Influenza, Human/complications/epidemiology; Patient Admission/*statistics & numerical data; Pneumonia/*epidemiology/etiology; Sepsis/*epidemiology

Long-Term Outcomes of the ADRENAL Trial - Venkatesh, Balasubramanian; Finfer, Simon; Myburgh, John; Cohen, Jeremy; Billot, Laurent (The New England journal of medicine, 2018)
ADRENAL试验的长期结局
Keywords: Humans; Treatment Outcome; Female; Male; Survival Rate; Odds Ratio; Anti-Inflammatory Agents/*therapeutic use; Hydrocortisone/*therapeutic use; Shock, Septic/*drug therapy/mortality

Toxidrome Recognition in Chemical-Weapons Attacks - Ciottone, Gregory R. (The New England journal of medicine, 2018)
化学腐蚀中的氧化钛识别
Keywords: Humans; Diagnosis, Differential; Algorithms; History, 20th Century; History, Ancient; Triage; Decontamination; *Chemical Terrorism; Chemical Warfare Agents/classification/*poisoning; Chemical Warfare/history; Poisoning/diagnosis/therapy

Ultrasound Guidance for Pleural-Catheter Placement - Peris, Adriano; Tutino, Lorenzo; Cianchi, Giovanni; Gensini, Gianfranco (2018)
胸腔置管术的超声引导
Keywords: Humans; Contraindications, Procedure; Lung/diagnostic imaging; Catheters; Drainage/methods; Pleura/*diagnostic imaging; Thoracentesis/adverse effects/instrumentation/*methods; Ultrasonography, Interventional/adverse effects/instrumentation/*methods

Case 8-2018: A 55-Year-Old Woman with Shock and Labile Blood Pressure - Loscalzo, Joseph; Roy, Nathalie; Shah, Ravi V.; Tsai, Joy N.; Cahalane, Alexis M.; Steiner, Johannes; Stone, James R. (The New England journal of medicine, 2018)
病例8-2018：1例55岁的患休克和不稳定血压的耳后女性
Keywords: Humans; Female; Middle Aged; Diagnosis, Differential; Magnetic Resonance Imaging; Myocardium/*pathology; Echocardiography; Stroke Volume; Coronary Angiography; Blood Pressure/physiology; Electrocardiography; Heart-Assist Devices; Adrenal Gland Neoplasms/complications/*diagnosis/pathology; Adrenal Glands/*diagnostic imaging/pathology; Pheochromocytoma/complications/*diagnosis/pathology; Shock, Cardiogenic/*etiology/physiopathology/therapy; Takotsubo Cardiomyopathy/*diagnosis/etiology; Troponin I/blood

Patient-Centered Outcomes and Resuscitation Fluids - Myburgh, John (The New England journal of medicine, 2018)
以患者为中心的结局和复苏液体
Keywords: Humans; Fluid Therapy; *Resuscitation; *Rehydration Solutions

Balanced Crystalloids versus Saline in Noncritically Ill Adults - Self, Wesley H.; Semler, Matthew W.; Wanderer, Jonathan P.; Wang, Li; Byrne, Daniel W.; Collins, Sean P.; Slovis, Corey M.; Lindsell, Christopher J.; Ehrenfeld, Jesse M.; Siew, Edward D.; Shaw, Andrew D.; Bernard, Gordon R.; et al. (The New England journal of medicine, 2018)
BACKGROUND: Comparative clinical effects of balanced crystalloids and saline are uncertain, particularly in noncritically ill patients cared for outside an intensive care unit (ICU). METHODS: We conducted a single-center, pragmatic, multiple-crossover trial comparing balanced crystalloids (lactated Ringer's solution or Plasma-Lyte A) with saline among adults who were treated with intravenous crystalloids in the emergency department and were subsequently hospitalized outside an ICU. The type of crystalloid that was administered in the emergency department was assigned to each patient on the basis of calendar month, with the entire emergency department crossing over between balanced crystalloids and saline monthly during the 16-month trial. The primary outcome was hospital-free days (days alive after discharge before day 28). Secondary outcomes included major adverse kidney events within 30 days - a composite of death from any cause, new renal-replacement therapy, or persistent renal dysfunction (defined as an elevation of the creatinine level to â‰¥200% of baseline) - all censored at hospital discharge or 30 days, whichever occurred first. RESULTS: A total of 13,347 patients were enrolled, with a median crystalloid volume administered in the emergency department of 1079 ml and 88.3% of the patients exclusively receiving the assigned crystalloid. The number of hospital-free days did not differ between the balanced-crystalloids and saline groups (median, 25 days in each group; adjusted odds ratio with balanced crystalloids, 0.98; 95% confidence interval [CI], 0.92 to 1.04; P=0.41). Balanced crystalloids resulted in a lower incidence of major adverse kidney events within 30 days than saline (4.7% vs. 5.6%; adjusted odds ratio, 0.82; 95% CI, 0.70 to 0.95; P=0.01). CONCLUSIONS: Among noncritically ill adults treated with intravenous fluids in the emergency department, there was no difference in hospital-free days between treatment with balanced crystalloids and treatment with saline.
非危重成人中的平衡晶体液与生理盐水 背景：平衡晶体液和生理盐水的比较临床效应尚不确定，尤其是在重症监护室(ICU)以外护理的非危重患者中。 方法：我们进行了一项单中心、实用性、多交叉试验，在随后在ICU外住院的急诊科接受静脉晶体治疗的成人中，对平衡晶体液（乳酸林格氏液或Plasma-Lyte a）与生理盐水进行了比较。根据日历月，为每例患者分配急诊科给予的晶体类型，在16个月试验期间，整个急诊科每月交叉一次平衡晶体和生理盐水。主要结局为无住院天数（第28天前出院后存活的天数）。次要结局包括30天内的主要肾脏不良事件-由任何原因的死亡、新的肾脏替代治疗或持续性肾功能不全（定义为肌酐水平升高至â‰¥基线的200%）组成的复合终点-均在出院时或30天删失，以先发生者为准。 结果：共入选13,347例患者，在急诊科给予的中位晶体体积为1079 mL，88.3%的患者仅接受分配的晶体。平衡晶体组和生理盐水组之间的无住院天数没有差异（中位数，每组25天；平衡晶体组的调整比值比，0.98；95%置信区间[CI]，0.92-1.04；P = 0.41）。平衡晶体液组的30天内主要肾脏不良事件的发生率低于生理盐水组（4.7%vs. 5.6%；校正比值比，0.82；95%CI，0.70至0.95；P = 0.01）。 结论：在急诊科接受静脉输液治疗的非危重成人患者中，平衡晶体液治疗与生理盐水治疗之间无住院天数无差异。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Emergency Service, Hospital; Hospitalization; Cross-Over Studies; Sodium Chloride/*therapeutic use; *Fluid Therapy; *Emergency Treatment; Acute Disease/mortality/*therapy; Electrolytes/blood/*therapeutic use; Isotonic Solutions/*therapeutic use; Kidney Diseases/mortality/therapy; Renal Replacement Therapy; Ringer's Lactate

Balanced Crystalloids versus Saline in Critically Ill Adults - Semler, Matthew W.; Self, Wesley H.; Wanderer, Jonathan P.; Ehrenfeld, Jesse M.; Wang, Li; Byrne, Daniel W.; Stollings, Joanna L.; Kumar, Avinash B.; Hughes, Christopher G.; Hernandez, Antonio; Guillamondegui, Oscar D.; May, Addison K.; et al. (The New England journal of medicine, 2018)
BACKGROUND: Both balanced crystalloids and saline are used for intravenous fluid administration in critically ill adults, but it is not known which results in better clinical outcomes. METHODS: In a pragmatic, cluster-randomized, multiple-crossover trial conducted in five intensive care units at an academic center, we assigned 15,802 adults to receive saline (0.9% sodium chloride) or balanced crystalloids (lactated Ringer's solution or Plasma-Lyte A) according to the randomization of the unit to which they were admitted. The primary outcome was a major adverse kidney event within 30 days - a composite of death from any cause, new renal-replacement therapy, or persistent renal dysfunction (defined as an elevation of the creatinine level to â‰¥200% of baseline) - all censored at hospital discharge or 30 days, whichever occurred first. RESULTS: Among the 7942 patients in the balanced-crystalloids group, 1139 (14.3%) had a major adverse kidney event, as compared with 1211 of 7860 patients (15.4%) in the saline group (marginal odds ratio, 0.91; 95% confidence interval [CI], 0.84 to 0.99; conditional odds ratio, 0.90; 95% CI, 0.82 to 0.99; P=0.04). In-hospital mortality at 30 days was 10.3% in the balanced-crystalloids group and 11.1% in the saline group (P=0.06). The incidence of new renal-replacement therapy was 2.5% and 2.9%, respectively (P=0.08), and the incidence of persistent renal dysfunction was 6.4% and 6.6%, respectively (P=0.60). CONCLUSIONS: Among critically ill adults, the use of balanced crystalloids for intravenous fluid administration resulted in a lower rate of the composite outcome of death from any cause, new renal-replacement therapy, or persistent renal dysfunction than the use of saline.
Balanced crystalloid vs. saline in non-critically ill adults 背景：平衡晶体液和生理盐水均用于危重成人的静脉液体给药，但尚不清楚哪种方法可获得更好的临床结局。 方法：在一个学术中心的5个重症监护室进行的实用性、整群随机、多交叉试验中，我们根据入住单位的随机化分配，将15802名成人分配至接受生理盐水（0.9%氯化钠）或平衡晶体液（乳酸林格氏液或Plasma-Lyte a）。主要结局是30天内的主要肾脏不良事件-全因死亡、新的肾脏替代治疗或持续性肾功能不全（定义为肌酐水平升高至基线的â‰¥200%）的复合终点-在出院或30天时删失，以先发生者为准。 结果：在平衡晶体组7942例患者中，1139例 (14.3%) 发生了主要不良肾脏事件，而生理盐水组7860例患者中有1211例 (15.4%) 发生了主要不良肾脏事件（边际比值比，0.91；95%置信区间 [CI]，0.84-0.99；条件比值比，0.90；95%CI，0.82-0.99；P = 0.04）。平衡晶体组30天时的住院死亡率为10.3%，生理盐水组为11.1%(P = 0.06)。新的肾脏替代治疗的发生率分别为2.5%和2.9%(P = 0.08)，持续性肾功能不全的发生率分别为6.4%和6.6%(P = 0.60)。 结论：在危重成人中，使用平衡晶体液进行静脉液体给药导致复合结局（全因死亡、新的肾脏替代治疗或持续性肾功能不全）的发生率低于使用生理盐水。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Adult; Emergency Service, Hospital; Infusions, Intravenous; Cross-Over Studies; Critical Illness/mortality/*therapy; Sodium Chloride/*therapeutic use; *Fluid Therapy; Isotonic Solutions/*therapeutic use; Ringer's Lactate; Electrolytes/*therapeutic use; Kidney Diseases/epidemiology/therapy; Renal Replacement Therapy/statistics & numerical data

Adjunctive Glucocorticoid Therapy in Patients with Septic Shock - Venkatesh, Balasubramanian; Finfer, Simon; Cohen, Jeremy; Rajbhandari, Dorrilyn; Arabi, Yaseen; Bellomo, Rinaldo; Billot, Laurent; Correa, Maryam; Glass, Parisa; Harward, Meg; Joyce, Christopher; Li, Qiang; et al. (The New England journal of medicine, 2018)
BACKGROUND: Whether hydrocortisone reduces mortality among patients with septic shock is unclear. METHODS: We randomly assigned patients with septic shock who were undergoing mechanical ventilation to receive hydrocortisone (at a dose of 200 mg per day) or placebo for 7 days or until death or discharge from the intensive care unit (ICU), whichever came first. The primary outcome was death from any cause at 90 days. RESULTS: From March 2013 through April 2017, a total of 3800 patients underwent randomization. Status with respect to the primary outcome was ascertained in 3658 patients (1832 of whom had been assigned to the hydrocortisone group and 1826 to the placebo group). At 90 days, 511 patients (27.9%) in the hydrocortisone group and 526 (28.8%) in the placebo group had died (odds ratio, 0.95; 95% confidence interval [CI], 0.82 to 1.10; P=0.50). The effect of the trial regimen was similar in six prespecified subgroups. Patients who had been assigned to receive hydrocortisone had faster resolution of shock than those assigned to the placebo group (median duration, 3 days [interquartile range, 2 to 5] vs. 4 days [interquartile range, 2 to 9]; hazard ratio, 1.32; 95% CI, 1.23 to 1.41; P<0.001). Patients in the hydrocortisone group had a shorter duration of the initial episode of mechanical ventilation than those in the placebo group (median, 6 days [interquartile range, 3 to 18] vs. 7 days [interquartile range, 3 to 24]; hazard ratio, 1.13; 95% CI, 1.05 to 1.22; P<0.001), but taking into account episodes of recurrence of ventilation, there were no significant differences in the number of days alive and free from mechanical ventilation. Fewer patients in the hydrocortisone group than in the placebo group received a blood transfusion (37.0% vs. 41.7%; odds ratio, 0.82; 95% CI, 0.72 to 0.94; P=0.004). There were no significant between-group differences with respect to mortality at 28 days, the rate of recurrence of shock, the number of days alive and out of the ICU, the number of days alive and out of the hospital, the recurrence of mechanical ventilation, the rate of renal-replacement therapy, and the incidence of new-onset bacteremia or fungemia. CONCLUSIONS: Among patients with septic shock undergoing mechanical ventilation, a continuous infusion of hydrocortisone did not result in lower 90-day mortality than placebo.
脓毒性休克患者的糖皮质激素辅助治疗 背景：氢化可的松是否可降低感染性休克患者的死亡率尚不清楚。 方法：我们随机分配接受机械通气的感染性休克患者接受氢化可的松（剂量为每天200 mg）或安慰剂治疗7天，或直至死亡或离开重症监护室 (ICU)，以先发生者为准。主要结局为90天时的全因死亡。 结果：从2013年3月至2017年4月，共有3800例患者接受了随机化。在3658例患者中确定了主要结局的状态（其中1832例被分配至氢化可的松组，1826例被分配至安慰剂组）。90天时，氢化可的松组511例 (27.9%) 和安慰剂组526例 (28.8%) 死亡（优势比0.95;95%可信区间 [CI] ,0.82-1.10;P = 0.50）。在6个预先规定的亚组中，试验方案的作用相似。被分配接受氢化可的松治疗的患者比被分配到安慰剂组的患者休克缓解更快（中位持续时间，3天 [四分位距，2 ~ 5] 比4天 [四分位距，2 ~ 9] ;危险比，1.32;95%CI，1.23 ~ 1.41;P < 0.001）。氢化可的松组患者的首次机械通气时间短于安慰剂组（中位数，6天 [四分位距，3 ~ 18]vs. 7天 [四分位距，3 ~ 24]；风险比，1.13；95%CI，1.05 ~ 1.22；P < 0.001），但考虑到通气复发的发作，存活和无机械通气的天数无显著差异。氢化可的松组接受输血的患者少于安慰剂组（37.0%vs. 41.7%；比值比，0.82；95%CI，0.72-0.94；P = 0.004）。在28天时的死亡率、休克复发率、存活和离开 ICU 的天数、存活和离开医院的天数、机械通气的复发率、肾脏替代治疗的比率方面没有显著的组间差异。以及新发菌血症或真菌血症的发生率。 结论：在接受机械通气的感染性休克患者中，连续输注氢化可的松的90天死亡率并不低于安慰剂。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Double-Blind Method; Aged; APACHE; Recurrence; Respiration, Artificial; Infusions, Intravenous; Survival Rate; Bacteremia/etiology; Renal Replacement Therapy; Anti-Inflammatory Agents/adverse effects/*therapeutic use; Chemotherapy, Adjuvant; Fungemia/etiology; Hydrocortisone/adverse effects/*therapeutic use; Shock, Septic/complications/*drug therapy/mortality/therapy

Influenza Season and ARDS after Cardiac Surgery - Groeneveld, Geert H.; van Paassen, Judith; van Dissel, Jaap T.; Arbous, M. Sesmu (The New England journal of medicine, 2018)
心脏手术后流感季节和 ARDS
Keywords: Humans; Adult; Risk Factors; Retrospective Studies; Child; Age Factors; Incidence; Cardiac Surgical Procedures/*adverse effects; Influenza, Human/*complications; Postoperative Complications/*etiology; Respiratory Distress Syndrome/epidemiology/*etiology; Seasons

An Unconscious Patient with a DNR Tattoo - Holt, Gregory E.; Sarmento, Bianca; Kett, Daniel; Goodman, Kenneth W. (The New England journal of medicine, 2017)
带有 DNR 纹身的无意识患者
Keywords: Humans; Male; Aged; *Unconsciousness; Decision Making/ethics; Resuscitation Orders/*ethics; Tattooing/*ethics

The Code, the Cloud, and the Doppler - Lion, Alex (The New England journal of medicine, 2017)
密码、云和多普勒
Keywords: Humans; Female; Child, Preschool; Equipment Failure; *Cardiopulmonary Resuscitation; *Physician-Patient Relations; Intubation, Intratracheal/instrumentation; Nuclear Family

Age of Red Cells for Transfusion and Outcomes in Critically Ill Adults - Cooper, D. James; McQuilten, Zoe K.; Nichol, Alistair; Ady, Bridget; Aubron, CÃ©cile; Bailey, Michael; Bellomo, Rinaldo; Gantner, Dashiell; Irving, David O.; Kaukonen, Kirsi-Maija; McArthur, Colin; Murray, Lynne; et al. (The New England journal of medicine, 2017)
BACKGROUND: It is uncertain whether the duration of red-cell storage affects mortality after transfusion among critically ill adults. METHODS: In an international, multicenter, randomized, double-blind trial, we assigned critically ill adults to receive either the freshest available, compatible, allogeneic red cells (short-term storage group) or standard-issue (oldest available), compatible, allogeneic red cells (long-term storage group). The primary outcome was 90-day mortality. RESULTS: From November 2012 through December 2016, at 59 centers in five countries, 4994 patients underwent randomization and 4919 (98.5%) were included in the primary analysis. Among the 2457 patients in the short-term storage group, the mean storage duration was 11.8 days. Among the 2462 patients in the long-term storage group, the mean storage duration was 22.4 days. At 90 days, there were 610 deaths (24.8%) in the short-term storage group and 594 (24.1%) in the long-term storage group (absolute risk difference, 0.7 percentage points; 95% confidence interval [CI], -1.7 to 3.1; P=0.57). At 180 days, the absolute risk difference was 0.4 percentage points (95% CI, -2.1 to 3.0; P=0.75). Most of the prespecified secondary measures showed no significant between-group differences in outcome. CONCLUSIONS: The age of transfused red cells did not affect 90-day mortality among critically ill adults.
危重病人输注红细胞的年龄和结局 背景：红细胞储存的持续时间是否影响危重成人输血后的死亡率尚不确定。 方法：在一项国际、多中心、随机、双盲试验中，我们分配危重成人接受最新鲜的相容同种异体红细胞（短期储存组）或标准问题（最早可用）、相容同种异体红细胞（长期储存组）。主要结局是90天死亡率。 结果：从2012年11月至2016年12月，在5个国家的59家临床试验机构，4994例患者接受了随机化，4919例（98.5%）被纳入主要分析。在短期储存组的2457例患者中，平均储存时间为11.8天。在长期储存组的2462例患者中，平均储存时间为22.4天。90d 时，短期保存组死亡610例 (24.8%)，长期保存组死亡594例 (24.1%)（绝对危险度差，0.7个百分点；95%可信区间 [CI]，-1.7～3.1；P = 0.57）。在180天时，绝对风险差异为0.4个百分点（95%CI，-2.1至3.0；P = 0.75）。大多数预先规定的次要指标显示结局无显著组间差异。 结论：输注红细胞的年龄不影响危重成人的90天死亡率。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Time Factors; Double-Blind Method; Adult; Kaplan-Meier Estimate; Intention to Treat Analysis; Transplantation, Homologous; Critical Illness/mortality/*therapy; *Blood Preservation; Erythrocyte Transfusion/*mortality

Decompression Sickness - Sun, Qing; Gao, Guangkai (The New England journal of medicine, 2017)
减压病
Keywords: Humans; Male; Adult; Tomography, X-Ray Computed; *Radiography, Abdominal; Decompression Sickness/complications/*diagnostic imaging/pathology; Embolism, Air/*diagnostic imaging/etiology; Portal Vein/*diagnostic imaging; Skin/*pathology; Vomiting/etiology

Case 26-2017 - Letourneau, Alyssa R.; Price, Melissa C.; Azar, Marwan M. (The New England journal of medicine, 2017)
病例26-2017
Keywords: Humans; Female; Middle Aged; Diagnosis, Differential; Tomography, X-Ray Computed; Immunocompromised Host; Dyspnea/etiology; Hypoxia/etiology; Pneumonia, Viral/complications/*diagnosis; Lung/diagnostic imaging/*pathology; Hypotension/etiology; Fever/etiology; Lung Diseases/diagnosis; Anti-Inflammatory Agents/adverse effects; Cytomegalovirus Infections/complications/*diagnosis; Dermatomyositis/*complications/diagnosis/drug therapy; Muscle Weakness/etiology; Tuberculosis, Pulmonary/diagnosis

Acute Respiratory Distress Syndrome - Thompson, B. Taylor; Chambers, Rachel C.; Liu, Kathleen D. (The New England journal of medicine, 2017)
急性呼吸窘迫综合征
Keywords: Humans; Risk Factors; Combined Modality Therapy; Lung/diagnostic imaging; *Respiration, Artificial; Radiography; *Fluid Therapy; *Respiratory Distress Syndrome/etiology/physiopathology/prevention & control/therapy

Acute Lung Failure - Our Evolving Understanding of ARDS - Bernard, Gordon (The New England journal of medicine, 2017)
急性肺衰竭-我们对 ARDS 的不断发展的理解
Keywords: Humans; History, 21st Century; History, 19th Century; History, 20th Century; Lung/*diagnostic imaging; Cognitive Dysfunction/etiology; Radiography/history; Respiration, Artificial/adverse effects/*history; Respiratory Distress Syndrome/diagnostic imaging/*history/mortality/therapy

Angiotensin II for the Treatment of Vasodilatory Shock - Promise and Caution - Dellinger, R. Phillip; Trzeciak, Stephen (The New England journal of medicine, 2017)
血管紧张素 II 治疗血管舒张性休克-承诺和注意事项
Keywords: Humans; Vasoconstrictor Agents; *Shock; *Angiotensin II

Angiotensin II for the Treatment of Vasodilatory Shock - Khanna, Ashish; English, Shane W.; Wang, Xueyuan S.; Ham, Kealy; Tumlin, James; Szerlip, Harold; Busse, Laurence W.; Altaweel, Laith; Albertson, Timothy E.; Mackey, Caleb; McCurdy, Michael T.; Boldt, David W.; et al. (The New England journal of medicine, 2017)
BACKGROUND: Vasodilatory shock that does not respond to high-dose vasopressors is associated with high mortality. We investigated the effectiveness of angiotensin II for the treatment of patients with this condition. METHODS: We randomly assigned patients with vasodilatory shock who were receiving more than 0.2 Î¼g of norepinephrine per kilogram of body weight per minute or the equivalent dose of another vasopressor to receive infusions of either angiotensin II or placebo. The primary end point was a response with respect to mean arterial pressure at hour 3 after the start of infusion, with response defined as an increase from baseline of at least 10 mm Hg or an increase to at least 75 mm Hg, without an increase in the dose of background vasopressors. RESULTS: A total of 344 patients were assigned to one of the two regimens; 321 received a study intervention (163 received angiotensin II, and 158 received placebo) and were included in the analysis. The primary end point was reached by more patients in the angiotensin II group (114 of 163 patients, 69.9%) than in the placebo group (37 of 158 patients, 23.4%) (odds ratio, 7.95; 95% confidence interval [CI], 4.76 to 13.3; P<0.001). At 48 hours, the mean improvement in the cardiovascular Sequential Organ Failure Assessment (SOFA) score (scores range from 0 to 4, with higher scores indicating more severe dysfunction) was greater in the angiotensin II group than in the placebo group (-1.75 vs. -1.28, P=0.01). Serious adverse events were reported in 60.7% of the patients in the angiotensin II group and in 67.1% in the placebo group. Death by day 28 occurred in 75 of 163 patients (46%) in the angiotensin II group and in 85 of 158 patients (54%) in the placebo group (hazard ratio, 0.78; 95% CI, 0.57 to 1.07; P=0.12). CONCLUSIONS: Angiotensin II effectively increased blood pressure in patients with vasodilatory shock that did not respond to high doses of conventional vasopressors.
血管紧张素 II 治疗血管舒张性休克 背景：大剂量升压药治疗无效的血管舒张性休克与高死亡率相关。我们研究了血管紧张素 II 治疗这种疾病患者的有效性。 方法：我们随机分配血管舒张性休克患者接受每分钟每公斤体重0.2±¼g的去甲肾上腺素或等效剂量的另一种血管加压药，接受血管紧张素 II 或安慰剂输注。主要终点是输注开始后3小时平均动脉压的反应，反应定义为相对于基线至少增加 10 mmHg 或增加至至少75 mmHg，背景血管加压药的剂量未增加。 结果：共有344例患者被分配到两种方案中的一种；321例接受了研究干预（163例接受血管紧张素II，158例接受安慰剂）并被纳入分析。与安慰剂组（158例患者中的37例，23.4%）相比，血管紧张素 II 组（163例患者中的114例，69.9%）有更多的患者达到主要终点（比值比，7.95；95%置信区间 [CI]，4.76至13.3；P < 0.001）。在48小时，血管紧张素 II 组的心血管序贯器官衰竭评估 (SOFA) 评分的平均改善（评分范围为0-4，评分越高表明功能障碍越严重）大于安慰剂组 (-1.75 vs.-1.28，P = 0.01)。血管紧张素 II 组60.7%的患者和安慰剂组67.1%的患者报告了严重不良事件。血管紧张素 II 组163例患者中的75例 (46%) 和安慰剂组158例患者中的85例 (54%) 在第28天死亡（风险比，0.78；95%CI，0.57-1.07；P = 0.12）。 结论：血管紧张素Ⅱ可有效提高对大剂量常规升压药无反应的血管舒张性休克患者的血压。
Keywords: Humans; Drug Therapy, Combination; Female; Male; Middle Aged; Double-Blind Method; Aged; Blood Pressure/*drug effects; Organ Dysfunction Scores; Angiotensin II/adverse effects/*therapeutic use; Catecholamines/administration & dosage; Hypotension/drug therapy; Shock/*drug therapy/physiopathology; Vasoconstrictor Agents/adverse effects/*therapeutic use

Noninvasive Ventilation in the Premature Newborn - Is Less Always More? - Schreiber, Michael D; Marks, Jeremy D. (The New England journal of medicine, 2017)
早产新生儿的无创通气-总是减少吗？
Keywords: Humans; Infant, Newborn; Infant, Premature; *Noninvasive Ventilation; *Infant, Very Low Birth Weight; Respiratory Distress Syndrome, Newborn

Ventilation in Extremely Preterm Infants and Respiratory Function at 8 Years - Doyle, Lex W.; Carse, Elizabeth; Adams, Anne-Marie; Ranganathan, Sarath; Opie, Gillian; Cheong, Jeanie L. Y. (The New England journal of medicine, 2017)
BACKGROUND: Assisted ventilation for extremely preterm infants (<28 weeks of gestation) has become less invasive, but it is unclear whether such developments in care are associated with improvements in short-term or long-term lung function. We compared changes over time in the use of assisted ventilation and oxygen therapy during the newborn period and in lung function at 8 years of age in children whose birth was extremely premature. METHODS: We conducted longitudinal follow-up of all survivors of extremely preterm birth who were born in Victoria, Australia, in three periods - the years 1991 and 1992 (225 infants), 1997 (151 infants), and 2005 (170 infants). Perinatal data were collected prospectively, including data on the duration and type of assisted ventilation provided, the duration of oxygen therapy, and oxygen requirements at 36 weeks of age. Expiratory airflow was measured at 8 years of age, and values were converted to z scores for age, height, ethnic group, and sex. RESULTS: The duration of assisted ventilation rose substantially over time, with a large increase in the duration of nasal continuous positive airway pressure. Despite the increase in the use of less invasive ventilation over time, the duration of oxygen therapy and the rate of oxygen dependence at 36 weeks rose, and airflows at 8 years of age were worse in 2005 than in earlier periods. For instance, for 2005 versus 1991-1992, the mean difference in the z scores for the ratio of forced expiratory volume in 1 second to forced vital capacity was -0.75 (95% confidence interval [CI], -1.07 to -0.44; P<0.001), and for 2005 versus 1997 the mean difference was -0.53 (95% CI, -0.86 to -0.19; P=0.002). CONCLUSIONS: Despite substantial increases in the use of less invasive ventilation after birth, there was no significant decline in oxygen dependence at 36 weeks and no significant improvement in lung function in childhood over time.
极早产儿的通气和8岁时的呼吸功能 背景：极早产儿（< 孕 28周）辅助通气的侵入性较小，但尚不清楚这种护理发展是否与短期或长期肺功能改善相关。我们比较了极早产儿童在新生儿期使用辅助通气和氧疗以及8岁时肺功能随时间的变化。 方法：我们对在澳大利亚维多利亚出生的极早产的所有存活者进行了纵向随访，分三个时期-1991年和1992年（225例婴儿）、1997年（151例婴儿）和2005年（170例婴儿）。前瞻性收集围生期数据，包括提供辅助通气的持续时间和类型、氧疗持续时间和36周龄时的需氧量数据。8岁时测定呼气气流，数值换算为年龄、身高、民族、性别的 z 评分。 结果：随着时间的推移，辅助通气的持续时间大幅增加，经鼻持续气道正压通气的持续时间大幅增加。尽管随着时间的推移，微创通气的使用增加，但2005年氧疗的持续时间和36周时的氧依赖率上升，8岁时的气流比早期更差。例如，2005年与1991-1992年相比，1秒用力呼气容积与用力肺活量比值的 z 评分平均差异为-0.75（95%置信区间 [CI]，-1.07至-0.44；P < 0.001），2005年与1997年相比，平均差异为-0.53（95%CI，-0.86至-0.19；P = 0.002）。 结论：尽管出生后微创通气的使用显著增加，但36周时氧依赖性无显著下降，儿童期肺功能未随时间显著改善。
Keywords: Humans; Female; Male; Time Factors; Child; Infant, Newborn; Follow-Up Studies; Survival Rate; *Respiration, Artificial; Glucocorticoids/therapeutic use; *Infant, Extremely Premature; Bronchopulmonary Dysplasia/prevention & control; *Forced Expiratory Volume; *Vital Capacity; Continuous Positive Airway Pressure/statistics & numerical data; High-Frequency Ventilation; Intermittent Positive-Pressure Ventilation; Oxygen Inhalation Therapy/statistics & numerical data; Respiratory Distress Syndrome, Newborn/*therapy

Reanalysis of the Crystalloid versus Hydroxyethyl Starch Trial (CHEST) - Patel, Anushka; Pieper, Karen; Myburgh, John A.; Perkovic, Vlado; Finfer, Simon; Yang, Qinghong; Li, Qiang; Billot, Laurent (The New England journal of medicine, 2017)
晶体与羟乙基淀粉试验 (CHEST) 的再分析
Keywords: Humans; Fluid Therapy; *Hydroxyethyl Starch Derivatives; *Isotonic Solutions

State Sepsis Mandates - A New Era for Regulation of Hospital Quality - Hershey, Tina B.; Kahn, Jeremy M. (The New England journal of medicine, 2017)
国家败血症任务-医院质量监管的新时代
Keywords: Humans; Length of Stay; Adult; Child; *Practice Guidelines as Topic; Hospital Mortality/trends; Sepsis/mortality/*therapy; *Government Regulation; Evidence-Based Medicine/legislation & jurisprudence; Hospitals/standards; Inappropriate Prescribing; New York/epidemiology; Quality of Health Care/*legislation & jurisprudence

Management of Septic Shock - Berger, Rebecca E.; Rivers, Emanuel; Levy, Mitchell M. (The New England journal of medicine, 2017)
感染性休克的管理
Keywords: Humans; Female; Aged; Blood Pressure; Infusions, Intravenous; Oxygen/blood; *Erythrocyte Transfusion; Combined Modality Therapy; Anti-Bacterial Agents/therapeutic use; Practice Guidelines as Topic; Vasoconstrictor Agents/therapeutic use; Resuscitation/methods; *Fluid Therapy; Shock, Septic/*therapy

Time to Treatment and Mortality during Mandated Emergency Care for Sepsis - Seymour, Christopher W.; Gesten, Foster; Prescott, Hallie C.; Friedrich, Marcus E.; Iwashyna, Theodore J.; Phillips, Gary S.; Lemeshow, Stanley; Osborn, Tiffany; Terry, Kathleen M.; Levy, Mitchell M. (The New England journal of medicine, 2017)
BACKGROUND: In 2013, New York began requiring hospitals to follow protocols for the early identification and treatment of sepsis. However, there is controversy about whether more rapid treatment of sepsis improves outcomes in patients. METHODS: We studied data from patients with sepsis and septic shock that were reported to the New York State Department of Health from April 1, 2014, to June 30, 2016. Patients had a sepsis protocol initiated within 6 hours after arrival in the emergency department and had all items in a 3-hour bundle of care for patients with sepsis (i.e., blood cultures, broad-spectrum antibiotic agents, and lactate measurement) completed within 12 hours. Multilevel models were used to assess the associations between the time until completion of the 3-hour bundle and risk-adjusted mortality. We also examined the times to the administration of antibiotics and to the completion of an initial bolus of intravenous fluid. RESULTS: Among 49,331 patients at 149 hospitals, 40,696 (82.5%) had the 3-hour bundle completed within 3 hours. The median time to completion of the 3-hour bundle was 1.30 hours (interquartile range, 0.65 to 2.35), the median time to the administration of antibiotics was 0.95 hours (interquartile range, 0.35 to 1.95), and the median time to completion of the fluid bolus was 2.56 hours (interquartile range, 1.33 to 4.20). Among patients who had the 3-hour bundle completed within 12 hours, a longer time to the completion of the bundle was associated with higher risk-adjusted in-hospital mortality (odds ratio, 1.04 per hour; 95% confidence interval [CI], 1.02 to 1.05; P<0.001), as was a longer time to the administration of antibiotics (odds ratio, 1.04 per hour; 95% CI, 1.03 to 1.06; P<0.001) but not a longer time to the completion of a bolus of intravenous fluids (odds ratio, 1.01 per hour; 95% CI, 0.99 to 1.02; P=0.21). CONCLUSIONS: More rapid completion of a 3-hour bundle of sepsis care and rapid administration of antibiotics, but not rapid completion of an initial bolus of intravenous fluids, were associated with lower risk-adjusted in-hospital mortality.
败血症强制紧急治疗期间的至治疗时间和死亡率 背景：2013年，纽约开始要求医院遵循脓毒症早期识别和治疗的方案。然而，关于更快速治疗脓毒症是否能改善患者预后存在争议。 方法：我们研究了2014年04月01日至2016年06月30日报告至纽约州卫生部的败血症和感染性休克患者的数据。患者在到达急诊科后6小时内开始败血症方案，并在12小时内完成败血症患者3小时集束化护理中的所有项目（即血培养、广谱抗生素和乳酸盐测量）。使用多级模型评估完成3小时捆绑的时间与风险调整死亡率之间的相关性。我们还检查了至抗生素给药和完成初始静脉推注液体的时间。 结果：在149家医院的49331例患者中，40696例 (82.5%) 在3小时内完成3小时集束化。完成3小时集束化的中位时间为1.30小时（四分位距，0.65至2.35），抗生素给药的中位时间为0.95小时（四分位距，0.35至1.95），完成液体推注的中位时间为2.56小时（四分位距，1.33至4.20）。在12小时内完成3小时集束化的患者中，完成集束化的时间越长，风险校正的住院死亡率越高（比值比，1.04/小时；95%置信区间 [CI]，1.02-1.05；P < 0.001），抗生素给药时间越长（比值比，1.04/小时；95%CI，1.03至1.06；P < 0.001），但至完成静脉推注液体的时间不更长（比值比，1.01/小时；95%CI，0.99至1.02；P = 0.21）。 结论：更快完成3小时的败血症护理和抗生素快速给药，但未快速完成静脉输液的初始推注，与较低的经风险调整的住院死亡率相关。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Aged, 80 and over; Retrospective Studies; Hospital Mortality; Infusions, Intravenous; Multivariate Analysis; Combined Modality Therapy; Anti-Bacterial Agents/*therapeutic use; *Fluid Therapy; *Emergency Treatment; *Time-to-Treatment; Clinical Audit; Sepsis/*mortality/*therapy; Shock, Septic/mortality/therapy

Early, Goal-Directed Therapy for Septic Shock - A Patient-Level Meta-Analysis - Rowan, Kathryn M.; Angus, Derek C.; Bailey, Michael; Barnato, Amber E.; Bellomo, Rinaldo; Canter, Ruth R.; Coats, Timothy J.; Delaney, Anthony; Gimbel, Elizabeth; Grieve, Richard D.; Harrison, David A.; Higgins, Alisa M.; et al. (The New England journal of medicine, 2017)
BACKGROUND: After a single-center trial and observational studies suggesting that early, goal-directed therapy (EGDT) reduced mortality from septic shock, three multicenter trials (ProCESS, ARISE, and ProMISe) showed no benefit. This meta-analysis of individual patient data from the three recent trials was designed prospectively to improve statistical power and explore heterogeneity of treatment effect of EGDT. METHODS: We harmonized entry criteria, intervention protocols, outcomes, resource-use measures, and data collection across the trials and specified all analyses before unblinding. After completion of the trials, we pooled data, excluding the protocol-based standard-therapy group from the ProCESS trial, and resolved residual differences. The primary outcome was 90-day mortality. Secondary outcomes included 1-year survival, organ support, and hospitalization costs. We tested for treatment-by-subgroup interactions for 16 patient characteristics and 6 care-delivery characteristics. RESULTS: We studied 3723 patients at 138 hospitals in seven countries. Mortality at 90 days was similar for EGDT (462 of 1852 patients [24.9%]) and usual care (475 of 1871 patients [25.4%]); the adjusted odds ratio was 0.97 (95% confidence interval, 0.82 to 1.14; P=0.68). EGDT was associated with greater mean (±SD) use of intensive care (5.3±7.1 vs. 4.9±7.0 days, P=0.04) and cardiovascular support (1.9±3.7 vs. 1.6±2.9 days, P=0.01) than was usual care; other outcomes did not differ significantly, although average costs were higher with EGDT. Subgroup analyses showed no benefit from EGDT for patients with worse shock (higher serum lactate level, combined hypotension and hyperlactatemia, or higher predicted risk of death) or for hospitals with a lower propensity to use vasopressors or fluids during usual resuscitation. CONCLUSIONS: In this meta-analysis of individual patient data, EGDT did not result in better outcomes than usual care and was associated with higher hospitalization costs across a broad range of patient and hospital characteristics.
脓毒性休克的早期目标导向治疗-患者水平荟萃分析 背景：在一项单中心试验和观察性研究提示早期目标导向治疗(EGDT)可降低感染性休克死亡率后，3项多中心试验（ProCESS、ARISE和ProMISe）未显示获益。对最近3项试验的个体患者数据进行荟萃分析，旨在提高统计学把握度并探索EGDT治疗效果的异质性。 方法：我们统一了各试验的入选标准、干预方案、结局、资源利用措施和数据收集，并规定了揭盲前的所有分析。试验完成后，我们将数据汇总，从ProCESS试验中排除了基于方案的标准治疗组，并解决了残余差异。主要结局为90天死亡率。次要结局包括1年生存率、器官支持和住院费用。我们检验了16例患者特征和6例护理特征的治疗与亚组相互作用。 结果：我们研究了7个国家138家医院的3723例患者。EGDT（462/1852名患者[24.9%]）和常规护理（475/1871名患者[25.4%]）的90天死亡率相似；校正比值比为0.97（95%置信区间，0.82-1.14；P = 0.68）。与常规护理相比，EGDT与重症监护的平均使用率(æ±SD)（5.3τ±7.1 vs. 4.9τ±7.0天，P = 0.04）和心血管支持（1.9τ±3.7 vs. 1.6τ±2.9天，P = 0.01）相关；尽管EGDT的平均费用较高，但其他结局无显著差异。亚组分析显示，对于休克较差（血清乳酸盐水平较高、低血压和高乳酸盐血症合并存在或死亡风险预测值较高）的患者或在常规复苏期间使用血管加压药或液体的倾向较低的医院，EGDT并无获益。 结论：在本次个体患者数据荟萃分析中，EGDT未产生优于常规护理的结局，并且与广泛患者和医院特征下的住院费用较高相关。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Survival Analysis; Aged; Randomized Controlled Trials as Topic; Hospital Mortality; Infusions, Intravenous; *Erythrocyte Transfusion; Combined Modality Therapy; Practice Guidelines as Topic; Cost-Benefit Analysis; Cardiotonic Agents/therapeutic use; *Fluid Therapy; Hospitalization/economics; Quality-Adjusted Life Years; Resuscitation/economics/*methods; Shock, Septic/mortality/*therapy; Vasoconstrictor Agents/*therapeutic use

Spiraling Out of Control - Mixter, Sara; Sedighi Manesh, Reza; Keller, Sara C.; Platt, Laura; Hollander, Harry (The New England journal of medicine, 2017)
A 22-year-old man presented to the emergency department on Christmas Day with a 5-day history of myalgias, cough, dyspnea, nonbilious emesis, and nonbloody diarrhea. Although he had been ill for several days, he ultimately sought treatment because of intractable vomiting. He reported feeling feverish, although he had not measured his temperature, and noted one episode of hemoptysis.
螺旋失控 一名22岁男性在圣诞节因肌痛、咳嗽、呼吸困难、无胆汁呕吐和无血性腹泻5天而前往急诊科就诊。尽管他已患病数天，但由于顽固性呕吐最终就医。他报告感觉发热，但他未测量体温，并观察到一次咯血。
Keywords: Humans; Male; Young Adult; Diagnosis, Differential; Tomography, X-Ray Computed; Anti-Bacterial Agents/therapeutic use; Diarrhea/etiology; Radiography; Lung/diagnostic imaging/pathology; Jaundice, Obstructive/etiology; Leptospira interrogans/*isolation & purification; Leptospirosis/complications/*diagnosis/drug therapy; Lipase/blood; Lung Diseases/*diagnostic imaging/microbiology; Myalgia/etiology

Levosimendan for the Low Cardiac Output Syndrome after Cardiac Surgery - Desai, Akshay S.; Jarcho, John A. (The New England journal of medicine, 2017)
左西孟旦治疗心脏术后低心排综合征
Keywords: Humans; Cardiac Surgical Procedures; *Cardiac Output, Low; *Hydrazones; Cardiotonic Agents; Pyridazines; Simendan

Levosimendan for Hemodynamic Support after Cardiac Surgery - Landoni, Giovanni; Lomivorotov, Vladimir V.; Alvaro, Gabriele; Lobreglio, Rosetta; Pisano, Antonio; Guarracino, Fabio; CalabrÃ², Maria G.; Grigoryev, Evgeny V.; Likhvantsev, Valery V.; Salgado-Filho, Marcello F.; Bianchi, Alessandro; Pasyuga, Vadim V.; et al. (The New England journal of medicine, 2017)
BACKGROUND: Acute left ventricular dysfunction is a major complication of cardiac surgery and is associated with increased mortality. Meta-analyses of small trials suggest that levosimendan may result in a higher rate of survival among patients undergoing cardiac surgery. METHODS: We conducted a multicenter, randomized, double-blind, placebo-controlled trial involving patients in whom perioperative hemodynamic support was indicated after cardiac surgery, according to prespecified criteria. Patients were randomly assigned to receive levosimendan (in a continuous infusion at a dose of 0.025 to 0.2 Î¼g per kilogram of body weight per minute) or placebo, for up to 48 hours or until discharge from the intensive care unit (ICU), in addition to standard care. The primary outcome was 30-day mortality. RESULTS: The trial was stopped for futility after 506 patients were enrolled. A total of 248 patients were assigned to receive levosimendan and 258 to receive placebo. There was no significant difference in 30-day mortality between the levosimendan group and the placebo group (32 patients [12.9%] and 33 patients [12.8%], respectively; absolute risk difference, 0.1 percentage points; 95% confidence interval [CI], -5.7 to 5.9; P=0.97). There were no significant differences between the levosimendan group and the placebo group in the durations of mechanical ventilation (median, 19 hours and 21 hours, respectively; median difference, -2 hours; 95% CI, -5 to 1; P=0.48), ICU stay (median, 72 hours and 84 hours, respectively; median difference, -12 hours; 95% CI, -21 to 2; P=0.09), and hospital stay (median, 14 days and 14 days, respectively; median difference, 0 days; 95% CI, -1 to 2; P=0.39). There was no significant difference between the levosimendan group and the placebo group in rates of hypotension or cardiac arrhythmias. CONCLUSIONS: In patients who required perioperative hemodynamic support after cardiac surgery, low-dose levosimendan in addition to standard care did not result in lower 30-day mortality than placebo.
左西孟旦用于心脏术后血流动力学支持 背景：急性左心室功能不全是心脏手术的主要并发症，与死亡率增加相关。小型试验的荟萃分析表明，接受心脏手术的患者中，左西孟旦可能会提高生存率。 方法：我们进行了一项多中心、随机、双盲、安慰剂对照试验，纳入了按照预先规定的标准，有心脏手术后围手术期血流动力学支持指征的患者。除标准治疗外，患者被随机分配接受左西孟旦（以0.025至0.2μ¼g/kg体重/分钟的剂量连续输注）或安慰剂，最长48小时或直至离开重症监护室(ICU)。主要结局为30天死亡率。 结果：506例患者入组后因无效而停止试验。共有248例患者被分配接受左西孟旦治疗，258例患者被分配接受安慰剂治疗。左西孟旦组与安慰剂组30天死亡率无显著差异（分别为32例患者[12.9%]和33例患者[12.8%]；绝对风险差，0.1个百分点；95%置信区间[CI]，-5.7至5.9；P = 0.97）。左西孟旦组和安慰剂组在机械通气时间（中位数，分别为19小时和21小时；中位数差值，-2小时；95%CI，-5至1；P = 0.48）、ICU停留时间（中位数，分别为72小时和84小时；中位数差值，-12小时；95%CI，-21至2；P = 0.09）、住院时间（中位数分别为14天和14天；中位数差异为0天；95%CI，-1至2；P = 0.39）。在低血压或心律失常发生率方面，左西孟旦组与安慰剂组之间无显著差异。 结论：在心脏手术后需要围手术期血液动力学支持的患者中，与安慰剂相比，在标准治疗的基础上加用低剂量左西孟旦并未降低30天死亡率。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Length of Stay; Respiration, Artificial; Perioperative Period; Infusions, Intravenous; *Cardiac Surgical Procedures; Treatment Failure; Hemodynamics/*drug effects; *Mortality; Simendan; Cardiac Output, Low/*drug therapy; Cardiotonic Agents/administration & dosage/adverse effects/*therapeutic use; Hydrazones/administration & dosage/adverse effects/*therapeutic use; Postoperative Complications/drug therapy; Pyridazines/administration & dosage/adverse effects/*therapeutic use; Stroke Volume/drug effects

Levosimendan in Patients with Left Ventricular Dysfunction Undergoing Cardiac Surgery - Mehta, Rajendra H.; Leimberger, Jeffrey D.; van Diepen, Sean; Meza, James; Wang, Alice; Jankowich, Rachael; Harrison, Robert W.; Hay, Douglas; Fremes, Stephen; Duncan, Andra; Soltesz, Edward G.; Luber, John; et al. (The New England journal of medicine, 2017)
BACKGROUND: Levosimendan is an inotropic agent that has been shown in small studies to prevent or treat the low cardiac output syndrome after cardiac surgery. METHODS: In a multicenter, randomized, placebo-controlled, phase 3 trial, we evaluated the efficacy and safety of levosimendan in patients with a left ventricular ejection fraction of 35% or less who were undergoing cardiac surgery with the use of cardiopulmonary bypass. Patients were randomly assigned to receive either intravenous levosimendan (at a dose of 0.2 Î¼g per kilogram of body weight per minute for 1 hour, followed by a dose of 0.1 Î¼g per kilogram per minute for 23 hours) or placebo, with the infusion started before surgery. The two primary end points were a four-component composite of death through day 30, renal-replacement therapy through day 30, perioperative myocardial infarction through day 5, or use of a mechanical cardiac assist device through day 5; and a two-component composite of death through day 30 or use of a mechanical cardiac assist device through day 5. RESULTS: A total of 882 patients underwent randomization, 849 of whom received levosimendan or placebo and were included in the modified intention-to-treat population. The four-component primary end point occurred in 105 of 428 patients (24.5%) assigned to receive levosimendan and in 103 of 421 (24.5%) assigned to receive placebo (adjusted odds ratio, 1.00; 99% confidence interval [CI], 0.66 to 1.54; P=0.98). The two-component primary end point occurred in 56 patients (13.1%) assigned to receive levosimendan and in 48 (11.4%) assigned to receive placebo (adjusted odds ratio, 1.18; 96% CI, 0.76 to 1.82; P=0.45). The rate of adverse events did not differ significantly between the two groups. CONCLUSIONS: Prophylactic levosimendan did not result in a rate of the short-term composite end point of death, renal-replacement therapy, perioperative myocardial infarction, or use of a mechanical cardiac assist device that was lower than the rate with placebo among patients with a reduced left ventricular ejection fraction who were undergoing cardiac surgery with the use of cardiopulmonary bypass.
左西孟旦在心脏手术左心功能不全患者中的应用 背景：左西孟旦是一种正性肌力药物，小型研究显示其可预防或治疗心脏手术后的低心排综合征。 方法：在一项多中心、随机、安慰剂对照的iii期试验中，我们评价了左西孟旦在接受体外循环心脏手术的左心室射血分数≤35%患者中的有效性和安全性。患者被随机分配接受静脉注射左西孟旦（剂量为0.2¼g/kg体重/分钟，持续1小时，随后剂量为0.1¼g/kg体重/分钟，持续23小时）或安慰剂，在手术前开始输注。2个主要终点是至第30天死亡、至第30天肾脏替代治疗、至第5天围手术期心肌梗死或至第5天使用机械心脏辅助装置的4部分复合终点；以及30天内死亡或5天内使用机械心脏辅助装置的两部分复合事件。 结果：共有882例患者接受随机分组，其中849例接受左西孟旦或安慰剂，并纳入改良的意向治疗人群。428例被分配接受左西孟旦治疗的患者中有105例(24.5%)发生了4个组分的主要终点，421例被分配接受安慰剂治疗的患者中有103例(24.5%)发生了4个组分的主要终点（调整后的比值比，1.00；99%置信区间[CI]，0.66-1.54；P = 0.98）。56例(13.1%)被分配接受左西孟旦治疗的患者和48例(11.4%)被分配接受安慰剂治疗的患者发生了两部分主要终点（调整后比值比为1.18；96%CI，0.76至1.82；P = 0.45）。两组间不良事件的发生率无显著差异。 结论：预防性左西孟旦治疗不会导致短期复合终点死亡、肾脏替代治疗、围手术期心肌梗死的发生率，或在使用心肺转流术进行心脏手术的左心室射血分数降低患者中，使用的机械心脏辅助装置低于安慰剂组的发生率。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Perioperative Period; Infusions, Intravenous; *Cardiac Surgical Procedures; Treatment Failure; *Mortality; Cardiotonic Agents/adverse effects/*therapeutic use; Renal Replacement Therapy/statistics & numerical data; Simendan; Cardiac Output, Low/*drug therapy; Postoperative Complications/drug therapy; Stroke Volume/drug effects; Heart-Assist Devices/statistics & numerical data; Hydrazones/adverse effects/*therapeutic use; Myocardial Infarction/epidemiology; Pyridazines/adverse effects/*therapeutic use; Ventricular Dysfunction, Left/*drug therapy

Use of Pressure Transducers - Ortega, Rafael; Connor, Christopher; Kotova, Faina; Deng, Wu; Lacerra, Christopher (2017)
压力传感器的使用
Keywords: Humans; *Transducers, Pressure; Blood Pressure Determination/adverse effects/instrumentation/*methods

Docosahexaenoic Acid and Bronchopulmonary Dysplasia in Preterm Infants - Collins, Carmel T.; Makrides, Maria; McPhee, Andrew J.; Sullivan, Thomas R.; Davis, Peter G.; Thio, Marta; Simmer, Karen; Rajadurai, Victor S.; Travadi, Javeed; Berry, Mary J.; Liley, Helen G.; Opie, Gillian F.; et al. (The New England journal of medicine, 2017)
BACKGROUND: Studies in animals and in humans have suggested that docosahexaenoic acid (DHA), an n-3 long-chain polyunsaturated fatty acid, might reduce the risk of bronchopulmonary dysplasia, but appropriately designed trials are lacking. METHODS: We randomly assigned 1273 infants born before 29 weeks of gestation (stratified according to sex, gestational age [<27 weeks or 27 to <29 weeks], and center) within 3 days after their first enteral feeding to receive either an enteral emulsion providing DHA at a dose of 60 mg per kilogram of body weight per day or a control (soy) emulsion without DHA until 36 weeks of postmenstrual age. The primary outcome was bronchopulmonary dysplasia, defined on a physiological basis (with the use of oxygen-saturation monitoring in selected infants), at 36 weeks of postmenstrual age or discharge home, whichever occurred first. RESULTS: A total of 1205 infants survived to the primary outcome assessment. Of the 592 infants assigned to the DHA group, 291 (49.1% by multiple imputation) were classified as having physiological bronchopulmonary dysplasia, as compared with 269 (43.9%) of the 613 infants assigned to the control group (relative risk adjusted for randomization strata, 1.13; 95% confidence interval [CI], 1.02 to 1.25; P=0.02). The composite outcome of physiological bronchopulmonary dysplasia or death before 36 weeks of postmenstrual age occurred in 52.3% of the infants in the DHA group and in 46.4% of the infants in the control group (adjusted relative risk, 1.11; 95% CI, 1.00 to 1.23; P=0.045). There were no significant differences between the two groups in the rates of death or any other neonatal illnesses. Bronchopulmonary dysplasia based on a clinical definition occurred in 53.2% of the infants in the DHA group and in 49.7% of the infants in the control group (P=0.06). CONCLUSIONS: Enteral DHA supplementation at a dose of 60 mg per kilogram per day did not result in a lower risk of physiological bronchopulmonary dysplasia than a control emulsion among preterm infants born before 29 weeks of gestation and may have resulted in a greater risk.
二十碳六烯酸与早产儿支气管肺发育不良 背景：动物和人体研究表明，n-3长链多不饱和脂肪酸二十二碳六烯酸(DHA)可能会降低支气管肺发育不良的风险，但缺乏适当设计的试验。 方法：我们将1273例在妊娠29周前出生的婴儿（根据性别、胎龄[< 27周或27至 < 29周]分层）随机分配，和中心）在首次肠内喂养后3天内接受肠内乳剂（提供DHA，剂量为60 mg/kg体重/天）或对照（大豆）乳剂（不含DHA），直至月经后36周。主要结局是支气管肺发育不良，根据生理学定义（在选定的婴儿中使用氧饱和度监测），在月经后年龄36周或出院时，以先发生者为准。 结果：共有1205名婴儿存活至主要结局评估。DHA组的592名婴儿中，291名婴儿（49.1%采用多重插补法）属于生理性支气管肺发育不良，而对照组的613名婴儿中，269名婴儿(43.9%)属于生理性支气管肺发育不良（根据随机分层调整的相对风险，1.13；95%置信区间[CI]，1.02-1.25；P = 0.02）。DHA组52.3%的婴儿和对照组46.4%的婴儿发生了36周经后胎龄前生理性支气管肺发育不良或死亡的复合结局（校正的相对风险，1.11；95%CI，1.00至1.23；P = 0.045）。两组间死亡率或任何其他新生儿疾病无显著差异。根据临床定义，DHA组53.2%的婴儿和对照组49.7%的婴儿出现支气管肺发育不良(P = 0.06)。 结论：在妊娠29周前出生的早产儿中，与对照乳剂相比，以每天60 mg/kg的剂量肠内补充DHA不会导致生理性支气管肺发育不良的风险降低，并且可能导致更大的风险。
Keywords: Humans; Female; Male; Double-Blind Method; Infant, Newborn; Gestational Age; Infant, Premature; Bronchopulmonary Dysplasia/*prevention & control; Docosahexaenoic Acids/adverse effects/*therapeutic use; Emulsions/therapeutic use; Regression Analysis

Empyema Necessitatis - Gismondi, Ronaldo A.; de Souza, Luiz F. F. (The New England journal of medicine, 2017)
需要脓胸
Keywords: Humans; Male; Adult; Tomography, X-Ray Computed; Dyspnea/etiology; Empyema, Tuberculous/complications/*diagnostic imaging; Mycobacterium tuberculosis/isolation & purification; Thorax/diagnostic imaging/pathology

Tight Glycemic Control in Critically Ill Children - Agus, Michael S. D.; Wypij, David; Hirshberg, Eliotte L.; Srinivasan, Vijay; Faustino, E. Vincent; Luckett, Peter M.; Alexander, Jamin L.; Asaro, Lisa A.; Curley, Martha A. Q.; Steil, Garry M.; Nadkarni, Vinay M. (The New England journal of medicine, 2017)
BACKGROUND: In multicenter studies, tight glycemic control targeting a normal blood glucose level has not been shown to improve outcomes in critically ill adults or children after cardiac surgery. Studies involving critically ill children who have not undergone cardiac surgery are lacking. METHODS: In a 35-center trial, we randomly assigned critically ill children with confirmed hyperglycemia (excluding patients who had undergone cardiac surgery) to one of two ranges of glycemic control: 80 to 110 mg per deciliter (4.4 to 6.1 mmol per liter; lower-target group) or 150 to 180 mg per deciliter (8.3 to 10.0 mmol per liter; higher-target group). Clinicians were guided by continuous glucose monitoring and explicit methods for insulin adjustment. The primary outcome was the number of intensive care unit (ICU)-free days to day 28. RESULTS: The trial was stopped early, on the recommendation of the data and safety monitoring board, owing to a low likelihood of benefit and evidence of the possibility of harm. Of 713 patients, 360 were randomly assigned to the lower-target group and 353 to the higher-target group. In the intention-to-treat analysis, the median number of ICU-free days did not differ significantly between the lower-target group and the higher-target group (19.4 days [interquartile range IQR, 0 to 24.2] and 19.4 days [IQR, 6.7 to 23.9], respectively; P=0.58). In per-protocol analyses, the median time-weighted average glucose level was significantly lower in the lower-target group (109 mg per deciliter [IQR, 102 to 118]; 6.1 mmol per liter [IQR, 5.7 to 6.6]) than in the higher-target group (123 mg per deciliter [IQR, 108 to 142]; 6.8 mmol per liter [IQR, 6.0 to 7.9]; P<0.001). Patients in the lower-target group also had higher rates of health care-associated infections than those in the higher-target group (12 of 349 patients [3.4%] vs. 4 of 349 [1.1%], P=0.04), as well as higher rates of severe hypoglycemia, defined as a blood glucose level below 40 mg per deciliter (2.2 mmol per liter) (18 patients [5.2%] vs. 7 [2.0%], P=0.03). No significant differences were observed in mortality, severity of organ dysfunction, or the number of ventilator-free days. CONCLUSIONS: Critically ill children with hyperglycemia did not benefit from tight glycemic control targeted to a blood glucose level of 80 to 110 mg per deciliter, as compared with a level of 150 to 180 mg per deciliter.
危重病儿童的严格血糖控制 背景：在多中心研究中，严格的血糖控制以正常血糖水平为目标，尚未显示能改善危重成人或儿童心脏手术后的结局。缺乏涉及未接受过心脏手术的重症儿童的研究。 方法：在一项35个中心的试验中，我们将确诊为高血糖的危重儿童（不包括接受过心脏手术的患者）随机分配至两个血糖控制范围之一：80至110 mg/dl（4.4至6.1 mmol/l；较低目标组）或150-180 mg/dl（8.3-10.0 mmol/l；较高目标组）。临床医生以动态血糖监测和胰岛素调整的明确方法为指导。主要结局是至第28天无重症监护室(ICU)的天数。 结果：根据数据和安全性监查委员会的建议，试验提前终止，因为获益可能性较低，且有证据表明危害的可能性。在713例患者中，360例被随机分配至较低目标组，353例被分配至较高目标组。在意向治疗分析中，低目标组与高目标组之间的中位无ICU天数无显著差异（分别为19.4天[四分位距IQR，0至24.2]和19.4天[IQR，6.7至23.9]；P = 0.58）。在符合方案分析中，低目标组(109 mg/dl[IQR，102-118]；6.1 mmol/l[IQR，5.7-6.6])的中位时间加权平均血糖水平显著低于高目标组(123 mg/dl[IQR，108-142]；6.8 mmol/l[IQR，6.0-7.9]；P < 0.001)。低目标组患者的医疗保健相关感染率也高于高目标组（12/349例患者[3.4%]vs. 4/349例患者[1.1%]，P = 0.04），严重低血糖的发生率也更高，定义为血糖水平低于40 mg/dl(2.2 mmol/l)（18例患者[5.2%]对比7例[2.0%]，P = 0.03）。未观察到死亡率、器官功能障碍严重程度或无呼吸机使用天数的显著差异。 结论：与血糖水平为150至180 mg/dl相比，高血糖重症儿童患者接受严格的血糖控制（目标血糖水平为80至110 mg/dl）并未获益。
Keywords: Humans; Female; Male; Length of Stay; Adolescent; Child; Infant; Infant, Newborn; Child, Preschool; Hospital Mortality; Intention to Treat Analysis; Postoperative Period; Critical Illness/*therapy; Intensive Care Units, Pediatric; Hypoglycemic Agents/*administration & dosage; Insulin/*administration & dosage; Hyperglycemia/*drug therapy; Blood Glucose/*analysis; Cardiovascular Surgical Procedures; Glucose/administration & dosage

Case 4-2017. A 2-Month-Old Girl with Growth Retardation and Respiratory Failure. - Kinane, T. Bernard; Lin, Angela E.; Lahoud-Rahme, Manuella; Westra, Sjirk J.; Mark, Eugene J. (The New England journal of medicine, 2017)
病例4-2017。1例2个月大的生长迟缓和呼吸衰竭女孩。
Keywords: Humans; Female; Male; Diagnosis, Differential; Infant; Magnetic Resonance Imaging; Echocardiography; Brain/diagnostic imaging; Mutation; Lung/diagnostic imaging; Heart/diagnostic imaging; Radiography, Thoracic; Respiratory Insufficiency/etiology; Abnormalities, Multiple; Failure to Thrive/etiology; Filamins/*genetics; Genetic Diseases, X-Linked; Growth Disorders/etiology; Heart Defects, Congenital/diagnostic imaging; Hemangioma/complications/diagnosis; Pedigree; Periventricular Nodular Heterotopia/complications/*diagnosis/genetics

Bezlotoxumab for Prevention of Recurrent Clostridium difficile Infection - Wilcox, Mark H.; Gerding, Dale N.; Poxton, Ian R.; Kelly, Ciaran; Nathan, Richard; Birch, Thomas; Cornely, Oliver A.; Rahav, Galia; Bouza, Emilio; Lee, Christine; Jenkin, Grant; Jensen, Werner; et al. (The New England journal of medicine, 2017)
BACKGROUND: Clostridium difficile is the most common cause of infectious diarrhea in hospitalized patients. Recurrences are common after antibiotic therapy. Actoxumab and bezlotoxumab are human monoclonal antibodies against C. difficile toxins A and B, respectively. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials, MODIFY I and MODIFY II, involving 2655 adults receiving oral standard-of-care antibiotics for primary or recurrent C. difficile infection. Participants received an infusion of bezlotoxumab (10 mg per kilogram of body weight), actoxumab plus bezlotoxumab (10 mg per kilogram each), or placebo; actoxumab alone (10 mg per kilogram) was given in MODIFY I but discontinued after a planned interim analysis. The primary end point was recurrent infection (new episode after initial clinical cure) within 12 weeks after infusion in the modified intention-to-treat population. RESULTS: In both trials, the rate of recurrent C. difficile infection was significantly lower with bezlotoxumab alone than with placebo (MODIFY I: 17% [67 of 386] vs. 28% [109 of 395]; adjusted difference, -10.1 percentage points; 95% confidence interval [CI], -15.9 to -4.3; P<0.001; MODIFY II: 16% [62 of 395] vs. 26% [97 of 378]; adjusted difference, -9.9 percentage points; 95% CI, -15.5 to -4.3; P<0.001) and was significantly lower with actoxumab plus bezlotoxumab than with placebo (MODIFY I: 16% [61 of 383] vs. 28% [109 of 395]; adjusted difference, -11.6 percentage points; 95% CI, -17.4 to -5.9; P<0.001; MODIFY II: 15% [58 of 390] vs. 26% [97 of 378]; adjusted difference, -10.7 percentage points; 95% CI, -16.4 to -5.1; P<0.001). In prespecified subgroup analyses (combined data set), rates of recurrent infection were lower in both groups that received bezlotoxumab than in the placebo group in subpopulations at high risk for recurrent infection or for an adverse outcome. The rates of initial clinical cure were 80% with bezlotoxumab alone, 73% with actoxumab plus bezlotoxumab, and 80% with placebo; the rates of sustained cure (initial clinical cure without recurrent infection in 12 weeks) were 64%, 58%, and 54%, respectively. The rates of adverse events were similar among these groups; the most common events were diarrhea and nausea. CONCLUSIONS: Among participants receiving antibiotic treatment for primary or recurrent C. difficile infection, bezlotoxumab was associated with a substantially lower rate of recurrent infection than placebo and had a safety profile similar to that of placebo. The addition of actoxumab did not improve efficacy.
Bezlotoxumab用于预防复发性艰难梭菌感染 背景：艰难梭菌是住院患者感染性腹泻最常见的原因。抗生素治疗后复发很常见。Actoxumab和bezlotoxumab分别是针对艰难梭菌毒素A和B的人单克隆抗体。 方法：我们进行了两项双盲、随机、安慰剂对照、3期试验，MODIFY I和MODIFY II，涉及2655例接受口服标准治疗抗生素治疗原发性或复发性艰难梭菌感染的成人。受试者接受bezlotoxumab（10 mg/kg体重）、actoxumab + bezlotoxumab（各10 mg/kg）或安慰剂输注；在MODIFY I中接受actoxumab单药(10 mg/kg)，但在计划的期中分析后停药。主要终点是改良的意向治疗人群在输注后12周内复发感染（初次临床治愈后新发）。 结果：在两项试验中，bezlotoxumab单药治疗组的复发性艰难梭菌感染率显著低于安慰剂组（MODIFY I：17%[67/386]对比28%[109/395]；校正差异，-10.1个百分点；95%置信区间[CI]， -15.9至-4.3；P < 0.001；MODIFY II：16%[62/395]vs. 26%[97/378]；校正的差异，-9.9个百分点；95%CI，-15.5至-4.3；P < 0.001），actoxumab联合bezlotoxumab显著低于安慰剂（MODIFY I：16%[61/383]对比28%[109/395]；校正的差异，-11.6个百分点；95%CI，-17.4至-5.9；P < 0.001；MODIFY II：15%[58/390]对比26%[97/378]；调整后差异，-10.7个百分点；95%CI，-16.4至-5.1；P < 0.001）。在预先指定的亚组分析（联合数据集）中，在复发性感染高危或不良结局亚群中，接受bezlotoxumab的两组复发性感染的发生率均低于安慰剂组。bezlotoxumab单药、actoxumab联合bezlotoxumab和安慰剂的初始临床治愈率分别为80%、73%和80%；持续治愈率（在12周内初始临床治愈而无复发性感染）分别为64%、58%和54%。这些组的不良事件发生率相似；最常见的事件是腹泻和恶心。 结论：在接受抗生素治疗原发性或复发性艰难梭菌感染的受试者中，bezlotoxumab组的复发性感染率显著低于安慰剂组，且安全性特征与安慰剂组相似。添加actoxumab未改善疗效。
Keywords: Humans; Drug Therapy, Combination; Female; Male; Middle Aged; Double-Blind Method; Aged; Adult; Aged, 80 and over; Young Adult; Adolescent; Infusions, Intravenous; Kaplan-Meier Estimate; Intention to Treat Analysis; *Clostridioides difficile; Anti-Bacterial Agents/therapeutic use; Clostridium Infections/*prevention & control; Broadly Neutralizing Antibodies; Secondary Prevention; Antibodies, Monoclonal/adverse effects/*therapeutic use; Antibodies, Neutralizing/adverse effects/*therapeutic use

Therapeutic Hypothermia after In-Hospital Cardiac Arrest in Children - Moler, Frank W.; Silverstein, Faye S.; Holubkov, Richard; Slomine, Beth S.; Christensen, James R.; Nadkarni, Vinay M.; Meert, Kathleen L.; Browning, Brittan; Pemberton, Victoria L.; Page, Kent; Gildea, Marianne R.; Scholefield, Barnaby R.; et al. (The New England journal of medicine, 2017)
BACKGROUND: Targeted temperature management is recommended for comatose adults and children after out-of-hospital cardiac arrest; however, data on temperature management after in-hospital cardiac arrest are limited. METHODS: In a trial conducted at 37 children's hospitals, we compared two temperature interventions in children who had had in-hospital cardiac arrest. Within 6 hours after the return of circulation, comatose children older than 48 hours and younger than 18 years of age were randomly assigned to therapeutic hypothermia (target temperature, 33.0Â°C) or therapeutic normothermia (target temperature, 36.8Â°C). The primary efficacy outcome, survival at 12 months after cardiac arrest with a score of 70 or higher on the Vineland Adaptive Behavior Scales, second edition (VABS-II, on which scores range from 20 to 160, with higher scores indicating better function), was evaluated among patients who had had a VABS-II score of at least 70 before the cardiac arrest. RESULTS: The trial was terminated because of futility after 329 patients had undergone randomization. Among the 257 patients who had a VABS-II score of at least 70 before cardiac arrest and who could be evaluated, the rate of the primary efficacy outcome did not differ significantly between the hypothermia group and the normothermia group (36% [48 of 133 patients] and 39% [48 of 124 patients], respectively; relative risk, 0.92; 95% confidence interval [CI], 0.67 to 1.27; P=0.63). Among 317 patients who could be evaluated for change in neurobehavioral function, the change in VABS-II score from baseline to 12 months did not differ significantly between the groups (P=0.70). Among 327 patients who could be evaluated for 1-year survival, the rate of 1-year survival did not differ significantly between the hypothermia group and the normothermia group (49% [81 of 166 patients] and 46% [74 of 161 patients], respectively; relative risk, 1.07; 95% CI, 0.85 to 1.34; P=0.56). The incidences of blood-product use, infection, and serious adverse events, as well as 28-day mortality, did not differ significantly between groups. CONCLUSIONS: Among comatose children who survived in-hospital cardiac arrest, therapeutic hypothermia, as compared with therapeutic normothermia, did not confer a significant benefit in survival with a favorable functional outcome at 1 year.
儿童院内心脏骤停后的治疗性低体温 背景：对于昏迷的成人和儿童，院外心脏骤停后建议进行针对性的温度管理；然而，有关院内心脏骤停后温度管理的数据有限。 方法：在一项在37家儿童医院进行的试验中，我们在发生院内心脏骤停的儿童中比较了两种温度干预。在循环恢复后6小时内，48小时以上和18岁以下的昏迷儿童被随机分配至治疗性低温组（目标温度33.0 ℃）或治疗性常温组（目标温度36.8 ℃）。主要疗效结局，第2版Vineland适应行为量表（VABS-II，评分范围为20-160，评分越高表示功能越好）评分为70或更高的心脏骤停后12个月的生存期，在心脏骤停前VABS-II评分至少为70的患者中进行评价。 结果：329例患者接受随机分组后，因无效而终止试验。在257名心脏骤停前VABS-II评分至少为70并且可以进行评估的患者中，低温组和正常体温组之间主要疗效结局的比率没有显著差异（分别为36%[48/133名患者]和39%[48/124名患者]；相对风险，0.92；95%置信区间[CI]，0.67至1.27；P = 0.63）。在317例可评价神经行为功能变化的患者中，VABS-II评分从基线至12个月的变化在两组之间无显著差异(P = 0.70)。在可评估1年生存率的327例患者中，低温组和正常体温组的1年生存率无显著差异（分别为49%[166例患者中的81例]和46%[161例患者中的74例]；相对风险，1.07；95%CI，0.85-1.34；P = 0.56）。治疗组之间的血液制品使用、感染和严重不良事件的发生率以及28天死亡率没有显著差异。 结论：在住院期间心脏骤停存活的昏迷儿童中，与治疗性正常体温相比，治疗性低体温在1年时未产生显著的生存获益和良好的功能结局。
Keywords: Humans; Female; Male; Survival Analysis; Adolescent; Child; Infant; Infant, Newborn; Child, Preschool; Hospitalization; Treatment Failure; *Hypothermia, Induced; Hospitals, Pediatric; Body Temperature; *Coma/complications; Heart Arrest/complications/mortality/*therapy

Case 2-2017. An 18-Year-Old Woman with Acute Liver Failure. - Olson, Kristian R.; Davarpanah, Amir H.; Schaefer, Esperance A.; Elias, Nahel; Misdraji, Joseph (The New England journal of medicine, 2017)
病例2-2017。1例18岁女性急性肝衰竭患者。
Keywords: Humans; Female; Diagnosis, Differential; Adolescent; Ultrasonography, Doppler; Liver Transplantation; Abdomen/diagnostic imaging; Acetaminophen/adverse effects; Hepatolenticular Degeneration/complications/*diagnosis/pathology; Jaundice/etiology; Liver Diseases/diagnosis; Liver Failure, Acute/*etiology; Liver Function Tests; Liver/diagnostic imaging/*pathology; Puerperal Disorders/diagnosis/etiology

A View from the Edge - Creating a Culture of Caring - Awdish, Rana L. A. (The New England journal of medicine, 2017)
边缘视角——创建关爱文化
Keywords: Humans; Female; Pregnancy; Professional-Patient Relations; *Physician-Patient Relations; *Empathy; *Staff Development; Adenoma/complications/*therapy; Hemorrhage/etiology; Liver Neoplasms/complications/*therapy; Neoplasms, Unknown Primary; Pregnancy Complications, Neoplastic/*therapy; Rupture, Spontaneous/complications/therapy

Epidemiology of Acute Kidney Injury in Critically Ill Children and Young Adults - Kaddourah, Ahmad; Basu, Rajit K.; Bagshaw, Sean M.; Goldstein, Stuart L. (The New England journal of medicine, 2017)
BACKGROUND: The epidemiologic characteristics of children and young adults with acute kidney injury have been described in single-center and retrospective studies. We conducted a multinational, prospective study involving patients admitted to pediatric intensive care units to define the incremental risk of death and complications associated with severe acute kidney injury. METHODS: We used the Kidney Disease: Improving Global Outcomes criteria to define acute kidney injury. Severe acute kidney injury was defined as stage 2 or 3 acute kidney injury (plasma creatinine level â‰¥2 times the baseline level or urine output <0.5 ml per kilogram of body weight per hour for â‰¥12 hours) and was assessed for the first 7 days of intensive care. All patients 3 months to 25 years of age who were admitted to 1 of 32 participating units were screened during 3 consecutive months. The primary outcome was 28-day mortality. RESULTS: A total of 4683 patients were evaluated; acute kidney injury developed in 1261 patients (26.9%; 95% confidence interval [CI], 25.6 to 28.2), and severe acute kidney injury developed in 543 patients (11.6%; 95% CI, 10.7 to 12.5). Severe acute kidney injury conferred an increased risk of death by day 28 after adjustment for 16 covariates (adjusted odds ratio, 1.77; 95% CI, 1.17 to 2.68); death occurred in 60 of the 543 patients (11.0%) with severe acute kidney injury versus 105 of the 4140 patients (2.5%) without severe acute kidney injury (P<0.001). Severe acute kidney injury was associated with increased use of mechanical ventilation and renal-replacement therapy. A stepwise increase in 28-day mortality was associated with worsening severity of acute kidney injury (P<0.001 by log-rank test). Assessment of acute kidney injury according to the plasma creatinine level alone failed to identify acute kidney injury in 67.2% of the patients with low urine output. CONCLUSIONS: Acute kidney injury is common and is associated with poor outcomes, including increased mortality, among critically ill children and young adults.
危重病儿童和年轻成人中急性肾损伤的流行病学 背景：单中心和回顾性研究描述了儿童和年轻成人急性肾损伤的流行病学特征。我们进行了一项多国、前瞻性研究，包括入住儿科重症监护室的患者，以确定与重度急性肾损伤相关的死亡和并发症的风险增加。 方法：我们使用肾病：改善全球预后标准来定义急性肾损伤。重度急性肾损伤定义为2期或3期急性肾损伤（â‰¥12小时，血浆肌酐水平â‰¥2倍基线水平或尿量 < 0.5 mL/kg体重/小时），并在重症监护的前7天进行评估。在连续3个月期间，对入住32家参与单位之一的所有3个月至25岁的患者进行了筛选。主要结局为28天死亡率。 结果：共评价了4683例患者；1261例患者发生了急性肾损伤（26.9%；95%置信区间[CI]，25.6至28.2），543例患者发生了重度急性肾损伤（11.6%；95%CI，10.7至12.5）。在对16个协变量进行校正后（校正后的比值比，1.77；95%CI，1.17-2.68），重度急性肾损伤使第28天的死亡风险增加；543例重度急性肾损伤患者中有60例(11.0%)死亡，4140例无重度急性肾损伤患者中有105例(2.5%)死亡(P < 0.001)。重度急性肾损伤与机械通气和肾脏替代治疗的使用增加相关。28天死亡率逐步增加与急性肾损伤严重程度恶化相关（P < 0.001，对数秩检验）。仅根据血浆肌酐水平评估急性肾损伤未能在67.2%的低尿量患者中识别出急性肾损伤。 结论：急性肾损伤在重症儿童和年轻成人中很常见，并且与不良结局相关，包括死亡率增加。
Keywords: Humans; Treatment Outcome; Female; Male; Prospective Studies; Length of Stay; Adult; Young Adult; Respiration, Artificial; Adolescent; Risk Factors; Child; Infant; Severity of Illness Index; Child, Preschool; *Critical Illness; Intensive Care Units, Pediatric; Creatinine/blood; Renal Replacement Therapy; Acute Kidney Injury/complications/*epidemiology/mortality/therapy

Acute Kidney Injury in Critically Ill Children - An Ominous Legacy - Ingelfinger, Julie R. (The New England journal of medicine, 2017)
危重病儿童中的急性肾损伤–遗留问题
Keywords: Humans; Child; *Critical Illness; Intensive Care Units, Pediatric; *Acute Kidney Injury; Gentamicins

All in a Day's Work - Equity vs. Equality at a Public ICU in Brazil. - Machado, FlÃ¡via R. (The New England journal of medicine, 2016)
一天的工作-巴西公共ICU的公平与平等。
Keywords: Humans; Intensive Care Units/*organization & administration; Brazil; Budgets; Health Care Rationing/*economics/ethics; Healthcare Disparities/economics/*ethics; Hospitals, Public/*economics; Insurance Coverage/trends

Publication of Secondary Analyses from Randomized Trials in Critical Care - Ramanan, Mahesh; Myburgh, John; Finfer, Simon; Bellomo, Rinaldo; Venkatesh, Balasubramanian (The New England journal of medicine, 2016)
来自重症监护随机试验的次要分析的出版物
Keywords: Humans; *Randomized Controlled Trials as Topic; *Critical Care; Bibliometrics; Datasets as Topic; Periodicals as Topic/*statistics & numerical data; Publishing/statistics & numerical data

Levosimendan for the Prevention of Acute Organ Dysfunction in Sepsis - Gordon, Anthony C.; Perkins, Gavin D.; Singer, Mervyn; McAuley, Daniel F.; Orme, Robert M. L.; Santhakumaran, Shalini; Mason, Alexina J.; Cross, Mary; Al-Beidh, Farah; Best-Lane, Janis; Brealey, David; Nutt, Christopher L.; et al. (The New England journal of medicine, 2016)
BACKGROUND: Levosimendan is a calcium-sensitizing drug with inotropic and other properties that may improve outcomes in patients with sepsis. METHODS: We conducted a double-blind, randomized clinical trial to investigate whether levosimendan reduces the severity of organ dysfunction in adults with sepsis. Patients were randomly assigned to receive a blinded infusion of levosimendan (at a dose of 0.05 to 0.2 μg per kilogram of body weight per minute) for 24 hours or placebo in addition to standard care. The primary outcome was the mean daily Sequential Organ Failure Assessment (SOFA) score in the intensive care unit up to day 28 (scores for each of five systems range from 0 to 4, with higher scores indicating more severe dysfunction; maximum score, 20). Secondary outcomes included 28-day mortality, time to weaning from mechanical ventilation, and adverse events. RESULTS: The trial recruited 516 patients; 259 were assigned to receive levosimendan and 257 to receive placebo. There was no significant difference in the mean (±SD) SOFA score between the levosimendan group and the placebo group (6.68±3.96 vs. 6.06±3.89; mean difference, 0.61; 95% confidence interval [CI], -0.07 to 1.29; P=0.053). Mortality at 28 days was 34.5% in the levosimendan group and 30.9% in the placebo group (absolute difference, 3.6 percentage points; 95% CI, -4.5 to 11.7; P=0.43). Among patients requiring ventilation at baseline, those in the levosimendan group were less likely than those in the placebo group to be successfully weaned from mechanical ventilation over the period of 28 days (hazard ratio, 0.77; 95% CI, 0.60 to 0.97; P=0.03). More patients in the levosimendan group than in the placebo group had supraventricular tachyarrhythmia (3.1% vs. 0.4%; absolute difference, 2.7 percentage points; 95% CI, 0.1 to 5.3; P=0.04). CONCLUSIONS: The addition of levosimendan to standard treatment in adults with sepsis was not associated with less severe organ dysfunction or lower mortality. Levosimendan was associated with a lower likelihood of successful weaning from mechanical ventilation and a higher risk of supraventricular tachyarrhythmia.
左西孟旦预防脓毒症患者的急性器官功能障碍 背景：左西孟旦是一种钙增敏药物，具有正性肌力和其他特性，可能改善败血症患者的结局。 方法：我们进行了一项双盲、随机临床试验，以研究左西孟旦是否能降低脓毒症成人患者器官功能障碍的严重程度。患者被随机分配在标准治疗的基础上接受盲态输注左西孟旦（剂量为每分钟每千克体重0.05至0.2¼g）24小时或安慰剂。主要结局是重症监护室中直至第28天的平均每日序贯器官衰竭评估(SOFA)评分（5个系统的评分范围为0-4，评分越高表明功能障碍越严重；最大评分，20）。次要结局包括28天死亡率、机械通气撤机时间和不良事件。 结果：试验招募了516例患者；259例被分配接受左西孟旦，257例接受安慰剂。左西孟旦组和安慰剂组的SOFA平均评分(õ±SD)无显著差异（6.68≦±3.96 vs. 6.06≦±3.89；平均差，0.61；95%置信区间[CI]，-0.07至1.29；P = 0.053）。28天时死亡率左西孟旦组为34.5%，安慰剂组为30.9%（绝对差异，3.6个百分点；95%CI，-4.5至11.7；P = 0.43）。在基线时需要通气的患者中，左西孟旦组在28天内成功脱离机械通气的可能性低于安慰剂组（风险比，0.77；95%CI，0.60至0.97；P = 0.03）。左西孟旦组发生室上性快速性心律失常的患者多于安慰剂组（3.1%vs.0.4%；绝对差异，2.7个百分点；95%CI，0.1-5.3；P = 0.04）。 结论：在标准治疗的基础上加用左西孟旦治疗成人脓毒血症不会导致较轻的器官功能障碍或较低的死亡率。左西孟旦成功停用机械通气的可能性较低，发生室上性快速性心律失常的风险较高。

Hearing without Listening - Drazen, Jeffrey M. (The New England journal of medicine, 2016)
听力不听
Keywords: Humans; Intensive Care Units; Patient Care Team; *Interprofessional Relations; *Point-of-Care Systems; *Medical Records Systems, Computerized; *Teaching Rounds

Nasal High-Flow Therapy for Primary Respiratory Support in Preterm Infants - Roberts, Calum T.; Owen, Louise S.; Manley, Brett J.; FrÃ¸island, Dag H.; Donath, Susan M.; Dalziel, Kim M.; Pritchard, Margo A.; Cartwright, David W.; Collins, Clare L.; Malhotra, Atul; Davis, Peter G. (The New England journal of medicine, 2016)
BACKGROUND: Treatment with nasal high-flow therapy has efficacy similar to that of nasal continuous positive airway pressure (CPAP) when used as postextubation support in neonates. The efficacy of high-flow therapy as the primary means of respiratory support for preterm infants with respiratory distress has not been proved. METHODS: In this international, multicenter, randomized, noninferiority trial, we assigned 564 preterm infants (gestational age, â‰¥28 weeks 0 days) with early respiratory distress who had not received surfactant replacement to treatment with either nasal high-flow therapy or nasal CPAP. The primary outcome was treatment failure within 72 hours after randomization. Noninferiority was determined by calculating the absolute difference in the risk of the primary outcome; the chosen margin of noninferiority was 10 percentage points. Infants in whom high-flow therapy failed could receive rescue CPAP; infants in whom CPAP failed were intubated and mechanically ventilated. RESULTS: Trial recruitment stopped early at the recommendation of the independent data and safety monitoring committee because of a significant difference in the primary outcome between treatment groups. Treatment failure occurred in 71 of 278 infants (25.5%) in the high-flow group and in 38 of 286 infants (13.3%) in the CPAP group (risk difference, 12.3 percentage points; 95% confidence interval [CI], 5.8 to 18.7; P<0.001). The rate of intubation within 72 hours did not differ significantly between the high-flow and CPAP groups (15.5% and 11.5%, respectively; risk difference, 3.9 percentage points; 95% CI, -1.7 to 9.6; P=0.17), nor did the rate of adverse events. CONCLUSIONS: When used as primary support for preterm infants with respiratory distress, high-flow therapy resulted in a significantly higher rate of treatment failure than did CPAP.
经鼻高流量治疗用于早产儿初级呼吸支持 背景：在新生儿中，当用作拔管后支持时，经鼻高流量治疗的有效性与经鼻持续气道正压通气(CPAP)相似。尚未证实高流量治疗作为呼吸窘迫早产儿呼吸支持的主要手段的疗效。 方法：在这项国际、多中心、随机、非劣效性试验中，我们将564例早期呼吸窘迫未接受表面活性剂替代治疗的早产儿（胎龄â‰¥28周0天）分配至经鼻高流量治疗组或经鼻CPAP组。主要结局为随机分组后72小时内治疗失败。通过计算主要结局风险的绝对差异确定非劣效性；选择的非劣效性界值为10个百分点。高流量治疗失败的婴儿可以接受急救CPAP；对CPAP失败的婴儿进行插管和机械通气。 结果：由于治疗组间主要结局存在显著差异，根据独立数据和安全性监查委员会的建议，试验招募提前停止。高流量组的278名婴儿中有71名婴儿(25.5%)治疗失败，CPAP组的286名婴儿中有38名婴儿(13.3%)治疗失败（风险差异，12.3个百分点；95%置信区间[CI]，5.8至18.7；P < 0.001）。高流量组和CPAP组的72小时内插管率无显著差异（分别为15.5%和11.5%；风险差异，3.9个百分点；95%CI，-1.7至9.6；P = 0.17），不良事件率也无显著差异。 结论：当用作呼吸窘迫早产儿的主要支持时，高流量治疗导致的治疗失败率显著高于CPAP。
Keywords: Humans; Female; Male; Infant, Newborn; Gestational Age; Treatment Failure; Infant, Premature; *Noninvasive Ventilation; *Continuous Positive Airway Pressure; Oxygen Inhalation Therapy/*methods; Infant, Low Birth Weight; Pulmonary Surfactants/therapeutic use; Respiratory Distress Syndrome, Newborn/mortality/*therapy

The DNR Order after 40 Years - Burns, Jeffrey P.; Truog, Robert D. (The New England journal of medicine, 2016)
40年后的DNR订单
Keywords: Humans; History, 20th Century; *Cardiopulmonary Resuscitation/ethics/history; *Resuscitation Orders/ethics; Informed Consent/history; Patient Rights/ethics/history; Terminal Care/history/methods

Fire-Related Inhalation Injury - Sheridan, Robert L. (The New England journal of medicine, 2016)
火灾相关吸入损伤
Keywords: Humans; Bronchoscopy; Burns, Inhalation/diagnosis/etiology/*therapy; Fires

CASE RECORDS of the MASSACHUSETTS GENERAL HOSPITAL. Case 21-2016. A 32-Year-Old Man in an Unresponsive State. - Fenves, Andrew Z.; Schaefer, Pamela W.; Luther, Jay; Pierce, Virginia M. (The New England journal of medicine, 2016)
马萨诸塞州总医院病例记录。病例21-2016。无反应状态的32岁男性。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Ultrasonography; Brain/*pathology; Radiography; Fatal Outcome; Lung/diagnostic imaging/pathology; Liver Function Tests; Decerebrate State/etiology; Gallbladder/diagnostic imaging/pathology; Hepatic Encephalopathy/*etiology; Hepatitis B/complications/*diagnosis; Hepatitis, Viral, Human/diagnosis; Hypoglycemia/etiology; Liver Failure, Acute/*diagnosis/etiology; Prisoners; Unconsciousness/etiology

Initiation Strategies for Renal-Replacement Therapy in the Intensive Care Unit - Gaudry, Stéphane; Hajage, David; Schortgen, Fréderique; Martin-Lefevre, Laurent; Pons, Bertrand; Boulet, Eric; Boyer, Alexandre; Chevrel, Guillaume; Lerolle, Nicolas; Carpentier, Dorothée; de Prost, Nicolas; Lautrette, Alexandre; et al. (The New England journal of medicine, 2016)
BACKGROUND: The timing of renal-replacement therapy in critically ill patients who have acute kidney injury but no potentially life-threatening complication directly related to renal failure is a subject of debate. METHODS: In this multicenter randomized trial, we assigned patients with severe acute kidney injury (Kidney Disease: Improving Global Outcomes [KDIGO] classification, stage 3 [stages range from 1 to 3, with higher stages indicating more severe kidney injury]) who required mechanical ventilation, catecholamine infusion, or both and did not have a potentially life-threatening complication directly related to renal failure to either an early or a delayed strategy of renal-replacement therapy. With the early strategy, renal-replacement therapy was started immediately after randomization. With the delayed strategy, renal-replacement therapy was initiated if at least one of the following criteria was met: severe hyperkalemia, metabolic acidosis, pulmonary edema, blood urea nitrogen level higher than 112 mg per deciliter, or oliguria for more than 72 hours after randomization. The primary outcome was overall survival at day 60. RESULTS: A total of 620 patients underwent randomization. The Kaplan-Meier estimates of mortality at day 60 did not differ significantly between the early and delayed strategies; 150 deaths occurred among 311 patients in the early-strategy group (48.5%; 95% confidence interval [CI], 42.6 to 53.8), and 153 deaths occurred among 308 patients in the delayed-strategy group (49.7%, 95% CI, 43.8 to 55.0; P=0.79). A total of 151 patients (49%) in the delayed-strategy group did not receive renal-replacement therapy. The rate of catheter-related bloodstream infections was higher in the early-strategy group than in the delayed-strategy group (10% vs. 5%, P=0.03). Diuresis, a marker of improved kidney function, occurred earlier in the delayed-strategy group (P<0.001). CONCLUSIONS: In a trial involving critically ill patients with severe acute kidney injury, we found no significant difference with regard to mortality between an early and a delayed strategy for the initiation of renal-replacement therapy. A delayed strategy averted the need for renal-replacement therapy in an appreciable number of patients.
重症监护室中肾脏替代治疗的启动策略 背景：在发生急性肾损伤但无与肾衰竭直接相关的潜在危及生命的并发症的重症患者中，肾脏替代治疗的时机仍存在争议。 方法：在这项多中心随机试验中，我们将重度急性肾损伤患者（肾病：改善全球预后[KDIGO]分类，3期[阶段范围从1至3，较高的阶段表明更严重的肾损伤]）分配为需要机械通气、儿茶酚胺输注、或两者均有，并且没有与早期或延迟肾脏替代治疗策略直接相关的潜在危及生命的肾衰竭并发症。采用早期策略，在随机化后立即开始肾脏替代治疗。采用延迟策略时，如果满足以下至少一项标准，则开始肾脏替代治疗：随机化后超过72小时重度高钾血症、代谢性酸中毒、肺水肿、血尿素氮水平高于112 mg/dl或少尿。主要结局为第60天的总生存期。 结果：共620例患者接受随机分组。早期策略组和延迟策略组第60天死亡率的Kaplan-Meier估计值无显著差异；早期策略组311例患者发生150例死亡（48.5%；95%置信区间[CI]，42.6至53.8），延迟策略组308例患者发生153例死亡（49.7%，95%CI，43.8至55.0；P = 0.79）。延迟策略组中总计151名患者(49%)未接受肾脏替代治疗。早期策略组导管相关血流感染率高于延迟策略组(10%vs. 5%，P = 0.03)。延迟策略组更早出现利尿（肾功能改善的标志物）(P < 0.001)。 结论：在一项涉及重度急性肾损伤重症患者的试验中，我们发现肾脏替代治疗早期和延迟策略之间死亡率无显著差异。延迟策略避免了相当数量患者的肾脏替代治疗需求。
Keywords: Humans; Middle Aged; Aged; Intensive Care Units; Severity of Illness Index; Follow-Up Studies; Kaplan-Meier Estimate; Time-to-Treatment; *Renal Replacement Therapy; Acute Kidney Injury/mortality/physiopathology/*therapy; Urine

Renal-Replacement Therapy in the Critically Ill--Does Timing Matter? - Mehta, Ravindra L (The New England journal of medicine, 2016)
危重病患者的肾脏替代治疗--时机是否重要？
Keywords: Humans; Critical Illness/*therapy; *Renal Replacement Therapy; Acute Kidney Injury/therapy

CLINICAL PRACTICE. Upper Gastrointestinal Bleeding Due to a Peptic Ulcer. - Laine, Loren (The New England journal of medicine, 2016)
临床实践。消化性溃疡导致的上消化道出血。
Keywords: Humans; Female; Middle Aged; *Endoscopy; Anti-Bacterial Agents/therapeutic use; Practice Guidelines as Topic; Anti-Inflammatory Agents, Non-Steroidal/adverse effects; Secondary Prevention; Breath Tests; Gastrointestinal Hemorrhage/diagnosis/etiology/*therapy; Helicobacter Infections/diagnosis/*drug therapy; Peptic Ulcer/*complications

The Sharing of Loss - Srivastava, Ranjana (The New England journal of medicine, 2016)
分享损失
Keywords: Humans; Female; *Interprofessional Relations; *Bereavement; *Death; Physician-Patient Relations; Physicians/*psychology

Patterns of Growth and Decline in Lung Function in Persistent Childhood Asthma - McGeachie, M. J.; Yates, K. P.; Zhou, X.; Guo, F.; Sternberg, A. L.; Van Natta, M. L.; Wise, R. A.; Szefler, S. J.; Sharma, S.; Kho, A. T.; Cho, M. H.; Croteau-Chonka, D. C.; et al. (The New England journal of medicine, 2016)
BACKGROUND: Tracking longitudinal measurements of growth and decline in lung function in patients with persistent childhood asthma may reveal links between asthma and subsequent chronic airflow obstruction. METHODS: We classified children with asthma according to four characteristic patterns of lung-function growth and decline on the basis of graphs showing forced expiratory volume in 1 second (FEV1), representing spirometric measurements performed from childhood into adulthood. Risk factors associated with abnormal patterns were also examined. To define normal values, we used FEV1 values from participants in the National Health and Nutrition Examination Survey who did not have asthma. RESULTS: Of the 684 study participants, 170 (25%) had a normal pattern of lung-function growth without early decline, and 514 (75%) had abnormal patterns: 176 (26%) had reduced growth and an early decline, 160 (23%) had reduced growth only, and 178 (26%) had normal growth and an early decline. Lower baseline values for FEV1, smaller bronchodilator response, airway hyperresponsiveness at baseline, and male sex were associated with reduced growth (P<0.001 for all comparisons). At the last spirometric measurement (mean [Â±SD] age, 26.0Â±1.8 years), 73 participants (11%) met Global Initiative for Chronic Obstructive Lung Disease spirometric criteria for lung-function impairment that was consistent with chronic obstructive pulmonary disease (COPD); these participants were more likely to have a reduced pattern of growth than a normal pattern (18% vs. 3%, P<0.001). CONCLUSIONS: Childhood impairment of lung function and male sex were the most significant predictors of abnormal longitudinal patterns of lung-function growth and decline. Children with persistent asthma and reduced growth of lung function are at increased risk for fixed airflow obstruction and possibly COPD in early adulthood.
持续性儿童哮喘肺功能的消长模式 背景：追踪持续性儿童哮喘患者肺功能的增长和下降的纵向测量可能揭示哮喘与随后的慢性气流阻塞之间的联系。 方法：我们根据肺功能生长和下降的四种特征模式，对哮喘儿童进行分类，基于图示1秒用力呼气容积(FEV1)，代表从儿童期到成年期进行的肺量计测量。还检查了与异常模式相关的风险因素。为了定义正常值，我们使用了美国国家健康与营养调查中未患哮喘的参与者的FEV1值。 结果：684例研究参与者中，170例(25%)肺功能生长模式正常，无早期下降，514例(75%)有异常模式：176例(26%)生长减少和早期下降，160例(23%)仅生长减少，178例(26%)生长正常和早期下降。FEV1较低的基线值、较小的支气管扩张剂反应、基线时的气道高反应性和男性性别与生长减缓相关（所有比较P < 0.001）。在末次肺量计测量时（平均[·±SD]年龄，26.0≦±1.8岁），73名参与者(11%)符合慢性阻塞性肺疾病全球倡议肺功能损害肺量计标准，与慢性阻塞性肺疾病(COPD)一致；这些受试者比正常模式更可能出现生长模式下降(18%vs. 3%，P < 0.001)。 结论：肺功能受损和男性是肺功能生长和下降异常纵向模式的最显著预测因素。持续性哮喘和肺功能生长减缓的儿童在成年早期发生固定气道阻塞和可能的COPD的风险增加。
Keywords: Humans; Female; Male; Longitudinal Studies; Young Adult; Adolescent; Risk Factors; Child; Child, Preschool; Kaplan-Meier Estimate; Sex Factors; Spirometry; Anti-Inflammatory Agents/*therapeutic use; Administration, Inhalation; Asthma/drug therapy/*physiopathology; Bronchodilator Agents/therapeutic use; Budesonide/therapeutic use; Forced Expiratory Volume; Lung/growth & development/*physiology; Nedocromil/therapeutic use

One-Year Outcomes in Caregivers of Critically Ill Patients - Cameron, Jill I.; Chu, Leslie M.; Matte, Andrea; Tomlinson, George; Chan, Linda; Thomas, Claire; Friedrich, Jan O.; Mehta, Sangeeta; Lamontagne, Francois; Levasseur, Melanie; Ferguson, Niall D.; Adhikari, Neill K. J.; et al. (The New England journal of medicine, 2016)
BACKGROUND: Few resources are available to support caregivers of patients who have survived critical illness; consequently, the caregivers' own health may suffer. We studied caregiver and patient characteristics to determine which characteristics were associated with caregivers' health outcomes during the first year after patient discharge from an intensive care unit (ICU). METHODS: We prospectively enrolled 280 caregivers of patients who had received 7 or more days of mechanical ventilation in an ICU. Using hospital data and self-administered questionnaires, we collected information on caregiver and patient characteristics, including caregiver depressive symptoms, psychological well-being, health-related quality of life, sense of control over life, and effect of providing care on other activities. Assessments occurred 7 days and 3, 6, and 12 months after ICU discharge. RESULTS: The caregivers' mean age was 53 years, 70% were women, and 61% were caring for a spouse. A large percentage of caregivers (67% initially and 43% at 1 year) reported high levels of depressive symptoms. Depressive symptoms decreased at least partially with time in 84% of the caregivers but did not in 16%. Variables that were significantly associated with worse mental health outcomes in caregivers were younger age, greater effect of patient care on other activities, less social support, less sense of control over life, and less personal growth. No patient variables were consistently associated with caregiver outcomes over time. CONCLUSIONS: In this study, most caregivers of critically ill patients reported high levels of depressive symptoms, which commonly persisted up to 1 year and did not decrease in some caregivers.
危重患者护理人员的一年结局 背景：可用于支持危重疾病患者的护理人员的资源很少；因此，护理人员自身的健康可能会受到影响。我们研究了护理人员和患者特征，以确定哪些特征与护理人员从重症监护室(ICU)出院后第一年的健康结局相关。 方法：我们前瞻性入选了280名在ICU接受7天或7天以上机械通气的患者的护理人员。使用医院数据和自填问卷，我们收集了有关护理人员和患者特征的信息，包括护理人员的抑郁症状、心理健康、健康相关生活质量、生活控制感以及对其他活动提供护理的影响。在离开ICU后7天以及3、6和12个月进行评估。 结果：照顾者的平均年龄为53岁，70%为女性，61%照顾配偶。大部分护理者（67%初始护理，43%第1年）报告了高水平的抑郁症状。84%的照料者的抑郁症状随时间推移至少部分减轻，但16%未减轻。与照顾者较差的心理健康结局显著相关的变量为年龄较小、患者护理对其他活动的影响较大、社会支持较少、对生活的控制感较低和个人成长较少。没有患者变量一致地与护理人员的结局随时间相关。 结论：在本研究中，大多数重症患者的照顾者报告了高水平的抑郁症状，通常持续长达1年，在某些照顾者中未下降。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Adult; Quality of Life; Stress, Psychological; Caregivers/*psychology; Critical Illness/*nursing; Depression/epidemiology/*etiology; Family/*psychology

Health as a Family Affair - Wittenberg, Eve; Prosser, Lisa A. (The New England journal of medicine, 2016)
家庭健康事务
Keywords: Humans; Adult; United States; *Caregivers/psychology/statistics & numerical data; *Family Health; *Home Nursing; Chronic Disease/*nursing

IMAGES IN CLINICAL MEDICINE. Metronidazole-Associated Encephalopathy. - Farmakiotis, Dimitrios; Zeluff, Barry (The New England journal of medicine, 2016)
临床药物图像。甲硝唑相关脑病。
Keywords: Humans; Male; Middle Aged; Bacteremia/etiology; Fatal Outcome; Brain Diseases/*chemically induced; Catheterization, Central Venous/adverse effects; Clostridium Infections/drug therapy; Dysarthria/chemically induced; Gait Disorders, Neurologic/chemically induced; Liver Cirrhosis/complications/congenital; Metronidazole/*adverse effects

Parenteral Nutrition in Critically Ill Children - Mehta, Nilesh M. (The New England journal of medicine, 2016)
危重病儿童的肠外营养
Keywords: Humans; Female; Male; Critical Illness/*therapy; *Parenteral Nutrition

Early versus Late Parenteral Nutrition in Critically Ill Children - Fivez, Tom; Kerklaan, Dorian; Mesotten, Dieter; Verbruggen, Sascha; Wouters, Pieter J.; Vanhorebeek, Ilse; Debaveye, Yves; Vlasselaers, Dirk; Desmet, Lars; Casaer, Michael P.; Garcia Guerra, Gonzalo; Hanot, Jan; et al. (The New England journal of medicine, 2016)
BACKGROUND: Recent trials have questioned the benefit of early parenteral nutrition in adults. The effect of early parenteral nutrition on clinical outcomes in critically ill children is unclear. METHODS: We conducted a multicenter, randomized, controlled trial involving 1440 critically ill children to investigate whether withholding parenteral nutrition for 1 week (i.e., providing late parenteral nutrition) in the pediatric intensive care unit (ICU) is clinically superior to providing early parenteral nutrition. Fluid loading was similar in the two groups. The two primary end points were new infection acquired during the ICU stay and the adjusted duration of ICU dependency, as assessed by the number of days in the ICU and as time to discharge alive from ICU. For the 723 patients receiving early parenteral nutrition, parenteral nutrition was initiated within 24 hours after ICU admission, whereas for the 717 patients receiving late parenteral nutrition, parenteral nutrition was not provided until the morning of the 8th day in the ICU. In both groups, enteral nutrition was attempted early and intravenous micronutrients were provided. RESULTS: Although mortality was similar in the two groups, the percentage of patients with a new infection was 10.7% in the group receiving late parenteral nutrition, as compared with 18.5% in the group receiving early parenteral nutrition (adjusted odds ratio, 0.48; 95% confidence interval [CI], 0.35 to 0.66). The mean (±SE) duration of ICU stay was 6.5±0.4 days in the group receiving late parenteral nutrition, as compared with 9.2±0.8 days in the group receiving early parenteral nutrition; there was also a higher likelihood of an earlier live discharge from the ICU at any time in the late-parenteral-nutrition group (adjusted hazard ratio, 1.23; 95% CI, 1.11 to 1.37). Late parenteral nutrition was associated with a shorter duration of mechanical ventilatory support than was early parenteral nutrition (P=0.001), as well as a smaller proportion of patients receiving renal-replacement therapy (P=0.04) and a shorter duration of hospital stay (P=0.001). Late parenteral nutrition was also associated with lower plasma levels of γ-glutamyltransferase and alkaline phosphatase than was early parenteral nutrition (P=0.001 and P=0.04, respectively), as well as higher levels of bilirubin (P=0.004) and C-reactive protein (P=0.006). CONCLUSIONS: In critically ill children, withholding parenteral nutrition for 1 week in the ICU was clinically superior to providing early parenteral nutrition.
危重病儿童早期与晚期肠外营养的比较 背景：近期试验对成人早期肠外营养的获益提出了质疑。尚不清楚早期肠外营养对重症儿童临床结局的影响。 方法：我们进行了一项多中心、随机化、对照试验，涉及1440例危重儿童，研究在儿科重症监护室(ICU)暂停肠外营养1周（即，提供晚期肠外营养）是否在临床上优于提供早期肠外营养。两组的液体负荷相似。两个主要终点为ICU住院期间获得的新感染和调整后的ICU依赖持续时间，评估指标为ICU住院天数和从ICU存活出院的时间。对于723例接受早期肠外营养的患者，在入住ICU后24小时内开始肠外营养，而对于717例接受晚期肠外营养的患者，直到入住ICU第8天早晨才提供肠外营养。在两组中，早期尝试肠内营养，并提供静脉微量营养素。 结果：尽管两组的死亡率相似，但接受晚期肠外营养组新发感染的患者百分比为10.7%，相比之下，接受早期肠外营养组为18.5%（调整后比值比，0.48；95%置信区间[CI]，0.35-0.66）。接受晚期肠外营养组的平均ICU停留时间为6.5Δ±0.4天，与之相比，接受早期肠外营养组的平均ICU停留时间为9.2Δ±0.8天；晚期肠外营养组在任何时间更有可能较早离开ICU（调整后的风险比，1.23；95%CI，1.11至1.37）。晚期肠外营养组的机械通气支持持续时间短于早期肠外营养组(P = 0.001)，接受肾脏替代治疗的患者比例较小(P = 0.04)，住院时间较短(P = 0.001)。与早期肠外营养相比，晚期肠外营养还与血清³-谷氨酰转移酶和碱性磷酸酶水平较低（分别为P = 0.001和P = 0.04），以及胆红素(P = 0.004)和C-反应蛋白(P = 0.006)水平较高相关。 结论：在危重儿童中，在ICU中暂停肠外营养1周在临床上优于提供早期肠外营养。
Keywords: Humans; Female; Male; Time Factors; Length of Stay; Respiration, Artificial; Child; Infant; Child, Preschool; Fluid Therapy; Kaplan-Meier Estimate; Enteral Nutrition; Critical Illness/mortality/*therapy; Intensive Care Units, Pediatric; *Parenteral Nutrition; gamma-Glutamyltransferase/blood; Infections/epidemiology

Outcomes of Two Trials of Oxygen-Saturation Targets in Preterm Infants - Tarnow-Mordi, William; Stenson, Ben; Kirby, Adrienne; Juszczak, Edmund; Donoghoe, Mark; Deshpande, Sanjeev; Morley, Colin; King, Andrew; Doyle, Lex W.; Fleck, Brian W.; Davis, Peter G.; Halliday, Henry L.; et al. (The New England journal of medicine, 2016)
BACKGROUND: The safest ranges of oxygen saturation in preterm infants have been the subject of debate. METHODS: In two trials, conducted in Australia and the United Kingdom, infants born before 28 weeks' gestation were randomly assigned to either a lower (85 to 89%) or a higher (91 to 95%) oxygen-saturation range. During enrollment, the oximeters were revised to correct a calibration-algorithm artifact. The primary outcome was death or disability at a corrected gestational age of 2 years; this outcome was evaluated among infants whose oxygen saturation was measured with any study oximeter in the Australian trial and those whose oxygen saturation was measured with a revised oximeter in the U.K. trial. RESULTS: After 1135 infants in Australia and 973 infants in the United Kingdom had been enrolled in the trial, an interim analysis showed increased mortality at a corrected gestational age of 36 weeks, and enrollment was stopped. Death or disability in the Australian trial (with all oximeters included) occurred in 247 of 549 infants (45.0%) in the lower-target group versus 217 of 545 infants (39.8%) in the higher-target group (adjusted relative risk, 1.12; 95% confidence interval [CI], 0.98 to 1.27; P=0.10); death or disability in the U.K. trial (with only revised oximeters included) occurred in 185 of 366 infants (50.5%) in the lower-target group versus 164 of 357 infants (45.9%) in the higher-target group (adjusted relative risk, 1.10; 95% CI, 0.97 to 1.24; P=0.15). In post hoc combined, unadjusted analyses that included all oximeters, death or disability occurred in 492 of 1022 infants (48.1%) in the lower-target group versus 437 of 1013 infants (43.1%) in the higher-target group (relative risk, 1.11; 95% CI, 1.01 to 1.23; P=0.02), and death occurred in 222 of 1045 infants (21.2%) in the lower-target group versus 185 of 1045 infants (17.7%) in the higher-target group (relative risk, 1.20; 95% CI, 1.01 to 1.43; P=0.04). In the group in which revised oximeters were used, death or disability occurred in 287 of 580 infants (49.5%) in the lower-target group versus 248 of 563 infants (44.0%) in the higher-target group (relative risk, 1.12; 95% CI, 0.99 to 1.27; P=0.07), and death occurred in 144 of 587 infants (24.5%) versus 99 of 586 infants (16.9%) (relative risk, 1.45; 95% CI, 1.16 to 1.82; P=0.001). CONCLUSIONS: Use of an oxygen-saturation target range of 85 to 89% versus 91 to 95% resulted in nonsignificantly higher rates of death or disability at 2 years in each trial but in significantly increased risks of this combined outcome and of death alone in post hoc combined analyses.
早产儿血氧饱和度目标的两项试验结果 背景：早产儿最安全的氧饱和度范围一直是争论的主题。 方法：在澳大利亚和英国进行的两项试验中，28周前出生的婴儿被随机分配到较低（85至89%）或较高（91至95%）氧饱和度范围。入组期间，对血氧仪进行了修订，以校正校准算法伪影。主要结局为校正胎龄为2岁时的死亡或残疾；在澳大利亚试验中使用任何研究血氧仪测量氧饱和度的婴儿和英国试验中使用改良血氧仪测量氧饱和度的婴儿中评价该结局。 结果：澳大利亚1135名婴儿和英国973名婴儿入组试验后，中期分析显示校正胎龄36周时死亡率增加，停止入组。在澳大利亚试验中（包括所有的血氧测量仪），低目标组549名婴儿中有247名婴儿(45.0%)死亡或残疾，而高目标组545名婴儿中有217名婴儿(39.8%)死亡或残疾（校正后的相对风险，1.12；95%置信区间[CI]，0.98-1.27；P = 0.10）；在英国试验中（仅包括修订的血氧测量仪），较低目标组366名婴儿中有185名婴儿(50.5%)发生死亡或残疾，而较高目标组357名婴儿中有164名婴儿(45.9%)发生死亡或残疾（调整后的相对风险，1.10；95%CI，0.97-1.24；P = 0.15）。在包括所有血氧仪的事后合并、未调整分析中，低目标组的492/1022名婴儿(48.1%)与高目标组的437/1013名婴儿(43.1%)发生了死亡或残疾（相对风险，1.11；95%CI，1.01至1.23；P = 0.02），低目标组1045名婴儿中有222名婴儿死亡(21.2%)，而高目标组1045名婴儿中有185名婴儿死亡(17.7%)（相对风险，1.20；95%CI，1.01至1.43；P = 0.04）。在使用改良型血氧测量仪的组中，较低目标组的287/580名婴儿(49.5%)发生死亡或残疾，而较高目标组的248/563名婴儿(44.0%)发生死亡或残疾（相对风险，1.12；95%CI，0.99-1.27；P = 0.07），587名婴儿中有144名婴儿死亡(24.5%)，586名婴儿中有99名婴儿死亡(16.9%)（相对风险，1.45；95%CI，1.16至1.82；P = 0.001）。 结论：在每项试验中，使用氧饱和度目标范围85-89%vs. 91-95%导致2年时死亡或残疾率非显著性升高，但在事后综合分析中，该综合结局和单独死亡的风险显著升高。
Keywords: Humans; Female; Male; Oximetry; United Kingdom; Infant; Infant, Newborn; Child, Preschool; Australia; Oxygen/*blood; Risk; *Infant Mortality; Developmental Disabilities/*epidemiology; Infant, Extremely Premature/*blood; Oxygen Inhalation Therapy/adverse effects/*methods

IMAGES IN CLINICAL MEDICINE. Percutaneous Rotational Pulmonary Thrombectomy. - Oguzhan, Abdurrahman (The New England journal of medicine, 2016)
临床药物图像。经皮旋转肺血栓切除术。
Keywords: Humans; Female; Aged; Thrombectomy/*methods; Fibrinolytic Agents/therapeutic use; Combined Modality Therapy; Electrocardiography; Radiography; Fatal Outcome; Pulmonary Embolism/diagnostic imaging/drug therapy/*surgery; Tissue Plasminogen Activator/therapeutic use

IMAGES IN CLINICAL MEDICINE. Air Bronchogram. - Natt, Bhupinder; Raz, Yuval (The New England journal of medicine, 2015)
临床药物图像。空气支气管造影。
Keywords: Humans; Female; Adult; Lung/*diagnostic imaging; *Bronchography; Kidney Failure, Chronic/complications; Pneumonia/diagnostic imaging/etiology; Respiratory Distress Syndrome/*diagnostic imaging/etiology

CASE RECORDS of the MASSACHUSETTS GENERAL HOSPITAL. Case 39-2015. A 22-Year-Old Man with Hypoxemia and Shock. - Shenoy, Erica S.; Lai, Peggy S.; Shepard, Jo-Anne O.; Kradin, Richard L. (The New England journal of medicine, 2015)
Case records of Massachusetts General Hospital. Case 21-2016. 32 year old male with unresponsive status.
Keywords: Humans; Male; Young Adult; Diagnosis, Differential; Polymerase Chain Reaction; Radiography; Fatal Outcome; Shock/etiology; Hypoxia/etiology; Lung/diagnostic imaging/*pathology; Respiratory Insufficiency/etiology; Herpesvirus 2, Human; Influenza A Virus, H3N2 Subtype/*isolation & purification; Influenza, Human/complications/*diagnosis/virology; Pneumonia, Staphylococcal/*diagnosis/etiology; Pneumonia, Viral/etiology/virology

IMAGES IN CLINICAL MEDICINE. Cullen's and Grey Turner's Signs in Acute Pancreatitis. - Valette, Xavier; du Cheyron, Damien (The New England journal of medicine, 2015)
临床医学图像。Cullen’s和Grey Turner’s Signs in Acute Pancreatitis.
Keywords: Humans; Male; Middle Aged; Fatal Outcome; Jaundice/etiology; Ecchymosis/*etiology; Pancreatitis, Acute Necrotizing/complications/*diagnosis

Acetaminophen for Fever in Critically Ill Patients with Suspected Infection - Young, Paul; Saxena, Manoj; Bellomo, Rinaldo; Freebairn, Ross; Hammond, Naomi; van Haren, Frank; Holliday, Mark; Henderson, Seton; Mackle, Diane; McArthur, Colin; McGuinness, Shay; Myburgh, John; et al. (The New England journal of medicine, 2015)
BACKGROUND: Acetaminophen is a common therapy for fever in patients in the intensive care unit (ICU) who have probable infection, but its effects are unknown. METHODS: We randomly assigned 700 ICU patients with fever (body temperature, â‰¥38Â°C) and known or suspected infection to receive either 1 g of intravenous acetaminophen or placebo every 6 hours until ICU discharge, resolution of fever, cessation of antimicrobial therapy, or death. The primary outcome was ICU-free days (days alive and free from the need for intensive care) from randomization to day 28. RESULTS: The number of ICU-free days to day 28 did not differ significantly between the acetaminophen group and the placebo group: 23 days (interquartile range, 13 to 25) among patients assigned to acetaminophen and 22 days (interquartile range, 12 to 25) among patients assigned to placebo (Hodges-Lehmann estimate of absolute difference, 0 days; 96.2% confidence interval [CI], 0 to 1; P=0.07). A total of 55 of 345 patients in the acetaminophen group (15.9%) and 57 of 344 patients in the placebo group (16.6%) had died by day 90 (relative risk, 0.96; 95% CI, 0.66 to 1.39; P=0.84). CONCLUSIONS: Early administration of acetaminophen to treat fever due to probable infection did not affect the number of ICU-free days.
对乙酰氨基酚治疗疑似感染的危重患者的发热 背景：对乙酰氨基酚是重症监护室 (ICU) 可能感染患者发热的常用疗法，但其作用尚不清楚。 方法：我们随机分配700例有发热（体温，â‰¥38Â°C）和已知或疑似感染的 ICU 患者每6小时接受 1 g 静脉注射对乙酰氨基酚或安慰剂，直至离开ICU、发热消退、停止抗菌治疗或死亡。主要结局为从随机化至第28天的无 ICU 天数（存活天数，无需重症监护）。 结果：对乙酰氨基酚组和安慰剂组之间至第28天的无 ICU 天数无显著差异：分配至对乙酰氨基酚组的患者为23天（四分位距，13-25），分配至安慰剂组的患者为22天（四分位距，12-25）（绝对差异的 Hodges-Lehmann 估计，0天；96.2%置信区间 [CI]，0-1；P = 0.07）。到第90天，对乙酰氨基酚组345例患者中共有55例 (15.9%) 和安慰剂组344例患者中共有57例 (16.6%) 死亡（相对风险，0.96；95%CI，0.66-1.39；P = 0.84）。 结论：早期给予对乙酰氨基酚治疗可能感染引起的发热并不影响无 ICU 天数。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Double-Blind Method; Aged; Critical Illness; Intensive Care Units; Length of Stay; Kaplan-Meier Estimate; Acetaminophen/*therapeutic use; Body Temperature/drug effects; Fever/*drug therapy/etiology; Infections/complications/*drug therapy

Resolvin Infectious Inflammation by Targeting the Host Response - Lee, Craig R.; Zeldin, Darryl C. (The New England journal of medicine, 2015)
通过靶向宿主反应解决感染性炎症
Keywords: Humans; Animals; Disease Models, Animal; Mice; Sepsis; Cells, Cultured; Atorvastatin/pharmacology/therapeutic use; Docosahexaenoic Acids/*biosynthesis/physiology/therapeutic use; Endothelial Cells/physiology; Escherichia coli Infections/drug therapy/*immunology; Hydroxymethylglutaryl-CoA Reductase Inhibitors/pharmacology/therapeutic use; Inflammation/drug therapy/etiology/*metabolism; Neutrophils/physiology; Phagocytosis/drug effects

CASE RECORDS of the MASSACHUSETTS GENERAL HOSPITAL. Case 32-2015. A 57-Year-Old Man with Severe Pneumonia and Hypoxemic Respiratory Failure. - Mansour, Michael K.; Ackman, Jeanne B.; Branda, John A.; Kradin, Richard L. (The New England journal of medicine, 2015)
马萨诸塞州总医院病例记录。病例32-2015。一名57岁的男性，患有重度肺炎和低氧性呼吸衰竭。
Keywords: Humans; Male; Middle Aged; Anti-Bacterial Agents/therapeutic use; Liver Cirrhosis/complications; Necrosis; Radiography; Fatal Outcome; Bronchoscopy; Respiratory Insufficiency/etiology; Fever/etiology; Blastomyces/*isolation & purification; Blastomycosis/complications/*diagnosis; Community-Acquired Infections/diagnosis/drug therapy; Delayed Diagnosis; Kidney Tubules/pathology; Lung/diagnostic imaging/microbiology/*pathology; Pneumonia/*diagnosis/drug therapy/etiology; Travel

Invasive Candidiasis - Kullberg, Bart Jan; Arendrup, Maiken C. (The New England journal of medicine, 2015)
侵袭性念珠菌病
Keywords: Humans; *Candidiasis, Invasive/diagnosis/epidemiology/microbiology/therapy; Antifungal Agents/*therapeutic use; Candida/isolation & purification; Catheter-Related Infections/therapy; Drug Resistance, Fungal

Maintenance Intravenous Fluids in Acutely Ill Patients - Moritz, Michael L.; Ayus, Juan C. (The New England journal of medicine, 2015)
急性病患者中的维持静脉补液
Keywords: Humans; Female; Male; Hypotonic Solutions; Infusions, Intravenous; Acute Disease; *Fluid Therapy; Arginine Vasopressin/physiology; Hyponatremia/*therapy; Saline Solution, Hypertonic/administration & dosage; Water-Electrolyte Balance

Intravascular Complications of Central Venous Catheterization by Insertion Site - Parienti, Jean-Jacques; Mongardon, Nicolas; Mégarbane, Bruno; Mira, Jean-Paul; Kalfon, Pierre; Gros, Antoine; Marqué, Sophie; Thuong, Marie; Pottier, Véronique; Ramakers, Michel; Savary, Benoît; Seguin, Amélie; et al. (The New England journal of medicine, 2015)
BACKGROUND: Three anatomical sites are commonly used to insert central venous catheters, but insertion at each site has the potential for major complications. METHODS: In this multicenter trial, we randomly assigned nontunneled central venous catheterization in patients in the adult intensive care unit (ICU) to the subclavian, jugular, or femoral vein (in a 1:1:1 ratio if all three insertion sites were suitable [three-choice scheme] and in a 1:1 ratio if two sites were suitable [two-choice scheme]). The primary outcome measure was a composite of catheter-related bloodstream infection and symptomatic deep-vein thrombosis. RESULTS: A total of 3471 catheters were inserted in 3027 patients. In the three-choice comparison, there were 8, 20, and 22 primary outcome events in the subclavian, jugular, and femoral groups, respectively (1.5, 3.6, and 4.6 per 1000 catheter-days; P=0.02). In pairwise comparisons, the risk of the primary outcome was significantly higher in the femoral group than in the subclavian group (hazard ratio, 3.5; 95% confidence interval [CI], 1.5 to 7.8; P=0.003) and in the jugular group than in the subclavian group (hazard ratio, 2.1; 95% CI, 1.0 to 4.3; P=0.04), whereas the risk in the femoral group was similar to that in the jugular group (hazard ratio, 1.3; 95% CI, 0.8 to 2.1; P=0.30). In the three-choice comparison, pneumothorax requiring chest-tube insertion occurred in association with 13 (1.5%) of the subclavian-vein insertions and 4 (0.5%) of the jugular-vein insertions. CONCLUSIONS: In this trial, subclavian-vein catheterization was associated with a lower risk of bloodstream infection and symptomatic thrombosis and a higher risk of pneumothorax than jugular-vein or femoral-vein catheterization.
按置入部位列出的中心静脉导管插入的血管内并发症 背景：通常在3个解剖部位插入中心静脉导管，但每个部位插入都有可能发生严重并发症。 方法：在这项多中心试验中，我们将成人重症监护室(ICU)患者的非隧道式中心静脉导管插入术随机分配至锁骨下、颈静脉、或股静脉（如果三个插入部位均适合，比例为1:1:1[三选方案]；如果两个部位都适合，比例为1:1[两选方案]）。主要结局指标是导管相关血流感染和症状性深静脉血栓形成的复合终点。 结果：在3027例患者中总计插入了3471根导管。在三选比较中，锁骨下组、颈静脉组和股静脉组分别发生了8、20和22起主要结局事件（每1000导管日1.5、3.6和4.6起事件；P = 0.02）。在成对比较中，主要结局的风险在股骨组显著高于锁骨下组（风险比，3.5；95%置信区间[CI]，1.5至7.8；P = 0.003），在颈静脉组显著高于锁骨下组（风险比，2.1；95%CI，1.0至4.3；P = 0.04）。然而，股骨组的风险与颈静脉组相似（风险比1.3；95%CI 0.8-2.1；P = 0.30）。在三选比较中，需要胸管插入的气胸与锁骨下静脉插入13例(1.5%)和颈静脉插入4例(0.5%)相关。 结论：在本试验中，锁骨下静脉置管与颈静脉或股静脉置管相比，血流感染和症状性血栓形成的风险较低，气胸的风险较高。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Risk; Sepsis/*etiology; Catheter-Related Infections/*etiology; Catheterization, Central Venous/adverse effects/*methods; Femoral Vein; Jugular Veins; Subclavian Vein; Venous Thrombosis/*etiology

Ischemic Limb Gangrene with Pulses - Warkentin, Theodore E. (The New England journal of medicine, 2015)
伴有脉冲的缺血性肢体坏疽
Keywords: Humans; Diagnosis, Differential; Extremities/*blood supply; Microcirculation; Disseminated Intravascular Coagulation/complications; *Gangrene/etiology/microbiology/pathology/therapy; Pulse; Venous Thrombosis/complications

Electrolyte and Acid-Base Disturbances in Patients with Diabetes Mellitus - Palmer, Biff F.; Clegg, Deborah J. (The New England journal of medicine, 2015)
糖尿病患者的电解质和酸碱平衡紊乱
Keywords: Humans; Acid-Base Imbalance/*metabolism; Acidosis, Renal Tubular/metabolism; Acidosis/etiology; Diabetes Complications/metabolism; Diabetes Mellitus/*metabolism; Diabetic Ketoacidosis/therapy; Potassium/blood; Sodium/blood; Water-Electrolyte Imbalance/*metabolism

Human Infection with a Novel Avian Influenza A(H5N6) Virus - Yang, Zi-Feng; Mok, Chris K. P.; Peiris, Joseph S. M.; Zhong, Nan-Shan (The New England journal of medicine, 2015)
人感染新型禽流感a(H5N6)病毒
Keywords: Humans; Male; Middle Aged; Animals; China; Radiography; Lung/diagnostic imaging/pathology; Influenza A virus/classification/isolation & purification; Influenza in Birds; Influenza, Human/diagnosis/therapy/*virology; Poultry

CASE RECORDS of the MASSACHUSETTS GENERAL HOSPITAL. Case 20-2015. A Newborn Girl with Hypotension, Coagulopathy, Anemia, and Hyperbilirubinemia. - Roumiantsev, Serguei; Shah, Uzma; Westra, Sjirk J.; Misdraji, Joseph (The New England journal of medicine, 2015)
马萨诸塞州总医院病例记录。病例20-2015。低血压、凝血障碍、贫血和高胆红素血症新生儿。
Keywords: Humans; Female; Diagnosis, Differential; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Brain/pathology; Hypotension/etiology; Anemia/etiology; Blood Chemical Analysis; Blood Coagulation Disorders/drug therapy; Hematologic Diseases/diagnosis; Hemochromatosis/complications/*diagnosis; Hyperbilirubinemia/etiology; Liver/*pathology; Placenta/*pathology; Salivary Gland Diseases/complications/diagnosis; Sepsis/diagnosis

Permissive Underfeeding or Standard Enteral Feeding in Critically Ill Adults - Arabi, Yaseen M.; Aldawood, Abdulaziz S.; Haddad, Samir H.; Al-Dorzi, Hasan M.; Tamim, Hani M.; Jones, Gwynne; Mehta, Sangeeta; McIntyre, Lauralyn; Solaiman, Othman; Sakkijha, Maram H.; Sadat, Musharaf; Afesh, Lara (The New England journal of medicine, 2015)
BACKGROUND: The appropriate caloric goal for critically ill adults is unclear. We evaluated the effect of restriction of nonprotein calories (permissive underfeeding), as compared with standard enteral feeding, on 90-day mortality among critically ill adults, with maintenance of the full recommended amount of protein in both groups. METHODS: At seven centers, we randomly assigned 894 critically ill adults with a medical, surgical, or trauma admission category to permissive underfeeding (40 to 60% of calculated caloric requirements) or standard enteral feeding (70 to 100%) for up to 14 days while maintaining a similar protein intake in the two groups. The primary outcome was 90-day mortality. RESULTS: Baseline characteristics were similar in the two groups; 96.8% of the patients were receiving mechanical ventilation. During the intervention period, the permissive-underfeeding group received fewer mean (±SD) calories than did the standard-feeding group (835±297 kcal per day vs. 1299±467 kcal per day, P<0.001; 46±14% vs. 71±22% of caloric requirements, P<0.001). Protein intake was similar in the two groups (57±24 g per day and 59±25 g per day, respectively; P=0.29). The 90-day mortality was similar: 121 of 445 patients (27.2%) in the permissive-underfeeding group and 127 of 440 patients (28.9%) in the standard-feeding group died (relative risk with permissive underfeeding, 0.94; 95% confidence interval [CI], 0.76 to 1.16; P=0.58). No serious adverse events were reported; there were no significant between-group differences with respect to feeding intolerance, diarrhea, infections acquired in the intensive care unit (ICU), or ICU or hospital length of stay. CONCLUSIONS: Enteral feeding to deliver a moderate amount of nonprotein calories to critically ill adults was not associated with lower mortality than that associated with planned delivery of a full amount of nonprotein calories.
危重成人中的允许性喂养不足或标准肠内喂养 背景：目前尚不清楚危重成人患者的适当热量目标。我们评估了与标准肠内喂养相比，限制非蛋白质卡路里（允许的喂养不足）对危重成人90天死亡率的影响，两组均维持完整的推荐蛋白质量。 方法：在7个中心，我们将894例入院分类为内科、外科或创伤的危重成人随机分配至允许低摄食（计算的热量需求的40-60%）或标准肠内喂养(70-100%)，最长14天，同时两组维持相似的蛋白质摄入。主要结局为90天死亡率。 结果：两组的基线特征相似；96.8%的患者正在接受机械通气。在干预期间，允许-喂养不足组比标准喂养组接受更少的平均卡路里(≦±SD)（每天835≦±297 kcal与每天1299≦±467 kcal，P < 0.001；46≦±14%与71≦±22%卡路里需求，P < 0.001）。两组的蛋白质摄入量相似（分别为57τ±24 g/天和59τ±25 g/天；P = 0.29）。90天死亡率相似：允许-喂养不足组的121/445例患者(27.2%)和标准喂养组的127/440例患者(28.9%)死亡（允许-喂养不足的相对风险，0.94；95%置信区间[CI]，0.76-1.16；P = 0.58）。未报告严重不良事件；在喂养不耐受、腹泻、重症监护室(ICU)获得性感染或ICU或住院时间方面，没有显著的组间差异。 结论：与计划输送足量非蛋白卡路里相比，为危重成人输送中等量非蛋白卡路里的肠内喂养与死亡率更低无关。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Length of Stay; Adult; Respiration, Artificial; Kaplan-Meier Estimate; *Caloric Restriction; Critical Illness/mortality/*therapy; Energy Intake; *Enteral Nutrition/methods; Lipids/blood; Nutritional Requirements; Proteins/administration & dosage

Videos in clinical medicine. Noninvasive positive-pressure ventilation. - Kelly, Christopher R.; Higgins, Andrew R.; Chandra, Subani (2015)
临床医学视频。无创正压通气。
Keywords: Humans; Respiratory Insufficiency/*therapy; Contraindications; Positive-Pressure Respiration/instrumentation/*methods

Vasopressin antagonists - Berl, Tomas (The New England journal of medicine, 2015)
血管加压素拮抗剂
Keywords: Humans; History, 21st Century; Practice Guidelines as Topic; History, 19th Century; History, 20th Century; Sodium/blood; Antidiuretic Hormone Receptor Antagonists/adverse effects/pharmacokinetics/*pharmacology/*therapeutic use; Hyponatremia/blood/*drug therapy; Vasopressins/history/*physiology

Saving lives with high-flow nasal oxygen - Matthay, Michael A. (The New England journal of medicine, 2015)
高流量鼻氧抢救生命
Keywords: Humans; Female; Male; Positive-Pressure Respiration/*instrumentation; Oxygen/*administration & dosage; Respiratory Distress Syndrome/*therapy

High-flow oxygen through nasal cannula in acute hypoxemic respiratory failure - Frat, Jean-Pierre; Thille, Arnaud W.; Mercat, Alain; Girault, Christophe; Ragot, Stéphanie; Perbet, Sébastien; Prat, Gwénael; Boulain, Thierry; Morawiec, Elise; Cottereau, Alice; Devaquet, Jérôme; Nseir, Saad; et al. (The New England journal of medicine, 2015)
BACKGROUND: Whether noninvasive ventilation should be administered in patients with acute hypoxemic respiratory failure is debated. Therapy with high-flow oxygen through a nasal cannula may offer an alternative in patients with hypoxemia. METHODS: We performed a multicenter, open-label trial in which we randomly assigned patients without hypercapnia who had acute hypoxemic respiratory failure and a ratio of the partial pressure of arterial oxygen to the fraction of inspired oxygen of 300 mm Hg or less to high-flow oxygen therapy, standard oxygen therapy delivered through a face mask, or noninvasive positive-pressure ventilation. The primary outcome was the proportion of patients intubated at day 28; secondary outcomes included all-cause mortality in the intensive care unit and at 90 days and the number of ventilator-free days at day 28. RESULTS: A total of 310 patients were included in the analyses. The intubation rate (primary outcome) was 38% (40 of 106 patients) in the high-flow-oxygen group, 47% (44 of 94) in the standard group, and 50% (55 of 110) in the noninvasive-ventilation group (P=0.18 for all comparisons). The number of ventilator-free days at day 28 was significantly higher in the high-flow-oxygen group (24±8 days, vs. 22±10 in the standard-oxygen group and 19±12 in the noninvasive-ventilation group; P=0.02 for all comparisons). The hazard ratio for death at 90 days was 2.01 (95% confidence interval [CI], 1.01 to 3.99) with standard oxygen versus high-flow oxygen (P=0.046) and 2.50 (95% CI, 1.31 to 4.78) with noninvasive ventilation versus high-flow oxygen (P=0.006). CONCLUSIONS: In patients with nonhypercapnic acute hypoxemic respiratory failure, treatment with high-flow oxygen, standard oxygen, or noninvasive ventilation did not result in significantly different intubation rates. There was a significant difference in favor of high-flow oxygen in 90-day mortality.
急性低氧性呼吸衰竭中经鼻插管的高流量氧气 背景：急性低氧性呼吸衰竭患者是否应给予无创通气治疗仍有争议。经鼻插管的高流量氧气治疗可为低氧血症患者提供替代治疗。 方法：我们进行了一项多中心、开放标签试验，其中我们将无高碳酸血症且伴有急性低氧性呼吸衰竭且动脉血氧分压与吸入氧浓度之比≤300 mmHg的患者随机分配至高流量氧疗组，通过面罩或无创正压通气进行标准氧疗。主要结局为第28天时插管的患者比例；次要结局包括重症监护室和90天时的全因死亡率以及第28天时无呼吸机使用天数。 结果：共有310例患者纳入分析。高流量氧组的插管率（主要结局）为38%（106例患者中的40例），标准组为47%（94例中的44例），无创通气组为50%（110例中的55例）（所有比较均为P = 0.18）。高流量氧气组第28天的无呼吸机天数显著更高（标准氧气组24 μm±8天vs. 22 μm±10天，无创通气组19 μm±12天；所有比较均为P = 0.02）。标准氧气与高流量氧气组90天时死亡的风险比为2.01（95%置信区间[CI]，1.01至3.99）(P = 0.046)，无创通气与高流量氧气组90天时死亡的风险比为2.50（95%CI，1.31至4.78）(P = 0.006)。 结论：在非高碳酸血性急性低氧性呼吸衰竭患者中，高流量氧、标准氧或无创通气治疗未导致显著不同的插管率。90天死亡率存在显著差异，支持高流量氧。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Kaplan-Meier Estimate; Acute Disease; Positive-Pressure Respiration/*instrumentation; Hypoxia/etiology; Oxygen/*administration & dosage; Intubation, Intratracheal/statistics & numerical data; Oxygen Inhalation Therapy/instrumentation/*methods; Respiratory Insufficiency/complications/mortality/*therapy

Increasing incidence of the neonatal abstinence syndrome in U.S. neonatal ICUs. - Tolia, Veeral N.; Patrick, Stephen W.; Bennett, Monica M.; Murthy, Karna; Sousa, John; Smith, P. Brian; Clark, Reese H.; Spitzer, Alan R. (The New England journal of medicine, 2015)
BACKGROUND: The incidence of the neonatal abstinence syndrome, a drug-withdrawal syndrome that most commonly occurs after in utero exposure to opioids, is known to have increased during the past decade. However, recent trends in the incidence of the syndrome and changes in demographic characteristics and hospital treatment of these infants have not been well characterized. METHODS: Using multiple cross-sectional analyses and a deidentified data set, we analyzed data from infants with the neonatal abstinence syndrome from 2004 through 2013 in 299 neonatal intensive care units (NICUs) across the United States. We evaluated trends in incidence and health care utilization and changes in infant and maternal clinical characteristics. RESULTS: Among 674,845 infants admitted to NICUs, we identified 10,327 with the neonatal abstinence syndrome. From 2004 through 2013, the rate of NICU admissions for the neonatal abstinence syndrome increased from 7 cases per 1000 admissions to 27 cases per 1000 admissions; the median length of stay increased from 13 days to 19 days (P<0.001 for both trends). The total percentage of NICU days nationwide that were attributed to the neonatal abstinence syndrome increased from 0.6% to 4.0% (P<0.001 for trend), with eight centers reporting that more than 20% of all NICU days were attributed to the care of these infants in 2013. Infants increasingly received pharmacotherapy (74% in 2004-2005 vs. 87% in 2012-2013, P<0.001 for trend), with morphine the most commonly used drug (49% in 2004 vs. 72% in 2013, P<0.001 for trend). CONCLUSIONS: From 2004 through 2013, the neonatal abstinence syndrome was responsible for a substantial and growing portion of resources dedicated to critically ill neonates in NICUs nationwide.
美国新生儿ICU中新生儿戒断综合征的发生率增加。 背景：已知在过去十年中，新生儿戒断综合征（一种最常在子宫内暴露于阿片类药物后发生的药物戒断综合征）的发生率增加。然而，综合征发病率的近期趋势以及这些婴儿的人口统计学特征和医院治疗的变化尚未得到很好的描述。 方法：使用多横断面分析和去身份识别数据集，我们分析了2004-2013年美国299家新生儿重症监护室(NICU)的新生儿戒断综合征婴儿数据。我们评估了发生率和医疗保健利用以及婴儿和母亲临床特征变化的趋势。 结果：在NICU收治的674,845例婴儿中，我们确定了10,327例新生儿戒断综合征。从2004年至2013年，因新生儿戒断综合征入住NICU的比率从7例/1000人增加至27例/1000人；中位住院时间从13天增加至19天（两种趋势均为P < 0.001）。全国范围内归因于新生儿戒断综合征的NICU总天数百分比从0.6%增加至4.0%（趋势P < 0.001），8个中心报告，2013年超过20%的所有NICU天数归因于这些婴儿的护理。越来越多的婴儿接受了药物治疗（2004-2005为74%，2012-2013为87%，趋势P < 0.001），吗啡是最常用的药物（2004年为49%，2013年为72%，趋势P < 0.001）。 结论：2004-2013年，新生儿戒断综合征是NICU中专门用于危重新生儿的大量且不断增长的全国资源的原因。
Keywords: Humans; Cohort Studies; Infant, Newborn; Gestational Age; Incidence; Cross-Sectional Studies; United States/epidemiology; Datasets as Topic; Intensive Care Units, Neonatal/*statistics & numerical data; Health Resources/*statistics & numerical data/trends; Length of Stay/trends; Neonatal Abstinence Syndrome/*epidemiology; Patient Admission/trends

Images in clinical medicine. Trapped lung. - Albores, Jeffrey; Wang, Tisha (The New England journal of medicine, 2015)
临床医学图像。肺部滞留。
Keywords: Humans; Female; Middle Aged; Tomography, X-Ray Computed; Lung/*diagnostic imaging/pathology; Kidney Failure, Chronic/complications; Hydrothorax/*diagnostic imaging/etiology; Lung Compliance; Pleura/diagnostic imaging/*pathology; Pneumothorax/*diagnostic imaging/etiology

Clinical problem-solving. Sick as a dog. - Foster, Clayton L.; Mould, Kara; Reynolds, Paul; Simonian, Philip L.; Erlandson, Kristine M. (The New England journal of medicine, 2015)
临床问题解决。像狗一样生病。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Animals; Pseudomonas/isolation & purification; Radiography; Dyspnea/etiology; Lung/diagnostic imaging/pathology; Fever/etiology; Myalgia/etiology; Diagnostic Errors; Dogs/microbiology; Plague/complications/*diagnosis/transmission; Pneumonia, Bacterial/diagnosis; Yersinia pestis/*isolation & purification

Systemic inflammatory response syndrome criteria in defining severe sepsis - Kaukonen, Kirsi-Maija; Bailey, Michael; Pilcher, David; Cooper, D. Jamie; Bellomo, Rinaldo (The New England journal of medicine, 2015)
BACKGROUND: The consensus definition of severe sepsis requires suspected or proven infection, organ failure, and signs that meet two or more criteria for the systemic inflammatory response syndrome (SIRS). We aimed to test the sensitivity, face validity, and construct validity of this approach. METHODS: We studied data from patients from 172 intensive care units in Australia and New Zealand from 2000 through 2013. We identified patients with infection and organ failure and categorized them according to whether they had signs meeting two or more SIRS criteria (SIRS-positive severe sepsis) or less than two SIRS criteria (SIRS-negative severe sepsis). We compared their characteristics and outcomes and assessed them for the presence of a step increase in the risk of death at a threshold of two SIRS criteria. RESULTS: Of 1,171,797 patients, a total of 109,663 had infection and organ failure. Among these, 96,385 patients (87.9%) had SIRS-positive severe sepsis and 13,278 (12.1%) had SIRS-negative severe sepsis. Over a period of 14 years, these groups had similar characteristics and changes in mortality (SIRS-positive group: from 36.1% [829 of 2296 patients] to 18.3% [2037 of 11,119], P<0.001; SIRS-negative group: from 27.7% [100 of 361] to 9.3% [122 of 1315], P<0.001). Moreover, this pattern remained similar after adjustment for baseline characteristics (odds ratio in the SIRS-positive group, 0.96; 95% confidence interval [CI], 0.96 to 0.97; odds ratio in the SIRS-negative group, 0.96; 95% CI, 0.94 to 0.98; P=0.12 for between-group difference). In the adjusted analysis, mortality increased linearly with each additional SIRS criterion (odds ratio for each additional criterion, 1.13; 95% CI, 1.11 to 1.15; P<0.001) without any transitional increase in risk at a threshold of two SIRS criteria. CONCLUSIONS: The need for two or more SIRS criteria to define severe sepsis excluded one in eight otherwise similar patients with infection, organ failure, and substantial mortality and failed to define a transition point in the risk of death.
定义重度脓毒症的全身炎症反应综合征标准 背景：重度脓毒症的共识定义需要怀疑或证实的感染、器官衰竭和符合全身炎症反应综合征(SIRS)2个或2个以上标准的体征。我们旨在检验这种方法的敏感性、表面效度和结构效度。 方法：我们研究了2000年至2013年澳大利亚和新西兰172家重症监护室的患者数据。我们确定了感染和器官衰竭患者，并根据患者的体征是否符合2个或2个以上SIRS标准（SIRS阳性重度脓毒症）或少于2个SIRS标准（SIRS阴性重度脓毒症）进行分类。我们比较了他们的特征和结局，并评估了在两个SIRS标准的阈值下，他们的死亡风险是否有逐步增加。 结果：在1,171,797例患者中，共有109,663例发生感染和器官衰竭。其中96,385例(87.9%)患者患有SIRS阳性的严重脓毒症，13,278例(12.1%)患者患有SIRS阴性的严重脓毒症。在14年期间，这些组具有相似的特征和死亡率变化（SIRS阳性组：从36.1%[2296例患者中的829例]至18.3%[11,119例患者中的2037例]，P < 0.001；SIRS阴性组：从27.7%[361例患者中的100例]至9.3%[1315例患者中的122例]，P < 0.001）。此外，校正基线特征后，这种模式仍然相似（SIRS阳性组的比值比为0.96；95%置信区间[CI]为0.96-0.97；SIRS阴性组的比值比为0.96；95%CI为0.94-0.98；组间差异P = 0.12）。在校正分析中，死亡率随着每增加一个SIRS标准而线性增加（每增加一个标准的比值比，1.13；95%CI，1.11-1.15；P < 0.001），在两个SIRS标准的阈值下，没有任何风险的过渡性增加。 结论：定义严重脓毒症需要满足2个或更多SIRS标准，排除了1/8其他类似的感染、器官衰竭和实质性死亡患者，未能定义死亡风险的转换点。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Retrospective Studies; Severity of Illness Index; Australia; New Zealand; Sensitivity and Specificity; Odds Ratio; Multiple Organ Failure; Databases, Factual; Organ Dysfunction Scores; Sepsis/classification/*diagnosis/mortality; Systemic Inflammatory Response Syndrome/classification/*diagnosis/mortality

Case records of the Massachusetts General Hospital. Case 12-2015. A newborn boy with respiratory distress, lethargy, and hypernatremia. - Lin, Ting-Yi; Ebb, David H.; Boepple, Paul A.; Thiele, Elizabeth A.; Rincon, Sandra P.; Mordes, Daniel A. (The New England journal of medicine, 2015)
麻省总医院的病例记录。病例12-2015。一名呼吸窘迫、嗜睡和高钠血症的新生男婴。
Keywords: Humans; Male; Diagnosis, Differential; Infant, Newborn; Brain/*pathology; Fatal Outcome; Respiratory Insufficiency/etiology; Hypotension/etiology; Brain Neoplasms/complications/diagnostic imaging/*pathology; Diabetes Insipidus/diagnosis; Echoencephalography; Hypernatremia/etiology; Lethargy/etiology; Meconium Aspiration Syndrome/*complications; Myoclonus/etiology; Neuroectodermal Tumors/complications/diagnostic imaging/*pathology; Persistent Fetal Circulation Syndrome/diagnosis/etiology

Case records of the Massachusetts General Hospital. Case 11-2015. A 28-year-old woman with headache, fever, and a rash. - Manian, Farrin A.; Alame, Diana (The New England journal of medicine, 2015)
麻省总医院的病例记录。病例11-2015。1例28岁女性患者，伴有头痛、发热和皮疹。
Keywords: Humans; Female; Recurrence; Adult; Diagnosis, Differential; Exanthema/etiology; Meningococcal Infections/complications/*diagnosis; Fever/etiology; Complement C8/*deficiency; Headache/etiology; Immunologic Deficiency Syndromes/complications/*diagnosis; Neisseria meningitidis/*isolation & purification

Age of transfused blood in critically ill adults - Lacroix, Jacques; Hébert, Paul C.; Fergusson, Dean A.; Tinmouth, Alan; Cook, Deborah J.; Marshall, John C.; Clayton, Lucy; McIntyre, Lauralyn; Callum, Jeannie; Turgeon, Alexis F.; Blajchman, Morris A.; Walsh, Timothy S.; et al. (The New England journal of medicine, 2015)
BACKGROUND: Fresh red cells may improve outcomes in critically ill patients by enhancing oxygen delivery while minimizing the risks of toxic effects from cellular changes and the accumulation of bioactive materials in blood components during prolonged storage. METHODS: In this multicenter, randomized, blinded trial, we assigned critically ill adults to receive either red cells that had been stored for less than 8 days or standard-issue red cells (the oldest compatible units available in the blood bank). The primary outcome measure was 90-day mortality. RESULTS: Between March 2009 and May 2014, at 64 centers in Canada and Europe, 1211 patients were assigned to receive fresh red cells (fresh-blood group) and 1219 patients were assigned to receive standard-issue red cells (standard-blood group). Red cells were stored a mean (±SD) of 6.1±4.9 days in the fresh-blood group as compared with 22.0±8.4 days in the standard-blood group (P<0.001). At 90 days, 448 patients (37.0%) in the fresh-blood group and 430 patients (35.3%) in the standard-blood group had died (absolute risk difference, 1.7 percentage points; 95% confidence interval [CI], -2.1 to 5.5). In the survival analysis, the hazard ratio for death in the fresh-blood group, as compared with the standard-blood group, was 1.1 (95% CI, 0.9 to 1.2; P=0.38). There were no significant between-group differences in any of the secondary outcomes (major illnesses; duration of respiratory, hemodynamic, or renal support; length of stay in the hospital; and transfusion reactions) or in the subgroup analyses. CONCLUSIONS: Transfusion of fresh red cells, as compared with standard-issue red cells, did not decrease the 90-day mortality among critically ill adults.
危重成人患者输血年龄 背景：在危重患者中，新鲜红细胞可以通过增强氧气输送量改善结局，同时将细胞变化的毒性作用和长期储存期间血液成分中生物活性物质蓄积的风险降至最低。 方法：在这项多中心、随机化、设盲试验中，我们将危重成人分配至接受储存少于8天的红细胞或标准发放的红细胞（血库中可用的最旧的相容单位）。主要结局指标为90天死亡率。 结果：2009年3月至2014年5月，在加拿大和欧洲的64家中心，1211例患者被分配接受新鲜红细胞（新鲜血型），1219例患者被分配接受标准发放的红细胞（标准血型）。新鲜血液组的红细胞平均储存时间为6.1 μm±4.9天，标准血液组为22.0 μm±8.4天(P < 0.001)。90天时，新鲜血液组448名患者(37.0%)和标准血液组430名患者(35.3%)死亡（绝对风险差1.7个百分点；95%置信区间[CI]，-2.1至5.5）。在生存分析中，新鲜血液组与标准血液组相比的死亡风险比为1.1(95%CI，0.9-1.2；P = 0.38)。任何次要结局（重大疾病；呼吸、血液动力学或肾脏支持的持续时间；住院时间；输血反应）或亚组分析均无显著的组间差异。 结论：与标准红细胞相比，输注新鲜红细胞未降低危重成人患者的90天死亡率。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Time Factors; Double-Blind Method; Aged; Length of Stay; Adult; Kaplan-Meier Estimate; Intention to Treat Analysis; Logistic Models; Critical Illness/mortality/*therapy; *Blood Preservation; *Erythrocyte Transfusion/adverse effects

Molecular physiology of water balance - Knepper, Mark A.; Kwon, Tae-Hwan; Nielsen, Soren (The New England journal of medicine, 2015)
水平衡的分子生理学
Keywords: Humans; Animals; Aquaporins/physiology; Arginine Vasopressin/genetics/*physiology; Kidney Tubules/metabolism/physiology; Receptors, Vasopressin/physiology; Sodium-Potassium-Chloride Symporters/*physiology; Water-Electrolyte Balance/*physiology

Trial of early, goal-directed resuscitation for septic shock - Mouncey, Paul R.; Osborn, Tiffany M.; Power, G. Sarah; Harrison, David A.; Sadique, M. Zia; Grieve, Richard D.; Jahan, Rahi; Harvey, Sheila E.; Bell, Derek; Bion, Julian F.; Coats, Timothy J.; Singer, Mervyn; et al. (The New England journal of medicine, 2015)
BACKGROUND: Early, goal-directed therapy (EGDT) is recommended in international guidelines for the resuscitation of patients presenting with early septic shock. However, adoption has been limited, and uncertainty about its effectiveness remains. METHODS: We conducted a pragmatic randomized trial with an integrated cost-effectiveness analysis in 56 hospitals in England. Patients were randomly assigned to receive either EGDT (a 6-hour resuscitation protocol) or usual care. The primary clinical outcome was all-cause mortality at 90 days. RESULTS: We enrolled 1260 patients, with 630 assigned to EGDT and 630 to usual care. By 90 days, 184 of 623 patients (29.5%) in the EGDT group and 181 of 620 patients (29.2%) in the usual-care group had died (relative risk in the EGDT group, 1.01; 95% confidence interval [CI], 0.85 to 1.20; P=0.90), for an absolute risk reduction in the EGDT group of -0.3 percentage points (95% CI, -5.4 to 4.7). Increased treatment intensity in the EGDT group was indicated by increased use of intravenous fluids, vasoactive drugs, and red-cell transfusions and reflected by significantly worse organ-failure scores, more days receiving advanced cardiovascular support, and longer stays in the intensive care unit. There were no significant differences in any other secondary outcomes, including health-related quality of life, or in rates of serious adverse events. On average, EGDT increased costs, and the probability that it was cost-effective was below 20%. CONCLUSIONS: In patients with septic shock who were identified early and received intravenous antibiotics and adequate fluid resuscitation, hemodynamic management according to a strict EGDT protocol did not lead to an improvement in outcome.
脓毒性休克的早期目标导向复苏试验 背景：国际指南推荐早期目标导向治疗(EGDT)用于早期感染性休克患者的复苏。然而，采用有限，其有效性仍不确定。 方法：我们在英国56家医院进行了一项实用随机试验，并进行了综合成本-效果分析。患者被随机分配接受EGDT（6小时复苏方案）或常规护理。主要临床结局为90天时的全因死亡率。 结果：我们入选了1260例患者，其中630例被分配至EGDT组，630例被分配至常规护理组。90天时，EGDT组623例患者中的184例(29.5%)和常规护理组620例患者中的181例(29.2%)死亡（EGDT组的相对风险为1.01；95%置信区间[CI]，0.85-1.20；P = 0.90），EGDT组的绝对风险降低了-0.3个百分点（95%CI，-5.4至4.7）。EGDT组治疗强度的增加表现为静脉输液、血管活性药物和红细胞输注的增加，反映为器官衰竭评分显著恶化、接受高级心血管支持的天数更多和在重症监护室的住院时间更长。任何其他次要结局，包括健康相关生活质量或严重不良事件发生率均无显著差异。平均而言，EGDT增加了成本，成本效益概率低于20%。 结论：在早期发现并接受静脉内抗生素和充分液体复苏的感染性休克患者中，根据严格EGDT方案进行血流动力学管理不会导致结局改善。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Quality of Life; Clinical Protocols; Infusions, Intravenous; Kaplan-Meier Estimate; Combined Modality Therapy; Practice Guidelines as Topic; Anti-Bacterial Agents/*therapeutic use; Cost-Benefit Analysis; *Fluid Therapy; *Blood Transfusion; Quality-Adjusted Life Years; Resuscitation/economics/*methods; Shock, Septic/mortality/*therapy; Vasoconstrictor Agents/*therapeutic use

Videos in clinical medicine. Putting on and removing personal protective equipment. - Ortega, Rafael; Bhadelia, Nahid; Obanor, Osamede; Cyr, Kyle; Yu, Priscilla; McMahon, Maureen; Gotzmann, Dahlia (2015)
临床医学视频。穿戴和移除个人防护设备。
Keywords: Humans; Protective Clothing; *Protective Devices; Occupational Exposure/*prevention & control

Community-acquired pneumonia requiring hospitalization among U.S. children. - Jain, Seema; Williams, Derek J.; Arnold, Sandra R.; Ampofo, Krow; Bramley, Anna M.; Reed, Carrie; Stockmann, Chris; Anderson, Evan J.; Grijalva, Carlos G.; Self, Wesley H.; Zhu, Yuwei; Patel, Anami; et al. (The New England journal of medicine, 2015)
BACKGROUND: Incidence estimates of hospitalizations for community-acquired pneumonia among children in the United States that are based on prospective data collection are limited. Updated estimates of pneumonia that has been confirmed radiographically and with the use of current laboratory diagnostic tests are needed. METHODS: We conducted active population-based surveillance for community-acquired pneumonia requiring hospitalization among children younger than 18 years of age in three hospitals in Memphis, Nashville, and Salt Lake City. We excluded children with recent hospitalization or severe immunosuppression. Blood and respiratory specimens were systematically collected for pathogen detection with the use of multiple methods. Chest radiographs were reviewed independently by study radiologists. RESULTS: From January 2010 through June 2012, we enrolled 2638 of 3803 eligible children (69%), 2358 of whom (89%) had radiographic evidence of pneumonia. The median age of the children was 2 years (interquartile range, 1 to 6); 497 of 2358 children (21%) required intensive care, and 3 (<1%) died. Among 2222 children with radiographic evidence of pneumonia and with specimens available for bacterial and viral testing, a viral or bacterial pathogen was detected in 1802 (81%), one or more viruses in 1472 (66%), bacteria in 175 (8%), and both bacterial and viral pathogens in 155 (7%). The annual incidence of pneumonia was 15.7 cases per 10,000 children (95% confidence interval [CI], 14.9 to 16.5), with the highest rate among children younger than 2 years of age (62.2 cases per 10,000 children; 95% CI, 57.6 to 67.1). Respiratory syncytial virus was more common among children younger than 5 years of age than among older children (37% vs. 8%), as were adenovirus (15% vs. 3%) and human metapneumovirus (15% vs. 8%). Mycoplasma pneumoniae was more common among children 5 years of age or older than among younger children (19% vs. 3%). CONCLUSIONS: The burden of hospitalization for children with community-acquired pneumonia was highest among the very young, with respiratory viruses the most commonly detected causes of pneumonia.
美国儿童中需要住院治疗的社区获得性肺炎。 背景：基于前瞻性数据收集的美国儿童社区获得性肺炎住院发生率估计值有限。需要更新经放射学证实的肺炎的估计值，并使用当前实验室诊断检测。 方法：我们在Memphis、Nashville和盐湖城的三家医院对18岁以下需要住院的社区获得性肺炎患儿进行了基于人群的主动监测。我们排除了近期住院或重度免疫抑制的儿童。使用多种方法系统地采集血液和呼吸道样本进行病原体检测。研究放射科医生独立审查了胸片。 结果：从2010年1月至2012年6月，我们入选了3803例合格儿童中的2638例(69%)，其中2358例(89%)有肺炎的影像学证据。患儿的中位年龄为2岁（四分位距，1-6岁）；2358例患儿中497例(21%)需要重症监护，3例(< 1%)死亡。在2222例有肺炎影像学证据且有可用于细菌和病毒检测的标本的儿童中，1802例(81%)检测到病毒或细菌病原体，1472例(66%)检测到一种或多种病毒，175例(8%)检测到细菌，155例(7%)同时检测到细菌和病毒病原体。肺炎的年发病率为15.7例/10000名儿童（95%置信区间[CI]，14.9至16.5），其中2岁以下儿童的发病率最高（62.2例/10000名儿童；95%CI，57.6至67.1）。5岁以下儿童中呼吸道合胞病毒比大龄儿童更常见(37%vs. 8%)，腺病毒(15%vs. 3%)和人类偏肺病毒(15%vs. 8%)也是如此。肺炎支原体在5岁或5岁以上儿童中比在幼儿中更常见(19%vs. 3%)。 结论：社区获得性肺炎儿童的住院负担在非常年幼的人群中最高，呼吸道病毒是最常检测到的肺炎原因。
Keywords: Humans; Female; Male; Adolescent; Child; Infant; Infant, Newborn; Child, Preschool; Population Surveillance; Lung/diagnostic imaging; Radiography; Hospitalization/*statistics & numerical data; Age Distribution; Community-Acquired Infections/epidemiology/microbiology; Metapneumovirus/isolation & purification; Mycoplasma pneumoniae/isolation & purification; Pneumonia, Viral/epidemiology; Pneumonia/diagnostic imaging/*epidemiology/microbiology; Respiratory Syncytial Viruses/isolation & purification; Tennessee/epidemiology; Utah/epidemiology

Videos in clinical medicine. Electrocardiographic monitoring in adults. - Ortega, Rafael; Mazzini, Michael; Xue, Kristine; Espaillat, Diego (2015)
临床医学视频。成人心电图监测。
Keywords: Humans; Adult; Arrhythmias, Cardiac/*diagnosis; Electrocardiography/adverse effects/instrumentation/*methods; Myocardial Ischemia/*diagnosis

Driving pressure and respiratory mechanics in ARDS - Loring, Stephen H.; Malhotra, Atul (The New England journal of medicine, 2015)
ARDS中的驱动压力和呼吸力学
Keywords: Humans; *Tidal Volume; Positive-Pressure Respiration/*methods; Respiratory Distress Syndrome/*mortality

Driving pressure and survival in the acute respiratory distress syndrome - Amato, Marcelo B. P.; Meade, Maureen O.; Slutsky, Arthur S.; Brochard, Laurent; Costa, Eduardo L. V.; Schoenfeld, David A.; Stewart, Thomas E.; Briel, Matthias; Talmor, Daniel; Mercat, Alain; Richard, Jean-Christophe M.; Carvalho, Carlos R. R.; et al. (The New England journal of medicine, 2015)
BACKGROUND: Mechanical-ventilation strategies that use lower end-inspiratory (plateau) airway pressures, lower tidal volumes (VT), and higher positive end-expiratory pressures (PEEPs) can improve survival in patients with the acute respiratory distress syndrome (ARDS), but the relative importance of each of these components is uncertain. Because respiratory-system compliance (CRS) is strongly related to the volume of aerated remaining functional lung during disease (termed functional lung size), we hypothesized that driving pressure (Î”P=VT/CRS), in which VT is intrinsically normalized to functional lung size (instead of predicted lung size in healthy persons), would be an index more strongly associated with survival than VT or PEEP in patients who are not actively breathing. METHODS: Using a statistical tool known as multilevel mediation analysis to analyze individual data from 3562 patients with ARDS enrolled in nine previously reported randomized trials, we examined Î”P as an independent variable associated with survival. In the mediation analysis, we estimated the isolated effects of changes in Î”P resulting from randomized ventilator settings while minimizing confounding due to the baseline severity of lung disease. RESULTS: Among ventilation variables, Î”P was most strongly associated with survival. A 1-SD increment in Î”P (approximately 7 cm of water) was associated with increased mortality (relative risk, 1.41; 95% confidence interval [CI], 1.31 to 1.51; P<0.001), even in patients receiving "protective" plateau pressures and VT (relative risk, 1.36; 95% CI, 1.17 to 1.58; P<0.001). Individual changes in VT or PEEP after randomization were not independently associated with survival; they were associated only if they were among the changes that led to reductions in Î”P (mediation effects of Î”P, P=0.004 and P=0.001, respectively). CONCLUSIONS: We found that Î”P was the ventilation variable that best stratified risk. Decreases in Î”P owing to changes in ventilator settings were strongly associated with increased survival.
急性呼吸窘迫综合征中的驾驶压力和生存率 背景：使用较低的吸气末（平台）气道压力、较低的潮气量(VT)和较高的呼气末正压(PEEP)的机械通气策略可改善急性呼吸窘迫综合征(ARDS)患者的生存率，但尚不确定这些组分的相对重要性。由于呼吸系统顺应性(CRS)与疾病期间充气剩余功能性肺的体积（称为功能性肺大小）密切相关，我们假设驱动压力(æP = VT/CRS)，其中VT本质上归一化为功能性肺大小（而不是健康人群中预测的肺大小），在无主动呼吸的患者中，与VT或PEEP相比，是与生存率更密切相关的指标。 方法：使用一种称为多级中介效应分析的统计工具，对纳入9项既往报告的随机试验的3562例ARDS患者的个体数据进行分析，我们检查了与生存相关的自变量ΔΔΔP。在中介分析中，我们评估了随机呼吸机设置导致的短期“P”变化的孤立效应，同时尽量减少基线肺部疾病严重程度导致的混杂。 结果：在通气变量中，ΔΔΔP与生存率密切相关。即使在接受“保护性”平台压和VT的患者中（相对风险，1.36；95%CI，1.17至1.58；P < 0.001），相对P值（大约7 cm水）增加1个标准差与死亡率增加相关（相对风险，1.41；95%置信区间[CI]，1.31至1.51；P < 0.001）。随机化后VT或PEEP的个体变化与生存期无独立相关性；仅当它们属于导致ΔΔΔΔP的变化时才相关（ΔΔP的中介效应，分别为P = 0.004和P = 0.001）。 结论：我们发现dmsp是分层风险最好的通气变量。通气设备设置改变导致的血小板减少与生存率升高密切相关。
Keywords: Humans; Prognosis; Multivariate Analysis; Risk; Proportional Hazards Models; Lung Compliance; *Tidal Volume; Positive-Pressure Respiration/*methods; Lung/anatomy & histology/physiology; Pressure; Respiratory Distress Syndrome/*mortality/physiopathology/therapy

Interactive medical case. Itching for a diagnosis. - Schaefer, Libby; Vaidya, Anand; Rennke, Helmut G.; Paik, Julie (The New England journal of medicine, 2015)
交互式医学病例。诊断为瘙痒。
Keywords: Humans; Female; Middle Aged; Diagnosis, Differential; Ultrasonography; Renal Dialysis; Glucocorticoids/*therapeutic use; Glomerulosclerosis, Focal Segmental/complications/*diagnosis/therapy; Kidney/diagnostic imaging/*pathology; Nephrotic Syndrome/*diagnosis/etiology; Proteinuria/diagnosis/etiology; Pruritus/etiology

Acid-base problems in diabetic ketoacidosis - Kamel, Kamel S.; Halperin, Mitchell L. (The New England journal of medicine, 2015)
糖尿病酮症酸中毒的酸碱问题
Keywords: Humans; Child; Fatty Acids/metabolism; Oxidation-Reduction; Acid-Base Equilibrium/*physiology; Bicarbonates/blood; Brain Edema/*etiology; Diabetic Ketoacidosis/complications/*drug therapy/*metabolism; Mitochondria/metabolism; Osmolar Concentration; Sodium Bicarbonate/adverse effects/metabolism/*therapeutic use

Interactive medical case. A Liberian health care worker with fever. - Levine, Adam C.; Shetty, Pranav P.; Henwood, Patricia C.; Sabeti, Pardis; Katz, Joel T.; Vaidya, Anand (The New England journal of medicine, 2015)
交互式医学病例。一名发烧的利比里亚医护人员。
Keywords: Humans; Female; Middle Aged; Diagnosis, Differential; Disease Progression; Combined Modality Therapy; Anti-Bacterial Agents/therapeutic use; Protective Clothing; *Fluid Therapy; Antibodies, Viral/blood; Ciprofloxacin/therapeutic use; Ebolavirus/genetics/*isolation & purification/ultrastructure; Fever/*etiology; Hemorrhagic Fever, Ebola/complications/*diagnosis/therapy/transmission; Liberia; Malaria/diagnosis; Musculoskeletal Pain/etiology; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral/isolation & purification

Case records of the Massachusetts General Hospital. Case 4-2015. A 49-year-old man with obtundation followed by agitation and acidosis. - Cooper, Cynthia M.; Baron, Jason M. (The New England journal of medicine, 2015)
麻省总医院的病例记录。病例4-2015。1例49岁男性，意识迟钝，随后发生激越和酸中毒。
Keywords: Humans; Male; Middle Aged; Glasgow Coma Scale; Diagnosis, Differential; Acidosis/etiology; *Substance Abuse Detection; Calcium Oxalate/urine; Chromatography, High Pressure Liquid; Consciousness Disorders/*etiology; Drug Overdose/diagnosis; Ethylene Glycol/*poisoning; Poisoning/complications/diagnosis/drug therapy; Psychomotor Agitation/etiology; Trazodone/poisoning; Urinalysis

Case records of the Massachusetts General Hospital. Case 3-2015. A 60-year-old woman with abdominal pain, dyspnea, and diplopia. - David, William S.; Temin, Elizabeth S.; Kraeft, Jessica J.; Hooper, David C. (The New England journal of medicine, 2015)
麻省总医院的病例记录。病例3-2015。一名60岁的女性患者出现腹痛、呼吸困难和复视。
Keywords: Humans; Female; Middle Aged; Diagnosis, Differential; Abdominal Pain/etiology; *Electromyography; Botulism/complications/*diagnosis; Diplopia/etiology; Dyspnea/*etiology/therapy; Nervous System Diseases/diagnosis; Radiography, Abdominal

Disorders of plasma sodium--causes, consequences, and correction - Sterns, Richard H. (The New England journal of medicine, 2015)
血浆钠紊乱--原因、后果和纠正
Keywords: Humans; Saline Solution, Hypertonic/therapeutic use; Brain Edema/etiology; Brain Diseases/*etiology; Demyelinating Diseases/etiology; Hypernatremia/etiology/*therapy; Hyponatremia/etiology/*therapy; Plasma/*chemistry/metabolism; Sodium/*blood/urine; Water-Electrolyte Imbalance/*complications/metabolism

A case of severe Ebola virus infection complicated by gram-negative septicemia - Kreuels, Benno; Wichmann, Dominic; Emmerich, Petra; Schmidt-Chanasit, Jonas; de Heer, Geraldine; Kluge, Stefan; Sow, Abdourahmane; RennÃ©, Thomas; GÃ¼nther, Stephan; Lohse, Ansgar W.; Addo, Marylyn M.; Schmiedel, Stefan (The New England journal of medicine, 2014)
Ebola virus disease (EVD) developed in a patient who contracted the disease in Sierra Leone and was airlifted to an isolation facility in Hamburg, Germany, for treatment. During the course of the illness, he had numerous complications, including septicemia, respiratory failure, and encephalopathy. Intensive supportive treatment consisting of high-volume fluid resuscitation (approximately 10 liters per day in the first 72 hours), broad-spectrum antibiotic therapy, and ventilatory support resulted in full recovery without the use of experimental therapies. Discharge was delayed owing to the detection of viral RNA in urine (day 30) and sweat (at the last assessment on day 40) by means of polymerase-chain-reaction (PCR) assay, but the last positive culture was identified in plasma on day 14 and in urine on day 26. This case shows the challenges in the management of EVD and suggests that even severe EVD can be treated effectively with routine intensive care.
埃博拉病毒感染并发革兰阴性败血症一例 埃博拉病毒病(EVD)是在一名在塞拉利昂感染该病的患者中出现的，该患者被空运至德国汉堡的一个隔离设施接受治疗。在病程中，患者出现多种并发症，包括败血症、呼吸衰竭和脑病。强化支持性治疗包括高容量液体复苏（最初72小时内，大约10L/天）、广谱抗生素治疗和通气支持，在未使用试验性治疗的情况下，患者完全恢复。通过聚合酶链反应(PCR)检测方法，由于在尿液（第30天）和汗液（第40天最后一次评估时）中检测到病毒RNA，患者延迟出院，但在第14天的血浆和第26天的尿液中发现最后一次阳性培养物。该病例显示了EVD管理的挑战，表明即使是重度EVD，也可以通过常规重症监护进行有效治疗。
Keywords: Humans; Male; Adult; Critical Care; Fluid Therapy; Anti-Infective Agents/*therapeutic use; Viral Load; Parenteral Nutrition; Bacteremia/drug therapy/*etiology; Diarrhea/etiology/therapy; Ebolavirus/genetics/isolation & purification; Gram-Negative Bacterial Infections/drug therapy/*etiology; Hemorrhagic Fever, Ebola/complications/*therapy; Hepatitis B, Chronic/complications; RNA, Viral/blood; Sierra Leone

Lactic acidosis - Kraut, Jeffrey A.; Madias, Nicolaos E. (The New England journal of medicine, 2014)
乳酸酸中毒
Keywords: Humans; Prognosis; Fluid Therapy; *Acidosis, Lactic/diagnosis/etiology/metabolism/therapy; Acid-Base Equilibrium; Hyperlactatemia/metabolism; Lactic Acid/*metabolism; Sodium Bicarbonate/therapeutic use

Integration of acid-base and electrolyte disorders - Seifter, Julian L. (The New England journal of medicine, 2014)
酸碱和电解质紊乱的综合
Keywords: Humans; Female; Male; Aged; Adult; Hydrogen-Ion Concentration; Acid-Base Equilibrium/*physiology; Acid-Base Imbalance/*diagnosis/metabolism; Bicarbonates/*metabolism; Electrolytes/metabolism; Ions/metabolism; Models, Chemical

Trial of the route of early nutritional support in critically ill adults - Harvey, Sheila E.; Parrott, Francesca; Harrison, David A.; Bear, Danielle E.; Segaran, Ella; Beale, Richard; Bellingan, Geoff; Leonard, Richard; Mythen, Michael G.; Rowan, Kathryn M. (The New England journal of medicine, 2014)
BACKGROUND: Uncertainty exists about the most effective route for delivery of early nutritional support in critically ill adults. We hypothesized that delivery through the parenteral route is superior to that through the enteral route. METHODS: We conducted a pragmatic, randomized trial involving adults with an unplanned admission to one of 33 English intensive care units. We randomly assigned patients who could be fed through either the parenteral or the enteral route to a delivery route, with nutritional support initiated within 36 hours after admission and continued for up to 5 days. The primary outcome was all-cause mortality at 30 days. RESULTS: We enrolled 2400 patients; 2388 (99.5%) were included in the analysis (1191 in the parenteral group and 1197 in the enteral group). By 30 days, 393 of 1188 patients (33.1%) in the parenteral group and 409 of 1195 patients (34.2%) in the enteral group had died (relative risk in parenteral group, 0.97; 95% confidence interval, 0.86 to 1.08; P=0.57). There were significant reductions in the parenteral group, as compared with the enteral group, in rates of hypoglycemia (44 patients [3.7%] vs. 74 patients [6.2%]; P=0.006) and vomiting (100 patients [8.4%] vs. 194 patients [16.2%]; P<0.001). There were no significant differences between the parenteral group and the enteral group in the mean number of treated infectious complications (0.22 vs. 0.21; P=0.72), 90-day mortality (442 of 1184 patients [37.3%] vs. 464 of 1188 patients [39.1%], P=0.40), in rates of 14 other secondary outcomes, or in rates of adverse events. Caloric intake was similar in the two groups, with the target intake not achieved in most patients. CONCLUSIONS: We found no significant difference in 30-day mortality associated with the route of delivery of early nutritional support in critically ill adults.
在重症成人中进行的早期营养支持途径试验 背景：关于危重成人患者早期营养支持最有效的途径仍存在不确定性。我们假设通过肠外途径给药优于通过肠内途径给药。 方法：我们进行了一项实用的随机试验，涉及计划外入住33家英国重症监护室之一的成人。我们将可通过肠外或肠内途径进食的患者随机分配至递送途径，在入院后36小时内开始营养支持，并持续长达5天。主要结局为30天时的全因死亡率。 结果：我们入选了2400例患者；2388(99.5%)例被纳入分析（肠外组1191例，肠内组1197例）。到第30天，肠外组1188例患者中393例(33.1%)和肠内组1195例患者中409例(34.2%)死亡（肠外组相对风险，0.97；95%置信区间，0.86-1.08；P = 0.57）。与肠内组相比，肠外组低血糖（44例患者[3.7%]vs. 74例患者[6.2%]；P = 0.006）和呕吐（100例患者[8.4%]vs. 194例患者[16.2%]；P < 0.001）的发生率显著降低。肠外组和肠内组在治疗的感染性并发症平均数(0.22 vs. 0.21；P = 0.72)、90天死亡率（1184例患者中的442例[37.3%]vs. 1188例患者中的464例[39.1%]，P = 0.40）、14个其他次要结局的发生率或不良事件发生率方面无显著差异。两组的热量摄入相似，大多数患者未达到目标摄入。 结论：我们发现重症成人中早期营养支持给药途径相关的30天死亡率无显著差异。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Adult; *Parenteral Nutrition/adverse effects; Critical Illness/mortality/*therapy; Energy Intake; Vomiting/etiology; Hypoglycemia/etiology; *Enteral Nutrition/adverse effects

The route of early nutrition in critical illness - Cook, Deborah; Arabi, Yaseen (The New England journal of medicine, 2014)
危重病早期营养途径
Keywords: Humans; Female; Male; Critical Illness/*therapy; *Enteral Nutrition; *Parenteral Nutrition

Simvastatin in the acute respiratory distress syndrome - McAuley, Daniel F.; Laffey, John G.; O'Kane, Cecilia M.; Perkins, Gavin D.; Mullan, Brian; Trinder, T. John; Johnston, Paul; Hopkins, Philip A.; Johnston, Andrew J.; McDowell, Cliona; McNally, Christine (The New England journal of medicine, 2014)
BACKGROUND: Studies in animals and in vitro and phase 2 studies in humans suggest that statins may be beneficial in the treatment of the acute respiratory distress syndrome (ARDS). This study tested the hypothesis that treatment with simvastatin would improve clinical outcomes in patients with ARDS. METHODS: In this multicenter, double-blind clinical trial, we randomly assigned (in a 1:1 ratio) patients with an onset of ARDS within the previous 48 hours to receive enteral simvastatin at a dose of 80 mg or placebo once daily for a maximum of 28 days. The primary outcome was the number of ventilator-free days to day 28. Secondary outcomes included the number of days free of nonpulmonary organ failure to day 28, mortality at 28 days, and safety. RESULTS: The study recruited 540 patients, with 259 patients assigned to simvastatin and 281 to placebo. The groups were well matched with respect to demographic and baseline physiological variables. There was no significant difference between the study groups in the mean (±SD) number of ventilator-free days (12.6±9.9 with simvastatin and 11.5±10.4 with placebo, P=0.21) or days free of nonpulmonary organ failure (19.4±11.1 and 17.8±11.7, respectively; P=0.11) or in mortality at 28 days (22.0% and 26.8%, respectively; P=0.23). There was no significant difference between the two groups in the incidence of serious adverse events related to the study drug. CONCLUSIONS: Simvastatin therapy, although safe and associated with minimal adverse effects, did not improve clinical outcomes in patients with ARDS.
Acute respiratory distress syndrome 背景：在动物中的研究以及在人体中的体外和2期研究表明，他汀类药物可能有益于急性呼吸窘迫综合征 (ARDS) 的治疗。本研究检验了辛伐他汀治疗可改善 ARDS 患者临床结局的假设。 方法：在这项多中心、双盲临床试验中，我们随机分配（以1：1的比例）在过去48小时内发生 ARDS 的患者接受辛伐他汀肠内给药，剂量为 80 mg 或安慰剂，每日一次，最长28天。主要结局是至第28天无呼吸机的天数。次要结局包括至第28天无非肺器官衰竭的天数、第28天死亡率和安全性。 结果：该研究招募了540例患者，其中259例患者被分配到辛伐他汀组，281例患者被分配到安慰剂组。两组在人口统计学和基线生理变量方面匹配良好。研究组之间的平均 (Â±SD) 无呼吸机天数（辛伐他汀组为12.6Â±9.9，安慰剂组为11.5Â±10.4，P = 0.21）或无非肺器官衰竭天数（分别为19.4Â±11.1和17.8Â±11.7；P = 0.11）或28天时的死亡率（分别为22.0%和26.8%；P = 0.23）无显著差异。两组研究药物相关严重不良事件发生率比较差异无统计学意义。 结论：辛伐他汀治疗虽然安全且不良反应小，但并不能改善 ARDS 患者的临床预后。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Intensive Care Units; Adult; Respiration, Artificial; Kaplan-Meier Estimate; Combined Modality Therapy; Tidal Volume; Treatment Failure; Hydroxymethylglutaryl-CoA Reductase Inhibitors/adverse effects/*therapeutic use; Respiratory Distress Syndrome/*drug therapy/etiology/therapy; Simvastatin/adverse effects/*therapeutic use

Oxygen desaturation in infants during aeromedical transport - LÃ¶llgen, Ruth M.; Woods, Patricia; Wall, Margaret; Berry, Andrew (The New England journal of medicine, 2014)
婴儿在航空医疗转运过程中的氧饱和度下降
Keywords: Humans; Infant; Infant, Newborn; Oxygen/*blood; Transportation of Patients; *Air Ambulances; Hypoxia/*etiology

Goal-directed resuscitation for patients with early septic shock - Peake, Sandra L.; Delaney, Anthony; Bailey, Michael; Bellomo, Rinaldo; Cameron, Peter A.; Cooper, D. James; Higgins, Alisa M.; Holdgate, Anna; Howe, Belinda D.; Webb, Steven A. R.; Williams, Patricia (The New England journal of medicine, 2014)
BACKGROUND: Early goal-directed therapy (EGDT) has been endorsed in the guidelines of the Surviving Sepsis Campaign as a key strategy to decrease mortality among patients presenting to the emergency department with septic shock. However, its effectiveness is uncertain. METHODS: In this trial conducted at 51 centers (mostly in Australia or New Zealand), we randomly assigned patients presenting to the emergency department with early septic shock to receive either EGDT or usual care. The primary outcome was all-cause mortality within 90 days after randomization. RESULTS: Of the 1600 enrolled patients, 796 were assigned to the EGDT group and 804 to the usual-care group. Primary outcome data were available for more than 99% of the patients. Patients in the EGDT group received a larger mean (±SD) volume of intravenous fluids in the first 6 hours after randomization than did those in the usual-care group (1964±1415 ml vs. 1713±1401 ml) and were more likely to receive vasopressor infusions (66.6% vs. 57.8%), red-cell transfusions (13.6% vs. 7.0%), and dobutamine (15.4% vs. 2.6%) (P<0.001 for all comparisons). At 90 days after randomization, 147 deaths had occurred in the EGDT group and 150 had occurred in the usual-care group, for rates of death of 18.6% and 18.8%, respectively (absolute risk difference with EGDT vs. usual care, -0.3 percentage points; 95% confidence interval, -4.1 to 3.6; P=0.90). There was no significant difference in survival time, in-hospital mortality, duration of organ support, or length of hospital stay. CONCLUSIONS: In critically ill patients presenting to the emergency department with early septic shock, EGDT did not reduce all-cause mortality at 90 days.
早期感染性休克患者的目标导向复苏 背景：早期目标导向治疗(EGDT)作为降低因脓毒性休克到急诊科就诊的患者死亡率的关键策略已在拯救败血症运动指南中得到认可。但是，其有效性尚不确定。 方法：本试验在51家中心进行（主要在澳大利亚或新西兰），我们将早期脓毒性休克急诊室就诊的患者随机分配至EGDT组或常规治疗组。主要结局为随机分组后90天内的全因死亡率。 结果：在1600例入组患者中，796例被分配至EGDT组，804例被分配至常规护理组。99%以上患者的主要结局数据可用。EGDT组患者在随机分配后的最初6小时内接受的静脉输液平均(±SD)体积大于常规护理组患者(1964±1415 mL vs. 1713±1401 mL)，更可能接受血管加压素输注(66.6%vs. 57.8%)、红细胞输注(13.6%vs. 7.0%)。和多巴酚丁胺（15.4%对比2.6%）（所有比较P < 0.001）。在随机分组后90天，EGDT组发生147例死亡，常规护理组发生150例死亡，死亡率分别为18.6%和18.8%（EGDT与常规护理的绝对风险差异，-0.3个百分点；95%置信区间，-4.1至3.6；P = 0.90）。生存时间、住院死亡率、器官支持持续时间或住院时间无显著差异。 结论：在因早期感染性休克而就诊于急诊科的重症患者中，EGDT并未降低90天时的全因死亡率。
Keywords: Humans; Female; Male; Middle Aged; Survival Analysis; Aged; Critical Illness; Length of Stay; Adult; Emergency Service, Hospital; Respiration, Artificial; Combined Modality Therapy; Erythrocyte Transfusion; *Fluid Therapy; Renal Replacement Therapy; Shock, Septic/mortality/*therapy; Vasoconstrictor Agents/*therapeutic use; Dobutamine/therapeutic use

Videos in clinical medicine. Ultrasound-guided insertion of a radial arterial catheter. - Ailon, Jonathan; Mourad, Ophyr; Chien, Vince; Saun, Tomas; Dev, Shelly P. (2014)
临床医学视频。超声引导下插入桡动脉导管。
Keywords: Humans; Ultrasonography, Interventional; Catheterization, Peripheral/adverse effects/instrumentation/*methods; Radial Artery

Physiological approach to assessment of acid-base disturbances - Berend, Kenrick; de Vries, Aiko P. J.; Gans, Rijk O. B. (The New England journal of medicine, 2014)
评估酸碱紊乱的生理学方法
Keywords: Humans; Reference Values; Oxygen/metabolism; Hydrogen-Ion Concentration; Acid-Base Imbalance/*diagnosis/etiology/physiopathology; Bicarbonates/metabolism; Homeostasis/physiology

Transfusion threshold of 7 g per deciliter--the new normal - HÃ©bert, Paul C.; Carson, Jeffrey L. (The New England journal of medicine, 2014)
输血阈值为7 g/dl-新正常值
Keywords: Humans; Female; Male; *Erythrocyte Transfusion; *Hemoglobins; Shock, Septic/*therapy

Lower versus higher hemoglobin threshold for transfusion in septic shock - Holst, Lars B.; Haase, Nicolai; Wetterslev, JÃ¸rn; Wernerman, Jan; Guttormsen, Anne B.; Karlsson, Sari; Johansson, PÃ¤r I.; Aneman, Anders; Vang, Marianne L.; Winding, Robert; Nebrich, Lars; Nibro, Helle L.; et al. (The New England journal of medicine, 2014)
BACKGROUND: Blood transfusions are frequently given to patients with septic shock. However, the benefits and harms of different hemoglobin thresholds for transfusion have not been established. METHODS: In this multicenter, parallel-group trial, we randomly assigned patients in the intensive care unit (ICU) who had septic shock and a hemoglobin concentration of 9 g per deciliter or less to receive 1 unit of leukoreduced red cells when the hemoglobin level was 7 g per deciliter or less (lower threshold) or when the level was 9 g per deciliter or less (higher threshold) during the ICU stay. The primary outcome measure was death by 90 days after randomization. RESULTS: We analyzed data from 998 of 1005 patients (99.3%) who underwent randomization. The two intervention groups had similar baseline characteristics. In the ICU, the lower-threshold group received a median of 1 unit of blood (interquartile range, 0 to 3) and the higher-threshold group received a median of 4 units (interquartile range, 2 to 7). At 90 days after randomization, 216 of 502 patients (43.0%) assigned to the lower-threshold group, as compared with 223 of 496 (45.0%) assigned to the higher-threshold group, had died (relative risk, 0.94; 95% confidence interval, 0.78 to 1.09; P=0.44). The results were similar in analyses adjusted for risk factors at baseline and in analyses of the per-protocol populations. The numbers of patients who had ischemic events, who had severe adverse reactions, and who required life support were similar in the two intervention groups. CONCLUSIONS: Among patients with septic shock, mortality at 90 days and rates of ischemic events and use of life support were similar among those assigned to blood transfusion at a higher hemoglobin threshold and those assigned to blood transfusion at a lower threshold; the latter group received fewer transfusions.
脓毒性休克中输血的血红蛋白阈值较低vs.较高 背景：感染性休克患者常接受输血。然而，不同血红蛋白阈值对输血的益处和危害尚未确定。 方法：在这项多中心、平行组试验中，我们将患有脓毒性休克且血红蛋白浓度≤9 g/dl的重症监护室(ICU)患者随机分组，当血红蛋白水平≤7 g/dl（阈值下限）或当血红蛋白水平≤9 g/dl（阈值上限 < 7 g/dl）时接受1个单位的白细胞减少红细胞输注。eshold）。主要结局指标为随机分组后90天的死亡率。 结果：我们分析了1005例接受随机化患者中998例(99.3%)的数据。两个干预组的基线特征相似。在ICU中，低阈值组接受了中位数为1个单位的血液（四分位距，0-3），高阈值组接受了中位数为4个单位的血液（四分位距，2-7）。在随机分组后90天，216/502(43.0%)的患者被分配到低阈值组，而223/496(45.0%)的患者被分配到高阈值组，他们已经死亡（相对风险，0.94；95%置信区间，0.78-1.09；P = 0.44）。在针对基线风险因素调整的分析和符合方案人群分析中，结果相似。两个干预组中发生缺血性事件、发生重度不良反应和需要生命支持的患者数量相似。 结论：在感染性休克患者中，以较高血红蛋白阈值分配接受输血的患者与以较低阈值分配接受输血的患者90天时的死亡率、缺血事件发生率和生命支持使用率相似；后者接受的输血较少。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Kaplan-Meier Estimate; Single-Blind Method; Risk; *Hemoglobins/analysis; Ischemia/etiology; *Erythrocyte Transfusion/adverse effects; Myocardial Ischemia/etiology; Shock, Septic/blood/complications/mortality/*therapy

Case records of the Massachusetts General Hospital. Case 27-2014. A 10-month-old boy with microcephaly and episodic cyanosis. - Sahai, Inderneel; Mochida, Ganeshwaran H.; Grabowski, Eric F.; Caruso, Paul A. (The New England journal of medicine, 2014)
麻省总医院的病例记录。病例27-2014。1例10个月男童，伴有小头畸形和发作性发绀。
Keywords: Humans; Male; Diagnosis, Differential; Infant; Magnetic Resonance Imaging; Brain/*blood supply/pathology; Cyanosis/etiology; Hematologic Tests; Hyperhomocysteinemia/complications/*diagnosis/genetics; Methylenetetrahydrofolate Reductase (NADPH2)/cerebrospinal fluid/*deficiency; Microcephaly/*etiology/pathology; Nerve Fibers, Myelinated/pathology; Venous Thrombosis/*diagnosis

Case records of the Massachusetts General Hospital. Case 26-2014. A 21-month-old boy with lethargy, respiratory distress, and abdominal distention. - Klig, Jean E.; Sharma, Amita; Skolnik, Aaron B. (The New England journal of medicine, 2014)
麻省总医院的病例记录。病例26-2014。21个月大男孩，嗜睡、呼吸窘迫和腹胀。
Keywords: Humans; Male; Diagnosis, Differential; Infant; Renal Dialysis; Respiratory Insufficiency/*etiology; Poisoning/diagnosis/therapy; Lethargy/etiology; Abdomen/pathology; Acidosis/*chemically induced; Salicylates/blood/*poisoning; Tachypnea/etiology

Dying with dignity in the intensive care unit - Cook, Deborah; Rocker, Graeme (The New England journal of medicine, 2014)
在重症监护室尊严地死去
Keywords: Humans; Palliative Care; Critical Illness/therapy; *Intensive Care Units; Attitude to Death; Attitude of Health Personnel; *Death; *Withholding Treatment/standards; Right to Die; Terminal Care/*methods/standards

Where we die - Rothman, David J. (The New England journal of medicine, 2014)
我们的死亡之地
Keywords: Humans; United States; History, 21st Century; History, 19th Century; History, 20th Century; Hospitalization/*trends; *Death; Hospice Care/statistics & numerical data/trends; Intensive Care Units/statistics & numerical data/*trends; Terminal Care/history/*trends

Case records of the Massachusetts General Hospital. Case 19-2014. A 19-year-old woman with headache, fever, stiff neck, and mental-status changes. - Gorman, Mark P.; Rincon, Sandra P.; Pierce, Virginia M. (The New England journal of medicine, 2014)
麻省总医院的病例记录。病例19-2014。1例19岁女性患者，伴有头痛、发热、颈项强直和精神状态改变。
Keywords: Humans; Female; Young Adult; Diagnosis, Differential; Magnetic Resonance Imaging; Brain/pathology; Immunoglobulins, Intravenous/therapeutic use; Fever/etiology; Headache/etiology; Antibodies, Bacterial/blood; Encephalomyelitis/complications/*diagnosis/microbiology; Muscle Rigidity/etiology; Mycoplasma Infections/complications/*diagnosis; Mycoplasma pneumoniae/immunology/*isolation & purification; Neck Muscles; Spinal Cord/pathology

Rosuvastatin for sepsis-associated acute respiratory distress syndrome - Truwit, Jonathon D.; Bernard, Gordon R.; Steingrub, Jay; Matthay, Michael A.; Liu, Kathleen D.; Albertson, Timothy E.; Brower, Roy G.; Shanholtz, Carl; Rock, Peter; Douglas, Ivor S.; deBoisblanc, Bennett P.; Hough, Catherine L.; et al. (The New England journal of medicine, 2014)
BACKGROUND: In the acute respiratory distress syndrome (ARDS), inflammation in the lungs and other organs can cause life-threatening organ failure. Inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A reductase (statins) can modulate inflammatory responses. Previous observational studies suggested that statins improved clinical outcomes in patients with sepsis. We hypothesized that rosuvastatin therapy would improve clinical outcomes in critically ill patients with sepsis-associated ARDS. METHODS: We conducted a multicenter trial in which patients with sepsis-associated ARDS were randomly assigned to receive either enteral rosuvastatin or placebo in a double-blind manner. The primary outcome was mortality before hospital discharge home or until study day 60 if the patient was still in a health care facility. Secondary outcomes included the number of ventilator-free days (days that patients were alive and breathing spontaneously) to day 28 and organ-failure-free days to day 14. RESULTS: The study was stopped because of futility after 745 of an estimated 1000 patients had been enrolled. There was no significant difference between study groups in 60-day in-hospital mortality (28.5% with rosuvastatin and 24.9% with placebo, P=0.21) or in mean (±SD) ventilator-free days (15.1±10.8 with rosuvastatin and 15.1±11.0 with placebo, P=0.96). The groups were well matched with respect to demographic and key physiological variables. Rosuvastatin therapy, as compared with placebo, was associated with fewer days free of renal failure to day 14 (10.1±5.3 vs. 11.0±4.7, P=0.01) and fewer days free of hepatic failure to day 14 (10.8±5.0 vs. 11.8±4.3, P=0.003). Rosuvastatin was not associated with an increased incidence of serum creatine kinase levels that were more than 10 times the upper limit of the normal range. CONCLUSIONS: Rosuvastatin therapy did not improve clinical outcomes in patients with sepsis-associated ARDS and may have contributed to hepatic and renal organ dysfunction.
瑞舒伐他汀治疗脓毒症相关急性呼吸窘迫综合征 背景：在急性呼吸窘迫综合征(ARDS)中，肺脏和其他器官的炎症可引起危及生命的器官衰竭。3-羟基-3-甲基戊二酰辅酶A还原酶抑制剂（他汀类）可调节炎症反应。既往的观察性研究表明，他汀类药物改善了脓毒症患者的临床结局。我们假设瑞舒伐他汀治疗可改善脓毒症相关ARDS重症患者的临床结局。 方法：我们进行了一项多中心试验，其中脓毒症相关ARDS患者以双盲方式随机接受瑞舒伐他汀或安慰剂肠内给药。主要结局为出院回家前或研究第60天之前（如果患者仍在医疗保健机构）的死亡率。次要结局包括至第28天无呼吸机通气的天数（患者存活和自主呼吸的天数）和至第14天无器官衰竭的天数。 结果：在入组约1000例患者中的745例后，因无效而停止研究。研究组间60天住院死亡率（瑞舒伐他汀组为28.5%，安慰剂组为24.9%，P = 0.21）或平均无呼吸机天数(õ±SD)（瑞舒伐他汀组为15.1õ±10.8，安慰剂组为15.1õ±11.0，P = 0.96）无显著差异。各组的人口统计学和关键生理变量匹配良好。与安慰剂相比，瑞舒伐他汀治疗与以下方面相关：至第14天无肾衰竭的天数较少(10.1 μm±5.3 vs. 11.0 μm±4.7，P = 0.01)，至第14天无肝衰竭的天数较少(10.8 μm±5.0 vs. 11.8 μm±4.3，P = 0.003)。瑞舒伐他汀与血清肌酸激酶水平超过正常范围上限10倍的发生率增加无关。 结论：瑞舒伐他汀治疗未改善脓毒症相关ARDS患者的临床结局，可能导致肝肾器官功能障碍。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Survival Analysis; Aged; Adult; Hospital Mortality; Treatment Failure; Sepsis/*complications/mortality; Hydroxymethylglutaryl-CoA Reductase Inhibitors/adverse effects/*therapeutic use; Creatine Kinase/blood; Fluorobenzenes/adverse effects/*therapeutic use; Liver Failure/etiology; Pyrimidines/adverse effects/*therapeutic use; Renal Insufficiency/etiology; Respiratory Distress Syndrome/*drug therapy/etiology/mortality; Rosuvastatin Calcium; Sulfonamides/adverse effects/*therapeutic use

Traumatic intracranial hypertension - Stocchetti, Nino; Maas, Andrew I. R. (The New England journal of medicine, 2014)
外伤性颅内高压
Keywords: Humans; Decompressive Craniectomy; Saline Solution, Hypertonic/therapeutic use; Osmolar Concentration; *Intracranial Hypertension/etiology/physiopathology/therapy; *Intracranial Pressure; Craniocerebral Trauma/*complications; Drainage; Mannitol/therapeutic use

Case records of the Massachusetts General Hospital. Case 15-2014. A man in the military who was injured by an improvised explosive device in Afghanistan. - Sheridan, Robert L.; Shumaker, Peter R.; King, David R.; Wright, Cameron D.; Itani, Kamal M. F.; Cancio, Leopoldo C. (The New England journal of medicine, 2014)
麻省总医院的病例记录。病例15-2014。一名军人在阿富汗被简易爆炸装置击伤。
Keywords: Humans; Male; Adult; United States; *Military Personnel; Afghan Campaign 2001-; Afghanistan; Blast Injuries/*therapy; Military Medicine/methods/*organization & administration; Multiple Trauma/etiology/*therapy

ICU-acquired weakness and recovery from critical illness - Kress, John P.; Hall, Jesse B. (The New England journal of medicine, 2014)
ICU获得性虚弱和危重症恢复
Keywords: Humans; Risk Factors; *Intensive Care Units; Critical Illness/*rehabilitation; Muscle Fibers, Skeletal/pathology/physiology; Muscle Weakness/diagnosis/*etiology/physiopathology/prevention & control; Polyneuropathies/diagnosis/*etiology/physiopathology

Is there a good MAP for septic shock? - Russell, James A (The New England journal of medicine, 2014)
脓毒性休克是否有良好的MAP？
Keywords: Humans; Female; Male; *Blood Pressure; Shock, Septic/*therapy; Vasoconstrictor Agents/*therapeutic use; Resuscitation/*methods

High versus low blood-pressure target in patients with septic shock - Asfar, Pierre; Meziani, Ferhat; Hamel, Jean-François; Grelon, Fabien; Megarbane, Bruno; Anguel, Nadia; Mira, Jean-Paul; Dequin, Pierre-François; Gergaud, Soizic; Weiss, Nicolas; Legay, François; Le Tulzo, Yves; et al. (The New England journal of medicine, 2014)
BACKGROUND: The Surviving Sepsis Campaign recommends targeting a mean arterial pressure of at least 65 mm Hg during initial resuscitation of patients with septic shock. However, whether this blood-pressure target is more or less effective than a higher target is unknown. METHODS: In a multicenter, open-label trial, we randomly assigned 776 patients with septic shock to undergo resuscitation with a mean arterial pressure target of either 80 to 85 mm Hg (high-target group) or 65 to 70 mm Hg (low-target group). The primary end point was mortality at day 28. RESULTS: At 28 days, there was no significant between-group difference in mortality, with deaths reported in 142 of 388 patients in the high-target group (36.6%) and 132 of 388 patients in the low-target group (34.0%) (hazard ratio in the high-target group, 1.07; 95% confidence interval [CI], 0.84 to 1.38; P=0.57). There was also no significant difference in mortality at 90 days, with 170 deaths (43.8%) and 164 deaths (42.3%), respectively (hazard ratio, 1.04; 95% CI, 0.83 to 1.30; P=0.74). The occurrence of serious adverse events did not differ significantly between the two groups (74 events [19.1%] and 69 events [17.8%], respectively; P=0.64). However, the incidence of newly diagnosed atrial fibrillation was higher in the high-target group than in the low-target group. Among patients with chronic hypertension, those in the high-target group required less renal-replacement therapy than did those in the low-target group, but such therapy was not associated with a difference in mortality. CONCLUSIONS: Targeting a mean arterial pressure of 80 to 85 mm Hg, as compared with 65 to 70 mm Hg, in patients with septic shock undergoing resuscitation did not result in significant differences in mortality at either 28 or 90 days.
脓毒性休克患者中的高vs.低血压目标 背景：拯救脓毒症运动建议脓毒性休克患者初始复苏期间将平均动脉压定为至少65 mmHg。但是，尚不清楚这种血压目标是否比更高的目标更有效。 方法：在一项多中心、开放标签试验中，我们将776例脓毒性休克患者随机分配至接受平均动脉压目标为80-85 mmHg（高目标组）或65-70 mmHg（低目标组）的复苏。主要终点为第28天的死亡率。 结果：28天时，死亡率无显著的组间差异，高目标组388例患者中的142例(36.6%)和低目标组388例患者中的132例(34.0%)报告了死亡（高目标组的风险比，1.07；95%置信区间[CI]，0.84至1.38；P = 0.57）。90天时的死亡率也无显著差异，分别为170例死亡(43.8%)和164例死亡(42.3%)（风险比，1.04；95%CI，0.83-1.30；P = 0.74）。两组间严重不良事件的发生率无显著差异（分别为74起事件[19.1%]和69起事件[17.8%]；P = 0.64）。但是，高目标组新诊断房颤的发生率高于低目标组。在慢性高血压患者中，与低目标组相比，高目标组患者需要较少的肾脏替代治疗，但这种治疗与死亡率差异无关。 结论：与65-70 mmHg相比，接受复苏的感染性休克患者的平均动脉压目标为80-85 mmHg，在28天或90天死亡率方面没有显著差异。
Keywords: Humans; Female; Male; Middle Aged; Aged; Incidence; *Blood Pressure; Renal Replacement Therapy; Vasoconstrictor Agents/*therapeutic use; Atrial Fibrillation/epidemiology; Resuscitation/adverse effects/*methods; Shock, Septic/mortality/physiopathology/*therapy

Case records of the Massachusetts General Hospital. Case 11-2014. A man with traumatic injuries after a bomb explosion at the Boston Marathon. - Eikermann, Matthias; Velmahos, George; Abbara, Suhny; Huang, Paul L.; Fagan, Shawn P.; Hirschberg, Ronald E.; Kwon, John Y.; NosÃ©, Vania (The New England journal of medicine, 2014)
麻省总医院的病例记录。病例11-2014。一名男子在波士顿马拉松的一次爆炸中受伤。
Keywords: Humans; Male; Adult; Echocardiography; Tourniquets; Boston; Electrocardiography; Radiography, Thoracic; Heart/*diagnostic imaging; Leg/diagnostic imaging; *Bombs; *Explosions; Amputation, Traumatic/*surgery/therapy; Amputation/rehabilitation; Artifacts; Blast Injuries/diagnosis/rehabilitation/*surgery/therapy; Burns/therapy; Buttocks/diagnostic imaging; Foot Injuries/diagnostic imaging/surgery; Foreign Bodies/*diagnostic imaging/surgery; Foreign-Body Migration/*diagnostic imaging; Leg Injuries/*diagnostic imaging/surgery; Multidetector Computed Tomography; Running

Albumin replacement in patients with severe sepsis or septic shock - Caironi, Pietro; Tognoni, Gianni; Masson, Serge; Fumagalli, Roberto; Pesenti, Antonio; Romero, Marilena; Fanizza, Caterina; Caspani, Luisa; Faenza, Stefano; Grasselli, Giacomo; Iapichino, Gaetano; Antonelli, Massimo; et al. (The New England journal of medicine, 2014)
BACKGROUND: Although previous studies have suggested the potential advantages of albumin administration in patients with severe sepsis, its efficacy has not been fully established. METHODS: In this multicenter, open-label trial, we randomly assigned 1818 patients with severe sepsis, in 100 intensive care units (ICUs), to receive either 20% albumin and crystalloid solution or crystalloid solution alone. In the albumin group, the target serum albumin concentration was 30 g per liter or more until discharge from the ICU or 28 days after randomization. The primary outcome was death from any cause at 28 days. Secondary outcomes were death from any cause at 90 days, the number of patients with organ dysfunction and the degree of dysfunction, and length of stay in the ICU and the hospital. RESULTS: During the first 7 days, patients in the albumin group, as compared with those in the crystalloid group, had a higher mean arterial pressure (P=0.03) and lower net fluid balance (P<0.001). The total daily amount of administered fluid did not differ significantly between the two groups (P=0.10). At 28 days, 285 of 895 patients (31.8%) in the albumin group and 288 of 900 (32.0%) in the crystalloid group had died (relative risk in the albumin group, 1.00; 95% confidence interval [CI], 0.87 to 1.14; P=0.94). At 90 days, 365 of 888 patients (41.1%) in the albumin group and 389 of 893 (43.6%) in the crystalloid group had died (relative risk, 0.94; 95% CI, 0.85 to 1.05; P=0.29). No significant differences in other secondary outcomes were observed between the two groups. CONCLUSIONS: In patients with severe sepsis, albumin replacement in addition to crystalloids, as compared with crystalloids alone, did not improve the rate of survival at 28 and 90 days.
白蛋白替代治疗重度败血症或感染性休克患者 背景：尽管既往研究表明，在重度脓毒症患者中给予白蛋白具有潜在优势，但其疗效尚未完全确立。 方法：在这项多中心、开放标签试验中，我们将1818例重度脓毒症患者随机分配至100个重症监护室(ICU)，接受20%白蛋白和晶体溶液或单独接受晶体溶液。在白蛋白组，目标血清白蛋白浓度≥30 g/l，直至离开ICU或随机化后28天。主要结局为第28天因任何原因死亡。次要结局为90天时任何原因导致的死亡、器官功能障碍的患者数量和功能障碍的程度以及ICU和医院的住院时间。 结果：在前7天，与晶体组相比，白蛋白组患者的平均动脉压较高(P = 0.03)，净液体平衡较低(P < 0.001)。两组之间的每日总液体量没有显著差异(P = 0.10)。第28天，白蛋白组895例患者中的285例(31.8%)和晶体组900例患者中的288例(32.0%)死亡（白蛋白组的相对风险，1.00；95%置信区间[CI]，0.87-1.14；P = 0.94）。90天时，白蛋白组888例患者中的365例(41.1%)和晶体组893例患者中的389例(43.6%)死亡（相对风险，0.94；95%CI，0.85-1.05；P = 0.29）。未观察到两组之间其他次要结局的显著差异。 结论：在重度脓毒症患者中，与单独使用晶体组相比，晶体组加用白蛋白替代治疗没有改善28天和90天的生存率。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Aged; Crystalloid Solutions; Survival Rate; Sepsis/mortality/*therapy; Shock, Septic/mortality/*therapy; Albumins/*administration & dosage; Isotonic Solutions/*administration & dosage; Rehydration Solutions/*therapeutic use; Serum Albumin/analysis

Nutrition in the acute phase of critical illness - Casaer, Michael P.; Van den Berghe, Greet (The New England journal of medicine, 2014)
危重症急性期的营养
Keywords: Humans; Time Factors; Animals; Randomized Controlled Trials as Topic; Critical Illness/*rehabilitation; *Nutritional Requirements; Amino Acids/administration & dosage; Anorexia/diet therapy; Enteral Nutrition/*methods; Food; Lipids/administration & dosage; Micronutrients/administration & dosage; Parenteral Nutrition/*methods

Images in clinical medicine. Reexpansion pulmonary edema after thoracentesis. - Perricone, Giovanni; Mazzarelli, Chiara (The New England journal of medicine, 2014)
临床医学图像。胸腔穿刺术后复张性肺水肿。
Keywords: Humans; Female; Aged; Radiography; Paracentesis/*adverse effects; Pleural Effusion/therapy; Pulmonary Edema/*diagnostic imaging/etiology

Speech in an orally intubated patient - Girbes, Armand R. J.; Elbers, Paul W. G. (The New England journal of medicine, 2014)
经口插管患者的言语
Keywords: Humans; Male; Middle Aged; *Intubation, Intratracheal; *Larynx, Artificial; *Speech, Alaryngeal/instrumentation

Late outcomes of a randomized trial of high-frequency oscillation in neonates - Zivanovic, Sanja; Peacock, Janet; Alcazar-Paris, Mireia; Lo, Jessica W.; Lunt, Alan; Marlow, Neil; Calvert, Sandy; Greenough, Anne (The New England journal of medicine, 2014)
BACKGROUND: Results from an observational study involving neonates suggested that high-frequency oscillatory ventilation (HFOV), as compared with conventional ventilation, was associated with superior small-airway function at follow-up. Data from randomized trials are needed to confirm this finding. METHODS: We studied 319 adolescents who had been born before 29 weeks of gestation and had been enrolled in a multicenter, randomized trial that compared HFOV with conventional ventilation immediately after birth. The trial involved 797 neonates, of whom 592 survived to hospital discharge. We compared follow-up data from adolescents who had been randomly assigned to HFOV with follow-up data from those who had been randomly assigned to conventional ventilation, with respect to lung function and respiratory health, health-related quality of life, and functional status, as assessed with the use of questionnaires completed when the participants were 11 to 14 years of age. The primary outcome was forced expiratory flow at 75% of the expired vital capacity (FEF75). RESULTS: The HFOV group had superior results on a test of small-airway function (z score for FEF75, -0.97 with HFOV vs. -1.19 with conventional therapy; adjusted difference, 0.23 [95% confidence interval, 0.02 to 0.45]). There were significant differences in favor of HFOV in several other measures of respiratory function, including forced expiratory volume in 1 second, forced vital capacity, peak expiratory flow, diffusing capacity, and impulse-oscillometric findings. As compared with the conventional-therapy group, the HFOV group had significantly higher ratings from teachers in three of eight school subjects assessed, but there were no other significant differences in functional outcomes. CONCLUSIONS: In a randomized trial involving children who had been born extremely prematurely, those who had undergone HFOV, as compared with those who had received conventional ventilation, had superior lung function at 11 to 14 years of age, with no evidence of poorer functional outcomes.
新生儿高频振荡随机试验的晚期结局 背景：一项涉及新生儿的观察性研究的结果表明，与常规通气相比，高频振荡通气(HFOV)与随访时小气道功能较优相关。需要随机试验的数据来证实这一结果。 方法：我们研究了319名在妊娠29周前出生的青少年，入组一项多中心随机试验，比较了HFOV与出生后立即常规通气。试验涉及797名新生儿，其中592名存活至出院。我们比较了随机分配接受HFOV的青少年的随访数据与随机分配接受常规通气的青少年的随访数据，包括肺功能和呼吸健康、健康相关生活质量和功能状态，当受试者年龄为11至14岁时，通过使用问卷进行评估。主要结局为75%呼气肺活量(FEF75)时的用力呼气流量。 结果：HFOV组的小气道功能试验结果更优（FEF75的z评分， -HFOV组为0.97，常规治疗组为-1.19；校正后差异，0.23[95%置信区间，0.02-0.45]）。在呼吸功能的其他几个测量指标中，包括1秒用力呼气容积、用力肺活量、呼气峰流量、弥散量和脉冲振荡结果，存在有利于HFOV的显著差异。与常规治疗组相比，HFOV组8名接受评估的学校受试者中有3名的教师的评分显著更高，但功能结局无其他显著差异。 结论：在一项涉及极早产儿童的随机试验中，与接受常规通气的儿童相比，接受HFOV的儿童在11-14岁时肺功能更优，无证据表明功能结局较差。
Keywords: Humans; Female; Male; Respiration, Artificial; Adolescent; Child; Infant, Newborn; Follow-Up Studies; Quality of Life; *High-Frequency Ventilation; *Infant, Extremely Premature; *Forced Expiratory Flow Rates; *Respiration

Videos in clinical medicine. PICC placement in the neonate. - McCay, Amy S.; Elliott, Elizabeth C.; Walden, Marlene (2014)
临床医学视频。新生儿PICC置入。
Keywords: Humans; Infant, Newborn; Parenteral Nutrition/methods; Contraindications; Catheterization, Central Venous/adverse effects/instrumentation/*methods; Central Venous Catheters; Infant, Very Low Birth Weight

Bleeding and coagulopathies in critical care - Hunt, Beverley J. (The New England journal of medicine, 2014)
重症监护中的出血和凝血病
Keywords: Humans; Critical Care; Diagnosis, Differential; Blood Coagulation Disorders/complications/*diagnosis/therapy; Blood Component Transfusion; Disseminated Intravascular Coagulation/diagnosis; Hemorrhage/etiology/*therapy; Kidney Diseases/complications/diagnosis; Liver Diseases/complications/diagnosis; Thrombocytopenia/diagnosis

Case records of the Massachusetts General Hospital. Case 6-2014. A 35-day-old boy with fever, vomiting, mottled skin, and severe anemia. - Yager, Phoebe H.; Luginbuhl, Lynn M.; Dekker, John P. (The New England journal of medicine, 2014)
麻省总医院的病例记录。病例6-2014。患儿男，35天，发热、呕吐、皮肤斑驳、重度贫血。
Keywords: Humans; Male; Diagnosis, Differential; Infant; Fever/etiology; Vomiting/etiology; Anemia/*etiology; Babesia microti/*isolation & purification; Babesiosis/complications/congenital/*diagnosis/therapy; Blood/*parasitology; Exchange Transfusion, Whole Blood/*methods; Sepsis/etiology/therapy; Skin Diseases/etiology; Tick-Borne Diseases/diagnosis

The hospital-dependent patient - Reuben, David B.; Tinetti, Mary E. (The New England journal of medicine, 2014)
依赖医院的患者
Keywords: Humans; United States; Patient Readmission/*statistics & numerical data; *Hospitalization; Professional-Patient Relations; Medicare

Clinical practice. Community-acquired pneumonia. - Wunderink, Richard G.; Waterer, Grant W. (The New England journal of medicine, 2014)
临床实践。社区获得性肺炎。
Keywords: Humans; Female; Aged; Diagnosis, Differential; Practice Guidelines as Topic; Hospitalization; Drug Resistance, Bacterial; Anti-Bacterial Agents/*therapeutic use; Lung/diagnostic imaging; Radiography; Alzheimer Disease/complications; Community-Acquired Infections/diagnosis/microbiology/therapy; Pneumonia/diagnosis/microbiology/*therapy

Sedation and delirium in the intensive care unit - Reade, Michael C.; Finfer, Simon (The New England journal of medicine, 2014)
重症监护室中的镇静和谵妄
Keywords: Humans; Intensive Care Units; Respiration, Artificial; Algorithms; *Postoperative Care/adverse effects; Analgesics/adverse effects/*therapeutic use; Delirium/*drug therapy/etiology; Hypnotics and Sedatives/administration & dosage/*adverse effects; Pain/complications/*drug therapy; Postoperative Complications/*drug therapy/etiology

Still delirious after all these years - Jones, David S. (The New England journal of medicine, 2014)
经过这么多年仍精神错乱
Keywords: Humans; History, 20th Century; Cardiac Surgical Procedures/history; Critical Care/*history; Delirium/etiology/*history; Intensive Care Units/history; Postoperative Care/adverse effects/*history; Postoperative Complications/*history

Videos in clinical medicine. Endotracheal extubation. - Ortega, Rafael; Connor, Christopher; Rodriguez, Gerardo; Spencer, Caresse (2014)
Endotracheal extubation should be performed without causing trauma, while maintaining adequate oxygenation and ventilation. The equipment needed to provide suction, ventilation, and reintubation should be readily available. If extubation is judged to be unsafe, the procedure should be postponed and the patient reevaluated. Most complications related to extubation are preventable. Before performing extubation, the clinician must carefully prepare the medical resources needed to address reasonably foreseeable complications. A failed extubation can lead to a precipitous deterioration in the patient's condition, and attempts to improvise solutions under these challenging circumstances are rarely satisfactory.
临床医学视频。气管内拔管。 应在不造成创伤的情况下进行气管内拔管，同时维持充分的氧合和通气。提供抽吸、通气和重新插管所需的设备应随时可用。如果判定拔管不安全，应推迟手术并重新评估患者。大多数拔管相关并发症是可以预防的。在拔管之前，临床医生必须仔细准备处理合理可预见并发症所需的医疗资源。失败的拔管可导致患者病情的急速恶化，在这些具有挑战性的情况下，尝试改进解决方案很少能令人满意。
Keywords: Humans; Contraindications; Intubation, Intratracheal/instrumentation; Airway Extubation/adverse effects/*methods; Obesity, Morbid

Chronic critical illness - Lamas, Daniela (The New England journal of medicine, 2014)
慢性危重症
Keywords: Humans; Intensive Care Units; *Critical Illness; *Communication; Third-Party Consent; *Physician-Patient Relations; *Chronic Disease; Tracheotomy; Unnecessary Procedures/ethics

Tight glycemic control in children--is the target in sight? - Agus, Michael S. D. (The New England journal of medicine, 2014)
儿童严格控制血糖——目标在眼前吗？
Keywords: Humans; Critical Illness/*therapy; Hypoglycemic Agents/*administration & dosage; Insulin/*administration & dosage; Hyperglycemia/*drug therapy; *Blood Glucose; *Health Care Costs; *Length of Stay

A randomized trial of hyperglycemic control in pediatric intensive care - Macrae, Duncan; Grieve, Richard; Allen, Elizabeth; Sadique, Zia; Morris, Kevin; Pappachan, John; Parslow, Roger; Tasker, Robert C.; Elbourne, Diana (The New England journal of medicine, 2014)
BACKGROUND: Whether an insulin infusion should be used for tight control of hyperglycemia in critically ill children remains unclear. METHODS: We randomly assigned children (â‰¤16 years of age) who were admitted to the pediatric intensive care unit (ICU) and were expected to require mechanical ventilation and vasoactive drugs for at least 12 hours to either tight glycemic control, with a target blood glucose range of 72 to 126 mg per deciliter (4.0 to 7.0 mmol per liter), or conventional glycemic control, with a target level below 216 mg per deciliter (12.0 mmol per liter). The primary outcome was the number of days alive and free from mechanical ventilation at 30 days after randomization. The main prespecified subgroup analysis compared children who had undergone cardiac surgery with those who had not. We also assessed costs of hospital and community health services. RESULTS: A total of 1369 patients at 13 centers in England underwent randomization: 694 to tight glycemic control and 675 to conventional glycemic control; 60% had undergone cardiac surgery. The mean between-group difference in the number of days alive and free from mechanical ventilation at 30 days was 0.36 days (95% confidence interval [CI], -0.42 to 1.14); the effects did not differ according to subgroup. Severe hypoglycemia (blood glucose, <36 mg per deciliter [2.0 mmol per liter]) occurred in a higher proportion of children in the tight-glycemic-control group than in the conventional-glycemic-control group (7.3% vs. 1.5%, P<0.001). Overall, the mean 12-month costs were lower in the tight-glycemic-control group than in the conventional-glycemic-control group. The mean 12-month costs were similar in the two groups in the cardiac-surgery subgroup, but in the subgroup that had not undergone cardiac surgery, the mean cost was significantly lower in the tight-glycemic-control group than in the conventional-glycemic-control group: -$13,120 (95% CI, -$24,682 to -$1,559). CONCLUSIONS: This multicenter, randomized trial showed that tight glycemic control in critically ill children had no significant effect on major clinical outcomes, although the incidence of hypoglycemia was higher with tight glucose control than with conventional glucose control.
儿科重症监护中高血糖控制的随机试验 背景：胰岛素输注是否应用于危重儿童高血糖的严格控制仍不清楚。 方法：我们将入住儿科重症监护室(ICU)、预期需要机械通气和血管活性药物治疗至少12小时的儿童（â‰ë16岁）随机分配至严格的血糖控制组，目标血糖范围为72-126 mg/dl(4.0-7.0 mmol/l)，或常规血糖控制，目标水平低于216 mg/dl(12.0 mmol/l)。主要结局是随机化后30天时存活且无机械通气的天数。预定的主要亚组分析比较了接受过心脏手术和未接受过心脏手术的儿童。我们还评估了医院和社区卫生服务的成本。 结果：英格兰13个中心的共1369例患者接受随机分组：694例接受严格血糖控制，675例接受常规血糖控制；60%接受过心脏手术。30天时存活和无机械通气天数的平均组间差异为0.36天（95%置信区间[CI]，-0.42至1.14）；效应没有根据亚组而有差异。严格血糖控制组儿童发生严重低血糖（血糖，< 36 mg/dl[2.0 mmol/l]）的比例高于常规血糖控制组(7.3%vs. 1.5%，P < 0.001)。总体而言，严格血糖控制组的平均12个月费用低于常规血糖控制组。在心脏手术亚组中，两组的平均12个月费用相似，但在未接受心脏手术的亚组中，严格血糖控制组的平均费用显著低于常规血糖控制组：-13,120美元（95%CI，-24,682美元至-1,559美元）。 结论：这项多中心、随机试验表明，尽管严格血糖控制的低血糖发生率高于常规血糖控制，但危重儿童中严格血糖控制对主要临床结局无显著影响。
Keywords: Humans; Treatment Outcome; Respiration, Artificial; Cardiac Surgical Procedures; Adolescent; Child; Infant; Child, Preschool; Infusions, Intravenous; Critical Care/methods; Critical Illness/mortality/*therapy; Intensive Care Units, Pediatric; Energy Intake; Hyperglycemia/*drug therapy; Hypoglycemia/chemically induced; *Blood Glucose; *Health Care Costs; *Length of Stay; Hospitalization/economics/statistics & numerical data; Hypoglycemic Agents/*administration & dosage/adverse effects; Insulin/*administration & dosage/adverse effects

Images in clinical medicine. Rumpel-Leede sign. - Wang, Krystle; Lee, Jason (The New England journal of medicine, 2014)
临床医学图像。Rumpel-Leede征。
Keywords: Humans; Female; Middle Aged; *Iatrogenic Disease; Arm/pathology; Blood Pressure Monitors/*adverse effects; Ecchymosis/*etiology/pathology

Videos in clinical medicine. Pulmonary-artery catheterization. - Kelly, Christopher R.; Rabbani, LeRoy E. (2013)
临床医学视频。肺动脉导管插入。
Keywords: Humans; Contraindications; Aftercare; Arrhythmias, Cardiac/etiology; Catheterization, Swan-Ganz/adverse effects/*methods; Heart Diseases/diagnosis; Hypertension, Pulmonary/diagnosis

Clinical problem-solving. A shocking development. - Levenson, Joshua E.; Kaul, Daniel R.; Saint, Sanjay; Nallamothu, Brahmajee K.; Gurm, Hitinder S. (The New England journal of medicine, 2013)
临床问题解决。令人震惊的发展。
Keywords: Humans; Female; Young Adult; Diagnosis, Differential; Echocardiography; Antiviral Agents/therapeutic use; Electrocardiography; Vomiting/etiology; Influenza A virus/isolation & purification; Influenza, Human/*complications/diagnosis/drug therapy; Mucocutaneous Lymph Node Syndrome/complications; Myocarditis/*diagnosis/etiology; Shock, Cardiogenic/etiology

Ventilator-induced lung injury - Slutsky, Arthur S.; Ranieri, V. Marco (The New England journal of medicine, 2013)
呼吸机所致肺损伤
Keywords: Humans; Animals; Tidal Volume; Lung/pathology/*physiology; Positive-Pressure Respiration/adverse effects; Pulmonary Edema/etiology; Ventilator-Induced Lung Injury/etiology/*prevention & control

Videos in clinical medicine: Laryngeal mask airway in medical emergencies - Lighthall, Geoffrey; Harrison, T. Kyle; Chu, Larry F. (2013)
This video demonstrates the placement of a laryngeal mask airway, an alternative airway device that is both efficacious and easy to place. The laryngeal mask airway is routinely used for patients receiving general anesthesia and, increasingly, in patient resuscitation.
临床医学中的视频：内科急症中的喉罩 本视频显示了喉罩气道的置入，这是一种有效且易于置入的替代气道器械。喉罩常规用于接受全身麻醉的患者，越来越多地用于患者复苏。
Keywords: Humans; *Laryngeal Masks/adverse effects; Cardiopulmonary Resuscitation/instrumentation/*methods; Emergencies; Heart Arrest/therapy

Circulatory shock - Vincent, Jean-Louis; De Backer, Daniel (The New England journal of medicine, 2013)
循环性休克
Keywords: Humans; Diagnosis, Differential; Vasoconstrictor Agents/therapeutic use; Cardiotonic Agents/therapeutic use; *Fluid Therapy; Cardiovascular Agents/*therapeutic use; Lactic Acid/blood; Shock/diagnosis/drug therapy/*therapy; Vasodilator Agents/therapeutic use

High-flow nasal cannulae in very preterm infants after extubation - Manley, Brett J.; Owen, Louise S.; Doyle, Lex W.; Andersen, Chad C.; Cartwright, David W.; Pritchard, Margo A.; Donath, Susan M.; Davis, Peter G. (The New England journal of medicine, 2013)
BACKGROUND: The use of high-flow nasal cannulae is an increasingly popular alternative to nasal continuous positive airway pressure (CPAP) for noninvasive respiratory support of very preterm infants (gestational age, <32 weeks) after extubation. However, data on the efficacy or safety of such cannulae in this population are lacking. METHODS: In this multicenter, randomized, noninferiority trial, we assigned 303 very preterm infants to receive treatment with either high-flow nasal cannulae (5 to 6 liters per minute) or nasal CPAP (7 cm of water) after extubation. The primary outcome was treatment failure within 7 days. Noninferiority was determined by calculating the absolute difference in the risk of the primary outcome; the margin of noninferiority was 20 percentage points. Infants in whom treatment with high-flow nasal cannulae failed could be treated with nasal CPAP; infants in whom nasal CPAP failed were reintubated. RESULTS: The use of high-flow nasal cannulae was noninferior to the use of nasal CPAP, with treatment failure occurring in 52 of 152 infants (34.2%) in the nasal-cannulae group and in 39 of 151 infants (25.8%) in the CPAP group (risk difference, 8.4 percentage points; 95% confidence interval, -1.9 to 18.7). Almost half the infants in whom treatment with high-flow nasal cannulae failed were successfully treated with CPAP without reintubation. The incidence of nasal trauma was significantly lower in the nasal-cannulae group than in the CPAP group (P=0.01), but there were no significant differences in rates of serious adverse events or other complications. CONCLUSIONS: Although the result for the primary outcome was close to the margin of noninferiority, the efficacy of high-flow nasal cannulae was similar to that of CPAP as respiratory support for very preterm infants after extubation.
高流量鼻导管在早产儿拔管后的应用 背景：高流量鼻插管作为经鼻持续气道正压通气(CPAP)的替代方法，在早产儿（胎龄，< 32周）拔管后进行无创呼吸支持时越来越受欢迎。但是，缺乏此类插管在该人群中的疗效或安全性数据。 方法：在这项多中心、随机、非劣效性试验中，我们将303例早早产儿分配至拔管后接受高流量鼻插管（5-6L/分钟）或鼻CPAP（7 cm水）治疗。主要结局是7天内治疗失败。通过计算主要结局风险的绝对差异确定非劣效性；非劣效性界值为20个百分点。经鼻高流量插管治疗失败的患儿可经鼻CPAP治疗；经鼻CPAP治疗失败的患儿可重新插管。 结果：高流量鼻导管的使用不劣于鼻CPAP的使用，鼻导管组152名婴儿中有52名(34.2%)治疗失败，CPAP组151名婴儿中有39名(25.8%)治疗失败（风险差异，8.4个百分点；95%置信区间，-1.9至18.7）。几乎一半高流量鼻插管治疗失败的婴儿使用CPAP治疗成功，未重新插管。鼻插管组的鼻创伤发生率显著低于CPAP组(P = 0.01)，但严重不良事件或其他并发症的发生率无显著差异。 结论：尽管主要结局的结果接近非劣效性边界，但高流量鼻插管作为拔管后极早产儿呼吸支持的有效性与CPAP相似。
Keywords: Humans; Female; Male; Infant, Newborn; Gestational Age; *Infant, Premature; Treatment Failure; *Airway Extubation; *Continuous Positive Airway Pressure; Catheters; Oxygen Inhalation Therapy/*instrumentation/methods

Disability after critical illness - Herridge, Margaret; Cameron, Jill I. (The New England journal of medicine, 2013)
Disability after critical illness
Keywords: Humans; Female; Male; Cognition Disorders/*etiology; Critical Illness/*psychology; Respiratory Insufficiency/*complications; Shock/*complications

Long-term cognitive impairment after critical illness - Pandharipande, P. P.; Girard, T. D.; Jackson, J. C.; Morandi, A.; Thompson, J. L.; Pun, B. T.; Brummel, N. E.; Hughes, C. G.; Vasilevskis, E. E.; Shintani, A. K.; Moons, K. G.; Geevarghese, S. K.; et al. (The New England journal of medicine, 2013)
BACKGROUND: Survivors of critical illness often have a prolonged and disabling form of cognitive impairment that remains inadequately characterized. METHODS: We enrolled adults with respiratory failure or shock in the medical or surgical intensive care unit (ICU), evaluated them for in-hospital delirium, and assessed global cognition and executive function 3 and 12 months after discharge with the use of the Repeatable Battery for the Assessment of Neuropsychological Status (population age-adjusted mean [±SD] score, 100±15, with lower values indicating worse global cognition) and the Trail Making Test, Part B (population age-, sex-, and education-adjusted mean score, 50±10, with lower scores indicating worse executive function). Associations of the duration of delirium and the use of sedative or analgesic agents with the outcomes were assessed with the use of linear regression, with adjustment for potential confounders. RESULTS: Of the 821 patients enrolled, 6% had cognitive impairment at baseline, and delirium developed in 74% during the hospital stay. At 3 months, 40% of the patients had global cognition scores that were 1.5 SD below the population means (similar to scores for patients with moderate traumatic brain injury), and 26% had scores 2 SD below the population means (similar to scores for patients with mild Alzheimer's disease). Deficits occurred in both older and younger patients and persisted, with 34% and 24% of all patients with assessments at 12 months that were similar to scores for patients with moderate traumatic brain injury and scores for patients with mild Alzheimer's disease, respectively. A longer duration of delirium was independently associated with worse global cognition at 3 and 12 months (P=0.001 and P=0.04, respectively) and worse executive function at 3 and 12 months (P=0.004 and P=0.007, respectively). Use of sedative or analgesic medications was not consistently associated with cognitive impairment at 3 and 12 months. CONCLUSIONS: Patients in medical and surgical ICUs are at high risk for long-term cognitive impairment. A longer duration of delirium in the hospital was associated with worse global cognition and executive function scores at 3 and 12 months.
危重疾病后的长期认知功能障碍 背景：危重疾病幸存者通常有长期和致残性认知功能障碍，尚未充分描述其特征。 方法：我们入选了内科或外科重症监护室(ICU)的呼吸衰竭或休克成人患者，对其院内谵妄进行了评价，并在出院后3个月和12个月，使用重复性成套测试评估神经心理状态（人群年龄校正的平均[Λ±SD]评分，100æ±15，较低值表示整体认知较差）和连线测试B部分（人群年龄、性别、和教育校正的平均评分，50≦±10，分数越低表示执行功能越差）。通过线性回归，调整潜在的混杂因素，评估谵妄持续时间、镇静剂或镇痛剂的使用与结局的相关性。 结果：在入组的821例患者中，6%在基线时有认知功能障碍，74%在住院期间发生谵妄。第3个月时，40%的患者的整体认知评分比群体平均值低1.5 SD（与中度创伤性脑损伤患者的评分相似），26%的患者比群体平均值低2 SD（与轻度阿尔茨海默病患者的评分相似）。在老年和年轻患者中均存在缺陷且持续存在，在第12个月评估时，34%和24%的患者与中度创伤性脑损伤患者和轻度阿尔茨海默病患者的评分相似。谵妄持续时间较长与3个月和12个月时整体认知较差（分别为P = 0.001和P = 0.04）和3个月和12个月时执行功能较差（分别为P = 0.004和P = 0.007）独立相关。在3个月和12个月时，镇静或镇痛药物的使用与认知障碍不一致。 结论：内科和外科ICU中的患者存在长期认知障碍的高风险。谵妄在医院的持续时间较长与3个月和12个月时整体认知和执行功能评分较差相关。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Intensive Care Units; Linear Models; Delirium/complications; Cognition Disorders/*etiology; Critical Illness/*psychology; Respiratory Insufficiency/*complications; Shock/*complications; Executive Function

Resuscitation fluids - Myburgh, John A.; Mythen, Michael G. (The New England journal of medicine, 2013)
复苏液体
Keywords: Humans; Crystalloid Solutions; History, 19th Century; History, 20th Century; *Fluid Therapy/history; *Rehydration Solutions/chemistry/therapeutic use; Albumins/administration & dosage; Colloids/administration & dosage; Glycocalyx/physiology; Isotonic Solutions/administration & dosage; Resuscitation/history/*methods

Severe sepsis and septic shock - Angus, Derek C.; van der Poll, Tom (The New England journal of medicine, 2013)
重度败血症和感染性休克
Keywords: Humans; Resuscitation; Risk Factors; Incidence; *Sepsis/etiology/immunology; *Shock, Septic/diagnosis/etiology/physiopathology/therapy

Critical care--an all-encompassing specialty - Finfer, Simon; Vincent, Jean-Louis (The New England journal of medicine, 2013)
重症监护--涵盖所有专业
Keywords: Humans; Intensive Care Units; *Critical Care/trends

A trial comparing noninvasive ventilation strategies in preterm infants - Kirpalani, Haresh; Millar, David; Lemyre, Brigitte; Yoder, Bradley A.; Chiu, Aaron; Roberts, Robin S. (The New England journal of medicine, 2013)
BACKGROUND: To reduce the risk of bronchopulmonary dysplasia in extremely-low-birth-weight infants, clinicians attempt to minimize the use of endotracheal intubation by the early introduction of less invasive forms of positive airway pressure. METHODS: We randomly assigned 1009 infants with a birth weight of less than 1000 g and a gestational age of less than 30 weeks to one of two forms of noninvasive respiratory support--nasal intermittent positive-pressure ventilation (IPPV) or nasal continuous positive airway pressure (CPAP)--at the time of the first use of noninvasive respiratory support during the first 28 days of life. The primary outcome was death before 36 weeks of postmenstrual age or survival with bronchopulmonary dysplasia. RESULTS: Of the 497 infants assigned to nasal IPPV for whom adequate data were available, 191 died or survived with bronchopulmonary dysplasia (38.4%), as compared with 180 of 490 infants assigned to nasal CPAP (36.7%) (adjusted odds ratio, 1.09; 95% confidence interval, 0.83 to 1.43; P=0.56). The frequencies of air leaks and necrotizing enterocolitis, the duration of respiratory support, and the time to full feedings did not differ significantly between treatment groups. CONCLUSIONS: Among extremely-low-birth-weight infants, the rate of survival to 36 weeks of postmenstrual age without bronchopulmonary dysplasia did not differ significantly after noninvasive respiratory support with nasal IPPV as compared with nasal CPAP.
一项比较早产儿无创通气策略的试验 背景：为了降低极低出生体重婴儿发生支气管肺发育不良的风险，临床医生试图通过早期引入微创型气道正压通气，尽量减少气管插管的使用。 方法：我们将1009例出生体重小于1000g、胎龄小于30周的婴儿随机分为两种无创呼吸支持方式之一——经鼻间歇正压通气(IPPV)或经鼻持续气道正压通气(CPAP)——在首次使用无创呼吸时进行。出生后28天内的长期支持。主要结局是在月经后年龄36周前死亡或支气管肺发育不良生存。 结果：在497名可获得充分数据的婴儿中，191名婴儿死亡或存活，伴有支气管肺发育不良(38.4%)，与之相比，490名接受鼻塞CPAP治疗的婴儿中有180名婴儿死亡或存活(36.7%)（校正比值比，1.09；95%置信区间，0.83至1.43；P = 0.56）。治疗组之间的漏气和坏死性小肠结肠炎的频率、呼吸支持的持续时间和完全喂养的时间没有显著差异。 结论：在极低出生体重婴儿中，与经鼻CPAP相比，采用经鼻IPPV进行无创呼吸支持后，至36周经后年龄无支气管肺发育不良的生存率无显著差异。
Keywords: Humans; Female; Male; Infant, Newborn; Survival Rate; Infant, Premature; *Continuous Positive Airway Pressure/adverse effects; *Infant, Extremely Low Birth Weight; *Intermittent Positive-Pressure Ventilation/adverse effects; Bronchopulmonary Dysplasia/epidemiology/*prevention & control; Infant, Premature, Diseases/mortality; Retinopathy of Prematurity/epidemiology

A trial of intraoperative low-tidal-volume ventilation in abdominal surgery - Futier, Emmanuel; Constantin, Jean-Michel; Paugam-Burtz, Catherine; Pascal, Julien; Eurin, Mathilde; Neuschwander, Arthur; Marret, Emmanuel; Beaussier, Marc; Gutton, Christophe; Lefrant, Jean-Yves; Allaouchiche, Bernard; Verzilli, Daniel; et al. (The New England journal of medicine, 2013)
BACKGROUND: Lung-protective ventilation with the use of low tidal volumes and positive end-expiratory pressure is considered best practice in the care of many critically ill patients. However, its role in anesthetized patients undergoing major surgery is not known. METHODS: In this multicenter, double-blind, parallel-group trial, we randomly assigned 400 adults at intermediate to high risk of pulmonary complications after major abdominal surgery to either nonprotective mechanical ventilation or a strategy of lung-protective ventilation. The primary outcome was a composite of major pulmonary and extrapulmonary complications occurring within the first 7 days after surgery. RESULTS: The two intervention groups had similar characteristics at baseline. In the intention-to-treat analysis, the primary outcome occurred in 21 of 200 patients (10.5%) assigned to lung-protective ventilation, as compared with 55 of 200 (27.5%) assigned to nonprotective ventilation (relative risk, 0.40; 95% confidence interval [CI], 0.24 to 0.68; P=0.001). Over the 7-day postoperative period, 10 patients (5.0%) assigned to lung-protective ventilation required noninvasive ventilation or intubation for acute respiratory failure, as compared with 34 (17.0%) assigned to nonprotective ventilation (relative risk, 0.29; 95% CI, 0.14 to 0.61; P=0.001). The length of the hospital stay was shorter among patients receiving lung-protective ventilation than among those receiving nonprotective ventilation (mean difference, -2.45 days; 95% CI, -4.17 to -0.72; P=0.006). CONCLUSIONS: As compared with a practice of nonprotective mechanical ventilation, the use of a lung-protective ventilation strategy in intermediate-risk and high-risk patients undergoing major abdominal surgery was associated with improved clinical outcomes and reduced health care utilization. (IMPROVE ClinicalTrials.gov number, NCT01282996.).
低潮气量通气在腹部外科手术中的应用 背景：使用低潮气量和呼气末正压进行肺保护通气被认为是许多危重患者护理的最佳实践。然而，其在接受大手术的麻醉患者中的作用尚不清楚。 方法：在这项多中心、双盲、平行组试验中，我们将400例腹部大手术后肺部并发症中-高危成人随机分配至无保护性机械通气组或肺保护性通气策略组。主要结局是术后前7天内发生的主要肺部和肺外并发症的复合终点。 结果：两个干预组在基线时具有相似的特征。在意向治疗分析中，200例肺保护通气患者中21例(10.5%)出现主要结局，相比之下，200例无保护通气患者中55例(27.5%)出现主要结局（相对风险，0.40；95%置信区间[CI]，0.24至0.68；P = 0.001）。在术后7天期间，10例(5.0%)分配接受肺保护通气的患者需要无创通气或插管治疗急性呼吸衰竭，相比之下，34例(17.0%)分配接受非保护通气的患者需要无创通气或插管治疗急性呼吸衰竭（相对风险，0.29；95%CI，0.14至0.61；P = 0.001）。接受肺保护通气的患者的住院时间短于未接受保护通气的患者（平均差异，-2.45天；95%CI，-4.17至-0.72；P = 0.006）。 结论：与无保护性机械通气实践相比，在接受重大腹部手术的中危和高危患者中使用肺保护性通气策略与临床结局改善和医疗保健利用降低相关。（改善ClinicalTrials.gov编号，NCT01282996）。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Digestive System Surgical Procedures; Intention to Treat Analysis; Abdomen/*surgery; *Tidal Volume; Positive-Pressure Respiration/*methods; Operative Time; Postoperative Complications/*prevention & control/therapy; Respiratory Insufficiency/etiology/*prevention & control/therapy

Mourning on morning rounds - Vallurupalli, Mounica (The New England journal of medicine, 2013)
早晨查房时悲伤
Keywords: Humans; Female; Male; *Internship and Residency; *Grief; Attitude of Health Personnel; *Death; Physicians/*psychology; *Adaptation, Psychological; Guilt; Students, Medical/psychology; Teaching Rounds

Case records of the Massachusetts General Hospital. Case 23-2013. A 54-year-old woman with abdominal pain, vomiting, and confusion. - Kalantar-Zadeh, Kamyar; Uppot, Raul N.; Lewandrowski, Kent B. (The New England journal of medicine, 2013)
麻省总医院的病例记录。病例3-2015。一名60岁女性患者出现腹痛、呼吸困难和复视。
Keywords: Humans; Female; Middle Aged; Diagnosis, Differential; Tomography, X-Ray Computed; Ultrasonography; Abdominal Pain/etiology; Hydrogen-Ion Concentration; Confusion/etiology; Vomiting/etiology; Acidosis, Lactic/chemically induced/*diagnosis; Diabetes Mellitus, Type 2/complications/drug therapy; Kidney/diagnostic imaging/pathology; Lactic Acid/*blood; Metformin/*adverse effects/therapeutic use; Pancreas/diagnostic imaging/pathology; Pancreatitis/chemically induced/diagnosis; Renal Insufficiency, Chronic/complications

Screening inpatients for MRSA--case closed - Edmond, Michael B.; Wenzel, Richard P. (The New England journal of medicine, 2013)
筛选住院患者的 MRSA--病例关闭
Keywords: Humans; Female; Male; *Intensive Care Units; *Methicillin-Resistant Staphylococcus aureus; Infection Control/*methods; Carrier State/*diagnosis; Cross Infection/*prevention & control; Disinfection/*methods; Staphylococcal Infections/*prevention & control

Targeted versus universal decolonization to prevent ICU infection - Huang, Susan S.; Septimus, Edward; Kleinman, Ken; Moody, Julia; Hickok, Jason; Avery, Taliser R.; Lankiewicz, Julie; Gombosev, Adrijana; Terpstra, Leah; Hartford, Fallon; Hayden, Mary K.; Jernigan, John A.; et al. (The New England journal of medicine, 2013)
BACKGROUND: Both targeted decolonization and universal decolonization of patients in intensive care units (ICUs) are candidate strategies to prevent health care-associated infections, particularly those caused by methicillin-resistant Staphylococcus aureus (MRSA). METHODS: We conducted a pragmatic, cluster-randomized trial. Hospitals were randomly assigned to one of three strategies, with all adult ICUs in a given hospital assigned to the same strategy. Group 1 implemented MRSA screening and isolation; group 2, targeted decolonization (i.e., screening, isolation, and decolonization of MRSA carriers); and group 3, universal decolonization (i.e., no screening, and decolonization of all patients). Proportional-hazards models were used to assess differences in infection reductions across the study groups, with clustering according to hospital. RESULTS: A total of 43 hospitals (including 74 ICUs and 74,256 patients during the intervention period) underwent randomization. In the intervention period versus the baseline period, modeled hazard ratios for MRSA clinical isolates were 0.92 for screening and isolation (crude rate, 3.2 vs. 3.4 isolates per 1000 days), 0.75 for targeted decolonization (3.2 vs. 4.3 isolates per 1000 days), and 0.63 for universal decolonization (2.1 vs. 3.4 isolates per 1000 days) (P=0.01 for test of all groups being equal). In the intervention versus baseline periods, hazard ratios for bloodstream infection with any pathogen in the three groups were 0.99 (crude rate, 4.1 vs. 4.2 infections per 1000 days), 0.78 (3.7 vs. 4.8 infections per 1000 days), and 0.56 (3.6 vs. 6.1 infections per 1000 days), respectively (P<0.001 for test of all groups being equal). Universal decolonization resulted in a significantly greater reduction in the rate of all bloodstream infections than either targeted decolonization or screening and isolation. One bloodstream infection was prevented per 54 patients who underwent decolonization. The reductions in rates of MRSA bloodstream infection were similar to those of all bloodstream infections, but the difference was not significant. Adverse events, which occurred in 7 patients, were mild and related to chlorhexidine. CONCLUSIONS: In routine ICU practice, universal decolonization was more effective than targeted decolonization or screening and isolation in reducing rates of MRSA clinical isolates and bloodstream infection from any pathogen.
Targeted versus universal decolonization to prevent ICU infection 背景：重症监护室(ICU)患者的靶向去定植和普遍去定植都是预防医疗保健相关感染的候选策略，特别是由耐甲氧西林金黄色葡萄球菌(MRSA)引起的感染。 方法：我们进行了一项实用的群组随机试验。医院被随机分配到三种策略之一，指定医院的所有成人ICU被分配到相同的策略。第1组实施MRSA筛查和分离；第2组，有针对性地去定植（即MRSA携带者的筛查、分离和去定植）；第3组，普遍去定植（即所有患者不进行筛查和去定植）。采用比例风险模型评估了研究组间感染减少的差异，并根据医院进行聚类。 结果：共有43家医院（包括74家ICU和74,256例患者干预期间）进行了随机化。在干预阶段与基线阶段，模拟MRSA临床分离株的风险比，筛选和分离是0.92（粗率，3.2与3.4株/1000天），靶向去定植是0.75（3.2与4.3株/1000天），和0.63（普遍去定植）（2.1与3.4个分离株/1000天）（所有组的检验相等，P = 0.01）。在干预与基线期相比，3组任何病原体血液感染的风险比分别为0.99（粗率，4.1与4.2例感染/1000天）、0.78（3.7与4.8例感染/1000天）和0.56（3.6与6.1例感染/1000天），分别进行比较（P < 0.001，所有组的检验结果相等）。与目标去定植或筛查和隔离相比，普遍去定植导致所有血液感染率显著降低。每54名进行去定植的患者预防1例血液感染。MRSA血液感染率的下降与所有血液感染率的下降相似，但是没有显著差异。7名患者发生的不良事件均为轻度，且与氯己定相关。 结论：在常规ICU实践中，普遍去定植比靶向去定植或筛选分离更有效，可降低MRSA临床分离株和任何病原菌血液感染率。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; *Intensive Care Units; Infection Control/*methods; Disease Transmission, Infectious/prevention & control; Carrier State/*diagnosis; Disinfection/*methods; *Methicillin-Resistant Staphylococcus aureus/isolation & purification; Bacteremia/psychology; Baths; Chlorhexidine/adverse effects/therapeutic use; Comparative Effectiveness Research; Cross Infection/*prevention & control/transmission; Mupirocin/adverse effects/therapeutic use; Nasal Cavity/microbiology; Staphylococcal Infections/diagnosis/*prevention & control/transmission

Prone positioning in severe acute respiratory distress syndrome - GuÃ©rin, Claude; Reignier, Jean; Richard, Jean-Christophe; Beuret, Pascal; Gacouin, Arnaud; Boulain, Thierry; Mercier, Emmanuelle; Badet, Michel; Mercat, Alain; Baudin, Olivier; Clavel, Marc; Chatellier, Delphine; et al. (The New England journal of medicine, 2013)
BACKGROUND: Previous trials involving patients with the acute respiratory distress syndrome (ARDS) have failed to show a beneficial effect of prone positioning during mechanical ventilatory support on outcomes. We evaluated the effect of early application of prone positioning on outcomes in patients with severe ARDS. METHODS: In this multicenter, prospective, randomized, controlled trial, we randomly assigned 466 patients with severe ARDS to undergo prone-positioning sessions of at least 16 hours or to be left in the supine position. Severe ARDS was defined as a ratio of the partial pressure of arterial oxygen to the fraction of inspired oxygen (FiO2) of less than 150 mm Hg, with an FiO2 of at least 0.6, a positive end-expiratory pressure of at least 5 cm of water, and a tidal volume close to 6 ml per kilogram of predicted body weight. The primary outcome was the proportion of patients who died from any cause within 28 days after inclusion. RESULTS: A total of 237 patients were assigned to the prone group, and 229 patients were assigned to the supine group. The 28-day mortality was 16.0% in the prone group and 32.8% in the supine group (P<0.001). The hazard ratio for death with prone positioning was 0.39 (95% confidence interval [CI], 0.25 to 0.63). Unadjusted 90-day mortality was 23.6% in the prone group versus 41.0% in the supine group (P<0.001), with a hazard ratio of 0.44 (95% CI, 0.29 to 0.67). The incidence of complications did not differ significantly between the groups, except for the incidence of cardiac arrests, which was higher in the supine group. CONCLUSIONS: In patients with severe ARDS, early application of prolonged prone-positioning sessions significantly decreased 28-day and 90-day mortality.
重度急性呼吸窘迫综合征的俯卧位 背景：既往涉及急性呼吸窘迫综合征(ARDS)患者的试验未能显示机械通气支持期间俯卧位对结局的有益影响。我们评估了早期应用俯卧位对重度ARDS患者结局的影响。 方法：在这项多中心、前瞻性、随机对照试验中，我们将466例重度ARDS患者随机分配至至少16小时的仰卧位或保持仰卧位。重度ARDS定义为动脉血氧分压与吸入气中的氧气分数的比值(FiO2)小于150 mmHg，FiO2至少为0.6，呼气末正压至少为5 cm水，潮气量接近预测体重的6 mL/kg。主要结局是入选后28天内全因死亡的患者比例。 结果：俯卧位组共计237名患者，仰卧位组共计229名患者。俯卧位组和仰卧位组的28天死亡率分别为16.0%和32.8%(P < 0.001)。俯卧位死亡的风险比为0.39（95%置信区间[CI]，0.25-0.63）。俯卧位组未经调整的90天死亡率为23.6%，仰卧位组为41.0%(P < 0.001)，风险比为0.44(95%CI，0.29-0.67)。除了仰卧位组心脏骤停的发生率更高外，两组间并发症的发生率无显著差异。 结论：在重度ARDS患者中，早期应用延长prone-positioning治疗显著降低了28天和90天死亡率。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Kaplan-Meier Estimate; Oxygen/blood; *Prone Position; *Positive-Pressure Respiration/methods; Respiratory Distress Syndrome/mortality/*therapy

A randomized trial of nighttime physician staffing in an intensive care unit - Kerlin, Meeta Prasad; Small, Dylan S.; Cooney, Elizabeth; Fuchs, Barry D.; Bellini, Lisa M.; Mikkelsen, Mark E.; Schweickert, William D.; Bakhru, Rita N.; Gabler, Nicole B.; Harhay, Michael O.; Hansen-Flaschen, John; Halpern, Scott D. (The New England journal of medicine, 2013)
BACKGROUND: Increasing numbers of intensive care units (ICUs) are adopting the practice of nighttime intensivist staffing despite the lack of experimental evidence of its effectiveness. METHODS: We conducted a 1-year randomized trial in an academic medical ICU of the effects of nighttime staffing with in-hospital intensivists (intervention) as compared with nighttime coverage by daytime intensivists who were available for consultation by telephone (control). We randomly assigned blocks of 7 consecutive nights to the intervention or the control strategy. The primary outcome was patients' length of stay in the ICU. Secondary outcomes were patients' length of stay in the hospital, ICU and in-hospital mortality, discharge disposition, and rates of readmission to the ICU. For length-of-stay outcomes, we performed time-to-event analyses, with data censored at the time of a patient's death or transfer to another ICU. RESULTS: A total of 1598 patients were included in the analyses. The median Acute Physiology and Chronic Health Evaluation (APACHE) III score (in which scores range from 0 to 299, with higher scores indicating more severe illness) was 67 (interquartile range, 47 to 91), the median length of stay in the ICU was 52.7 hours (interquartile range, 29.0 to 113.4), and mortality in the ICU was 18%. Patients who were admitted on intervention days were exposed to nighttime intensivists on more nights than were patients admitted on control days (median, 100% of nights [interquartile range, 67 to 100] vs. median, 0% [interquartile range, 0 to 33]; P<0.001). Nonetheless, intensivist staffing on the night of admission did not have a significant effect on the length of stay in the ICU (rate ratio for the time to ICU discharge, 0.98; 95% confidence interval [CI], 0.88 to 1.09; P=0.72), ICU mortality (relative risk, 1.07; 95% CI, 0.90 to 1.28), or any other end point. Analyses restricted to patients who were admitted at night showed similar results, as did sensitivity analyses that used different definitions of exposure and outcome. CONCLUSIONS: In an academic medical ICU in the United States, nighttime in-hospital intensivist staffing did not improve patient outcomes.
在重症监护室配备夜间医生的一项随机试验 背景：尽管缺乏有效性的实验证据，但是越来越多的重症监护室(ICU)采用夜间重症监护室人员配备的做法。 方法：我们在一个学术的医疗ICU中进行了一项为期1年的随机试验，比较了夜间配备院内重症监护医生（干预）与由可通过电话咨询（对照）的日间重症监护医生进行夜间覆盖的影响。我们将连续7晚的区组随机分配至干预或控制策略组。主要结局为患者的ICU住院时间。次要结局是患者的住院时间、ICU和住院死亡率、出院分布和再次进入ICU的比率。对于住院时间结局，我们进行了至事件发生时间分析，在患者死亡或转入另一ICU时删失数据。 结果：分析中共纳入1598例患者。中位急性生理学与慢性健康状况(APACHE)III评分（其中评分范围为0-299，评分越高表明病情越严重）为67（四分位距，47-91），中位ICU住院时间为52.7小时（四分位距，29.0-113.4），ICU死亡率为18%。干预日入院的患者与对照日入院的患者相比，夜间重症监护患者的暴露量更多（中位数，100%夜间[四分位距，67-100]vs.中位数，0%[四分位距，0-33]；P < 0.001）。但是，入住当晚的重症监护医生人员配备对ICU住院时间（至离开ICU时间的率比，0.98；95%置信区间[CI]，0.88-1.09；P = 0.72）、ICU死亡率（相对风险，1.07；95%CI，0.90-1.28）或任何其他终点均无显著影响。仅限于夜间住院患者的分析显示了相似的结果，同样的敏感性分析使用了不同的暴露和结局定义。 结论：在美国的一个学术性医疗ICU中，夜间医院内重症监护医生人员配备未改善患者结局。
Keywords: Humans; Female; Male; Middle Aged; Aged; Length of Stay; Kaplan-Meier Estimate; *Intensive Care Units; Hospitals, University; *Personnel Staffing and Scheduling; Workforce; *Hospital Mortality; *Hospitalists; Pennsylvania

In prone ventilation, one good turn deserves another - Soo Hoo, Guy W. (The New England journal of medicine, 2013)
在俯卧位通气时，一次良好的转弯是值得的
Keywords: Humans; Female; Male; *Prone Position; *Positive-Pressure Respiration; Respiratory Distress Syndrome/*therapy

Videos in clinical medicine. Needle aspiration of primary spontaneous pneumothorax. - Pasquier, Mathieu; Hugli, Olivier; Carron, Pierre-Nicolas (2013)
临床医学视频。原发性自发性气胸的针吸术。
Keywords: Humans; Contraindications; Pneumothorax/*surgery; Suction/adverse effects/instrumentation/*methods

Images in clinical medicine. Botryoid white-cell nuclei. - Chew, Edward; Juneja, Surender (The New England journal of medicine, 2013)
临床医学图像。葡萄状白细胞核。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Cell Nucleus/*pathology; Fever/*chemically induced; Leukocytes/*pathology; Methamphetamine/*adverse effects; Multiple Organ Failure/chemically induced; Unconscious, Psychology

Low glutamine levels during critical illness--adaptive or maladaptive? - Van den Berghe, Greet (The New England journal of medicine, 2013)
危重病时谷氨酰胺水平低-适应性或不适应性？
Keywords: Humans; Female; Male; *Respiration, Artificial; Antioxidants/*therapeutic use; Glutamine/*therapeutic use; Multiple Organ Failure/*drug therapy

A randomized trial of glutamine and antioxidants in critically ill patients - Heyland, Daren; Muscedere, John; Wischmeyer, Paul E.; Cook, Deborah; Jones, Gwynne; Albert, Martin; Elke, Gunnar; Berger, Mette M.; Day, Andrew G. (The New England journal of medicine, 2013)
BACKGROUND: Critically ill patients have considerable oxidative stress. Glutamine and antioxidant supplementation may offer therapeutic benefit, although current data are conflicting. METHODS: In this blinded 2-by-2 factorial trial, we randomly assigned 1223 critically ill adults in 40 intensive care units (ICUs) in Canada, the United States, and Europe who had multiorgan failure and were receiving mechanical ventilation to receive supplements of glutamine, antioxidants, both, or placebo. Supplements were started within 24 hours after admission to the ICU and were provided both intravenously and enterally. The primary outcome was 28-day mortality. Because of the interim-analysis plan, a P value of less than 0.044 at the final analysis was considered to indicate statistical significance. RESULTS: There was a trend toward increased mortality at 28 days among patients who received glutamine as compared with those who did not receive glutamine (32.4% vs. 27.2%; adjusted odds ratio, 1.28; 95% confidence interval [CI], 1.00 to 1.64; P=0.05). In-hospital mortality and mortality at 6 months were significantly higher among those who received glutamine than among those who did not. Glutamine had no effect on rates of organ failure or infectious complications. Antioxidants had no effect on 28-day mortality (30.8%, vs. 28.8% with no antioxidants; adjusted odds ratio, 1.09; 95% CI, 0.86 to 1.40; P=0.48) or any other secondary end point. There were no differences among the groups with respect to serious adverse events (P=0.83). CONCLUSIONS: Early provision of glutamine or antioxidants did not improve clinical outcomes, and glutamine was associated with an increase in mortality among critically ill patients with multiorgan failure.
谷氨酰胺和抗氧化剂在重症患者中的随机试验 背景：危重患者存在相当大的氧化应激。补充谷氨酰胺和抗氧化剂可能提供治疗获益，但目前的数据相互矛盾。 方法：在这项设盲的2 × 2析因试验中，我们将加拿大、美国和欧洲40个重症监护室(ICU)的1223例伴有多器官功能衰竭且正在接受机械通气的危重成人随机分配至接受谷氨酰胺、抗氧化剂或安慰剂补充。进入ICU后24小时内开始补充，并通过静脉和肠内途径提供。主要结局为28天死亡率。由于中期分析计划，认为最终分析时P值小于0.044具有统计学意义。 结果：与未接受谷氨酰胺的患者相比，接受谷氨酰胺的患者28天时死亡率有增加的趋势（32.4%vs. 27.2%；校正比值比，1.28；95%置信区间[CI]，1.00至1.64；P = 0.05）。接受谷氨酰胺的患者住院死亡率和6个月死亡率显著高于未接受谷氨酰胺的患者。谷氨酰胺对器官衰竭或感染并发症的发生率没有影响。抗氧化剂对28天死亡率（30.8%，对比无抗氧化剂的28.8%；校正比值比，1.09；95%CI，0.86-1.40；P = 0.48）或任何其他次要终点无影响。各组间严重不良事件无差异(P = 0.83)。 结论：早期提供谷氨酰胺或抗氧化剂不能改善临床结局，谷氨酰胺与多器官功能衰竭重症患者死亡率增加相关。
Keywords: Humans; Female; Male; Middle Aged; Aged; Critical Illness; Adult; Aged, 80 and over; Young Adult; Adolescent; Hospital Mortality; Kaplan-Meier Estimate; Survival Rate; Intention to Treat Analysis; Single-Blind Method; Logistic Models; *Respiration, Artificial; Antioxidants/adverse effects/*therapeutic use; Glutamine/adverse effects/*therapeutic use; Multiple Organ Failure/*drug therapy/mortality/therapy

Complications of mechanical ventilation--the CDC's new surveillance paradigm - Klompas, Michael (The New England journal of medicine, 2013)
机械通气并发症--美国CDC新的监测模式
Keywords: Humans; United States; Anti-Bacterial Agents/therapeutic use; *Benchmarking; Centers for Disease Control and Prevention, U.S.; Pneumonia, Ventilator-Associated/drug therapy/*epidemiology; Population Surveillance/*methods; Respiration, Artificial/*adverse effects/standards/statistics & numerical data

Adrenal dysfunction in critically ill patients - Gomez-Sanchez, Celso E. (The New England journal of medicine, 2013)
重症患者中的肾上腺功能不全
Keywords: Humans; Female; Male; *Critical Illness; Adrenocorticotropic Hormone/*blood; Hydrocortisone/*metabolism

Reduced cortisol metabolism during critical illness - Boonen, Eva; Vervenne, Hilke; Meersseman, Philippe; Andrew, Ruth; Mortier, Leen; Declercq, Peter E.; Vanwijngaerden, Yoo-Mee; Spriet, Isabel; Wouters, Pieter J.; Vander Perre, Sarah; Langouche, Lies; Vanhorebeek, Ilse; et al. (The New England journal of medicine, 2013)
BACKGROUND: Critical illness is often accompanied by hypercortisolemia, which has been attributed to stress-induced activation of the hypothalamic-pituitary-adrenal axis. However, low corticotropin levels have also been reported in critically ill patients, which may be due to reduced cortisol metabolism. METHODS: In a total of 158 patients in the intensive care unit and 64 matched controls, we tested five aspects of cortisol metabolism: daily levels of corticotropin and cortisol; plasma cortisol clearance, metabolism, and production during infusion of deuterium-labeled steroid hormones as tracers; plasma clearance of 100 mg of hydrocortisone; levels of urinary cortisol metabolites; and levels of messenger RNA and protein in liver and adipose tissue, to assess major cortisol-metabolizing enzymes. RESULTS: Total and free circulating cortisol levels were consistently higher in the patients than in controls, whereas corticotropin levels were lower (P<0.001 for both comparisons). Cortisol production was 83% higher in the patients (P=0.02). There was a reduction of more than 50% in cortisol clearance during tracer infusion and after the administration of 100 mg of hydrocortisone in the patients (Pâ‰¤0.03 for both comparisons). All these factors accounted for an increase by a factor of 3.5 in plasma cortisol levels in the patients, as compared with controls (P<0.001). Impaired cortisol clearance also correlated with a lower cortisol response to corticotropin stimulation. Reduced cortisol metabolism was associated with reduced inactivation of cortisol in the liver and kidney, as suggested by urinary steroid ratios, tracer kinetics, and assessment of liver-biopsy samples (Pâ‰¤0.004 for all comparisons). CONCLUSIONS: During critical illness, reduced cortisol breakdown, related to suppressed expression and activity of cortisol-metabolizing enzymes, contributed to hypercortisolemia and hence corticotropin suppression. The diagnostic and therapeutic implications for critically ill patients are unknown.
危重病期间皮质醇代谢降低 背景：危重症患者常伴有高皮质醇血症，这归因于应激诱导的下丘脑-垂体-肾上腺轴激活。然而，在重症患者中也报告了促肾上腺皮质激素水平降低，这可能是由于皮质醇代谢降低所致。 方法：在重症监护室的158例患者和匹配的64例对照中，我们检测了皮质醇代谢的5个方面：促肾上腺皮质激素和皮质醇的每日水平；血浆皮质醇的清除，代谢，以及输注氘标记的类固醇激素作为示踪剂时的产生；血浆清除100 mg氢化可的松；尿皮质醇代谢物水平；肝和脂肪组织信使RNA和蛋白质水平，以评估主要的皮质醇代谢酶。 结果：与对照组相比，患者的总循环皮质醇和游离循环皮质醇水平始终较高，而促肾上腺皮质激素水平较低（两项比较P < 0.001）。患者的皮质醇生成增加了83%(P = 0.02)。患者接受示踪剂输注期间和100 mg氢化可的松给药后，皮质醇清除率降低超过50%（2个比较Pâ‰ë0.03）。与对照组相比，所有这些因素均导致患者血浆皮质醇水平升高3.5倍(P < 0.001)。皮质醇清除率受损也与促肾上腺皮质激素刺激引起的皮质醇反应降低相关。尿类固醇比值、示踪剂动力学和肝活检样本评估表明，皮质醇代谢降低与肝脏和肾脏中皮质醇失活减少相关（所有比较Pâ‰æ0.004）。 结论：在危重疾病期间，皮质醇分解减少（与皮质醇代谢酶的表达和活性抑制相关）导致皮质醇增多，进而导致促肾上腺皮质激素抑制。对重症患者的诊断和治疗意义尚不清楚。
Keywords: Humans; Female; Male; Middle Aged; Aged; Case-Control Studies; Intensive Care Units; RNA, Messenger/metabolism; *Critical Illness; Adrenocorticotropic Hormone/*blood; 11-beta-Hydroxysteroid Dehydrogenases/genetics/metabolism; Cushing Syndrome; Hydrocortisone/blood/*metabolism

Case records of the Massachusetts General Hospital. Case 9-2013. A 9-year-old boy with fever, cough, respiratory distress, and chest pain. - Fracchia, Mary Shannon; El Saleeby, Chadi M.; Murali, Mandakolathur R.; Sagar, Pallavi; Mino-Kenudson, Mari (The New England journal of medicine, 2013)
麻省总医院的病例记录。病例9-2013。一名9岁男孩，伴有发热、咳嗽、呼吸窘迫和胸痛。
Keywords: Humans; Male; Diagnosis, Differential; Child; Ultrasonography; Radiography; Dyspnea/etiology; Lung/diagnostic imaging/*pathology; Cough/etiology; Fever/etiology; Lung Diseases/diagnosis; *Aspergillus flavus; *Aspergillus fumigatus; Alveolitis, Extrinsic Allergic/complications/diagnostic imaging/*pathology; Chest Pain/etiology; Lymphatic Diseases/diagnostic imaging

Images in clinical medicine. Blast lung. - Barnard, Edward; Johnston, Andrew (The New England journal of medicine, 2013)
临床医学图像。肺潴留。
Keywords: Humans; Male; Child; Radiography; Lung/*diagnostic imaging; Blast Injuries/*diagnostic imaging; Lung Injury/*diagnostic imaging/etiology

High-frequency oscillatory ventilation on shaky ground - Malhotra, Atul; Drazen, Jeffrey M. (The New England journal of medicine, 2013)
震动地面高频振荡通风
Keywords: Humans; Female; Male; *High-Frequency Ventilation; *Positive-Pressure Respiration; Respiratory Distress Syndrome/*therapy

High-frequency oscillation in early acute respiratory distress syndrome - Ferguson, Niall D.; Cook, Deborah J.; Guyatt, Gordon H.; Mehta, Sangeeta; Hand, Lori; Austin, Peggy; Zhou, Qi; Matte, Andrea; Walter, Stephen D.; Lamontagne, Francois; Granton, John T.; Arabi, Yaseen M.; et al. (The New England journal of medicine, 2013)
BACKGROUND: Previous trials suggesting that high-frequency oscillatory ventilation (HFOV) reduced mortality among adults with the acute respiratory distress syndrome (ARDS) were limited by the use of outdated comparator ventilation strategies and small sample sizes. METHODS: In a multicenter, randomized, controlled trial conducted at 39 intensive care units in five countries, we randomly assigned adults with new-onset, moderate-to-severe ARDS to HFOV targeting lung recruitment or to a control ventilation strategy targeting lung recruitment with the use of low tidal volumes and high positive end-expiratory pressure. The primary outcome was the rate of in-hospital death from any cause. RESULTS: On the recommendation of the data monitoring committee, we stopped the trial after 548 of a planned 1200 patients had undergone randomization. The two study groups were well matched at baseline. The HFOV group underwent HFOV for a median of 3 days (interquartile range, 2 to 8); in addition, 34 of 273 patients (12%) in the control group received HFOV for refractory hypoxemia. In-hospital mortality was 47% in the HFOV group, as compared with 35% in the control group (relative risk of death with HFOV, 1.33; 95% confidence interval, 1.09 to 1.64; P=0.005). This finding was independent of baseline abnormalities in oxygenation or respiratory compliance. Patients in the HFOV group received higher doses of midazolam than did patients in the control group (199 mg per day [interquartile range, 100 to 382] vs. 141 mg per day [interquartile range, 68 to 240], P<0.001), and more patients in the HFOV group than in the control group received neuromuscular blockers (83% vs. 68%, P<0.001). In addition, more patients in the HFOV group received vasoactive drugs (91% vs. 84%, P=0.01) and received them for a longer period than did patients in the control group (5 days vs. 3 days, P=0.01). CONCLUSIONS: In adults with moderate-to-severe ARDS, early application of HFOV, as compared with a ventilation strategy of low tidal volume and high positive end-expiratory pressure, does not reduce, and may increase, in-hospital mortality.
高频振荡治疗早期急性呼吸窘迫综合征 背景：既往试验表明，高频振荡通气(HFOV)降低急性呼吸窘迫综合征(ARDS)成人患者的死亡率受到使用过时的比较通气策略和小样本量的限制。 方法：在一项多中心、随机、对照试验中，我们在5个国家的39个重症监护室中随机分配了新发、中重度ARDS改为使用低潮气量和高呼气末正压通气的HFOV靶向肺复张或对照通气策略靶向肺复张。主要结局为任何原因导致的住院死亡率。 结果：根据数据监查委员会的建议，我们在计划的1200例患者中的548例接受随机化后停止了试验。两个研究组基线时匹配良好。HFOV组进行HFOV的中位时间为3天（四分位距为2-8）；此外，对照组273例患者中的34例(12%)因难治性低氧血症接受HFOV。HFOV组的住院死亡率为47%，而对照组为35%（HFOV的相对死亡风险为1.33；95%置信区间，1.09至1.64；P = 0.005）。该结果与氧合或呼吸顺应性的基线异常无关。HFOV组患者接受的咪达唑仑剂量高于对照组患者（199 mg/天[四分位距，100至382]vs. 141 mg/天[四分位距，68至240]，P < 0.001），HFOV组接受神经肌肉阻滞剂的患者多于对照组(83%vs. 68%，P < 0.001)。此外，HFOV组中接受血管活性药物的患者更多（91%对比84%，P = 0.01），并且与对照组患者相比，接受血管活性药物的时间更长（5天对比3天，P = 0.01）。 结论：在中重度ARDS成人中，与低潮气量和高呼气末正压通气策略相比，早期应用HFOV并未降低并可能增加住院死亡率。
Keywords: Humans; Female; Male; Middle Aged; Survival Analysis; Aged; Adult; Hospital Mortality; Treatment Failure; *High-Frequency Ventilation; *Positive-Pressure Respiration; Hypoxia/etiology; Midazolam/administration & dosage; Hypnotics and Sedatives/administration & dosage; Respiratory Distress Syndrome/complications/mortality/*therapy

High-frequency oscillation for acute respiratory distress syndrome - Young, Duncan; Lamb, Sarah E.; Shah, Sanjoy; MacKenzie, Iain; Tunnicliffe, William; Lall, Ranjit; Rowan, Kathy; Cuthbertson, Brian H. (The New England journal of medicine, 2013)
BACKGROUND: Patients with the acute respiratory distress syndrome (ARDS) require mechanical ventilation to maintain arterial oxygenation, but this treatment may produce secondary lung injury. High-frequency oscillatory ventilation (HFOV) may reduce this secondary damage. METHODS: In a multicenter study, we randomly assigned adults requiring mechanical ventilation for ARDS to undergo either HFOV with a Novalung R100 ventilator (Metran) or usual ventilatory care. All the patients had a ratio of the partial pressure of arterial oxygen (PaO) to the fraction of inspired oxygen (FiO) of 200 mm Hg (26.7 kPa) or less and an expected duration of ventilation of at least 2 days. The primary outcome was all-cause mortality 30 days after randomization. RESULTS: There was no significant between-group difference in the primary outcome, which occurred in 166 of 398 patients (41.7%) in the HFOV group and 163 of 397 patients (41.1%) in the conventional-ventilation group (P=0.85 by the chi-square test). After adjustment for study center, sex, score on the Acute Physiology and Chronic Health Evaluation (APACHE) II, and the initial PaO:FiO ratio, the odds ratio for survival in the conventional-ventilation group was 1.03 (95% confidence interval, 0.75 to 1.40; P=0.87 by logistic regression). CONCLUSIONS: The use of HFOV had no significant effect on 30-day mortality in patients undergoing mechanical ventilation for ARDS.
高频振荡治疗早期急性呼吸窘迫综合征 背景：急性呼吸窘迫综合征(ARDS)患者需要机械通气来维持动脉氧合，但这种治疗可能产生继发性肺损伤。高频振荡通气(HFOV)可减少这种继发性损伤。 方法：在一项多中心研究中，我们将需要机械通气治疗ARDS的成人随机分配至Novalung R100呼吸机(Metran)HFOV组或常规通气治疗组。所有患者的动脉血氧分压(PaO)与吸入气中的氧浓度(FiO)之比≤200 mmHg(26.7 kPa)，预期通气时间至少为2天。主要结局为随机化后30天的全因死亡率。 结果：主要结局无显著的组间差异，HFOV组166/398(41.7%)例患者和常规通气组163/397(41.1%)例患者发生了主要结局（经卡方检验，P = 0.85）。校正研究中心、性别、急性生理和慢性健康评估(APACHE)II评分和初始PaO:FiO比值后，常规通气组的生存优势比为1.03（95%置信区间，0.75-1.40；logistic回归，P = 0.87）。 结论：HFOV的使用对接受机械通气治疗ARDS患者的30天死亡率无显著影响。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Respiration, Artificial; Hospital Mortality; Kaplan-Meier Estimate; Algorithms; Logistic Models; Treatment Failure; Anti-Infective Agents/therapeutic use; Hypoxia/etiology; Respiratory Distress Syndrome/complications/mortality/*therapy; *High-Frequency Ventilation/methods

Burden of human metapneumovirus infection in young children - Edwards, Kathryn M.; Zhu, Yuwei; Griffin, Marie R.; Weinberg, Geoffrey A.; Hall, Caroline B.; Szilagyi, Peter G.; Staat, Mary A.; Iwane, Marika; Prill, Mila M.; Williams, John V. (The New England journal of medicine, 2013)
BACKGROUND: The inpatient and outpatient burden of human metapneumovirus (HMPV) infection among young children has not been well established. METHODS: We conducted prospective, population-based surveillance for acute respiratory illness or fever among inpatient and outpatient children less than 5 years of age in three U.S. counties from 2003 through 2009. Clinical and demographic data were obtained from parents and medical records, HMPV was detected by means of a reverse-transcriptase polymerase-chain-reaction assay, and population-based rates of hospitalization and estimated rates of outpatient visits associated with HMPV infection were determined. RESULTS: HMPV was detected in 200 of 3490 hospitalized children (6%), 222 of 3257 children in outpatient clinics (7%), 224 of 3001 children in the emergency department (7%), and 10 of 770 asymptomatic controls (1%). Overall annual rates of hospitalization associated with HMPV infection were 1 per 1000 children less than 5 years of age, 3 per 1000 infants less than 6 months of age, and 2 per 1000 children 6 to 11 months of age. Children hospitalized with HMPV infection, as compared with those hospitalized without HMPV infection, were older and more likely to receive a diagnosis of pneumonia or asthma, to require supplemental oxygen, and to have a longer stay in the intensive care unit. The estimated annual burden of outpatient visits associated with HMPV infection was 55 clinic visits and 13 emergency department visits per 1000 children. The majority of HMPV-positive inpatient and outpatient children had no underlying medical conditions, although premature birth and asthma were more frequent among hospitalized children with HMPV infection than among those without HMPV infection. CONCLUSIONS: HMPV infection is associated with a substantial burden of hospitalizations and outpatient visits among children throughout the first 5 years of life, especially during the first year. Most children with HMPV infection were previously healthy.
幼儿人类偏肺病毒感染的负担 背景：年幼儿童中人类偏肺病毒(HMPV)感染的住院和门诊负担尚未确立。 方法：我们从2003年至2009年在三个美国区县的小于5岁的住院和门诊儿童中进行了急性呼吸道疾病或发热的前瞻性、基于人群的监测。从父母和病历中获取临床和人口统计学数据，通过逆转录酶聚合酶链反应检测HMPV，并确定以人群为基础的住院率和与HMPV感染相关的估计门诊量。 结果：3490例住院患儿中有200例检出HMPV(6%)，3257例门诊患儿中有222例检出HMPV(7%)，3001例急诊患儿中有224例检出HMPV(7%)，770例无症状对照中有10例检出HMPV(1%)。与HMPV感染相关的总体年住院率为：小于5岁儿童1/1000，小于6个月婴儿3/1000，6-11个月儿童2/1000。与无HMPV感染的住院患儿相比，HMPV感染的住院患儿年龄更大，更可能被诊断为肺炎或哮喘，需要补充氧气，入住重症监护室的时间更长。与HMPV感染相关的门诊就诊的估计年度负担为每1000名儿童55次门诊就诊和13次急诊就诊。大多数HMPV阳性住院和门诊儿童无基础疾病，尽管HMPV感染住院儿童中早产和哮喘的发生率高于无HMPV感染的住院儿童。 结论：HMPV感染与儿童出生后最初5年内，尤其是第一年的住院和门诊就诊的重大负担相关。大多数HMPV感染儿童既往健康。
Keywords: Humans; Female; Male; Prospective Studies; Infant; Child, Preschool; Population Surveillance; United States/epidemiology; Hospitalization/*statistics & numerical data; *Metapneumovirus; Paramyxoviridae Infections/complications/*epidemiology; Pneumonia, Viral/epidemiology/virology; Respiratory Tract Infections/virology

Use of health IT for higher-value critical care - Chen, Lena M.; Kennedy, Edward H.; Sales, Anne; Hofer, Timothy P. (The New England journal of medicine, 2013)
将健康IT用于更高价值的重症监护
Keywords: Humans; United Kingdom; Severity of Illness Index; United States; Practice Guidelines as Topic; Intensive Care Units/*organization & administration; Critical Care/*organization & administration; Workforce; *Decision Making, Computer-Assisted; *Electronic Health Records/statistics & numerical data; Heart Diseases/classification/therapy; Hospital Bed Capacity; Patient Admission/standards/statistics & numerical data; Resource Allocation; Triage/methods

Effect of daily chlorhexidine bathing on hospital-acquired infection - Climo, Michael W.; Yokoe, Deborah S.; Warren, David K.; Perl, Trish M.; Bolon, Maureen; Herwaldt, Loreen A.; Weinstein, Robert A.; Sepkowitz, Kent A.; Jernigan, John A.; Sanogo, Kakotan; Wong, Edward S. (The New England journal of medicine, 2013)
BACKGROUND: Results of previous single-center, observational studies suggest that daily bathing of patients with chlorhexidine may prevent hospital-acquired bloodstream infections and the acquisition of multidrug-resistant organisms (MDROs). METHODS: We conducted a multicenter, cluster-randomized, nonblinded crossover trial to evaluate the effect of daily bathing with chlorhexidine-impregnated washcloths on the acquisition of MDROs and the incidence of hospital-acquired bloodstream infections. Nine intensive care and bone marrow transplantation units in six hospitals were randomly assigned to bathe patients either with no-rinse 2% chlorhexidine-impregnated washcloths or with nonantimicrobial washcloths for a 6-month period, exchanged for the alternate product during the subsequent 6 months. The incidence rates of acquisition of MDROs and the rates of hospital-acquired bloodstream infections were compared between the two periods by means of Poisson regression analysis. RESULTS: A total of 7727 patients were enrolled during the study. The overall rate of MDRO acquisition was 5.10 cases per 1000 patient-days with chlorhexidine bathing versus 6.60 cases per 1000 patient-days with nonantimicrobial washcloths (P=0.03), the equivalent of a 23% lower rate with chlorhexidine bathing. The overall rate of hospital-acquired bloodstream infections was 4.78 cases per 1000 patient-days with chlorhexidine bathing versus 6.60 cases per 1000 patient-days with nonantimicrobial washcloths (P=0.007), a 28% lower rate with chlorhexidine-impregnated washcloths. No serious skin reactions were noted during either study period. CONCLUSIONS: Daily bathing with chlorhexidine-impregnated washcloths significantly reduced the risks of acquisition of MDROs and development of hospital-acquired bloodstream infections.
氯己定每日洗浴对医院获得性感染的影响 背景：既往的单中心、观察性研究结果表明，氯己定患者每日洗浴可预防医院获得性血液感染和多重耐药菌(MDROs)的获得。 方法：我们进行了一项多中心、群组随机、非盲交叉试验，以评价每天用氯己定浸渍的浴巾沐浴对MDROs的获得和医院获得性血液感染的发生率的影响。6家医院的9个重症监护和骨髓移植病房被随机分配到用2%氯己定浸渍的无冲洗浴巾或无抗菌性浴巾为患者洗澡6个月，在随后的6个月更换替代产品。通过Poisson回归分析比较两个阶段的MDROs发生率和医院获得性血液感染的发生率。 结果：研究期间共入组7727例患者。使用氯己定浸浴的MDRO总获得率为5.10例/1000患者-天，而使用非抗菌性浴巾为6.60例/1000患者-天(P = 0.03)，相当于使用氯己定浸浴的比率低23%。使用氯己定浸浴的医院获得性血液感染的总发生率为4.78例/1000患者-天，而使用非抗菌性浴巾的为6.60例/1000患者-天(P = 0.007)，氯己定浸渍的浴巾的发生率低28%。两个研究阶段均未观察到严重皮肤反应。 结论：使用氯己定浸渍的浴巾进行每日洗澡显著降低了MDROs的获得和医院获得性血液感染的发生风险。
Keywords: Humans; Intensive Care Units; Kaplan-Meier Estimate; Incidence; *Drug Resistance, Multiple, Bacterial; Cross-Over Studies; Proportional Hazards Models; *Baths; Anti-Infective Agents, Local/*therapeutic use; Bacteremia/epidemiology/microbiology/*prevention & control; Chlorhexidine/*therapeutic use; Cross Infection/epidemiology/*prevention & control; Enterococcus/drug effects/isolation & purification; Gram-Positive Bacterial Infections/prevention & control; Methicillin-Resistant Staphylococcus aureus/isolation & purification; Staphylococcal Infections/prevention & control; Vancomycin Resistance

Rivaroxaban for thromboprophylaxis in acutely ill medical patients - Cohen, Alexander T.; Spiro, Theodore E.; Büller, Harry R.; Haskell, Lloyd; Hu, Dayi; Hull, Russell; Mebazaa, Alexandre; Merli, Geno; Schellong, Sebastian; Spyropoulos, Alex C.; Tapson, Victor (The New England journal of medicine, 2013)
BACKGROUND: The clinically appropriate duration of thromboprophylaxis in hospitalized patients with acute medical illnesses is unknown. In this multicenter, randomized, double-blind trial, we evaluated the efficacy and safety of oral rivaroxaban administered for an extended period, as compared with subcutaneous enoxaparin administered for a standard period, followed by placebo. METHODS: We randomly assigned patients 40 years of age or older who were hospitalized for an acute medical illness to receive subcutaneous enoxaparin, 40 mg once daily, for 10±4 days and oral placebo for 35±4 days or to receive subcutaneous placebo for 10±4 days and oral rivaroxaban, 10 mg once daily, for 35±4 days. The primary efficacy outcomes were the composite of asymptomatic proximal or symptomatic venous thromboembolism up to day 10 (noninferiority test) and up to day 35 (superiority test). The principal safety outcome was the composite of major or clinically relevant nonmajor bleeding. RESULTS: A total of 8101 patients underwent randomization. A primary efficacy outcome event occurred in 78 of 2938 patients (2.7%) receiving rivaroxaban and 82 of 2993 patients (2.7%) receiving enoxaparin at day 10 (relative risk with rivaroxaban, 0.97; 95% confidence interval [CI], 0.71 to 1.31; P=0.003 for noninferiority) and in 131 of 2967 patients (4.4%) who received rivaroxaban and 175 of 3057 patients (5.7%) who received enoxaparin followed by placebo at day 35 (relative risk, 0.77; 95% CI, 0.62 to 0.96; P=0.02). A principal safety outcome event occurred in 111 of 3997 patients (2.8%) in the rivaroxaban group and 49 of 4001 patients (1.2%) in the enoxaparin group at day 10 (P<0.001) and in 164 patients (4.1%) and 67 patients (1.7%) in the respective groups at day 35 (P<0.001). CONCLUSIONS: In acutely ill medical patients, rivaroxaban was noninferior to enoxaparin for standard-duration thromboprophylaxis. Extended-duration rivaroxaban reduced the risk of venous thromboembolism. Rivaroxaban was associated with an increased risk of bleeding.
利伐沙班在急性病患者中用于血栓预防 背景：急性内科疾病住院患者血栓预防的临床适当持续时间未知。在本项多中心、随机化、双盲试验中，我们评估了口服利伐沙班扩展期给药的疗效和安全性，与标准期皮下注射依诺肝素，随后给予安慰剂相比。 方法：我们将因急性疾病住院的40岁或40岁以上患者随机分配至接受依诺肝素40 mg皮下给药，每日一次，持续10 μm±4天和安慰剂口服给药，持续35 μm±4天或安慰剂皮下给药，持续10 μm±4天和利伐沙班10 mg口服给药，每日一次，持续35 μm±4天。主要疗效结局是第10天（非劣效性检验）和第35天（优效性检验）无症状近端或症状性静脉血栓栓塞的复合终点。主要安全性结局是大出血或临床相关非大出血的复合终点。 结果：共有8101例患者接受随机分组。在第10天接受利伐沙班的2938例患者中有78例(2.7%)和接受依诺肝素的2993例患者中有82例(2.7%)发生了主要疗效结局事件（利伐沙班的相对风险，0.97；95%置信区间[CI]，0.71-1.31；非劣效性P = 0.003），第35天接受利伐沙班的2967例患者中有131例(4.4%)，接受依诺肝素随后接受安慰剂的3057例患者中有175例(5.7%)（相对风险，0.77；95%CI，0.62-0.96；P = 0.02）。第10天时利伐沙班组3997例患者中的111例(2.8%)和依诺肝素组4001例患者中的49例(1.2%)(P < 0.001)发生了主要安全性结局事件，第35天时各组分别有164例患者(4.1%)和67例患者(1.7%)(P < 0.001)发生了主要安全性结局事件。 结论：在急性病患者中，利伐沙班在标准持续时间血栓预防方面非劣效于依诺肝素。延长利伐沙班用药时间可降低静脉血栓栓塞的风险。利伐沙班与出血风险增加相关。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Adult; Administration, Oral; Acute Disease; Drug Administration Schedule; Anticoagulants/adverse effects/*therapeutic use; *Factor Xa Inhibitors; Enoxaparin/adverse effects/*therapeutic use; Hemorrhage/*chemically induced; Injections, Subcutaneous; Morpholines/adverse effects/*therapeutic use; Rivaroxaban; Thiophenes/adverse effects/*therapeutic use; Venous Thromboembolism/epidemiology/*prevention & control

Images in clinical medicine. Hemifacial flushing. - Keogh, Peter; Wood, James (The New England journal of medicine, 2013)
临床医学图像。半侧颜面潮红。
Keywords: Humans; Male; Middle Aged; Jugular Veins; Central Venous Catheters/*adverse effects; Flushing/etiology/*pathology; Upper Extremity Deep Vein Thrombosis/*complications

Fever of unknown origin or fever of too many origins? - Horowitz, Harold W (The New England journal of medicine, 2013)
原因不明的发热或原因过多的发热？
Keywords: Humans; Anti-Bacterial Agents/*therapeutic use; Patient Care Team; *Diagnosis, Differential; Bacterial Infections/complications/*diagnosis/drug therapy; Fever of Unknown Origin/*etiology

The bystander effect in medical care - Stavert, Robert R.; Lott, Jason P. (The New England journal of medicine, 2013)
医疗护理中的旁观者效应
Keywords: Humans; Male; Adult; Diagnosis, Differential; Workforce; *Intensive Care Units/organization & administration; *Group Processes; *Leadership; Patient Care Management/*organization & administration

Case records of the Massachusetts General Hospital. Case 40-2012. A 43-year-old woman with cardiorespiratory arrest after a cesarean section. - Ecker, Jeffrey L.; Solt, Ken; Fitzsimons, Michael G.; MacGillivray, Thomas E. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例40-2012。1例43岁女性在剖宫产后发生心跳呼吸骤停。
Keywords: Humans; Female; Adult; Pregnancy; Extracorporeal Membrane Oxygenation; Placenta Previa/surgery; *Cesarean Section; *Echocardiography, Transesophageal; Bradycardia/etiology; Embolism, Amniotic Fluid/*diagnostic imaging/therapy; Heart Arrest/*etiology; Heart Diseases/complications/*diagnostic imaging

Continuous renal-replacement therapy for acute kidney injury - Tolwani, Ashita (The New England journal of medicine, 2012)
急性肾损伤的连续肾脏替代治疗
Keywords: Humans; Male; Young Adult; Practice Guidelines as Topic; *Postoperative Complications; Creatinine/blood; Acute Kidney Injury/etiology/*therapy; *Renal Replacement Therapy/adverse effects/methods; Aneurysm, Dissecting/complications/surgery; Aortic Aneurysm, Thoracic/complications/surgery; Heart Valve Prosthesis Implantation; Marfan Syndrome/complications

Neurodevelopmental outcomes in the early CPAP and pulse oximetry trial - Vaucher, Yvonne E.; Peralta-Carcelen, Myriam; Finer, Neil N.; Carlo, Waldemar A.; Gantz, Marie G.; Walsh, Michele C.; Laptook, Abbot R.; Yoder, Bradley A.; Faix, Roger G.; Das, Abhik; Schibler, Kurt; Rich, Wade; et al. (The New England journal of medicine, 2012)
BACKGROUND: Previous results from our trial of early treatment with continuous positive airway pressure (CPAP) versus early surfactant treatment in infants showed no significant difference in the outcome of death or bronchopulmonary dysplasia. A lower (vs. higher) target range of oxygen saturation was associated with a lower rate of severe retinopathy but higher mortality. We now report longer-term results from our prespecified hypotheses. METHODS: Using a 2-by-2 factorial design, we randomly assigned infants born between 24 weeks 0 days and 27 weeks 6 days of gestation to early CPAP with a limited ventilation strategy or early surfactant administration and to lower or higher target ranges of oxygen saturation (85 to 89% or 91 to 95%). The primary composite outcome for the longer-term analysis was death before assessment at 18 to 22 months or neurodevelopmental impairment at 18 to 22 months of corrected age. RESULTS: The primary outcome was determined for 1234 of 1316 enrolled infants (93.8%); 990 of the 1058 surviving infants (93.6%) were evaluated at 18 to 22 months of corrected age. Death or neurodevelopmental impairment occurred in 27.9% of the infants in the CPAP group (173 of 621 infants), versus 29.9% of those in the surfactant group (183 of 613) (relative risk, 0.93; 95% confidence interval [CI], 0.78 to 1.10; P=0.38), and in 30.2% of the infants in the lower-oxygen-saturation group (185 of 612), versus 27.5% of those in the higher-oxygen-saturation group (171 of 622) (relative risk, 1.12; 95% CI, 0.94 to 1.32; P=0.21). Mortality was increased with the lower-oxygen-saturation target (22.1%, vs. 18.2% with the higher-oxygen-saturation target; relative risk, 1.25; 95% CI, 1.00 to 1.55; P=0.046). CONCLUSIONS: We found no significant differences in the composite outcome of death or neurodevelopmental impairment among extremely premature infants randomly assigned to early CPAP or early surfactant administration and to a lower or higher target range of oxygen saturation.
早期CPAP和脉搏血氧饱和度试验中的神经发育结局 背景：我们先前在婴儿中进行的早期持续气道正压通气(CPAP)治疗与早期表面活性物质治疗的试验结果显示，死亡或支气管肺发育不良结局无显著差异。较低（vs.较高）的氧饱和度目标范围与较低的重度视网膜病变发生率但较高的死亡率相关。我们现在报告来自我们预先指定假设的长期结果。 方法：采用2 × 2析因设计，我们将出生时介于孕24周0天至孕27周6天之间的婴儿随机分配至早期使用有限通气策略的CPAP组或早期使用表面活性剂组和较低或较高的氧饱和度目标范围组（85-89%或91-95%）。长期分析的主要复合结局为校正年龄18-22个月时评估前死亡或18-22个月时神经发育受损。 结果：确定了入选的1316名婴儿中1234名(93.8%)的主要结局；在1058名存活婴儿中，990名(93.6%)在校正年龄18至22个月时接受了评价。CPAP组27.9%的婴儿（173/621名婴儿）发生死亡或神经发育受损，而表面活性剂组29.9%的婴儿（183/613名婴儿）发生死亡或神经发育受损（相对风险0.93；95%置信区间[CI]0.78-1.10；P = 0.38），而较低氧饱和度组30.2%的婴儿（185/612名婴儿）发生死亡或神经发育受损。而氧饱和度较高组(171/622)为27.5%（相对危险度，1.12;95%CI,0.94至1.32;P = 0.21）。低氧饱和度目标组的死亡率增加（22.1%，高氧饱和度目标组是18.2%；相对风险，1.25；95%CI，1.00至1.55；P = 0.046）。 结论：我们发现，极早产儿的死亡或神经发育受损的复合结局并无显著差异，极早产儿随机接受早期CPAP或早期表面活性剂治疗，并接受较低或较高的氧饱和度目标范围。
Keywords: Humans; Female; Oximetry; Outcome Assessment, Health Care; Infant; Infant, Newborn; Follow-Up Studies; Socioeconomic Factors; Infant Mortality; Oxygen/administration & dosage/blood; Developmental Disabilities/*epidemiology; *Continuous Positive Airway Pressure/adverse effects; Retinopathy of Prematurity/epidemiology; *Child Development; *Oxygen Inhalation Therapy/adverse effects; Bronchopulmonary Dysplasia/epidemiology; Infant, Extremely Low Birth Weight; Infant, Extremely Premature; Pulmonary Surfactants/adverse effects/*therapeutic use

Brain in a box - Ropper, Allan H. (The New England journal of medicine, 2012)
脑子在一个盒子里
Keywords: Humans; Female; Male; *Monitoring, Physiologic; Radiography; *Intracranial Pressure; *Neurologic Examination; Brain Injuries/*physiopathology; Brain/*diagnostic imaging; Intracranial Hypertension/*diagnosis

Case records of the Massachusetts General Hospital. Case 39-2012. A 55-year-old man with alcoholism, recurrent seizures, and agitation. - Nejad, Shamim H.; Schaefer, Pamela W.; Bajwa, Ednan K.; Smith, Felicia A. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例39-2012。1例55岁男性，伴有酒精中毒、复发性癫痫发作和激越。
Keywords: Humans; Male; Middle Aged; Diagnosis, Differential; Brain/diagnostic imaging/pathology; Alcoholism/complications; Radiography; Psychomotor Agitation/etiology; Alcohol Withdrawal Delirium/*diagnosis; Alcohol Withdrawal Seizures/*diagnosis; Seizures/etiology

Interactive medical case. A patient found unresponsive. - Sacks, Zadok; Vaidya, Anand; Sharma, Niraj; Gottlieb, Barbara (The New England journal of medicine, 2012)
交互式医学病例。发现患者无应答。
Keywords: Humans; Female; Diagnosis, Differential; Adolescent; Unconsciousness/etiology; *Suicide, Attempted; Anorexia Nervosa/complications/diagnosis/psychology/*therapy; Antidepressive Agents/therapeutic use; Antipsychotic Agents/poisoning; Depressive Disorder, Major/*complications/drug therapy; Dibenzothiazepines/poisoning; Duloxetine Hydrochloride; Electrocardiography/drug effects; Hypokalemia/complications; Quetiapine Fumarate; Thiophenes/therapeutic use

Weaning patients from the ventilator - McConville, John F.; Kress, John P. (The New England journal of medicine, 2012)
患者脱离呼吸机
Keywords: Humans; Time Factors; Positive-Pressure Respiration; Algorithms; Ventilator Weaning/adverse effects/*methods; Respiratory Insufficiency/therapy

Preventing lethal hospital outbreaks of antibiotic-resistant bacteria - Sandora, Thomas J.; Goldmann, Donald A. (The New England journal of medicine, 2012)
预防抗生素耐药菌在医院致死性暴发
Keywords: Humans; Hospital Mortality; United States; *Drug Resistance, Bacterial; Infection Control/*methods; *Drug Resistance, Multiple; Cross Infection/microbiology/*prevention & control/transmission; Disease Outbreaks/*prevention & control; Klebsiella Infections/diagnosis/mortality; Klebsiella pneumoniae/isolation & purification; Methicillin-Resistant Staphylococcus aureus; National Institutes of Health (U.S.)

Case records of the Massachusetts General Hospital. Case 36-2012. Recovery of a 16-year-old girl from trauma and burns after a car accident. - Sheridan, Robert L.; Schaefer, Pamela W.; Whalen, Michael; Fagan, Shawn; Stoddard, Frederick J. Jr; Schneider, Jeffrey C.; McConkey, Brock; Cancio, Leopoldo C. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例36-2012。一名16岁女孩在车祸后从创伤和烧伤中恢复。
Keywords: Humans; Female; Adolescent; Brain/diagnostic imaging; Radiography; *Accidents, Traffic; *Artificial Limbs/adverse effects; Brain Injuries/diagnostic imaging/therapy; Burns/etiology/*therapy; Multiple Trauma/etiology/rehabilitation/*therapy; Prosthesis Design; Smoke Inhalation Injury/therapy; Wound Healing

Images in clinical medicine. Anaphylaxis associated with blue dye. - Gil-Moreno, Antonio; Perez-Benavente, Assumpcio (The New England journal of medicine, 2012)
临床医学图像。与蓝色染料相关的过敏反应。
Keywords: Humans; Female; Adult; Anaphylaxis/*etiology; Coloring Agents/*adverse effects; Lymph Node Excision; Uterine Cervical Neoplasms/surgery

Intensive care in low-income countries--a critical need - Firth, Paul; Ttendo, Stephen (The New England journal of medicine, 2012)
低收入国家的重症监护--一种关键需求
Keywords: Humans; Poverty; Intensive Care Units/*organization & administration; *Critical Care; *Developing Countries; *Health Services Needs and Demand; Uganda

Case records of the Massachusetts General Hospital. Case 35-2012. A 69-year-old chronically ill man with weakness, anorexia, and diffuse pain. - Greenwald, Jeffrey L.; McDermott, Shaunagh; Dighe, Anand S. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例35-2012。一名69岁的慢性病男性，伴有虚弱、厌食和弥漫性疼痛。
Keywords: Humans; Male; Middle Aged; Diagnosis, Differential; Brain/pathology; Ultrasonography; *Kidney Transplantation; Lung/diagnostic imaging; Kidney/diagnostic imaging; Radiography; Muscle Weakness/etiology; Bradycardia/etiology; Adrenal Insufficiency/diagnosis; Anorexia/*etiology; Chronic Pain/etiology; Diabetes Complications; Hydrocortisone/blood; Hypothyroidism/complications/*diagnosis; Kidney Failure, Chronic/surgery; Thyrotropin/blood; Thyroxine/blood

Hydroxyethyl starch or saline for fluid resuscitation in intensive care - Myburgh, John A.; Finfer, Simon; Bellomo, Rinaldo; Billot, Laurent; Cass, Alan; Gattas, David; Glass, Parisa; Lipman, Jeffrey; Liu, Bette; McArthur, Colin; McGuinness, Shay; Rajbhandari, Dorrilyn; et al. (The New England journal of medicine, 2012)
BACKGROUND: The safety and efficacy of hydroxyethyl starch (HES) for fluid resuscitation have not been fully evaluated, and adverse effects of HES on survival and renal function have been reported. METHODS: We randomly assigned 7000 patients who had been admitted to an intensive care unit (ICU) in a 1:1 ratio to receive either 6% HES with a molecular weight of 130 kD and a molar substitution ratio of 0.4 (130/0.4, Voluven) in 0.9% sodium chloride or 0.9% sodium chloride (saline) for all fluid resuscitation until ICU discharge, death, or 90 days after randomization. The primary outcome was death within 90 days. Secondary outcomes included acute kidney injury and failure and treatment with renal-replacement therapy. RESULTS: A total of 597 of 3315 patients (18.0%) in the HES group and 566 of 3336 (17.0%) in the saline group died (relative risk in the HES group, 1.06; 95% confidence interval [CI], 0.96 to 1.18; P=0.26). There was no significant difference in mortality in six predefined subgroups. Renal-replacement therapy was used in 235 of 3352 patients (7.0%) in the HES group and 196 of 3375 (5.8%) in the saline group (relative risk, 1.21; 95% CI, 1.00 to 1.45; P=0.04). In the HES and saline groups, renal injury occurred in 34.6% and 38.0% of patients, respectively (P=0.005), and renal failure occurred in 10.4% and 9.2% of patients, respectively (P=0.12). HES was associated with significantly more adverse events (5.3% vs. 2.8%, P<0.001). CONCLUSIONS: In patients in the ICU, there was no significant difference in 90-day mortality between patients resuscitated with 6% HES (130/0.4) or saline. However, more patients who received resuscitation with HES were treated with renal-replacement therapy.
羟乙基淀粉或生理盐水用于重症监护患者的液体复苏 背景：羟乙基淀粉用于液体复苏的安全性和有效性尚未得到充分评价，有报道羟乙基淀粉对存活和肾功能产生不良影响。 方法：我们以1:1的比例随机分配7000例入住重症监护室(ICU)的患者接受分子量为130kd、摩尔取代率为0.4（130/0.4，万汶）的0.9%氯化钠或0.9%氯化钠（生理盐水）溶液，用于所有液体复苏，直至离开ICU、死亡或随机分配后90天。主要结局为90天内死亡。次要结局包括急性肾损伤和肾衰竭以及肾脏替代治疗。 结果：在HES组，3315名患者中共有597名(18.0%)死亡，生理盐水组中3336名患者中共有566名(17.0%)死亡（HES组的相对风险，1.06；95%置信区间[CI]，0.96至1.18；P = 0.26）。6个预定义亚组的死亡率无显著差异。HES组235/3352名患者(7.0%)和生理盐水组196/3375名患者(5.8%)使用了肾脏替代治疗（相对风险，1.21；95%CI，1.00至1.45；P = 0.04）。在HES组和生理盐水组，分别有34.6%和38.0%的患者发生了肾损伤(P = 0.005)，分别有10.4%和9.2%的患者发生了肾衰竭(P = 0.12)。HES组的不良事件显著较多(5.3%vs. 2.8%，P < 0.001)。 结论：在ICU患者中，接受6%HES(130/0.4)或生理盐水复苏的患者的90天死亡率没有显著差异。但是，有更多接受羟乙基淀粉复苏的患者接受了肾脏替代治疗。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Adult; Critical Care; Hospital Mortality; Intention to Treat Analysis; Critical Illness/mortality/*therapy; Resuscitation/methods; Creatinine/blood/urine; Fluid Therapy/adverse effects/*methods; Hydroxyethyl Starch Derivatives/adverse effects/*therapeutic use; Kidney Diseases/etiology; Sodium Chloride/therapeutic use

Monitoring ventilation with capnography - Ortega, Rafael; Connor, Christopher; Kim, Sora; Djang, Robin; Patel, Kunal (2012)
Capnography, the graphic display of the exhaled and inhaled carbon dioxide concentration plotted against time, is used to monitor ventilation. This video reviews the principles of capnography and explains how to interpret the information it provides.
使用二氧化碳监测仪监测通气 二氧化碳监测仪，指的是根据时间绘制的呼气和吸入性二氧化碳浓度的图形显示，用于监测通气。本视频回顾了二氧化碳监测技术的原理，并解释了如何解释其提供的信息。
Keywords: Humans; Respiration, Artificial; Monitoring, Physiologic/*methods; Contraindications; *Anesthesia, General; Capnography/adverse effects/*methods; Monitoring, Intraoperative/methods

"If I had only known"--on choice and uncertainty in the ICU - Raiten, Jesse M.; Neuman, Mark D. (The New England journal of medicine, 2012)
After receiving a ventricular assist device, a patient experiences months of advances and setbacks in the ICU. She's one of a new subcategory of ICU patients: the chronically critically ill. Their stories reveal shortcomings of common perspectives on medical decision making.
“如果我只知道”--在ICU的选择和不确定性 在接受心室辅助装置后，患者在ICU经历了数月的进步和挫折。她是ICU患者的一个新的亚类：慢性危重病患者。他们的故事揭示了医疗决策中常见观点的不足。
Keywords: Humans; Female; Intensive Care Units; Decision Making; Family; *Choice Behavior; *Critical Care/psychology; *Uncertainty; Chronic Disease/*therapy; General Surgery; Heart Failure/therapy; Heart-Assist Devices; Patients/psychology

Case records of the Massachusetts General Hospital. Case 32-2012. A 35-year-old man with respiratory and renal failure. - Glassock, Richard J.; Khorashadi, Leila; Kushner, Yael B. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例32-2012。1例35岁男性呼吸衰竭和肾衰竭患者。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Pulmonary Alveoli/pathology; Radiography; Lung/diagnostic imaging/pathology; Respiratory Insufficiency/etiology; Hemorrhage/etiology; Renal Insufficiency/etiology; Anti-Glomerular Basement Membrane Disease/diagnosis; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis/diagnosis; Autoantibodies/blood; Kidney/*pathology/ultrastructure; Lung Diseases/diagnosis/etiology; Lupus Erythematosus, Systemic/complications/*diagnosis; Lupus Nephritis/complications/*pathology

Case records of the Massachusetts General Hospital. Case 31-2012. An 18-year-old man with blurred vision, dysarthria, and ataxia. - Yager, Phoebe H.; Singhal, Aneesh B.; Nogueira, Raul G. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例31-2012。1例18岁男性，伴有视力模糊、构音障碍和共济失调。
Keywords: Humans; Male; Diagnosis, Differential; Mechanical Thrombolysis; Adolescent; Risk Factors; Acute Disease; Radiography; Ataxia/etiology; Basilar Artery/diagnostic imaging; Brain Ischemia/complications/diagnosis; Coma/etiology; Dysarthria/etiology; Foramen Ovale, Patent/complications/*diagnosis; Stroke/complications/*diagnosis; Thromboembolism/complications/*diagnosis/therapy; Vision Disorders/etiology

Glucose in the ICU--evidence, guidelines, and outcomes - Kavanagh, Brian P. (The New England journal of medicine, 2012)
ICU中的葡萄糖-证据、指南和结局
Keywords: Humans; Female; Male; *Cardiac Surgical Procedures; Postoperative Complications/*drug therapy; Hypoglycemic Agents/*therapeutic use; Hyperglycemia/*drug therapy

Tight glycemic control versus standard care after pediatric cardiac surgery - Agus, Michael S. D.; Steil, Garry M.; Wypij, David; Costello, John M.; Laussen, Peter C.; Langer, Monica; Alexander, Jamin L.; Scoppettuolo, Lisa A.; Pigula, Frank A.; Charpie, John R.; Ohye, Richard G.; Gaies, Michael G. (The New England journal of medicine, 2012)
BACKGROUND: In some studies, tight glycemic control with insulin improved outcomes in adults undergoing cardiac surgery, but these benefits are unproven in critically ill children at risk for hyperinsulinemic hypoglycemia. We tested the hypothesis that tight glycemic control reduces morbidity after pediatric cardiac surgery. METHODS: In this two-center, prospective, randomized trial, we enrolled 980 children, 0 to 36 months of age, undergoing surgery with cardiopulmonary bypass. Patients were randomly assigned to either tight glycemic control (with the use of an insulin-dosing algorithm targeting a blood glucose level of 80 to 110 mg per deciliter [4.4 to 6.1 mmol per liter]) or standard care in the cardiac intensive care unit (ICU). Continuous glucose monitoring was used to guide the frequency of blood glucose measurement and to detect impending hypoglycemia. The primary outcome was the rate of health care-associated infections in the cardiac ICU. Secondary outcomes included mortality, length of stay, organ failure, and hypoglycemia. RESULTS: A total of 444 of the 490 children assigned to tight glycemic control (91%) received insulin versus 9 of 490 children assigned to standard care (2%). Although normoglycemia was achieved earlier with tight glycemic control than with standard care (6 hours vs. 16 hours, P<0.001) and was maintained for a greater proportion of the critical illness period (50% vs. 33%, P<0.001), tight glycemic control was not associated with a significantly decreased rate of health care-associated infections (8.6 vs. 9.9 per 1000 patient-days, P=0.67). Secondary outcomes did not differ significantly between groups, and tight glycemic control did not benefit high-risk subgroups. Only 3% of the patients assigned to tight glycemic control had severe hypoglycemia (blood glucose <40 mg per deciliter [2.2 mmol per liter]). CONCLUSIONS: Tight glycemic control can be achieved with a low hypoglycemia rate after cardiac surgery in children, but it does not significantly change the infection rate, mortality, length of stay, or measures of organ failure, as compared with standard care.
儿童心脏手术后严格血糖控制与标准治疗的比较 背景：在一些研究中，胰岛素严格控制血糖改善了接受心脏手术的成人的结局，但这些获益尚未在存在高胰岛素血症性低血糖风险的重症儿童中得到证实。我们检验了严格控制血糖可降低儿科心脏手术后发病率的假设。 方法：在这项两中心、前瞻性、随机试验中，我们纳入了980例接受体外循环手术的0-36个月儿童。将患者随机分配至严格血糖控制组（使用胰岛素给药方案，目标血糖水平为80-110 mg/dl[4.4-6.1 mmol/l]）或心脏重症监护室(ICU)标准治疗组。使用连续血糖监测来指导血糖测量的频率和检测即将发生的低血糖。主要结局是心脏ICU中卫生保健相关感染率。次要结局包括死亡率、住院时间、器官衰竭和低血糖。 结果：490名接受严格血糖控制的儿童中共有444名(91%)接受了胰岛素治疗，490名接受标准治疗的儿童中共有9名(2%)接受了胰岛素治疗。尽管与标准治疗相比，严格控制血糖可更早达到血糖正常（6小时vs. 16小时，P < 0.001），且在危重疾病期维持更大比例(50%vs. 33%，P < 0.001)，严格的血糖控制与医疗保健相关感染率的显著降低无关（8.6/1000患者-天vs. 9.9/1000患者-天，P = 0.67）。次要结局没有显著的组间差异，严格的血糖控制没有使高风险亚组获益。分配至严格血糖控制组的患者中，仅3%发生重度低血糖（血糖 < 40 mg/dl[2.2 mmol/l]）。 结论：与标准治疗相比，儿童心脏手术后可以通过较低的低血糖发生率实现严格的血糖控制，但不会显著改变感染率、死亡率、住院时间或器官衰竭指标。
Keywords: Humans; Female; Male; Infant; Blood Glucose/metabolism; Child, Preschool; Intention to Treat Analysis; *Cardiac Surgical Procedures; Critical Illness/therapy; Postoperative Complications/*drug therapy; Intensive Care Units, Pediatric; Hyperglycemia/*drug therapy; Hypoglycemia/chemically induced; Hypoglycemic Agents/adverse effects/*therapeutic use; Infections/epidemiology

Understanding low sugar from NICE-SUGAR - Hirsch, Irl B. (The New England journal of medicine, 2012)
从NICE-sugar中了解低糖
Keywords: Humans; Critical Illness/*mortality; Hyperglycemia/*drug therapy; Hypoglycemia/*mortality; Hypoglycemic Agents/*adverse effects

Hypoglycemia and risk of death in critically ill patients - Finfer, Simon; Liu, Bette; Chittock, Dean R.; Norton, Robyn; Myburgh, John A.; McArthur, Colin; Mitchell, Imogen; Foster, Denise; Dhingra, Vinay; Henderson, William R.; Ronco, Juan J.; Bellomo, Rinaldo; et al. (The New England journal of medicine, 2012)
BACKGROUND: Whether hypoglycemia leads to death in critically ill patients is unclear. METHODS: We examined the associations between moderate and severe hypoglycemia (blood glucose, 41 to 70 mg per deciliter [2.3 to 3.9 mmol per liter] and â‰¤40 mg per deciliter [2.2 mmol per liter], respectively) and death among 6026 critically ill patients in intensive care units (ICUs). Patients were randomly assigned to intensive or conventional glucose control. We used Cox regression analysis with adjustment for treatment assignment and for baseline and postrandomization covariates. RESULTS: Follow-up data were available for 6026 patients: 2714 (45.0%) had moderate hypoglycemia, 2237 of whom (82.4%) were in the intensive-control group (i.e., 74.2% of the 3013 patients in the group), and 223 patients (3.7%) had severe hypoglycemia, 208 of whom (93.3%) were in the intensive-control group (i.e., 6.9% of the patients in this group). Of the 3089 patients who did not have hypoglycemia, 726 (23.5%) died, as compared with 774 of the 2714 with moderate hypoglycemia (28.5%) and 79 of the 223 with severe hypoglycemia (35.4%). The adjusted hazard ratios for death among patients with moderate or severe hypoglycemia, as compared with those without hypoglycemia, were 1.41 (95% confidence interval [CI], 1.21 to 1.62; P<0.001) and 2.10 (95% CI, 1.59 to 2.77; P<0.001), respectively. The association with death was increased among patients who had moderate hypoglycemia on more than 1 day (>1 day vs. 1 day, P=0.01), those who died from distributive (vasodilated) shock (P<0.001), and those who had severe hypoglycemia in the absence of insulin treatment (hazard ratio, 3.84; 95% CI, 2.37 to 6.23; P<0.001). CONCLUSIONS: In critically ill patients, intensive glucose control leads to moderate and severe hypoglycemia, both of which are associated with an increased risk of death. The association exhibits a dose-response relationship and is strongest for death from distributive shock. However, these data cannot prove a causal relationship.
重症患者中的低血糖和死亡风险 背景：低血糖是否导致危重患者死亡尚不清楚。 方法：我们在6026例重症监护病房(ICU)的危重患者中，检查了中度和重度低血糖（血糖，分别为41-70 mg/dl[2.3-3.9 mmol/l]和â‰õ40 mg/dl[2.2 mmol/l]）与死亡之间的关系。患者被随机分配接受强化或常规血糖控制。我们使用Cox回归分析，对治疗分配、基线和随机化后协变量进行调整。 结果：6026例患者有随访数据：2714例(45.0%)发生中度低血糖，其中2237例(82.4%)在强化对照组（即，3013例患者中的74.2%），223例(3.7%)发生重度低血糖，其中208例(93.3%)在强化对照组（即，6.9%的患者）。在未发生低血糖的3089例患者中，有726例(23.5%)死亡，相比之下，在2714例中度低血糖患者中有774例(28.5%)死亡，在223例重度低血糖患者中有79例(35.4%)死亡。与无低血糖的患者相比，中度或重度低血糖患者的死亡校正风险比分别为1.41（95%置信区间[CI]，1.21至1.62；P < 0.001）和2.10（95%CI，1.59至2.77；P < 0.001）。在超过1天发生中度低血糖（> 1天vs. 1天，P = 0.01）、死于分布性休克（血管扩张）的患者(P < 0.001)和未接受胰岛素治疗的重度低血糖患者中，与死亡的相关性增加（风险比，3.84；95%CI，2.37-6.23；P < 0.001）。 结论：在重症患者中，强化血糖控制可导致中度和重度低血糖，两者均与死亡风险增加相关。这种关联表现出一种剂量-反应关系，对分布性休克导致的死亡最强。但是，这些数据不能证明因果关系。
Keywords: Humans; Follow-Up Studies; Risk; Proportional Hazards Models; Critical Illness/*mortality/therapy; Hyperglycemia/*drug therapy; Hypoglycemia/chemically induced/*mortality; Hypoglycemic Agents/*adverse effects/therapeutic use

Case records of the Massachusetts General Hospital. Case 22-2012. A 34-year-old man with intractable vomiting after ingestion of an unknown substance. - MacÃas Konstantopoulos, Wendy; Burns Ewald, Michele; Pratt, Daniel S. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例22-2012。1例34岁男性在摄入未知物质后发生顽固性呕吐。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Renal Dialysis; Vomiting/etiology; Antimony Potassium Tartrate/*poisoning; Chemical and Drug Induced Liver Injury/diagnosis/etiology; Liver Failure, Acute/chemically induced/diagnosis/drug therapy; Poisoning/complications/*diagnosis/therapy

Management of opioid analgesic overdose - Boyer, Edward W. (The New England journal of medicine, 2012)
阿片类镇痛药过量的管理
Keywords: Humans; Intubation, Intratracheal; Analgesics, Opioid/pharmacokinetics/*poisoning; Drug Overdose/diagnosis/epidemiology/physiopathology/therapy; Naloxone/administration & dosage/*therapeutic use; Narcotic Antagonists/administration & dosage/*therapeutic use

Hydroxyethyl starch 130/0.42 versus Ringer's acetate in severe sepsis. - Perner, Anders; Haase, Nicolai; Guttormsen, Anne B.; Tenhunen, Jyrki; Klemenzson, Gudmundur; Åneman, Anders; Madsen, Kristian R.; Møller, Morten H.; Elkjær, Jeanie M.; Poulsen, Lone M.; Bendtsen, Asger; Winding, Robert; et al. (The New England journal of medicine, 2012)
BACKGROUND: Hydroxyethyl starch (HES) [corrected] is widely used for fluid resuscitation in intensive care units (ICUs), but its safety and efficacy have not been established in patients with severe sepsis. METHODS: In this multicenter, parallel-group, blinded trial, we randomly assigned patients with severe sepsis to fluid resuscitation in the ICU with either 6% HES 130/0.42 (Tetraspan) or Ringer's acetate at a dose of up to 33 ml per kilogram of ideal body weight per day. The primary outcome measure was either death or end-stage kidney failure (dependence on dialysis) at 90 days after randomization. RESULTS: Of the 804 patients who underwent randomization, 798 were included in the modified intention-to-treat population. The two intervention groups had similar baseline characteristics. At 90 days after randomization, 201 of 398 patients (51%) assigned to HES 130/0.42 had died, as compared with 172 of 400 patients (43%) assigned to Ringer's acetate (relative risk, 1.17; 95% confidence interval [CI], 1.01 to 1.36; P=0.03); 1 patient in each group had end-stage kidney failure. In the 90-day period, 87 patients (22%) assigned to HES 130/0.42 were treated with renal-replacement therapy versus 65 patients (16%) assigned to Ringer's acetate (relative risk, 1.35; 95% CI, 1.01 to 1.80; P=0.04), and 38 patients (10%) and 25 patients (6%), respectively, had severe bleeding (relative risk, 1.52; 95% CI, 0.94 to 2.48; P=0.09). The results were supported by multivariate analyses, with adjustment for known risk factors for death or acute kidney injury at baseline. CONCLUSIONS: Patients with severe sepsis assigned to fluid resuscitation with HES 130/0.42 had an increased risk of death at day 90 and were more likely to require renal-replacement therapy, as compared with those receiving Ringer's acetate.
羟乙基淀粉130/0.42与醋酸林格氏液在重度脓毒症中的比较。 背景：羟乙基淀粉(HES)[校正]被广泛用于重症监护室(ICU)的液体复苏，但其在严重脓毒症患者中的安全性和有效性尚未确立。 方法：在这项多中心、平行组、设盲试验中，我们将重度脓毒症患者随机分配至ICU液体复苏组，接受6%HES 130/0.42(Tetraspan)或醋酸林格氏液，剂量高达33 mL/kg理想体重/天。主要结局指标为随机分组后90天时的死亡或终末期肾衰竭（依赖透析）。 结果：在804例接受随机分组的患者中，798例纳入改良的意向治疗人群。两个干预组的基线特征相似。在随机分配后90天，有201/398名(51%)分配到HES 130/0.42治疗组的患者死亡，而有172/400名(43%)分配到醋酸林格氏液治疗组的患者死亡（相对风险，1.17；95%置信区间[CI]，1.01至1.36；P = 0.03）；每组各有1名患者发生终末期肾衰竭。在90天期间，有87名(22%)分配到HES 130/0.42治疗组的患者接受了肾脏替代治疗，而有65名(16%)分配到醋酸林格氏液治疗组（相对风险，1.35；95%CI，1.01至1.80；P = 0.04），并且分别有38名(10%)和25名(6%)患者发生了重度出血（相对风险，1.52；95%CI，0.94至2.48；P=0.09).结果得到多变量分析的支持，对基线时死亡或急性肾损伤的已知风险因素进行了校正。 结论：与接受醋酸林格氏液复苏的患者相比，接受HES 130/0.42液体复苏的重度脓毒症患者在第90天的死亡风险增加，并且更可能需要肾脏替代治疗。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Intention to Treat Analysis; Hemorrhage/chemically induced; Hydroxyethyl Starch Derivatives/adverse effects/*therapeutic use; *Fluid Therapy/adverse effects/methods; Renal Replacement Therapy; Isotonic Solutions/adverse effects/*therapeutic use; Kidney Failure, Chronic/etiology/therapy; Sepsis/complications/mortality/*therapy

How far do you go? Intensive care in a resource-poor setting - Eyssallenne, Antonia P. (The New England journal of medicine, 2012)
您能走多远？资源匮乏条件下的重症监护
Keywords: Humans; Female; Child; Palliative Care; Death; *Critical Care/economics; *Developing Countries/economics; *Medical Futility; Haiti; Health Resources

Videos in clinical medicine. Ultrasound-guided peripheral i.v. placement. - Joing, Scott; Strote, Seth; Caroon, Liberty; Wall, Christopher; Hess, Jamie; Roline, Chad; Oh, Laura; Dolan, Ben; Poutre, Robb; Carney, Kathleen; Plummer, David; Reardon, Robert (2012)
临床医学视频。超声引导外周静脉内置入。
Keywords: Humans; Catheterization, Peripheral/adverse effects/instrumentation/*methods; Arm/*blood supply; Ultrasonography, Interventional/methods; Veins/anatomy & histology/diagnostic imaging

Case records of the Massachusetts General Hospital. Case 19-2012. A premature newborn boy with respiratory distress. - Catlin, Elizabeth A.; Warren, H. Shaw; Shailam, Randheer; Lahoud-Rahme, Manuella; Lew, Madelyn (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例19-2012。呼吸窘迫早产新生男婴。
Keywords: Humans; Male; Diagnosis, Differential; Infant, Newborn; Echocardiography; Infant, Premature; Multiple Organ Failure/etiology; Radiography; Fatal Outcome; Myocardium/pathology; Lung/diagnostic imaging/*pathology; Liver/*pathology; Adrenal Glands/*pathology; Herpes Simplex/complications/*diagnosis/pathology; Methadone/adverse effects; Neonatal Abstinence Syndrome/complications; Pneumonia, Viral/complications; Respiratory Distress Syndrome, Newborn/diagnosis/*etiology; Sepsis/diagnosis/virology

Guillain-BarrÃ© syndrome - Yuki, Nobuhiro; Hartung, Hans-Peter (The New England journal of medicine, 2012)
格林巴利综合征
Keywords: Humans; Prognosis; Diagnosis, Differential; Animals; Disease Models, Animal; Incidence; Immunotherapy; *Guillain-Barre Syndrome/diagnosis/etiology/therapy; Autoantibodies/physiology; Gangliosides/immunology; Myelin Sheath/immunology

Rapid whole-genome sequencing for investigation of a neonatal MRSA outbreak - KÃ¶ser, Claudio U.; Holden, Matthew T. G.; Ellington, Matthew J.; Cartwright, Edward J. P.; Brown, Nicholas M.; Ogilvy-Stuart, Amanda L.; Hsu, Li Yang; Chewapreecha, Claire; Croucher, Nicholas J.; Harris, Simon R.; Sanders, Mandy; Enright, Mark C.; et al. (The New England journal of medicine, 2012)
BACKGROUND: Isolates of methicillin-resistant Staphylococcus aureus (MRSA) belonging to a single lineage are often indistinguishable by means of current typing techniques. Whole-genome sequencing may provide improved resolution to define transmission pathways and characterize outbreaks. METHODS: We investigated a putative MRSA outbreak in a neonatal intensive care unit. By using rapid high-throughput sequencing technology with a clinically relevant turnaround time, we retrospectively sequenced the DNA from seven isolates associated with the outbreak and another seven MRSA isolates associated with carriage of MRSA or bacteremia in the same hospital. RESULTS: We constructed a phylogenetic tree by comparing single-nucleotide polymorphisms (SNPs) in the core genome to a reference genome (an epidemic MRSA clone, EMRSA-15 [sequence type 22]). This revealed a distinct cluster of outbreak isolates and clear separation between these and the nonoutbreak isolates. A previously missed transmission event was detected between two patients with bacteremia who were not part of the outbreak. We created an artificial "resistome" of antibiotic-resistance genes and demonstrated concordance between it and the results of phenotypic susceptibility testing; we also created a "toxome" consisting of toxin genes. One outbreak isolate had a hypermutator phenotype with a higher number of SNPs than the other outbreak isolates, highlighting the difficulty of imposing a simple threshold for the number of SNPs between isolates to decide whether they are part of a recent transmission chain. CONCLUSIONS: Whole-genome sequencing can provide clinically relevant data within a time frame that can influence patient care. The need for automated data interpretation and the provision of clinically meaningful reports represent hurdles to clinical implementation.
用于调查新生儿MRSA爆发的快速全基因组测序 背景：通过当前的分型技术，单株菌系的耐甲氧西林金黄色葡萄球菌(MRSA)分离株通常无法区分。全基因组测序可以提供更高的分辨率来定义传播途径和描述暴发的特征。 方法：我们调查了新生儿重症监护室的推定MRSA暴发。通过使用具有临床相关周转时间的快速高通量测序技术，我们回顾性地对与暴发相关的7株分离株和同一家医院中与携带MRSA或菌血症相关的另外7株MRSA分离株进行了DNA测序。 结果：我们通过比较核心基因组与参考基因组（流行性MRSA克隆，EMRSA-15[序列类型22]）的单核苷酸多态性(SNP)构建了一个生物合成树。这表明爆发分离株有明显的集群，并且这些分离株与非爆发分离株有明显的区别。在两名不属于暴发的菌血症患者之间检测到之前遗漏的传播事件。我们创建了抗生素耐药基因的人工“耐药组”，并证明了其与表型药敏试验结果的一致性；我们还创建了由毒素基因组成的“毒素组”。1株爆发分离株具有超突变表型，其SNP数量高于其他爆发分离株，突出说明难以对分离株之间的SNP数量设定一个简单阈值，以决定其是否为近期传播链的一部分。 结论：全基因组测序可以在一个时间框架内提供临床相关数据，可能影响患者护理。自动化数据解释的需求和提供有临床意义的报告代表了临床实施的障碍。
Keywords: Humans; Retrospective Studies; Infant, Newborn; Phenotype; Phylogeny; Microbial Sensitivity Tests; Intensive Care Units, Neonatal; Polymorphism, Single Nucleotide; Sequence Analysis, DNA/methods; *Disease Outbreaks; *Genome, Bacterial; Bacteremia/epidemiology/*microbiology; Cross Infection/epidemiology/microbiology; DNA, Bacterial/analysis; Methicillin Resistance/genetics; Methicillin-Resistant Staphylococcus aureus/*genetics/isolation & purification; Staphylococcal Infections/*epidemiology/microbiology

Clinical practice. Acute limb ischemia. - Creager, Mark A.; Kaufman, John A.; Conte, Michael S. (The New England journal of medicine, 2012)
临床实践。急性肢体缺血。
Keywords: Humans; Male; Middle Aged; Image Processing, Computer-Assisted; Practice Guidelines as Topic; Acute Disease; *Angioplasty; Angiography; Fibrinolytic Agents/*therapeutic use; Ischemia/diagnosis/*therapy; Lower Extremity/*blood supply

Drowning - Szpilman, David; Bierens, Joost J. L. M.; Handley, Anthony J.; Orlowski, James P. (The New England journal of medicine, 2012)
溺水
Keywords: Humans; Female; Male; Intensive Care Units; Risk Factors; Child; Age Factors; Resuscitation/*methods; *Drowning/physiopathology/prevention & control; Near Drowning/*therapy

Drotrecogin alfa (activated) in adults with septic shock - Ranieri, V. Marco; Thompson, B. Taylor; Barie, Philip S.; Dhainaut, Jean-FranÃ§ois; Douglas, Ivor S.; Finfer, Simon; GÃ¥rdlund, Bengt; Marshall, John C.; Rhodes, Andrew; Artigas, Antonio; Payen, Didier; Tenhunen, Jyrki; et al. (The New England journal of medicine, 2012)
BACKGROUND: There have been conflicting reports on the efficacy of recombinant human activated protein C, or drotrecogin alfa (activated) (DrotAA), for the treatment of patients with septic shock. METHODS: In this randomized, double-blind, placebo-controlled, multicenter trial, we assigned 1697 patients with infection, systemic inflammation, and shock who were receiving fluids and vasopressors above a threshold dose for 4 hours to receive either DrotAA (at a dose of 24 Î¼g per kilogram of body weight per hour) or placebo for 96 hours. The primary outcome was death from any cause 28 days after randomization. RESULTS: At 28 days, 223 of 846 patients (26.4%) in the DrotAA group and 202 of 834 (24.2%) in the placebo group had died (relative risk in the DrotAA group, 1.09; 95% confidence interval [CI], 0.92 to 1.28; P=0.31). At 90 days, 287 of 842 patients (34.1%) in the DrotAA group and 269 of 822 (32.7%) in the placebo group had died (relative risk, 1.04; 95% CI, 0.90 to 1.19; P=0.56). Among patients with severe protein C deficiency at baseline, 98 of 342 (28.7%) in the DrotAA group had died at 28 days, as compared with 102 of 331 (30.8%) in the placebo group (risk ratio, 0.93; 95% CI, 0.74 to 1.17; P=0.54). Similarly, rates of death at 28 and 90 days were not significantly different in other predefined subgroups, including patients at increased risk for death. Serious bleeding during the treatment period occurred in 10 patients in the DrotAA group and 8 in the placebo group (P=0.81). CONCLUSIONS: DrotAA did not significantly reduce mortality at 28 or 90 days, as compared with placebo, in patients with septic shock.
Drotrecoginα（活化）治疗脓毒性休克成人患者 背景：关于重组人活化蛋白C或drotrecogin α（活化）(DrotAA)治疗脓毒性休克患者的疗效的报告不一致。 方法：在这项随机、双盲、安慰剂对照、多中心试验中，我们将1697例感染、全身性炎症和休克患者分配至接受高于阈值剂量的液体和血管加压素治疗4小时，接受DrotAA（剂量为24±¼g/kg体重/小时）或安慰剂治疗96小时。主要结局为随机化后28天因任何原因导致的死亡。 结果：第28天，DrotAA组的223/846例患者(26.4%)和安慰剂组的202/834例患者(24.2%)死亡（DrotAA组的相对风险，1.09；95%置信区间[CI]，0.92至1.28；P = 0.31）。90天时，DrotAA组842例患者中的287例(34.1%)和安慰剂组822例患者中的269例(32.7%)死亡（相对风险，1.04；95%CI，0.90-1.19；P = 0.56）。基线时重度蛋白C缺乏的患者中，DrotAA组98/342(28.7%)的患者在28天时死亡，相比之下，安慰剂组102/331(30.8%)的患者死亡（风险比0.93；95%CI，0.74-1.17；P = 0.54）。同样，在其他预定亚组（包括死亡风险增加的患者）中，28天和90天时的死亡率也没有显著差异。DrotAA组10例患者和安慰剂组8例患者在治疗期间发生严重出血(P = 0.81)。 结论：与安慰剂相比，DrotAA未显著降低感染性休克患者28或90天时的死亡率。
Keywords: Humans; Drug Therapy, Combination; Double-Blind Method; Adult; Kaplan-Meier Estimate; Odds Ratio; Anti-Infective Agents/*therapeutic use; Treatment Failure; Protein C Deficiency/complications/mortality; Protein C/*therapeutic use; Recombinant Proteins/therapeutic use; Shock, Septic/complications/*drug therapy/mortality

Septic shock--evaluating another failed treatment - Wenzel, Richard P.; Edmond, Michael B. (The New England journal of medicine, 2012)
感染性休克--评估另一种失败的治疗
Keywords: Humans; Anti-Infective Agents/*therapeutic use; Protein C/*therapeutic use; Recombinant Proteins/therapeutic use; Shock, Septic/*drug therapy

Intensive enough? - Campbell, Victoria (The New England journal of medicine, 2012)
足够密集？
Keywords: Humans; Female; Male; *Intensive Care Units; Critical Illness/*mortality; *Personnel Staffing and Scheduling; Workforce; *Hospital Mortality

Nighttime intensivist staffing and mortality among critically ill patients - Wallace, David J.; Angus, Derek C.; Barnato, Amber E.; Kramer, Andrew A.; Kahn, Jeremy M. (The New England journal of medicine, 2012)
BACKGROUND: Hospitals are increasingly adopting 24-hour intensivist physician staffing as a strategy to improve intensive care unit (ICU) outcomes. However, the degree to which nighttime intensivists are associated with improvements in the quality of ICU care is unknown. METHODS: We conducted a retrospective cohort study involving ICUs that participated in the Acute Physiology and Chronic Health Evaluation (APACHE) clinical information system from 2009 through 2010, linking a survey of ICU staffing practices with patient-level outcomes data from adult ICU admissions. Multivariate models were used to assess the relationship between nighttime intensivist staffing and in-hospital mortality among ICU patients, with adjustment for daytime intensivist staffing, severity of illness, and case mix. We conducted a confirmatory analysis in a second, population-based cohort of hospitals in Pennsylvania from which less detailed data were available. RESULTS: The analysis with the use of the APACHE database included 65,752 patients admitted to 49 ICUs in 25 hospitals. In ICUs with low-intensity daytime staffing, nighttime intensivist staffing was associated with a reduction in risk-adjusted in-hospital mortality (adjusted odds ratio for death, 0.62; P=0.04). Among ICUs with high-intensity daytime staffing, nighttime intensivist staffing conferred no benefit with respect to risk-adjusted in-hospital mortality (odds ratio, 1.08; P=0.78). In the verification cohort, there was a similar relationship among daytime staffing, nighttime staffing, and in-hospital mortality. The interaction between nighttime staffing and daytime staffing was not significant (P=0.18), yet the direction of the findings were similar to those in the APACHE cohort. CONCLUSIONS: The addition of nighttime intensivist staffing to a low-intensity daytime staffing model was associated with reduced mortality. However, a reduction in mortality was not seen in ICUs with high-intensity daytime staffing.
重症患者中的夜间重症监护人员配备和死亡率 背景：医院越来越多地采用24小时重症监护医师人员配备作为改善重症监护室(ICU)结局的策略。但是，尚不清楚夜间重症监护医生与ICU治疗质量改善的相关程度。 方法：我们进行了一项回顾性队列研究，包括2009年至2010年参与急性生理和慢性健康评估(APACHE)临床信息系统的ICU，将ICU人员配备实践调查与成人ICU入院患者水平结局数据相关联。多变量模型用于评估ICU患者中夜间重症监护医生人员配备与住院死亡率之间的关系，对日间重症监护医生人员配备、疾病严重程度和病例组合进行调整。我们在第二项宾夕法尼亚州基于人群的医院队列中进行了验证性分析，从中获得了不太详细的数据。 结果：使用APACHE数据库进行分析，纳入25家医院49间ICU的65,752例患者。在具有低强度日间人员配备的ICU中，夜间重症监护医生人员配备与风险调整的住院死亡率降低相关（死亡调整比值比，0.62；P = 0.04）。在具有高强度日间人员配备的ICU中，夜间重症监护医生人员配备对经风险校正的住院死亡率无获益（比值比，1.08；P = 0.78）。在验证队列中，日间人员配备、夜间人员配备和住院死亡率之间的关系相似。夜间人员配备和日间人员配备之间的相互作用不显著(P = 0.18)，然而结果的方向与APACHE队列相似。 结论：在低强度日间人员配备模型中添加夜间重症监护医生人员配备与死亡率降低相关。然而，在高强度日间人员配备的ICU中未观察到死亡率降低。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Aged; APACHE; Adult; Retrospective Studies; Multivariate Analysis; Risk; *Intensive Care Units; *Personnel Staffing and Scheduling; Workforce; *Hospital Mortality; Critical Illness/*mortality/therapy

Freedom from the tyranny of choice--teaching the end-of-life conversation - Lamas, Daniela; Rosenbaum, Lisa (The New England journal of medicine, 2012)
摆脱选择专制--教育生命终结的谈话
Keywords: Humans; Female; Male; Adult; Respiration, Artificial; *Terminal Care; *Patient Participation; Resuscitation Orders; *Physician-Patient Relations; Internship and Residency/*methods

Images in clinical medicine. Pneumoperitoneum. - Ailon, Jonathan (The New England journal of medicine, 2012)
临床医学图像。气腹。
Keywords: Humans; Female; Aged; Radiography; Fatal Outcome; Glioblastoma/complications; Intestinal Perforation/complications; Peritoneal Cavity/diagnostic imaging; Pneumoperitoneum/*diagnostic imaging/etiology

Case records of the Massachusetts General Hospital. Case 11-2012. A 60-year-old man with weakness, rash, and renal failure. - Channick, Richard N.; Lorenzo, Mayra E.; Wu, Carol C.; Hoang, Mai P. (The New England journal of medicine, 2012)
麻省总医院的病例记录。病例32-2012。1例35岁男性呼吸衰竭和肾衰竭患者。
Keywords: Humans; Male; Middle Aged; Diagnosis, Differential; Exanthema/etiology; Skin/*pathology; Acute Kidney Injury/etiology; Communicable Diseases/diagnosis; Rhabdomyolysis/*etiology; Rocky Mountain Spotted Fever/complications/*pathology; Schizophrenia/complications

Oral rivaroxaban for the treatment of symptomatic pulmonary embolism - BÃ¼ller, Harry R.; Prins, Martin H.; Lensin, Anthonie W. A.; Decousus, HervÃ©; Jacobson, Barry F.; Minar, Erich; Chlumsky, Jaromir; Verhamme, Peter; Wells, Phil; Agnelli, Giancarlo; Cohen, Alexander; Berkowitz, Scott D.; et al. (The New England journal of medicine, 2012)
BACKGROUND: A fixed-dose regimen of rivaroxaban, an oral factor Xa inhibitor, has been shown to be as effective as standard anticoagulant therapy for the treatment of deep-vein thrombosis, without the need for laboratory monitoring. This approach may also simplify the treatment of pulmonary embolism. METHODS: In a randomized, open-label, event-driven, noninferiority trial involving 4832 patients who had acute symptomatic pulmonary embolism with or without deep-vein thrombosis, we compared rivaroxaban (15 mg twice daily for 3 weeks, followed by 20 mg once daily) with standard therapy with enoxaparin followed by an adjusted-dose vitamin K antagonist for 3, 6, or 12 months. The primary efficacy outcome was symptomatic recurrent venous thromboembolism. The principal safety outcome was major or clinically relevant nonmajor bleeding. RESULTS: Rivaroxaban was noninferior to standard therapy (noninferiority margin, 2.0; P=0.003) for the primary efficacy outcome, with 50 events in the rivaroxaban group (2.1%) versus 44 events in the standard-therapy group (1.8%) (hazard ratio, 1.12; 95% confidence interval [CI], 0.75 to 1.68). The principal safety outcome occurred in 10.3% of patients in the rivaroxaban group and 11.4% of those in the standard-therapy group (hazard ratio, 0.90; 95% CI, 0.76 to 1.07; P=0.23). Major bleeding was observed in 26 patients (1.1%) in the rivaroxaban group and 52 patients (2.2%) in the standard-therapy group (hazard ratio, 0.49; 95% CI, 0.31 to 0.79; P=0.003). Rates of other adverse events were similar in the two groups. CONCLUSIONS: A fixed-dose regimen of rivaroxaban alone was noninferior to standard therapy for the initial and long-term treatment of pulmonary embolism and had a potentially improved benefit-risk profile.
口服利伐沙班治疗症状性肺栓塞 背景：已证实口服Xa因子抑制剂利伐沙班的固定剂量方案治疗深静脉血栓形成与标准抗凝治疗一样有效，无需实验室监测。这种方法也可能简化肺栓塞的治疗。 方法：在一项随机、开放标签、事件驱动、非劣效性试验中，纳入4832例有急性症状性肺栓塞伴或不伴深静脉血栓形成的患者，我们比较了利伐沙班（15 mg，每日两次，持续3周，随后20 mg，每日一次），依诺肝素标准治疗，随后调整维生素K拮抗剂剂量，持续3、6或12个月。主要疗效结局是症状性复发性静脉血栓栓塞。主要安全性结局为大出血或临床相关非大出血。 结果：对于主要疗效结局，利伐沙班非劣效于标准治疗（非劣效性界值，2.0；P = 0.003），利伐沙班组50起事件(2.1%)对比标准治疗组44起事件(1.8%)（风险比，1.12；95%置信区间[CI]，0.75至1.68）。利伐沙班组10.3%的患者和标准治疗组11.4%的患者发生了主要安全性结局（风险比，0.90；95%CI，0.76-1.07；P = 0.23）。利伐沙班组26例患者(1.1%)和标准治疗组52例患者(2.2%)观察到大出血（风险比，0.49；95%CI，0.31-0.79；P = 0.003）。两组中其他不良事件的发生率相似。 结论：对于肺栓塞的初始和长期治疗，利伐沙班单药固定剂量方案不劣于标准治疗，可能改善获益-风险特征。
Keywords: Humans; Drug Therapy, Combination; Treatment Outcome; Female; Male; Middle Aged; Aged; Recurrence; Follow-Up Studies; Kaplan-Meier Estimate; Administration, Oral; Hemorrhage/chemically induced; Anticoagulants/adverse effects/*therapeutic use; Morpholines/adverse effects/*therapeutic use; Rivaroxaban; Thiophenes/adverse effects/*therapeutic use; Enoxaparin/adverse effects/therapeutic use; International Normalized Ratio; Pulmonary Embolism/*drug therapy/mortality; Vitamin K/antagonists & inhibitors

Videos in clinical medicine. Emergency pericardiocentesis. - Fitch, Michael T.; Nicks, Bret A.; Pariyadath, Manoj; McGinnis, Henderson D.; Manthey, David E. (2012)
临床医学视频。紧急心包穿刺术。
Keywords: Humans; Contraindications; Aftercare; Cardiac Tamponade/diagnosis/*surgery; Emergency Treatment/methods; Pericardiocentesis/adverse effects/instrumentation/*methods

Images in clinical medicine. Barium aspiration. - Albeldawi, Mazen; Makkar, Rohit (The New England journal of medicine, 2012)
临床医学图像。钡吸入。
Keywords: Humans; Male; Aged; Fatal Outcome; Respiratory Insufficiency/*etiology; *Bronchography; Barium Sulfate/*adverse effects; Pneumonia, Aspiration/complications/*diagnostic imaging

Sildenafil for severe lymphatic malformations - Swetman, Glenda L.; Berk, David R.; Vasanawala, Shreyas S.; Feinstein, Jeffrey A.; Lane, Alfred T.; Bruckner, Anna L. (The New England journal of medicine, 2012)
西地那非治疗重度淋巴畸形
Keywords: Humans; Female; Male; Infant; Administration, Oral; Lymphatic Abnormalities/*drug therapy; Phosphodiesterase 5 Inhibitors/*therapeutic use; Piperazines/*therapeutic use; Purines/therapeutic use; Sildenafil Citrate; Sulfones/*therapeutic use

Low-molecular-weight heparin and mortality in acutely ill medical patients - Kakkar, Ajay K.; Cimminiello, Claudio; Goldhaber, Samuel Z.; Parakh, Rajiv; Wang, Chen; Bergmann, Jean-FranÃ§ois (The New England journal of medicine, 2011)
BACKGROUND: Although thromboprophylaxis reduces the incidence of venous thromboembolism in acutely ill medical patients, an associated reduction in the rate of death from any cause has not been shown. METHODS: We conducted a double-blind, placebo-controlled, randomized trial to assess the effect of subcutaneous enoxaparin (40 mg daily) as compared with placebo--both administered for 10Â±4 days in patients who were wearing elastic stockings with graduated compression--on the rate of death from any cause among hospitalized, acutely ill medical patients at participating sites in China, India, Korea, Malaysia, Mexico, the Philippines, and Tunisia. Inclusion criteria were an age of at least 40 years and hospitalization for acute decompensated heart failure, severe systemic infection with at least one risk factor for venous thromboembolism, or active cancer. The primary efficacy outcome was the rate of death from any cause at 30 days after randomization. The primary safety outcome was the rate of major bleeding during and up to 48 hours after the treatment period. RESULTS: A total of 8307 patients were randomly assigned to receive enoxaparin plus elastic stockings with graduated compression (4171 patients) or placebo plus elastic stockings with graduated compression (4136 patients) and were included in the intention-to-treat population. The rate of death from any cause at day 30 was 4.9% in the enoxaparin group as compared with 4.8% in the placebo group (risk ratio, 1.0; 95% confidence interval [CI], 0.8 to 1.2; P=0.83). The rate of major bleeding was 0.4% in the enoxaparin group and 0.3% in the placebo group (risk ratio, 1.4; 95% CI, 0.7 to 3.1; P=0.35). CONCLUSIONS: The use of enoxaparin plus elastic stockings with graduated compression, as compared with elastic stockings with graduated compression alone, was not associated with a reduction in the rate of death from any cause among hospitalized, acutely ill medical patients.
急性内科患者中低分子量肝素与死亡率 背景：尽管血栓预防可降低急性病患者静脉血栓栓塞的发生率，但尚未显示与任何原因导致的死亡率降低相关。 方法：我们进行了一项双盲、安慰剂对照、随机试验，以评估依诺肝素皮下给药（每日40 mg）与安慰剂相比的效果-在穿着梯度压缩弹力袜的患者中，两种药物均给药10天±4天-对住院患者全因死亡率的影响。中国、印度、韩国、马来西亚、墨西哥、菲律宾和突尼斯参与研究中心的急性疾病患者。入选标准为年龄≥40岁，因急性失代偿性心力衰竭、重度全身感染伴至少一项静脉血栓栓塞风险因素或活动性癌症而住院。主要有效性结局为随机分组后30天时因任何原因所致的死亡率。主要安全性结局是治疗期间和治疗后48小时内大出血的发生率。 结果：共有8307例患者被随机分配接受依诺肝素加压力刻度弹力袜（4171例患者）或安慰剂加压力刻度弹力袜（4136例患者），并纳入意向治疗人群。依诺肝素组第30天全因死亡率为4.9%，安慰剂组为4.8%（风险比，1.0；95%置信区间[CI]，0.8-1.2；P = 0.83）。依诺肝素组大出血发生率为0.4%，安慰剂组为0.3%（风险比，1.4；95%CI，0.7至3.1；P = 0.35）。 结论：与单独使用压力分级弹力袜相比，依诺肝素加压力分级弹力袜与住院急性疾病患者中全因死亡率降低无关。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Cause of Death; Intention to Treat Analysis; Combined Modality Therapy; Acute Disease; *Hospital Mortality; Heart Failure/therapy; Anticoagulants/adverse effects/*therapeutic use; Hemorrhage/etiology; Enoxaparin/adverse effects/*therapeutic use; Injections, Subcutaneous; Infections/therapy; Stockings, Compression; Venous Thromboembolism/prevention & control

Case records of the Massachusetts General Hospital. Case 39-2011. A woman in her 90s with unilateral ptosis. - Venna, Nagagopal; Gonzalez, R. Gilberto; Zukerberg, Lawrence R. (The New England journal of medicine, 2011)
麻省总医院的病例记录。病例39-2011。一名90多岁的女性患有单侧上睑下垂。
Keywords: Humans; Female; Aged, 80 and over; Diagnosis, Differential; Brain/diagnostic imaging/*pathology; Radiography; Fatal Outcome; Lung/diagnostic imaging/pathology; Respiratory Insufficiency/etiology; Nervous System Diseases/diagnosis; Blepharoptosis/*etiology; Myasthenia Gravis/*diagnosis/etiology; Myocarditis/complications/pathology; Paraneoplastic Syndromes/*diagnosis; Polymyositis/complications/pathology; Thymoma/complications/*pathology; Thymus Neoplasms/complications/*pathology

Images in clinical medicine. Pneumopericardium associated with a peptic ulcer. - Andrianov, Alexandre; Nissenbaum, Michael A. (The New England journal of medicine, 2011)
临床医学图像。与消化性溃疡相关的心包积气。
Keywords: Humans; Male; Middle Aged; Radiography; Dyspnea/etiology; Gastric Fistula/complications; Peptic Ulcer Perforation/*complications; Pericardium/diagnostic imaging; Pneumopericardium/*diagnostic imaging/etiology; Stomach Ulcer/*complications

Case records of the Massachusetts General Hospital. Case 38-2011. A 34-year-old man with diarrhea and weakness. - Ryan, Edward T.; Cronin, Carmel G.; Branda, John A. (The New England journal of medicine, 2011)
麻省总医院病例记录。病例21-2016。32岁男性患者，无反应状态。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Chronic Disease; Diarrhea/etiology; Radiography; Hypokalemia/complications; Coccidiosis/complications/*diagnosis; Feces/parasitology; HIV Infections/complications/*diagnosis; Ileus/etiology; Intestines/diagnostic imaging; Paralysis/etiology; Protozoan Infections/diagnosis; Sarcocystidae/*isolation & purification

Case records of the Massachusetts General Hospital. Case 35-2011: A 33-year-old woman with postpartum leukocytosis and Gram-positive bacteremia. - Soper, David E.; Lee, Susanna I.; Kim, Ji Yeon; McDonald, Anna G. (The New England journal of medicine, 2011)
麻省总医院的病例记录。病例35-2011：一例33岁的女性产后白细胞增多和革兰氏阳性菌血症患者。
Keywords: Humans; Female; Adult; Diagnosis, Differential; Pregnancy; Anti-Bacterial Agents/therapeutic use; Vagina/microbiology; Clostridium perfringens/*isolation & purification; Leukocytosis/etiology; Bacteremia/*microbiology; Clostridium Infections/complications/*diagnosis/pathology; Gram-Positive Bacterial Infections/drug therapy/microbiology; Placenta/microbiology/pathology; Pre-Eclampsia; Puerperal Disorders

Extracorporeal membrane oxygenation for ARDS in adults - Brodie, Daniel; Bacchetta, Matthew (The New England journal of medicine, 2011)
A 41-year-old woman presents with severe community-acquired pneumococcal pneumonia. Chest radiography reveals diffuse bilateral infiltrates, and hypoxemic respiratory failure develops despite appropriate antibiotic therapy. She is intubated and mechanical ventilation is initiated with a volume- and pressure-limited approach for the acute respiratory distress syndrome (ARDS). Over the ensuing 24 hours, her partial pressure of arterial oxygen (Pao2) decreases to 40 mm Hg, despite ventilatory support with a fraction of inspired oxygen (Fio2) of 1.0 and a positive end-expiratory pressure (PEEP) of 20 cm of water. She is placed in the prone position and a neuromuscular blocking agent is administered, without improvement in her Pao2. An intensive care specialist recommends the initiation of extracorporeal membrane oxygenation (ECMO).
体外膜肺氧合治疗成人ARDS 1例41岁女性患者出现重度社区获得性肺炎球菌性肺炎。胸部x线显示弥漫性双侧浸润，尽管采用适当的抗生素治疗仍发生低氧性呼吸衰竭。对其进行插管，并采用容量和压力限制方法开始机械通气治疗急性呼吸窘迫综合征(ARDS)。在接下来的24小时内，尽管采用吸入氧浓度分数(Fio2)为1.0和呼气末正压(PEEP)为20 cm水进行通气支持，但其动脉血氧分压(Pao2)降至40 mmHg。患者处于俯卧位，给予神经肌肉阻滞剂，Pao2无改善。重症监护专家建议开始体外膜肺氧合(ECMO)。
Keywords: Humans; Female; Adult; Practice Guidelines as Topic; *Extracorporeal Membrane Oxygenation/adverse effects/methods; Respiratory Distress Syndrome/etiology/*therapy; Community-Acquired Infections/complications; Hypoxia/etiology/therapy; Pneumonia, Pneumococcal/complications

Images in clinical medicine. Traumatic diaphragmatic hernia. - Picetti, Edoardo; Mergoni, Mario (The New England journal of medicine, 2011)
临床医学图像。创伤性膈疝。
Keywords: Humans; Male; Child; Radiography; Dyspnea/etiology; Vomiting/etiology; Diaphragm/diagnostic imaging/*injuries; Hernia, Diaphragmatic, Traumatic/complications/*diagnostic imaging; Rupture/diagnostic imaging

Images in clinical medicine. Ortner's syndrome. - Prada-Delgado, Oscar; Barge-Caballero, Eduardo (The New England journal of medicine, 2011)
临床医学图像。奥特纳综合征。
Keywords: Humans; Female; Middle Aged; Tomography, X-Ray Computed; Cardiomegaly/complications/*diagnostic imaging; Heart Atria/diagnostic imaging; Heart Failure/complications; Hoarseness/*etiology; Vocal Cord Paralysis/etiology

Cardiac arrest and the limitations of clinical trials - Sanders, Arthur B. (The New England journal of medicine, 2011)
心脏骤停和临床试验的局限性
Keywords: Humans; Cardiopulmonary Resuscitation/*methods; Out-of-Hospital Cardiac Arrest/*therapy

A trial of an impedance threshold device in out-of-hospital cardiac arrest - Aufderheide, Tom P.; Nichol, Graham; Rea, Thomas D.; Brown, Siobhan P.; Leroux, Brian G.; Pepe, Paul E.; Kudenchuk, Peter J.; Christenson, Jim; Daya, Mohamud R.; Dorian, Paul; Callaway, Clifton W.; Idris, Ahamed H.; et al. (The New England journal of medicine, 2011)
BACKGROUND: The impedance threshold device (ITD) is designed to enhance venous return and cardiac output during cardiopulmonary resuscitation (CPR) by increasing the degree of negative intrathoracic pressure. Previous studies have suggested that the use of an ITD during CPR may improve survival rates after cardiac arrest. METHODS: We compared the use of an active ITD with that of a sham ITD in patients with out-of-hospital cardiac arrest who underwent standard CPR at 10 sites in the United States and Canada. Patients, investigators, study coordinators, and all care providers were unaware of the treatment assignments. The primary outcome was survival to hospital discharge with satisfactory function (i.e., a score of â‰¤3 on the modified Rankin scale, which ranges from 0 to 6, with higher scores indicating greater disability). RESULTS: Of 8718 patients included in the analysis, 4345 were randomly assigned to treatment with a sham ITD and 4373 to treatment with an active device. A total of 260 patients (6.0%) in the sham-ITD group and 254 patients (5.8%) in the active-ITD group met the primary outcome (risk difference adjusted for sequential monitoring, -0.1 percentage points; 95% confidence interval, -1.1 to 0.8; P=0.71). There were also no significant differences in the secondary outcomes, including rates of return of spontaneous circulation on arrival at the emergency department, survival to hospital admission, and survival to hospital discharge. CONCLUSIONS: Use of the ITD did not significantly improve survival with satisfactory function among patients with out-of-hospital cardiac arrest receiving standard CPR.
阻抗阈值装置在院外心脏骤停中的应用 背景：阻抗阈值装置(ITD)旨在通过增加胸内负压的程度，在心肺复苏(CPR)过程中增强静脉回流和心输出量。既往研究表明，在CPR过程中使用ITD可改善心脏骤停后的生存率。 方法：我们比较了在美国和加拿大10个研究中心进行标准CPR的院外心脏骤停患者中活性ITD和假ITD的使用情况。患者、研究者、研究协调员和所有护理人员均不知晓治疗分配。主要结局为出院时的生存期，功能令人满意（即，改良Rankin量表â‰ë3评分，范围为0-6，评分越高表明残疾程度越大）。 结果：在分析中纳入的8718例患者中，4345例被随机分配接受假ITD治疗，4373例被分配接受活性器械治疗。假ITD组和活性ITD组分别有260名患者(6.0%)和254名患者(5.8%)达到主要结局（根据序贯监测调整的风险差异，-0.1个百分点；95%置信区间，-1.1至0.8；P = 0.71）。次要结局也无显著差异，包括到达急诊科时自主循环恢复率、存活至入院和存活至出院。 结论：在接受标准CPR的院外心脏骤停患者中，使用ITD并未显著改善存活率，功能令人满意。
Keywords: Humans; Treatment Outcome; Female; Male; Aged; Emergency Medical Services; Out-of-Hospital Cardiac Arrest/mortality/*therapy; Cardiopulmonary Resuscitation/*instrumentation

Early versus later rhythm analysis in patients with out-of-hospital cardiac arrest - Stiell, Ian G.; Nichol, Graham; Leroux, Brian G.; Rea, Thomas D.; Ornato, Joseph P.; Powell, Judy; Christenson, James; Callaway, Clifton W.; Kudenchuk, Peter J.; Aufderheide, Tom P.; Idris, Ahamed H.; Daya, Mohamud R.; et al. (The New England journal of medicine, 2011)
BACKGROUND: In a departure from the previous strategy of immediate defibrillation, the 2005 resuscitation guidelines from the American Heart Association-International Liaison Committee on Resuscitation suggested that emergency medical service (EMS) personnel could provide 2 minutes of cardiopulmonary resuscitation (CPR) before the first analysis of cardiac rhythm. We compared the strategy of a brief period of CPR with early analysis of rhythm with the strategy of a longer period of CPR with delayed analysis of rhythm. METHODS: We conducted a cluster-randomized trial involving adults with out-of-hospital cardiac arrest at 10 Resuscitation Outcomes Consortium sites in the United States and Canada. Patients in the early-analysis group were assigned to receive 30 to 60 seconds of EMS-administered CPR and those in the later-analysis group were assigned to receive 180 seconds of CPR, before the initial electrocardiographic analysis. The primary outcome was survival to hospital discharge with satisfactory functional status (a modified Rankin scale score of â‰¤3, on a scale of 0 to 6, with higher scores indicating greater disability). RESULTS: We included 9933 patients, of whom 5290 were assigned to early analysis of cardiac rhythm and 4643 to later analysis. A total of 273 patients (5.9%) in the later-analysis group and 310 patients (5.9%) in the early-analysis group met the criteria for the primary outcome, with a cluster-adjusted difference of -0.2 percentage points (95% confidence interval, -1.1 to 0.7; P=0.59). Analyses of the data with adjustment for confounding factors, as well as subgroup analyses, also showed no survival benefit for either study group. CONCLUSIONS: Among patients who had an out-of-hospital cardiac arrest, we found no difference in the outcomes with a brief period, as compared with a longer period, of EMS-administered CPR before the first analysis of cardiac rhythm.
院外心脏骤停患者的早期与晚期节律分析 背景：与之前的即刻除颤策略不同，美国心脏协会-复苏国际联络委员会2005年复苏指南建议，急救医疗服务(EMS)人员可在首次分析心律前提供2 min心肺复苏(CPR)。我们比较了短时期CPR伴早期节律分析的策略与较长时期CPR伴延迟节律分析的策略。 方法：我们在美国和加拿大的10个复苏结局联盟中心进行了一项涉及院外心脏骤停成人的集群随机试验。早期分析组患者被分配接受30至60秒的EMS CPR，后期分析组患者被分配接受180秒的CPR，均在初始心电图分析之前。主要结局是出院后存活，功能状态满意（改良Rankin量表评分‰â3，量表0-6分，分数越高表示残疾程度越大）。 结果：我们纳入了9933例患者，其中5290例被分配至早期心律分析，4643例被分配至后期分析。晚期分析组和早期分析组分别有273例(5.9%)和310例(5.9%)患者符合主要结局的标准，集群校正的差异为-0.2个百分点（95%置信区间， -1.1至0.7；P = 0.59）。针对混杂因素进行调整的数据分析以及亚组分析也显示，任一研究组均无生存获益。 结论：在院外发生心脏骤停的患者中，我们发现在首次分析心律前，与较长时期相比，EMS-给予CPR的短期结局无差异。
Keywords: Humans; Treatment Outcome; Female; Male; Time Factors; Aged; Heart Rate; Emergency Medical Services; Cardiopulmonary Resuscitation/*methods; Out-of-Hospital Cardiac Arrest/mortality/*therapy; Electrocardiography

Intrapleural use of tissue plasminogen activator and DNase in pleural infection - Rahman, Najib M.; Maskell, Nicholas A.; West, Alex; Teoh, Richard; Arnold, Anthony; Mackinlay, Carolyn; Peckham, Daniel; Davies, Chris W. H.; Ali, Nabeel; Kinnear, William; Bentley, Andrew; Kahan, Brennan C.; et al. (The New England journal of medicine, 2011)
BACKGROUND: More than 30% of patients with pleural infection either die or require surgery. Drainage of infected fluid is key to successful treatment, but intrapleural fibrinolytic therapy did not improve outcomes in an earlier, large, randomized trial. METHODS: We conducted a blinded, 2-by-2 factorial trial in which 210 patients with pleural infection were randomly assigned to receive one of four study treatments for 3 days: double placebo, intrapleural tissue plasminogen activator (t-PA) and DNase, t-PA and placebo, or DNase and placebo. The primary outcome was the change in pleural opacity, measured as the percentage of the hemithorax occupied by effusion, on chest radiography on day 7 as compared with day 1. Secondary outcomes included referral for surgery, duration of hospital stay, and adverse events. RESULTS: The mean (±SD) change in pleural opacity was greater in the t-PA-DNase group than in the placebo group (-29.5±23.3% vs. -17.2±19.6%; difference, -7.9%; 95% confidence interval [CI], -13.4 to -2.4; P=0.005); the change observed with t-PA alone and with DNase alone (-17.2±24.3 and -14.7±16.4%, respectively) was not significantly different from that observed with placebo. The frequency of surgical referral at 3 months was lower in the t-PA-DNase group than in the placebo group (2 of 48 patients [4%] vs. 8 of 51 patients [16%]; odds ratio for surgical referral, 0.17; 95% CI, 0.03 to 0.87; P=0.03) but was greater in the DNase group (18 of 46 patients [39%]) than in the placebo group (odds ratio, 3.56; 95% CI, 1.30 to 9.75; P=0.01). Combined t-PA-DNase therapy was associated with a reduction in the hospital stay, as compared with placebo (difference, -6.7 days; 95% CI, -12.0 to -1.9; P=0.006); the hospital stay with either agent alone was not significantly different from that with placebo. The frequency of adverse events did not differ significantly among the groups. CONCLUSIONS: Intrapleural t-PA-DNase therapy improved fluid drainage in patients with pleural infection and reduced the frequency of surgical referral and the duration of the hospital stay. Treatment with DNase alone or t-PA alone was ineffective.
胸膜腔内应用组织型纤溶酶原激活剂和dna酶治疗胸膜感染 背景：超过30%的胸膜感染患者死亡或需要手术治疗。感染液体引流是成功治疗的关键，但在一项早期、大型、随机化试验中，胸腔内纤维蛋白溶解治疗未改善结局。 方法：我们进行了一项盲法、2 × 2析因试验，其中210例胸膜感染患者被随机分配接受为期3天的四种研究治疗之一：双重安慰剂、胸膜内组织纤溶酶原激活剂(t-PA)和dna酶、t-PA和安慰剂或dna酶和安慰剂。主要结局是与第1天相比，第7天胸部x线检查胸膜不透明的变化，测量为积液占据的半胸百分比。次要结局包括转诊进行手术、住院时间和不良事件。 结果：t-PA-DNase组的胸膜混浊度的平均(Δ±SD)变化大于安慰剂组（Δ29.5±23.3%vs.Δ17.2±19.6%；差异，-7.9%；95%置信区间[CI]， -13.4至-2.4；P = 0.005）；观察到t-PA单独给药和DNase单独给药时的变化（-17.2Δ±24.3和-14.7Δ±16.4%，分别）与安慰剂组观察到的结果无显著差异。t-PA-DNase组3个月时手术转诊的频率低于安慰剂组（48例患者中的2例[4%]vs. 51例患者中的8例[16%]；手术转诊的比值比，0.17；95%CI，0.03至0.87；P = 0.03），但dna酶组（46例患者中的18例[39%]）高于安慰剂组（比值比，3.56；95%CI，1.30至9.75；P = 0.01）。与安慰剂相比，联合t-PA-DNase治疗与住院时间缩短相关（差异，-6.7天；95%CI，-12.0至-1.9；P = 0.006）；两种药物单药治疗的住院时间与安慰剂无显著差异。各组间不良事件的频率没有显著差异。 结论：胸腔内t-PA-DNase治疗改善了胸膜感染患者的液体引流，降低了外科转诊频率和住院时间。单用dna酶或单用t-PA治疗无效。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Adult; Intention to Treat Analysis; Linear Models; Lung/diagnostic imaging; Radiography; Deoxyribonucleases/adverse effects/*therapeutic use; Fibrinolytic Agents/adverse effects/*therapeutic use; Instillation, Drug; Pleural Diseases/diagnostic imaging/*drug therapy/mortality; Pleural Effusion/diagnostic imaging/*drug therapy; Tissue Plasminogen Activator/adverse effects/*therapeutic use

Early versus late parenteral nutrition in critically ill adults - Casaer, Michael P.; Mesotten, Dieter; Hermans, Greet; Wouters, Pieter J.; Schetz, Miet; Meyfroidt, Geert; Van Cromphaut, Sophie; Ingels, Catherine; Meersseman, Philippe; Muller, Jan; Vlasselaers, Dirk; Debaveye, Yves; et al. (The New England journal of medicine, 2011)
BACKGROUND: Controversy exists about the timing of the initiation of parenteral nutrition in critically ill adults in whom caloric targets cannot be met by enteral nutrition alone. METHODS: In this randomized, multicenter trial, we compared early initiation of parenteral nutrition (European guidelines) with late initiation (American and Canadian guidelines) in adults in the intensive care unit (ICU) to supplement insufficient enteral nutrition. In 2312 patients, parenteral nutrition was initiated within 48 hours after ICU admission (early-initiation group), whereas in 2328 patients, parenteral nutrition was not initiated before day 8 (late-initiation group). A protocol for the early initiation of enteral nutrition was applied to both groups, and insulin was infused to achieve normoglycemia. RESULTS: Patients in the late-initiation group had a relative increase of 6.3% in the likelihood of being discharged alive earlier from the ICU (hazard ratio, 1.06; 95% confidence interval [CI], 1.00 to 1.13; P=0.04) and from the hospital (hazard ratio, 1.06; 95% CI, 1.00 to 1.13; P=0.04), without evidence of decreased functional status at hospital discharge. Rates of death in the ICU and in the hospital and rates of survival at 90 days were similar in the two groups. Patients in the late-initiation group, as compared with the early-initiation group, had fewer ICU infections (22.8% vs. 26.2%, P=0.008) and a lower incidence of cholestasis (P<0.001). The late-initiation group had a relative reduction of 9.7% in the proportion of patients requiring more than 2 days of mechanical ventilation (P=0.006), a median reduction of 3 days in the duration of renal-replacement therapy (P=0.008), and a mean reduction in health care costs of â‚¬1,110 (about $1,600) (P=0.04). CONCLUSIONS: Late initiation of parenteral nutrition was associated with faster recovery and fewer complications, as compared with early initiation.
危重病儿童早期与晚期肠外营养的比较 背景：在仅通过肠内营养无法达到热量目标的重症成人中，开始肠外营养的时机仍存在争议。 方法：在这项随机、多中心试验中，我们比较了重症监护室(ICU)成人早期开始肠外营养（欧洲指南）与晚期开始肠外营养（美国和加拿大指南），以补充不足的肠内营养。2312例患者在进入ICU后48小时内开始肠外营养（早期开始组），而2328例患者在第8天之前未开始肠外营养（晚期开始组）。两组均采用早期开始肠内营养的方案，并输注胰岛素以达到正常血糖。 结果：晚期开始治疗组患者从ICU（风险比，1.06；95%置信区间[CI]，1.00至1.13；P = 0.04）和医院（风险比，1.06；95%CI，1.00至1.13；P = 0.04）出院的可能性相对增加6.3%，无出院时功能状态下降的证据。两组的ICU和医院死亡率以及90天生存率相似。与早期启动组相比，晚期启动组患者的ICU感染更少(22.8%vs. 26.2%，P = 0.008)，胆汁淤积发生率更低(P < 0.001)。晚期开始治疗组中，需要2天以上机械通气的患者比例相对下降9.7%(P=0.006)，肾脏替代治疗的持续时间中位数下降3天(P=0.008)，医疗保健费用平均下降â<unk>1,110（约1,600美元）(P=0.04)。 结论：与早期开始相比，延迟开始胃肠外营养与更快恢复和更少并发症相关。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Time Factors; Aged; Intensive Care Units; Adult; Kaplan-Meier Estimate; Practice Guidelines as Topic; Enteral Nutrition; Length of Stay/statistics & numerical data; Critical Illness/mortality/*therapy; Energy Intake; *Parenteral Nutrition; Infections/epidemiology; Inflammation/epidemiology

Nutrition support in critical illness--bridging the evidence gap - Ziegler, Thomas R. (The New England journal of medicine, 2011)
危重病患者的营养支持--弥补证据缺口
Keywords: Humans; Time Factors; Critical Illness/*therapy; Enteral Nutrition; Vitamins/therapeutic use; Blood Glucose; Hospital Costs; *Parenteral Nutrition

Clinical problem-solving. Looking at the whole picture. - Donagh, Carol; Bruzzi, John; MacNeill, Briain; DaCosta, Mark; Berman, Jeffrey S.; O'Regan, Anthony W. (The New England journal of medicine, 2011)
临床问题解决。观察整个过程。
Keywords: Humans; Female; Middle Aged; Immunocompromised Host; Lung/diagnostic imaging; Radiography; Dyspnea/etiology; Echocardiography, Transesophageal; Heart Diseases/complications/*diagnostic imaging; Foramen Ovale, Patent/complications/*diagnosis; Heart Atria/diagnostic imaging; Breast Neoplasms/complications; Radionuclide Imaging; Thrombosis/complications/*diagnostic imaging

Images in clinical medicine. "Thumb sign" of epiglottitis. - Grover, Casey (The New England journal of medicine, 2011)
临床医学图像。会厌炎“拇指征”。
Keywords: Humans; Male; Middle Aged; Radiography; Epiglottis/*diagnostic imaging/pathology; Epiglottitis/*diagnostic imaging

Case records of the Massachusetts General Hospital. Case 23-2011. A 40-year-old pregnant woman with placenta accreta who declined blood products. - Barth, William H. Jr; Kwolek, Christopher J.; Abrams, Joshua L.; Ecker, Jeffrey L.; Roberts, Drucilla J. (The New England journal of medicine, 2011)
麻省总医院的病例记录。病例23-2011。1例40岁胎盘植入孕妇，拒绝血液制品。
Keywords: Humans; Female; Adult; Pregnancy; Ultrasonography; Ethics, Medical; *Treatment Refusal; *Blood Transfusion; Blood Loss, Surgical/prevention & control; Cesarean Section/*methods; Hemostatic Techniques; Hysterectomy/methods; Personal Autonomy; Placenta Accreta/diagnostic imaging/pathology/*therapy; Placenta Previa/diagnostic imaging/pathology/*therapy; Religion; Uterus/pathology

Rapid-response teams - Jones, Daryl A.; DeVita, Michael A.; Bellomo, Rinaldo (The New England journal of medicine, 2011)
快速团队回复
Keywords: Humans; Monitoring, Physiologic; Critical Care; Critical Illness/*therapy; *Hospital Rapid Response Team/organization & administration; Iatrogenic Disease/prevention & control; Medical Errors/prevention & control

Images in clinical medicine. Angioedema. - Bramante, Robert Matthew; Rand, Masha (The New England journal of medicine, 2011)
临床医学图像。血管性水肿。
Keywords: Humans; Male; Aged; Angiotensin-Converting Enzyme Inhibitors/*adverse effects; Angioedema/chemically induced/*pathology; Enalapril/*adverse effects; Tongue Diseases/chemically induced/*pathology

The lost decade of nesiritide - Topol, Eric J. (The New England journal of medicine, 2011)
奈西立肽的损失十年
Keywords: Humans; Treatment Outcome; Acute Disease; Hypotension/chemically induced; Drug Approval; Dyspnea/*drug therapy/etiology; Heart Failure/complications/*drug therapy; Natriuretic Agents/adverse effects/*therapeutic use; Natriuretic Peptide, Brain/adverse effects/*therapeutic use

Effect of nesiritide in patients with acute decompensated heart failure - O'Connor, C. M.; Starling, R. C.; Hernandez, A. F.; Armstrong, P. W.; Dickstein, K.; Hasselblad, V.; Heizer, G. M.; Komajda, M.; Massie, B. M.; McMurray, J. J. V.; Nieminen, M. S.; Reist, C. J.; et al. (The New England journal of medicine, 2011)
BACKGROUND: Nesiritide is approved in the United States for early relief of dyspnea in patients with acute heart failure. Previous meta-analyses have raised questions regarding renal toxicity and the mortality associated with this agent. METHODS: We randomly assigned 7141 patients who were hospitalized with acute heart failure to receive either nesiritide or placebo for 24 to 168 hours in addition to standard care. Coprimary end points were the change in dyspnea at 6 and 24 hours, as measured on a 7-point Likert scale, and the composite end point of rehospitalization for heart failure or death within 30 days. RESULTS: Patients randomly assigned to nesiritide, as compared with those assigned to placebo, more frequently reported markedly or moderately improved dyspnea at 6 hours (44.5% vs. 42.1%, P=0.03) and 24 hours (68.2% vs. 66.1%, P=0.007), but the prespecified level for significance (Pâ‰¤0.005 for both assessments or Pâ‰¤0.0025 for either) was not met. The rate of rehospitalization for heart failure or death from any cause within 30 days was 9.4% in the nesiritide group versus 10.1% in the placebo group (absolute difference, -0.7 percentage points; 95% confidence interval [CI], -2.1 to 0.7; P=0.31). There were no significant differences in rates of death from any cause at 30 days (3.6% with nesiritide vs. 4.0% with placebo; absolute difference, -0.4 percentage points; 95% CI, -1.3 to 0.5) or rates of worsening renal function, defined by more than a 25% decrease in the estimated glomerular filtration rate (31.4% vs. 29.5%; odds ratio, 1.09; 95% CI, 0.98 to 1.21; P=0.11). CONCLUSIONS: Nesiritide was not associated with an increase or a decrease in the rate of death and rehospitalization and had a small, nonsignificant effect on dyspnea when used in combination with other therapies. It was not associated with a worsening of renal function, but it was associated with an increase in rates of hypotension. On the basis of these results, nesiritide cannot be recommended for routine use in the broad population of patients with acute heart failure.
奈西利肽在急性失代偿性心力衰竭患者中的疗效 背景：奈西立肽在美国获批用于早期缓解急性心力衰竭患者的呼吸困难。既往荟萃分析提出了与该药物相关的肾毒性和死亡率问题。 方法：我们随机分配了7141例急性心力衰竭住院患者，在标准治疗的基础上接受奈西立肽或安慰剂治疗24-168小时。共同主要终点为6小时和24小时时呼吸困难的变化，采用7分Likert量表测量，复合终点为30天内因心力衰竭再住院或死亡。 结果：与安慰剂组患者相比，随机分配至奈西立肽组的患者在6小时(44.5%vs. 42.1%，P = 0.03)和24小时(68.2%vs. 66.1%，P = 0.007)更常报告呼吸困难明显或中度改善，但未达到预先规定的显著性水平（两项评估均为Pâ‰ë0.005，两项评估均为Pâ‰ë0.0025）。奈西立肽组30天内因心力衰竭或全因死亡再次住院的发生率为9.4%，安慰剂组为10.1%（绝对差异，-0.7个百分点；95%置信区间[CI]，-2.1至0.7；P = 0.31）。30天时全因死亡率（奈西立肽组3.6%vs安慰剂组4.0%；绝对差异，-0.4个百分点；95%CI，-1.3至0.5）或肾功能恶化率（定义为估计的肾小球滤过率降低超过25%）（31.4%vs 29.5%；比值比，1.09；95%CI，0.98-1.21；P = 0.11）。 结论：当与其他疗法联合使用时，奈西立肽与死亡率和再住院率的增加或降低无关，对呼吸困难有较小的非显著性影响。与肾功能恶化无关，但与低血压发生率增加相关。基于这些结果，奈西立肽不推荐在广泛的急性心力衰竭患者人群中常规使用。
Keywords: Humans; Female; Male; Middle Aged; Double-Blind Method; Aged; Recurrence; Intention to Treat Analysis; Acute Disease; Patient Readmission/*statistics & numerical data; Kidney Diseases/etiology; Hypotension/chemically induced; Dyspnea/*drug therapy/etiology; Natriuretic Agents/adverse effects/*therapeutic use; Natriuretic Peptide, Brain/adverse effects/*therapeutic use; Heart Failure/complications/*drug therapy/mortality

Assessing the safety of adding LABAs to inhaled corticosteroids for treating asthma - Chowdhury, Badrul A.; Seymour, Sally M.; Levenson, Mark S. (The New England journal of medicine, 2011)
评估在吸入性糖皮质激素的基础上加用LABA治疗哮喘的安全性
Keywords: Humans; Drug Therapy, Combination; Adult; Adolescent; Child; Child, Preschool; United States; Adrenal Cortex Hormones/*therapeutic use; United States Food and Drug Administration; Administration, Inhalation; Drug Approval; *Clinical Trials as Topic; Adrenergic beta-Agonists/*adverse effects/therapeutic use; Asthma/*drug therapy; Bronchodilator Agents/*adverse effects/therapeutic use; Drug Evaluation

Fluid resuscitation in acute illness--time to reappraise the basics - Myburgh, John A. (The New England journal of medicine, 2011)
急性病中的液体复苏--重新评价基础知识的时间
Keywords: Humans; Risk; Critical Illness/therapy; Sodium Chloride/administration & dosage; Albumins/administration & dosage; Africa, Eastern; Fluid Therapy/*methods/mortality; Shock/mortality/*therapy

Mortality after fluid bolus in African children with severe infection - Maitland, Kathryn; Kiguli, Sarah; Opoka, Robert O.; Engoru, Charles; Olupot-Olupot, Peter; Akech, Samuel O.; Nyeko, Richard; Mtove, George; Reyburn, Hugh; Lang, Trudie; Brent, Bernadette; Evans, Jennifer A.; et al. (The New England journal of medicine, 2011)
BACKGROUND: The role of fluid resuscitation in the treatment of children with shock and life-threatening infections who live in resource-limited settings is not established. METHODS: We randomly assigned children with severe febrile illness and impaired perfusion to receive boluses of 20 to 40 ml of 5% albumin solution (albumin-bolus group) or 0.9% saline solution (saline-bolus group) per kilogram of body weight or no bolus (control group) at the time of admission to a hospital in Uganda, Kenya, or Tanzania (stratum A); children with severe hypotension were randomly assigned to one of the bolus groups only (stratum B). All children received appropriate antimicrobial treatment, intravenous maintenance fluids, and supportive care, according to guidelines. Children with malnutrition or gastroenteritis were excluded. The primary end point was 48-hour mortality; secondary end points included pulmonary edema, increased intracranial pressure, and mortality or neurologic sequelae at 4 weeks. RESULTS: The data and safety monitoring committee recommended halting recruitment after 3141 of the projected 3600 children in stratum A were enrolled. Malaria status (57% overall) and clinical severity were similar across groups. The 48-hour mortality was 10.6% (111 of 1050 children), 10.5% (110 of 1047 children), and 7.3% (76 of 1044 children) in the albumin-bolus, saline-bolus, and control groups, respectively (relative risk for saline bolus vs. control, 1.44; 95% confidence interval [CI], 1.09 to 1.90; P=0.01; relative risk for albumin bolus vs. saline bolus, 1.01; 95% CI, 0.78 to 1.29; P=0.96; and relative risk for any bolus vs. control, 1.45; 95% CI, 1.13 to 1.86; P=0.003). The 4-week mortality was 12.2%, 12.0%, and 8.7% in the three groups, respectively (P=0.004 for the comparison of bolus with control). Neurologic sequelae occurred in 2.2%, 1.9%, and 2.0% of the children in the respective groups (P=0.92), and pulmonary edema or increased intracranial pressure occurred in 2.6%, 2.2%, and 1.7% (P=0.17), respectively. In stratum B, 69% of the children (9 of 13) in the albumin-bolus group and 56% (9 of 16) in the saline-bolus group died (P=0.45). The results were consistent across centers and across subgroups according to the severity of shock and status with respect to malaria, coma, sepsis, acidosis, and severe anemia. CONCLUSIONS: Fluid boluses significantly increased 48-hour mortality in critically ill children with impaired perfusion in these resource-limited settings in Africa.
非洲重度感染儿童液体推注后的死亡率 背景：尚未确定液体复苏在治疗居住在资源有限环境中的休克和危及生命的感染儿童中的作用。 方法：我们将重度发热性疾病和灌注受损的儿童随机分配至乌干达、肯尼亚、或坦桑尼亚（A层）；重度低血压儿童随机分配至仅推注组之一（B层）。根据指南，所有儿童均接受适当的抗菌治疗、静脉维持液体和支持治疗。排除营养不良或胃肠炎患儿。主要终点为48小时死亡率；次要终点包括4周时肺水肿、颅内压升高和死亡率或神经系统后遗症。 结果：数据和安全性监查委员会建议在A层计划招募的3600例儿童中有3141例入组后停止招募。各组间的疟疾状态（总体57%）和临床严重程度相似。白蛋白推注组、生理盐水推注组和对照组的48小时死亡率分别为10.6%（111/1050名儿童）、10.5%（110/1047名儿童）和7.3%（76/1044名儿童）（生理盐水推注vs.对照的相对风险，1.44；95%置信区间[CI]，1.09至1.90；P = 0.01；白蛋白推注vs.生理盐水推注的相对风险，1.01；95%CI，0.78-1.29；P = 0.96；任何推注与对照的相对风险，1.45；95%CI，1.13-1.86；P = 0.003）。3组的4周死亡率分别为12.2%、12.0%和8.7%（推注与对照比较，P = 0.004）。各组中2.2%、1.9%和2.0%的儿童发生了神经系统后遗症(P = 0.92)，和肺水肿或颅内压增高的发生率分别为2.6%、2.2%和1.7%(P = 0.17)。在B层，白蛋白输注组69%的儿童(9/13)和生理盐水输注组56%的儿童(9/16)死亡(P = 0.45)。根据休克的严重程度和疟疾、昏迷、败血症、酸中毒和重度贫血的状态，各中心和各亚组之间的结果一致。 结论：在非洲这些资源有限的环境中，液体推注显著增加了灌注受损的重症儿童的48小时死亡率。
Keywords: Humans; Female; Male; Child; Infant; Child, Preschool; Intention to Treat Analysis; Risk; Critical Illness/mortality/therapy; Resuscitation/methods; Fever; Albumins/*administration & dosage; Africa, Eastern; Fluid Therapy/*methods/mortality; Shock/mortality/*therapy; Hypotension/therapy; Infections/mortality/*therapy; Sodium Chloride/*administration & dosage

Images in clinical medicine. Laryngopharyngeal edema. - Watanabe, Kenta; Nakaya, Muneo (The New England journal of medicine, 2011)
临床医学图像。喉咽水肿。
Keywords: Humans; Female; Aged; Anesthetics, Local/*adverse effects; Edema/etiology/*pathology; Epinephrine/adverse effects; Hypopharynx/*pathology; Lidocaine/adverse effects; Pharyngeal Diseases/etiology/*pathology

Videos in clinical medicine. Fiberoptic intubation. - Heidegger, Thomas (2011)
临床医学视频。光纤插管。
Keywords: Humans; Contraindications; Anesthesia, General; Intubation, Intratracheal/adverse effects/instrumentation/*methods; Optical Fibers

Images in clinical medicine. Fat embolism syndrome. - Liu, Hsiao-Kan; Chen, Wen-Chau (The New England journal of medicine, 2011)
临床医学图像。脂肪栓塞综合征。
Keywords: Humans; Male; Middle Aged; Magnetic Resonance Imaging; Brain Diseases/etiology/*pathology; Cerebrum/*pathology; Embolism, Fat/etiology/*pathology; Femoral Fractures/*complications; Purpura/etiology/pathology

Increased 36-week survival with high oxygen saturation target in extremely preterm infants - Stenson, Ben; Brocklehurst, Peter; Tarnow-Mordi, William (The New England journal of medicine, 2011)
在极度早产儿中增加36周生存率和高氧饱和度目标
Keywords: Humans; Infant, Newborn; Oxygen/*blood; Algorithms; Oxygen Inhalation Therapy/*methods; Infant, Premature/*blood; Oximetry/instrumentation

Case records of the Massachusetts General Hospital. Case 12-2011. A 9-month-old boy with acute liver failure. - Fearing, Marsha Kay; Israel, Esther J.; Sahai, Inderneel; Rapalino, Otto; Lisovsky, Mikhail (The New England journal of medicine, 2011)
麻省总医院的病例记录。病例12-2011。1例9个月大的急性肝衰竭男孩。
Keywords: Humans; Male; Diagnosis, Differential; Infant, Newborn; Ultrasonography; Diarrhea/etiology; Biopsy; Abdomen/diagnostic imaging; Liver Failure, Acute/*etiology; Liver/diagnostic imaging/*pathology; Fatty Liver/complications/*pathology; Genes, Recessive; Lipid Metabolism, Inborn Errors/complications/*diagnosis/pathology; Membrane Transport Proteins/*deficiency/genetics; Metabolism, Inborn Errors/diagnosis

Videos in clinical medicine. Pulse oximetry. - Ortega, Rafael; Hansen, Christopher J.; Elterman, Kelly; Woo, Albert (2011)
临床医学视频。脉搏血氧饱和度。
Keywords: Humans; Contraindications; Hemoglobins/analysis; Hypoxia/*diagnosis; Oximetry/adverse effects/instrumentation/*methods; Oxyhemoglobins/analysis

Decompressive craniectomy in diffuse traumatic brain injury - Cooper, D. James; Rosenfeld, Jeffrey V.; Murray, Lynnette; Arabi, Yaseen M.; Davies, Andrew R.; D'Urso, Paul; Kossmann, Thomas; Ponsford, Jennie; Seppelt, Ian; Reilly, Peter; Wolfe, Rory (The New England journal of medicine, 2011)
BACKGROUND: It is unclear whether decompressive craniectomy improves the functional outcome in patients with severe traumatic brain injury and refractory raised intracranial pressure. METHODS: From December 2002 through April 2010, we randomly assigned 155 adults with severe diffuse traumatic brain injury and intracranial hypertension that was refractory to first-tier therapies to undergo either bifrontotemporoparietal decompressive craniectomy or standard care. The original primary outcome was an unfavorable outcome (a composite of death, vegetative state, or severe disability), as evaluated on the Extended Glasgow Outcome Scale 6 months after the injury. The final primary outcome was the score on the Extended Glasgow Outcome Scale at 6 months. RESULTS: Patients in the craniectomy group, as compared with those in the standard-care group, had less time with intracranial pressures above the treatment threshold (P<0.001), fewer interventions for increased intracranial pressure (P<0.02 for all comparisons), and fewer days in the intensive care unit (ICU) (P<0.001). However, patients undergoing craniectomy had worse scores on the Extended Glasgow Outcome Scale than those receiving standard care (odds ratio for a worse score in the craniectomy group, 1.84; 95% confidence interval [CI], 1.05 to 3.24; P=0.03) and a greater risk of an unfavorable outcome (odds ratio, 2.21; 95% CI, 1.14 to 4.26; P=0.02). Rates of death at 6 months were similar in the craniectomy group (19%) and the standard-care group (18%). CONCLUSIONS: In adults with severe diffuse traumatic brain injury and refractory intracranial hypertension, early bifrontotemporoparietal decompressive craniectomy decreased intracranial pressure and the length of stay in the ICU but was associated with more unfavorable outcomes.
Decompressive craniectomy in diffuse traumatic brain injury 背景：目前尚不清楚去骨瓣减压术是否能改善重度创伤性脑损伤和难治性颅内压升高患者的功能结局。 方法：从2002年12月至2010年4月，我们将155例经一线治疗无效的重度弥漫性创伤性脑损伤和颅内高压成人患者随机分配至接受双额颞顶去骨瓣减压术或标准治疗。最初的主要结局是不良结局（死亡、植物人状态或重度残疾的复合结局），根据损伤后6个月扩展的格拉斯哥结局量表进行评价。最终主要结局为6个月时扩展的格拉斯哥结局量表评分。 结果：与标准治疗组相比，颅骨切除术组患者的颅内压高于治疗阈值的时间更短(P < 0.001)，颅内压升高的干预措施更少（所有比较P < 0.02），在重症监护室(ICU)的天数更少(P < 0.001)。然而，接受颅骨切除术的患者的扩展格拉斯哥结局量表评分比接受标准治疗的患者差（颅骨切除术组评分较差的比值比为1.84；95%置信区间[CI]，1.05至3.24；P = 0.03），不利结局的风险更大（比值比为2.21；95%CI，1.14至4.26；P=0.02).6个月时颅骨切除术组(19%)和标准治疗组(18%)的死亡率相似。 结论：在患有重度弥漫性创伤性脑损伤和难治性颅内高压的成人中，早期双额颞顶去骨瓣减压术降低了颅内压和ICU住院时间，但与更不利的结局相关。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Length of Stay; Adult; Intracranial Pressure; Young Adult; Adolescent; Glasgow Outcome Scale; Logistic Models; *Decompressive Craniectomy; Brain Injuries/complications/physiopathology/*surgery/therapy; Intracranial Hypertension/etiology/surgery; Standard of Care

Time for a culture change? - Platt, Richard (The New England journal of medicine, 2011)
培养更换时间？
Keywords: Humans; Intensive Care Units; *Methicillin-Resistant Staphylococcus aureus; Infection Control/*methods; Cross Infection/*prevention & control/transmission; Disease Transmission, Infectious/*prevention & control; Staphylococcal Infections/*prevention & control/transmission

Veterans Affairs initiative to prevent methicillin-resistant Staphylococcus aureus infections - Jain, Rajiv; Kralovic, Stephen M.; Evans, Martin E.; Ambrose, Meredith; Simbartl, Loretta A.; Obrosky, D. Scott; Render, Marta L.; Freyberg, Ron W.; Jernigan, John A.; Muder, Robert R.; Miller, LaToya J.; Roselle, Gary A. (The New England journal of medicine, 2011)
BACKGROUND: Health care-associated infections with methicillin-resistant Staphylococcus aureus (MRSA) have been an increasing concern in Veterans Affairs (VA) hospitals. METHODS: A "MRSA bundle" was implemented in 2007 in acute care VA hospitals nationwide in an effort to decrease health care-associated infections with MRSA. The bundle consisted of universal nasal surveillance for MRSA, contact precautions for patients colonized or infected with MRSA, hand hygiene, and a change in the institutional culture whereby infection control would become the responsibility of everyone who had contact with patients. Each month, personnel at each facility entered into a central database aggregate data on adherence to surveillance practice, the prevalence of MRSA colonization or infection, and health care-associated transmissions of and infections with MRSA. We assessed the effect of the MRSA bundle on health care-associated MRSA infections. RESULTS: From October 2007, when the bundle was fully implemented, through June 2010, there were 1,934,598 admissions to or transfers or discharges from intensive care units (ICUs) and non-ICUs (ICUs, 365,139; non-ICUs, 1,569,459) and 8,318,675 patient-days (ICUs, 1,312,840; and non-ICUs, 7,005,835). During this period, the percentage of patients who were screened at admission increased from 82% to 96%, and the percentage who were screened at transfer or discharge increased from 72% to 93%. The mean (Â±SD) prevalence of MRSA colonization or infection at the time of hospital admission was 13.6Â±3.7%. The rates of health care-associated MRSA infections in ICUs had not changed in the 2 years before October 2007 (P=0.50 for trend) but declined with implementation of the bundle, from 1.64 infections per 1000 patient-days in October 2007 to 0.62 per 1000 patient-days in June 2010, a decrease of 62% (P<0.001 for trend). During this same period, the rates of health care-associated MRSA infections in non-ICUs fell from 0.47 per 1000 patient-days to 0.26 per 1000 patient-days, a decrease of 45% (P<0.001 for trend). CONCLUSIONS: A program of universal surveillance, contact precautions, hand hygiene, and institutional culture change was associated with a decrease in health care-associated transmissions of and infections with MRSA in a large health care system.
退伍军人事务倡议预防耐甲氧西林金黄色葡萄球菌感染 背景：在退伍军人事务部(VA)医院，医疗保健相关的耐甲氧西林金黄色葡萄球菌(MRSA)感染日益受到关注。 方法：2007年在全国范围内的急救VA医院实施“MRSA束”，努力减少医疗相关MRSA感染。该组合包括对MRSA的普遍鼻监测、MRSA定植或感染患者的接触注意事项、手卫生和机构培养的变化，借此控制感染将成为接触患者的每个人的责任。每个月，每个机构的工作人员将遵守监测实践、MRSA定植或感染率、卫生保健相关MRSA传播和感染的汇总数据输入中心数据库。我们评估了MRSA束对卫生保健相关MRSA感染的影响。 结果：从2007年10月起，当该组合完全实施时，到2010年6月，有1,934,598例入住重症监护室(ICU)或转出或离开重症监护室(ICU)和非ICU（ICU，365,139；非ICU，1,569,459），以及8,318,675患者-天（ICU，1,312,840；非ICU，7,005,835）。在此期间，入院时接受筛选的患者百分比从82%增至96%，转院或出院时接受筛选的患者百分比从72%增至93%。入院时MRSA定植或感染的平均(Δ±SD)发生率是13.6Δ±3.7%。在2007年10月之前的2年中，ICU中卫生保健相关MRSA感染率没有变化（趋势P = 0.50），但是随着集束化的实施而下降，从2007年10月的1.64例感染/1000患者-天下降至2010年6月的0.62例/1000患者-天，下降了62%（趋势P < 0.001）。在同一时期，非ICU中医疗护理相关MRSA感染率从每1000患者日0.47下降。降至0.26/1000患者-天，下降45%（趋势P < 0.001）。 结论：在一个大型卫生保健系统中，普遍监测、接触预防措施、手卫生和机构培养变化项目与卫生保健相关MRSA传播和感染减少相关。
Keywords: Humans; United States; *Intensive Care Units; *Methicillin-Resistant Staphylococcus aureus; Infection Control/*methods; Professional Role; Cross Infection/*prevention & control/transmission; Disease Transmission, Infectious/*prevention & control; Hand Disinfection; Hospitals, Veterans/organization & administration; Organizational Culture; Staphylococcal Infections/microbiology/*prevention & control/transmission; Universal Precautions

Intervention to reduce transmission of resistant bacteria in intensive care - Huskins, W. Charles; Huckabee, Charmaine M.; O'Grady, Naomi P.; Murray, Patrick; Kopetskie, Heather; Zimmer, Louise; Walker, Mary Ellen; Sinkowitz-Cochran, Ronda L.; Jernigan, John A.; Samore, Matthew; Wallace, Dennis; Goldmann, Donald A. (The New England journal of medicine, 2011)
BACKGROUND: Intensive care units (ICUs) are high-risk settings for the transmission of methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococcus (VRE). METHODS: In a cluster-randomized trial, we evaluated the effect of surveillance for MRSA and VRE colonization and of the expanded use of barrier precautions (intervention) as compared with existing practice (control) on the incidence of MRSA or VRE colonization or infection in adult ICUs. Surveillance cultures were obtained from patients in all participating ICUs; the results were reported only to ICUs assigned to the intervention. In intervention ICUs, patients who were colonized or infected with MRSA or VRE were assigned to care with contact precautions; all the other patients were assigned to care with universal gloving until their discharge or until surveillance cultures obtained at admission were reported to be negative. RESULTS: During a 6-month intervention period, there were 5434 admissions to 10 intervention ICUs, and 3705 admissions to 8 control ICUs. Patients who were colonized or infected with MRSA or VRE were assigned to barrier precautions more frequently in intervention ICUs than in control ICUs (a median of 92% of ICU days with either contact precautions or universal gloving [51% with contact precautions and 43% with universal gloving] in intervention ICUs vs. a median of 38% of ICU days with contact precautions in control ICUs, P<0.001). In intervention ICUs, health care providers used clean gloves, gowns, and hand hygiene less frequently than required for contacts with patients assigned to barrier precautions; when contact precautions were specified, gloves were used for a median of 82% of contacts, gowns for 77% of contacts, and hand hygiene after 69% of contacts, and when universal gloving was specified, gloves were used for a median of 72% of contacts and hand hygiene after 62% of contacts. The mean (±SE) ICU-level incidence of events of colonization or infection with MRSA or VRE per 1000 patient-days at risk, adjusted for baseline incidence, did not differ significantly between the intervention and control ICUs (40.4±3.3 and 35.6±3.7 in the two groups, respectively; P=0.35). CONCLUSIONS: The intervention was not effective in reducing the transmission of MRSA or VRE, although the use of barrier precautions by providers was less than what was required.
减少重症监护中耐药菌传播的干预措施 背景：重症监护病房(ICU)是传播耐甲氧西林金黄色葡萄球菌(MRSA)和耐万古霉素肠球菌(VRE)的高危环境。 方法：在一项集群随机试验中，我们评价了MRSA和VRE定植的监测和扩大使用屏障预防措施（干预）与现有实践（对照）相比对成人ICU中MRSA或VRE定植或感染发生率的影响。从所有参与ICU的患者中获取监测培养物；结果仅报告给分配至干预的ICU。在介入ICU中，MRSA或VRE定植或感染的患者被分配到采取接触预防措施的护理组；所有其他患者被分配到普遍戴手套护理组，直到他们出院或直到入院时的监测培养报告为阴性。 结果：在6个月的干预期间，10间介入ICU共5434例入院，8间对照ICU共3705例入院。与对照ICU相比，MRSA或VRE定植或感染的患者在介入ICU更常被分配到屏障预防措施组（92%的ICU日中位时间使用了接触预防措施或通用手套[51%使用了接触预防措施，43%使用了通用手套]），而干预ICU的中位数为在对照ICU中，38%的ICU时间有接触注意事项，P < 0.001）。在干预ICU中，医护人员使用清洁手套、隔离衣和手卫生的频率低于与分配至屏障预防措施的患者接触所需的频率；当规定了接触预防措施时，82%的接触者使用了手套，77%的接触者使用了隔离衣，69%的接触者使用了手卫生，当规定使用通用手套时，72%的接触者使用手套，62%的接触者使用手套后保持手卫生。经基线发生率校正后，每1000个风险患者日MRSA或VRE定植或感染事件的平均ICU水平发生率(ΔΔSE)在干预和对照ICU之间无显著差异（两组分别为40.4 μm±3.3和35.6 μm±3.7；P = 0.35）。 结论：干预措施不能有效减少MRSA或VRE的传播，虽然提供者使用屏障预防措施的数量低于要求。
Keywords: Humans; Anti-Bacterial Agents/therapeutic use; *Intensive Care Units; *Vancomycin Resistance; *Methicillin-Resistant Staphylococcus aureus; Colony Count, Microbial; Patient Isolation; Infection Control/*methods; Disease Transmission, Infectious/*prevention & control; Hand Disinfection; Cross Infection/prevention & control/*transmission; Enterococcus/drug effects; Gloves, Protective/statistics & numerical data; Gram-Positive Bacterial Infections/microbiology/prevention & control/*transmission; Staphylococcal Infections/microbiology/prevention & control/transmission; Surgical Attire/statistics & numerical data

Propranolol for intractable diffuse lymphangiomatosis - Ozeki, Michio; Fukao, Toshiyuki; Kondo, Naomi (The New England journal of medicine, 2011)
普萘洛尔治疗难治性弥漫性淋巴管瘤病
Keywords: Humans; Male; Adolescent; Radiography; Lung/diagnostic imaging/pathology; Chylothorax; Lung Neoplasms/congenital/drug therapy; Lymphangioma/congenital/*drug therapy; Propranolol/*therapeutic use; Vascular Endothelial Growth Factor A/*antagonists & inhibitors/blood

The burden of functional recovery from ARDS - Hall, Jesse B.; Kress, John P. (The New England journal of medicine, 2011)
ARDS功能恢复的负担
Keywords: Humans; Quality of Life; Survivors; *Recovery of Function; *Respiratory Distress Syndrome/complications/physiopathology/rehabilitation; Lung/physiology; Work

Functional disability 5 years after acute respiratory distress syndrome - Herridge, Margaret S.; Tansey, Catherine M.; MattÃ©, Andrea; Tomlinson, George; Diaz-Granados, Natalia; Cooper, Andrew; Guest, Cameron B.; Mazer, C. David; Mehta, Sangeeta; Stewart, Thomas E.; Kudlow, Paul; Cook, Deborah; et al. (The New England journal of medicine, 2011)
BACKGROUND: There have been few detailed, in-person interviews and examinations to obtain follow-up data on 5-year outcomes among survivors of the acute respiratory distress syndrome (ARDS). METHODS: We evaluated 109 survivors of ARDS at 3, 6, and 12 months and at 2, 3, 4, and 5 years after discharge from the intensive care unit. At each visit, patients were interviewed and examined; underwent pulmonary-function tests, the 6-minute walk test, resting and exercise oximetry, chest imaging, and a quality-of-life evaluation; and reported their use of health care services. RESULTS: At 5 years, the median 6-minute walk distance was 436 m (76% of predicted distance) and the Physical Component Score on the Medical Outcomes Study 36-Item Short-Form Health Survey was 41 (mean norm score matched for age and sex, 50). With respect to this score, younger patients had a greater rate of recovery than older patients, but neither group returned to normal predicted levels of physical function at 5 years. Pulmonary function was normal to near-normal. A constellation of other physical and psychological problems developed or persisted in patients and family caregivers for up to 5 years. Patients with more coexisting illnesses incurred greater 5-year costs. CONCLUSIONS: Exercise limitation, physical and psychological sequelae, decreased physical quality of life, and increased costs and use of health care services are important legacies of severe lung injury.
急性呼吸窘迫综合征后5年功能障碍 背景：在急性呼吸窘迫综合征(ARDS)生存者中，很少有详细的当面访谈和检查来获取有关5年结局的随访数据。 方法：我们评价了109例ARDS存活者在离开重症监护室后第3、6和12个月以及第2、3、4和5年时的情况。每次访视时，对患者进行访谈和检查；进行肺功能检查、6 min步行试验、静息和运动血氧测定、胸部影像学检查和生活质量评价；并报告其对医疗保健服务的使用情况。 结果：5年时，中位6 min步行距离为436 m（预测距离的76%），医学结局研究36项健康调查简表的身体健康评分为41（年龄和性别匹配的平均标准评分，50）。就该评分而言，年轻患者的恢复率高于老年患者，但在5年时两组均未恢复至正常预测的身体功能水平。肺功能正常至接近正常。在长达5年的时间内，患者和家庭护理人员出现或持续存在的一系列其他身体和心理问题。有更多并存疾病的患者5年费用更高。 结论：运动限制、生理和心理后遗症、身体生活质量下降以及医疗费用和医疗服务使用增加是重度肺损伤的重要后遗症。
Keywords: Humans; Female; Male; Middle Aged; Adult; Follow-Up Studies; Activities of Daily Living; Kaplan-Meier Estimate; Exercise Test; Recovery of Function; *Quality of Life; *Disabled Persons; Respiratory Function Tests; Survivors/psychology; Walking; Lung/physiology; Work; Health Services/statistics & numerical data; Respiratory Distress Syndrome/*complications/physiopathology/psychology

Dalteparin versus unfractionated heparin in critically ill patients - Cook, Deborah; Meade, Maureen; Guyatt, Gordon; Walter, Stephen; Heels-Ansdell, Diane; Warkentin, Theodore E.; Zytaruk, Nicole; Crowther, Mark; Geerts, William; Cooper, D. Jamie; Vallance, Shirley; Qushmaq, Ismael; et al. (The New England journal of medicine, 2011)
BACKGROUND: The effects of thromboprophylaxis with low-molecular-weight heparin, as compared with unfractionated heparin, on venous thromboembolism, bleeding, and other outcomes are uncertain in critically ill patients. METHODS: In this multicenter trial, we tested the superiority of dalteparin over unfractionated heparin by randomly assigning 3764 patients to receive either subcutaneous dalteparin (at a dose of 5000 IU once daily) plus placebo once daily (for parallel-group twice-daily injections) or unfractionated heparin (at a dose of 5000 IU twice daily) while they were in the intensive care unit. The primary outcome, proximal leg deep-vein thrombosis, was diagnosed on compression ultrasonography performed within 2 days after admission, twice weekly, and as clinically indicated. Additional testing for venous thromboembolism was performed as clinically indicated. Data were analyzed according to the intention-to-treat principle. RESULTS: There was no significant between-group difference in the rate of proximal leg deep-vein thrombosis, which occurred in 96 of 1873 patients (5.1%) receiving dalteparin versus 109 of 1873 patients (5.8%) receiving unfractionated heparin (hazard ratio in the dalteparin group, 0.92; 95% confidence interval [CI], 0.68 to 1.23; P=0.57). The proportion of patients with pulmonary emboli was significantly lower with dalteparin (24 patients, 1.3%) than with unfractionated heparin (43 patients, 2.3%) (hazard ratio, 0.51; 95% CI, 0.30 to 0.88; P=0.01). There was no significant between-group difference in the rates of major bleeding (hazard ratio, 1.00; 95% CI, 0.75 to 1.34; P=0.98) or death in the hospital (hazard ratio, 0.92; 95% CI, 0.80 to 1.05; P=0.21). In prespecified per-protocol analyses, the results were similar to those of the main analyses, but fewer patients receiving dalteparin had heparin-induced thrombocytopenia (hazard ratio, 0.27; 95% CI, 0.08 to 0.98; P=0.046). CONCLUSIONS: Among critically ill patients, dalteparin was not superior to unfractionated heparin in decreasing the incidence of proximal deep-vein thrombosis.
重症患者中达肝素与普通肝素的比较 背景：在重症患者中，与普通肝素相比，低分子量肝素血栓预防对静脉血栓栓塞、出血和其他结局的影响尚不确定。 方法：在本项多中心试验中，我们通过随机分配3764例患者接受皮下注射达肝素（剂量为5000 IU每日一次）加安慰剂每日一次（平行组每日两次注射）或普通肝素（剂量为5000 IU每日两次），同时他们处于强化%肝素治疗期，检验了达肝素相对于普通肝素的优效性。__%监护病房。主要结局为近端腿深静脉血栓形成，根据入院后2天内的加压超声检查诊断，每周两次，根据临床指征诊断。根据临床指征进行额外的静脉血栓栓塞试验。根据意向治疗原则分析数据。 结果：近端腿深静脉血栓形成的发生率无显著的组间差异，1873例接受达肝素的患者中有96例(5.1%)发生，而1873例接受普通肝素的患者中有109例(5.8%)发生（达肝素组的风险比为0.92；95%置信区间[CI]，0.68-1.23；P = 0.57）。达肝素组发生肺栓塞的患者比例（24例患者，1.3%）显著低于普通肝素组（43例患者，2.3%）（风险比，0.51；95%CI，0.30至0.88；P = 0.01）。大出血（风险比，1.00；95%CI，0.75-1.34；P = 0.98）或住院期间死亡（风险比，0.92；95%CI，0.80-1.05；P = 0.21）的发生率无显著的组间差异。在预先规定的符合方案分析中，结果与主要分析相似，但接受达肝素的患者发生肝素诱导性血小板减少症的患者较少（风险比，0.27；95%CI，0.08至0.98；P = 0.046）。 结论：重症患者中，在降低近端深静脉血栓形成发生率方面，达肝素并不优于普通肝素。
Keywords: Humans; Female; Male; Middle Aged; Kaplan-Meier Estimate; Incidence; Hemorrhage/chemically induced; Critical Illness/mortality/*therapy; Thrombocytopenia/chemically induced; Anticoagulants/adverse effects/*therapeutic use; Heparin/adverse effects/*therapeutic use; Venous Thrombosis/epidemiology/*prevention & control; Injections, Subcutaneous; Dalteparin/adverse effects/*therapeutic use; Pulmonary Embolism/epidemiology/prevention & control; Thromboembolism/prevention & control

Case records of the Massachusetts General Hospital. Case 9-2011. A 37-year-old man with flushing and hypotension. - Murali, Mandakolathur R.; Castells, Mariana C.; Song, James Y.; Dudzinski, David M.; Hasserjian, Robert P. (2011)
麻省总医院的病例记录。病例9-2011。1例37岁男性，伴有潮红和低血压。
Keywords: Humans; Male; Adult; Diagnosis, Differential; Echocardiography; Electrocardiography; Radiography; Hypotension/etiology; Anaphylaxis/diagnosis; Bone Marrow/*pathology; Endocrine Gland Neoplasms/diagnosis; Flushing/etiology; Mastocytosis, Systemic/complications/diagnosis/*pathology; Ribs/diagnostic imaging/pathology; Thoracic Vertebrae/diagnostic imaging/pathology

Case records of the Massachusetts General Hospital: Case 7-2011: a 52-year-old man with upper respiratory symptoms and low oxygen saturation levels - Pallais, J. Carl; Mackool, Bonnie T.; Pitman, Martha Bishop (The New England journal of medicine, 2011)
麻省总医院病例记录：病例7-2011：一名有上呼吸道症状和低氧饱和度水平的52岁男性
Keywords: Humans; Male; Middle Aged; Oximetry; Diagnosis, Differential; Oxygen/*blood; Cough/etiology; Hemolysis; Skin/*pathology; Celiac Disease/complications/*pathology; Dapsone/*adverse effects/therapeutic use; Dermatitis Herpetiformis/drug therapy/*etiology/pathology; Diabetes Mellitus, Type 1/*complications; Duodenum/*pathology; Glycated Hemoglobin A/analysis; Methemoglobinemia/blood/chemically induced/*diagnosis

Clinical practice. Deep-vein thrombosis of the upper extremities. - Kucher, Nils (The New England journal of medicine, 2011)
临床实践。上肢深静脉血栓形成。
Keywords: Humans; Female; Middle Aged; Catheterization, Central Venous; Risk Factors; Ultrasonography; Thrombolytic Therapy; Practice Guidelines as Topic; *Venous Thrombosis/diagnostic imaging/drug therapy/surgery; Anticoagulants/*therapeutic use; Catheters, Indwelling/*adverse effects; Phlebography; Pulmonary Embolism/prevention & control; Upper Extremity/*blood supply

Images in clinical medicine. Malignant pericardial effusion. - Xiong, Wei; Shi, Chanjuan (2011)
临床医学图像。恶性心包积液。
Keywords: Humans; Male; Middle Aged; Tomography, X-Ray Computed; Echocardiography; Carcinoma, Non-Small-Cell Lung/complications/diagnostic imaging/pathology; Cardiac Tamponade/diagnostic imaging/etiology; Cardiomegaly/diagnostic imaging/etiology; Lung Neoplasms/complications/diagnostic imaging/pathology; Pericardial Effusion/*diagnostic imaging/etiology

Crizotinib in anaplastic large-cell lymphoma - Gambacorti-Passerini, Carlo; Messa, Cristina; Pogliani, Enrico M. (The New England journal of medicine, 2011)
克唑替尼治疗间变性大细胞淋巴瘤
Keywords: Humans; Female; Male; Recurrence; Adult; Young Adult; Anaplastic Lymphoma Kinase; Crizotinib; Lymphoma, Large-Cell, Anaplastic/*drug therapy; Protein Kinase Inhibitors/adverse effects/*therapeutic use; Protein-Tyrosine Kinases/*antagonists & inhibitors; Pyrazoles/adverse effects/*therapeutic use; Pyridines/adverse effects/*therapeutic use; Receptor Protein-Tyrosine Kinases; Salvage Therapy

Case records of the Massachusetts General Hospital. Case 6-2011. A 77-year-old man with dyspnea, weakness, and diaphoresis. - Tsibris, Athe M. N.; Shepard, Jo-Anne O.; Zukerberg, Lawrence R. (The New England journal of medicine, 2011)
麻省总医院的病例记录。病例6-2011。1例77岁男性患者，伴有呼吸困难、无力和出汗。
Keywords: Humans; Male; Aged; Diagnosis, Differential; Fatal Outcome; Dyspnea/etiology; Pneumonia, Bacterial/diagnosis; Anaplasma phagocytophilum/*isolation & purification; Anaplasmosis/blood/complications/*diagnosis; Asthenia/etiology; Cardiomyopathies/complications; Infections/diagnosis; Neutrophils/microbiology; Sweating

Point-of-care ultrasonography - Moore, Christopher L.; Copel, Joshua A. (The New England journal of medicine, 2011)
床旁超声检查
Keywords: Humans; History, 21st Century; Mass Screening; History, 20th Century; Lung/diagnostic imaging; *Point-of-Care Systems; Pneumothorax/diagnostic imaging; Aortic Aneurysm, Abdominal/diagnostic imaging; Ultrasonography/history/*methods

Videos in clinical medicine. Intraosseous catheter placement in children. - Nagler, Joshua; Krauss, Baruch (2011)
临床医学视频。儿童骨内导管置入。
Keywords: Humans; Child; Infant; Life Support Care; Contraindications; Humerus; Infusions, Intraosseous/adverse effects/instrumentation/*methods; Tibia

Images in clinical medicine. Lingual hematoma after thrombolytic therapy. - Vijayan, Sethumadhavan; Chase, Alexander (The New England journal of medicine, 2011)
临床医学图像。溶栓治疗后出现舌血肿。
Keywords: Humans; Female; Aged; Fibrinolytic Agents/*adverse effects; Hematoma/*chemically induced/pathology; Heparin/*adverse effects; Myocardial Infarction/drug therapy; Thrombolytic Therapy/*adverse effects; Tongue Diseases/*chemically induced/pathology; Tongue/pathology

Videos in clinical medicine. Arterial puncture for blood gas analysis. - Dev, Shelly P.; Hillmer, Melinda D.; Ferri, Mauricio (2011)
临床医学视频。动脉穿刺行血气分析。
Keywords: Humans; Contraindications; Radial Artery; *Blood Gas Analysis; Carbon Dioxide/blood; Methemoglobinemia/blood; Punctures/adverse effects/instrumentation/*methods; Respiratory Distress Syndrome/blood

A critic's assessment of our approach to cardiac arrest - Bardy, Gust H. (The New England journal of medicine, 2011)
评论家对我们心脏骤停方法的评估
Keywords: Humans; Time Factors; Survival Rate; Comorbidity; Treatment Failure; *Cardiopulmonary Resuscitation; Emergency Treatment; Heart Arrest/complications/mortality/*therapy; *Defibrillators; Ventricular Fibrillation/epidemiology/*etiology/therapy

Images in clinical medicine: A photosensitive dermatitis in the intensive care unit - Mercieri, Marco; Mercieri, Angelo (The New England journal of medicine, 2011)
临床医学图像：重症监护室中的光敏性皮炎
Keywords: Humans; Male; Aged, 80 and over; Fatal Outcome; Skin/pathology; Niacin/blood; Pellagra/complications/*pathology; Photosensitivity Disorders/complications/*pathology; Pneumonia/etiology; Pulmonary Disease, Chronic Obstructive/complications

Ventricular tachyarrhythmias after cardiac arrest in public versus at home - Weisfeldt, Myron L.; Everson-Stewart, Siobhan; Sitlani, Colleen; Rea, Thomas; Aufderheide, Tom P.; Atkins, Dianne L.; Bigham, Blair; Brooks, Steven C.; Foerster, Christopher; Gray, Randal; Ornato, Joseph P.; Powell, Judy; et al. (The New England journal of medicine, 2011)
BACKGROUND: The incidence of ventricular fibrillation or pulseless ventricular tachycardia as the first recorded rhythm after out-of-hospital cardiac arrest has unexpectedly declined. The success of bystander-deployed automated external defibrillators (AEDs) in public settings suggests that this may be the more common initial rhythm when out-of-hospital cardiac arrest occurs in public. We conducted a study to determine whether the location of the arrest, the type of arrhythmia, and the probability of survival are associated. METHODS: Between 2005 and 2007, we conducted a prospective cohort study of out-of-hospital cardiac arrest in adults in 10 North American communities. We assessed the frequencies of ventricular fibrillation or pulseless ventricular tachycardia and of survival to hospital discharge for arrests at home as compared with arrests in public. RESULTS: Of 12,930 evaluated out-of-hospital cardiac arrests, 2042 occurred in public and 9564 at home. For cardiac arrests at home, the incidence of ventricular fibrillation or pulseless ventricular tachycardia was 25% when the arrest was witnessed by emergency-medical-services (EMS) personnel, 35% when it was witnessed by a bystander, and 36% when a bystander applied an AED. For cardiac arrests in public, the corresponding rates were 38%, 60%, and 79%. The adjusted odds ratio for initial ventricular fibrillation or pulseless ventricular tachycardia in public versus at home was 2.28 (95% confidence interval [CI], 1.96 to 2.66; P < 0.001) for bystander-witnessed arrests and 4.48 (95% CI, 2.23 to 8.97; P<0.001) for arrests in which bystanders applied AEDs. The rate of survival to hospital discharge was 34% for arrests in public settings with AEDs applied by bystanders versus 12% for arrests at home (adjusted odds ratio, 2.49; 95% CI, 1.03 to 5.99; P = 0.04). CONCLUSIONS: Regardless of whether out-of-hospital cardiac arrests are witnessed by EMS personnel or bystanders and whether AEDs are applied by bystanders, the proportion of arrests with initial ventricular fibrillation or pulseless ventricular tachycardia is much greater in public settings than at home. The incremental value of resuscitation strategies, such as the ready availability of an AED, may be related to the place where the arrest occurs.
心脏骤停后的室性快速性心律失常：公开与在家比较 背景：院外心脏骤停后首次记录到节律的室颤或无脉性室性心动过速的发生率意外下降。旁观者自动体外除颤器(AED)在公共环境中的成功表明，这可能是院外心脏骤停在公共环境中发生时更常见的初始节律。我们进行了一项研究，以确定心脏骤停位置、心律失常类型和存活概率是否相关。 方法：2005年至2007年间，我们对10个北美社区的成人院外心脏骤停进行了前瞻性队列研究。我们评估了室颤或无脉性室性心动过速的频率以及在家中停搏与在公共场合停搏的存活至出院的频率。 结果：在12,930例评估的院外心脏骤停中，2042例发生在公众场所，9564例发生在家中。对于家中的心脏骤停，在急救医疗服务(EMS)人员见证下发生心室颤动或无脉性室性心动过速的发生率为25%，在旁观者见证下发生心室颤动或无脉性室性心动过速的发生率为35%，在旁观者应用AED时发生心室颤动或无脉性室性心动过速的发生率为36%。对于公众中的心脏骤停，相应的比率分别为38%、60%和79%。在公众与家中，旁观者见证的心跳骤停与旁观者应用AED的心跳骤停的初始心室颤动或无脉性室性心动过速的校正比值比分别为2.28（95%置信区间[CI]，1.96至2.66；P < 0.001）和4.48（95%CI，2.23至8.97；P < 0.001）。在公众环境中，旁观者使用AED的患者的出院生存率为34%，而在家患者的出院生存率为12%（校正比值比为2.49；95%CI，1.03至5.99；P = 0.04）。 结论：无论院外心脏骤停是否由EMS人员或旁观者目击，以及AED是否由旁观者应用，在公共环境中初始发生心室颤动或无脉性室性心动过速的骤停比例远大于家庭。复苏策略的增量价值，如AED的随时可用，可能与心脏骤停发生的部位有关。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Time Factors; Aged; Survival Rate; Age Factors; Incidence; Comorbidity; Cardiopulmonary Resuscitation; Hospitalization; Logistic Models; Emergency Treatment; *Defibrillators; Heart Arrest/*complications/mortality/therapy; Tachycardia, Ventricular/epidemiology/*etiology; Ventricular Fibrillation/epidemiology/*etiology; Volunteers

Case records of the Massachusetts General Hospital. Case 2-2011. A 30-year-old woman with shock after treatment of a furuncle. - Moellering, Robert C. Jr; Abbott, Gerald F.; Ferraro, Mary Jane (The New England journal of medicine, 2011)
麻省总医院的病例记录。病例2-2011。1例30岁女性，因疖治疗后休克。
Keywords: Humans; Female; Adult; Brain/diagnostic imaging; Fatal Outcome; Shock/etiology; Radiography, Thoracic; Chest Pain/etiology; Community-Acquired Infections/diagnosis; Furunculosis/microbiology/therapy; Methicillin-Resistant Staphylococcus aureus/*isolation & purification; Sepsis/complications/*diagnosis/microbiology; Staphylococcal Infections/complications/*diagnosis/microbiology

Case records of the Massachusetts General Hospital. Case 40-2010. A 68-year-old woman with chest pain during an airplane flight. - Picard, Michael H.; Rosenfield, Kenneth; Digumarthy, Subba; Smith, R. Neal (2010)
麻省总医院的病例记录。病例40-2010。一名68岁女性在乘坐飞机时出现胸痛。
Keywords: Humans; Female; Aged; Recurrence; Diagnosis, Differential; Stents; Myocardium/*pathology; Echocardiography; Electrocardiography; Radiography; Fatal Outcome; Heart/diagnostic imaging; Myocardial Infarction/complications/*diagnosis/therapy; Hypertension/complications; Shock, Cardiogenic/etiology; Chest Pain/etiology; *Aerospace Medicine; Angioplasty, Balloon, Coronary; Cardiac Tamponade/diagnosis; Heart Rupture, Post-Infarction/*pathology; Ventricular Outflow Obstruction/diagnosis

Clinical practice. Glycemic control in the ICU. - Kavanagh, Brian P.; McCowen, Karen C. (The New England journal of medicine, 2010)
临床实践。ICU的血糖控制。
Keywords: Humans; Male; Adult; Blood Glucose/metabolism; Critical Illness/*therapy; *Nutritional Support; *Intensive Care Units; Practice Guidelines as Topic; Acute Disease; Monitoring, Physiologic/methods; Hypoglycemic Agents/*therapeutic use; Insulin/*therapeutic use; Hyperglycemia/diagnosis/etiology/*therapy; Hypoglycemia/diagnosis

Images in clinical medicine. Flail chest. - Alexander, Philip (2010)
临床医学图像。连枷胸。
Keywords: Humans; Male; Young Adult; Motion; Flail Chest/pathology/*physiopathology; Rib Fractures/physiopathology

Images in clinical medicine. Neonatal pneumomediastinum and the spinnaker-sail sign. - Correia-Pinto, Jorge; Henriques-Coelho, Tiago (The New England journal of medicine, 2010)
临床医学图像。新生儿纵隔气肿和“旋帆征”。
Keywords: Humans; Male; Infant, Newborn; Radiography, Thoracic; Diaphragm/*diagnostic imaging; Mediastinal Emphysema/*diagnostic imaging; Mediastinum/diagnostic imaging; Thymus Gland/*diagnostic imaging

Up in the air--suspending ethical medical practice - Shaner, D. Malcolm (The New England journal of medicine, 2010)
暂停伦理医学实践
Keywords: Humans; *Ethics, Institutional; Heart Arrest/therapy; *Ethics, Medical; Aerospace Medicine/ethics; Aviation/*ethics; Cardiopulmonary Resuscitation/*ethics; Medical Futility/*ethics

Images in clinical medicine. The jaw-thrust maneuver. - Albrecht, Eric; Schoettker, Patrick (2010)
临床医学图像。下颌前移。
Keywords: Humans; Respiration, Artificial/*methods; Jaw

Acoustic findings in a patient with radiation pneumonitis - Murphy, Raymond; Vyshedskiy, Andrey (2010)
放射性肺炎患者的声学结果
Keywords: Humans; Female; Aged; Radiography; *Respiratory Sounds; Acoustics; Radiation Pneumonitis/diagnostic imaging/*physiopathology

Off-label use of recombinant activated factor VII--safe or not safe? - Aledort, Louis M (The New England journal of medicine, 2010)
超说明书使用重组活化因子VII——安全或不安全？
Keywords: Humans; *Off-Label Use; Factor VIIa/*adverse effects/therapeutic use; Hemorrhage/*drug therapy; Hemostatics/*adverse effects/therapeutic use; Thromboembolism/chemically induced; Thrombosis/*chemically induced

Safety of recombinant activated factor VII in randomized clinical trials - Levi, Marcel; Levy, Jerrold H.; Andersen, Henning Friis; Truloff, David (The New England journal of medicine, 2010)
BACKGROUND: The use of recombinant activated factor VII (rFVIIa) on an off-label basis to treat life-threatening bleeding has been associated with a perceived increased risk of thromboembolic complications. However, data from placebo-controlled trials are needed to properly assess the thromboembolic risk. To address this issue, we evaluated the rate of thromboembolic events in all published randomized, placebo-controlled trials of rFVIIa used on an off-label basis. METHODS: We analyzed data from 35 randomized clinical trials (26 studies involving patients and 9 studies involving healthy volunteers) to determine the frequency of thromboembolic events. The data were pooled with the use of random-effects models to calculate the odds ratios and 95% confidence intervals. RESULTS: Among 4468 subjects (4119 patients and 349 healthy volunteers), 401 [corrected] had thromboembolic events (9.0%). [corrected] Rates of arterial thromboembolic events among all 4468 subjects were higher among those who received rFVIIa than among those who received placebo (5.5% vs. 3.2%, P=0.003). Rates of venous thromboembolic events were similar among subjects who received rFVIIa and those who received placebo (5.3% vs. 5.7%). Among subjects who received rFVIIa, 2.9% had coronary arterial thromboembolic events, as compared with 1.1% of those who received placebo (P=0.002). Rates of arterial thromboembolic events were higher among subjects who received rFVIIa than among subjects who received placebo, particularly among those who were 65 years of age or older (9.0% vs. 3.8%, P=0.003); the rates were especially high among subjects 75 years of age or older (10.8% vs. 4.1%, P=0.02). CONCLUSIONS: In a large and comprehensive cohort of persons in placebo-controlled trials of rFVIIa, treatment with high doses of rFVIIa on an off-label basis significantly increased the risk of arterial but not venous thromboembolic events, especially among the elderly.
重组活化因子VII在随机临床试验中的安全性 背景：以标签外方式使用重组活化因子VII(rFVIIa)治疗危及生命的出血与血栓栓塞并发症风险增加相关。然而，需要安慰剂对照试验的数据来正确评估血栓栓塞风险。为了解决这个问题，我们评估了所有已发表的以标签外方式使用rFVIIa的随机、安慰剂对照试验中血栓栓塞事件的发生率。 方法：我们分析了35项随机临床试验（26项研究涉及患者，9项研究涉及健康志愿者）的数据，以确定血栓栓塞事件的频率。使用随机效应模型汇总数据，计算比值比和95%置信区间。 结果：在4468名受试者（4119名患者和349名健康志愿者）中，401名受试者（校正）发生血栓栓塞事件(9.0%)。所有4468名受试者中，接受rFVIIa治疗的受试者的动脉血栓栓塞事件发生率高于接受安慰剂治疗的受试者(5.5%vs. 3.2%，P = 0.003)。接受rFVIIa和安慰剂的受试者静脉血栓栓塞事件的发生率相似（5.3%对比5.7%）。在接受rFVIIa的受试者中，2.9%发生冠状动脉血栓栓塞事件，相比之下，接受安慰剂的受试者中为1.1%(P = 0.002)。接受rFVIIa的受试者动脉血栓栓塞事件的发生率高于接受安慰剂的受试者，尤其是65岁或65岁以上的受试者(9.0%vs. 3.8%，P = 0.003)；75岁或75岁以上的受试者发生率尤其高(10.8%vs. 4.1%，P = 0.02)。 结论：在rFVIIa安慰剂对照试验的一个大型综合队列人群中，标签外使用高剂量rFVIIa治疗显著增加动脉血栓栓塞事件的风险，但未增加静脉血栓栓塞事件的风险，尤其是老年人。
Keywords: Humans; Middle Aged; Aged; Adult; Randomized Controlled Trials as Topic; Logistic Models; Odds Ratio; *Off-Label Use; Factor VIIa/*adverse effects/therapeutic use; Hemostatics/*adverse effects/therapeutic use; Thrombosis/*chemically induced; Hemorrhage/*drug therapy/etiology/prevention & control; Thromboembolism/*chemically induced

Targeted temperature management for comatose survivors of cardiac arrest - Holzer, Michael (The New England journal of medicine, 2010)
心脏骤停昏迷幸存者的目标温度管理
Keywords: Humans; Male; Middle Aged; Prognosis; Practice Guidelines as Topic; Body Temperature; Ringer's Lactate; *Hypothermia, Induced/adverse effects/methods; Advanced Cardiac Life Support; Coma/etiology/*therapy; Heart Arrest/complications/*therapy; Isotonic Solutions/therapeutic use; Ventricular Fibrillation/complications

Neuromuscular blocking agents in ARDS - Slutsky, Arthur S. (The New England journal of medicine, 2010)
ARDS的神经肌肉阻滞剂
Keywords: Humans; Combined Modality Therapy; *Respiration, Artificial/adverse effects; Atracurium/*analogs & derivatives/therapeutic use; Neuromuscular Blocking Agents/pharmacology/*therapeutic use; Oxygen Consumption/drug effects; Respiratory Distress Syndrome/*drug therapy/therapy; Ventilator-Induced Lung Injury/*prevention & control

Neuromuscular blockers in early acute respiratory distress syndrome - Papazian, Laurent; Forel, Jean-Marie; Gacouin, Arnaud; Penot-Ragon, Christine; Perrin, Gilles; Loundou, Anderson; Jaber, Samir; Arnal, Jean-Michel; Perez, Didier; Seghboyan, Jean-Marie; Constantin, Jean-Michel; Courant, Pierre; et al. (The New England journal of medicine, 2010)
BACKGROUND: In patients undergoing mechanical ventilation for the acute respiratory distress syndrome (ARDS), neuromuscular blocking agents may improve oxygenation and decrease ventilator-induced lung injury but may also cause muscle weakness. We evaluated clinical outcomes after 2 days of therapy with neuromuscular blocking agents in patients with early, severe ARDS. METHODS: In this multicenter, double-blind trial, 340 patients presenting to the intensive care unit (ICU) with an onset of severe ARDS within the previous 48 hours were randomly assigned to receive, for 48 hours, either cisatracurium besylate (178 patients) or placebo (162 patients). Severe ARDS was defined as a ratio of the partial pressure of arterial oxygen (PaO2) to the fraction of inspired oxygen (FIO2) of less than 150, with a positive end-expiratory pressure of 5 cm or more of water and a tidal volume of 6 to 8 ml per kilogram of predicted body weight. The primary outcome was the proportion of patients who died either before hospital discharge or within 90 days after study enrollment (i.e., the 90-day in-hospital mortality rate), adjusted for predefined covariates and baseline differences between groups with the use of a Cox model. RESULTS: The hazard ratio for death at 90 days in the cisatracurium group, as compared with the placebo group, was 0.68 (95% confidence interval [CI], 0.48 to 0.98; P=0.04), after adjustment for both the baseline PaO2:FIO2 and plateau pressure and the Simplified Acute Physiology II score. The crude 90-day mortality was 31.6% (95% CI, 25.2 to 38.8) in the cisatracurium group and 40.7% (95% CI, 33.5 to 48.4) in the placebo group (P=0.08). Mortality at 28 days was 23.7% (95% CI, 18.1 to 30.5) with cisatracurium and 33.3% (95% CI, 26.5 to 40.9) with placebo (P=0.05). The rate of ICU-acquired paresis did not differ significantly between the two groups. CONCLUSIONS: In patients with severe ARDS, early administration of a neuromuscular blocking agent improved the adjusted 90-day survival and increased the time off the ventilator without increasing muscle weakness.
神经肌肉阻滞剂治疗早期急性呼吸窘迫综合征 背景：在接受机械通气治疗急性呼吸窘迫综合征(ARDS)的患者中，神经肌肉阻滞剂可能改善氧合和降低呼吸机诱导的肺损伤，但也可能引起肌无力。我们评价了早期重度ARDS患者神经肌肉阻滞剂治疗2天后的临床结局。 方法：在这项多中心、双盲试验中，340例在过去48小时内发生重度ARDS的入住重症监护室(ICU)的患者被随机分配接受48小时的顺苯磺酸阿曲库铵（178例患者）或安慰剂（162例患者）。重度ARDS定义为动脉血氧分压(PaO2)与吸入气中的氧气分数(FIO2)的比值小于150，呼气末正压为5 cm或更多的水，潮气量为6～8 mL/kg预测体重。主要结局是出院前或入组后90天内死亡的患者比例（即90天院内死亡率），使用Cox模型校正预定义的协变量和组间基线差异。 结果：在调整基线PaO2:FIO2和平台压以及简化急性生理学II评分后，顺阿曲库铵组与安慰剂组相比90天时的死亡风险比为0.68（95%置信区间[CI]，0.48-0.98；P = 0.04）。顺阿曲库铵组90天粗死亡率为31.6%(95%CI，25.2-38.8)，安慰剂组为40.7%(95%CI，33.5-48.4)(P = 0.08)。顺阿曲库铵组第28天的死亡率为23.7%（95%CI，18.1至30.5），安慰剂组为33.3%（95%CI，26.5至40.9）(P = 0.05)。两组间ICU获得性轻瘫的发生率无显著差异。 结论：在重度ARDS患者中，早期给予神经肌肉阻滞剂改善了调整后的90天生存率，延长了脱离呼吸机的时间，而未增加肌无力。
Keywords: Humans; Treatment Outcome; Middle Aged; Double-Blind Method; Infusions, Intravenous; Survival Rate; Combined Modality Therapy; Multiple Organ Failure; Proportional Hazards Models; *Respiration, Artificial; Atracurium/adverse effects/*analogs & derivatives/therapeutic use; Neuromuscular Blocking Agents/adverse effects/*therapeutic use; Respiratory Distress Syndrome/*drug therapy/mortality/therapy; Pneumothorax/epidemiology; Ventilator Weaning/methods

The reality of drug shortages--the case of the injectable agent propofol - Jensen, Valerie; Rappaport, Bob A. (The New England journal of medicine, 2010)
药品短缺的现实--注射型异丙酚制剂的实例
Keywords: Humans; United States; Drug Labeling; Injections, Intravenous; United States Food and Drug Administration; Anesthetics, Intravenous/*supply & distribution; Drug Costs; Drug Industry; Economic Competition; Product Recalls and Withdrawals; Propofol/*supply & distribution

Clinical practice. Emergency treatment of asthma. - Lazarus, Stephen C. (The New England journal of medicine, 2010)
临床实践。哮喘的紧急治疗。
Keywords: Humans; Female; Middle Aged; Oxygen Inhalation Therapy; Practice Guidelines as Topic; Administration, Oral; Adrenal Cortex Hormones/therapeutic use; Adrenergic beta-Agonists/therapeutic use; *Emergency Treatment; Administration, Inhalation; Forced Expiratory Volume; Asthma/*drug therapy; Anti-Asthmatic Agents/*therapeutic use; Cholinergic Antagonists/therapeutic use; Status Asthmaticus/physiopathology/prevention & control/*therapy

Sepsis and endothelial permeability - Lee, Warren L.; Slutsky, Arthur S. (The New England journal of medicine, 2010)
败血症和内皮通透性
Keywords: Humans; Animals; Mice; Signal Transduction; Permeability; Antigens, CD/*metabolism; Cadherins/*metabolism; Endothelium, Vascular/*metabolism; Glycoproteins/metabolism; Nerve Tissue Proteins/*metabolism; Receptors, Cell Surface/metabolism; Receptors, Immunologic/*metabolism; Sepsis/*metabolism

In CPR, less may be better - Weisfeldt, Myron L. (The New England journal of medicine, 2010)
在CPR中，越少越好
Keywords: Humans; Survival Rate; Cardiopulmonary Resuscitation/*methods; *Respiration, Artificial; Volunteers; Emergency Medical Service Communication Systems; Heart Arrest/etiology/mortality/*therapy

Images in clinical medicine. Pneumothorax--an uncommon complication of a common procedure. - Nazir, Tahir; Punekar, Shuja (The New England journal of medicine, 2010)
临床医学图像。气胸-一种常见手术的不常见并发症。
Keywords: Humans; Female; Aged, 80 and over; Glasgow Coma Scale; Radiography; Fatal Outcome; Intubation, Gastrointestinal/*adverse effects/instrumentation; Pneumothorax/diagnostic imaging/*etiology; Stroke/complications

Compression-only CPR or standard CPR in out-of-hospital cardiac arrest - Svensson, Leif; Bohm, Katarina; Castrèn, Maaret; Pettersson, Hans; Engerström, Lars; Herlitz, Johan; Rosenqvist, Mårten (The New England journal of medicine, 2010)
BACKGROUND: Emergency medical dispatchers give instructions on how to perform cardiopulmonary resuscitation (CPR) over the telephone to callers requesting help for a patient with suspected cardiac arrest, before the arrival of emergency medical services (EMS) personnel. A previous study indicated that instructions to perform CPR consisting of only chest compression result in a treatment efficacy that is similar or even superior to that associated with instructions given to perform standard CPR, which consists of both compression and ventilation. That study, however, was not powered to assess a possible difference in survival. The aim of this prospective, randomized study was to evaluate the possible superiority of compression-only CPR over standard CPR with respect to survival. METHODS: Patients with suspected, witnessed, out-of-hospital cardiac arrest were randomly assigned to undergo either compression-only CPR or standard CPR. The primary end point was 30-day survival. RESULTS: Data for the primary analysis were collected from February 2005 through January 2009 for a total of 1276 patients. Of these, 620 patients had been assigned to receive compression-only CPR and 656 patients had been assigned to receive standard CPR. The rate of 30-day survival was similar in the two groups: 8.7% (54 of 620 patients) in the group receiving compression-only CPR and 7.0% (46 of 656 patients) in the group receiving standard CPR (absolute difference for compression-only vs. standard CPR, 1.7 percentage points; 95% confidence interval, -1.2 to 4.6; P=0.29). CONCLUSIONS: This prospective, randomized study showed no significant difference with respect to survival at 30 days between instructions given by an emergency medical dispatcher, before the arrival of EMS personnel, for compression-only CPR and instructions for standard CPR in patients with suspected, witnessed, out-of-hospital cardiac arrest.
院外心脏骤停的单纯按压CPR或标准CPR 背景：紧急医疗调度员在紧急医疗服务(EMS)人员到达之前，向请求帮助疑似心脏骤停患者的呼叫者提供如何通过电话进行心肺复苏(CPR)的说明。之前的一项研究表明，指示进行仅包括胸部按压的CPR，可产生类似于或甚至优于由实施标准CPR（包括按压和通气）相关指示的治疗效果。但是，该研究没有把握度评估可能的生存差异。这项前瞻性、随机研究的目的是评价单纯按压CPR与标准CPR相比在生存率方面的可能优效性。 方法：将疑似、有目击者的院外心脏骤停患者随机分配至仅接受按压CPR组或标准CPR组。主要终点为30天生存率。 结果：从2005年2月至2009年1月共收集了1276例患者的主要分析数据。其中，620例患者被分配接受单纯按压CPR，656例患者被分配接受标准CPR。两组的30天生存率相似：仅接受按压CPR组为8.7%（620例患者中的54例），接受标准CPR组为7.0%（656例患者中的46例）（仅接受按压与标准CPR的绝对差异为1.7个百分点；95%置信区间，-1.2至4.6；P = 0.29）。 结论：这项前瞻性、随机研究表明，在EMS人员到达之前，由紧急医疗调度员提供的指导，对于疑似、有目击者的院外心脏骤停患者，仅进行按压CPR和标准CPR的指导之间30天生存率没有显著差异。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Adult; Survival Rate; Logistic Models; Cardiopulmonary Resuscitation/*methods; *Respiration, Artificial; Volunteers; Emergency Medical Service Communication Systems; Chi-Square Distribution; Heart Arrest/mortality/*therapy

CPR with chest compression alone or with rescue breathing - Rea, Thomas D.; Fahrenbruch, Carol; Culley, Linda; Donohoe, Rachael T.; Hambly, Cindy; Innes, Jennifer; Bloomingdale, Megan; Subido, Cleo; Romines, Steven; Eisenberg, Mickey S. (The New England journal of medicine, 2010)
BACKGROUND: The role of rescue breathing in cardiopulmonary resuscitation (CPR) performed by a layperson is uncertain. We hypothesized that the dispatcher instructions to bystanders to provide chest compression alone would result in improved survival as compared with instructions to provide chest compression plus rescue breathing. METHODS: We conducted a multicenter, randomized trial of dispatcher instructions to bystanders for performing CPR. The patients were persons 18 years of age or older with out-of-hospital cardiac arrest for whom dispatchers initiated CPR instruction to bystanders. Patients were randomly assigned to receive chest compression alone or chest compression plus rescue breathing. The primary outcome was survival to hospital discharge. Secondary outcomes included a favorable neurologic outcome at discharge. RESULTS: Of the 1941 patients who met the inclusion criteria, 981 were randomly assigned to receive chest compression alone and 960 to receive chest compression plus rescue breathing. We observed no significant difference between the two groups in the proportion of patients who survived to hospital discharge (12.5% with chest compression alone and 11.0% with chest compression plus rescue breathing, P=0.31) or in the proportion who survived with a favorable neurologic outcome in the two sites that assessed this secondary outcome (14.4% and 11.5%, respectively; P=0.13). Prespecified subgroup analyses showed a trend toward a higher proportion of patients surviving to hospital discharge with chest compression alone as compared with chest compression plus rescue breathing for patients with a cardiac cause of arrest (15.5% vs. 12.3%, P=0.09) and for those with shockable rhythms (31.9% vs. 25.7%, P=0.09). CONCLUSIONS: Dispatcher instruction consisting of chest compression alone did not increase the survival rate overall, although there was a trend toward better outcomes in key clinical subgroups. The results support a strategy for CPR performed by laypersons that emphasizes chest compression and minimizes the role of rescue breathing.
CPR，仅胸部按压或人工呼吸 背景：人工呼吸在外行心肺复苏中的作用尚不确定。我们假设，与提供胸部按压加人工呼吸的指示相比，向旁观者提供单独胸部按压的调度员指示将改善生存率。 方法：我们进行了一项多中心、随机试验，对进行CPR的旁观者进行了调度员指导。患者为18岁或18岁以上，患有院外心脏骤停，调度员对其进行旁观者CPR指导。患者被随机分配接受单纯胸部按压或胸部按压加人工呼吸。主要结局是存活至出院。次要结局包括出院时良好的神经系统结局。 结果：在1941例符合入选标准的患者中，981例被随机分配接受单纯胸部按压，960例接受胸部按压加人工呼吸。我们观察到两组存活至出院的患者比例无显著差异（单独胸部按压组为12.5%，胸部按压加人工呼吸组为11.0%，P = 0.31）或评估该次要结局的两个研究中心中具有有利神经系统结局的存活患者的比例（分别为14.4%和11.5%；P = 0.13）。预先规定的亚组分析显示，对于心脏骤停原因(15.5%vs. 12.3%，P = 0.09)和伴有可电击节律(31.9%vs. 25.7%，P = 0.09)的患者，单独胸部按压组存活至出院的患者比例高于胸部按压加人工呼吸组。 结论：尽管在关键临床亚组中存在更好结局的趋势，但是仅由胸部按压组成的调度员指导并未增加总生存率。结果支持非专业人员实施的CPR策略，强调胸部按压，尽量减少人工呼吸的作用。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Survival Rate; Statistics, Nonparametric; Cardiopulmonary Resuscitation/*methods; *Respiration, Artificial; Volunteers; Emergency Medical Service Communication Systems; Chi-Square Distribution; Heart Arrest/mortality/*therapy

Case records of the Massachusetts General Hospital. Case 21-2010. A request for retrieval of oocytes from a 36-year-old woman with anoxic brain injury. - Greer, David M.; Styer, Aaron K.; Toth, Thomas L.; Kindregan, Charles P.; Romero, Javier M. (The New England journal of medicine, 2010)
麻省总医院的病例记录。病例21-2010。要求从一名36岁缺氧性脑损伤女性中获取卵母细胞。
Keywords: Humans; Female; Prognosis; Adult; Pulmonary Artery/diagnostic imaging; Withholding Treatment; Radiography; Heart Arrest/etiology; *Third-Party Consent; *Hypoxia, Brain/diagnostic imaging/etiology; Cryopreservation/ethics; Ethics Committees, Clinical; Intracranial Hypertension/etiology; Oocyte Retrieval/*ethics; Posthumous Conception/*ethics/psychology; Pulmonary Embolism/complications

Immunotherapy for sepsis--a new approach against an ancient foe - Hotchkiss, Richard S.; Opal, Steven (The New England journal of medicine, 2010)
败血症的免疫治疗--一种对抗古老敌人的新方法
Keywords: Humans; *Immunotherapy; *Immune Tolerance; Antigens, CD/*physiology; Apoptosis/immunology; B7-H1 Antigen; CD4-Positive T-Lymphocytes/physiology; Interleukin-1/therapeutic use; Interleukin-10/biosynthesis; Interleukin-15/therapeutic use; Monocytes/physiology; Sepsis/*immunology/*therapy

Clinical problem-solving. All in the family. - Easter, Joshua S.; Josephson, S. Andrew; Vinton, Deborah T.; Saint, Sanjay; Edlow, Jonathan A. (The New England journal of medicine, 2010)
临床问题解决。全是家人。
Keywords: Humans; Female; Adult; Diagnosis, Differential; Tomography, X-Ray Computed; Echocardiography; Brain/diagnostic imaging; Genetic Testing; Aphasia/etiology; Arteriovenous Malformations/complications/*diagnostic imaging; Embolism, Paradoxical/complications; Paresis/etiology; Pulmonary Artery/*abnormalities/diagnostic imaging; Pulmonary Veins/*abnormalities/diagnostic imaging; Stroke/*etiology; Telangiectasia, Hereditary Hemorrhagic/complications/*diagnosis/genetics

Myxedema coma induced by ingestion of raw bok choy - Chu, Michael; Seltzer, Terry F. (The New England journal of medicine, 2010)
生白菜致粘液性水肿昏迷
Keywords: Humans; Female; Aged, 80 and over; Brassica rapa/*adverse effects/chemistry/enzymology; Coma/*etiology; Cooking; Glucosinolates/*adverse effects/metabolism; Glycoside Hydrolases/metabolism; Hydrolysis; Myxedema/etiology; Thyroid Gland/drug effects

Haiti earthquake relief, phase two--long-term needs and local resources - Bayard, Dominique (The New England journal of medicine, 2010)
海地地震救援，第二阶段--长期需求和当地资源
Keywords: Humans; Female; Male; Haiti; Volunteers; *Disasters; *Earthquakes; *Health Services; Health Services Needs and Demand; Relief Work/*organization & administration

Hospital-acquired infections due to gram-negative bacteria - Peleg, Anton Y.; Hooper, David C. (The New England journal of medicine, 2010)
革兰氏阴性菌导致的医院获得性感染
Keywords: Humans; Risk Factors; Anti-Bacterial Agents/*therapeutic use; Gram-Negative Bacterial Infections/*drug therapy; Bacteremia/drug therapy; Pneumonia, Bacterial/drug therapy; *Drug Resistance, Bacterial/physiology; *Gram-Negative Bacteria/isolation & purification/physiology; Cross Infection/*drug therapy/*microbiology; Urinary Tract Infections/drug therapy

Treatment decisions after brain injury--tensions among quality, preference, and cost - Holloway, Robert G.; Quill, Timothy E. (The New England journal of medicine, 2010)
脑损伤后的治疗决策--质量、偏好和成本之间的紧张关系
Keywords: Humans; Prognosis; Palliative Care; United States; Health Care Costs; *Decision Making; Disclosure; *Professional-Family Relations; Patient Participation; *Withholding Treatment/standards; Brain Injuries/economics/*therapy; Quality of Health Care; Reimbursement, Incentive; Terminal Care/standards/statistics & numerical data; Tracheostomy/standards/*statistics & numerical data

Clinical aspects of pandemic 2009 influenza A (H1N1) virus infection - Bautista, Edgar; Chotpitayasunondh, Tawee; Gao, Zhancheng; Harper, Scott A.; Shaw, Michael; Uyeki, Timothy M.; Zaki, Sherif R.; Hayden, Frederick G.; Hui, David S.; Kettner, Joel D.; Kumar, Anand; Lim, Matthew; et al. (The New England journal of medicine, 2010)
2009年大流行甲型流感(H1N1)病毒感染的临床表现
Keywords: Humans; Risk Factors; Severity of Illness Index; Antiviral Agents/therapeutic use; *Disease Outbreaks; *Influenza A Virus, H1N1 Subtype/isolation & purification/pathogenicity; *Influenza, Human/diagnosis/drug therapy/epidemiology/immunology; Antigens, Viral/analysis; Drug Resistance, Viral; Lung/immunology/pathology; Oseltamivir/therapeutic use; RNA, Viral/analysis

Autologous pancreatic islet transplantation for severe trauma - Jindal, Rahul M.; Ricordi, Camillo; Shriver, Craig D. (The New England journal of medicine, 2010)
自体胰岛移植治疗严重创伤
Keywords: Humans; Male; Young Adult; *Islets of Langerhans Transplantation; Multiple Trauma/surgery; Pancreas/*injuries/surgery

Videos in clinical medicine. Ultrasound-guided internal jugular vein cannulation. - Ortega, Rafael; Song, Michael; Hansen, Christopher J.; Barash, Paul (The New England journal of medicine, 2010)
临床医学视频。超声引导下颈内静脉穿刺置管术。
Keywords: Humans; Ultrasonography; Contraindications; Jugular Veins; Catheterization, Central Venous/adverse effects/instrumentation/*methods

Disaster-relief anesthesia--notes on coming home - Firth, Paul G. (The New England journal of medicine, 2010)
灾难救助麻醉--回家的注意事项
Keywords: Humans; Child; Haiti; *Disasters; *Anesthesiology; *Disaster Medicine; Earthquakes; Physicians/psychology; Relief Work

Parenteral nutrition in the critically ill patient - Scurlock, Corey S.; Raikhelkar, Jayashree; Mechanick, Jeffrey (The New England journal of medicine, 2010)
危重患者的肠外营养
Keywords: Humans; Critical Illness/*therapy; Blood Glucose; Hypoglycemic Agents/*therapeutic use; Insulin/*therapeutic use; *Parenteral Nutrition

Preparing for 2009 H1N1 Influenza - Wenzel, Richard P.; Edmond, Michael B. (The New England journal of medicine, 2009)
2009 H1N1流感的准备
Keywords: Humans; Intensive Care Units; *Influenza A Virus, H1N1 Subtype; Critical Care/statistics & numerical data; Disease Outbreaks/*prevention & control/statistics & numerical data; Health Planning; Influenza, Human/*epidemiology/therapy

Renal support in acute kidney injury--how much is enough? - Palevsky, Paul M (The New England journal of medicine, 2009)
急性肾损伤中的肾脏支持--多少足够？
Keywords: Humans; Treatment Outcome; Critical Illness/mortality/*therapy; Acute Kidney Injury/mortality/*therapy; Hemodiafiltration/*methods

Intensity of continuous renal-replacement therapy in critically ill patients - Bellomo, Rinaldo; Cass, Alan; Cole, Louise; Finfer, Simon; Gallagher, Martin; Lo, Serigne; McArthur, Colin; McGuinness, Shay; Myburgh, John; Norton, Robyn; Scheinkestel, Carlos; Su, Steve (The New England journal of medicine, 2009)
BACKGROUND: The optimal intensity of continuous renal-replacement therapy remains unclear. We conducted a multicenter, randomized trial to compare the effect of this therapy, delivered at two different levels of intensity, on 90-day mortality among critically ill patients with acute kidney injury. METHODS: We randomly assigned critically ill adults with acute kidney injury to continuous renal-replacement therapy in the form of postdilution continuous venovenous hemodiafiltration with an effluent flow of either 40 ml per kilogram of body weight per hour (higher intensity) or 25 ml per kilogram per hour (lower intensity). The primary outcome measure was death within 90 days after randomization. RESULTS: Of the 1508 enrolled patients, 747 were randomly assigned to higher-intensity therapy, and 761 to lower-intensity therapy with continuous venovenous hemodiafiltration. Data on primary outcomes were available for 1464 patients (97.1%): 721 in the higher-intensity group and 743 in the lower-intensity group. The two study groups had similar baseline characteristics and received the study treatment for an average of 6.3 and 5.9 days, respectively (P=0.35). At 90 days after randomization, 322 deaths had occurred in the higher-intensity group and 332 deaths in the lower-intensity group, for a mortality of 44.7% in each group (odds ratio, 1.00; 95% confidence interval [CI], 0.81 to 1.23; P=0.99). At 90 days, 6.8% of survivors in the higher-intensity group (27 of 399), as compared with 4.4% of survivors in the lower-intensity group (18 of 411), were still receiving renal-replacement therapy (odds ratio, 1.59; 95% CI, 0.86 to 2.92; P=0.14). Hypophosphatemia was more common in the higher-intensity group than in the lower-intensity group (65% vs. 54%, P<0.001). CONCLUSIONS: In critically ill patients with acute kidney injury, treatment with higher-intensity continuous renal-replacement therapy did not reduce mortality at 90 days. (ClinicalTrials.gov number, NCT00221013.)
重症患者中连续性肾脏替代治疗的强度 背景：连续肾脏替代治疗的强度尚不清楚。我们有一项多中心、随机试验，旨在比较以两种不同强度给药的该疗法对急性肾损伤重症患者90天死亡率的影响。 ODS：我们将kg急性肾损伤成人患者随机分配接受肾脏替代治疗，具体形式为后稀释连续性静脉-静脉血液透析滤过，流出液流速为40 mL/kg体重/小时（较高强度）或25 mL/kg体重/小时（较低强度）。主要结局指标为随机分组后90天内的死亡。 结果：1508例入组患者中，747例被随机分配接受较高强度治疗，761例被分配接受连续性静脉-静脉血液透析滤过的较低强度治疗。1464例患者(97.1%)的主要结局数据可用：较高强度组721例，较低强度组743例。两个研究组的基线特征相似，平均治疗时间分别为6.3天和5.9天(P = 0.35)。死亡后90天时，较高强度随机分配组中出现322例死亡，较低强度组中出现332例死亡，各组的死亡率为44.7%（比值比，1.00；95%置信区间[CI]，0.81-1.23；P = 0.99）。第90天，较高强度组6.8%的存活者(27/399)和较低强度组4.4%的存活者(18/411)仍接受肾脏替代治疗（比值比，1.59；95%CI，0.86-2.92；P = 0.14）。较高强度组中的低磷血症较低强度组更常见(65%vs. 54%，P < 0.001)。 结论：急性肾损伤重症患者中，较高强度连续肾脏替代治疗并未降低90天时的死亡率。（ClinicalTrials.gov数量，NCT00221013。）
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Prospective Studies; Aged; Kaplan-Meier Estimate; Critical Illness/mortality/*therapy; Acute Kidney Injury/mortality/*therapy; Hemodiafiltration/adverse effects/*methods

Parenteral nutrition in the critically ill patient - Ziegler, Thomas R. (The New England journal of medicine, 2009)
A 67-year-old woman with type 2 diabetes mellitus undergoes extensive resection of the small bowel and right colon with a jejunostomy and colostomy because of mesenteric ischemia. In the surgical intensive care unit, severe systemic inflammatory response syndrome with possible sepsis develops. The patient is treated with volume resuscitation, vasopressor support, mechanical ventilation, broad-spectrum antibiotics, and intravenous insulin infusion. Low-dose tube feedings are initiated postoperatively through a nasogastric tube. However, these feedings are discontinued after the development of escalating vasopressor requirements, worsening abdominal distention, and increased gastric residual volume, along with an episode of emesis. The hospital nutritional-support service is consulted for feeding recommendations. A discussion with the patient's family reveals that during the previous 6 months, she lost approximately 15% of her usual body weight and decreased her food intake because of abdominal pain associated with eating. Her preoperative body weight was 51 kg (112 lb), or 90% of her ideal body weight. The physical examination reveals mild wasting of skeletal muscle and fat. Blood tests show hypomagnesemia, hypophosphatemia, and normal hepatic and renal function. Central venous parenteral nutrition is recommended.
危重患者的肠外营养 一名67岁的2型糖尿病女性患者因肠系膜缺血接受了小肠和右半结肠广泛切除术以及空肠造口术和结肠造口术。在外科重症监护室，发生了重度全身炎症反应综合征，可能伴有败血症。患者接受容量复苏、血管加压素支持、机械通气、广谱抗生素和静脉胰岛素输注治疗。术后通过鼻胃管开始低剂量管饲。但是，在出现血管加压素需求增加、腹胀恶化和胃残留量增加以及呕吐发作后，停止这些喂养。关于喂养建议，请咨询医院营养支持服务。与患者家属的讨论显示，在过去6个月内，患者体重减轻约15%，进食相关腹痛导致进食减少。她的术前体重为51 kg(112 lb)，或理想体重的90%。体格检查显示骨骼肌和脂肪轻度消耗。血液检查显示低镁血症、低磷血症，肝肾功能正常。推荐使用中心静脉肠外营养。
Keywords: Humans; Female; Aged; Intensive Care Units; Catheterization, Central Venous; Practice Guidelines as Topic; Postoperative Complications/*therapy; *Critical Illness; Contraindications; *Parenteral Nutrition/adverse effects/methods; Diabetes Mellitus, Type 2/complications; Ischemia/etiology/surgery; Mesentery/blood supply; Protein-Energy Malnutrition/*therapy

Predisposing factors for adrenal insufficiency - Kaufman, David A. (The New England journal of medicine, 2009)
肾上腺功能不全的诱发因素
Keywords: Humans; Critical Illness; Reproducibility of Results; *Adrenocorticotropic Hormone/administration & dosage; Adrenal Insufficiency/*diagnosis; Hydrocortisone/*blood

Glucose control in critically ill patients - Van den Berghe, Greet; Bouillon, Roger; Mesotten, Dieter (The New England journal of medicine, 2009)
重症患者的血糖控制
Keywords: Humans; Critical Care/*methods; Bias; Hypoglycemic Agents/*administration & dosage; Insulin/*administration & dosage; *Blood Glucose/analysis; Critical Illness/*mortality/therapy; Hyperglycemia/*drug therapy; Hypoglycemia/chemically induced; Parenteral Nutrition

Predisposing factors for adrenal insufficiency - Bornstein, Stefan R. (The New England journal of medicine, 2009)
肾上腺功能不全的诱发因素
Keywords: Humans; Critical Illness; Diagnosis, Differential; Hydrocortisone/*therapeutic use; Adrenal Insufficiency/drug therapy/*etiology/genetics; Causality; Drug-Related Side Effects and Adverse Reactions; Genetic Diseases, Inborn; Glucocorticoids/*deficiency/metabolism; Sepsis/*complications/drug therapy

Decontamination of the digestive tract in ICU patients - Meessen, Nico E.; Nap, Raoul E.; Andriessen, Maarten P. (The New England journal of medicine, 2009)
ICU患者的消化道净化
Keywords: Humans; Intensive Care Units; Gastrointestinal Tract/*microbiology; *Vancomycin Resistance; Disease Outbreaks; *Decontamination; *Enterococcus faecium; Ampicillin Resistance; Bacteremia/epidemiology/prevention & control; Cross Infection/epidemiology/prevention & control; Gram-Positive Bacterial Infections/*epidemiology; Oropharynx/*microbiology

Vitamin D deficiency in critically ill patients - Lee, Paul; Eisman, John A.; Center, Jacqueline R. (The New England journal of medicine, 2009)
重症患者维生素D缺乏
Keywords: Humans; Prospective Studies; Intensive Care Units; *Critical Illness; Vitamin D Deficiency/*epidemiology; Vitamin D/analogs & derivatives/blood

Glucose control in the ICU--how tight is too tight? - Inzucchi, Silvio E; Siegel, Mark D. (The New England journal of medicine, 2009)
ICU中的血糖控制--过紧的程度如何？
Keywords: Humans; Intensive Care Units; Critical Illness/mortality/*therapy; Hypoglycemic Agents/*therapeutic use; Insulin/*therapeutic use; Hyperglycemia/*drug therapy; Hypoglycemia/chemically induced

Intensive versus conventional glucose control in critically ill patients - Finfer, Simon; Chittock, Dean R.; Su, Steve Yu-Shuo; Blair, Deborah; Foster, Denise; Dhingra, Vinay; Bellomo, Rinaldo; Cook, Deborah; Dodek, Peter; Henderson, William R.; HÃ©bert, Paul C.; Heritier, Stephane; et al. (The New England journal of medicine, 2009)
BACKGROUND: The optimal target range for blood glucose in critically ill patients remains unclear. METHODS: Within 24 hours after admission to an intensive care unit (ICU), adults who were expected to require treatment in the ICU on 3 or more consecutive days were randomly assigned to undergo either intensive glucose control, with a target blood glucose range of 81 to 108 mg per deciliter (4.5 to 6.0 mmol per liter), or conventional glucose control, with a target of 180 mg or less per deciliter (10.0 mmol or less per liter). We defined the primary end point as death from any cause within 90 days after randomization. RESULTS: Of the 6104 patients who underwent randomization, 3054 were assigned to undergo intensive control and 3050 to undergo conventional control; data with regard to the primary outcome at day 90 were available for 3010 and 3012 patients, respectively. The two groups had similar characteristics at baseline. A total of 829 patients (27.5%) in the intensive-control group and 751 (24.9%) in the conventional-control group died (odds ratio for intensive control, 1.14; 95% confidence interval, 1.02 to 1.28; P=0.02). The treatment effect did not differ significantly between operative (surgical) patients and nonoperative (medical) patients (odds ratio for death in the intensive-control group, 1.31 and 1.07, respectively; P=0.10). Severe hypoglycemia (blood glucose level, < or = 40 mg per deciliter [2.2 mmol per liter]) was reported in 206 of 3016 patients (6.8%) in the intensive-control group and 15 of 3014 (0.5%) in the conventional-control group (P<0.001). There was no significant difference between the two treatment groups in the median number of days in the ICU (P=0.84) or hospital (P=0.86) or the median number of days of mechanical ventilation (P=0.56) or renal-replacement therapy (P=0.39). CONCLUSIONS: In this large, international, randomized trial, we found that intensive glucose control increased mortality among adults in the ICU: a blood glucose target of 180 mg or less per deciliter resulted in lower mortality than did a target of 81 to 108 mg per deciliter. (ClinicalTrials.gov number, NCT00220987.)
重症患者中的强化血糖控制与常规血糖控制 背景：危重患者血糖的最佳目标范围仍不清楚。 方法：在入住重症监护室(ICU)后24小时内，预期需要连续3天或3天以上在ICU接受治疗的成人被随机分配接受强化血糖控制，目标血糖范围为81至108 mg/dl（4.5至6.0 mmol/l），或常规血糖控制，目标为180 mg或更低每分升（10.0 mmol或更低每升）。我们将主要终点定义为随机分组后90天内全因死亡。 结果：在6104例接受随机分组的患者中，3054例被分配接受强化控制，3050例被分配接受常规控制；第90天的主要结局相关数据分别来自3010例和3012例患者。两组基线特征相似。强化对照组和常规对照组分别共有829例(27.5%)和751例(24.9%)患者死亡（强化控制的优势比为1.14；95%置信区间，1.02-1.28；P = 0.02）。手术（外科）患者和非手术（内科）患者的治疗效果无显著差异（强化对照组死亡的比值比分别为1.31和1.07；P = 0.10）。3016例强化对照组患者中206例(6.8%)和3014例常规对照组患者中15例(0.5%)报告了重度低血糖（血糖水平≤40 mg/dl[2.2 mmol/l]）(P < 0.001)。两个治疗组在ICU(P = 0.84)或医院(P = 0.86)的中位天数或机械通气(P = 0.56)或肾脏替代治疗(P = 0.39)的中位天数方面无显著差异。 结论：在这项大型、国际化、随机试验中，我们发现强化血糖控制可增加ICU成人患者的死亡率：180 mg/dl或更低的血糖控制目标比81-108 mg/dl的目标死亡率更低。（ClinicalTrials.gov数量，NCT00220987。）
Keywords: Humans; Female; Male; Middle Aged; Intensive Care Units; Length of Stay; Kaplan-Meier Estimate; Critical Care/*methods; Adrenal Cortex Hormones/therapeutic use; Critical Illness/mortality/*therapy; *Blood Glucose/analysis; Hyperglycemia/*drug therapy; Hypoglycemia/chemically induced; Hypoglycemic Agents/adverse effects/*therapeutic use; Insulin/adverse effects/*therapeutic use

Clinical decisions. Care of an unresponsive patient with a poor prognosis--polling results. - Kritek, Patricia A.; Slutsky, Arthur S.; Hudson, Leonard D. (The New England journal of medicine, 2009)
临床决策。护理无反应且预后-轮询结果差的患者。
Keywords: Humans; Male; Middle Aged; Prognosis; Family; *Palliative Care; *Resuscitation Orders; *Withholding Treatment/legislation & jurisprudence; Aneurysm, Ruptured/*therapy; Ethics Consultation; Intracranial Aneurysm/*therapy; Subarachnoid Hemorrhage/therapy

Clinical decisions. Care of an unresponsive patient with a poor prognosis. - Slutsky, Arthur S.; Hudson, Leonard D. (The New England journal of medicine, 2009)
临床决策。护理无反应的预后不良患者。
Keywords: Humans; Male; Middle Aged; Prognosis; *Palliative Care; Aneurysm, Ruptured/complications/*therapy; Hydrocephalus/complications/therapy; Intracranial Aneurysm/complications/*therapy; Subarachnoid Hemorrhage/complications/therapy

Decontamination of the digestive tract and oropharynx in ICU patients - de Smet, A. M. G. A.; Kluytmans, J. A. J. W.; Cooper, B. S.; Mascini, E. M.; Benus, R. F. J.; van der Werf, T. S.; van der Hoeven, J. G.; Pickkers, P.; Bogaers-Hofman, D.; van der Meer, N. J. M.; Bernards, A. T.; Kuijper, E. J.; et al. (The New England journal of medicine, 2009)
BACKGROUND: Selective digestive tract decontamination (SDD) and selective oropharyngeal decontamination (SOD) are infection-prevention measures used in the treatment of some patients in intensive care, but reported effects on patient outcome are conflicting. METHODS: We evaluated the effectiveness of SDD and SOD in a crossover study using cluster randomization in 13 intensive care units (ICUs), all in The Netherlands. Patients with an expected duration of intubation of more than 48 hours or an expected ICU stay of more than 72 hours were eligible. In each ICU, three regimens (SDD, SOD, and standard care) were applied in random order over the course of 6 months. Mortality at day 28 was the primary end point. SDD consisted of 4 days of intravenous cefotaxime and topical application of tobramycin, colistin, and amphotericin B in the oropharynx and stomach. SOD consisted of oropharyngeal application only of the same antibiotics. Monthly point-prevalence studies were performed to analyze antibiotic resistance. RESULTS: A total of 5939 patients were enrolled in the study, with 1990 assigned to standard care, 1904 to SOD, and 2045 to SDD; crude mortality in the groups at day 28 was 27.5%, 26.6%, and 26.9%, respectively. In a random-effects logistic-regression model with age, sex, Acute Physiology and Chronic Health Evaluation (APACHE II) score, intubation status, and medical specialty used as covariates, odds ratios for death at day 28 in the SOD and SDD groups, as compared with the standard-care group, were 0.86 (95% confidence interval [CI], 0.74 to 0.99) and 0.83 (95% CI, 0.72 to 0.97), respectively. CONCLUSIONS: In an ICU population in which the mortality rate associated with standard care was 27.5% at day 28, the rate was reduced by an estimated 3.5 percentage points with SDD and by 2.9 percentage points with SOD. (Controlled Clinical Trials number, ISRCTN35176830.)
ICU患者的消化道和口咽消毒 背景：选择性消化道净化(SDD)和选择性口咽净化(SOD)是一些重症监护患者治疗中使用的感染预防措施，但报告的对患者结局的影响存在矛盾。 方法：我们在一项交叉研究中评估了SDD和SOD的有效性，该研究在13个重症监护室(ICU)中采用集群随机法，均在荷兰进行。预期插管时间超过48小时或预期ICU停留时间超过72小时的患者符合条件。在每个ICU中，在6个月的过程中，按随机顺序应用三种方案（SDD、SOD和标准治疗）。第28天的死亡率为主要终点。SDD包括4天的静脉注射头孢噻肟和口咽和胃局部应用妥布霉素、多粘菌素和两性霉素B。SOD仅由口咽应用相同抗生素组成。每月进行点患病率研究，以分析抗生素耐药性。 结果：共有5939例患者入组研究，1990例分配至标准治疗组，1904例分配至SOD组，2045例分配至SDD组；第28天各组的粗死亡率分别为27.5%、26.6%和26.9%。在一个将年龄、性别、急性生理和慢性健康评估(APACHE II)评分、插管状态和医学专业作为协变量的随机效应logistic回归模型中，与标准治疗组相比，SOD和SDD组第28天死亡的比值比为0.86（95%置信区间[CI]，0.74-0.99）和0.83(95%CI，0.72-0.97)。 结论：在标准治疗相关的ICU人群中，第28天时死亡率为27.5%，SDD和SOD的死亡率分别估计降低了3.5个百分点和2.9个百分点。（对照临床试验编号，ISRCTN35176830。）
Keywords: Humans; Female; Male; Middle Aged; Aged; APACHE; Intensive Care Units; Respiration, Artificial; Anti-Bacterial Agents/therapeutic use; Gastrointestinal Tract/*microbiology; Logistic Models; Infection Control/methods; Cross-Over Studies; Critical Illness/mortality/therapy; Cross Infection/epidemiology/*prevention & control; *Decontamination; Oropharynx/*microbiology; Bacteremia/epidemiology/*prevention & control; Gram-Negative Bacteria/isolation & purification

Videos in clinical medicine. Peripheral intravenous cannulation. - Ortega, Rafael; Sekhar, Pavan; Song, Michael; Hansen, Christopher J.; Peterson, Lauren (The New England journal of medicine, 2008)
临床医学视频。外周静脉插管。
Keywords: Humans; Catheterization, Peripheral/adverse effects/instrumentation/*methods; Contraindications; Infusions, Intravenous/instrumentation/*methods; Lower Extremity/blood supply; Upper Extremity/blood supply

Videos in clinical medicine. Umbilical vascular catheterization. - Anderson, JoDee; Leonard, Douglas; Braner, Dana A. V.; Lai, Susanna; Tegtmeyer, Ken (The New England journal of medicine, 2008)
临床医学视频。脐血管插管。
Keywords: Humans; Critical Care; Infant, Newborn; Catheterization, Central Venous/methods; Catheterization, Peripheral/adverse effects/instrumentation/*methods; Catheters, Indwelling; Contraindications; Protective Clothing; Resuscitation/methods; Umbilical Arteries/anatomy & histology; Umbilicus/anatomy & histology/blood supply; Veins/anatomy & histology

Dialysis in acute kidney injury--more is not better - Bonventre, Joseph V. (The New England journal of medicine, 2008)
急性肾损伤中的透析--越多越好
Keywords: Humans; Time Factors; Critical Illness; Acute Kidney Injury/*therapy; Hemodiafiltration/*methods; Renal Dialysis/*methods

Intensity of renal support in critically ill patients with acute kidney injury - Palevsky, Paul M.; Zhang, Jane Hongyuan; O'Connor, Theresa Z.; Chertow, Glenn M.; Crowley, Susan T.; Choudhury, Devasmita; Finkel, Kevin; Kellum, John A.; Paganini, Emil; Schein, Roland M. H.; Smith, Mark W.; Swanson, Kathleen M.; et al. (The New England journal of medicine, 2008)
BACKGROUND: The optimal intensity of renal-replacement therapy in critically ill patients with acute kidney injury is controversial. METHODS: We randomly assigned critically ill patients with acute kidney injury and failure of at least one nonrenal organ or sepsis to receive intensive or less intensive renal-replacement therapy. The primary end point was death from any cause by day 60. In both study groups, hemodynamically stable patients underwent intermittent hemodialysis, and hemodynamically unstable patients underwent continuous venovenous hemodiafiltration or sustained low-efficiency dialysis. Patients receiving the intensive treatment strategy underwent intermittent hemodialysis and sustained low-efficiency dialysis six times per week and continuous venovenous hemodiafiltration at 35 ml per kilogram of body weight per hour; for patients receiving the less-intensive treatment strategy, the corresponding treatments were provided thrice weekly and at 20 ml per kilogram per hour. RESULTS: Baseline characteristics of the 1124 patients in the two groups were similar. The rate of death from any cause by day 60 was 53.6% with intensive therapy and 51.5% with less-intensive therapy (odds ratio, 1.09; 95% confidence interval, 0.86 to 1.40; P=0.47). There was no significant difference between the two groups in the duration of renal-replacement therapy or the rate of recovery of kidney function or nonrenal organ failure. Hypotension during intermittent dialysis occurred in more patients randomly assigned to receive intensive therapy, although the frequency of hemodialysis sessions complicated by hypotension was similar in the two groups. CONCLUSIONS: Intensive renal support in critically ill patients with acute kidney injury did not decrease mortality, improve recovery of kidney function, or reduce the rate of nonrenal organ failure as compared with less-intensive therapy involving a defined dose of intermittent hemodialysis three times per week and continuous renal-replacement therapy at 20 ml per kilogram per hour. (ClinicalTrials.gov number, NCT00076219.)
急性肾损伤重症患者中的肾脏支持强度 背景：急性肾损伤重症患者中，肾脏替代治疗的最佳强度存在争议。 方法：我们将急性肾损伤伴至少一种非肾脏器官功能衰竭或败血症的重症患者随机分配至接受强化或弱强度肾脏替代治疗。主要终点是第60天的全因死亡。两个研究组中，血流动力学稳定患者接受了间歇性血液透析，血流动力学不稳定患者接受了连续性静脉-静脉血液透析滤过或持续低效透析。接受强化治疗策略的患者接受了间歇性血液透析和持续低效透析，每周6次，连续性静脉-静脉血液透析滤过，速率为35 mL/kg体重/小时；对于接受弱强度治疗策略的患者，每周提供3次相应治疗，速率为20 mL/kg/h。 结果：两组1124例患者的基线特征相似。第60天，任何原因导致的死亡率，强化治疗组为53.6%，弱强化治疗组为51.5%（比值比，1.09；95%置信区间，0.86-1.40；P = 0.47）。在肾脏替代治疗的持续时间或肾功能或非肾脏器官衰竭的恢复率方面，两组之间没有显著差异。间歇性透析期间低血压发生于随机分配接受强化治疗的更多患者中，尽管两组中血液透析治疗期间并发低血压的频率相似。 结论：急性肾损伤重症患者中，强化肾脏支持并未降低死亡率，改善肾功能恢复，或与弱强化治疗相比，降低非肾脏器官衰竭的发生率，包括规定剂量的间歇性血液透析，每周3次和连续肾脏替代治疗，速率为20 mL/kg/小时。（临床试验gov编号，NCT00076219。）
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Time Factors; Critical Illness; Kaplan-Meier Estimate; Multiple Organ Failure/etiology; Acute Kidney Injury/complications/mortality/*therapy; Hemodiafiltration/adverse effects/*methods; Renal Dialysis/adverse effects/*methods

Videos in clinical medicine. Cricothyroidotomy. - Hsiao, James; Pacheco-Fowler, Victor (The New England journal of medicine, 2008)
临床医学视频。环甲膜切开术。
Keywords: Humans; Respiration, Artificial; Postoperative Care; Contraindications; Airway Obstruction/*surgery; Cricoid Cartilage; Membranes/surgery; Thyroid Cartilage; Tracheostomy/instrumentation; Tracheotomy/adverse effects/instrumentation/*methods

Intensive insulin therapy and pentastarch resuscitation in severe sepsis - Brunkhorst, Frank M.; Engel, Christoph; Bloos, Frank; Meier-Hellmann, Andreas; Ragaller, Max; Weiler, Norbert; Moerer, Onnen; Gruendling, Matthias; Oppert, Michael; Grond, Stefan; Olthoff, Derk; Jaschinski, Ulrich; et al. (The New England journal of medicine, 2008)
BACKGROUND: The role of intensive insulin therapy in patients with severe sepsis is uncertain. Fluid resuscitation improves survival among patients with septic shock, but evidence is lacking to support the choice of either crystalloids or colloids. METHODS: In a multicenter, two-by-two factorial trial, we randomly assigned patients with severe sepsis to receive either intensive insulin therapy to maintain euglycemia or conventional insulin therapy and either 10% pentastarch, a low-molecular-weight hydroxyethyl starch (HES 200/0.5), or modified Ringer's lactate for fluid resuscitation. The rate of death at 28 days and the mean score for organ failure were coprimary end points. RESULTS: The trial was stopped early for safety reasons. Among 537 patients who could be evaluated, the mean morning blood glucose level was lower in the intensive-therapy group (112 mg per deciliter [6.2 mmol per liter]) than in the conventional-therapy group (151 mg per deciliter [8.4 mmol per liter], P<0.001). However, at 28 days, there was no significant difference between the two groups in the rate of death or the mean score for organ failure. The rate of severe hypoglycemia (glucose level, < or = 40 mg per deciliter [2.2 mmol per liter]) was higher in the intensive-therapy group than in the conventional-therapy group (17.0% vs. 4.1%, P<0.001), as was the rate of serious adverse events (10.9% vs. 5.2%, P=0.01). HES therapy was associated with higher rates of acute renal failure and renal-replacement therapy than was Ringer's lactate. CONCLUSIONS: The use of intensive insulin therapy placed critically ill patients with sepsis at increased risk for serious adverse events related to hypoglycemia. As used in this study, HES was harmful, and its toxicity increased with accumulating doses. (ClinicalTrials.gov number, NCT00135473.)
严重脓毒症的胰岛素强化治疗和淀粉样复苏 背景：胰岛素强化治疗在重度脓毒症患者中的作用尚不确定。液体复苏可改善感染性休克患者的生存率，但缺乏证据支持晶体或胶体的选择。 方法：在一项多中心、2 × 2析因试验中，我们将重度脓毒症患者随机分配至接受强化胰岛素治疗以维持正常血糖或常规胰岛素治疗，以及10%淀粉、低分子量羟乙基淀粉(HES 200/0.5)或改良乳酸林格氏液进行液体复苏。28天时的死亡率和器官衰竭的平均评分为共同主要终点。 结果：由于安全性原因，试验提前终止。在可评估的537例患者中，强化治疗组的平均早晨血糖水平(112 mg/dl[6.2 mmol/l])低于常规治疗组(151 mg/dl[8.4 mmol/l]，P < 0.001)。但是，在28天时，两组之间的死亡率或器官衰竭平均评分没有显著差异。强化治疗组重度低血糖（血糖水平≤40 mg/dl[2.2 mmol/l]）的发生率高于常规治疗组(17.0%vs. 4.1%，P < 0.001)，严重不良事件的发生率也是如此(10.9%vs. 5.2%，P = 0.01)。与乳酸林格氏液相比，羟乙基淀粉治疗与急性肾功能衰竭和肾脏替代治疗的发生率较高相关。 结论：使用胰岛素强化治疗使败血症重症患者发生低血糖相关严重不良事件的风险增加。在本研究中，羟乙基淀粉是有害的，其毒性随累积剂量的增加而增加。（ClinicalTrials.gov数量，NCT00135473。）
Keywords: Humans; Female; Male; Middle Aged; Aged; Critical Illness; Risk Factors; Infusions, Intravenous; Kaplan-Meier Estimate; Dose-Response Relationship, Drug; Multivariate Analysis; Combined Modality Therapy; Treatment Failure; Hypoglycemic Agents/*administration & dosage/adverse effects; Insulin/*administration & dosage/adverse effects; Hypoglycemia/*chemically induced; *Fluid Therapy; Acute Kidney Injury/*etiology; Hydroxyethyl Starch Derivatives/administration & dosage/*adverse effects/therapeutic use; Isotonic Solutions/adverse effects/therapeutic use; Ringer's Solution; Sepsis/drug therapy/mortality/*therapy

Epoetin alfa in critically ill patients - Mikhail, Ashraf (The New England journal of medicine, 2007)
重症患者中的阿法依泊汀
Keywords: Humans; Critical Illness/*therapy; Injections, Intravenous; Injections, Subcutaneous; Absorption; Epoetin Alfa; Erythropoietin/*administration & dosage/pharmacokinetics; Recombinant Proteins

Videos in clinical medicine. Central venous catheterization--subclavian vein. - Braner, Dana A. V.; Lai, Susanna; Eman, Scott; Tegtmeyer, Ken (The New England journal of medicine, 2007)
临床医学视频。中心静脉置管--锁骨下静脉。
Keywords: Humans; Contraindications; Pneumothorax/etiology; Subclavian Vein; Catheterization, Central Venous/adverse effects/*instrumentation/*methods; Cross Infection/etiology/prevention & control; Subclavian Artery/injuries

Videos in clinical medicine. Chest-tube insertion. - Dev, Shelly P.; Nascimiento, Bartolomeu Jr; Simone, Carmine; Chien, Vincent (The New England journal of medicine, 2007)
临床医学视频。胸管插入。
Keywords: Humans; Contraindications; *Chest Tubes/adverse effects; Drainage/instrumentation/*methods; Pleural Diseases/*therapy

Targeting anemia with erythropoietin during critical illness - Cook, Deborah; Crowther, Mark (The New England journal of medicine, 2007)
危重症时促红细胞生成素治疗贫血
Keywords: Humans; Critical Illness/*therapy; Hemoglobins/analysis; Epoetin Alfa; Recombinant Proteins; Erythrocyte Transfusion/statistics & numerical data; Erythropoietin/adverse effects/*therapeutic use; Hematinics/adverse effects/*therapeutic use; Thrombosis/chemically induced; Wounds and Injuries/blood/drug therapy

Efficacy and safety of epoetin alfa in critically ill patients - Corwin, Howard L.; Gettinger, Andrew; Fabian, Timothy C.; May, Addison; Pearl, Ronald G.; Heard, Stephen; An, Robert; Bowers, Peter J.; Burton, Paul; Klausner, Mark A.; Corwin, Michael J. (The New England journal of medicine, 2007)
BACKGROUND: Anemia, which is common in the critically ill, is often treated with red-cell transfusions, which are associated with poor clinical outcomes. We hypothesized that therapy with recombinant human erythropoietin (epoetin alfa) might reduce the need for red-cell transfusions. METHODS: In this prospective, randomized, placebo-controlled trial, we enrolled 1460 medical, surgical, or trauma patients between 48 and 96 hours after admission to the intensive care unit. Epoetin alfa (40,000 U) or placebo was administered weekly, for a maximum of 3 weeks; patients were followed for 140 days. The primary end point was the percentage of patients who received a red-cell transfusion. Secondary end points were the number of red-cell units transfused, mortality, and the change in hemoglobin concentration from baseline. RESULTS: As compared with the use of placebo, epoetin alfa therapy did not result in a decrease in either the number of patients who received a red-cell transfusion (relative risk for the epoetin alfa group vs. the placebo group, 0.95; 95% confidence interval [CI], 0.85 to 1.06) or the mean (+/-SD) number of red-cell units transfused (4.5+/-4.6 units in the epoetin alfa group and 4.3+/-4.8 units in the placebo group, P=0.42). However, the hemoglobin concentration at day 29 increased more in the epoetin alfa group than in the placebo group (1.6+/-2.0 g per deciliter vs. 1.2+/-1.8 g per deciliter, P<0.001). Mortality tended to be lower at day 29 among patients receiving epoetin alfa (adjusted hazard ratio, 0.79; 95% CI, 0.56 to 1.10); this effect was also seen in prespecified analyses in those with a diagnosis of trauma (adjusted hazard ratio, 0.37; 95% CI, 0.19 to 0.72). A similar pattern was seen at day 140 (adjusted hazard ratio, 0.86; 95% CI, 0.65 to 1.13), particularly in those with trauma (adjusted hazard ratio, 0.40; 95% CI, 0.23 to 0.69). As compared with placebo, epoetin alfa was associated with a significant increase in the incidence of thrombotic events (hazard ratio, 1.41; 95% CI, 1.06 to 1.86). CONCLUSIONS: The use of epoetin alfa does not reduce the incidence of red-cell transfusion among critically ill patients, but it may reduce mortality in patients with trauma. Treatment with epoetin alfa is associated with an increase in the incidence of thrombotic events. (ClinicalTrials.gov number, NCT00091910 [ClinicalTrials.gov].).
epoetin α在重症患者中的疗效和安全性 背景：在重症患者中常见的贫血通常采用红细胞输注治疗，这与临床结局较差相关。我们假设重组人红细胞生成素(epoetin α)治疗可能减少红细胞输注的需要。 方法：在这项前瞻性、随机、安慰剂对照试验中，我们入选了1460例在入住重症监护室48至96小时内的内科、外科或创伤患者。每周给予依泊汀α(40,000 U)或安慰剂，最长3周；随访患者140天。主要终点是接受红细胞输注的患者百分比。次要终点是输注的红细胞单位数、死亡率和血红蛋白浓度较基线的变化。 结果：与使用安慰剂相比，依泊汀α治疗未导致接受红细胞输注的患者数量减少（依泊汀α组相对于安慰剂组的相对风险，0.95；95%置信区间[CI]，0.85-1.06）或平均(+/-SD)输注的红细胞单位数（依泊汀α组为4.5±4.6 U，安慰剂组为4.3±4.8 U，P = 0.42）。然而，在第29天，阿法依泊汀组的血红蛋白浓度比安慰剂组增加更多(1.6±2.0 g/dl vs. 1.2±1.8 g/dl，P < 0.001)。第29天时，接受依泊汀α治疗的患者死亡率有降低的趋势（调整后的风险比，0.79；95%CI，0.56-1.10）；在预先规定的创伤诊断分析中也观察到这种影响（调整后的风险比，0.37；95%CI，0.19-0.72）。在第140天时观察到相似的模式（调整后的风险比，0.86；95%CI，0.65-1.13），尤其是创伤患者（调整后的风险比，0.40；95%CI，0.23-0.69）。与安慰剂相比，依泊汀α与血栓事件发生率的显著增加相关（风险比为1.41；95%CI，1.06至1.86）。 结论：在危重患者中，使用阿法依泊汀不会降低红细胞输注的发生率，但可能降低创伤患者的死亡率。依泊汀α治疗与血栓事件发生率增加相关。（ClinicalTrials.gov编号，NCT00091910[ClinicalTrials.gov].).
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Double-Blind Method; Aged; Intensive Care Units; Length of Stay; Adult; Trauma Severity Indices; Kaplan-Meier Estimate; Proportional Hazards Models; Critical Illness/mortality/*therapy; Respiration, Artificial/statistics & numerical data; Epoetin Alfa; Recombinant Proteins; Erythropoietin/adverse effects/*therapeutic use; Hematinics/adverse effects/*therapeutic use; Thrombosis/chemically induced; Erythrocyte Transfusion/*statistics & numerical data; Hemoglobins/metabolism; Wounds and Injuries/blood/*drug therapy/mortality

Videos in clinical medicine. Positive-pressure ventilation with a face mask and a bag-valve device. - Ortega, Rafael; Mehio, Abdel K.; Woo, Albert; Hafez, Dina H. (The New England journal of medicine, 2007)
临床医学视频。面罩和袋阀装置正压通气。
Keywords: Humans; Equipment Design; Respiratory Insufficiency/*therapy; Contraindications; Apnea/therapy; Masks; Positive-Pressure Respiration/adverse effects/instrumentation/*methods

Videos in clinical medicine. Central venous catheterization. - Graham, Alan S.; Ozment, Caroline; Tegtmeyer, Ken; Lai, Susanna; Braner, Dana A. V. (The New England journal of medicine, 2007)
临床医学视频。中心静脉导管插入术。
Keywords: Humans; Contraindications; Jugular Veins; Catheterization, Central Venous/adverse effects/instrumentation/*methods; Medical Errors; Neck/anatomy & histology; Venous Thrombosis/etiology

Videos in clinical medicine. Orotracheal intubation. - Kabrhel, Christopher; Thomsen, Todd W.; Setnik, Gary S.; Walls, Ron M. (The New England journal of medicine, 2007)
临床医学视频。经口气管插管。
Keywords: Humans; Critical Illness/therapy; Contraindications; Protective Clothing; Emergency Treatment; Intubation, Intratracheal/adverse effects/instrumentation/*methods; Laryngoscopes

Blood transfusion--when is more really less? - Corwin, Howard L; Carson, Jeffrey L. (The New England journal of medicine, 2007)
输血--何时更少？
Keywords: Humans; Child; Infant; Critical Illness/*therapy; Hemoglobins/analysis; *Erythrocyte Transfusion/standards; Anemia/diagnosis/*therapy

Transfusion strategies for patients in pediatric intensive care units - Lacroix, Jacques; HÃ©bert, Paul C.; Hutchison, James S.; Hume, Heather A.; Tucci, Marisa; Ducruet, Thierry; Gauvin, France; Collet, Jean-Paul; Toledano, Baruch J.; Robillard, Pierre; Joffe, Ari; Biarent, Dominique; et al. (The New England journal of medicine, 2007)
BACKGROUND: The optimal hemoglobin threshold for erythrocyte transfusions in critically ill children is unknown. We hypothesized that a restrictive transfusion strategy of using packed red cells that were leukocyte-reduced before storage would be as safe as a liberal transfusion strategy, as judged by the outcome of multiple-organ dysfunction. METHODS: In this noninferiority trial, we enrolled 637 stable, critically ill children who had hemoglobin concentrations below 9.5 g per deciliter within 7 days after admission to an intensive care unit. We randomly assigned 320 patients to a hemoglobin threshold of 7 g per deciliter for red-cell transfusion (restrictive-strategy group) and 317 patients to a threshold of 9.5 g per deciliter (liberal-strategy group). RESULTS: Hemoglobin concentrations were maintained at a mean (+/-SD) level that was 2.1+/-0.2 g per deciliter lower in the restrictive-strategy group than in the liberal-strategy group (lowest average levels, 8.7+/-0.4 and 10.8+/-0.5 g per deciliter, respectively; P<0.001). Patients in the restrictive-strategy group received 44% fewer transfusions; 174 patients (54%) in that group did not receive any transfusions, as compared with 7 patients (2%) in the liberal-strategy group (P<0.001). New or progressive multiple-organ dysfunction syndrome (the primary outcome) developed in 38 patients in the restrictive-strategy group, as compared with 39 in the liberal-strategy group (12% in both groups) (absolute risk reduction with the restrictive strategy, 0.4%; 95% confidence interval, -4.6 to 5.4). There were 14 deaths in each group within 28 days after randomization. No significant differences were found in other outcomes, including adverse events. CONCLUSIONS: In stable, critically ill children a hemoglobin threshold of 7 g per deciliter for red-cell transfusion can decrease transfusion requirements without increasing adverse outcomes. (Controlled-trials.com number, ISRCTN37246456 [controlled-trials.com].).
儿科重症监护室患者的输血策略 背景：危重患儿红细胞输注的最佳血红蛋白阈值尚不清楚。我们假设，根据多器官功能障碍的结局判断，使用储存前减少白细胞的浓缩红细胞的限制性输血策略与自由输血策略同样安全。 方法：在本项非劣效性试验中，我们入选了637例稳定的危重儿童，这些儿童在进入重症监护室7天内血红蛋白浓度低于9.5 g/dl。我们将320例患者随机分配至血红蛋白阈值为7 g/dl的红细胞输血组（限制策略组）和317例患者随机分配至阈值为9.5 g/dl的红细胞输血组（自由策略组）。 结果：限制策略组的血红蛋白浓度维持在平均(+/-SD)水平，即2.1±0.2 g/dl，低于自由策略组（最低平均水平，分别为8.7±0.4和10.8±0.5 g/dl；P < 0.001）。限制策略组患者的输血次数减少了44%；该组有174例患者(54%)未接受任何输血，而自由策略组有7例患者(2%)(P < 0.001)。限制策略组38例患者出现新发或进展性多器官功能障碍综合征（主要结局），而自由策略组39例（两组均为12%）（限制策略的绝对风险降低，0.4%；95%置信区间，-4.6至5.4）。在随机分组后28天内，每组均有14例死亡。其他结局未见显著差异，包括不良事件。 结论：在稳定的危重儿童中，红细胞输注的血红蛋白阈值为7 g/dl，可降低输血需求，而不增加不良结局。（Controlled-trials.com编号，ISRCTN37246456[controlled-trials.com].).
Keywords: Humans; Female; Male; Child; Infant; Infant, Newborn; Severity of Illness Index; Child, Preschool; *Erythrocyte Transfusion; Critical Illness/mortality/*therapy; Intensive Care Units, Pediatric; Hemoglobins/*analysis; Anemia/blood/diagnosis/*therapy; Leukocyte Reduction Procedures; Multiple Organ Failure/epidemiology

A randomized trial of diagnostic techniques for ventilator-associated pneumonia (The New England journal of medicine, 2006)
BACKGROUND: Critically ill patients who require mechanical ventilation are at risk for ventilator-associated pneumonia. Current data are conflicting as to the optimal diagnostic approach in patients who have suspected ventilator-associated pneumonia. METHODS: In a multicenter trial, we randomly assigned immunocompetent adults who were receiving mechanical ventilation and who had suspected ventilator-associated pneumonia after 4 days in the intensive care unit (ICU) to undergo either bronchoalveolar lavage with quantitative culture of the bronchoalveolar-lavage fluid or endotracheal aspiration with nonquantitative culture of the aspirate. Patients known to be colonized or infected with pseudomonas species or methicillin-resistant Staphylococcus aureus were excluded. Empirical antibiotic therapy was initiated in all patients until culture results were available, at which point a protocol of targeted therapy was used for discontinuing or reducing the dose or number of antibiotics, or for resuming antibiotic therapy to treat a preenrollment condition if the culture was negative. RESULTS: We enrolled 740 patients in 28 ICUs in Canada and the United States. There was no significant difference in the primary outcome (28-day mortality rate) between the bronchoalveolar-lavage group and the endotracheal-aspiration group (18.9% and 18.4%, respectively; P=0.94). The bronchoalveolar-lavage group and the endotracheal-aspiration group also had similar rates of targeted therapy (74.2% and 74.6%, respectively; P=0.90), days alive without antibiotics (10.4+/-7.5 and 10.6+/-7.9, P=0.86), and maximum organ-dysfunction scores (mean [+/-SD], 8.3+/-3.6 and 8.6+/-4.0; P=0.26). The two groups did not differ significantly in the length of stay in the ICU or hospital. CONCLUSIONS: Two diagnostic strategies for ventilator-associated pneumonia--bronchoalveolar lavage with quantitative culture of the bronchoalveolar-lavage fluid and endotracheal aspiration with nonquantitative culture of the aspirate--are associated with similar clinical outcomes and similar overall use of antibiotics. (Current Controlled Trials number, ISRCTN51767272 [controlled-trials.com].).
呼吸机相关性肺炎诊断技术的随机试验 背景：需要机械通气的重症患者有发生呼吸机相关性肺炎的风险。目前关于疑似呼吸机相关性肺炎患者的最佳诊断方法的数据存在争议。 方法：在一项多中心试验中，我们将接受机械通气并在重症监护室(ICU)住院4天后疑似发生呼吸机相关性肺炎的免疫功能正常的成人随机分配至接受支气管肺泡灌洗液定量培养或气管内抽吸物非定量培养.排除已知定植或感染假单胞菌或耐甲氧西林金黄色葡萄球菌的患者。所有患者均开始抗生素经验性治疗，直至获得培养结果，在培养结果可用时，使用靶向治疗方案中止或减少抗生素剂量或数量，或者如果培养结果为阴性，则恢复抗生素治疗，以治疗入组前状况。 结果：我们在加拿大和美国的28个ICU纳入了740例患者。支气管肺泡灌洗组和气管内吸引组的主要结局（28天死亡率）无显著差异（分别为18.9%和18.4%；P = 0.94）。支气管肺泡灌洗组和气管内抽吸组的靶向治疗率（分别为74.2%和74.6%；P = 0.90）、无抗生素存活天数（10.4±7.5和10.6±7.9，P = 0.86）和最大器官功能障碍评分（均值[+/-SD]，8.3±3.6和8.6±4.0；P = 0.26）也相似。两组在ICU或医院的住院时间没有显著差异。 结论：呼吸机相关性肺炎的两种诊断策略-使用支气管肺泡灌洗液定量培养的支气管肺泡灌洗和使用抽吸物非定量培养的气管内抽吸-与相似的临床结局和相似的抗生素总体使用相关。（当前对照试验编号，ISRCTN51767272[对照试验。com].）。
Keywords: Humans; Female; Male; Middle Aged; Critical Illness; Intensive Care Units; Length of Stay; Anti-Bacterial Agents/*therapeutic use; Bronchoscopy; *Bronchoalveolar Lavage; Bronchoalveolar Lavage Fluid/microbiology; Pneumonia, Ventilator-Associated/*diagnosis/drug therapy/mortality; Trachea/*microbiology

Intensive care of patients with HIV infection - Saccente, Michael (The New England journal of medicine, 2006)
HIV感染患者的重症监护
Keywords: Humans; Critical Illness; *Patient Compliance; Anti-Retroviral Agents/*therapeutic use; HIV Infections/*drug therapy

Intensive care of patients with HIV infection - Huang, Laurence; Quartin, Andrew; Jones, Denis; Havlir, Diane V. (The New England journal of medicine, 2006)
HIV感染患者的重症监护
Keywords: Humans; Critical Illness/*therapy; Informed Consent; *Critical Care/legislation & jurisprudence/standards; AIDS Serodiagnosis; Anti-Retroviral Agents/adverse effects/*therapeutic use; Antiretroviral Therapy, Highly Active; Disclosure; Drug Interactions; Heart Diseases/complications/therapy; HIV Infections/complications/diagnosis/*drug therapy; Kidney Diseases/complications/therapy; Liver Diseases/complications/therapy; Lung Diseases/complications/therapy

Efficacy and safety of corticosteroids for persistent acute respiratory distress syndrome - Steinberg, Kenneth P.; Hudson, Leonard D.; Goodman, Richard B.; Hough, Catherine Lee; Lanken, Paul N.; Hyzy, Robert; Thompson, B. Taylor; Ancukiewicz, Marek (The New England journal of medicine, 2006)
BACKGROUND: Persistent acute respiratory distress syndrome (ARDS) is characterized by excessive fibroproliferation, ongoing inflammation, prolonged mechanical ventilation, and a substantial risk of death. Because previous reports suggested that corticosteroids may improve survival, we performed a multicenter, randomized controlled trial of corticosteroids in patients with persistent ARDS. METHODS: We randomly assigned 180 patients with ARDS of at least seven days' duration to receive either methylprednisolone or placebo in a double-blind fashion. The primary end point was mortality at 60 days. Secondary end points included the number of ventilator-free days and organ-failure-free days, biochemical markers of inflammation and fibroproliferation, and infectious complications. RESULTS: At 60 days, the hospital mortality rate was 28.6 percent in the placebo group (95 percent confidence interval, 20.3 to 38.6 percent) and 29.2 percent in the methylprednisolone group (95 percent confidence interval, 20.8 to 39.4 percent; P=1.0); at 180 days, the rates were 31.9 percent (95 percent confidence interval, 23.2 to 42.0 percent) and 31.5 percent (95 percent confidence interval, 22.8 to 41.7 percent; P=1.0), respectively. Methylprednisolone was associated with significantly increased 60- and 180-day mortality rates among patients enrolled at least 14 days after the onset of ARDS. Methylprednisolone increased the number of ventilator-free and shock-free days during the first 28 days in association with an improvement in oxygenation, respiratory-system compliance, and blood pressure with fewer days of vasopressor therapy. As compared with placebo, methylprednisolone did not increase the rate of infectious complications but was associated with a higher rate of neuromuscular weakness. CONCLUSIONS: These results do not support the routine use of methylprednisolone for persistent ARDS despite the improvement in cardiopulmonary physiology. In addition, starting methylprednisolone therapy more than two weeks after the onset of ARDS may increase the risk of death. (ClinicalTrials.gov number, NCT00295269.).
糖皮质激素治疗持续性急性呼吸窘迫综合征的疗效和安全性 背景：持续性急性呼吸窘迫综合征(ARDS)的特征是过度纤维增生、持续炎症、长期机械通气和显著的死亡风险。由于之前的报道提示皮质类固醇可能改善生存，我们在持续性ARDS患者中进行了一项皮质类固醇的多中心、随机对照试验。 方法：我们以双盲的方式将180例ARDS患者随机分配至甲泼尼龙组或安慰剂组，这些患者病程至少7天。主要终点为60天时的死亡率。次要终点包括无呼吸机天数和无器官衰竭天数、炎症和纤维增生的生化标志物以及感染性并发症。 结果：60天时，安慰剂组的住院死亡率为28.6%（95%置信区间，20.3-38.6%），甲泼尼龙组为29.2%（95%置信区间，20.8-39.4%；P = 1.0）；180天时，两组的住院死亡率为31.9%（95%置信区间，23.2%-42.0%）和31.5%（95%置信区间，22.8-41.7%；P = 1.0）。在ARDS发作后至少14天入组的患者中，甲泼尼龙与60天和180天死亡率显著增加相关。甲泼尼龙增加前28天无呼吸机和无休克的天数，与氧合、呼吸系统依从性和血压改善以及较少的血管加压药治疗天数相关。与安慰剂相比，甲泼尼龙未增加感染并发症的发生率，但与神经肌肉无力的发生率较高相关。 结论：尽管心肺生理学有所改善，但这些结果不支持常规使用甲泼尼龙治疗持续性ARDS。此外，ARDS发生后2周以上开始甲泼尼龙治疗可能增加死亡风险。（ClinicalTrials.gov数量，NCT00295269）。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Double-Blind Method; Survival Analysis; Critical Illness; Adult; Respiration, Artificial; Hospital Mortality; Oxygen/blood; Combined Modality Therapy; Shock, Septic/etiology; Inflammation/drug therapy; Blood Glucose/analysis; Blood Pressure/drug effects; Injections, Intravenous; Pneumonia/etiology; Glucocorticoids/adverse effects/pharmacology/*therapeutic use; Methylprednisolone/adverse effects/pharmacology/*therapeutic use; Muscle Weakness/chemically induced; Respiratory Distress Syndrome/*drug therapy/mortality/physiopathology

Videos in Clinical Medicine. Placement of an arterial line. - Tegtmeyer, Ken; Brady, Glenn; Lai, Susanna; Hodo, Richard; Braner, Dana (The New England journal of medicine, 2006)
临床医学视频。放置动脉导管。
Keywords: Humans; Catheterization, Peripheral/instrumentation/*methods

Intensive insulin in intensive care - Malhotra, Atul (The New England journal of medicine, 2006)
重症监护中强化胰岛素
Keywords: Humans; APACHE; Intensive Care Units; *Critical Care; Critical Illness/mortality/*therapy; Blood Glucose; Hypoglycemic Agents/*administration & dosage; Insulin/*administration & dosage; Kidney Diseases/prevention & control

Intensive insulin therapy in the medical ICU - Van den Berghe, Greet; Wilmer, Alexander; Hermans, Greet; Meersseman, Wouter; Wouters, Pieter J.; Milants, Ilse; Van Wijngaerden, Eric; Bobbaers, Herman; Bouillon, Roger (The New England journal of medicine, 2006)
BACKGROUND: Intensive insulin therapy reduces morbidity and mortality in patients in surgical intensive care units (ICUs), but its role in patients in medical ICUs is unknown. METHODS: In a prospective, randomized, controlled study of adult patients admitted to our medical ICU, we studied patients who were considered to need intensive care for at least three days. On admission, patients were randomly assigned to strict normalization of blood glucose levels (80 to 110 mg per deciliter [4.4 to 6.1 mmol per liter]) with the use of insulin infusion or to conventional therapy (insulin administered when the blood glucose level exceeded 215 mg per deciliter [12 mmol per liter], with the infusion tapered when the level fell below 180 mg per deciliter [10 mmol per liter]). There was a history of diabetes in 16.9 percent of the patients. RESULTS: In the intention-to-treat analysis of 1200 patients, intensive insulin therapy reduced blood glucose levels but did not significantly reduce in-hospital mortality (40.0 percent in the conventional-treatment group vs. 37.3 percent in the intensive-treatment group, P=0.33). However, morbidity was significantly reduced by the prevention of newly acquired kidney injury, accelerated weaning from mechanical ventilation, and accelerated discharge from the ICU and the hospital. Although length of stay in the ICU could not be predicted on admission, among 433 patients who stayed in the ICU for less than three days, mortality was greater among those receiving intensive insulin therapy. In contrast, among 767 patients who stayed in the ICU for three or more days, in-hospital mortality in the 386 who received intensive insulin therapy was reduced from 52.5 to 43.0 percent (P=0.009) and morbidity was also reduced. CONCLUSIONS: Intensive insulin therapy significantly reduced morbidity but not mortality among all patients in the medical ICU. Although the risk of subsequent death and disease was reduced in patients treated for three or more days, these patients could not be identified before therapy. Further studies are needed to confirm these preliminary data. (ClinicalTrials.gov number, NCT00115479.)
内科ICU中的胰岛素强化治疗 背景：胰岛素强化治疗可降低外科重症监护室(ICU)患者的发病率和死亡率，但其在内科ICU患者中的作用尚不清楚。 方法：在一项对入住我们的内科ICU的成人患者进行的前瞻性、随机、对照研究中，我们对被认为需要重症监护至少3天的患者进行了研究。入院时，患者被随机分配至使用胰岛素输注使血糖水平严格正常化(80-110 mg/dl[4.4-6.1 mmol/l])或常规治疗（当血糖水平超过215 mg/dl[12 mmol/l]时给予胰岛素），当水平降至180 mg/dl[10 mmol/l]以下时，输注逐渐减量）。16.9%的患者有糖尿病史。 结果：在1200例患者的意向治疗分析中，强化胰岛素治疗降低了血糖水平，但未显著降低住院死亡率（常规治疗组40.0%vs.强化治疗组37.3%，P = 0.33）。但是，通过预防新发肾损伤、加速停止机械通气和加速离开ICU和医院，发病率显著降低。虽然入院时无法预测ICU住院时间，但在433例入住ICU小于3天的患者中，接受胰岛素强化治疗的患者死亡率更高。相反，在ICU住院3天或3天以上的767例患者中，386例接受强化胰岛素治疗的患者的院内死亡率从52.5%降至43.0%(P = 0.009)，发病率也有所降低。 结论：胰岛素强化治疗显著降低了内科ICU所有患者的发病率，但未降低死亡率。尽管接受3天或3天以上治疗的患者后续死亡和疾病的风险降低，但在治疗前无法确定这些患者。需要进一步研究来证实这些初步数据。（ClinicalTrials.gov数量，NCT00115479。）
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Prognosis; Survival Analysis; Aged; APACHE; Intensive Care Units; Length of Stay; Hospital Mortality; Proportional Hazards Models; *Critical Care; Critical Illness/classification/mortality/*therapy; Blood Glucose/drug effects; Hypoglycemic Agents/*administration & dosage; Insulin/*administration & dosage; Kidney Diseases/prevention & control; Ventilator Weaning

Cardiac replacement with a total artificial heart as a bridge to transplantation - Copeland, Jack G.; Smith, Richard G.; Arabia, Francisco A.; Nolan, Paul E.; Sethi, Gulshan K.; Tsau, Pei H.; McClellan, Douglas; Slepian, Marvin J. (The New England journal of medicine, 2004)
BACKGROUND: The CardioWest Total Artificial Heart orthotopically replaces both native cardiac ventricles and all cardiac valves, thus eliminating problems commonly seen in the bridge to transplantation with left ventricular and biventricular assist devices, such as right heart failure, valvular regurgitation, cardiac arrhythmias, ventricular clots, intraventricular communications, and low blood flows. METHODS: We conducted a nonrandomized, prospective study in five centers with the use of historical controls. The purpose was to assess the safety and efficacy of the CardioWest Total Artificial Heart in transplant-eligible patients at risk for imminent death from irreversible biventricular cardiac failure. The primary end points included the rates of survival to heart transplantation and of survival after transplantation. RESULTS: Eighty-one patients received the artificial-heart device. The rate of survival to transplantation was 79 percent (95 percent confidence interval, 68 to 87 percent). Of the 35 control patients who met the same entry criteria but did not receive the artificial heart, 46 percent survived to transplantation (P<0.001). Overall, the one-year survival rate among the patients who received the artificial heart was 70 percent, as compared with 31 percent among the controls (P<0.001). One-year and five-year survival rates after transplantation among patients who had received a total artificial heart as a bridge to transplantation were 86 and 64 percent. CONCLUSIONS: Implantation of the total artificial heart improved the rate of survival to cardiac transplantation and survival after transplantation. This device prevents death in critically ill patients who have irreversible biventricular failure and are candidates for cardiac transplantation.
采用全人工心脏作为移植过渡的心脏置换术 背景：CardioWest全人工心脏原位替代了自体心室和所有心脏瓣膜，从而消除了左心室和双心室辅助装置移植桥接中常见的问题，如右心衰竭、瓣膜反流、心律失常、心室凝块、脑室内交通，血流量较低。 方法：我们在5个中心使用历史对照进行了一项非随机、前瞻性研究。目的是评估CardioWest全人工心脏在有即将因不可逆双心室心力衰竭死亡风险的符合移植条件的患者中的安全性和有效性。主要终点包括心脏移植存活率和移植后存活率。 结果：81例患者接受了人工心脏装置。移植生存率为79%（95%置信区间，68-87%）。在符合相同入选标准但未接受人工心脏的35例对照患者中，46%的患者移植后存活(P < 0.001)。总体而言，接受人工心脏的患者的1年生存率为70%，而对照组为31%(P < 0.001)。在接受全人工心脏作为移植过渡的患者中，移植后1年和5年生存率分别为86%和64%。 结论：全人工心脏移植提高了心脏移植存活率和移植后存活率。该装置可预防患有不可逆双心室衰竭且适合心脏移植的重症患者死亡。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Critical Illness; Quality of Life; Survival Rate; *Heart Transplantation; Prosthesis Design; *Heart, Artificial/adverse effects; Heart Failure/mortality/*surgery; Hemorrhage/etiology/mortality; Infections/etiology/mortality; Prosthesis Failure

Is albumin safe? - Cook, Deborah (The New England journal of medicine, 2004)
白蛋白是否安全？
Keywords: Humans; Intensive Care Units; Critical Care; Critical Illness/mortality/*therapy; Albumins/adverse effects/*therapeutic use; Fluid Therapy/*methods; Hypovolemia/therapy; Sodium Chloride/*therapeutic use

A comparison of albumin and saline for fluid resuscitation in the intensive care unit - Finfer, Simon; Bellomo, Rinaldo; Boyce, Neil; French, Julie; Myburgh, John; Norton, Robyn (The New England journal of medicine, 2004)
BACKGROUND: It remains uncertain whether the choice of resuscitation fluid for patients in intensive care units (ICUs) affects survival. We conducted a multicenter, randomized, double-blind trial to compare the effect of fluid resuscitation with albumin or saline on mortality in a heterogeneous population of patients in the ICU. METHODS: We randomly assigned patients who had been admitted to the ICU to receive either 4 percent albumin or normal saline for intravascular-fluid resuscitation during the next 28 days. The primary outcome measure was death from any cause during the 28-day period after randomization. RESULTS: Of the 6997 patients who underwent randomization, 3497 were assigned to receive albumin and 3500 to receive saline; the two groups had similar baseline characteristics. There were 726 deaths in the albumin group, as compared with 729 deaths in the saline group (relative risk of death, 0.99; 95 percent confidence interval, 0.91 to 1.09; P=0.87). The proportion of patients with new single-organ and multiple-organ failure was similar in the two groups (P=0.85). There were no significant differences between the groups in the mean (+/-SD) numbers of days spent in the ICU (6.5+/-6.6 in the albumin group and 6.2+/-6.2 in the saline group, P=0.44), days spent in the hospital (15.3+/-9.6 and 15.6+/-9.6, respectively; P=0.30), days of mechanical ventilation (4.5+/-6.1 and 4.3+/-5.7, respectively; P=0.74), or days of renal-replacement therapy (0.5+/-2.3 and 0.4+/-2.0, respectively; P=0.41). CONCLUSIONS: In patients in the ICU, use of either 4 percent albumin or normal saline for fluid resuscitation results in similar outcomes at 28 days.
白蛋白与生理盐水在重症监护室液体复苏中的比较 背景：目前仍不确定重症监护室(ICU)患者选择液体复苏是否会影响生存率。我们进行了一项多中心、随机、双盲试验，以比较不同ICU患者人群中，白蛋白或生理盐水复苏对死亡率的影响。 方法：我们将患者随机分配，在接下来的28天内接受4%白蛋白或生理盐水进行血管内液体复苏。主要结局是随机分配后28天内全因死亡。 结果：在6997例接受随机分组的患者中，3497例被分配接受白蛋白，3500例接受生理盐水；两组的基线特征相似。白蛋白组726例患者死亡，相比之下，生理盐水组729例患者死亡（相对死亡风险0.99；95%置信区间0.91-1.09；P = 0.87）。两组中发生单器官和多器官功能衰竭的患者比例相似(P = 0.85)。两组在平均(+/-SD)ICU停留时间（白蛋白组为6.5±6.6，生理盐水组为6.2±6.2，P = 0.44）、住院通气时间（分别为15.3±9.6和15.6±9.6；P = 0.30）、机械通气天数（4.5±6.1和4.3±5.7，分别为(P = 0.74)或肾脏替代治疗的天数（分别为0.5±2.3和0.4±2.0；P = 0.41）。 结论：在ICU患者中，使用4%白蛋白或生理盐水进行液体复苏在28天时的结局相似。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Double-Blind Method; Survival Analysis; Intensive Care Units; Adult; Blood Pressure; Heart Rate; Risk; Critical Illness/mortality/*therapy; Fluid Therapy/*methods; Sodium Chloride/*therapeutic use; Albumins/*therapeutic use; Multiple Organ Failure/epidemiology; Hypovolemia/physiopathology/*therapy

Measurements of serum free cortisol in critically ill patients - Hamrahian, Amir H.; Oseni, Tawakalitu S.; Arafah, Baha M. (The New England journal of medicine, 2004)
BACKGROUND: Because more than 90 percent of circulating cortisol in human serum is protein-bound, changes in the binding proteins can alter measured serum total cortisol concentrations without influencing free concentrations of this hormone. We investigated the effect of decreased amounts of cortisol-binding proteins on serum total and free cortisol concentrations during critical illness, when glucocorticoid secretion is maximally stimulated. METHODS: Base-line serum total cortisol, cosyntropin-stimulated serum total cortisol, aldosterone, and free cortisol concentrations were measured in 66 critically ill patients and 33 healthy volunteers in groups that were similar with regard to sex and age. Of the 66 patients, 36 had hypoproteinemia (albumin concentration, 2.5 g per deciliter or less), and 30 had near-normal serum albumin concentrations (above 2.5 g per deciliter). RESULTS: Base-line and cosyntropin-stimulated serum total cortisol concentrations were lower in the patients with hypoproteinemia than in those with near-normal serum albumin concentrations (P<0.001). However, the mean (+/-SD) base-line serum free cortisol concentrations were similar in the two groups of patients (5.1+/-4.1 and 5.2+/-3.5 microg per deciliter [140.7+/-113.1 and 143.5+/-96.6 nmol per liter]) and were several times higher than the values in controls (0.6+/-0.3 microg per deciliter [16.6+/-8.3 nmol per liter], P<0.001 for both comparisons). Cosyntropin-stimulated serum total cortisol concentrations were subnormal (18.5 microg per deciliter [510.4 nmol per liter] or less) in 14 of the patients, all of whom had hypoproteinemia. In all 66 patients, including these 14 who had hypoproteinemia, the base-line and cosyntropin-stimulated serum free cortisol concentrations were high-normal or elevated. CONCLUSIONS: During critical illness, glucocorticoid secretion markedly increases, but the increase is not discernible when only the serum total cortisol concentration is measured. In this study, nearly 40 percent of critically ill patients with hypoproteinemia had subnormal serum total cortisol concentrations, even though their adrenal function was normal. Measuring serum free cortisol concentrations in critically ill patients with hypoproteinemia may help prevent the unnecessary use of glucocorticoid therapy.
重症患者血清游离皮质醇的测定 背景：由于人血清中超过90%的循环皮质醇与蛋白结合，因此结合蛋白的变化可以改变测量的血清总皮质醇浓度，而不影响该激素的游离浓度。我们研究了危重疾病期间（当糖皮质激素分泌受到最大刺激时）皮质醇结合蛋白量降低对血清总皮质醇和游离皮质醇浓度的影响。 方法：66例重症患者和33例健康志愿者在性别和年龄相似的组中测量了基线血清总皮质醇、促皮质素刺激的血清总皮质醇、醛固酮和游离皮质醇浓度。在66例患者中，36例有低蛋白血症（白蛋白浓度，2.5 g/dl或更低），30例有接近正常的血清白蛋白浓度（高于2.5 g/dl）。 结果：低蛋白血症患者的基线和促皮质素刺激的血清总皮质醇浓度低于接近正常血清白蛋白浓度的患者(P < 0.001)。然而，两组患者的平均(+/-SD)基线血清游离皮质醇浓度相似（5.1±4.1和5.2±3.5 μg/dl[140.7±113.1和143.5±96.6 nmol/l]），比对照组的值高数倍（0.6±0.3 μg/dl[16.6±8.3 nmol/l]，P < 0.001）。在14例患者中，促皮质素刺激的血清总皮质醇浓度低于正常（18.5 μg/dl[510.4 nmol/l]或更低），所有患者均有低蛋白血症。在所有66例患者中（包括这14例低蛋白血症患者），基线和促皮质素刺激的血清游离皮质醇浓度高-正常或升高。 结论：在危重病期间，糖皮质激素分泌显著增加，但仅测定血清总皮质醇浓度时，这种增加并不明显。在本研究中，近40%的低蛋白血症重症患者血清总皮质醇浓度低于正常，尽管他们的肾上腺功能正常。测量低蛋白血症重症患者的血清游离皮质醇浓度可能有助于预防不必要的糖皮质激素治疗。
Keywords: Humans; Middle Aged; Aged; APACHE; Regression Analysis; Hydrocortisone/*blood; *Critical Illness/classification; Adrenal Insufficiency/*blood/diagnosis; Adrenocorticotropic Hormone/blood; Aldosterone/blood; Cosyntropin/pharmacology; Hypoalbuminemia/blood; Hypoproteinemia/blood/complications; Pituitary-Adrenal System/*physiopathology

Glucocorticoid therapy in the intensive care unit - Loriaux, Lynn (The New England journal of medicine, 2004)
重症监护室的糖皮质激素治疗
Keywords: Humans; Intensive Care Units; Critical Illness/*therapy; Glucocorticoids/*therapeutic use; Hydrocortisone/*blood; Hypoalbuminemia/blood; Adrenal Insufficiency/*blood/diagnosis/drug therapy; Shock/drug therapy

Case records of the Massachusetts General Hospital. Weekly clinicopathological exercises. Case 6-2004. A 35-year-old woman with extensive, deep burns from a nightclub fire. - Sheridan, Robert L.; Schulz, John T.; Ryan, Colleen M.; McGinnis, Paul J. (The New England journal of medicine, 2004)
麻省总医院的病例记录。每周进行临床病理学活动。病例6-2004。一名35岁的女性在夜总会大面积深度烧伤。
Keywords: Humans; Female; Resuscitation; Adult; Critical Care; Lung/diagnostic imaging; *Fires; Burns/blood/complications/pathology/*therapy; Pulmonary Edema/diagnostic imaging/etiology; Radiography

Withdrawal of mechanical ventilation in anticipation of death in the intensive care unit - Cook, Deborah; Rocker, Graeme; Marshall, John; Sjokvist, Peter; Dodek, Peter; Griffith, Lauren; Freitag, Andreas; Varon, Joseph; Bradley, Christine; Levy, Mitchell; Finfer, Simon; Hamielec, Cindy; et al. (The New England journal of medicine, 2003)
BACKGROUND: In critically ill patients who are receiving mechanical ventilation, the factors associated with physicians' decisions to withdraw ventilation in anticipation of death are unclear. The objective of this study was to examine the clinical determinants that were associated with the withdrawal of mechanical ventilation. METHODS: We studied adults who were receiving mechanical ventilation in 15 intensive care units, recording base-line physiological characteristics, daily Multiple Organ Dysfunction Scores, the patient's decision-making ability, the type of life support administered, the use of do-not-resuscitate orders, the physician's prediction of the patient's status, and the physician's perceptions of the patient's preferences about the use of life support. We examined the relation between these factors and withdrawal of mechanical ventilation, using Cox proportional-hazards regression analysis. RESULTS: Of 851 patients who were receiving mechanical ventilation, 539 (63.3 percent) were successfully weaned, 146 (17.2 percent) died while receiving mechanical ventilation, and 166 (19.5 percent) had mechanical ventilation withdrawn. The need for inotropes or vasopressors was associated with withdrawal of the ventilator (hazard ratio, 1.78; 95 percent confidence interval, 1.20 to 2.66; P=0.004), as were the physician's prediction that the patient's likelihood of survival in the intensive care unit was less than 10 percent (hazard ratio, 3.49; 95 percent confidence interval, 1.39 to 8.79; P=0.002), the physician's prediction that future cognitive function would be severely impaired (hazard ratio, 2.51; 95 percent confidence interval, 1.28 to 4.94; P=0.04), and the physician's perception that the patient did not want life support used (hazard ratio, 4.19; 95 percent confidence interval, 2.57 to 6.81; P<0.001). CONCLUSIONS: Rather than age or the severity of the illness and organ dysfunction, the strongest determinants of the withdrawal of ventilation in critically ill patients were the physician's perception that the patient preferred not to use life support, the physician's predictions of a low likelihood of survival in the intensive care unit and a high likelihood of poor cognitive function, and the use of inotropes or vasopressors.
预期在重症监护室死亡时撤除机械通气 背景：在接受机械通气的重症患者中，与医生预计死亡时撤除通气决定相关的因素尚不清楚。本研究的目的是调查与停止机械通气相关的临床决定因素。 方法：我们研究了15个重症监护室中接受机械通气的成人患者，记录了基线生理特征、每日多器官功能障碍评分、患者的决策能力、给予的生命支持类型、不使用复苏医嘱、医生对患者状态的预测，以及医生对患者对使用生命支持的偏好的看法。我们使用Cox比例风险回归分析检验了这些因素与撤除机械通气之间的关系。 结果：在851例接受机械通气的患者中，539例(63.3%)成功撤机，146例(17.2%)在接受机械通气时死亡，166例(19.5%)撤除机械通气。正性肌力药或血管加压药的需求与停用呼吸机相关（风险比，1.78；95%置信区间，1.20-2.66；P = 0.004），与医生预测的一样，患者在重症监护室的生存可能性低于10%（风险比，3.49；95%置信区间，1.39至8.79；P = 0.002），医生预测未来认知功能将严重受损（风险比，2.51；95%置信区间，1.28至4.94；P = 0.04），以及医生认为患者不希望使用生命支持的看法（风险比，4.19；95%置信区间，2.57至6.81；P < 0.001）。 结论：与年龄或疾病和器官功能障碍的严重程度不同，决定重症患者停止通气的最主要因素是医生认为患者不愿意使用生命支持，医生预测患者在重症监护室的生存可能性较低，认知功能较差以及使用正性肌力药或血管加压药的可能性较高。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Critical Illness; Intensive Care Units; Adult; Analysis of Variance; Outcome Assessment, Health Care; Severity of Illness Index; Age Factors; *Respiration, Artificial; Vasoconstrictor Agents/therapeutic use; *Life Support Care; Decision Making; *Withholding Treatment; Cardiotonic Agents/therapeutic use; Death and Euthanasia; Empirical Approach; Ventilator Weaning; *Professional-Family Relations; Advance Directives; Regression Analysis

Nitroprusside in critically ill patients with left ventricular dysfunction and aortic stenosis - Khot, Umesh N.; Novaro, Gian M.; PopoviÄ‡, Zoran B.; Mills, Roger M.; Thomas, James D.; Tuzcu, E. Murat; Hammer, Donald; Nissen, Steven E.; Francis, Gary S. (The New England journal of medicine, 2003)
BACKGROUND: Vasodilators are considered to be contraindicated in patients with severe aortic stenosis because of concern that they may precipitate life-threatening hypotension. However, vasodilators such as nitroprusside may improve myocardial performance if peripheral vasoconstriction is contributing to afterload. METHODS: We determined the response to intravenous nitroprusside in 25 patients with severe aortic stenosis and left ventricular systolic dysfunction. Patients were included in the study if they had been admitted to the intensive care unit for invasive hemodynamic monitoring of heart failure and if they had a depressed ejection fraction (<or=0.35), severe aortic stenosis (aortic-valve area, <or=1 cm2), and a depressed cardiac index (<or=2.2 liters per minute per square meter). Patients were excluded if they had hypotension, defined as either the need for intravenous inotropic or pressor agents or a low mean systemic arterial pressure (<60 mm Hg). Patients were enrolled irrespective of other, coexisting valve disease or coronary artery disease. RESULTS: At base line, the mean (+/-SD) ejection fraction was 0.21+/-0.08; the aortic-valve area was 0.6+/-0.2 cm2, with peak and mean gradients of 65+/-37 and 39+/-23 mm Hg, respectively; and the cardiac index was 1.60+/-0.35 liters per minute per square meter. After six hours of therapy with nitroprusside (at which time the dose had been increased to a mean of 103+/-67 microg per minute), the cardiac index had increased to 2.22+/-0.44 liters per minute per square meter (P<0.001 for the comparison with base line). After 24 hours of nitroprusside infusion (dose, 128+/-96 microg per minute), the cardiac index had increased further, to 2.52+/-0.55 liters per minute per square meter (P<0.001 for the comparison with base line). Nitroprusside was well tolerated and had minimal side effects. CONCLUSIONS: Nitroprusside rapidly and markedly improves cardiac function in patients with decompensated heart failure due to severe left ventricular systolic dysfunction and severe aortic stenosis. It provides a safe and effective bridge to aortic-valve replacement or oral vasodilator therapy in these critically ill patients.
硝普钠治疗左心室功能不全合并主动脉瓣狭窄的重症患者 背景：考虑到血管扩张剂可能诱发危及生命的低血压，因此认为血管扩张剂禁用于重度主动脉瓣狭窄患者。但是，如果外周血管收缩促进后负荷，血管扩张剂（如硝普钠）可改善心肌功能。 方法：我们确定了25例重度主动脉瓣狭窄和左心室收缩功能不全患者对静脉硝普钠的反应。如果患者入住重症监护室进行有创性心力衰竭血液动力学监测，射血分数降低(≤0.35)、重度主动脉瓣狭窄（主动脉瓣区，≤1 cm2）和心脏指数降低(≤2.2 l/min/m2)，则纳入研究。如果患者出现低血压（定义为需要静脉正性肌力药或加压药或平均体循环动脉压较低[< 60 mmHg]），则将其排除。患者入组时不考虑其他共存的瓣膜疾病或冠状动脉疾病。 结果：在基线，平均(+/-SD)射血分数为0.21±0.08；主动脉瓣区为0.6±0.2 cm2，峰值和平均梯度分别为65±37和39±23 mmHg；心脏指数为1.60±0.35L/分/平方米。硝普盐治疗6小时后（此时剂量已增加至平均103±67 μg/min），心脏指数已增加至2.22±0.44 l/min/m2（与基线相比，P < 0.001）。硝普盐输注24小时后（剂量为128±96 μg/分钟），心脏指数进一步增加，达到2.52±0.55L/分钟/平方米（与基线相比，P < 0.001）。硝普钠耐受性良好，副作用极小。 结论：硝普钠可快速、显著改善因严重左心室收缩功能不全和严重主动脉瓣狭窄引起的失代偿性心力衰竭患者的心功能。为此类重症患者的主动脉瓣置换或口服血管扩张剂治疗提供了一种安全有效的过渡。
Keywords: Humans; Female; Male; Prospective Studies; Aged; Critical Illness; Stroke Volume; Hemodynamics/drug effects; Pressure; Aortic Valve; Aortic Valve Stenosis/classification/complications/*drug therapy/physiopathology; Heart Failure/*drug therapy/etiology/physiopathology; Nitroprusside/adverse effects/*therapeutic use; Non-programmatic; Vasodilator Agents/adverse effects/*therapeutic use; Ventricular Dysfunction, Left/complications

Neuromuscular sequelae of critical illness - Hudson, Leonard D.; Lee, Catherine M. (The New England journal of medicine, 2003)
危重疾病的神经肌肉后遗症
Keywords: Humans; Risk Factors; Follow-Up Studies; Quality of Life; Survivors; *Critical Illness; Respiratory Distress Syndrome/*complications; Fatigue/*etiology; Muscle Weakness/*etiology; Muscular Diseases/etiology; Polyneuropathies/etiology

Corticosteroid insufficiency in acutely ill patients - Cooper, Mark S.; Stewart, Paul M. (The New England journal of medicine, 2003)
急性发病患者中的糖皮质激素不足
Keywords: Humans; Critical Illness; Acute Disease; Glucocorticoids/therapeutic use; Hydrocortisone/blood; Adrenal Cortex Hormones/*deficiency/*therapeutic use; Adrenal Insufficiency/*diagnosis/*drug therapy; Cosyntropin; Hypothalamo-Hypophyseal System/physiology/*physiopathology; Pituitary-Adrenal System/physiology/*physiopathology; Shock, Septic/drug therapy

Progress in research on pulmonary-artery catheters - Parsons, Polly E. (The New England journal of medicine, 2003)
肺动脉导管的研究进展
Keywords: Humans; Risk Factors; Outcome Assessment, Health Care; Hospital Mortality; Critical Care/methods; Research Design; *Catheterization, Swan-Ganz; Perioperative Care/*methods; Surgical Procedures, Operative/*mortality

Daily hemodialysis and the outcome of acute renal failure - Schiffl, Helmut; Lang, Susanne M.; Fischer, Rainald (The New England journal of medicine, 2002)
BACKGROUND: Intermittent hemodialysis is widely used as renal-replacement therapy in patients with acute renal failure, but an adequate dose has not been defined. We performed a prospective study to determine the effect of daily intermittent hemodialysis, as compared with conventional (alternate-day) intermittent hemodialysis, on survival among patients with acute renal failure. METHODS: A total of 160 patients with acute renal failure were assigned to receive daily or conventional intermittent hemodialysis. Survival was the primary end point of the study. The duration of acute renal failure and the frequency of therapy-related complications were secondary end points. RESULTS: The two study groups were similar with respect to age, sex, cause and severity of acute renal failure, medical or surgical intensive care setting, and the score on the Acute Physiology, Age, and Chronic Health Evaluation. Daily hemodialysis resulted in better control of uremia, fewer hypotensive episodes during hemodialysis, and more rapid resolution of acute renal failure (mean [+/-SD], 9+/-2 vs. 16+/-6 days; P=0.001) than did conventional hemodialysis. The mortality rate, according to the intention-to-treat analysis, was 28 percent for daily dialysis and 46 percent for alternate-day dialysis (P=0.01). In a multiple regression analysis, less frequent hemodialysis (on alternate days, as opposed to daily) was an independent risk factor for death. CONCLUSIONS: The high mortality rate among critically ill patients with acute renal failure who require renal-replacement therapy is related to both coexisting conditions and uremic damage to other organ systems. Intensive hemodialysis reduces mortality without increasing hemodynamically induced morbidity.
每日血液透析和急性肾衰竭的结局 背景：间歇性血液透析广泛用作急性肾功能衰竭患者的肾脏替代治疗，但尚未确定足够的剂量。我们进行了一项前瞻性研究，以确定每日间歇性血液透析与常规（隔日）间歇性血液透析相比对急性肾衰竭患者生存率的影响。 方法：共有160例急性肾功能衰竭患者被分配接受每日或常规间歇性血液透析。生存期是研究的主要终点。急性肾衰竭的持续时间和治疗相关并发症的频率为次要终点。 结果：两个研究组在年龄、性别、急性肾衰竭的原因和严重程度、内科或外科重症监护环境以及急性生理学、年龄和慢性健康评估的评分方面相似。与常规血液透析相比，每日血液透析能更好地控制尿毒症、减少血液透析期间的低血压发作、更快地解决急性肾功能衰竭（平均[+/-SD]，9±2 vs. 16±6天；P = 0.001）。根据意向治疗分析，每日透析的死亡率为28%，隔日透析的死亡率为46%(P = 0.01)。在一项多元回归分析中，不频繁血液透析（隔日进行，而不是每天）是死亡的独立风险因素。 结论：需要肾脏替代治疗的急性肾功能衰竭重症患者中的高死亡率与共存疾病和其他器官系统的尿毒症性损伤相关。强化血液透析可降低死亡率，而不增加血液动力学诱导的发病率。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Prospective Studies; APACHE; Critical Illness; Logistic Models; Odds Ratio; Sepsis/complications; *Renal Dialysis; Acute Kidney Injury/classification/complications/mortality/*therapy; Oliguria/etiology

Hemodynamic and metabolic therapy in critically ill patients - Evans, T. W. (The New England journal of medicine, 2001)
重症患者的血液动力学和代谢治疗
Keywords: Hemodynamics; Humans; Hospital Mortality; Critical Illness/therapy; Critical Care/methods; *Monitoring, Physiologic; Blood Glucose/drug effects; Hypoglycemic Agents/*therapeutic use; Insulin/*therapeutic use; Postoperative Care/*methods; Sepsis/physiopathology/*therapy

Intensive insulin therapy in critically ill patients - van den Berghe, G.; Wouters, P.; Weekers, F.; Verwaest, C.; Bruyninckx, F.; Schetz, M.; Vlasselaers, D.; Ferdinande, P.; Lauwers, P.; Bouillon, R. (The New England journal of medicine, 2001)
BACKGROUND: Hyperglycemia and insulin resistance are common in critically ill patients, even if they have not previously had diabetes. Whether the normalization of blood glucose levels with insulin therapy improves the prognosis for such patients is not known. METHODS: We performed a prospective, randomized, controlled study involving adults admitted to our surgical intensive care unit who were receiving mechanical ventilation. On admission, patients were randomly assigned to receive intensive insulin therapy (maintenance of blood glucose at a level between 80 and 110 mg per deciliter [4.4 and 6.1 mmol per liter]) or conventional treatment (infusion of insulin only if the blood glucose level exceeded 215 mg per deciliter [11.9 mmol per liter] and maintenance of glucose at a level between 180 and 200 mg per deciliter [10.0 and 11.1 mmol per liter]). RESULTS: At 12 months, with a total of 1548 patients enrolled, intensive insulin therapy reduced mortality during intensive care from 8.0 percent with conventional treatment to 4.6 percent (P<0.04, with adjustment for sequential analyses). The benefit of intensive insulin therapy was attributable to its effect on mortality among patients who remained in the intensive care unit for more than five days (20.2 percent with conventional treatment, as compared with 10.6 percent with intensive insulin therapy, P=0.005). The greatest reduction in mortality involved deaths due to multiple-organ failure with a proven septic focus. Intensive insulin therapy also reduced overall in-hospital mortality by 34 percent, bloodstream infections by 46 percent, acute renal failure requiring dialysis or hemofiltration by 41 percent, the median number of red-cell transfusions by 50 percent, and critical-illness polyneuropathy by 44 percent, and patients receiving intensive therapy were less likely to require prolonged mechanical ventilation and intensive care. CONCLUSIONS: Intensive insulin therapy to maintain blood glucose at or below 110 mg per deciliter reduces morbidity and mortality among critically ill patients in the surgical intensive care unit.
重症患者的胰岛素强化治疗 背景：高血糖和胰岛素抵抗在危重患者中很常见，即使他们既往未患糖尿病。胰岛素治疗使血糖水平正常化是否能改善此类患者的预后尚不清楚。 方法：我们进行了一项前瞻性随机对照研究，涉及入住我们外科重症监护室并接受机械通气的成人患者。入院时，患者被随机分配接受强化胰岛素治疗（血糖维持在80-110 mg/dl[4.4-6.1 mmol/l]）或常规治疗（仅当血糖水平超过215 mg/dl[11.9 mmol/l]时输注胰岛素并维持%___葡萄糖）%，在180至200 mg/dl[10.0至11.1 mmol/l]的水平）。 结果：12个月时，共入选1548例患者，强化胰岛素治疗使重症监护期间的死亡率从常规治疗的8.0%降低至4.6%（P < 0.04，调整序贯分析）。强化胰岛素治疗的获益可归因于其对留在重症监护室5天以上患者死亡率的影响（常规治疗组为20.2%，而强化胰岛素治疗组为10.6%，P = 0.005）。死亡的最大降幅涉及证实有败血症病灶的多器官衰竭所致的死亡。胰岛素强化治疗还使住院总死亡率降低了34%，血液感染降低了46%，需要透析或血液滤过的急性肾衰竭降低了41%，红细胞输注中位数降低了50%，危重多发性神经病变降低了44%，接受强化治疗的患者不太可能需要延长机械通气和重症监护。 结论：胰岛素强化治疗将血糖维持在≤110 mg/dl可降低外科重症监护室危重患者的发病率和死亡率。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Survival Analysis; APACHE; Intensive Care Units; Length of Stay; Respiration, Artificial; Critical Illness/*therapy; Critical Care/methods; Logistic Models; Postoperative Care/*methods; *Hospital Mortality; Blood Glucose/drug effects/metabolism; Hypoglycemic Agents/administration & dosage/*therapeutic use; Insulin/administration & dosage/*therapeutic use

Reversal of catabolism by beta-blockade after severe burns - Herndon, D. N.; Hart, D. W.; Wolf, S. E.; Chinkes, D. L.; Wolfe, R. R. (The New England journal of medicine, 2001)
BACKGROUND: The catecholamine-mediated hypermetabolic response to severe burns causes increased energy expenditure and muscle-protein catabolism. We hypothesized that blockade of beta-adrenergic stimulation with propranolol would decrease resting energy expenditure and muscle catabolism in patients with severe burns. METHODS: Twenty-five children with acute and severe burns (more than 40 percent of total body-surface area) were studied in a randomized trial. Thirteen received oral propranolol for at least two weeks, and 12 served as untreated controls. The dose of propranolol was adjusted to decrease the resting heart rate by 20 percent from each patient's base-line value. Resting energy expenditure and skeletal-muscle protein kinetics were measured before and after two weeks of beta-blockade (or no therapy, in controls). Body composition was measured serially throughout hospitalization. RESULTS: Patients in the control group and the propranolol group were similar with respect to age, weight, percentage of total body-surface area burned, percentage of body-surface area with third-degree burns, and length of time from injury to metabolic study. Beta-blockade decreased the heart rates and resting energy expenditure in the propranolol group, both as compared with the base-line values (P<0.001 and P=0.01, respectively) and as compared with the values in the control group (P=0.03 and P=0.001, respectively). The net muscle-protein balance increased by 82 percent over base-line values in the propranolol group (P=0.002), whereas it decreased by 27 percent in the control group (P not significant). The fat-free mass, as measured by whole-body potassium scanning, did not change substantially in the propranolol group, whereas it decreased by a mean (+/-SE) of 9+/-2 percent in the control group (P=0.003). CONCLUSIONS: In children with burns, treatment with propranolol during hospitalization attenuates hypermetabolism and reverses muscle-protein catabolism.
重度烧伤后β-受体阻滞剂逆转分解代谢 背景：儿茶酚胺介导的对重度烧伤的高代谢反应导致能量消耗和肌肉-蛋白质分解代谢增加。我们假设，用普萘洛尔阻断β-肾上腺素能刺激可降低重度烧伤患者的静息能量消耗和肌肉分解代谢。 方法：在一项随机试验中对25例急性和重度烧伤（超过体表面积的40%）儿童进行了研究。13例患者口服普萘洛尔至少2周，12例患者作为未治疗对照。调整普萘洛尔剂量，使静息心率较每例患者的基线值降低20%。β-受体阻滞剂治疗前和治疗2周后（或对照组不治疗），测量静息时能量消耗和骨骼-肌肉蛋白质动力学。在整个住院期间连续测量身体组成。 结果：对照组和普萘洛尔组的患者在年龄、体重、总体体表面积烧伤百分比、体表面积与三度烧伤百分比、从损伤到代谢研究的时间长度方面相似。与基线值（分别为P < 0.001和P = 0.01）和对照组值（分别为P = 0.03和P = 0.001）相比，β-受体阻滞剂降低了普萘洛尔组的心率和静息能量消耗。普萘洛尔组净肌肉-蛋白质平衡比基线值增加了82%(P = 0.002)，而对照组减少了27%（P无显著性）。普萘洛尔组通过全身钾扫描测量的去脂体重没有显著变化，而对照组平均(+/-SE)下降了9±2%(P = 0.003)。 结论：在烧伤儿童中，住院期间接受普萘洛尔治疗可减轻高代谢并逆转肌肉-蛋白质分解代谢。
Keywords: Humans; Female; Male; Child; Heart Rate/drug effects; Body Composition; Adrenergic beta-Antagonists/pharmacology/*therapeutic use; Burns/*drug therapy/metabolism/physiopathology; Energy Metabolism/*drug effects; Muscle Proteins/*metabolism; Muscle, Skeletal/drug effects/metabolism; Propranolol/pharmacology/*therapeutic use

Aspiration pneumonitis and aspiration pneumonia - Marik, P. E. (The New England journal of medicine, 2001)
吸入性肺炎和吸入性肺炎
Keywords: Humans; Critical Illness; Risk Factors; *Pneumonia, Aspiration/epidemiology/etiology/microbiology/therapy; Enteral Nutrition/adverse effects

Daily interruption of sedative infusions in critically ill patients - Hong, J. J.; Mazuski, J. E.; Shapiro, M. J. (The New England journal of medicine, 2000)
重症患者每日中断镇静剂输注
Keywords: Humans; Time Factors; Length of Stay; Critical Illness/*therapy; Drug Administration Schedule; *Respiration, Artificial; Consciousness; Hypnotics and Sedatives/*administration & dosage; Analgesics/administration & dosage

A wake-up call in the intensive care unit - Heffner, J. E. (The New England journal of medicine, 2000)
重症监护室的唤醒电话
Keywords: Humans; Intensive Care Units; Infusions, Intravenous; Critical Illness/*therapy; Drug Administration Schedule; *Respiration, Artificial; Hypnotics and Sedatives/*administration & dosage

Daily interruption of sedative infusions in critically ill patients undergoing mechanical ventilation - Kress, J. P.; Pohlman, A. S.; O'Connor, M. F.; Hall, J. B. (The New England journal of medicine, 2000)
BACKGROUND: Conous infusions of sedative drugs in the intensive care unit may prolong the duration of mechanical ventilation, prolong the length of stay in the intensive care unit and the hospital, impede efforts to perform daily neurologic examinations, and increase the need for tests to assess alterations in mental status. Whether regular interruption of such infusions might accelerate recovery is not known. METHODS: We conducted a randomized, controlled trial involving 128 adult patients who were receiving mechanical ventilation and continuous infusions of sedative drugs in a medical intensive care unit. In the intervention group, the sedative infusions were interrupted until the patients were awake, on a daily basis; in the control group, the infusions were interrupted only at the discretion of the clinicians in the intensive care unit. RESULTS: The median duration of mechanical ventilation was 4.9 days in the intervention group, as compared with 7.3 days in the control group (P=0.004), and the median length of stay in the intensive care unit was 6.4 days as compared with 9.9 days, respectively (P=0.02). Six of the patients in the intervention group (9 percent) underwent diagnostic testing to assess changes in mental status, as compared with 16 of the patients in the control group (27 percent, P=0.02). Complications (e.g., removal of the endotracheal tube by the patient) occurred in three of the patients in the intervention group (4 percent) and four of the patients in the control group (7 percent, P=0.88). CONCLUSIONS: In patients who are receiving mechanical ventilation, daily interruption of sedative-drug infusions decreases the duration of mechanical ventilation and the length of stay in the intensive care unit.
在接受机械通气的重症患者中，每日中断镇静剂输注 背景：在重症监护室内连续输注镇静药物可能会延长机械通气的持续时间，延长重症监护室和医院的住院时间，阻碍进行每日神经系统检查的努力，并增加评估精神状态改变的测试需求。尚不清楚定期中断此类输注是否会加速恢复。 方法：我们进行了一项随机对照试验，包括128例在内科重症监护室接受机械通气并持续输注镇静药物的成人患者。干预组每天中断镇静剂输注直至患者清醒；对照组仅在重症监护室临床医生决定下中断输注。 结果：干预组和对照组的中位机械通气持续时间分别为4.9天和7.3天(P = 0.004)，重症监护室的中位住院时间分别为6.4天和9.9天(P = 0.02)。干预组中有6例患者(9%)进行了诊断试验以评估精神状态的变化，而对照组中有16例患者(27%，P = 0.02)。干预组3例患者(4%)和对照组4例患者(7%，P = 0.88)发生了并发症（例如，患者拔除气管内导管）。 结论：在接受机械通气的患者中，每天中断镇静药物输注减少了机械通气的持续时间和重症监护室的住院时间。
Keywords: Humans; Female; Male; Middle Aged; Aged; Intensive Care Units; Length of Stay; Adult; Critical Illness/*therapy; Analgesics, Opioid/administration & dosage; Drug Administration Schedule; *Respiration, Artificial; Morphine/administration & dosage; Hypnotics and Sedatives/*administration & dosage; Midazolam/*administration & dosage; Propofol/*administration & dosage

Growth hormone therapy in critically ill patients - Demling, R. (The New England journal of medicine, 1999)
重症患者的生长激素治疗
Keywords: Humans; Drug Administration Schedule; Critical Illness/mortality/*therapy; Human Growth Hormone/administration & dosage/*adverse effects

Increased mortality associated with growth hormone treatment in critically ill adults - Takala, J.; Ruokonen, E.; Webster, N. R.; Nielsen, M. S.; Zandstra, D. F.; Vundelinckx, G.; Hinds, C. J. (The New England journal of medicine, 1999)
BACKGROUND: The administration of growth hormone can attenuate the catabolic response to injury, surgery, and sepsis. However, the effect of high doses of growth hormone on the length of stay in intensive care and in the hospital, the duration of mechanical ventilation, and the outcome in critically ill adults who are hospitalized for long periods is not known. METHODS: We carried out two prospective, multicenter, double-blind, randomized, placebo-controlled trials in parallel involving 247 Finnish patients and 285 patients in other European countries who had been in an intensive care unit for 5 to 7 days and who were expected to require intensive care for at least 10 days. The patients had had cardiac surgery, abdominal surgery, multiple trauma, or acute respiratory failure. The patients received either growth hormone (mean [+/-SD] daily dose, 0.10 +/- 0.02 mg per kilogram of body weight) or placebo until discharge from intensive care or for a maximum of 21 days. RESULTS: The in-hospital mortality rate was higher in the patients who received growth hormone than in those who did not (P<0.001 for both studies). In the Finnish study, the mortality rate was 39 percent in the growth hormone group, as compared with 20 percent in the placebo group. The respective rates in the multinational study were 44 percent and 18 percent. The relative risk of death for patients receiving growth hormone was 1.9 (95 percent confidence interval, 1.3 to 2.9) in the Finnish study and 2.4 (95 percent confidence interval, 1.6 to 3.5) in the multinational study. Among the survivors, the length of stay in intensive care and in the hospital and the duration of mechanical ventilation were prolonged in the growth hormone group. CONCLUSIONS: In patients with prolonged critical illness, high doses of growth hormone are associated with increased morbidity and mortality.
在危重成人中与生长激素治疗相关的死亡率增加 背景：生长激素给药可减弱对损伤、手术和败血症的分解代谢反应。但是，高剂量生长激素对长期住院的重症成人患者的重症监护和住院时间、机械通气持续时间和结局的影响未知。 方法：我们进行了2项前瞻性、多中心、双盲、随机、安慰剂对照平行试验，涉及247例芬兰患者和285例其他欧洲国家患者，这些患者已在重症监护室住院5至7天，预期需要重症监护至少10天。患者曾行心脏手术、腹部手术、多发伤或急性呼吸衰竭。患者接受生长激素（平均[±SD]日剂量，0.10±0.02 mg/kg体重）或安慰剂，直至离开重症监护病房或最多21天。 结果：接受生长激素治疗的患者的住院死亡率高于未接受生长激素治疗的患者（两项研究均为P < 0.001）。在芬兰的研究中，生长激素组的死亡率为39%，而安慰剂组为20%。多国研究中的相应比率分别为44%和18%。芬兰研究中接受生长激素治疗的患者的相对死亡风险为1.9（95%置信区间，1.3-2.9），多国研究中为2.4（95%置信区间，1.6-3.5）。在存活者中，生长激素组的重症监护和住院时间以及机械通气的持续时间延长。 结论：在长期危重疾病患者中，高剂量生长激素与发病率和死亡率增加相关。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Double-Blind Method; Aged; Adult; Critical Care; Adolescent; Hospital Mortality; Cause of Death; Risk; Critical Illness/*mortality/*therapy; Shock, Septic/etiology; Multiple Organ Failure/etiology; Energy Intake; Human Growth Hormone/administration & dosage/*adverse effects; Insulin-Like Growth Factor I/analysis

Transfusions in critically ill patients - Ely, E. W.; Bernard, G. R. (The New England journal of medicine, 1999)
重症患者的输血
Keywords: Humans; APACHE; Critical Care; *Erythrocyte Transfusion; *Hemoglobins; Critical Illness/classification/mortality/*therapy

A multicenter, randomized, controlled clinical trial of transfusion requirements in critical care. Transfusion Requirements in Critical Care Investigators, Canadian Critical Care Trials Group. - HÃ©bert, P. C.; Wells, G.; Blajchman, M. A.; Marshall, J.; Martin, C.; Pagliarello, G.; Tweeddale, M.; Schweitzer, I.; Yetisir, E. (The New England journal of medicine, 1999)
BACKGROUND: To determine whether a restrictive strategy of red-cell transfusion and a liberal strategy produced equivalent results in critically ill patients, we compared the rates of death from all causes at 30 days and the severity of organ dysfunction. METHODS: We enrolled 838 critically ill patients with euvolemia after initial treatment who had hemoglobin concentrations of less than 9.0 g per deciliter within 72 hours after admission to the intensive care unit and randomly assigned 418 patients to a restrictive strategy of transfusion, in which red cells were transfused if the hemoglobin concentration dropped below 7.0 g per deciliter and hemoglobin concentrations were maintained at 7.0 to 9.0 g per deciliter, and 420 patients to a liberal strategy, in which transfusions were given when the hemoglobin concentration fell below 10.0 g per deciliter and hemoglobin concentrations were maintained at 10.0 to 12.0 g per deciliter. RESULTS: Overall, 30-day mortality was similar in the two groups (18.7 percent vs. 23.3 percent, P= 0.11). However, the rates were significantly lower with the restrictive transfusion strategy among patients who were less acutely ill -- those with an Acute Physiology and Chronic Health Evaluation II score of < or =20 (8.7 percent in the restrictive-strategy group and 16.1 percent in the liberal-strategy group; P=0.03) -- and among patients who were less than 55 years of age (5.7 percent and 13.0 percent, respectively; P=0.02), but not among patients with clinically significant cardiac disease (20.5 percent and 22.9 percent, respectively; P=0.69). The mortality rate during hospitalization was significantly lower in the restrictive-strategy group (22.3 percent vs. 28.1 percent, P=0.05). CONCLUSIONS: A restrictive strategy of red-cell transfusion is at least as effective as and possibly superior to a liberal transfusion strategy in critically ill patients, with the possible exception of patients with acute myocardial infarction and unstable angina.
重症监护中输血需求的多中心、随机、对照临床试验。加拿大重症医学试验组重症医学研究者的输血要求。 背景：为了确定限制性红细胞输注策略和开放性策略在危重患者中是否产生相同的结果，我们比较了30天时全因死亡率和器官功能障碍的严重程度。 方法：我们入选了838例初始治疗后血容量正常的危重患者，这些患者在入住重症监护室后72小时内血红蛋白浓度低于9.0 g/dl，并将418例患者随机分配至限制性输血策略组，其中，如果血红蛋白浓度降至7.0 g/dl以下，则输注红细胞，血红蛋白浓度维持在7.0-9.0 g/dl，420例患者采用自由策略，其中，当血红蛋白浓度降至10.0 g/dl以下且血红蛋白浓度维持在10.0-12.0 g/dl时，进行输血。 结果：总体而言，两组的30天死亡率相似（18.7%对比23.3%，P = 0.11）。但是，在急性疾病较轻的患者中，限制性输血策略的发生率显著较低-急性生理学和慢性健康状况II评分≤20的患者（限制性策略组为8.7%，自由策略组为16.1%；P = 0.03）-在年龄小于55岁的患者中（分别为5.7%和13.0%；P = 0.02），但在有临床显著心脏疾病的患者中（分别为20.5%和22.9%；P = 0.69）。住院期间，限制策略组的死亡率显著较低（22.3%对比28.1%，P = 0.05）。 结论：在重症患者中，红细胞输注的限制性策略至少与自由输血策略一样有效，并可能优于自由输血策略，急性心肌梗死和不稳定型心绞痛患者可能除外。
Keywords: Humans; Female; Male; Middle Aged; Survival Analysis; Aged; APACHE; Intensive Care Units; Adult; Hospital Mortality; Logistic Models; Multiple Organ Failure; *Critical Care; Critical Illness/classification/mortality/*therapy; *Erythrocyte Transfusion/standards/statistics & numerical data; Hemoglobins/*analysis

Objective estimates of the probability of death from burn injuries - Ryan, C. M.; Schoenfeld, D. A.; Thorpe, W. P.; Sheridan, R. L.; Cassem, E. H.; Tompkins, R. G. (The New England journal of medicine, 1998)
BACKGROUND: Over the past 20 years, there has been remarkable improvement in the chances of survival of patients treated in burn centers. A simple, accurate system for objectively estimating the probability of death would be useful in counseling patients and making medical decisions. METHODS: We conducted a retrospective review of all 1665 patients with acute burn injuries admitted from 1990 to 1994 to Massachusetts General Hospital and the Shriners Burns Institute in Boston. Using logistic-regression analysis, we developed probability estimates for the prediction of mortality based on a minimal set of well-defined variables. The resulting mortality formula was used to determine whether changes in mortality have occurred since 1984, and it was tested prospectively on all 530 patients with acute burn injuries admitted in 1995 or 1996. RESULTS: Of the 1665 patients (mean [+/-SD] age, 21+/-20 years; mean burn size, 14+/-20 percent of body-surface area), 1598 (96 percent) lived to discharge. The mean length of stay was 21+/-29 days. Three risk factors for death were identified: age greater than 60 years, more than 40 percent of body-surface area burned, and inhalation injury. The mortality formula we developed predicts 0.3 percent, 3 percent, 33 percent, or approximately 90 percent mortality, depending on whether zero, one, two, or three risk factors are present. The results of the prospective test of the formula were similar. A large increase in the proportion of patients who chose not to be resuscitated complicated comparisons of mortality over time. CONCLUSIONS: The probability of mortality after burns is low and can be predicted soon after injury on the basis of simple, objective clinical criteria.
烧伤死亡概率的客观估计值 背景：在过去20年中，烧伤中心治疗患者的生存机会显著改善。一个简单、准确的客观估计死亡概率的系统将有助于向患者提供咨询和医疗决策。 方法：我们对1990年至1994年麻省总医院和波士顿Shriners Burns研究所收治的所有1665例急性烧伤患者进行了回顾性审查。使用logistic回归分析，我们基于最小的定义明确的变量集开发了预测死亡率的概率估计值。使用得出的死亡率公式确定自1984年以来死亡率是否发生变化，并在1995年或1996年入院的所有530例急性烧伤患者中进行前瞻性检验。 结果：在1665例患者（平均[+/-SD]年龄，21±20岁；平均烧伤面积，体表面积的14±20%）中，1598例(96%)存活至出院。平均住院时间为21±29天。确定了3个死亡风险因素：年龄大于60岁、体表面积烧伤超过40%和吸入性损伤。根据是否存在0、1、2或3个风险因素，我们开发的死亡率公式预测死亡率为0.3%、3%、33%或约90%。公式的前瞻性检验结果相似。选择不复苏的患者比例大幅增加使死亡率随时间的比较变得复杂。 结论：烧伤后死亡概率较低，可根据简单、客观的临床标准进行伤后早期预测。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Length of Stay; Adult; Aged, 80 and over; Adolescent; Risk Factors; Retrospective Studies; Child; Infant; Child, Preschool; Age Factors; Logistic Models; Probability; Resuscitation Orders; *Trauma Severity Indices; Burns, Inhalation/mortality; Burns/*classification/*mortality; Mortality/trends

Corticosteroid therapy in severe illness - Lamberts, S. W.; Bruining, H. A.; de Jong, F. H. (The New England journal of medicine, 1997)
重度疾病的皮质类固醇治疗
Keywords: Humans; Critical Illness/*therapy; Hemodynamics/drug effects; Adrenal Cortex Hormones/pharmacology/*therapeutic use; Adrenal Insufficiency/*drug therapy/physiopathology; Hypothalamo-Hypophyseal System/physiopathology; Pituitary-Adrenal System/physiopathology

Case records of the Massachusetts General Hospital. Weekly clinicopathological exercises. Case 11-1997. A 51-year-old man with chronic obstructive pulmonary disease and generalized muscle weakness. (The New England journal of medicine, 1997)
麻省总医院的病例记录。每周进行临床病理学活动。病例11-1997。1例51岁男性，患有慢性阻塞性肺病和全身肌无力。
Keywords: Humans; Male; Middle Aged; Critical Illness; Diagnosis, Differential; Acute Disease; Alcoholism/complications; Electromyography; Glucocorticoids/adverse effects/therapeutic use; Respiratory Insufficiency/etiology; Nervous System Diseases/diagnosis; Muscle Weakness/*etiology; Lung Diseases, Obstructive/complications; Methylprednisolone/adverse effects/therapeutic use; Muscle, Skeletal/*pathology; Muscular Diseases/complications/*pathology; Myofibrils/pathology

The role of critical care nurses in euthanasia and assisted suicide - Dunn, P. A. (The New England journal of medicine, 1996)
危重病护士在安乐死和协助自杀中的作用
Keywords: Humans; Critical Care; United States; Stress, Psychological; *Euthanasia, Active; *Nurse's Role; Death and Euthanasia; Empirical Approach; Morphine/administration & dosage; Intention; *Nursing; *Suicide, Assisted; Euthanasia; Euthanasia, Active, Voluntary; San Francisco Bay Area; Terminal Care/methods; Trust

The role of critical care nurses in euthanasia and assisted suicide - Asch, D. A. (The New England journal of medicine, 1996)
BACKGROUND: Euthanasia and assisted suicide has received considerable attention recently in medical literature, public discussion, and proposed state legislation. Almost all the discussion in this area has focused on the role of physicians. However, nurses--especially critical care nurses--may be in a special position to understand the wishes of patients and to act on this understanding. METHODS: I mailed a survey to 1600 critical care nurses in the United States, asking them to describe anonymously any requests from patients, family members or others acting for patients (surrogates), or physicians to perform euthanasia or assisted suicide, as well as their own practices. RESULTS: Of the 1139 nurses who responded (71 percent), 852 said they practices exclusively in intensive care units for adults in the United States. Of these 852 nurses, 141 (17 percent) reported that they had received requests from patients or family members to perform euthanasia or assist in suicide; 129 (16 percent of those for whom data were available) reported that they had engaged in euthanasia; and an additional 36 (4 percent) reported that they had hastened a patient's death by only pretending to provide life-sustaining treatment ordered by a physician. Some nurses reported engaging in these practices without the request for advance knowledge of physicians or others. The method of euthanasia most commonly described was the administration of a high dose of an opiate to a terminally ill patient. CONCLUSIONS: As public debate continues about euthanasia and assisted suicide, some critical care nurses in the United States are engaging in the practice.
危重病护士在安乐死和协助自杀中的作用 背景：安乐死和协助自杀最近在医学文献、公共讨论和提出的国家立法中受到相当重视。这个领域几乎所有的讨论都集中在医生的作用上。然而，护士——尤其是重症护理护士——可能处于一种特殊的位置，能够理解患者的意愿并根据这种理解采取行动。 方法：我将一份调查邮寄给美国1600名危重病护士，要求他们匿名描述患者、家庭成员或其他为患者（代理人）行事的人、或医生执行安乐死或协助自杀的任何请求，以及他们自己的实践。 结果：在1139名回应的护士(71%)中，852名表示他们只在美国的成人重症监护室工作。在这852名护士中，141名(17%)报告他们已收到患者或家庭成员要求实施安乐死或协助自杀的请求；129名（其中16%的数据可用）报告他们已实施安乐死；另有36人(4%)报告说，他们只是假装提供医生开具的维持生命的治疗，从而加速了患者的死亡。一些护士报告在不要求医生或其他人员事先了解的情况下从事这些实践。最常描述的安乐死方法是对末期患者给予高剂量阿片类药物。 结论：随着关于安乐死和协助自杀的公众争论持续，美国的一些重症监护护士正在参与实践。
Keywords: Humans; Female; Male; Adult; Critical Care; United States; Stress, Psychological; Interprofessional Relations; *Euthanasia, Active; *Euthanasia, Active, Voluntary; *Nurse's Role; *Nurses; Death and Euthanasia; Empirical Approach; Ethics, Nursing; Euthanasia/*statistics & numerical data; Physicians; Professional-Patient Relations; Suicide, Assisted/*statistics & numerical data

Goal-oriented hemodynamic therapy - Simini, B. (The New England journal of medicine, 1996)
目标导向的血液动力学治疗
Keywords: Humans; Critical Illness; *Fluid Therapy; Shock/*therapy

Goal-oriented hemodynamic therapy - Haupt, M. T. (The New England journal of medicine, 1996)
目标导向的血液动力学治疗
Keywords: Humans; Oxygen/*blood; Critical Illness/mortality/*therapy; Blood Chemical Analysis; *Cardiac Output

Manipulating hemodynamics and oxygen transport in critically ill patients - Hinds, C.; Watson, D. (The New England journal of medicine, 1995)
操作重症患者的血液动力学和氧气运输
Keywords: Humans; Treatment Outcome; *Hemodynamics; Cardiac Output; Oxygen/blood; Critical Illness/*therapy

A trial of goal-oriented hemodynamic therapy in critically ill patients. SvO2 Collaborative Group. - Gattinoni, L.; Brazzi, L.; Pelosi, P.; Latini, R.; Tognoni, G.; Pesenti, A.; Fumagalli, R. (The New England journal of medicine, 1995)
BACKGROUND: Hemodynamic therapy to raise the cardiac index and oxygen delivery to supranormal may improve outcomes in critically ill patients. We studied whether increasing the cardiac index to a supranormal level (cardiac-index group) or increasing mixed venous oxygen saturation to a normal level (oxygen-saturation group) would decrease morbidity and mortality among critically ill patients, as compared with a control group in which the target was a normal cardiac index. METHODS: A total of 10,726 patients in 56 intensive care units were screened, among whom 762 patients belonging to predefined diagnostic categories with acute physiology scores of 11 or higher were randomly assigned to the three groups (252 to the control group, 253 to the cardiac-index group, and 257 to the oxygen-saturation group). RESULTS: The hemodynamic targets were reached by 94.3 percent of the control group, 44.9 percent of the cardiac-index group, and 66.7 percent of the oxygen-saturation group (P < 0.001). Mortality was 48.4, 48.6, and 52.1 percent, respectively (P = 0.638), up to the time of discharge from the intensive care unit and 62.3, 61.7, and 63.8 percent (P = 0.875) at six months. Among patients who survived, the number of dysfunctional organs and the length of the stay in the intensive care unit were similar in the three groups. No differences in mortality among the three groups were found for any diagnostic category. A subgroup analysis of the patients in whom hemodynamic targets were reached revealed similar mortality rates: 44.8, 40.4, and 39.0 percent, respectively (P = 0.478). CONCLUSIONS: Hemodynamic therapy aimed at achieving supranormal values for the cardiac index or normal values for mixed venous oxygen saturation does not reduce morbidity or mortality among critically ill patients.
一项在重症患者中开展的目标导向血液动力学治疗试验。SvO2协作组。 背景：提高心脏指数和超常氧供的血液动力学治疗可改善重症患者的结局。我们研究了与目标为正常心脏指数的对照组相比，将心脏指数增加到超常水平（心脏指数组）或将混合静脉血氧饱和度增加到正常水平（氧饱和度组）是否会降低重症患者的发病率和死亡率。 方法：共筛选56家重症监护室的10726例患者，其中762例属于预定诊断类别，急性生理评分为11分或以上的患者被随机分配到3组（252例分配至对照组，253例分配至心脏指数组，257例分配至氧饱和度组）。 结果：对照组、心脏指数组和氧饱和度组分别有94.3%、44.9%和66.7%达到血流动力学目标(P < 0.001)。至离开重症监护室时死亡率分别为48.4%、48.6%和52.1%(P = 0.638)，6个月时分别为62.3%、61.7%和63.8%(P = 0.875)。在存活的患者中，3组的功能障碍器官数量和重症监护室停留时间相似。对于任何诊断类别，三组间死亡率均无差异。达到血流动力学目标的患者亚组分析显示死亡率相似：分别为44.8%、40.4%和39.0%(P = 0.478)。 结论：旨在获得混合静脉血氧饱和度的心脏指数或正常值超常值的血流动力学治疗未降低重症患者的发病率或死亡率。
Keywords: Hemodynamics; Humans; Treatment Outcome; Female; Male; Middle Aged; Survival Analysis; Adult; Oxygen Consumption; Oxygen/*blood; Erythrocyte Transfusion; Vasoconstrictor Agents/therapeutic use; Critical Illness/mortality/*therapy; Vasodilator Agents/therapeutic use; *Cardiac Output

The value of geriatric interventions - Campion, E. W. (The New England journal of medicine, 1995)
老年干预的价值
Keywords: Humans; Aged; Activities of Daily Living; Patient Care Team; *Critical Care; *Hospitalization; *Geriatric Assessment; Hospital Units; Self Care

A randomized trial of comprehensive geriatric assessment in the care of hospitalized patients - Reuben, D. B.; Borok, G. M.; Wolde-Tsadik, G.; Ershoff, D. H.; Fishman, L. K.; Ambrosini, V. L.; Liu, Y.; Rubenstein, L. Z.; Beck, J. C. (The New England journal of medicine, 1995)
BACKGROUND: Although many studies describe benefits from the comprehensive assessment of elderly patients by an interdisciplinary team (comprehensive geriatric assessment), the most supportive evidence for the process has come from programs that rely on specialized inpatient units and long hospital stays. We examined whether an inpatient geriatric consultation service might also be beneficial in a trial involving four medical centers of a group-practice health maintenance organization (HMO). METHODS: We conducted a randomized clinical trial with 2353 hospitalized patients 65 years of age or older in whom at least 1 of 13 screening criteria were present: stroke, immobility, impairment in any basic activity of daily living, malnutrition, incontinence, confusion or dementia, prolonged bed rest, recent falls, depression, social or family problems, an unplanned readmission to the hospital within three months of a previous hospital stay, a new fracture, and age of 80 years or older. Of the 1337 patients assigned to the experimental group, 1261 (94 percent) received a comprehensive geriatric assessment in the form of a consultation, with limited follow-up; the 1016 patients assigned to the control group received usual care. The functional and health status of the patients was measured at base line and 3 and 12 months later; survival was assessed at 12 months. Subgroups of patients who might be presumed to benefit from comprehensive assessment were also studied. RESULTS: The survival rate at 12 months was 74 percent in the experimental group and 75 percent in the control group. At base line, 3 months, and 12 months the scores of the two groups on measures of functional and health status were similar. The analysis of 16 subgroups did not identify any with either clearly improved functional status or improved survival. CONCLUSIONS: In this HMO, comprehensive geriatric assessment by a consultation team, with limited follow-up, did not improve the health or survival of hospitalized patients selected on the basis of screening criteria.
住院患者护理中综合老年评估的随机试验 背景：尽管许多研究描述了跨学科团队对老年患者进行综合评估（综合老年评估）的获益，但该过程的最支持性证据来自依赖于专科住院单位和长期住院的项目。我们检查了老年住院咨询服务是否也对一项涉及团体医疗健康维护组织(HMO)的4家医学中心的试验有益。 方法：我们对2353例年龄≥65岁的住院患者进行了一项随机临床试验，其中13项筛选标准中至少有1项：卒中、静止不能、任何基本日常生活活动能力受损、营养不良、失禁、意识模糊或痴呆、长期卧床、近期跌倒、抑郁，社会或家庭问题、既往住院后3个月内计划外再次入院、新发骨折和年龄≥80岁。在分配至试验组的1337例患者中，1261例(94%)接受了以咨询形式进行的全面老年评估，随访期有限；而对照组的1016例患者接受了常规护理。在基线以及3个月和12个月后测量患者的功能和健康状况；在12个月时评估生存期。还对可能从综合评估中获益的患者亚组进行了研究。 结果：实验组12个月生存率为74%，对照组为75%。在基线、3个月和12个月时，两组功能和健康状况指标的评分相似。对16个亚组的分析未发现任何功能状态明显改善或生存期改善的情况。 结论：在这项HMO中，由一个咨询小组进行的全面老年评估，随访有限，没有改善根据筛查标准选择的住院患者的健康或生存。
Keywords: Humans; Treatment Outcome; Female; Male; Aged; Aged, 80 and over; Follow-Up Studies; Activities of Daily Living; *Critical Care; *Hospitalization; Health Status; California; *Patient Care Team; *Geriatric Assessment; *Health Maintenance Organizations; Referral and Consultation/*organization & administration

A randomized trial of care in a hospital medical unit especially designed to improve the functional outcomes of acutely ill older patients - Landefeld, C. S.; Palmer, R. M.; Kresevic, D. M.; Fortinsky, R. H.; Kowal, J. (The New England journal of medicine, 1995)
BACKGROUND: Older persons who re hospitalized for acute illnesses often lose their independence and are discharged to institutions for long-term care. METHODS: We studied 651 patients 70 years of age or older who were admitted for general medical care at a teaching hospital; these patients were randomly assigned to receive usual care or to be cared for in a special unit designed to help older persons maintain or achieve independence in self-care activities. The key elements of this program were a specially prepared environment (with, for example, uncluttered hallways, large clocks and calendars, and handrails); patient-centered care emphasizing independence, including specific protocols for prevention of disability and for rehabilitation; discharge planning with the goal of returning the patient to his or her home; and intensive review of medical care to minimize the adverse effects of procedures and medications. The main outcome we measured ws the change from admission to discharge in the number of five basic activities of daily living (bathing, getting dressed, using the toilet, moving from a bed to a chair, and eating) that the patient could perform independently. RESULTS: Twenty-four patients in each group died in the hospital. At the time of discharge, 65 (21 percent) of the 303 surviving patients in the intervention group were classified as much better in terms of their ability to perform basic activities of daily living, 39 (13 percent) as better, 151 (50 percent) as unchanged, 22 (7 percent) as worse, and 26 (9 percent) as much worse. In the usual care group, 40 (13 percent) of the 300 surviving patients were classified as much better, 33 (11 percent) as better, 163 (54 percent) as unchanged, 39 (13 percent) as worse, and 25 (8 percent) as much worse (P = 0.009). The difference between the groups remained significant (P = 0.04) in a multivariable model in which we controlled for potentially confounding base-line characteristics of the patients. Lengths of stay and hospital charges were similar in the two groups. Fewer patients assigned to the intervention group were discharged to long-term care institutions (43 patients [14 percent], as compared with 67 patients [22 percent] in the usual-care group; P = 0.01). Among the 493 patients discharged to private homes, similar proportions (about 10 percent) in the two groups were admitted to long-term care institutions during the three months after discharge. CONCLUSIONS: Specific changes in the provision of acute hospital care can improve the ability of a heterogeneous group of acutely ill older patients to perform basic activities of daily living at the time of discharge from the hospital and can reduce the frequency of discharge to institutions for long-term care.
一项在医院医疗病房中实施的旨在改善急性老年患者功能结局的随机化护理试验 背景：因急性疾病而住院的老年人通常会失去独立性，出院接受长期护理。 方法：我们研究了651例70岁或以上在教学医院住院接受一般医疗护理的患者；这些患者被随机分配接受常规护理或在旨在帮助老年人维持或实现自理活动独立性的特殊病房接受护理。该项目的关键要素是专门准备的环境（例如，走廊、大钟表、日历和扶手整洁）；以患者为中心的护理，强调独立性，包括预防残疾和康复的具体方案；出院计划，目标是将患者送回家中；并对医疗护理进行重点审查，以尽量减少手术和药物的不良反应。我们测量了患者能够独立进行的5项基本日常生活活动（洗澡、穿衣、上厕所、从床移动到椅子和进食）的数量从入院到出院的变化。 结果：每组24例患者在医院死亡。出院时，303例存活患者中，65例(21%)在进行基本日常活动的能力方面被归为更好、39例(13%)更好、151例(50%)无变化、22例(7%)更差、26例(9%)更差。在常规治疗组中，300例存活患者中40例(13%)被分类为明显好转，33例(11%)好转，163例(54%)无变化，39例(13%)恶化，25例(8%)恶化(P = 0.009)。在多变量模型中，组间差异仍然显著(P = 0.04)，其中我们控制了患者的潜在混杂基线特征。两组的住院时间和住院费用相似。与常规护理组的67例患者[22%]相比，干预组中出院进入长期护理机构的患者较少（43例患者[14%]；P = 0.01）。在出院后3个月内，493例患者中，两组有相似比例（约10%）的患者入住长期护理机构。 结论：提供急性医院护理的具体变化可提高异质性老年急性病患者组出院时进行基本日常生活活动的能力，并可降低出院至机构接受长期护理的频率。
Keywords: Humans; Treatment Outcome; Female; Male; Aged; Hospital Mortality; Acute Disease; *Critical Care; Patient Discharge; *Activities of Daily Living; *Geriatric Assessment; *Patient-Centered Care; Architectural Accessibility; Critical Illness/classification; Hospital Bed Capacity, 500 and over; Hospital Units/*organization & administration; Hospitals, Teaching; Ohio

Gastrointestinal bleeding in critically ill patients - Bardes, C. L.; Charlson, M. E. (The New England journal of medicine, 1994)
重症患者的胃肠道出血
Keywords: Humans; Risk Factors; *Critical Illness; Gastrointestinal Hemorrhage/*etiology

Elevation of systemic oxygen delivery in the treatment of critically ill patients - Hayes, M. A.; Timmins, A. C.; Yau, E. H.; Palazzo, M.; Hinds, C. J.; Watson, D. (The New England journal of medicine, 1994)
BACKGROUND: Elevation of systemic oxygen delivery and consumption has been associated with an improved outcome in critically ill patients. We conducted a randomized trial to determine whether boosting oxygen delivery by infusing the inotropic agent dobutamine would improve the outcome in a diverse group of such patients. METHODS: On the basis of previously published recommendations, we established the following goals: a cardiac index above 4.5 liters per minute per square meter of body-surface area, oxygen delivery above 600 ml per minute per square meter, and oxygen consumption above 170 ml per minute per square meter. If these goals were not achieved with volume expansion alone, patients were randomly assigned to a treatment or control group. The treatment group received intravenous dobutamine (5 to 200 micrograms per kilogram of body weight per minute) until all three goals had been achieved. Dobutamine was administered to the control group only if the cardiac index was below 2.8 liters per minute per square meter. RESULTS: A total of 109 patients were studied. In nine patients the therapeutic goals were achieved with volume expansion alone; all nine patients survived to leave the hospital. Fifty patients were randomly assigned to the treatment group, and 50 to the control group. During treatment, there were no differences between the two groups in mean arterial pressure or oxygen consumption, despite a significantly higher cardiac index and level of oxygen delivery in the treatment group (P < 0.05). Although the predicted risk of death during hospitalization was 34 percent for both groups, the in-hospital mortality was lower in the control group (34 percent) than in the treatment group (54 percent) (P = 0.04; 95 percent confidence interval, 0.9 to 39.1 percent). CONCLUSIONS: The use of dobutamine to boost the cardiac index and systemic oxygen delivery failed to improve the outcome in this heterogeneous group of critically ill patients. Contrary to what might have been expected, our results suggest that in some cases aggressive efforts to increase oxygen consumption may have been detrimental.
提高危重患者治疗中的全身氧输送 背景：全身氧输送和消耗的升高与重症患者的结局改善相关。我们进行了一项随机试验，以确定通过输注正性肌力药物多巴酚丁胺增强氧气输送是否会改善不同组此类患者的结局。 方法：根据之前公布的建议，我们确立了以下目标：心脏指数高于4.5 l/min/m2体表面积，氧气输送量高于600 mL/min/m2，氧气消耗量高于170 mL/min/m2。如果仅通过容量扩充未能达到这些目标，则将患者随机分配至治疗组或对照组。治疗组接受多巴酚丁胺静脉给药（每分钟5-200微克/千克体重），直至达到所有3个目标。仅当心脏指数低于2.8 l/min/m2时，才对对照组给予多巴酚丁胺。 结果：共对109例患者进行了研究。在9例患者中，仅通过容量扩充就达到了治疗目标；所有9例患者均存活至离开医院。50例患者随机分配至治疗组，50例患者随机分配至对照组。治疗期间，尽管治疗组的心脏指数和氧输送水平显著较高，但两组的平均动脉压或氧耗量无差异(P < 0.05)。尽管两组住院期间的死亡预测风险均为34%，但对照组的住院死亡率(34%)低于治疗组(54%)（P = 0.04；95%置信区间，0.9%-39.1%）。 结论：在这组异质性危重患者中，使用多巴酚丁胺增加心脏指数和全身氧输送未能改善结局。与预期相反，我们的结果表明，在某些情况下，积极努力增加耗氧量可能是有害的。
Keywords: Humans; Treatment Outcome; Female; Male; Middle Aged; Prospective Studies; Aged; Adult; Aged, 80 and over; Hospital Mortality; *Oxygen Consumption; Cardiac Output; Confidence Intervals; Norepinephrine/therapeutic use; Critical Illness/mortality/*therapy; *Oxygen Inhalation Therapy; Dobutamine/adverse effects/therapeutic use

Mechanical ventilation - Tobin, M. J. (The New England journal of medicine, 1994)
机械通气
Keywords: Humans; Monitoring, Physiologic; Positive-Pressure Respiration; Critical Care; Ventilators, Mechanical; Respiration, Artificial/*methods; Analgesics/therapeutic use; Respiratory Distress Syndrome/therapy

Prevention of upper gastrointestinal bleeding - Peterson, W. L. (The New England journal of medicine, 1994)
预防上消化道出血
Keywords: Humans; Risk Factors; Gastrointestinal Hemorrhage/*prevention & control; Critical Illness/mortality; Duodenal Ulcer/complications; Peptic Ulcer Hemorrhage/prevention & control

Risk factors for gastrointestinal bleeding in critically ill patients. Canadian Critical Care Trials Group. - Cook, D. J.; Fuller, H. D.; Guyatt, G. H.; Marshall, J. C.; Leasa, D.; Hall, R.; Winton, T. L.; Rutledge, F.; Todd, T. J.; Roy, P. (The New England journal of medicine, 1994)
BACKGROUND: The efficacy of prophylaxis against stress ulcers in preventing gastrointestinal bleeding in critically ill patients has led to its widespread use. The side effects and cost of prophylaxis, however, necessitate targeting preventive therapy to those patients most likely to benefit. METHODS: We conducted a prospective multicenter cohort study in which we evaluated potential risk factors for stress ulceration in patients admitted to intensive care units and documented the occurrence of clinically important gastrointestinal bleeding (defined as overt bleeding in association with hemodynamic compromise or the need for blood transfusion). RESULTS: Of 2252 patients, 33 (1.5 percent; 95 percent confidence interval, 1.0 to 2.1 percent) had clinically important bleeding. Two strong independent risk factors for bleeding were identified: respiratory failure (odds ratio, 15.6) and coagulopathy (odds ratio, 4.3). Of 847 patients who had one or both of these risk factors, 31 (3.7 percent; 95 percent confidence interval, 2.5 to 5.2 percent) had clinically important bleeding. Of 1405 patients without these risk factors, 2 (0.1 percent; 95 percent confidence interval, 0.02 to 0.5 percent) had clinically important bleeding. The mortality rate was 48.5 percent in the group with bleeding and 9.1 percent in the group without bleeding (P < 0.001). CONCLUSIONS: Few critically ill patients have clinically important gastrointestinal bleeding, and therefore prophylaxis against stress ulcers can be safely withheld from critically ill patients unless they have coagulopathy or require mechanical ventilation.
重症患者中胃肠道出血的风险因素。加拿大重症临床试验组。 背景：预防重症患者发生应激性溃疡以预防胃肠道出血已得到应用。然而，广泛存在的预防副作用和费用使得有必要对最有可能靶向获益的患者进行预防治疗。 方法：我们进行了一项多中心前瞻性队列研究，其中我们对入住重症监护室的患者发生应激性溃疡的潜在风险因素进行了评估，并记录了与明显出血相关的临床重要胃肠道出血的发生或需要输血的血液动力学n）。 结果：2252例患者中，33例（1.5%；95%置信区间，1.0%-2.1%）发生临床重要出血。发现强烈的出血风险因素：呼吸衰竭（比值比，15.6）和凝血病（独立比值比，4.3）。847例同时存在上述一种或两种风险因素的患者中，31例（3.7%；95%置信区间，2.5%至5.2%）发生有临床意义的出血。1405例无这些危险因素的患者中，2例（0.1%；95%置信区间，0.02-0.5%）发生临床重要出血。出血组的死亡率为48.5%，无出血组为9.1%(P < 0.001)。 结论：极少数重症患者发生具有临床意义的胃肠道出血，因此，重症患者可以安全地预防应激性溃疡，除非他们发生凝血病或需要机械通气。
Keywords: Humans; Female; Male; Middle Aged; Prospective Studies; Aged; Risk Factors; Confidence Intervals; Odds Ratio; Regression Analysis; Peptic Ulcer Hemorrhage/prevention & control; *Critical Illness/mortality; Anti-Ulcer Agents/therapeutic use; Gastrointestinal Hemorrhage/*etiology/prevention & control; Peptic Ulcer/etiology/prevention & control; Stress, Physiological/etiology/prevention & control

Drowning - Modell, J. H. (The New England journal of medicine, 1993)
溺水
Keywords: Humans; Child; Survival Rate; *Drowning/etiology/physiopathology/prevention & control; Near Drowning/mortality/therapy

Gastrointestinal damage associated with nonsteroidal antiinflammatory drugs - Dorais, J.; GrÃ©goire, G.; LeLorier, J. (The New England journal of medicine, 1992)
非甾体抗炎药引起的胃肠道损害
Keywords: Humans; Anti-Inflammatory Agents, Non-Steroidal/*adverse effects; Ileum/*drug effects; Jejunum/*drug effects; Peptic Ulcer/chemically induced

Persistent paralysis in critically ill patients after long-term administration of vecuronium - Segredo, V.; Caldwell, J. E.; Matthay, M. A.; Sharma, M. L.; Gruenke, L. D.; Miller, R. D. (The New England journal of medicine, 1992)
BACKGROUND: The muscle relaxant vecuronium is sometimes administered to facilitate mechanical ventilation. Neuromuscular paralysis lasting up to seven days may occur after the termination of long-term administration (i.e., more than two days) of vecuronium in critically ill patients. We investigated the role of clinical factors and plasma concentrations of vecuronium and its metabolite in causing this prolonged neuromuscular blockade. METHODS: We studied 16 critically ill adult patients (8 women and 8 men) who had received vecuronium to facilitate mechanical ventilation for at least two consecutive days. Clinical factors and plasma concentrations of vecuronium and 3-desacetylvecuronium, the active metabolite of vecuronium, were compared in patients with and without prolonged neuromuscular blockade. In addition, we performed detailed pharmacokinetic studies in the patients without prolonged neuromuscular blockade. RESULTS: Seven of the 16 patients had prolonged neuromuscular blockade, lasting from six hours to more than seven days, after the termination of vecuronium therapy. These seven patients, six of whom were women, had higher plasma magnesium concentrations and lower arterial blood pH values than the nine patients without prolonged neuromuscular blockade. They also had higher plasma concentrations of 3-desacetylvecuronium and a higher frequency of renal failure (seven of seven patients vs. four of nine patients, P less than 0.03). In the patients without prolonged neuromuscular blockade, the mean (+/- SD) plasma clearance, elimination half-life, and volume of distribution of vecuronium were 2.5 +/- 1.0 ml per kilogram of body weight per minute, 299 +/- 154 minutes, and 1.1 +/- 0.6 liters per kilogram, respectively. CONCLUSIONS: Prolonged neuromuscular blockade after the termination of long-term treatment with vecuronium is associated with metabolic acidosis, elevated plasma magnesium concentrations, female sex, and probably more important, the presence of renal failure and high plasma concentrations of 3-desacetylvecuronium.
重症患者长期服用维库溴铵后出现持续性瘫痪 背景：肌肉松弛剂维库溴铵有时用于辅助机械通气。危重患者长期服用维库溴铵（即2天以上）终止后，可能发生持续7天的神经肌肉麻痹。我们研究了临床因素和维库溴铵及其代谢物的血浆浓度在引起这种延长的神经肌肉阻滞作用中的作用。 方法：我们研究了16例重症成人患者（8例女性和8例男性），这些患者接受维库溴铵辅助机械通气至少连续2天。在有和无神经肌肉阻滞延长的患者中，比较维库溴铵的活性代谢产物维库溴铵和3-去乙酰基维库溴铵的临床因素和血浆浓度。此外，我们在无长期神经肌肉阻滞的患者中进行了详细的药代动力学研究。 结果：16例患者中有7例患者在维库溴铵治疗终止后出现神经肌肉阻滞延长，持续时间从6小时至7天以上。这7名患者（其中6名是女性）的血浆镁浓度高于没有延长神经肌肉阻滞的9名患者，动脉血pH值低于这9名患者。他们的3-去乙酰维库溴铵血浆浓度也更高，肾衰竭的频率更高（7/7位患者vs. 4/9位患者，P < 0.03）。在无神经肌肉阻滞延长的患者中，维库溴铵的平均(+/-SD)血浆清除率、消除半衰期和分布容积分别为2.5±1.0 mL/kg体重/分钟、299±154 min和1.1±0.6 l/kg。 结论：维库溴铵长期治疗结束后神经肌肉阻滞延长与代谢性酸中毒、血浆镁浓度升高、女性相关，可能更重要的是，出现肾衰竭和3-去乙酰维库溴铵血浆浓度高。
Keywords: Humans; Female; Male; Time Factors; Respiration, Artificial; Retrospective Studies; Sex Factors; *Critical Illness; Hydrogen-Ion Concentration; Kidney Diseases/complications; Magnesium/blood; Neuromuscular Junction/*drug effects; Paralysis/chemically induced; Vecuronium Bromide/*adverse effects/blood/pharmacokinetics

Catabolic illness. Strategies for enhancing recovery. - Wilmore, D. W. (The New England journal of medicine, 1991)
After injury, infection, extensive chemotherapy, and other critical illnesses, both protein and fat are lost from the body. Although minor alterations in body composition are probably of little clinical importance, losses of body protein of 10 percent or more contribute to morbidity and debility. This catabolic response can be modified and recovery can be accelerated by a variety of approaches. First, the inflammatory response can be reduced; second, specific nutrients can be provided to support the patient's tissue requirements during catabolic illness; and third, growth factors can be used to enhance protein synthesis and tissue repair. These approaches, whether used alone or in combination, will reduce the loss of body protein, which should accelerate recovery, shorten the length of hospitalization, and reduce convalescence.
分解代谢疾病。加速康复的策略。 在化疗、感染、广泛化疗和其他危重症之后，蛋白质和脂肪均从体内丢失。身体组成的变化可能没有临床意义，尽管身体蛋白质的10%或以上有助于发病和虚弱。可通过多种方法对这种分解代谢反应进行修饰并加速恢复。首先，可以减少炎症反应；其次，可以提供特定的营养物质，以支持患者在分解代谢疾病期间的组织需求；第三，可以使用生长因子来增强蛋白质合成和组织修复。这些方法，单独或联合使用，将减少机体蛋白质的损失，这应该加快康复，缩短住院时间，并减少恢复期。
Keywords: Humans; Weight Loss; *Critical Care; *Parenteral Nutrition, Total; Adipose Tissue/*metabolism; Cachexia/metabolism/therapy; Energy Intake; Growth Substances/administration & dosage; Metabolic Diseases/etiology/physiopathology/therapy; Muscles/*metabolism; Proteins/*metabolism; Stress, Physiological/metabolism/therapy

Lassa fever in the United States. Investigation of a case and new guidelines for management. - Holmes, G. P.; McCormick, J. B.; Trock, S. C.; Chase, R. A.; Lewis, S. M.; Mason, C. A.; Hall, P. A.; Brammer, L. S.; Perez-Oronoz, G. I.; McDonnell, M. K. (The New England journal of medicine, 1990)
美国的拉沙热。病例调查和新的管理指南。
Keywords: Humans; Male; Adult; Critical Care; Risk Factors; Clinical Protocols; Algorithms; Population Surveillance; United States/epidemiology; Communicable Disease Control/methods; Illinois/epidemiology; Lassa Fever/epidemiology/prevention & control/*therapy/transmission; Ribavirin/administration & dosage

Withholding and withdrawal of life support from the critically ill - Smedira, N. G.; Evans, B. H.; Grais, L. S.; Cohen, N. H.; Lo, B.; Cooke, M.; Schecter, W. P.; Fink, C.; Epstein-Jaffe, E.; May, C. (The New England journal of medicine, 1990)
We investigated decisions to withhold or withdraw life support from patients in the medical-surgical intensive care units at the Moffitt-Long Hospital of the University of California and San Francisco General Hospital, from July 1987 through June 1988. Among 1719 patients admitted to the two intensive care units, life support was withheld from 22 (1 percent) and withdrawn from 93 (5 percent). The reason for limiting care was poor prognosis. Of these 115 patients (18 of whom were considered brain-dead), 89 died in the intensive care unit (accounting for 45 percent of all deaths there), and all but 1 of the remaining patients died after transfer from the intensive care unit. Thirteen (11 percent) had earlier expressed the wish that their terminal care be limited, but this affected care in only four cases. Only 5 of the 115 patients made the actual decision to limit care; the others were incompetent at the time. Of the latter, 102 had families who participated in the decision; family members of the other 8 incompetent patients could not be found, and the decisions were made by physicians. Only 10 families initially disagreed with the recommendations to limit care, and they later agreed. The median duration of intensive care among the patients from whom life support was withheld or withdrawn was eight days at Moffitt-Long Hospital and four days at San Francisco General, as compared with medians of three and one days, respectively, for other patients who died in the intensive care units. We conclude that although life-sustaining care is withheld or withdrawn relatively infrequently from patients in the intensive care unit, such decisions precipitate about half of all deaths in the intensive care units of the hospitals we studied. In most of these cases the patients are incompetent, but physicians and families usually agree to limit care.
危重患者生命支持的暂停和撤除 从1987年7月至1988年6月，我们调查了加利福尼亚大学Moffitt-Long医院和旧金山综合医院内科-外科重症监护室患者停止或撤回生命支持的决定。在入住两个重症监护室的1719例患者中，22例患者(1%)停用生命支持药物，93例患者(5%)停用生命支持药物。限制护理的原因是预后不良。在这115例患者（其中18例被认为脑死亡）中，89例在重症监护室死亡（占所有死亡的45%），其余患者中，除1例患者外，所有患者均在转出重症监护室后死亡。13位(11%)患者早先表示希望限制终末护理，但是这只影响了4例患者的护理。115例患者中只有5例做出限制护理的实际决定；其他患者当时均不具备治疗能力。后者中，102名有家庭参与决策；另外8名功能不全患者的家庭成员无法找到，由医生做出决策。只有10个家庭最初不同意限制护理的建议，后来他们同意了。在Moffitt-Long医院和San Francisco General，停止或停止生命支持的患者的重症监护中位持续时间分别为8天和4天，相比之下，重症监护病房死亡的其他患者的中位持续时间分别为3天和1天。我们的结论是，尽管在重症监护室患者中相对较少地停止或撤除维持生命的治疗，但这样的决定会加速我们研究的医院重症监护室中约一半的死亡。在大多数情况下，患者无能，但医生和家属通常同意限制护理。
Keywords: Humans; Middle Aged; Adult; Critical Care; Cause of Death; Surveys and Questionnaires; Informed Consent; *Life Support Care; Decision Making; Family; San Francisco

Experience with anencephalic infants as prospective organ donors - Peabody, J. L.; Emery, J. R.; Ashwal, S. (The New England journal of medicine, 1989)
Recent advances have made organ transplantation in newborns feasible, but the paucity of organs small enough for this age group remains a major limitation. Because anencephalic infants can survive for no more than a few weeks, they have been considered as possible organ donors for other infants. Under current law, however, they cannot be used as donors until their brain-stem activity ceases and the criteria for total brain death are thereby met. If anencephalic infants receive customary care, their solid organs usually undergo irreversible hypoxic injury during the process of dying and become unsuitable for donation by the time of death. We modified the medical care of 12 live-born anencephalic infants for one week to determine whether organ viability could be maintained and whether the criteria of total brain death could be met. Six received intensive care from birth, and six only when signs of imminent death developed. Only two infants met the criteria for total brain death within one week, and no solid organs were procured. Most organs were suitable for transplantation at birth. When intensive care was provided from birth, organ function was maintained; however, brain-stem activity ceased in only one infant within the first week. When intensive care was delayed until death was imminent, most organs were damaged to an extent that made them no longer suitable for transplantation. Our findings suggest that it is usually not feasible, with the restrictions of current law, to procure solid organs for transplantation from anencephalic infants.
无脑儿作为预期器官供者的经验 最近的进展使新生儿器官移植变得可行，但足够小的器官不足以用于该年龄组仍是一个主要限制。由于无脑儿的存活时间不超过数周，因此被认为是其他婴儿的可能器官供体。然而，根据现行法律，在脑干活动停止并因此符合全脑死亡标准之前，它们不能作为供体。如果无脑儿接受习惯性照顾，其实质性器官通常在死亡过程中发生不可逆的缺氧损伤，并在死亡时变得不适合捐献。我们对12例活产无脑儿的医疗护理进行了一周的改良，以确定是否可以维持器官活力，以及是否可以满足全部脑死亡的标准。6例患者从出生时即接受了重症监护，6例患者仅在出现即将死亡的体征时接受了重症监护。只有2名婴儿在1周内符合全脑死亡的标准，未获得实质性器官。大多数器官在出生时适合移植。当从出生开始提供重症监护时，器官功能得以维持；然而，仅1例婴儿的脑干活动在第一周内停止。当重症监护推迟到即将死亡时，大多数器官受损的程度使它们不再适合移植。我们的研究结果表明，在现行法律的限制下，从无脑婴儿中获取用于移植的实体器官通常是不可行的。
Keywords: Humans; Monitoring, Physiologic; Critical Care; Brain Death; Infant, Newborn; United States; Liver Transplantation; *Tissue Donors; *Anencephaly; Heart Transplantation; Heart/physiology; Kidney Transplantation; Kidney/physiology; Liver/physiology; Tissue and Organ Procurement/legislation & jurisprudence/methods; Tissue Survival

Critical care medicine - Holbrook, P. R. (The New England journal of medicine, 1989)
重症医学
Keywords: *Critical Care; Specialization; Medicine

Critical care medicine--a new specialty? - Kelley, M. A. (The New England journal of medicine, 1988)
重症医学--新的专业？
Keywords: United States; *Intensive Care Units; *Critical Care; Forecasting; Workforce; Certification; Internal Medicine; Interprofessional Relations; Specialization

The effects of vasodilation with prostacyclin on oxygen delivery and uptake in critically ill patients - Bihari, D.; Smithies, M.; Gimson, A.; Tinker, J. (The New England journal of medicine, 1987)
We hypothesized that inadequate oxygenation of peripheral tissues may be unrecognized in critically ill patients and may worsen their prognosis. To test this hypothesis, we measured oxygen delivery to tissues, oxygen uptake, and the extraction ratio (uptake/delivery) before and during a 30-minute infusion of a vasodilator, prostacyclin (5 ng per kilogram of body weight per minute), in 27 critically ill patients with acute respiratory failure. Prostacyclin produced an increase in oxygen delivery (median value before vs. during infusion, 375 vs. 492 ml of oxygen per minute per square meter of body-surface area, P less than 0.001) that was similar in the 14 patients who survived and the 13 who died. This increase in oxygen delivery was associated with a significantly greater increase in oxygen uptake in the patients who died as compared with the survivors (median increase, 19 vs. 5 percent, P less than 0.001). In the survivors, the oxygen extraction ratio fell (median change, -17 percent; range, -27 to -6 percent) and the mixed venous oxygen tension increased. In the patients who died, the extraction ratio rose (median change, 11 percent; range -24 to +40 percent) and the mixed venous oxygen tension did not change. These data suggest the presence of a substantial oxygen debt in patients who subsequently die. Inadequate tissue oxygenation, which may be difficult to recognize, appears to be an important mechanism contributing to the development of irreversible multiple organ failure and subsequent death in some patients with acute respiratory failure.
血管扩张与前列环素对重症患者氧输送和氧摄取的影响 我们假设危重患者中外周组织氧合不足可能无法识别，并可能恶化其预后。为了验证这一假设，我们在27例急性呼吸衰竭的重症患者中，测量了血管扩张剂前列环素（每分钟5 ng/kg体重）30 min输注前和输注期间的组织氧气输送量、氧摄取和摄取率（摄取/输送）。前列环素导致氧气输送量增加（输注前和输注期间的中位值，每平方米体表面积每分钟375与492 mL氧气，P < 0.001），14例存活患者和13例死亡患者的结果相似。与存活者相比，这种氧输送增加与死亡患者的氧摄取显著增加相关（中位增加19%vs 5%，P < 0.001）。在存活者中，氧摄取率下降（中位变化，-17%；范围，-27至-6%），混合静脉血氧张力增加。在死亡患者中，氧摄取率升高（中位变化11%；范围-24至 + 40%），混合静脉血氧分压未发生变化。这些数据表明随后死亡的患者存在大量氧耗。可能难以识别的组织氧合不足似乎是促使一些急性呼吸衰竭患者发生不可逆性多器官衰竭并随后死亡的重要机制。
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Aged, 80 and over; Critical Care; Acute Disease; Epoprostenol/*pharmacology/therapeutic use; Hemodynamics/drug effects; Multiple Organ Failure/prevention & control; Oxygen Consumption/*drug effects; Respiratory Insufficiency/*drug therapy/metabolism/mortality; Vasodilator Agents/*pharmacology/therapeutic use

Neurologic uncertainty in newborn intensive care - Coulter, D. L. (The New England journal of medicine, 1987)
新生儿重症监护中的神经系统不确定性
Keywords: Humans; Prognosis; Infant, Newborn; Brain/physiopathology; Intensive Care Units, Neonatal; Electrocardiography; *Ethics, Medical; *Brain Death; Cerebral Palsy/etiology; Coma/*diagnosis; Infant, Newborn, Diseases/*diagnosis; Intellectual Disability/etiology

Accurate prediction of the outcome of pediatric intensive care. A new quantitative method. - Pollack, M. M.; Ruttimann, U. E.; Getson, P. R. (The New England journal of medicine, 1987)
We surveyed nine pediatric intensive care units (ICUs) to compare patient populations and to test prospectively the hypothesis that differences in mortality rates were due to differences in severity of illness. Age, clinical service, the reason for admission (emergency or scheduled), and the seriousness of the underlying chronic disease were recorded on admission. The severity of illness was assessed on the day of admission with a physiology-based measure, the Physiologic Stability Index. The resulting score was used to group patients according to mortality risk. The observed numbers of ICU survivors and nonsurvivors in each mortality-risk group from eight of the pediatric ICUs were compared with the predicted numbers of survivors and nonsurviors calculated from a mathematical function (logistic model) derived earlier from data on 822 patients at one of the institutions. Patient populations in the ICUs differed significantly with respect to age (range of medians, 15 to 36 months; P less than 0.0001), medical admissions (range, 39 to 81 percent; P less than 0.0001), emergency admissions (range, 53 to 91 percent; P less than 0.0001), and the percentage of patients with serious underlying chronic disease (range, 18 to 48 percent; P less than 0.0001). Mortality rates also differed significantly (range, 3.0 to 17.6 percent; P less than 0.0001), as did the Physiologic Stability Index scores (P less than 0.0001). The mathematical function based on the Physiologic Stability Index score and on age reliably predicted the outcomes in all ICUs. We conclude that differences in mortality rates among pediatric ICUs can be explained by differences in the severity of illness.
准确预测儿科重症监护的结局。一种新的定量方法。 我们调查了9个儿科重症监护室(ICU)，以比较患者人群，并前瞻性检验死亡率差异是由于疾病严重程度差异所致的假设。入院时记录年龄、临床服务、入院原因（急诊或计划）以及基础慢性疾病的严重性。在入院当天，采用基于生理学的指标（生理稳定性指数）评估了疾病的严重程度。结果的评分用于根据死亡风险对患者进行分组。将来自8个儿科ICU的每个死亡风险组中观察到的ICU存活者和非存活者的数量与从一个机构的822名患者的早期数据中获得的数学函数（logistic模型）计算的存活者和非存活者的预测数量进行比较。ICU中的患者人群在年龄（中位数范围，15-36个月；P < 0.0001）、内科入院（范围，39-81%；P < 0.0001）、急诊入院（范围，53-91%；P < 0.0001）方面存在显著差异，患有严重慢性基础疾病的患者百分比（范围：18%-48%；P < 0.0001）。死亡率也有显著差异（范围3.0%-17.6%；P < 0.0001），生理稳定性指数评分也有显著差异(P < 0.0001)。基于生理稳定性指数评分和年龄的数学函数可靠地预测了所有ICU的结局。我们的结论是，儿科ICU中死亡率的差异可以通过疾病严重程度的差异来解释。
Keywords: Humans; Prospective Studies; Infant; Infant, Newborn; Severity of Illness Index; Child, Preschool; Age Factors; United States; *Intensive Care Units; *Pediatrics; *Mortality; Outcome and Process Assessment, Health Care/*methods

Outcome assessment 70 years later: are we ready? - Schroeder, S. A. (The New England journal of medicine, 1987)
70年后的结局评估：我们准备好了吗？
Keywords: Humans; Mortality; Infant; Infant, Newborn; United States; Pediatrics; Outcome and Process Assessment, Health Care/*methods; *Accreditation; *Joint Commission on Accreditation of Healthcare Organizations; Intensive Care Units/standards

Medical vampires - Burnum, J. F. (The New England journal of medicine, 1986)
医用吸血者
Keywords: Humans; Critical Care; Bloodletting/*adverse effects; Clinical Laboratory Techniques/*standards

Monitoring oxygen transcutaneously in critically ill patients - Tremper, K. K.; Shoemaker, W. C.; Wender, D. (The New England journal of medicine, 1985)
重症患者经皮监测氧疗
Keywords: Humans; Critical Care/*methods; Monitoring, Physiologic/*methods; Oxygen/*analysis; Partial Pressure

Cardiopulmonary monitoring of critically ill patients (2) - Goldenheim, P. D.; Kazemi, H. (The New England journal of medicine, 1984)
重症患者的心肺监测(2)
Keywords: Humans; Arteries; Critical Care/*methods; Blood Pressure Determination/methods; Cardiac Catheterization/adverse effects/*methods; Catheterization/adverse effects/methods; Catheters, Indwelling/adverse effects; Central Venous Pressure; Monitoring, Physiologic/adverse effects/*methods; Myocardial Infarction/complications; Pulmonary Artery/injuries; Rupture; Thrombosis/etiology

Current concepts. Cardiopulmonary monitoring of critically ill patients (1). - Goldenheim, P. D.; Kazemi, H. (The New England journal of medicine, 1984)
当前概念。重症患者的心肺监测(1)。
Keywords: Humans; Critical Care/*methods; Ventilators, Mechanical; Monitoring, Physiologic/*methods; Blood Gas Analysis/methods; Electrocardiography/methods; Heart/*physiopathology; Lung/*physiopathology; Physical Examination/methods; Radiography, Thoracic/methods; Respiratory Function Tests/methods; Respiratory Insufficiency/diagnosis

The care of the terminally ill: morality and economics - Bayer, R.; Callahan, D.; Fletcher, J.; Hodgson, T.; Jennings, B.; Monsees, D.; Sieverts, S.; Veatch, R. (The New England journal of medicine, 1983)
Are current expenditures on dying patients disproportionate, unreasonable, or unjust? Although a review of empirical data reveals that care for the terminally ill is very costly, it is not appropriate to conclude that such expenditures represent a morally troubling misallocation of societal resources. Moreover, though efforts to reduce the costs of caring for the dying are not unreasonable, they must be undertaken with great caution. At present, such efforts should concentrate on three basic goals: development of better criteria for admission to intensive- and critical-care units; promotion of patient and family autonomy with regard to decisions to stop or refuse certain kinds of treatment; and promotion of alternative forms of institutional care, such as hospice care. The most difficult moral problems will arise when patients and their physicians seek access to therapies judged only marginally useful. There may be conflict between administrators with broad institutional responsibilities and clinicians committed to particular patients.
终末期疾病的护理：道德和经济 死亡患者目前的支出是否不成比例、不合理或不公正？尽管对经验数据的审查显示，对末期疾病的护理成本非常高，但不适合得出这样的结论，即这种支出在道义上代表了令人烦恼的社会资源分配不当。此外，虽然降低死亡患者护理成本的努力是合理的，但必须非常谨慎。目前，这些努力应集中于三个基本目标：制定入住重症监护室和重症监护室的更好标准；促进患者和家庭在决定停止或拒绝某些类型的治疗方面的自主；促进机构护理的替代形式，如临终关怀。当患者及其医生寻求仅有边际价值的治疗时，将出现最困难的道德问题。机构责任广泛的管理者与致力于特定患者的临床医生之间可能存在冲突。
Keywords: Humans; Critical Care; United States; Intensive Care Units/statistics & numerical data; Cost-Benefit Analysis; Family; *Morals; Ethics, Medical; Costs and Cost Analysis; Hospices; Neoplasms/therapy; Terminal Care/*economics/standards; Value of Life

Right-heart catheterization in the critically ill patient (The New England journal of medicine, 1983)
重症患者右心导管检查
Keywords: Humans; *Hemodynamics; *Cardiac Catheterization; *Critical Care; *Monitoring, Physiologic

Hemodynamic monitoring in the critically ill patient - Shaver, J. A. (The New England journal of medicine, 1983)
重症患者的血流动力学监测
Keywords: Humans; *Hemodynamics; *Cardiac Catheterization; Critical Care/*methods; Diagnostic Tests, Routine; Monitoring, Physiologic/*methods; *Technology Assessment, Biomedical; Multiple Organ Failure/diagnosis

Evaluation of right-heart catheterization in the critically ill patient without acute myocardial infarction - Connors, A. F. Jr; McCaffree, D. R.; Gray, B. A. (The New England journal of medicine, 1983)
无急性心肌梗死的重症患者中右心导管插入术的评价
Keywords: Humans; Female; Male; Middle Aged; Aged; Adult; Blood Pressure; Adolescent; *Hemodynamics; Critical Care/*methods; Diagnostic Tests, Routine; *Cardiac Catheterization/adverse effects; *Technology Assessment, Biomedical; Multiple Organ Failure/diagnosis; Pulmonary Wedge Pressure

Newborn intensive care and neonatal mortality in low-birth-weight infants: a population study - Paneth, N.; Kiely, J. L.; Wallenstein, S.; Marcus, M.; Pakter, J.; Susser, M. (The New England journal of medicine, 1982)
We examined the neonatal mortality rates of low-birth-weight infants (501 to 2250 g) born between 1976 and 1978 in three kinds of hospitals in New York City: those with newborn-intensive-care units (Level 3), those with capabilities for the care of most premature infants (Level 2), and those without any special facilities for premature newborns (Level 1). Among 13,560 singleton low-birth-weight infants, the adjusted neonatal mortality rate for Level 3 hospitals was 128.5 per thousand live births - significantly lower (P less than 0.001) than the rates for both level 2 (168.1) and Level 1 units (163.0). The association of level of care with mortality could not be accounted for by differences between groups in social or demographic status, in prenatal care, or in medical complication of pregnancy. We infer that birth at a Level 3 center lowers neonatal mortality in low-birth-weight infants. However, only 34 per cent of the patients in this study were born in such units.
低出生体重儿的新生儿重症监护和新生儿死亡率：一项人群研究 我们检查了纽约市1976年至1978年出生的三种医院中低出生体重儿（501至2250 g）的新生儿死亡率：有新生儿重症监护室的医院（3级），有能力护理大多数早产儿的医院（2级），以及无任何早产新生儿专用设施（1级）。在13,560名单胎低出生体重儿中，3级医院的调整后新生儿死亡率为每千名活产128.5例-显著低于(P < 0.001)2级(168.1)和1级单位(163.0)的死亡率。护理水平与死亡率的相关性不能通过社会或人口统计学状态、产前护理或妊娠医学并发症的组间差异来解释。我们推断在3级中心出生可降低低出生体重儿的新生儿死亡率。但是，本研究中仅34%的患者在此类病房出生。
Keywords: Humans; Female; Male; Infant; Infant, Newborn; Pregnancy; Risk; *Infant, Premature; *Critical Care; Transportation of Patients; *Infant Mortality; *Infant, Low Birth Weight; *Intensive Care Units, Neonatal; Hospitals/classification; Maternal Age; New York City; Obstetric Labor Complications; Parity; Pregnancy Complications; Prenatal Care

Evaluation of neonatal-intensive-care program - Sinclair, J. C.; Torrance, G. W.; Boyle, M. H.; Horwood, S. P.; Saigal, S.; Sackett, D. L. (The New England journal of medicine, 1981)
Within the past 15 years, regional neonatal-intensive-care programs have been introduced and have expanded rapidly. The efficacy of some of the individual interventions that constitute neonatal intensive care has been validated in randomized, controlled clinical trials. It is therefore generally assumed that neonatal-intensive-care programs that incorporate these maneuvers are effective in reducing death and disability. However, the overall effectiveness of these programs has not been tested experimentally. Moreover, much of the non-experimental evidence supporting their value is based on the experience of referral units and does not measure the impact on the populations they serve. A definitive economic evaluation of neonatal intensive care has not yet been reported, despite the high cost of such programs. We conclude that neonatal-intensive care programs require further evaluation with rigorous scientific methods.
新生儿重症监护计划评估 在过去15年内，引入了区域性新生儿重症监护项目，并已迅速扩展。一些构成新生儿重症监护的个体干预措施的疗效已在随机对照临床试验中得到验证。因此，一般假定新生儿重症监护计划中包含这些操作可有效减少死亡和残疾。但是，这些项目的总体有效性尚未通过实验进行检测。此外，许多支持其价值的非实验性证据是基于转诊单位的经验，并不衡量对其服务人群的影响。尽管此类项目的成本较高，但尚未报告对新生儿重症监护的确切经济评价。我们的结论是新生儿重症监护项目需要用严格的科学方法进行进一步的评估。
Keywords: Humans; Infant; Random Allocation; United States; Infant Mortality; Clinical Trials as Topic; Cost-Benefit Analysis; Morbidity; *Infant, Newborn; *Outcome and Process Assessment, Health Care; *Regional Medical Programs; Critical Care/economics/*standards; Evaluation Studies as Topic; Infant Care/*standards; Infant, Low Birth Weight; Infant, Newborn, Diseases/therapy; Infant, Premature, Diseases/therapy; Intensive Care Units/economics

High-cost users of medical care - Zook, C. J.; Moore, F. D. (The New England journal of medicine, 1980)
Cost characteristics of hospital patients were analyzed in 2238 medical records randomly selected from 42,880 dicharges in six contrasting hospital populations in the year 1976. Total hospital billings were concentrated on a few patients. On average, the high-cost 13% of patients consumed as many resources as the low-cost 87%. Repeated hospitalizations for the same disease were more characteristic of the expensive patients than were single cost-intensive stays, "intensive care," or prolonged single hospitalizations. Potentially harmful personal habits (e.g., drinking and smoking) were indicated in the records of high-cost patients substantially more often than in those of low-cost patients. Unexpected complications during treatment were five times more frequent in the high-cost group. Public policy programs for health insurance or cost control should include provisions based on the special characteristics of high-cost patients.
医疗护理高成本用户 1976年，在6个对比医院人群中，从42,880名酒渣鼻患者中随机选择2238份病历，对医院患者的费用特征进行了分析。医院账单总额集中在少数患者身上。平均而言，高成本的13%患者消耗的资源与低成本的87%一样多。相同疾病的重复住院比单一的费用-强化住院、“重症监护”或延长单次住院更具昂贵患者的特征。与低成本患者相比，高成本患者的记录显示，潜在有害的个人习惯（例如，饮酒和吸烟）显著更频繁。高成本组治疗期间的非预期并发症发生率高出5倍。健康保险或费用控制的公共政策计划应包括基于高成本患者的特殊特征的规定。
Keywords: Humans; Female; Male; Middle Aged; Time Factors; Aged; Adult; Adolescent; Child; Infant; Infant, Newborn; Child, Preschool; Age Factors; Sex Factors; Hospitals/*statistics & numerical data; Life Style; Accounts Payable and Receivable; Alcoholism/complications; Costs and Cost Analysis; Critical Care/economics; Hospitalization/*economics; Long-Term Care/economics; Patient Readmission/economics; Patients/*classification; Smoking/complications

Antacid versus cimetidine in preventing acute gastrointestinal bleeding. A randomized trial in 75 critically ill patients. - Priebe, H. J.; Skillman, J. J.; Bushnell, L. S.; Long, P. C.; Silen, W. (The New England journal of medicine, 1980)
Over a 15-month period, 75 critically ill patients at risk of acute gastrointestinal bleeding were randomized into two groups: one group (38 patients) received the H2-blocker cimetidine intravenously at an initial dosage of 300 mg every six hours, and the other group (37 patients) received antacid (Mylanta II) through a nasogastric tube at an intial dosage of 30 ml every hour. Gastric pH was measured hourly and titrated above 3.5. Upper-gastrointestinal-tract bleeding occurred in seven of 38 cimetidine-treated patients but in none of 37 antacid-treated patients (P less than 0.01). When antacid titration was added to the cimetidine regimen in four of seven patients with bleeding, all four stopped bleeding. Renal failure, sepsis, peritonitis, hypotension, respiratory failure, jaundice, multiple trauma, and major operative procedures were associated with an increased incidence of bleeding. Cimetidine does not adequately protect seriously ill patients from acute upper-gastrointestinal-tract bleeding. Antacid is better for this purpose.
抗酸剂与西咪替丁预防急性胃肠道出血的比较。一项在75例重症患者中开展的随机化试验。 在15个月期间，75例有急性胃肠道出血风险的重症患者被随机分为两组：一组（38例患者）接受H2阻滞剂西咪替丁静脉给药，初始剂量为300 mg，每6小时一次，另一组（37名患者）通过鼻胃管接受抗酸剂(Mylanta II)，初始剂量为30 mL/小时。每小时测量一次胃pH值，并将其滴定至3.5以上。38例西咪替丁治疗患者中有7例发生上消化道出血，而37例抗酸剂治疗患者中无上消化道出血(P < 0.01)。在4/7例出血患者的西咪替丁治疗方案中添加抗酸剂滴定后，所有4例患者均停止出血。肾衰竭、败血症、腹膜炎、低血压、呼吸衰竭、黄疸、多发性创伤和大手术操作与出血发生率增加相关。西咪替丁不能充分保护重症患者免受急性上消化道出血。抗酸剂更适合这个目的。
Keywords: Humans; Female; Male; Middle Aged; Random Allocation; Postoperative Care; Postoperative Complications/*prevention & control; Risk; Clinical Trials as Topic; Acute Disease; Intubation, Gastrointestinal; Drug Combinations; *Critical Care; Aluminum Hydroxide/therapeutic use; Antacids/administration & dosage/*therapeutic use; Cimetidine/administration & dosage/*therapeutic use; Gastrointestinal Hemorrhage/*prevention & control; Guanidines/*therapeutic use; Magnesium Hydroxide/therapeutic use; Simethicone/therapeutic use

Patient autonomy and "death with dignity": some clinical caveats - Jackson, D. L.; Youngner, S. (The New England journal of medicine, 1979)
患者自主性和“尊严死亡”：一些临床警告
Keywords: Humans; Female; Male; Middle Aged; Resuscitation; Aged; Intensive Care Units; Adolescent; United States; Decision Making; Family; Attitude to Death; *Patient Participation; Adjustment Disorders/psychology; Attitude of Health Personnel; Critical Care/legislation & jurisprudence/psychology; Ethics, Medical; Euthanasia, Passive/*psychology; Euthanasia/*psychology; Life Support Care/legislation & jurisprudence/*psychology; Suicide, Attempted/psychology; Wills

Antacid titration in the prevention of acute gastrointestinal bleeding: a controlled, randomized trial in 100 critically ill patients - Hastings, P. R.; Skillman, J. J.; Bushnell, L. S.; Silen, W. (The New England journal of medicine, 1978)
We randomized 100 critically ill patients at risk of developing acute gastrointestinal ulceration and bleeding into two groups. One (51 patients) received antacid prophylaxis, and the other (49 patients) received no specific form of prophylaxis. Hourly antacid titration kept the pH of the gastric contents above 3.5. Two of the 51 patients who received antacid prophylaxis and gastrointestinal bleeding. Twelve of the 49 control patients bled (P less than 0.005). Of the 12 patients in the control group who bled, seven were placed on antacid medication, and all seven apparently stopped bleeding. Analysis of all the patients showed that an increasing prevalence of respiratory, failure, sepsis, peritonitis, jaundice, renal failure and hypotension was correlated with a greater frequency of bleeding. No patients required operative treatment to control bleeding. These data indicate that the occurrence of acute gastrointestinal bleeding in critically ill patients can be reduced by antacid titration.
抗酸剂滴定预防急性胃肠道出血：一项在100例重症患者中开展的对照、随机化试验 我们将100例有发生急性胃肠道溃疡和出血风险的重症患者随机分为两组。1例患者（51例患者）接受抗酸剂预防治疗，另1例患者（49例患者）未接受特殊形式的预防治疗。每小时抗酸剂滴定使胃内容物pH值保持在3.5以上。51例接受抗酸剂预防治疗的患者中有2例发生胃肠道出血。49例对照患者中有12例出血(P < 0.005)。在对照组出血的12例患者中，7例接受抗酸药物治疗，7例出血均明显停止。对所有患者的分析表明，呼吸、衰竭、败血症、腹膜炎、黄疸、肾衰竭和低血压的患病率增加与出血频率增加相关。没有患者需要手术治疗来控制出血。这些数据表明，抗酸剂滴定可降低重症患者急性胃肠道出血的发生率。
Keywords: Humans; Female; Middle Aged; Aged; Risk; Acute Disease; *Critical Care; Antacids/*therapeutic use; Gastric Acidity Determination; Gastrointestinal Hemorrhage/epidemiology/*prevention & control; Hydrogen-Ion Concentration; Postoperative Complications/prevention & control; Statistics as Topic

Optimum care for hopelessly ill patients (The New England journal of medicine, 1976)
绝望患者的最佳护理
Keywords: Prognosis; Resuscitation; Intensive Care Units; Boston; Classification; Critical Care/*standards; Hospitals, General; Patient Care Planning; Terminal Care/*standards

Grief response of parents after referral of the critically ill newborn to a regional center - Benefield, D. G.; Leib, S. A.; Reuter, J. (The New England journal of medicine, 1976)
Attitudes, feelings, and behavior were studied in 101 mother-father pairs whose critically ill newborn infants survived after referral from the hospital of birth to a regional neonatal intensive-care unit for special care. As measured by an anticipatory-grief score, most parents experienced grief reactions similar to those whose infants do not survive the newborn period. The level of anticipatory grief did not appear to be associated with severity of infant illness as determined by the need for respirator therapy or major surgical procedures. The fathers reported drastic alteration in daily activity while wife and infant were hospitalized in separate facilities, and they assumed a central role in maintaining family stability during the crisis. These data suggest that an organized family-support program could play a prominent part in maintaining family stability during the delivery of newborn intensive care.
危重新生儿转诊至地区中心后父母的悲伤反应 在从出生医院转诊至区域性新生儿重症监护室接受特殊护理后存活的101例危重新生儿的母亲对中研究了态度、感觉和行为。根据预期-悲伤评分，大多数父母经历的悲伤反应与婴儿无法度过新生期的经历相似。预期悲伤的水平似乎与婴儿疾病的严重程度无关，这是由呼吸治疗或大手术的需要所决定的。父亲报告说，他们的日常活动发生了重大变化，而妻子和婴儿则在不同的设施中住院，他们在危机期间保持家庭稳定方面发挥了核心作用。这些数据表明，在新生儿重症监护期间，有组织的家庭支持项目可在维持家庭稳定方面发挥重要作用。
Keywords: Humans; Female; Male; Adult; Infant, Newborn; Pregnancy; Stress, Psychological; Surveys and Questionnaires; *Critical Care; *Grief; *Infant, Newborn, Diseases; *Parents; Anxiety, Separation; Attitude; Hospitals, Special; Life Style; Referral and Consultation

Survival, hospitalization charges and follow-up results in critically ill patients - Cullen, D. J.; Ferrara, L. C.; Briggs, B. A.; Walker, P. F.; Gilbert, J. (The New England journal of medicine, 1976)
In 226 consecutive critically ill primarily postoperative patients, we determined survival and quality of life, hospitalization charges, and consumption of blood and blood products. The patients were physiologically unstable and required intensive physician and nursing care. By one month, 123 patients had died (54 per cent), 70 were still hospitalized, and 31 were home; only one of 103 survivors had fully recovered. By 12 months, 164 patients (73 per cent) had died, 10 were still hospitalized, and 51 were home. Twenty-seven of 62 survivors had fully recovered. Hospitalization charges averaged $14,304 per patient. The total charge for blood and blood fractions was $617,710--21 per cent of the total hospitalization charge; $515,711 (83 per cent) of the blood charge went to 164 nonsurvivors, whereas $101,939 (17 per cent) went to the 62 survivors. These data document the use of increasingly limited resources in the management of critically ill patients. The medical profession must make difficult decisions to allocate these resources effectively.
重症患者生存情况、住院费用及随访结果 在226例主要为术后重症患者中，我们确定了生存率和生活质量、住院费用以及血液和血液制品的消耗。患者的生理状况不稳定，需要加强医生和护理。到1个月时，123例患者死亡(54%)，70例仍在住院，31例在家中；103例存活者中只有1例完全恢复。12个月时，164例患者(73%)死亡，10例仍在住院，51例在家中。62例存活者中27例完全恢复。每例患者的平均住院费用为14,304美元。血液和血液成分的总费用为617,710-21美元，占住院总费用的百分比；血液成分的515,711美元(83%)支付给164名非存活者，而62名存活者的总费用为101,939美元(17%)。这些数据记录了越来越有限的资源在危重患者管理中的使用。医学界必须做出艰难的决策才能有效地配置这些资源。
Keywords: Humans; Female; Male; Middle Aged; Aged; Length of Stay; Follow-Up Studies; Quality of Life; Blood Transfusion; Age Factors; *Critical Care; *Hospitalization; *Mortality; *Health Expenditures; Fees, Medical; Financing, Personal; Insurance, Health; Massachusetts

Toward a system of emergency medical care - Noble, B. K. (The New England journal of medicine, 1976)
建立紧急医疗护理系统
Keywords: Resuscitation; Massachusetts; *Quality of Health Care; Allied Health Personnel/education; Ambulances/standards; Critical Care/standards; Education, Medical, Continuing; Education, Nursing, Continuing; Emergency Medical Services/*standards; Legislation, Medical